The tale of a neglected energy source: elevated hydrogen exposure affects both microbial diversity and function in soil - Khdhiri, Mondher; Piché-Choquette, Sarah; Tremblay, Julien; Tringe, Susannah G.; Constant, Philippe; Müller, Volker (Applied and Environmental Microbiology, 2017)
The enrichment of H2-oxidizing bacteria (HOB) by H2 generated by nitrogen-fixing nodules has been shown to have a fertilization effect on several different crops. The benefit of HOB is attributed to their production of plant growth-promoting factors, yet their interactions with other members of soil microbial communities have received little attention. Here we report that the energy potential of H2, when supplied to soil, alters ecological niche partitioning of bacteria and fungi, with multifaceted consequences for both generalist and specialist microbial functions. We used dynamic microcosms to expose soil to the typical atmospheric H2 mixing ratio (0.5 ppmv) permeating soils, as well as mixing ratios comparable to those found at the soil-nodule interface (10,000 ppmv). Elevated H2 exposure exerted direct effects on two HOB subpopulations distinguished by their affinity for H2 while enhancing community level carbon substrate utilization potential and lowering CH4 uptake activity in soil. We found that H2 triggered changes in the abundance of microorganisms that were reproducible yet inconsistent across soils at the taxonomic level and even among HOB. Overall, H2 exposure altered microbial process rates at an intensity that depends upon soil abiotic and biotic features. We argue that further examination of direct and indirect effects of H2 on soil microbial communities will lead to a better understanding of the H2 fertilization effect and soil biogeochemical processes.
Keywords: biogeochemistry; microbial ecology; soil microbiology; trace gas

The structure of the distant Kuiper Belt in a nice model scenario - Pike, R. E.; Lawler, S.; Brasser, R.; Shankman, C. J.; Alexandersen, M.; Kavelaars, J. J. (The Astronomical Journal, 2017)
This work explores the orbital distribution of minor bodies in the outer Solar System emplaced as a result of a Nice model migration from the simulations of Brasser and Morbidelli. This planetary migration scatters a planetesimal disk from between 29 and 34 au and emplaces a population of objects into the Kuiper Belt region. From the 2:1 Neptune resonance and outward, the test particles analyzed populate the outer resonances with orbital distributions consistent with trans-Neptunian object (TNO) detections in semimajor axis, inclination, and eccentricity, while capture into the closest resonances is too efficient. The relative populations of the simulated scattering objects and resonant objects in the 3:1 and 4:1 resonances are also consistent with observed populations based on debiased TNO surveys, but the 5:1 resonance is severely underpopulated compared to population estimates from survey results. Scattering emplacement results in the expected orbital distribution for the majority of the TNO populations; however, the origin of the large observed population in the 5:1 resonance remains unexplained.
Keywords: Kuiper belt: general; planets and satellites: dynamical evolution and stability

The splitting of double-component active asteroid P/2016 J1 (PANSTARRS) - Moreno, F.; Pozuelos, F. J.; Novaković, B.; Licandro, J.; Cabrera-Lavers, A.; Bolin, Bryce; Jedicke, Robert; Gladman, Brett J.; Bannister, Michele T.; Gwyn, Stephen D. J.; Vereš, Peter; Chambers, Kenneth; et al. (The Astrophysical Journal, 2017)
We present deep imaging observations, orbital dynamics, and dust-tail model analyses of the double-component asteroid P/2016 J1 (J1-A and J1-B). The observations were acquired at the Gran Telescopio Canarias (GTC) and the Canada–France–Hawaii Telescope (CFHT) from mid-March to late July of 2016. A statistical analysis of backward-in-time integrations of the orbits of a large sample of clone objects of P/2016 J1-A and J1-B shows that the minimum separation between them occurred most likely ~2300 days prior to the current perihelion passage, i.e., during the previous orbit near perihelion. This closest approach was probably linked to a fragmentation event of their parent body. Monte Carlo dust-tail models show that those two components became active simultaneously ~250 days before the current perihelion, with comparable maximum loss rates of ~0.7 and ~0.5 kg s−1, and total ejected masses of 8 × 106 and 6 × 106 kg for fragments J1-A and J1-B, respectively. Consequently, the fragmentation event and the present dust activity are unrelated. The simultaneous activation times of the two components and the fact that the activity lasted 6–9 months or longer, strongly indicate ice sublimation as the most likely mechanism involved in the dust emission process.
Keywords: methods: numerical; minor planets, asteroids: individual (P/2016 J1 (PANSTARRS))

The spectroscopy and H-band imaging of Virgo Cluster Galaxies (SHIVir) Survey: scaling relations and the stellar-to-total mass relation - Ouellette, Nathalie N.-Q.; Courteau, Stéphane; Holtzman, Jon A.; Dutton, Aaron A.; Cappellari, Michele; Dalcanton, Julianne J.; Mcdonald, Michael; Roediger, Joel C.; Taylor, James E.; Tully, R. Brent; Côté, Patrick; Ferrarese, Laura; et al. (The Astrophysical Journal, 2017)
We present parameter distributions and fundamental scaling relations for 190 Virgo cluster galaxies in the SHIVir survey. The distribution of galaxy velocities is bimodal about V circ ~ 125 km s−1, hinting at the existence of dynamically unstable modes in the inner regions of galaxies. An analysis of the Tully-Fisher relation (TFR) of late-type galaxies (LTGs) and the fundamental plane (FP) of early-type galaxies (ETGs) is presented, yielding a compendium of galaxy scaling relations. The slope and zero-point of the Virgo TFR match those of field galaxies, while scatter differences likely reflect distinct evolutionary histories. The velocities minimizing scatter for the TFR and FP are measured at large apertures where the baryonic fraction becomes subdominant. While TFR residuals remain independent of any galaxy parameters, FP residuals (i.e., the FP "tilt") correlate strongly with the dynamical-to-stellar mass ratio, yielding stringent galaxy formation constraints. We construct a stellar-to-total mass relation (STMR) for ETGs and LTGs and find linear but distinct trends over the range M * = 108–11 M ⊙. Stellar-to-halo mass relations (SHMRs), which probe the extended dark matter halo, can be scaled down to masses estimated within the optical radius, showing a tight match with the Virgo STMR at low masses; possibly inadequate halo abundance matching prescriptions and broad radial scalings complicate this comparison at all masses. While ETGs appear to be more compact than LTGs of the same stellar mass in projected space, their mass-size relations in physical space are identical. The trends reported here may soon be validated through well-resolved numerical simulations.
Keywords: galaxies: clusters: individual (Virgo); galaxies: elliptical and lenticular, cD; galaxies: fundamental parameters; galaxies: kinematics and dynamics; galaxies: spiral; surveys

The SCUBA-2 Cosmology Legacy Survey: the clustering of submillimetre galaxies in the UKIDSS UDS field - Wilkinson, Aaron; Almaini, Omar; Chen, Chian-Chou; Smail, Ian; Arumugam, Vinodiran; Blain, Andrew; Chapin, Edward L.; Chapman, Scott C.; Conselice, Christopher J.; Cowley, William I.; Dunlop, James S.; Farrah, Duncan; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Submillimetre galaxies (SMGs) are among the most luminous dusty galaxies in the Universe, but their true nature remains unclear; are SMGs the progenitors of the massive elliptical galaxies we see in the local Universe, or are they just a short-lived phase among more typical star-forming galaxies? To explore this problem further, we investigate the clustering of SMGs identified in the SCUBA-2 Cosmology Legacy Survey. We use a catalogue of submillimetre (850 μm) source identifications derived using a combination of radio counterparts and colour/infrared selection to analyse a sample of 610 SMG counterparts in the United Kingdom Infrared Telescope (UKIRT) Infrared Deep Survey (UKIDSS) Ultra Deep Survey (UDS), making this the largest high-redshift sample of these galaxies to date. Using angular cross-correlation techniques, we estimate the halo masses for this large sample of SMGs and compare them with passive and star-forming galaxies selected in the same field. We find that SMGs, on average, occupy high-mass dark matter haloes (Mhalo > 1013 M⊙) at redshifts z > 2.5, consistent with being the progenitors of massive quiescent galaxies in present-day galaxy clusters. We also find evidence of downsizing, in which SMG activity shifts to lower mass haloes at lower redshifts. In terms of their clustering and halo masses, SMGs appear to be consistent with other star-forming galaxies at a given redshift.
Keywords: galaxies: evolution; galaxies: formation; galaxies: high-redshift; galaxies: starburst; large-scale structure of Universe

The repeating fast radio burst FRB 121102 as seen on milliarcsecond angular scales - Marcote, B.; Paragi, Z.; Hessels, J. W. T.; Keimpema, A.; Langevelde, H. J. Van; Huang, Y.; Bassa, C. G.; Bogdanov, S.; Bower, G. C.; Burke-Spolaor, S.; Butler, B. J.; Campbell, R. M.; et al. (The Astrophysical Journal, 2017)
The millisecond-duration radio flashes known as fast radio bursts (FRBs) represent an enigmatic astrophysical phenomenon. Recently, the sub-arcsecond localization (~100 mas precision) of FRB 121102 using the Very Large Array has led to its unambiguous association with persistent radio and optical counterparts, and to the identification of its host galaxy. However, an even more precise localization is needed in order to probe the direct physical relationship between the millisecond bursts themselves and the associated persistent emission. Here, we report very-long-baseline radio interferometric observations using the European VLBI Network and the 305 m Arecibo telescope, which simultaneously detect both the bursts and the persistent radio emission at milliarcsecond angular scales and show that they are co-located to within a projected linear separation of ≲40 pc (≲12 mas angular separation, at 95% confidence). We detect consistent angular broadening of the bursts and persistent radio source (~2–4 mas at 1.7 GHz), which are both similar to the expected Milky Way scattering contribution. The persistent radio source has a projected size constrained to be ≲0.7 pc (≲0.2 mas angular extent at 5.0 GHz) and a lower limit for the brightness temperature of Tb ≳5 x 10^7 K. Together, these observations provide strong evidence for a direct physical link between FRB 121102 and the compact persistent radio source. We argue that a burst source associated with a low-luminosity active galactic nucleus or a young neutron star energizing a supernova remnant are the two scenarios for FRB 121102 that best match the observed data.
Keywords: radiation mechanisms: non-thermal; radio continuum: galaxies; techniques: high angular resolution

The relation between globular cluster systems and supermassive black holes in spiral galaxies: the case study of NGC 4258 - González-Lópezlira, Rosa A.; Lomelí-Núñez, Luis; Álamo-Martínez, Karla; Órdenes-Briceño, Yasna; Loinard, Laurent; Georgiev, Iskren Y.; Muñoz, Roberto P.; Puzia, Thomas H.; Bruzual A., Gustavo; Gwyn, Stephen (The Astrophysical Journal, 2017)
We aim to explore the relationship between globular cluster total number, NGC, and central black hole mass, M •, in spiral galaxies, and compare it with that recently reported for ellipticals. We present results for the Sbc galaxy NGC 4258, from Canada–France–Hawaii Telescope data. Thanks to water masers with Keplerian rotation in a circumnuclear disk, NGC 4258 has the most precisely measured extragalactic distance and supermassive black hole mass to date. The globular cluster (GC) candidate selection is based on the (u*-i') versus (i'-Ks) diagram, which is a superb tool to distinguish GCs from foreground stars, background galaxies, and young stellar clusters, and hence can provide the best number counts of GCs from photometry alone, virtually free of contamination, even if the galaxy is not completely edge-on. The mean optical and optical-near-infrared colors of the clusters are consistent with those of the Milky Way and M 31, after extinction is taken into account. We directly identify 39 GC candidates; after completeness correction, GC luminosity function extrapolation, and correction for spatial coverage, we calculate a total NGC=144 +- 31(+38, -36) (random and systematic uncertainties, respectively). We have thus increased to six the sample of spiral galaxies with measurements of both M • and NGC. NGC 4258 has a specific frequency SN=0.4 +- 0.1$ (random uncertainty), and is consistent within 2σ with the NGC versus M • correlation followed by elliptical galaxies. The Milky Way continues to be the only spiral that deviates significantly from the relation.
Keywords: black hole physics; galaxies: spiral; galaxies: formation; galaxies: evolution; galaxies: star clusters: general; globular clusters: general; galaxies: individual (NGC 4258)

The peculiar multiwavelength evolution Of V1535 Sco - Linford, J. D.; Chomiuk, L.; Nelson, T.; Finzell, T.; Walter, F. M.; Sokoloski, J. L.; Mukai, K.; Mioduszewski, A. J.; Van der horst, A. J.; Weston, J. H. S.; Rupen, M. P. (The Astrophysical Journal, 2017)
We present multiwavelength observations of the unusual nova V1535 Sco throughout its outburst in 2015. Early radio observations were consistent with synchrotron emission, and early X-ray observations revealed the presence of high-energy (>1 keV) photons. These indicated that strong shocks were present during the first ~2 weeks of the nova's evolution. The radio spectral energy distribution was consistent with thermal emission from week 2 to week 6. Starting in week 7, the radio emission again showed evidence of synchrotron emission, and there was an increase in X-ray emission, indicating a second shock event. The optical spectra show evidence of at least two separate outflows, with the faster outflow possibly having a bipolar morphology. The optical and near-infrared light curves and the X-ray NH measurements indicated that the companion star is likely a K giant.
Keywords: novae, cataclysmic variables; radio continuum: stars; stars: individual (V1535 Sco); white dwarfs; X-rays: stars

The Optical Society’s 2016 Topical Meeting on Optical Interference Coatings: introduction - Ristau, Detlev; Li, Li; Sargent, Robert; Sytchkova, Anna (Applied Optics, 2017)
This feature issue of Applied Optics is dedicated to the 13th Topical Meeting on Optical Interference Coatings, which was held June 19–24, 2016, in Tucson, Arizona, USA. The conference, taking place every three years, is a focal point for global technical interchange in the field of optical interference coatings and provides premier opportunities for people working in the field to present their new advances in research and development. Papers presented at the meeting covered a broad range of topics, including fundamental research on coating design theory, new materials, and deposition and characterization technologies, as well as the vast and growing number of applications in electronic displays, communication, optical instruments, high power and ultra-fast lasers, solar cells, space missions, gravitational wave detection, and many others.

The norma spiral arm: large-scale pitch angle - Vallée, Jacques P. (Astrophysics and Space Science, 2017)
In the inner Galaxy, we statistically find the mean pitch angle of the recently mapped Norma arm in two galactic quadrants (observed tangentially at galactic longitudes near l=328∘ and near l=20∘), using the twin-tangent method, and obtain −13.7∘±1.4∘. We compared with other measurements in the literature. Also, using the latest published data on pitch angle and the latest published data on the radial starting point of the four arms (RGal=2.2 kpc) in each galactic quadrant, a revised velocity plot of the Norma spiral arm is made, along with other spiral arms in the Milky Way, in each Galactic quadrant.
Keywords: Galaxies: spiral; Galaxy: disk; Galaxy: structure; Methods: statistical; ISM: general; ISM: structure

The Next Generation Virgo Cluster Survey. XXVIII. Characterization of the galactic white dwarf population - Fantin, Nicholas J.; Côté, Patrick; Hanes, David A.; Gwyn, S. D. J.; Bianchi, Luciana; Ferrarese, Laura; Cuillandre, Jean-Charles; Mcconnachie, Alan; Starkenburg, Else (The Astrophysical Journal, 2017)
We use three different techniques to identify hundreds of white dwarf (WD) candidates in the Next Generation Virgo Cluster Survey (NGVS) based on photometry from the NGVS and GUViCS, and proper motions derived from the NGVS and the Sloan Digital Sky Survey (SDSS). Photometric distances for these candidates are calculated using theoretical color-absolute magnitude relations, while effective temperatures are measured by fitting their spectral energy distributions. Disk and halo WD candidates are separated using a tangential velocity cut of 200 km s-1 in a reduced proper motion diagram, which leads to a sample of six halo WD candidates. Cooling ages, calculated for an assumed WD mass of 0.6M o, range between 60 Myr and 6 Gyr, although these estimates depend sensitively on the adopted mass. Luminosity functions for the disk and halo subsamples are constructed and compared to previous results from the SDSS and SuperCOSMOS survey. We compute a number density of (2.81 ±0.52) ×10-3 pc-3 for the disk WD population - consistent with previous measurements. We find (7.85 ±4.55) ×10-6 pc-3 for the halo, or 0.3% of the disk. Observed stellar counts are also compared to predictions made by the TRILEGAL and Besanon stellar population synthesis models. The comparison suggests that the TRILEGAL model overpredicts the total number of WDs. The WD counts predicted by the Besanon model agree with the observations, although a discrepancy arises when comparing the predicted and observed halo WD populations; the difference is likely due to the WD masses in the adopted model halo.
Keywords: catalogs; Galaxy: stellar content; stars: kinematics and dynamics; stars: luminosity function, mass function; surveys; white dwarfs

The next generation virgo cluster survey (NGVS). XXIV. The red sequence to ∼10^6L⊙ and comparisons with galaxy formation models - Roediger, Joel C.; Ferrarese, Laura; Côté, Patrick; Macarthur, Lauren A.; Sánchez-Janssen, Rúben; Blakeslee, John P.; Peng, Eric W.; Liu, Chengze; Munoz, Roberto; Cuillandre, Jean-Charles; Gwyn, Stephen; Mei, Simona; et al. (The Astrophysical Journal, 2017)
We use deep optical photometry from the Next Generation Virgo Cluster Survey (NGVS) to investigate the color–magnitude diagram for the galaxies inhabiting the core of this cluster. The sensitivity of the NGVS imaging allows us to continuously probe galaxy colors over a factor of ~2 × 105 in luminosity, from brightest cluster galaxies to scales overlapping classical satellites of the Milky Way (Mg' ~ −9; M * ~ 106 M ⊙), within a single environment. Remarkably, we find the first evidence that the red sequence (RS) flattens in all colors at the faint-magnitude end (starting between −14 ≤ Mg' ≤ −13, around M * ~ 4 × 107 M ⊙), with the slope decreasing to ~60% or less of its value at brighter magnitudes. This could indicate that the stellar populations of faint dwarfs in Virgo's core share similar characteristics (e.g., constant mean age) over ~3 mag in luminosity, suggesting that these galaxies were quenched coevally, likely via pre-processing in smaller hosts. We also compare our results to galaxy formation models, finding that the RS in model clusters have slopes at intermediate magnitudes that are too shallow, and in the case of semianalytic models, do not reproduce the flattening seen at both extremes (bright/faint) of the Virgo RS. Deficiencies in the chemical evolution of model galaxies likely contribute to the model-data discrepancies at all masses, while overly efficient quenching may also be a factor at dwarf scales. Deep UV and near-IR photometry are required to unambiguously diagnose the cause of the faint-end flattening.
Keywords: galaxies: clusters: individual (Virgo); galaxies: dwarf; galaxies: elliptical and lenticular, cD; galaxies: evolution; galaxies: stellar content

The morphology of TiO2 nanotube arrays grown from atomically peened and non-atomically peened Ti films - Farsinezhad, Samira; Mohammadpour, Arash; Benlamri, Mourad; Dalrymple, Ashley N.; Shankar, Karthik (Journal of Nanoscience and Nanotechnology, 2017)
The growth of TiO2 nanotube arrays (TNTAs) on non-native substrates is essential for exploiting the full potential of this nanoarchitecture in applications such as gas sensing, biosensing, antifouling coatings, low-cost solar cells, drug-eluting bimedical implants and stem-cell differentiators. The direct formation of anodic TNTAs on non-native substrates requires the vacuum deposition of a thin film of titanium on the substrate followed by subsequent electrochemical anodization of the film. In this report, we studied the effect of atomic peening on the formation of Ti thin films on technologically important non-native substrates. We compared the structure and morphology of evaporated and sputtered Ti films, and correlated them to the morphology of the vertically oriented TiO2 nanostructures that resulted subsequent to anodization of those films. We calculated a minimum value of 1.33 eV/atom for the energy of refkected neutral Ar species arriving at the substrate when a chamber pressure of 1 mTorr is used during the sputter deposition of Ti. Previous approaches relied on substrate heating to elevated temperatures during Ti thin film deposition or ion-beam assisted Ti thin film deposition as a prerequisite to form TiO2 nanotube arrays (TNTAs). We demonstrated TNTAs on a variety of substrates at room temperature using both evaporated and sputtered Ti films without recourse to ion-beam sources. Evaporated Ti films were found to possess small grain size and high local surface roughness, which resulted in nanotubes with extremely rough sidewalls. Ti thin films formed by Ar+ ion sputtering at commonly used chamber pressures of 7–20 mTorr at substrate temperatures ranging from room-temperature to 250 °C possessed a highly rough surface and three-dimensional grains, which precluded the formation of ordered nanotubes upon anodization due to highly non-uniform pore nucleation processes. In contrast, Ti thin films sputtered at low chamber pressures of 0.8–2 mTorr had a low surface roughness due to the atomic peening process. Such films, even when deposited at room temperature, resulted in ordered nanotube arrays upon anodization.
Keywords: DC sputtering; electron beam evaporation; ion beam sputtering; polymeric substrates; Si wafers; vacuum deposition; zone models

The ISLAndS project. II. The lifetime star formation histories of six Andromeda dSphs - Skillman, Evan D.; Monelli, Matteo; Weisz, Daniel R.; Hidalgo, Sebastian L.; Aparicio, Antonio; Bernard, Edouard J.; Boylan-Kolchin, Michael; Cassisi, Santi; Cole, Andrew A.; Dolphin, Andrew E.; Ferguson, Henry C.; Gallart, Carme; et al. (The Astrophysical Journal, 2017)
The Initial Star formation and Lifetimes of Andromeda Satellites (ISLAndS) project employs Hubble Space Telescope imaging to study a representative sample of six Andromeda dSph satellite companion galaxies. Our main goal is to determine whether the star formation histories (SFHs) of the Andromeda dSph satellites demonstrate significant statistical differences from those of the Milky Way (MW). Our deep observations yield a time resolution at the oldest ages of ~1 Gyr, allowing meaningful comparisons to the MW satellites. The six dSphs present a variety of SFHs (e.g., a significant range in quenching times, Tq, from 9 to 6 Gyr ago) that are not strictly correlated with luminosity or present distance from M31. In agreement with observations of MW companions of similar mass, there is no evidence of complete quenching of star formation by the cosmic UV background responsible for reionization, but the possibility of a degree of quenching at reionization cannot be ruled out. We do not find significant differences between the SFHs of the members and non-members of the vast, thin plane of satellites. The SFHs of the ISLAndS M31 dSphs appear to be more uniform than those of the MW dSphs. Specifically, the primary difference between the SFHs of the ISLAndS dSphs and MW dSph companions of similar luminosities and host distances is the absence of late-quenching Tq ≤ 5 Gyr dSphs in the ISLAndS sample. Thus, models that can produce satellite populations with and without late-quenching satellites are of extreme interest.
Keywords: galaxies: dwarf; galaxies: evolution; galaxies: photometry; galaxies: stellar content; galaxies: structure

The irreversible structural change in Mn1.1Fe0.9P0.8Ge0.2: evidence for a magnetic driver - Liu, Xubo; Ryan, D. H.; Cranswick, L. M. D.; Liu, D. M.; Zhang, H. G.; Yue, Ming; Altounian, Z. (AIP Advances, 2017)
Neutron powder diffraction measurements complemented by first-principles density functional theory (DFT) calculations have been used to study the irreversible change that accompanies the reversible magnetocaloric transition (MCT) in Mn1.1Fe0.9P0.8Ge0.2. We observe the growth and loss of long-period antiferromagnetism as we pass through the MCT for the first time and the development of significant strain in the cycled material. We attribute both the reversible and irreversible changes to the distance dependence of the Mn-Mn exchange in the Mn-P(Ge) ab–plane layers.

The host galaxy and redshift of the repeating fast radio burst FRB 121102 - Tendulkar, S. P.; Bassa, C. G.; Cordes, J. M.; Bower, G. C.; Law, C. J.; Chatterjee, S.; Adams, E. A. K.; Bogdanov, S.; Burke-Spolaor, S.; Butler, B. J.; Demorest, P.; Hessels, J. W. T.; et al. (The Astrophysical Journal, 2017)
The precise localization of the repeating fast radio burst (FRB 121102) has provided the first unambiguous association (chance coincidence probability p lesssim 3 × 10−4) of an FRB with an optical and persistent radio counterpart. We report on optical imaging and spectroscopy of the counterpart and find that it is an extended (0farcs6–0farcs8) object displaying prominent Balmer and [O iii] emission lines. Based on the spectrum and emission line ratios, we classify the counterpart as a low-metallicity, star-forming, m r' = 25.1 AB mag dwarf galaxy at a redshift of z = 0.19273(8), corresponding to a luminosity distance of 972 Mpc. From the angular size, the redshift, and luminosity, we estimate the host galaxy to have a diameter lesssim4 kpc and a stellar mass of M * ~ (4–7) × 107 M ⊙, assuming a mass-to-light ratio between 2 to 3 M ⊙ L ⊙ −1. Based on the Hα flux, we estimate the star formation rate of the host to be 0.4 M ⊙ yr−1 and a substantial host dispersion measure (DM) depth lesssim324 pc cm−3. The net DM contribution of the host galaxy to FRB 121102 is likely to be lower than this value depending on geometrical factors. We show that the persistent radio source at FRB 121102's location reported by Marcote et al. is offset from the galaxy's center of light by ~200 mas and the host galaxy does not show optical signatures for AGN activity. If FRB 121102 is typical of the wider FRB population and if future interferometric localizations preferentially find them in dwarf galaxies with low metallicities and prominent emission lines, they would share such a preference with long gamma-ray bursts and superluminous supernovae.
Keywords: galaxies: distances and redshifts; galaxies: dwarf; galaxies: ISM; stars: magnetars; stars: neutron

The Green Bank Ammonia Survey: first results of NH3 mapping of the Gould Belt - Friesen, Rachel K.; Pineda, Jaime E.; Rosolowsky, Erik; Alves, Felipe; Chacón-Tanarro, Ana; Chen, Hope How-Huan; Chen, Michael Chun-Yuan; Di Francesco, James; Keown, Jared; Kirk, Helen; Punanova, Anna; Seo, Youngmin; et al. (The Astrophysical Journal, 2017)
We present an overview of the first data release (DR1) and first-look science from the Green Bank Ammonia Survey (GAS). GAS is a Large Program at the Green Bank Telescope to map all Gould Belt star-forming regions with AV ≳ 7 mag visible from the northern hemisphere in emission from NH3 and other key molecular tracers. This first release includes the data for four regions in the Gould Belt clouds: B18 in Taurus, NGC 1333 in Perseus, L1688 in Ophiuchus, and Orion A North in Orion. We compare the NH3 emission to dust continuum emission from Herschel and find that the two tracers correspond closely. We find that NH3 is present in over 60% of the lines of sight with AV ≳ 7 mag in three of the four DR1 regions, in agreement with expectations from previous observations. The sole exception is B18, where NH3 is detected toward ~40% of the lines of sight with AV ≳ 7 mag. Moreover, we find that the NH3 emission is generally extended beyond the typical 0.1 pc length scales of dense cores. We produce maps of the gas kinematics, temperature, and NH3 column densities through forward modeling of the hyperfine structure of the NH3 (1, 1) and (2, 2) lines. We show that the NH3 velocity dispersion, σv, and gas kinetic temperature, T K, vary systematically between the regions included in this release, with an increase in both the mean value and the spread of σv and T K with increasing star formation activity.
Keywords: ISM: individual objects (L1668, B18, OrionA molecular complex, NGC1333); ISM: molecules; stars: formation

The effects of activin A on the migration of human breast cancer cells and neutrophils and their migratory interaction - Xie, Dongxue; Liu, Zhonghui; Wu, Jiandong; Feng, Wenfang; Yang, Ke; Deng, Jixian; Tian, Ganghong; Santos, Susy; Cui, Xueling; Lin, Francis (Experimental Cell Research, 2017)
Activin A belongs to the superfamily of transforming growth factor beta (TGFβ) and is a critical regulatory cytokine in breast cancer and inflammation. However, the role of activin A in migration of breast cancer cells and immune cells was not well characterized. Here, a microfluidic device was used to examine the effect of activin A on the migration of human breast cancer cell line MDA-MB-231 cells and human blood neutrophils as well as their migratory interaction. We found that activin A promoted the basal migration but impaired epidermal growth factor (EGF)-induced migration of breast cancer cells. By contrast, activin A reduced neutrophil chemotaxis and transendothelial migration to N-Formyl-Met-Leu-Phe (fMLP). Finally, activin A promoted neutrophil chemotaxis to the supernatant from breast cancer cell culture. Collectively, our study revealed the different roles of activin A in regulating the migration of breast cancer cells and neutrophils and their migratory interaction. These findings suggested the potential of activin A as a therapeutic target for inflammation and breast cancers.
Keywords: activin A; breast cancer cells; neutrophils; migration; microfluidic device

The effect of stiffening tabs on the performance of lobed mixers at off-design conditions - Wright, Alexander; Mahallati, Ali; Conlon, Martin; Militzer, Julio (Conference Proceedings Repository, 2017)
This paper presents a computational investigation of scaled turbofan lobed mixer stiffening tabs at low-speed off-design conditions. Stiffening tabs provide rigidity to the thin lobed mixer by connecting the mixer valley to the more rigid centrebody. Evidence shows that the tabs affect the flow structures of turbofan exhaust systems at off-design core inlet swirl conditions. Observations were made downstream of the mixer in simulations that were carried out with an unstructured RANS solver and the k-ω SST turbulence model. To model off-design conditions, the core flow swirl was increased from axial flow to 10° at the moderate case and 30° at the high swirl case. The tab geometry was shown to perturb some of the less involved flow mixing structures, streamwise vortices near the lobe valley. Simulations of geometries with the tabs displayed more uniform flow throughout the common nozzle with higher thrust outputs; however, these minor improvements are negated by higher total pressure losses.

The earliest phases of high-mass star formation, as seen in NGC 6334 by Herschel-HOBYS - Tigé, J.; Motte, F.; Russeil, D.; Zavagno, A.; Hennemann, M.; Schneider, N.; Hill, T.; Nguyen Luong, Q.; Di Francesco, J.; Bontemps, S.; Louvet, F.; Didelon, P.; et al. (Astronomy & Astrophysics, 2017)
Aims. To constrain models of high-mass star formation, the Herschel-HOBYS key program aims at discovering massive dense cores (MDCs) able to host the high-mass analogs of low-mass prestellar cores, which have been searched for over the past decade. We here focus on NGC 6334, one of the best-studied HOBYS molecular cloud complexes. Methods. We used Herschel/PACS and SPIRE 70−500 μm images of the NGC 6334 complex complemented with (sub)millimeter and mid-infrared data. We built a complete procedure to extract ~0.1 pc dense cores with the getsources software, which simultaneously measures their far-infrared to millimeter fluxes. We carefully estimated the temperatures and masses of these dense cores from their spectral energy distributions (SEDs). We also identified the densest pc-scale cloud structures of NGC 6334, one 2 pc × 1 pc ridge and two 0.8 pc × 0.8 pc hubs, with volume-averaged densities of ~105 cm-3. Results. A cross-correlation with high-mass star formation signposts suggests a mass threshold of 75 M⊙ for MDCs in NGC 6334. MDCs have temperatures of 9.5−40 K, masses of 75−1000 M⊙, and densities of 1 × 105−7 × 107 cm-3. Their mid-infrared emission is used to separate 6 IR-bright and 10 IR-quiet protostellar MDCs while their 70 μm emission strength, with respect to fitted SEDs, helps identify 16 starless MDC candidates. The ability of the latter to host high-mass prestellar cores is investigated here and remains questionable. An increase in mass and density from the starless to the IR-quiet and IR-bright phases suggests that the protostars and MDCs simultaneously grow in mass. The statistical lifetimes of the high-mass prestellar and protostellar core phases, estimated to be 1−7 × 104 yr and at most 3 × 105 yr respectively, suggest a dynamical scenario of high-mass star formation. Conclusions. The present study provides good mass estimates for a statistically significant sample, covering the earliest phases of high-mass star formation. High-mass prestellar cores may not exist in NGC 6334, favoring a scenario presented here, which simultaneously forms clouds, ridges, MDCs, and high-mass protostars.
Keywords: dust, extinction; ISM: clouds; stars: formation; submillimeter: ISM; stars: protostars; ISM: individual objects: NGC 6334

The D-lactate dehydrogenase MoDLD1 is essential for growth and infection-related development in Magnaporthe oryzae - Zhou, Tengsheng; Qin, Li; Zhu, Xiaohan; Shen, Wenyun; Zou, Jitao; Wang, Zonghua; Wei, Yangdou (Environmental Microbiology, 2017)
Rice blast disease caused by Magnaporthe oryzae is initiated by the attachment of conidia to plant surfaces. Germ tubes emerging from conidia develop melanized appressoria to physically penetrate the host surface. Previous studies revealed that appressorium development requires the breakdown of storage lipids and glycogen that occur in peroxisomes and the cytosol respectively, culminating in production of pyruvate. However, the downstream product(s) entering the mitochondria for further oxidation is unclear. In this study, we aimed to investigate the molecular basis underlying the metabolic flux towards the mitochondria associated with the infectious‐related development in M. oryzae. We showed that D‐lactate is a key intermediate metabolite of the mobilization of lipids and glycogen, and its oxidative conversion to pyruvate is catalysed by a mitochondrial D‐lactate dehydrogenase MoDLD1. Deletion of MoDLD1 caused defects in conidiogenesis and appressorium formation, and subsequently the loss of fungal pathogenicity. Further analyses demonstrated that MoDLD1 activity is involved in the maintenance of redox homeostasis during conidial germination. Thus, MoDLD1 is a critical modulator that channels metabolite flow to the mitochondrion coupling cellular redox state, and contributes to development and virulence of M. oryzae.

The challenge of reconciling bottom-up agricultural methane emissions inventories with top-down measurements - Desjardins, R. L.; Worth, D. E.; Pattey, E.; Vanderzaag, A.; Srinivasan, R.; Mauder, M.; Worthy, D.; Sweeney, C.; Metzger, S. (Agricultural and Forest Meteorology, 2017)
Agriculture is estimated to produce more than 40% of anthropogenic methane (CH4) emissions, contributing to global climate change. Bottom-up, IPCC based methodologies are typically used to estimate the agriculture sector’s contribution, but these estimates are rarely verified beyond the farm gate, due to the challenge of separating interspersed sources. We present flux measurements of CH4, using eddy covariance (EC), relaxed eddy accumulation (REA) and wavelet covariance obtained using an aircraft-based measurement platform and compare these top-down estimates with bottom-up footprint adjusted inventory estimates of CH4 emissions for an agricultural region in eastern Ontario, Canada. Top-down CH4 fluxes agree well (mean ± 1 standard error: EC = 17 ± 4 mg CH4 m−2 d−1; REA = 19 ± 3 mg CH4 m−2 d−1, wavelet covariance = 16 ± 3 mg CH4 m−2 d−1), and are not statistically different, but significantly exceed bottom-up inventory estimates of CH4 emissions based on animal husbandry (8 ± 1 mg CH4 m−2 d−1). The discrepancy between top-down and bottom-up estimates was found to be related to both increasing fractional area of wetlands in the flux footprint, and increasing surface temperature. For the case when the wetland area in the flux footprint was less than 10% fractional coverage, the top-down and bottom-up estimates were within the measurement error. This result provides the first independent verification of agricultural methane emissions inventories at the regional scale. Wavelet analysis, which provides spatially resolved fluxes, was used to attempt to separate CH4 emissions from managed and unmanaged CH4 sources. Opportunities to minimize the challenges of verifying agricultural CH4 emissions inventories using aircraft flux measuring systems are discussed.
Keywords: eddy covariance; trace gas flux; relaxed eddy accumulation; wavelet analysis; CH4 sensor; farm; wetlands

The Canada–France Imaging Survey: first results from the u-band component - Ibata, Rodrigo A.; Mcconnachie, Alan; Cuillandre, Jean-Charles; Fantin, Nicholas; Haywood, Misha; Martin, Nicolas F.; Bergeron, Pierre; Beckmann, Volker; Bernard, Edouard; Bonifacio, Piercarlo; Caffau, Elisabetta; Carlberg, Raymond; et al. (The Astrophysical Journal, 2017)
The Canada–France Imaging Survey (CFIS) will map the northern high Galactic latitude sky in the u-band ("CFIS-u," 10,000 deg^2) and in the r-band ("CFIS-r," 5000 deg^2), enabling a host of stand-alone science investigations, and providing some of the ground-based data necessary for photometric redshift determination for the Euclid mission. In this first contribution, we present the u-band component of the survey, describe the observational strategy, and discuss some first highlight results, based on approximately one-third of the final area. We show that the Galactic anticenter structure is distributed continuously along the line of sight, out to beyond 20 kpc, and possesses a metallicity distribution that is essentially identical to that of the outer disk sampled by APOGEE. This suggests that it is probably a buckled disk of old metal-rich stars, rather than a stream or a flare. We also discuss the future potential for CFIS-u in discovering star-forming dwarf galaxies around the Local Group, the characterization of the white dwarf and blue straggler population of the Milky Way, as well as its sensitivity to low surface brightness structures in external galaxies.
Keywords: galaxies: formation; Galaxy: halo; Galaxy: stellar content; Galaxy: structure; surveys – white dwarfs

The Canada–France Ecliptic Plane Survey (CFEPS): high-latitude component - Petit, J-M.; Kavelaars, J. J.; Gladman, B. J.; Jones, R. L.; Parker, J. Wm.; Bieryla, A.; Van laerhoven, C.; Pike, R. E.; Nicholson, P.; Ashby, M. L. N.; Lawler, S. M. (The Astronomical Journal, 2017)
The High Ecliptic Latitude (HiLat) extension of the Canada–France Ecliptic Plane Survey (CFEPS), conducted from 2006 June to 2009 July, discovered a set of Trans-Neptunian objects (TNOs) that we report here. The HiLat component was designed to address one of the shortcomings of ecliptic surveys (like CFEPS), their low sensitivity to high-inclination objects. We searched 701 deg2 of sky ranging from 12° to 85° ecliptic latitude and discovered 24 TNOs, with inclinations between 15° and 104°. This survey places a very strong constraint on the inclination distribution of the hot component of the classical Kuiper Belt, ruling out any possibility of a large intrinsic fraction of highly inclined orbits. Using the parameterization of Brown, the HiLat sample combined with CFEPS imposes a width 14° ≤ σ ≤ 15fdg5, with a best match for σ = 14fdg5. HiLat discovered the first retrograde TNO, 2008 KV42, with an almost polar orbit with inclination 104°, and (418993) = 2009 MS9, a scattering object with perihelion in the region of Saturn's influence, with a ~ 400 au and i = 68°.
Keywords: Kuiper belt: general–surveys

The binary fraction of stars in dwarf galaxies: the case of Leo II - Spencer, Meghin E.; Mateo, Mario; Walker, Matthew G.; Olszewski, Edward W.; Mcconnachie, Alan W.; Kirby, Evan N.; Koch, Andreas (The Astronomical Journal, 2017)
We combine precision radial velocity data from four different published works of the stars in the Leo II dwarf spheroidal galaxy. This yields a data set that spans 19 years, has 14 different epochs of observation, and contains 372 unique red giant branch stars, 196 of which have repeat observations. Using this multi-epoch data set, we constrain the binary fraction for Leo II. We generate a suite of Monte Carlo simulations that test different binary fractions using Bayesian analysis and determine that the binary fraction for Leo II ranges from 0.30^-0.10+0.09 to 0.34^-0.11+0.11, depending on the distributions of binary orbital parameters assumed. This value is smaller than what has been found for the solar neighborhood (~0.4–0.6) but falls within the wide range of values that have been inferred for other dwarf spheroidals (0.14–0.69). The distribution of orbital periods has the greatest impact on the binary fraction results. If the fraction we find in Leo II is present in low-mass ultra-faints, it can artificially inflate the velocity dispersion of those systems and cause them to appear more dark matter rich than in actuality. For a galaxy with an intrinsic dispersion of 1 km s−1 and an observational sample of 100 stars, the dispersion can be increased by a factor of 1.5–2 for Leo II-like binary fractions or by a factor of three for binary fractions on the higher end of what has been seen in other dwarf spheroidals.
Keywords: binaries: general; galaxies: dwarf; galaxies: individual (Leo II); galaxies: kinematics and dynamics; Supporting material: machine-readable table

The 9577 and 9632 Å diffuse interstellar bands: C^+60 as carrier - Walker, G. A. H.; Campbell, E. K.; Maier, J. P.; Bohlender, D. (The Astrophysical Journal, 2017)
Galazutdinov et al. (2017) recently claimed that the relative strengths of the 9577 and 9632 Å diffuse interstellar bands (DIBs) are too poorly correlated to be caused by a single source, the C^+60 ion. Their conclusion is based on theoretical modeling of contaminating stellar Mg ii lines at 9631.9 and 9632.4 Å and UVES spectra. This contradicts their earlier result and those of several others that the two DIBs are closely correlated and, within the errors and effects of stellar blends, exhibit an intensity ratio consistent with that found in the 6 K laboratory spectrum of C^+60. We consider the use of close spectral standards to be superior to model atmosphere calculations in correcting for contamination by the Mg ii lines. We have examined some of the same UVES spectra and demonstrate that a lack of suitably observed telluric standards makes it impossible to adequately correct for telluric water vapor contamination, leading to unreliable continuum levels. The possible effects of higher temperatures, in the 30–100 K range, on the C^+60 electronic absorption band profiles, and their relative intensities, are also considered.
Keywords: ISM: molecules

Temperature measurement techniques for spray foam applications - Banister, C. J.; Moore, T .V.; Van Reenen, D. W. (International Journal of Heat and Mass Transfer, 2017)
Experiments were conducted to investigate the accuracy of thermocouple configurations in measuring temperatures within spray foam insulation products during application. Measurements of this kind are important for assessing products from the standpoint of thermal performance and safety. The response times of heating and cooling in air were first analyzed for several thermocouple configurations. The second phase of the investigation consisted of instrumenting five 2″ × 6″ wood frame cavities sheathed with a 2′ by 2′ piece of oriented strand board. A method is presented for instrumenting specimens in a way that is minimally thermally invasive, which leads to temperature results that can be trusted as highly accurate. The thermocouple type recommended for this application is insulated Type K 36 gauge, joined via welding. Larger wire gauges result in significantly underestimated temperatures, by as much as 30 °C. In combination with thermocouple types with higher thermal conductivity of wires, this underestimation can reach as much as 60 °C. The potential inaccuracies are particularly pronounced due to the low thermal mass and low thermal conductivity of spray foam insulation.
Keywords: spray foam; temperature measurement; thermocouples

Temperature measurement challenges and limitations for in-flight particles in suspension plasma spraying - Aziz, Bishoy; Gougeon, Patrick; Moreau, Christian (Journal of Thermal Spray Technology, 2017)
Suspension plasma spraying (SPS) acquires a significant interest from the industry. The deposited coatings using this technique were proved to have unique microstructural features compared to those built by conventional plasma spraying techniques. In order to optimize this process, in-flight particle diagnostics is considered a very useful tool that helps to control various spraying parameters and permits better coating reproducibility. In that context, the temperature of in-flight particles is one of the most important key elements that helps to optimize and control the SPS process. However, the limitations and challenges associated with this process have a significant effect on the accuracy of two-color pyrometric techniques used to measure the in-flight particle temperature. In this work, the influence of several nonthermal radiation sources on the particle temperature measurement is studied. The plasma radiation scattered by in-flight particles was found to have no significant influence on temperature measurement. Moreover, the detection of the two-color signals at two different locations was found to induce a significant error on temperature measurement. Finally, the plasma radiation surrounding the in-flight particles was identified as the main source of error on the temperature measurement of in-flight particles.
Keywords: optical measurement; particle plasma interaction; plasma diagnostics; protective coatings; suspension spraying; thermal barrier coatings (TBCs); yttria-stabilized zirconia (YSZ)

Tailored semiconductors for high-harmonic optoelectronics - Sivis, Murat; Taucer, Marco; Vampa, Giulio; Johnston, Kyle; Staudte, André; Naumov, Andrei Yu.; Villeneuve, D. M.; Ropers, Claus; Corkum, P. B. (Science, 2017)
The advent of high-harmonic generation in gases 30 years ago set the foundation for attosecond science and facilitated ultrafast spectroscopy in atoms, molecules, and solids. We explore high-harmonic generation in the solid state by means of nanostructured and ion-implanted semiconductors. We use wavelength-selective microscopic imaging to map enhanced harmonic emission and show that the generation medium and the driving field can be locally tailored in solids by modifying the chemical composition and morphology. This enables the control of high-harmonic technology within precisely engineered solid targets. We demonstrate customized high-harmonic wave fields with wavelengths down to 225 nanometers (ninth-harmonic order of 2-micrometer laser pulses) and present an integrated Fresnel zone plate target in silicon, which leads to diffraction-limited self-focusing of the generated harmonics down to 1-micrometer spot sizes.

Synthesis of N-alkyl substituted iminosugars from D-ribose - Wang, Haibo; Pan, Yang; Tang, Qin; Zou, Wei; Shao, Huawu (Chinese Chemical Letters, 2017)
An effective and facile method for the synthesis of N-alkylated hydroxylpyrrolidine and hydroxylpiperidine is described. A number of N-alkyl substituted iminosugars were prepared using iodine-induced intramolecular cyclization of acyclic alkenylamines as key step.
Keywords: iminosugar; pyrrolidine; piperidine; glycosidase; D-ribose

Synthesis of conducting polypyrrole-titanium oxide nanocomposite: study of structural, optical and electrical properties - Roy, Swarup; Mishra, Suryakant; Yogi, Priyanka; Saxena, Shailendra K.; Sagdeo, Pankaj R.; Kumar, Rajesh (Journal of Inorganic and Organometallic Polymers and Materials, 2017)
Optical and electronic properties of hybrid Polypyrrole (Ppy)–Titanium oxide (TiO2) nanocomposite, synthesized using oxidative chemical polymerization method have been investigated here. The synthesized organic–inorganic hybrid materials have been characterized using XRD, FT-IR, FESEM, UV–Vis, Raman, and TGA. Electrical conductance and dielectric behavior of the electrical phenomena of the sample have also been investigated. XRD results demonstrate the amorphous nature of Ppy, however, its composites with TiO2 exhibit crystalline nature. FT-IR spectroscopy reveals the presence of interaction between conducting Ppy and TiO2. UV–Vis study show changes in spectra of Ppy in presence of TiO2 with a slight increase in the band gap. The SEM results reveal encapsulation of TiO2 particles in Ppy matrix and agglomeration of grains have also been observed with evident changes in morphology with increasing percentages of TiO2. TGA data indicates that the composite materials show good thermal stability. Conductance results show that electrical conductivity of Ppy increases upon addition of TiO2. It has also been noticed that the dielectric parameters (dielectric constant, loss tangent) of Ppy vary with addition of TiO2. The resulting insight clearly suggests that by embedding TiO2 in Ppy the electrical properties of the composites can be improved.
Keywords: nanocomposite; polypyrrole; oxidation; TiO2; dielectric

Swift observations of two outbursts from the magnetar 4u 0142+61 - Archibald, R. F.; Kaspi, V. M.; Scholz, P.; Beardmore, A. P.; Gehrels, N.; Kennea, J. A. (The Astrophysical Journal, 2017)
4U 0142+61 is one of a small class of persistently bright magnetars. Here, we report on a monitoring campaign of 4U 0142+61 from 2011 July 26 to 2016 June 12 using the Swift X-ray Telescope, continuing a 16-year timing campaign with the Rossi X-ray Timing Explorer. We show that 4U 0142+61 had two radiatively loud timing events, on 2011 July 29 and 2015 February 28, both with short soft γ-ray bursts, and a long-lived flux decay associated with each case. We show that the 2015 timing event resulted in a net spin-down of the pulsar that is due to overrecovery of a glitch. We compare this timing event to previous such events in other pulsars with high magnetic fields and discuss net spin-down glitches now seen in several young, high-B pulsars.

Superior immunogenicity of HCV envelope glycoproteins when adjuvanted with cyclic-di-AMP, a STING activator or archaeosomes - Landi, A.; Law, J.; Hockman, D.; Logan, M.; Crawford, K.; Chen, C.; Kundu, J.; Ebensen, T.; Guzman, C. A.; Deschatelets, L.; Krishnan, L.; Tyrrell, D. L. J.; et al. (Vaccine, 2017)
Three decades after the discovery, hepatitis C virus (HCV) is still the leading cause of liver transplantation and poses a major threat to global health. In spite of recent advances in the development of direct acting antivirals, there is still a need for a prophylactic vaccine to limit the virus spread and protect at-risk populations, especially in developing countries, where the cost of the new treatments may severely limit access. The use of recombinant HCV glycoproteins E1E2 (rE1E2) in combination with the MF59, an oil-in-water emulsion-based adjuvant, has previously been shown to reduce the rate of chronicity in chimpanzees and to induce production of cross-neutralizing antibodies and cellular immune responses in human volunteers. To further improve neutralizing antibody responses in recipients along with robust T cell responses, we have explored the immunogenicity of different adjuvants when formulated with the HCV rE1E2 vaccine in mice. Our data show that cyclic di-adenosine monophosphate (c-di-AMP) and archaeosomes elicit strong neutralizing antibodies similar to those elicited using aluminum hydroxide/monophosphoryl lipid A (Alum/monophos. /MPLA) and MF59. However, both c-di-AMP and archaeosomes induced a more robust cellular immune response, which was confirmed by the detection of vaccine-specific poly-functional CD4+ T cells. We conclude that these adjuvants may substantially boost the immunogenicity of our E1E2 vaccine. In addition, our data also indicates that use of a partial or exclusive intranasal immunization regimen may also be feasible using c-di-AMP as adjuvant.
Keywords: vaccine; adjuvant; HCV rE1E2 glycoproteins; c-di-AMP; archaeosomes

Sulfur hexafluoride: a novel fixed point for contact thermometry - Dedyulin, S. N. (International Journal of Thermophysics, 2017)
In this paper, we report on the development at NRC of a sulfur hexafluoride (SF6) fixed-point cell for calibrating long-stem standard platinum resistance thermometers. Discussed in detail are the unique challenges of constructing the high-pressure fixed-point cell and realizing the triple point of SF6 in a commercial stirred liquid bath.
Keywords: Fixed-point cell; Sulfur hexafluoride; Triple point

Subwavelength' photonics - Cheben, Pavel; Fernandez, Iñigo Molina; Smith, David; Zhou, Weidong; Berini, Pierre (Optics and Photonics News, 2017)

Subwavelength metamaterial engineering for silicon photonics - Halir, Robert; Ortega-Moñux, Alejandro; Soler-Penades, Jordi; Luque-González, José M.; Sarmiento-Merenguel, Dario; Sánchez-Postigo, Alejandro; Wangüemert-Pérez, Gonzalo; Schmid, Jens; Xu, Dan-Xia; Janz, Siegfried; Lapointe, Jean; Molina-Fernández, Íñigo; et al. (Smart Photonic and Optoelectronic Integrated Circuits XIX, 2017)
Waveguides structured at the subwavelength scale frustrate diffraction and behave as optical metamaterials with controllable refractive index. These structures have found widespread applications in silicon photonics, ranging from sub-decibel efficiency fibre-chip couplers to spectrometers and polarization rotators. Here, we briey describe the design foundations for sub-wavelength waveguide devices, both in terms of analytic effective medium approximations, as well as through rigorous Floch-Bloquet mode simulation. We then focus on two novel structures that exemplify the use of subwavelength waveguides: mid-infrared waveguides and ultra-broadband beamsplitters.

Inverse method to obtain blocked forces of vibrating sound sources in buildings - Höller, Christoph; Gibbs, Barry M. (Acta Acustica united with Acustica, 2017)
Vibrating sources, such as building service equipment, are major contributors to noise in buildings. In order to predict and subsequently reduce the sound pressure levels generated by these devices, it is necessary to first predict the total vibrational power injected by them into the supporting building structure. Whilst simplified methods are available for the calculation of the total power through all contacts, it would be beneficial to have more detailed knowledge of the dominant contact powers. For sources on low-mobility building elements, the contact powers are determined by the blocked force, along with the real part of the receiver mobility at each contact. This paper describes a novel inverse method to obtain the blocked forces at each contact. The method employs an instrumented reception plate, which is numerically modelled to allow optimum accelerometer positions to be selected, for any source and any location. The underlying theory and measurement procedure are described, and experimental validations are presented.

Sublethal and reproductive effects of acute and chronic exposure to flowback and produced water from hydraulic fracturing on the water flea Daphnia magna - Blewett, Tamzin A.; Delompré, Perrine L. M.; He, Yuhe; Folkerts, Erik J.; Flynn, Shannon L.; Alessi, Daniel S.; Goss, Greg G. (Environmental Science & Technology, 2017)
Hydraulic fracturing is an industrial process allowing for the extraction of gas or oil. To fracture the rocks, a proprietary mix of chemicals is injected under high pressure, which later returns to the surface as flowback and produced water (FPW). FPW is a complex chemical mixture consisting of trace metals, organic compounds, and often, high levels of salts. FPW toxicity to the model freshwater crustacean Daphnia magna was characterized utilizing acute (48 h median lethal concentrations; LC50) and chronic (21 day) exposures. A decrease in reproduction was observed, with a mean value of 18.5 neonates produced per replicate over a 21 day chronic exposure to 0.04% FPW, which was a significant decrease from the average of 64 neonates produced in the controls. The time to first brood was delayed in the highest FPW (0.04%) treatment. Neonates exhibited an LC50 of 0.19% of full-strength FPW, making them more sensitive than adults, which displayed an LC50 value of 0.75%. Quantitative PCR highlighted significant changes in expression of genes encoding xenobiotic metabolism (cyp4) and moulting (cut). This study is the first to characterize chronic FPW toxicity and will help with the development of environmental monitoring and risk assessment of FPW spills.

Sub-fragmentation of structural reactive material casings under explosion - Zhang, Fan; Gauthier, Maxime; Cojocaru, Cristian (Shock compression of condensed matter - 2015 : proceedings of the Conference of the American Physical Society Topical Group on Shock Compression of Condensed Matter : 14-19 June 2015, Tampa Bay, Florida, USA, 2017)
A concept of reactive hot spots intruded in a thick, structural reactive material casing was investigated to generate fine fragments for efficient energy release from casing material under explosive loading. This was achieved through distributing micro MoO3 particles into a granular Al casing, made by hot isostatic pressing, in a fuel-rich ratio of 10Al+MoO3. Reaction of Al and MoO3 during casing primary or secondary fragmentation creates heat and gas products to form micro-scale hot spots, whose expansion initiates local fractures leading to fine fragments of the rest of Al. Explosion experiments, using a 4.4 cm diameter cased charge with a casing-to-explosive mass ratio of 1.78 in a 2.1 m3 cylindrical chamber, demonstrated the presence of fine fragments and more efficient fragment combustion to augment air blast, as compared to a baseline pure Al-cased charge, thus indicating the feasibility of the concept.

Study of the scratch resistance criteria and their relationship with mechanical properties and microstructure in a ternary thermoplastic blend - Motamedi, Pouyan; Bagheri, Reza (Wear, 2017)
Polymeric materials generally suffer from a low resistance to various types of surface mechanical damage, among which scratch is a prominent example. While several attempts have been made to assess the scratch resistance and its relationship with the bulk mechanical properties in simple polymeric systems, the available research on the polymeric blends is scarce. This study attempts to fill this gap by studying the link between the scratch resistance and mechanical properties in a ternary polymeric nanocomposite, which has proved to feature superior and tunable mechanical properties. For this aim, blends of polypropylene and polyamide 6 were prepared using melt blending with two different types and various amounts of compatibilizers. Their microstructure was studied using scanning electron microscopy and atomic force microscopy. It was observed that the type of morphology depends upon both compatibilizer type and content. Bulk mechanical properties were investigated at different loading conditions. The microstructure was seen to have a noticeable effect on ductility of the blends. Different scratch groove geometry parameters were seen to be affected by different mechanical properties. It was shown that relying exclusively on scratch groove geometry might lead to contradicting conclusions regarding the effect of bulk mechanical properties on scratch resistance. Instead, a heavier emphasis was placed upon the respective contribution of each parameter to the overall scratch visibility. In addition, it was shown that micro-mechanical scratch deformation mechanisms have a crucial impact on scratch visibility, and they are affected by a complex interplay among various mechanical properties. An analysis of these relationships is provided with the aim of moving towards a comprehensive understanding of scratch visibility and routes to its minimization.
Keywords: scratch; polypropylene; Polyamide; microstructure; mechanical properties

Structure from motion will revolutionize analyses of tidal wetland landscapes - Kalacska, M.; Chmura, G. L.; Lucanus, O.; Bérubé, D.; Arroyo-Mora, J. P. (Remote Sensing of Environment, 2017)
Ecosystem services of tidal wetlands depend upon hydrology and vegetation, which in turn vary with elevation differences on the order of centimeters. Variability on such a fine scale is not captured in digital elevation models prepared from conventionally acquired LiDAR data products that generally have a spatial resolution of 0.5–1.0 m and vertical uncertainties up to 15 cm. Until recently, capturing critical fine scale features required laborious, hands-on field surveys that took days to collect data and time limitations usually required surveys to be restricted to selected areas of a wetland. Using Structure-from-motion (SfM) photogrammetry and a small unmanned aerial vehicle, precise three-dimensional point clouds, digital surface models (DSM) and color orthomosaics were produced for three salt marshes in Eastern Canada. Vertical and horizontal measurements from the SfM photogrammetry compared favorably to those taken with a Differential Global Positioning System DGPS). Average horizontal displacements of 1.0–2.9 cm were found across the three salt marshes with an average elevation difference of 2.7 cm (± 1.7 cm) in comparison to DGPS. Analysis of the relationship of elevation between points taken with the DGPS and extracted from the SfM DSM gave an R2 of 0.99. With a ground sampling distance of 2.3 cm our SfM photogrammetry generated models captured variations in topography associated with geomorphic features such as creeks, ponds, channel edges, and logs not visible in the DSM prepared from LiDAR of the same sites. SfM photogrammetry enables mapping of important hydrological features, such as creeks carrying drainage from upland watersheds or connectivity of ponds on the wetland surface. The former are important for transport of contaminants or diadromous fish, and the latter is important for resident fish, water birds, and mosquito larvae. Using SfM to distinguish vegetation structure that may indicate vegetation composition will enable more informed analyses of elevational controls on plant distribution and better prediction of their fate with sea level rise.
Keywords: UAV; LiDAR; DGPS; digital elevation model; hydrology; salt marsh

Structure controlled long-range sequential tunneling in carbon-based molecular junctions - Morteza Najarian, Amin; Mccreery, Richard L. (ACS Nano, 2017)
Carbon-based molecular junctions consisting of aromatic oligomers between conducting sp2 hybridized carbon electrodes exhibit structure-dependent current densities (J) when the molecular layer thickness (d) exceeds ∼5 nm. All four of the molecular structures examined exhibit an unusual, nonlinear ln J vs bias voltage (V) dependence which is not expected for conventional coherent tunneling or activated hopping mechanisms. All molecules exhibit a weak temperature dependence, with J increasing typically by a factor of 2 over the range of 200–440 K. Fluorene and anthraquinone show linear plots of ln J vs d with nearly identical J values for the range d = 3–10 nm, despite significant differences in their free-molecule orbital energy levels. The observed current densities for anthraquinone, fluorene, nitroazobenzene, and bis-thienyl benzene for d = 7–10 nm show no correlation with occupied (HOMO) or unoccupied (LUMO) molecular orbital energies, contrary to expectations for transport mechanisms based on the offset between orbital energies and the electrode Fermi level. UV–vis absorption spectroscopy of molecular layers bonded to carbon electrodes revealed internal energy levels of the chemisorbed films and also indicated limited delocalization in the film interior. The observed current densities correlate well with the observed UV–vis absorption maxima for the molecular layers, implying a transport mechanism determined by the HOMO–LUMO energy gap. We conclude that transport in carbon-based aromatic molecular junctions is consistent with multistep tunneling through a barrier defined by the HOMO–LUMO gap, and not by charge transport at the electrode interfaces. In effect, interfacial “injection” at the molecule/electrode interfaces is not rate limiting due to relatively strong electronic coupling, and transport is controlled by the “bulk” properties of the molecular layer interior.
Keywords: charge transport; electronic coupling; localization length; molecular electronics; multistep tunneling; thermally assisted tunneling

Structural sequencing of oligopeptides aided by 1H iterative full-spin analysis - Gao, Wei; Mcalpine, James B.; Choules, Mary P.; Napolitano, José G.; Lankin, David C.; Simmler, Charlotte; Ho, Ngoc Anh; Lee, Hanki; Suh, Joo-Won; Burton, Ian W.; Cho, Sanghyun; Franzblau, Scott G.; et al. (Journal of Natural Products, 2017)
This report describes an approach using 1H NMR iterative full-spin analysis (HiFSA) to extract definitive structural information on unknown peptides from 1D 1H NMR data. By comparing the experimental data and HiFSA fingerprint of a known analogue, it is possible to isolate the characteristic 1H subspectrum of the different amino acids and, thus, elucidate the structure of the peptide. To illustrate this methodology, a comprehensive analysis of five new anti-Mycobacterium tuberculosis peptides (2–6), all analogues of ecumicin (1), was carried out. The method was validated by demonstrating congruence of the HiFSA-based structures with all available data, including MS and 2D NMR. The highly reproducible HiFSA fingerprints of the new ∼1600 amu peptides were generated in this process. Besides oligo-peptides, the HiFSA sequencing approach could be extended to all oligomeric compounds consisting of chains of monomers lacking H–H spin–spin coupling across the moieties. HiFSA sequencing is capable of differentiating complex oligomers that exhibit minor structural differences such as shifted hydoxyl or methyl groups. Because it employs the basic and most sensitive 1D 1H NMR experiment, HiFSA sequencing enables the exploration of peptide analogues up to at least 2000 amu, even with basic contemporary spectrometers and when only sub-milligram amounts of isolates are available.

Sticking to cellulose: exploiting Arabidopsis seed coat mucilage to understand cellulose biosynthesis and cell wall polysaccharide interactions - Griffiths, Jonathan S.; North, Helen M. (New Phytologist, 2017)
The cell wall defines the shape of cells and ultimately plant architecture. It provides mechanical resistance to osmotic pressure while still being malleable and allowing cells to grow and divide. These properties are determined by the different components of the wall and the interactions between them. The major components of the cell wall are the polysaccharides cellulose, hemicellulose and pectin. Cellulose biosynthesis has been extensively studied in Arabidopsis hypocotyls, and more recently in the mucilage‐producing epidermal cells of the seed coat. The latter has emerged as an excellent system to study cellulose biosynthesis and the interactions between cellulose and other cell wall polymers. Here we review some of the major advances in our understanding of cellulose biosynthesis in the seed coat, and how mucilage has aided our understanding of the interactions between cellulose and other cell wall components required for wall cohesion. Recently, 10 genes involved in cellulose or hemicellulose biosynthesis in mucilage have been identified. These discoveries have helped to demonstrate that xylan side‐chains on rhamnogalacturonan I act to link this pectin directly to cellulose. We also examine other factors that, either directly or indirectly, influence cellulose organization or crystallization in mucilage.
Keywords: Arabidopsis; arabinogalactan protein; cell wall; cellulose; hemicellulose; mucilage; pectin; receptor-like kinase

Stabilizing double perovskite for effective bifunctional oxygen electrocatalysis in alkaline conditions - Hua, Bin; Sun, Yi-Fei; Li, Meng; Yan, Ning; Chen, Jian; Zhang, Ya-Qian; Zeng, Yimin; Shalchi Amirkhiz, Babak; Luo, Jing-Li (Chemistry of Materials, 2017)
Oxygen electrocatalysis is at the heart of the emerging energy conversion and storage devices including reversible fuel cells and metal-air batteries. However, replacing the noble-metal-based oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts with affordable and robust alternatives remains challenging to date. Herein, we report a cation-ordered double perovskite oxide, i.e., PrBa0.85Ca0.15MnFeO5+δ, with excellent stability and activity in both OER and ORR. The layered crystal structure provides ordered oxygen vacancy channels and a vast amount of surface oxygen defects, while the moderate amount of iron dopant keeps the B-site cations at high oxidation state with optimal eg fillings. Importantly, the DFT calculations along with the advanced TEM analysis verify that the incorporation of Ca at the A-site stabilizes the perovskite structure under potential bias. Such a bifunctional catalyst shows comparable, if not better, activity relative to the state-of-the-art perovskite oxides (e.g., Ba0.5Sr0.5Co0.8Fe0.2O3−δ) while demonstrating remarkably enhanced robustness. This work presents a rational approach of designing efficient, robust, and cost-effective perovskite oxide for oxygen electrocatalysis and sheds light on the influences of the crystallographic structure on the catalytic property.

Spin-down evolution and radio disappearance of the magnetar PSR J1622–4950 - Scholz, P.; Camilo, F.; Sarkissian, J.; Reynolds, J. E.; Levin, L.; Bailes, M.; Burgay, M.; Johnston, S.; Kramer, M.; Possenti, A. (The Astrophysical Journal, 2017)
We report on 2.4 yr of radio timing measurements of the magnetar PSR J1622−4950 using the Parkes Observatory, between 2011 November and 2014 March. During this period the torque on the neutron star (inferred from the rotational frequency derivative) varied greatly, though much less erratically than during the 2 yr following its discovery in 2009. During the last year of our measurements the frequency derivative decreased in magnitude monotonically by 20%, to a value of −1.3 × 10−13 s−2, a factor of 8 smaller than when it was discovered. The flux density continued to vary greatly during our monitoring through 2014 March, reaching a relatively steady low level after late 2012. The pulse profile varied secularly on a similar timescale as the flux density and torque. A relatively rapid transition in all three properties was evident in early 2013. After PSR J1622−4950 was detected in all of our 87 observations up to 2014 March, we did not detect the magnetar in our resumed monitoring starting in 2015 January and have not detected it in any of the 30 observations conducted through 2016 September.
Keywords: pulsars: general; pulsars: individual (PSR J1622–4950); stars: magnetars; stars: neutron

Spectroscopic orbits of three binaries - Scarfe, C. D. (Revista Mexicana de Astronomia y Astrofisica, 2017)
This paper presents new spectroscopic orbits of three binaries with evolved primaries and periods of the order of a few years, two of them very eccentric. All the orbits were determined primarily from observations made with the DAO 1.2-m telescope and coudé spectrograph. Observations were obtained using the radial velocity spectrometer until it was decommissioned in 2004, and since then using a CCD detector, and cross-correlating the spectra with those of standard stars. It will be evident that the latter procedure leads to smaller observational scatter than the former did.

Spatio–temporal coupling to create sub-femtosecond pulses - Hammond, T. J. (Journal of Optics, 2017)
We use the confluence of two intensity-dependent processes—low-order harmonic generation and self-phase modulation—to spatio–temporally couple and compress few-cycle pulses to be sub-cycle in duration. These half-cycle transient fields self-focus in space and in time (increasing the peak field strength) and can generate isolated attosecond pulses. We explore some of the parameter spaces available to create these half-cycle transients and methods of improving the half-cycle contrast. We also discuss how these pulses can increase high harmonic generation efficiency in the water window.
Keywords: ultrafast nonlinear optics; space–time coupling; nonlinear pulse compression; high harmonic generation

Solid-state 17O NMR reveals hydrogen-bonding energetics: not all low-barrier hydrogen bonds are strong - Lu, Jiasheng; Hung, Ivan; Brinkmann, Andreas; Gan, Zhehong; Kong, Xianqi; Wu, Gang (Angewandte Chemie International Edition, 2017)
While NMR and IR spectroscopic signatures and structural characteristics of low‐barrier hydrogen bond (LBHB) formation are well documented in the literature, direct measurement of the LBHB energy is difficult. Here, we show that solid‐state 17O NMR spectroscopy can provide unique information about the energy required to break a LBHB. Our solid‐state 17O NMR data show that the HB enthalpy of the O⋅⋅⋅H⋅⋅⋅N LBHB formed in crystalline nicotinic acid is only 7.7±0.5 kcal mol−1, suggesting that not all LBHBs are particularly strong.

Sn–Bi–Sb alloys as anode materials for sodium ion batteries - Xie, Hezhen; Kalisvaart, W. Peter; Olsen, Brian C.; Luber, Erik J.; Mitlin, David; Buriak, Jillian M. (Journal of Materials Chemistry A, 2017)
In this work, the performance and electrochemical charge/discharge behavior of Sn–Bi–Sb alloy films were examined, as well as pure Sn, Bi, and Sb films, as anodes for sodium ion batteries (SIBs). Alloying was utilized as an approach to modify the morphology and active phases in an effort to improve the cycling stability of elemental anodes of Sn or Sb, while maintaining a high capacity. The films were prepared via sputtering, which enabled study of a broad swath of compositional space. The cycling performance of the Sb-rich compositions surpassed that of all other alloys tested as anodes for SIBs. The best performing alloy had a composition of 10 at% Sn, 10 at% Bi, and 80 at% Sb (called Sn10Bi10Sb80, here), and maintained 99% of its maximum capacity during cycling (621 mA h g−1) after 100 cycles. Stability of these anodes dropped as the quantity of Sb decreased; to contrast, Sn20Bi20Sb60, Sn25Bi25Sb50 and Sn33Bi33Sb33 were increasingly less stable as anodes in SIBs as the molar quantity of Sb in the films dropped to 60%, 50%, and 33%, respectively. The Sn10Bi10Sb80 electrode was found to possess a single phase as-deposited microstructure of Sn and Bi in substitutional solid solution with the Sb lattice and the sodiation sequence was found to be significantly different from pure Sb. Numerous possible mechanisms for the improvement in capacity retention were discussed, where modification and material response to internal stresses by changes in the Sb chemical potential and solid solution strengthening were found to be the most likely.

Smart tuning of 3D ordered electrocatalysts for enhanced oxygen reduction reaction - Sun, Yi-Fei; Zhang, Ya-Qian; Yang, Yan-Ling; Chen, Jian; Hua, Bin; Shi, Yi-Xiang; Wang, Chang-An; Luo, Jing-Li (Applied Catalysis B: Environmental, 2017)
Extensive research has been devoted to the development of advanced oxygen reduction reaction (ORR) catalysts with functionally diverse active sites. Herein, we show a smart approach to advancing the ORR catalytic activity of a 3D porous perovskite. The facile oxidative-reductive-oxidative (O-R-O) thermal treatment cycle executed on Ag doped LaFeO3 could stepwise switch on three different reaction sites (exsolved Ag-NPs, oxygen deficiency and Fe4+ with optimal electron configuration) for ORR. Detailed characterizations illustrate that the ORR activity is basically derived from the hierarchically porous scaffold which provides a large surface area and enough pore volumes for mass and ion diffusion. More importantly, the unique synergistic effects among three separate kinds of reaction sites endow the speed-up of oxygen adsorption, activation and O2− transportation. The exemplified results set out new design principles for the optimization of alternative catalysts.

Single-photon source based on Rydberg exciton blockade - Khazali, Mohammadsadegh; Heshami, Khabat; Simon, Christoph (Journal of Physics B: Atomic, Molecular and Optical Physics, 2017)
Bound states of electron–hole pairs in semiconductors demonstrate a hydrogen-like behavior in their high-lying excited states that are also known as Rydberg exciton states. The strong interaction between excitons in levels with high principal quantum numbers prevents the creation of more than one exciton in a small crystal; resulting in the Rydberg blockade effect. Here, we propose a new kind of solid-state single-photon source based on the recently observed Rydberg blockade effect for excitons in cuprous oxide. Our quantitative estimates based on single and double excitation probability dynamics indicate that GHz rates and values of the second-order correlation function ${g}_{2}(0)$ below the percent level can be simultaneously achievable. These results should pave the way to explore applications of Rydberg excitons in photonic quantum information processing.
Keywords: Rydberg excitons; Rydberg blockade; single-photon sources

Single laser modulated drive and detection of a nano-optomechanical cantilever - Sauer, Vincent T. K.; Diao, Zhu; Westwood-Bachman, Jocelyn N.; Freeman, Mark R.; Hiebert, Wayne K. (AIP Advances, 2017)
To reduce the complexity in a nano-optomechanical system a pump and probe scheme using only a single input laser is used to both coherently pump and probe the nanomechanical device. The system operates similarly to the traditional two laser system, but instead of using a constant power to probe the device and a separate, modulated laser to drive it with an optical gradient force, a single laser is utilized for both functions. A model of the measurement scheme’s response is developed which matches the experimental data obtained in the optomechanical Doppler regime and low cavity power limit. As such, the unconventional response still yields useful device information such as the resonant frequency of the device and its mechanical quality factor. The device is driven with low noise and its frequency is tracked using a phase-locked loop. This demonstrates its potential use for dynamic frequency measurements such as nanomechanical inertial mass loading. In such a system, the estimated mass resolution of the device is 6 zg and consistent with other detection methods.

Simultaneous X-ray, gamma-ray, and radio observations of the repeating fast radio burst FRB 121102 - Scholz, P.; Bogdanov, S.; Hessels, J. W. T.; Lynch, R. S.; Spitler, L. G.; Bassa, C. G.; Bower, G. C.; Burke-Spolaor, S.; Butler, B. J.; Chatterjee, S.; Cordes, J. M.; Gourdji, K.; et al. (The Astrophysical Journal, 2017)
We undertook coordinated campaigns with the Green Bank, Effelsberg, and Arecibo radio telescopes during Chandra X-ray Observatory and XMM-Newton observations of the repeating fast radio burst FRB 121102 to search for simultaneous radio and X-ray bursts. We find 12 radio bursts from FRB 121102 during 70 ks total of X-ray observations. We detect no X-ray photons at the times of radio bursts from FRB 121102 and further detect no X-ray bursts above the measured background at any time. We place a 5σ upper limit of 3 × 10−11 erg cm−2 on the 0.5–10 keV fluence for X-ray bursts at the time of radio bursts for durations $\lt 700$ ms, which corresponds to a burst energy of 4 × 1045 erg at the measured distance of FRB 121102. We also place limits on the 0.5–10 keV fluence of 5 × 10−10 and 1 × 10−9 erg cm−2 for bursts emitted at any time during the XMM-Newton and Chandra observations, respectively, assuming a typical X-ray burst duration of 5 ms. We analyze data from the Fermi Gamma-ray Space Telescope Gamma-ray Burst Monitor and place a 5σ upper limit on the 10–100 keV fluence of 4 × 10−9 erg cm−2 (5 × 1047 erg at the distance of FRB 121102) for gamma-ray bursts at the time of radio bursts. We also present a deep search for a persistent X-ray source using all of the X-ray observations taken to date and place a 5σ upper limit on the 0.5–10 keV flux of 4 × 10−15 erg s−1 cm−2 (3 × 1041 erg s−1 at the distance of FRB 121102). We discuss these non-detections in the context of the host environment of FRB 121102 and of possible sources of fast radio bursts in general.
Keywords: gamma rays: general; stars: neutron; X-rays: bursts; X-rays: general

Simulations of hydrogen gas in clathrate hydrates - Alavi, Saman; Ripmeester, John A. (Molecular Simulation, 2017)
In this article, computational studies of hydrogen storage in clathrate hydrate phases are reviewed. A summary of experimental studies of pure hydrogen and binary large guest + hydrogen clathrate hydrate formation are presented in the Introduction. The experimental results include studies of the synthesis conditions, X-ray and neutron diffraction structural characterisations, cage occupancies and guest spectroscopy in these phases. Computational studies of hydrogen clathrate hydrates are categorised in three sections and compared to experiments. In the first section, statistical mechanical, classical molecular dynamics (MD) and Monte Carlo simulations of the hydrogen clathrate hydrate phases are discussed. Many of these studies focus on determining the occupancy of hydrogen in the small- and large-structure II clathrate hydrate phases. In the second section, quantum mechanical studies of the eigenstates of H2 encapsulated in the clathrate hydrate cages are presented. Ab initio MDs simulations of hydrogen clathrate hydrate phases are also reviewed in this section. In the third section, computational studies of the diffusion of H2 molecules through the clathrate hydrate cages are reviewed. Diffusion of H2 guests is an important aspect for the practical use of clathrate hydrates as hydrogen storage materials. The conclusions summarise the insight that molecular simulations have given to the use of clathrate hydrates for hydrogen storage and future directions for hydrogen storage in water-based phases.
Keywords: Clathrate hydrates; hydrogen hydrate; ab initio calculations; molecular dynamics simulations; hydrogen storage

Seasonal changes in the properties of first-year, second-year and multi-year ice - Johnston, M. E. (Cold Regions Science and Technology, 2017)
To date, too few measurements have been available to document the seasonal change in the strength for different types of sea ice. The situation is remedied here with nearly 1300 borehole measurements on first-year ice (FYI), second-year ice (SYI) and multi-year ice (MYI) in the Canadian Arctic from the past 15 years. The thickness, temperature, salinity and borehole strength are given for five categories of sea ice: FYI, SYI, young multi-year ice (yMYI), thick level multi-year ice (TkMYI) and hummocked multi-year ice (hMYI). Results show that the deterioration of FYI and SYI is offset by about one month in summer, yMYI is more similar to TkMYI than SYI, and deteriorated MYI floes can have strengths comparable to more competent looking MYI floes in summer. The seasonal reduction in strength for different ice types is expressed here as an ‘equivalent floe strength’, which is the depth-averaged strength of all boreholes on a floe normalized by the maximum depth-averaged strength of FYI in winter (32 MPa). Seasonal trends in strength show SYI and MYI floes to be stronger than FYI floes in all seasons. The strength of FYI floes decreases from 61% (May) to 9% (July), relative to its 32 MPa winter maximum, whereas the equivalent floe strength of SYI decreases from 69% (May) to 16% (August), relative to 32 MPa. The equivalent floe strength of the combined category of yMYI & TkMYI decreases from 78% or more (May) to 40% (September). The equivalent floe strength of hMYI decreases from 102% (May) to 51% (September).
Keywords: first-year; second-year; young multi-year; hummock; borehole strength; thickness; temperature; salinity

SDSS IV MaNGA: discovery of an Hα blob associated with a dry galaxy pair-ejected gas or a “dark” galaxy candidate? - Lin, Lihwai; Lin, Jing-Hua; Hsu, Chin-Hao; Fu, Hai; Huang, Song; Sánchez, Sebastián F.; Gwyn, Stephen; Gelfand, Joseph D.; Cheung, Edmond; Masters, Karen; Peirani, Sébastien; Rujopakarn, Wiphu; et al. (The Astrophysical Journal, 2017)
We report the discovery of a mysterious giant Hα blob that is ~8 kpc away from the main MaNGA target 1-24145, one component of a dry galaxy merger, and has been identified in the first-year SDSS-IV MaNGA data. The size of the Hα blob is ~3–4 kpc in radius, and the Hα distribution is centrally concentrated. However, there is no optical continuum counterpart in the deep broadband images reaching ~26.9 mag arcsec−2 in surface brightness. We estimate that the masses of the ionized and cold gases are 3.3x10^5M⊙ and < 1.3x10^9M⊙, respectively. The emission-line ratios indicate that the Hα blob is photoionized by a combination of massive young stars and AGNs. Furthermore, the ionization line ratio decreases from MaNGA 1-24145 to the Hα blob, suggesting that the primary ionizing source may come from MaNGA 1-24145, likely a low-activity AGN. Possible explanations for this Hα blob include the AGN outflow, the gas remnant being tidally or ram-pressure stripped from MaNGA 1-24145, or an extremely low surface brightness galaxy. However, the stripping scenario is less favored according to galaxy merger simulations and the morphology of the Hα blob. With the current data, we cannot distinguish whether this Hα blob is ejected gas due to a past AGN outburst, or a special category of "ultra-diffuse galaxy" interacting with MaNGA 1-24145 that further induces the gas inflow to fuel the AGN in MaNGA 1-24145.
Keywords: galaxies: evolution; galaxies: interactions; galaxies: peculiar

Salt segregation and sample cleanup on perfluoro-coated nanostructured surfaces for laser desorption ionization mass spectrometry of biofluid samples - Zhou, Ya; Peng, Chen; Harris, Kenneth D.; Mandal, Rupasri; Harrison, D. Jed (Analytical Chemistry, 2017)
We present a surface assisted laser desorption ionization (SALDI) technique, coupled with fluorocarbon coating, to achieve selective segregation of ionic and/or hydrophilic analytes from background biofluid electrolytes for quantiatve mass spectrometric analysis. By controlling the contact angle of (1H,1H,2H,2H-perfluorooctyl) trichlorosilane or (1H,1H,2H,2H-perfluorooctyl) dimethylchlorosilane to a specific range (105–120°), background electrolytes can be made to segregate from hydrophilic analytes during a drying step on the surface of a highly nanoporous thin film. Nanoporous silicon films were prepared using glancing angle deposition (GLAD) thin film technology, then coated with fluorcarbon. This desalting method directly separates highly polar, ionic metabolites, such as amino acids, from salty biofluids such as aritificial cerebrospinal fluid (aCSF) and serum. Derivatization, extraction and rinsing steps are not required to separate the analytes from the bioelectrolytes. With on-chip desalting, the limit of quantitation for histidine spiked in aCSF is ∼1 μM, and calibration curves with internal standards can achieve a precision of 1–9% within a 1 to 50 μM range. Five highly polar organic acids in serum were successfully quantified, and the SALDI-MS results obtained on the desalted serum sample spots show both good reproducibility and compare well to results from NMR and liquid chromatography–mass spectrometry. Putative identification of a total of 32 metabolites was accomplished in blood using time-of-flight MS with perfluoro coated Si-GLAD SALDI, by comparison to tabulated data.

Robust bipolar light emission and charge transport in symmetric molecular junctions - Tefashe, Ushula M.; Nguyen, Quyen Van; Lafolet, Frederic; Lacroix, Jean-Christophe; Mccreery, Richard L. (Journal of the American Chemical Society, 2017)
Molecular junctions consisting of a Ru(bpy)3 oligomer between conducting carbon contacts exhibit an exponential dependence of junction current on molecular layer thickness (d) similar to that observed for other aromatic devices when d < 4 nm. However, when d > 4 nm, a change in transport mechanism occurs which coincides with light emission in the range of 600–900 nm. Unlike light emission from electrochemical cells or solid-state films containing Ru(bpy)3, emission is bipolar, occurs in vacuum, has rapid rise time (<5 ms), and persists for >10 h. Light emission directly indicates simultaneous hole and electron injection and transport, possibly resonant due to the high electric field present (>3 MV/cm). Transport differs fundamentally from previous tunneling and hopping mechanisms and is a clear “molecular signature” relating molecular structure to electronic behavior.

Results of the CCRI(II)-S12.H-3 supplementary comparison: comparison of methods for the calculation of the activity and standard uncertainty of a tritiated-water source measured using the LSC-TDCR method - Cassette, Philippe; Altzitzoglou, Timotheos; Antohe, Andrei; Rossi, Mario; Arinc, Arzu; Capogni, Marco; Galea, Raphael; Gudelis, Arunas; Kossert, Karsten; Lee, K. B.; Liang, Juncheng; Nedjadi, Youcef; et al. (Applied Radiation and Isotopes, 2017)
A comparison of calculations of the activity of a 3H2O liquid scintillation source using the same experimental data set collected at the LNE-LNHB with a triple-to-double coincidence ratio (TDCR) counter was completed. A total of 17 laboratories calculated the activity and standard uncertainty of the LS source using the files with experimental data provided by the LNE-LNHB. The results as well as relevant information on the computation techniques are presented and analysed in this paper. All results are compatible, even if there is a significant dispersion between the reported uncertainties. An output of this comparison is the estimation of the dispersion of TDCR measurement results when measurement conditions are well defined.
Keywords: LSC; TDCR; tritium; activity comparison

Response to alternating electric fields of tubulin dimers and microtubule ensembles in electrolytic solutions - Santelices, Iara B.; Friesen, Douglas E.; Bell, Clayton; Hough, Cameron M.; Xiao, Jack; Kalra, Aarat; Kar, Piyush; Freedman, Holly; Rezania, Vahid; Lewis, John D.; Shankar, Karthik; Tuszynski, Jack A. (Scientific Reports, 2017)
Microtubules (MTs), which are cylindrical protein filaments that play crucial roles in eukaryotic cell functions, have been implicated in electrical signalling as biological nanowires. We report on the small-signal AC (“alternating current”) conductance of electrolytic solutions containing MTs and tubulin dimers, using a microelectrode system. We find that MTs (212 nM tubulin) in a 20-fold diluted BRB80 electrolyte increase solution conductance by 23% at 100 kHz, and this effect is directly proportional to the concentration of MTs in solution. The frequency response of MT-containing electrolytes exhibits a concentration-independent peak in the conductance spectrum at 111 kHz (503 kHz FWHM that decreases linearly with MT concentration), which appears to be an intrinsic property of MT ensembles in aqueous environments. Conversely, tubulin dimers (42 nM) decrease solution conductance by 5% at 100 kHz under similar conditions. We attribute these effects primarily to changes in the mobility of ionic species due to counter-ion condensation effects, and changes in the solvent structure and solvation dynamics. These results provide insight into MTs’ ability to modulate the conductance of aqueous electrolytes, which in turn, has significant implications for biological information processing, especially in neurons, and for intracellular electrical communication in general.

Resorbability of a Bioglass®-based glass-ceramic scaffold produced via a powder metallurgy approach - Melli, Virginia; Lefebvre, Louis-Philippe; Lenci, Matthieu; Mondon, Marilyne; Sao-Joao, Sergio; Cigada, Alberto; Delafosse, David; De nardo, Luigi (Ceramics International, 2017)
Consolidation processes aimed at manufacturing cellular solids from bioglasses often result in a glass-ceramic microstructure, whose response to aqueous environment affects their performance. In this study, we evaluated the microstructure and the effect of crystallization on the dissolution mechanism of a Bioglass®-based glass-ceramic scaffold, produced with a powder metallurgy inspired technology. All the experiments are conducted in a controlled aqueous environment in order to avoid nucleation of different species or unknown chemical interactions between simulated body fluids and bioglass-ceramic material. The presence of a residual silica glass embedding different phases of not fully crystallized particles is highlighted, showing a complex multiscale structure elucidated via Focused Ion Beam (FIB) preparation and Scanning Transmission Electron Microscopy (STEM) observation. Crystalline and amorphous phases dissolved both in water, with different kinetics. The dissolution appears to be a surface phenomenon, which reduces the section of the foam struts without instability of the glass-ceramic material. Amorphization of crystalline phase is observed during immersion of the glass-ceramic material in stirring conditions at room temperature from the ions dissolved in water.
Keywords: 45S5 Bioglass®; glass-ceramic scaffold; resorption; amorphization

Recombinant incretin-secreting microbe improves metabolic dysfunction in high-fat diet fed rodents - Ryan, Paul M.; Patterson, Elaine; Kent, Robert M.; Stack, Helena; O’Connor, Paula M.; Murphy, Kiera; Peterson, Veronica L.; Mandal, Rupasri; Wishart, David S.; Dinan, Timothy G.; Cryan, John F.; Seeley, Randy J.; et al. (Scientific Reports, 2017)
The gut hormone glucagon-like peptide (GLP)-1 and its analogues represent a new generation of anti-diabetic drugs, which have also demonstrated propensity to modulate host lipid metabolism. Despite this, drugs of this nature are currently limited to intramuscular administration routes due to intestinal degradation. The aim of this study was to design a recombinant microbial delivery vector for a GLP-1 analogue and assess the efficacy of the therapeutic in improving host glucose, lipid and cholesterol metabolism in diet induced obese rodents. Diet-induced obese animals received either Lactobacillus paracasei NFBC 338 transformed to express a long-acting analogue of GLP-1 or the isogenic control microbe which solely harbored the pNZ44 plasmid. Short-term GLP-1 microbe intervention in rats reduced serum low-density lipoprotein cholesterol, triglycerides and triglyceride-rich lipoprotein cholesterol substantially. Conversely, extended GLP-1 microbe intervention improved glucose-dependent insulin secretion, glucose metabolism and cholesterol metabolism, compared to the high-fat control group. Interestingly, the microbe significantly attenuated the adiposity associated with the model and altered the serum lipidome, independently of GLP-1 secretion. These data indicate that recombinant incretin-secreting microbes may offer a novel and safe means of managing cholesterol metabolism and diet induced dyslipidaemia, as well as insulin sensitivity in metabolic dysfunction.

Recognition of protein-linked glycans as a determinant of peptidase activity - Noach, Ilit; Ficko-Blean, Elizabeth; Pluvinage, Benjamin; Stuart, Christopher; Jenkins, Meredith L.; Brochu, Denis; Buenbrazo, Nakita; Wakarchuk, Warren; Burke, John E.; Gilbert, Michel; Boraston, Alisdair B. (Proceedings of the National Academy of Sciences, 2017)
Protein glycosylation is one of the most abundant and important posttranslational modifications where the protein-linked glycans can impart specific physiochemical properties to the glycoprotein and/or the glycans themselves can mediate particular biological functions. The degradation of glycosylated proteins in normal or pathogenic processes, therefore, is an important biological process. This study reveals the molecular basis of how peptidases can use the O-glycans present on glycoproteins as a critical determinant of peptidase activity and, in doing so, provides unique insight into how peptidases may directly use posttranslational modifications present on their substrates to influence recognition and peptide bond cleavage.

Recent advances on p-Type III-nitride nanowires by molecular beam epitaxy - Zhao, Songrui; Mi, Zetian (Crystals, 2017)
p-Type doping represents a key step towards III-nitride (InN, GaN, AlN) optoelectronic devices. In the past, tremendous efforts have been devoted to obtaining high quality p-type III-nitrides, and extraordinary progress has been made in both materials and device aspects. In this article, we intend to discuss a small portion of these processes, focusing on the molecular beam epitaxy (MBE)-grown p-type InN and AlN—two bottleneck material systems that limit the development of III-nitride near-infrared and deep ultraviolet (UV) optoelectronic devices. We will show that by using MBE-grown nanowire structures, the long-lasting p-type doping challenges of InN and AlN can be largely addressed. New aspects of MBE growth of III-nitride nanostructures are also discussed.
Keywords: molecular beam epitaxy; nanowire; p-type; GaN; InN; AlN; laser; LED

Recent advances in the determination of some Galactic constants in the Milky Way - Vallée, Jacques P. (Astrophysics and Space Science, 2017)
Here we statistically evaluate recent advances in determining the Sun-Galactic Center distance (Rsun) as well as recent measures of the orbital velocity around the Galactic Center (Vlsr), and the angular rotation parameters of various objects. Recent statistical results point to Rsun =8.0±0.2 kpc, Vlsr =230±3 km/s, and angular rotation at the Sun (ω) near 29±1 km/s/kpc for the gas and stars at the Local Standard of Rest, and near 23±2 km/s/kpc for the spiral pattern itself.
Keywords: Galactic structure; Galactic constants; Galactic disk; Statistics

Time-resolved multi-mass ion imaging: femtosecond UV-VUV pump-probe spectroscopy with the PImMS camera - Forbes, Ruaridh; Makhija, Varun; Veyrinas, Kévin; Stolow, Albert; Lee, Jason W. L.; Burt, Michael; Brouard, Mark; Vallance, Claire; Wilkinson, Iain; Lausten, Rune; Hockett, Paul (The Journal of Chemical Physics, 2017)
The Pixel-Imaging Mass Spectrometry (PImMS) camera allows for 3D charged particle imaging measurements, in which the particle time-of-flight is recorded along with (x, y) position. Coupling the PImMS camera to an ultrafast pump-probe velocity-map imaging spectroscopy apparatus therefore provides a route to time-resolved multi-mass ion imaging, with both high count rates and large dynamic range, thus allowing for rapid measurements of complex photofragmentation dynamics. Furthermore, the use of vacuum ultraviolet wavelengths for the probe pulse allows for an enhanced observation window for the study of excited state molecular dynamics in small polyatomic molecules having relatively high ionization potentials. Herein, preliminary time-resolved multi-mass imaging results from C2F3I photolysis are presented. The experiments utilized femtosecond VUV and UV (160.8 nm and 267 nm) pump and probe laser pulses in order to demonstrate and explore this new time-resolved experimental ion imaging configuration. The data indicate the depth and power of this measurement modality, with a range of photofragments readily observed, and many indications of complex underlying wavepacket dynamics on the excited state(s) prepared.

Recent advances in engineering propionyl-CoA metabolism for microbial production of value-added chemicals and biofuels - Srirangan, Kajan; Bruder, Mark; Akawi, Lamees; Miscevic, Dragan; Kilpatrick, Shane; Moo-Young, Murray; Chou, C. Perry (Critical Reviews in Biotechnology, 2017)
Diminishing fossil fuel reserves and mounting environmental concerns associated with petrochemical manufacturing practices have generated significant interests in developing whole-cell biocatalytic systems for the production of value-added chemicals and biofuels. Although acetyl-CoA is a common natural biogenic precursor for the biosynthesis of numerous metabolites, propionyl-CoA is unpopular and non-native to most organisms. Nevertheless, with its C3-acyl moiety as a discrete building block, propionyl-CoA can serve as another key biogenic precursor to several biological products of industrial importance. As a result, engineering propionyl-CoA metabolism, particularly in genetically tractable hosts with the use of inexpensive feedstocks, has paved an avenue for novel biomanufacturing. Herein, we present a systematic review on manipulation of propionyl-CoA metabolism as well as relevant genetic and metabolic engineering strategies for microbial production of value-added chemicals and biofuels, including odd-chain alcohols and organic acids, bio(co)polymers and polyketides.
Keywords: biofuels; biopolymers; metabolic engineering; polyketides; propionyl-CoA; synthetic biology; value-added products

Rapid determination of nitrate in vegetables by gas chromatography mass spectrometry - Campanella, Beatrice; Onor, Massimo; Pagliano, Enea (Analytica Chimica Acta, 2017)
In this study we present a novel isotope dilution gas chromatography method for the determination of nitrate in vegetables. The analyte was extracted in water at 70∘C and mixed with 15N isotopically enriched nitrate internal standard. The sample was centrifuged and the supernatant reacted with sulfamic acid for removal of nitrite, and with triethyloxonium tetrafluoroborate for converting nitrate into volatile EtONO2. This simple aqueous chemistry allowed for separation of analyte from sample matrix in the form of a gaseous derivative which could be sampled in the headspace before GC–MS analysis. This key-feature of the method made possible the collection of clean chromatograms within an elution time of only 1.8 min. Detection of EtONO2 could be performed using electron impact ionization with a standard GC–MS setup. The method was optimized and validated for the analysis of nitrate in fresh vegetables in the 10-10,000 μg/g range with a detection limit of 2 μg/g. Due to the use of primary isotope dilution quantitation, traceable results of high-precision were attained.
Keywords: nitrate; vegetable; isotope dilution; gas chromatography mass spectrometry

Rapid and convenient oxidative release of thiol-conjugated forms of microcystins for chemical analysis - Miles, Christopher O. (Chemical Research in Toxicology, 2017)
Microcystins are potent cyclic heptapeptide toxins found in some cyanobacteria, and usually contain an α,β-unsaturated carbonyl group that is readily conjugated to thiol-containing amino acids, peptides, and proteins in vivo and in vitro. Methods for deconjugating these types of adducts have recently been reported, but the reactions are slow or result in derivatized microcystins. Mercaptoethanol derivatives of a range of microcystins were therefore used as model compounds to develop deconjugation procedures in which the dialkyl sulfide linkage was oxidized to a sulfoxide or sulfone that, when treated with base, rapidly eliminated the adducted thiol as its sulfenate or sulfinate via β-elimination to afford free microcystins with the α,β-unsaturated carbonyl group intact. These free microcystins can be analyzed by LC/MS to determine the toxin profile of bound microcystins. The method was tested on Cys- and GSH-derivatives of [Dha7]MC-LR. In solution, the deconjugation reactions were complete within minutes at pH 10.7 and within a few hours at pH 9.2. Oxidation of sulfides to sulfoxides is easier and more rapid than oxidation to sulfones, allowing the use of milder oxidants and shorter reaction times. Oxidation of any methionine residues present in the microcystins occurs inevitably during these procedures, and interpretation of the microcystin profile obtained by LC/MS analysis needs to take this into account. Oxidation of tryptophan residues and degradation of microcystins by excess oxidant were circumvented by the addition of Me2SO as a sacrificial reducing agent. These methods may be useful for other compounds that undergo conjugation via thia-Michael addition, such as acrylamide and deoxynivalenol. Oxidation of sulfides to sulfoxides can occur in vivo and could affect the bioavailability of toxins and drugs conjugated via thia-Michael addition, potentially exacerbating oxidative stress by catalytically converting GSH to its sulfenate via conjugation, oxidation, and elimination to regenerate the free toxin.

Rapid 3D chemical-specific imaging of minerals using stimulated Raman scattering microscopy - Houle, Marie-Andrée; Burruss, Robert C.; Ridsdale, Andrew; Moffatt, Douglas J.; Légaré, François; Stolow, Albert (Journal of Raman Spectroscopy, 2017)
Raman microscopy, which offers chemical‐specific imaging, has important applications in geological sciences. Conventional Raman imaging, however, is challenged by long acquisition times and can be overwhelmed by sample fluorescence. Here, we present the first applications of stimulated Raman scattering (SRS) microscopy, a nonlinear optical Raman technique, to samples of mineralogical interest. Combined with second harmonic generation microscopy, SRS offers a multimodal tool for rapid imaging of mineral samples with chemical specificity, structural sensitivity, and excellent three‐dimensional resolution. Our spectral focusing implementation allows for very rapid scanning of Raman spectral lineshapes, with an adjustable spectral resolution (set here to 25 cm−1) and an overall tuning range of 400–4500 cm−1. In mineralogical applications, this wide‐tuning range offers hyperspectral imaging of both trapped organics, via the CH region (~2900 cm−1), and the lower frequency (<1000 cm−1) ‘fingerprint’ modes important for mineral identification. The simultaneously acquired second harmonic generation image reveals details of the local crystallinity of non‐centrosymmetric minerals such as quartz. As opposed to single‐spectral‐point imaging, we emphasize the importance of tuning over the Raman lineshape while imaging, to unambiguously distinguish the resonant Raman response from nonresonant background signals. Based on the range of samples studied here, we believe that multimodal SRS microscopy will become a valuable imaging tool in the earth sciences, particularly in mineralogy, petroleum, and mineral resources research.

Radial heterojunction solar cell consisting of n-type rutile nanowire arrays infiltrated by p-type CdTe - Hosseini, Arezoo; Kar, Piyush; Hsieh, Ling-Hsuan; Wiltshire, Benjamin D.; Mohammadpour, Arash; Farsinezhad, Samira; Benlamri, Mourad; Zhang, Yun; Ercelebi, C.; Shankar, Karthik (Journal of Nanoscience and Nanotechnology, 2017)
We report a p–n heterojunction solid-state solar cell comprised of p-type CdTe that was electrochemically deposited onto hydrothermally synthesized vertically oriented arrays of n-type single crystal rutile TiO2 nanowire arrays (RNWAs). The nanowires were grown on fluorine doped tin oxide (FTO)-coated transparent conductive glass substrates by hydrothermal synthesis. Morphological studies revealed the TiO2 nanowires to be completely infiltrated by the CdTe. The solid-state solar cell exhibited an open circuit voltage of 0.6 V, a short-circuit current density of 3.57 mA cm−2, a fill factor of 44% and a power conversion efficiency of 0.96%.
Keywords: electrodeposition; mobility; monocrystalline rutile tio2 nanowires; photovoltaic; solid-state solar cell; solvothermal growth

Quantitative trait loci for resistance to stripe rust of wheat revealed using global field nurseries and opportunities for stacking resistance genes - Bokore, Firdissa E.; Cuthbert, Richard D.; Knox, Ron E.; Randhawa, Harpinder S.; Hiebert, Colin W.; Depauw, Ron M.; Singh, Asheesh K.; Singh, Arti; Sharpe, Andrew G.; N’diaye, Amidou; Pozniak, Curtis J.; Mccartney, Curt; et al. (Theoretical and Applied Genetics, 2017)
Stripe rust or yellow rust, caused by Puccinia striiformis Westend. f. sp. tritici Erikss., is a devastating disease of common wheat (Triticum aestivum L.) in many regions of the world. The objectives of this research were to identify and map quantitative trait loci (QTL) associated with stripe rust resistance in adapted Canadian spring wheat cultivars that are effective globally, and investigate opportunities for stacking resistance. Doubled haploid (DH) populations from the crosses Vesper/Lillian, Vesper/Stettler, Carberry/Vesper, Stettler/Red Fife and Carberry/AC Cadillac were phenotyped for stripe rust severity and infection response in field nurseries in Canada (Lethbridge and Swift Current), New Zealand (Lincoln), Mexico (Toluca) and Kenya (Njoro), and genotyped with SNP markers. Six QTL for stripe rust resistance in the population of Vesper/Lillian, five in Vesper/Stettler, seven in Stettler/Red Fife, four in Carberry/Vesper and nine in Carberry/AC Cadillac were identified. Lillian contributed stripe rust resistance QTL on chromosomes 4B, 5A, 6B and 7D, AC Cadillac on 2A, 2B, 3B and 5B, Carberry on 1A, 1B, 4A, 4B, 7A and 7D, Stettler on 1A, 2A, 3D, 4A, 5B and 6A, Red Fife on 2D, 3B and 4B, and Vesper on 1B, 2B and 7A. QTL on 1A, 1B, 2A, 2B, 3B, 4A, 4B, 5B, 7A and 7D were observed in multiple parents. The populations are compelling sources of recombination of many stripe rust resistance QTL for stacking disease resistance. Gene pyramiding should be possible with little chance of linkage drag of detrimental genes as the source parents were mostly adapted cultivars widely grown in Canada.

Quantitative ionization chamber alignment to a water surface: theory and simulation - Siebers, Jeffrey V.; Ververs, James D.; Tessier, Frédéric (Medical Physics, 2017)
Purpose: To examine the response properties of cylindrical cavity ionization chambers (ICs) in the depth‐ionization buildup region so as to obtain a robust chamber‐signal — based method for definitive water surface identification, hence absolute ionization chamber depth localization. Method & materials: An analytical model with simplistic physics and geometry is developed to explore the theoretical aspects of ionization chamber response near a phantom water surface. Monte Carlo simulations with full physics and ionization chamber geometry are utilized to extend the model's findings to realistic ion chambers in realistic beams and to study the effects of IC design parameters on the entrance dose response. Design parameters studied include full and simplified IC designs with varying central electrode thickness, wall thickness, and outer chamber radius. Piecewise continuous fits to the depth‐ionization signal gradient are used to quantify potential deviation of the gradient discontinuity from the chamber outer radius. Exponential, power, and hyperbolic sine functional forms are used to model the gradient for chamber depths of zero to the depth of the gradient discontinuity. Results: The depth‐ionization gradient as a function of depth is maximized and discontinuous when a submerged IC's outer radius coincides with the water surface. We term this depth the gradient chamber alignment point (gCAP). The maximum deviation between the gCAP location and the chamber outer radius is 0.13 mm for a hypothetical 4 mm thick wall, 6.45 mm outer radius chamber using the power function fit, however, the chamber outer radius is within the 95% confidence interval of the gCAP determined by this fit. gCAP dependence on the chamber wall thickness is possible, but not at a clinically relevant level. Conclusions: The depth‐ionization gradient has a discontinuity and is maximized when the outer‐radius of a submerged IC coincides with the water surface. This feature can be used to auto‐align ICs to the water surface at the time of scanning and/or be applied retrospectively to scan data to quantify absolute IC depth. Utilization of the gCAP should yield accurate and reproducible depth calibration for clinical depth‐ionization measurements between setups and between users.

Quantitative ionization chamber alignment to a water surface: performance of multiple chambers - Ververs, James D.; Mcewen, Malcolm R.; Siebers, Jeffrey V. (Medical Physics, 2017)
Purpose: The purpose of this study was to experimentally examine the reliability of the gradient chamber alignment point (gCAP) determination method for accurately identifying water surface location with a range of ionization chambers (ICs). Materials and methods: Twelve cylindrical ICs were scanned from depth through a water surface into air using a customized high‐accuracy scanning system which allows for accurate alignment of the IC with respect to the true water surface. Thirteen other cylindrical ICs and five parallel‐plate ICs were scanned using a standard commercially available scanning system. The thirty different ICs used in this study represent 22 different IC models. Measurements were taken with different radiation field parameters such as incident photon beam energies and field sizes. The effects of scan direction and water surface tension were also investigated. The depth at which the gradient of the relative ionization was maximized and discontinuous, the gCAP, was found for each curve. Each measured gCAP depth was compared with the theoretically expected gCAP location, the depth at which the submerged IC outer radius (OR) coincides with the water surface. Results: When scanning an IC from in water to air, the only parameter that affects the gCAP location is the IC OR. The gCAP location corresponds with the IC central axis positioned at a depth equal to the IC OR within the 0.1 mm measurement scan resolution for all eighteen ICs studied with the commercially available system. Using the customized scanning system, all but three ICs were identified exhibiting a gCAP within the scan resolution, with the other three within 0.25 mm of the expected location. This discrepancy was not observed in the same IC model when using the conventional scanning system. Altering the beam energy from 6 to 25 MV did not alter the gCAP location, nor did variations in the radiation field size or scan parameters. In‐air IC response is proportional to the IC wall thickness. Conclusion: The water‐to‐air scanning method coupled with gCAP analysis identifies the alignment of the IC OR to the water surface within the scanning resolution for all ICs studied. The gCAP method can precisely and reproducibly align the physical center of a given cylindrical IC with the water surface, be applied prospectively or retrospectively, and provides the prospect for automated water surface identification for scanning systems. The gCAP method eliminates the visual subjectivity inherent to current IC‐to‐water surface alignment techniques, has been validated with a wide variety of commercially available ICs, and should be independent of the scanning system used for data acquisition.

QLad: a noise-free quantum memory for broadband light at room temperature - Kaczmarek, K. T.; Ledingham, P. M.; Brecht, B.; Feizpour, A.; Thekkadath, G. S.; Thomas, S. E.; Munns, J. H. D.; Saunders, D. J.; Walmsley, I. A.; Nunn, J. (Conference on Lasers and Electro-Optics, 2017)
We implement a low-noise, broadband quantum memory for light via off-resonant two-photon absorption in warm atomic vapour. We store heralded single photons and verify that the retrieved fields are anti-bunched.

Projected changes to short- and long-duration precipitation extremes over the Canadian Prairie Provinces - Masud, M. B.; Khaliq, M. N.; Wheater, H. S. (Climate Dynamics, 2017)
The effects of climate change on April–October short- and long-duration precipitation extremes over the Canadian Prairie Provinces were evaluated using a multi-Regional Climate Model (RCM) ensemble available through the North American Regional Climate Change Assessment Program. Simulations considered include those performed with six RCMs driven by the National Centre for Environmental Prediction (NCEP) reanalysis II product for the 1981–2000 period and those driven by four Atmosphere–Ocean General Circulation Models (AOGCMs) for the current 1971–2000 and future 2041–2070 periods (i.e. a total of 11 current-to-future period simulation pairs). A regional frequency analysis approach was used to develop 2-, 5-, 10-, 25-, and 50-year return values of precipitation extremes from NCEP and AOGCM-driven current and future period simulations that respectively were used to study the performance of RCMs and projected changes for selected return values at regional, grid-cell and local scales. Performance errors due to internal dynamics and physics of RCMs studied for the 1981–2000 period reveal considerable variation in the performance of the RCMs. However, the performance errors were found to be much smaller for RCM ensemble averages than for individual RCMs. Projected changes in future climate to selected regional return values of short-duration (e.g. 15- and 30-min) precipitation extremes and for longer return periods (e.g. 50-year) were found to be mostly larger than those to the longer duration (e.g. 24- and 48-h) extremes and short return periods (e.g. 2-year). Overall, projected changes in precipitation extremes were larger for southeastern regions followed by southern and northern regions and smaller for southwestern and western regions of the study area. The changes to return values were also found to be statistically significant for the majority of the RCM–AOGCM simulation pairs. These projections might be useful as a key input for the future planning of urban drainage infrastructure and development of strategic climate change adaptation measures.
Keywords: climate change; precipitation extremes; regional frequency analysis; NARCCAP; Canadian Prairie Provinces

Producing and controlling half-cycle near-infrared electric-field transients - Hammond, T. J.; Villeneuve, D. M.; Corkum, P. B. (Optica, 2017)
In a few-cycle laser pulse, the peak field strength depends on the carrier envelope phase. Concurrently, coherent control requires the measurement and manipulation of the spectral phase of a light pulse to influence a dynamical process that has multiple interfering pathways. Here, we exploit the interference of second harmonic generation and self-phase modulation in an 80 μm thick quartz plate due to a two-cycle pulse centered at 1.8 μm with peak intensity 3×10^13   W/cm^2 to generate half-cycle electric field transients. In a monolithic step, we transform a measurement of the carrier envelope phase to the control over the pulse evolution with subcycle temporal accuracy. The high-intensity subcycle transient is scalable in pulse energy and will be useful for strong field physics and attosecond science: the ultrashort infrared pulse can generate isolated attosecond pulses from low bandgap semiconductor materials, and will be able to optically control currents on a subfemtosecond timescale.

Preservation of carbon dioxide clathrate hydrate in the presence of fructose or glucose and absence of sugars under freezer conditions - Nagashima, Hironori D.; Alavi, Saman; Ohmura, Ryo (Journal of Industrial and Engineering Chemistry, 2017)
To investigate the preservation of CO2 clathrate hydrate in the presence of fructose or glucose and absence of sugars, CO2 hydrate samples were preserved at 238.2 K, 253.2 K and 258.2 K under atmospheric pressure for three weeks. The preservations of CO2 hydrate with those two monosaccharide sugars at both 238.2 K and 253.2 K were lower than that of the pure CO2 hydrate without the sugars. The results indicated that the viscosity of super-cooled or stable sugar aqueous solution and occurrence of super-cooled water in the sample hydrate particles are significant factors in the preservation of CO2 hydrate.
Keywords: carbon dioxide hydrate; frozen desserts; solid carbonated food; clathrate hydrate; clathrate hydrate preservation

Preparative separation of monoclonal antibody aggregates by cation-exchange laterally-fed membrane chromatography - Madadkar, Pedram; Sadavarte, Rahul; Butler, Michael; Durocher, Yves; Ghosh, Raja (Journal of Chromatography B, 2017)
Cation exchange (CEX) chromatography is widely used for large-scale separation of monoclonal antibody (mAb) aggregates. The aggregates bind more strongly to CEX media and hence elute after the monomeric mAb in a salt gradient. However, monomer-aggregate resolution that is typically obtained is poor, which results in low product recovery. In the current study we address this challenge through the use of cation-exchange laterally-fed membrane chromatography (LFMC). Three different LFMC devices, each containing a bed of strong cation-exchange (S) membranes were used for preparative-scale removal of mAb aggregates. Trastuzumab (IgG1) biosimilar derived from human embryonic kidney 293 (293) cells was used as the primary model mAb in our study. The other mAbs investigated were Chinese hamster ovary (CHO) cell line derived Alemtuzumab (Campath-1H) and a heavy chain chimeric mAb EG2-hFc. In each of these case-studies, aggregates were well-resolved from the respective monomer. The separated and collected monomer and aggregate fractions were analyzed using techniques such as hydrophobic interaction membrane chromatography (HIMC), native polyacrylamide gel electrophoresis (or PAGE), and size-exclusion high-performance liquid chromatography (SE-HPLC). The high efficiency of separation obtained in each case was due to a combination of the small membrane pore size (3–5 μm), and the use of LFMC technology, which has been shown to be suitable for high-resolution, multi-component protein separations. Also, the LFMC based separation processes reported in this study were more than an order of magnitude faster than equivalent resin-based, cation exchange chromatography.
Keywords: monoclonal antibody; aggregates; membrane chromatography; device; protein purification; bioseparation

Preferential alignment of incommensurate block copolymer dot arrays forming moiré superstructures - Jin, Cong; Olsen, Brian C.; Luber, Erik J.; Buriak, Jillian M. (ACS Nano, 2017)
Block copolymer (BCP) self-assembly is of great interest as a cost-effective method for large-scale, high-resolution nanopattern fabrication. Directed self-assembly can induce long-range order and registration, reduce defect density, and enable access to patterns of higher complexity. Here we demonstrate preferential orientation of two incommensurate BCP dot arrays. A bottom layer of hexagonal silica dots is prepared via typical self-assembly from a PS-b-PDMS block copolymer. Self-assembly of a second, or top, layer of a different PS-b-PDMS block copolymer that forms a hexagonal dot pattern with different periodicity results in a predictable moiré superstructure. Four distinct moiré superstructures were demonstrated through a combination of different BCPs and different order of annealing. The registration force of the bottom layer of hexagonal dots is sufficient to direct the self-assembly of the top layer to adopt a preferred relative angle of rotation. Large-area helium ion microscopy imaging enabled quantification of the distributions of relative rotations between the two lattices in the moiré superstructures, yielding statistically meaningful results for each combination. It was also found that if the bottom layer dots were too large, the resulting moiré pattern was lost. A small reduction in the bottom layer dot size, however, resulted in large-area moiré superstructures, suggesting a specific size regime where interlayer registration forces can induce long-range preferential alignment of incommensurate BCP dot arrays.
Keywords: block copolymer; heteroepitaxy; incommensurate; moiré superstructure; nanopattern; self-assembly; sequential deposition

Poly(acrylic acid)-coated titanium dioxide nanoparticle and ultraviolet light co-exposure has minimal effect on developing zebrafish (Danio rerio) - Felix, Lindsey C.; Folkerts, Erik J.; He, Yuhe; Goss, Greg G. (Environmental Science: Nano, 2017)
Widespread production of titanium dioxide nanoparticles (TiO2 NPs) for use in various consumer products has increased the potential for their release into the environment. Most studies examine TiO2 NP toxicity under laboratory lighting that emits little to no ultraviolet (UV) radiation, yet these nanoscale particles are wide band-gap semiconductors capable of generating reactive oxygen species. The purpose of this study was to examine poly(acrylic acid)-coated TiO2 NP phototoxicity in vivo. Zebrafish (Danio rerio) embryos were exposed to 0.1, 1 or 10 mg L−1 of characterized uncoated TiO2 NPs (positive control), polymer-coated TiO2 NPs, and the polymer coating alone (negative control) in the presence or absence of UV light. Survival, hatching success, malformation, thiobarbituric acid reactive substances (TBARS), catalase activity, total glutathione (TG) level, superoxide dismutase activity, and alteration in antioxidant-related gene expression were measured. Uncoated TiO2 NPs produced hydroxyl radicals (OH˙), delayed hatch, induced lipid peroxidation, increased catalase activity and TG levels, and upregulated glutathione peroxidase 1a gene expression 1.59 fold in the presence of UV light. Polymer-coated TiO2 NP increased both TBARS production and TG levels under simulated sunlight illumination. We suggest that the polymer coating plays a role in OH˙-mediated effects of TiO2 NPs in developing zebrafish and that toxicity depends on UV illumination. Since the presence of UV light evidently affects TiO2 NP toxicity, the need for more environmentally representative nanotoxicity studies that take sunlight activation into account is strengthened.

Polarization gradient study of interstellar medium turbulence using the Canadian Galactic Plane Survey - Herron, C. A.; Geisbuesch, J.; Landecker, T. L.; Kothes, R.; Gaensler, B. M.; Lewis, G. F.; Mcclure-Griffiths, N. M.; Petroff, E. (The Astrophysical Journal, 2017)
We have investigated the magneto-ionic turbulence in the interstellar medium through spatial gradients of the complex radio polarization vector in the Canadian Galactic Plane Survey (CGPS). The CGPS data cover 1300 square degrees, over the range 53o <= l <= 192o, -3o <= b <= 5o, with an extension to b=17o.5 in the range 101o <= l <= 116o, and arcminute resolution at 1420 MHz. Previous studies found a correlation between the skewness and kurtosis of the polarization gradient and the Mach number of the turbulence, or assumed this correlation to deduce the Mach number of an observed turbulent region. We present polarization gradient images of the entire CGPS data set, and analyze the dependence of these images on angular resolution. The polarization gradients are filamentary, and the length of these filaments is largest toward the Galactic anti-center, with the smallest toward the inner Galaxy. This may imply that small-scale turbulence is stronger in the inner Galaxy, or that we observe more distant features at low Galactic longitudes. For every resolution studied, the skewness of the polarization gradient is influenced by the edges of bright polarization gradient regions, which are not related to the turbulence revealed by the polarization gradients. We also find that the skewness of the polarization gradient is sensitive to the size of the box used to calculate the skewness, but insensitive to Galactic longitude, implying that the skewness only probes the number and magnitude of the inhomogeneities within the box. We conclude that the skewness and kurtosis of the polarization gradient are not ideal statistics for probing natural magneto-ionic turbulence.

Plasmon-enhanced high-harmonic generation from silicon - Vampa, G.; Ghamsari, B. G.; Siadat Mousavi, S.; Hammond, T. J.; Olivieri, A.; Lisicka-Skrek, E.; Naumov, A. Yu; Villeneuve, D. M.; Staudte, A.; Berini, P.; Corkum, P. B. (Nature Physics, 2017)
Plasmonic antennas can enhance the intensity of a nanojoule laser pulse by localizing the electric field in their proximity. It has been proposed that the field can become strong enough to convert the fundamental laser frequency into high-order harmonics through an extremely nonlinear interaction with gas atoms that occupy the nanoscopic volume surrounding the antennas. However, the small number of gas atoms that can occupy this volume limits the generation of high harmonics. Here we use an array of monopole nano-antennas to demonstrate plasmon-assisted high-harmonic generation directly from the supporting crystalline silicon substrate. The high density of the substrate compared with a gas allows macroscopic buildup of harmonic emission. Despite the sparse coverage of antennas on the surface, harmonic emission is ten times brighter than without antennas. Imaging the high-harmonic radiation will allow nanometre and attosecond measurement of the plasmonic field8 thereby enabling more sensitive plasmon sensors while opening a new path to extreme-ultraviolet-frequency combs.

Photon-momentum transfer in photoionization: from few photons to many - Chelkowski, Szczepan; Bandrauk, André D.; Corkum, Paul B. (Physical Review A, 2017)
In most models and theoretical calculations describing multiphoton ionization by infrared light, the dipole approximation is used. This is equivalent to setting the very small photon momentum to zero. Using numerical solutions of the (nondipole) three-dimensional time-dependent Schrödinger equation for one-electron (H-like) systems, we investigate the effect the photon-momentum transfer to the photoelectron in various regimes: from the few (one, two, three, eight) absorbed photons to multiphoton and tunneling regimes. We find that in all regimes the average electron momentum acquired from absorbed photons is a linear function of the average energy of the photoelectron, but the slope is different in the few-photon and multiphoton regimes. In the multiphoton regime, the photon-momentum signature in the photoelectron-momentum distributions (along the photon momentum) depends on the ellipticity of the laser polarization, with linear laser polarization spectra different from circular polarization spectra. For a given laser intensity the average electron-momentum gain from an absorbed photon is over two and a half times smaller for linear polarization than for circular polarization. However, for both polarizations, the average electron-momentum gain is nearly equal to the average electron energy divided by the speed of light.

Phase retrieval approach for an accurate reconstruction of an arbitrary optical waveform in the petahertz optical oscilloscope - Kim, Kyung Taec; Kim, Kyungseung; Hammond, T j (Journal of Physics B: Atomic, Molecular and Optical Physics, 2017)
An arbitrary optical waveform can be measured using the technique called the 'petahertz optical oscilloscope' in which an electron trajectory in the process of high harmonic generation is used as a fast temporal gate. In the petahertz optical oscilloscope, a signal laser pulse that needs to be measured is superposed on a fundamental laser pulse that generates high harmonic radiation. The addition of the signal laser pulse slightly modifies the amplitude and phase of the harmonic radiation, which have information on the signal field. While these changes are imposed in the generation medium, the harmonic radiation is measured at the detector. Thus, one needs a special technique to find the phase modulation in the medium using the variation of the spatially-resolved harmonic spectrum measured at the far field. We find that a simple estimation using the deflection angle of the harmonic radiation is not accurate enough for a broadband signal pulse. Here we introduce a phase retrieval approach for the reconstruction of the broadband signal pulse. Our calculations show that the broadband signal pulse can be accurately reconstructed using the phase retrieval approach.

Perturbative high harmonic wave front control - Li, Zhengyan; Brown, Graham; Ko, Dong Hyuk; Kong, Fanqi; Arissian, Ladan; Corkum, P. B. (Physical Review Letters, 2017)
We pattern the wave front of a high harmonic beam by intersecting the intense driving laser pulse that generates the high harmonic with a weak control pulse. To illustrate the potential of wave-front control, we imprint a Fresnel zone plate pattern on a harmonic beam, causing the harmonics to focus and defocus. The quality of the focus that we achieve is measured using the spectral wave-front optical reconstruction by diffraction method. We will show that it is possible to enhance the peak intensity by orders of magnitude without a physical optical element in the path of the extreme ultraviolet (XUV) beam. Through perturbative wave-front control, XUV beams can be created with a flexibility approaching what technology allows for visible and infrared light.

Perspectives on the specific targeting of Fusarium graminearum for the development of alternative head blight treatment approaches - Cuperlovic-Culf, M.; Loewen, M.; Rajagopalan, N.; Surendra, A. (Plant Pathology, 2017)
Diseases of agricultural crops caused by fungi have devastating economic and health effects. Fusarium head blight (FHB) is one of the most damaging diseases of wheat and other small grain cereals. FHB reduces agricultural yield while also affecting food supply and safety through deposition of toxins (mycotoxins/phytotoxins). Control of FHB growth and toxin accumulation in grains remain major challenges. While the ultimate goal in the battle against FHB is the development of resistant wheat varieties, the actual use of fully resistant plants that preclude any need for treatment with fungicides remains out of sight. Current antifungals being applied against FHB are generally azole‐based inhibitors. However, usage of these azole‐based fungicides is being complicated by the facts that these are active only during specific short‐lived developmental time periods, fungi are developing increased resistance to them and they are having significant environmental impacts. As such, there is a great need for more targeted, specific and effective antifungal agents to address the significant threat of FHB. This review provides an overview of some of the more promising fungal targets that are currently being investigated for antifungal development.

Peptides for targeting βB2-crystallin fibrils - Ghaffari Sharaf, Mehdi; Cetinel, Sibel; Semenchenko, Valentyna; Damji, Karim F.; Unsworth, Larry D.; Montemagno, Carlo (Experimental Eye Research, 2017)
Crystallins are a major family of proteins located within the lens of the eye. Cataracts are thought to be due to the formation of insoluble fibrillar aggregates, which are largely composed of proteins from the crystallin family. Today the only cataract treatment that exists is surgery and this can be difficult to access for individuals in the developing world. Development of novel pharmacotherapeutic approaches for the treatment of cataract rests on the specific targeting of these structures. βB2-crystallin, a member of β-crystallin family, is a large component of the crystallin proteins within the lens, and as such was used to form model fibrils in vitro. Peptides were identified, using phage display techniques, that bound to these fibrils with high affinity. Fibrillation of recombinantly expressed human βB2-crystallin was performed in 10% (v/v) trifluoroethanol (TFE) solution (pH 2.0) at various temperatures, and its amyloid-like structure was confirmed using Thioflavin-T (ThT) assay, transmission electron microscopy (TEM), and X-ray fiber diffraction (XRFD) analysis. Affinity of identified phage-displayed peptides were analyzed using enzyme-linked immunosorbent assay (ELISA). Specific binding of a cyclic peptide (CKQFKDTTC) showed the highest affinity, which was confirmed using a competitive inhibition assay.
Keywords: Phage display; βB2-crystallin; amyloid-like fibril; fibrillar aggregate; cataract; targeting peptide

Peptide-mediated mast cell activation: ligand similarities for receptor recognition and protease-induced regulation - Lu, Lei; Kulka, Marianna; Unsworth, Larry D. (Journal of Leukocyte Biology, 2017)
MCs are crucial regulators of the innate immune response. MC degranulation is a rapid response mechanism that allows for the release of a stored plethora of inflammatory mediators, including histamine, heparin, various serine proteases, chemokines, and cytokines. The activation of MCs can lead to the de novo expression of a variety of chemokines and cytokines that can influence a variety of outcomes: inflammation, angiogenesis, and others. A variety of IgE‐independent mediators, including IgG, cytokines, chemokines, exogenous molecules, drugs, and cationic peptides, and others, can directly trigger MC activation. For decades, various peptide stimuli, including peptide toxins, neuropeptides, antimicrobial peptides, and endogenous bioactive peptides, have been associated with MC allergic reactions in various physiologic and pathologic conditions. Recently, an activation mechanism has been established, whereby the MRGPRX2 receptor is involved in most of the peptide stimuli‐related activation of human MCs. Interestingly, most of these peptide sequences seem to have a strong structural similarity that includes abundant positive charges and aromatic/aliphatic amino acids. In this review, we discuss the structures of known peptide stimuli and the receptors with which they interact for the express purpose of highlighting peptide elements as building blocks for tissue engineering applications.

Peptide-functionalized iron oxide magnetic nanoparticle for gold mining - Shen, Wei-Zheng; Cetinel, Sibel; Sharma, Kumakshi; Borujeny, Elham Rafie; Montemagno, Carlo (Journal of Nanoparticle Research, 2017)
Here, we present our work on preparing a novel nanomaterial composed of inorganic binding peptides and magnetic nanoparticles for inorganic mining. Two previously selected and well-characterized gold-binding peptides from cell surface display, AuBP1 and AuBP2, were exploited. This nanomaterial (AuBP-MNP) was designed to fulfill the following two significant functions: the surface conjugated gold-binding peptide will recognize and selectively bind to gold, while the magnetic nano-sized core will respond and migrate according to the applied external magnetic field. This will allow the smart nanomaterial to mine an individual material (gold) from a pool of mixture, without excessive solvent extraction, filtration, and concentration steps. The working efficiency of AuBP-MNP was determined by showing a dramatic reduction of gold nanoparticle colloid concentration, monitored by spectroscopy. The binding kinetics of AuBP-MNP onto the gold surface was determined using surface plasmon resonance (SPR) spectroscopy, which exhibits around 100 times higher binding kinetics than peptides alone. The binding capacity of AuBP-MNP was demonstrated by a bench-top mining test with gold microparticles.
Keywords: gold-binding peptide; magnetic nanoparticles; surface functionalization; gold mining; nanobiotechnology

Overexpression of Brassica napus myrosinase-associated protein 1 improved Sclerotinia sclerotiorum tolerance in Arabidopsis thaliana - Wu, Limin; Yu, Min; Holowachuk, Jennifer; Sharpe, Andrew; Lydiate, Derek; Hegedus, Dwayne; Gruber, Margaret (Canadian Journal of Plant Science = Revue canadienne de phytotechnie, 2017)
Canola (Brassica napus L.) productivity is severely affected by various biotic and abiotic stresses such as insects, pathogens, drought, and cold. Characterization of genes with specific effects on particular stress responses is one of the long-term goals for B. napus genetic improvement. Here we explored the roles of Brassica napus myrosinase-associated protein 1 (BnMyAP1), which was highly represented (expressed) in a B. napus subtractive library developed after leaf damage by the crucifer flea beetle [Phyllotreta cruciferae (Goeze)]. Expression of BnMyAP1 was under different developmental control in B. napus, but it was co-induced in B. napus by flea beetle feeding, Sclerotinia sclerotiorum (Lib.) de Bary infection, drought, and cold. A total of 20 BnMyAPs were represented in different B. napus stress and development expressed sequence tag libraries and indicated larger, more diversified families than were previously known. Overexpression of BnMyAP1 in Arabidopsis thaliana (L.) Heynh. resulted in an increased survival ratio (63%–90%) compared with that of the controls (15%–20%) after S. sclerotiorum infection, which suggests that BnMyAP1 could be used to protect B. napus oilseed and vegetables from the S. sclerotiorum disease.
Keywords: BnMyAP; Brassica napus L.; flea beetle; Sclerotinia sclerotiorum

OSSOS. VI. Striking biases in the detection of large semimajor axis trans-Neptunian objects - Shankman, Cory; Kavelaars, J. J.; Bannister, Michele T.; Gladman, Brett J.; Lawler, Samantha M.; Chen, Ying-Tung; Jakubik, Marian; Kaib, Nathan; Alexandersen, Mike; Gwyn, Stephen D. J.; Petit, Jean-Marc; Volk, Kathryn (The Astronomical Journal, 2017)
The accumulating but small set of large semimajor axis trans-Neptunian objects (TNOs) shows an apparent clustering in the orientations of their orbits. This clustering must either be representative of the intrinsic distribution of these TNOs, or else have arisen as a result of observation biases and/or statistically expected variations for such a small set of detected objects. The clustered TNOs were detected across different and independent surveys, which has led to claims that the detections are therefore free of observational bias. This apparent clustering has led to the so-called "Planet 9" hypothesis that a super-Earth currently resides in the distant solar system and causes this clustering. The Outer Solar System Origins Survey (OSSOS) is a large program that ran on the Canada–France–Hawaii Telescope from 2013 to 2017, discovering more than 800 new TNOs. One of the primary design goals of OSSOS was the careful determination of observational biases that would manifest within the detected sample. We demonstrate the striking and non-intuitive biases that exist for the detection of TNOs with large semimajor axes. The eight large semimajor axis OSSOS detections are an independent data set, of comparable size to the conglomerate samples used in previous studies. We conclude that the orbital distribution of the OSSOS sample is consistent with being detected from a uniform underlying angular distribution.

Origin of warm and hot gas emission from low-mass protostars: Herschel-HIFI observations of CO J = 16–15 - Kristensen, L. E.; Van Dishoeck, E. F.; Mottram, J. C.; Karska, A.; Yıldız, U. A.; Bergin, E. A.; Bjerkeli, P.; Cabrit, S.; Doty, S.; Evans, N. J.; Gusdorf, A.; Harsono, D.; et al. (Astronomy & Astrophysics, 2017)
Context. Through spectrally unresolved observations of high-J CO transitions, Herschel Photodetector Array Camera and Spectrometer (PACS) has revealed large reservoirs of warm (300 K) and hot (700 K) molecular gas around low-mass protostars. The excitation and physical origin of this gas is still not understood. Aims. We aim to shed light on the excitation and origin of the CO ladder observed toward protostars, and on the water abundance in different physical components within protostellar systems using spectrally resolved Herschel-HIFI data. Methods. Observations are presented of the highly excited CO line J = 16–15 (Eup/kB = 750 K) with the Herschel Heterodyne Instrument for the Far Infrared (HIFI) toward a sample of 24 low-mass protostellar objects. The sources were selected from the Herschel “Water in Star-forming regions with Herschel” (WISH) and “Dust, Ice, and Gas in Time” (DIGIT) key programs. Results. The spectrally resolved line profiles typically show two distinct velocity components: a broad Gaussian component with an average FWHM of 20 km s-1 containing the bulk of the flux, and a narrower Gaussian component with a FWHM of 5 km s-1 that is often offset from the source velocity. Some sources show other velocity components such as extremely-high-velocity features or “bullets”. All these velocity components were first detected in H2O line profiles. The average rotational temperature over the entire profile, as measured from comparison between CO J = 16–15 and 10–9 emission, is ~300 K. A radiative-transfer analysis shows that the average H2O/CO column-density ratio is ~0.02, suggesting a total H2O abundance of ~2 × 10-6, independent of velocity. Conclusions. Two distinct velocity profiles observed in the HIFI line profiles suggest that the high-J CO ladder observed with PACS consists of two excitation components. The warm PACS component (300 K) is associated with the broad HIFI component, and the hot PACS component (700 K) is associated with the offset HIFI component. The former originates in either outflow cavity shocks or the disk wind, and the latter in irradiated shocks. The low water abundance can be explained by photodissociation. The ubiquity of the warm and hot CO components suggest that fundamental mechanisms govern the excitation of these components; we hypothesize that the warm component arises when H2 stops being the dominant coolant. In this scenario, the hot component arises in cooling molecular H2-poor gas just prior to the onset of H2 formation. High spectral resolution observations of highly excited CO transitions uniquely shed light on the origin of warm and hot gas in low-mass protostellar objects.
Keywords: astrochemistry; ISM: jets and outflows; line: profiles; stars: formation; stars: jets; stars: winds, outflows

Orbits for the impatient: a bayesian rejection-sampling method for quickly fitting the orbits of long-period exoplanets - Blunt, Sarah; Nielsen, Eric L.; De Rosa, Robert J.; Konopacky, Quinn M.; Ryan, Dominic; Wang, Jason J.; Pueyo, Laurent; Rameau, Julien; Marois, Christian; Marchis, Franck; Macintosh, Bruce; Graham, James R.; et al. (The Astronomical Journal, 2017)
We describe a Bayesian rejection-sampling algorithm designed to efficiently compute posterior distributions of orbital elements for data covering short fractions of long-period exoplanet orbits. Our implementation of this method, Orbits for the Impatient (OFTI), converges up to several orders of magnitude faster than two implementations of Markov Chain Monte Carlo (MCMC) in this regime. We illustrate the efficiency of our approach by showing that OFTI calculates accurate posteriors for all existing astrometry of the exoplanet 51 Eri b up to 100 times faster than a Metropolis–Hastings MCMC. We demonstrate the accuracy of OFTI by comparing our results for several orbiting systems with those of various MCMC implementations, finding the output posteriors to be identical within shot noise. We also describe how our algorithm was used to successfully predict the location of 51 Eri b six months in the future based on less than three months of astrometry. Finally, we apply OFTI to 10 long-period exoplanets and brown dwarfs, all but one of which have been monitored over less than 3% of their orbits, producing fits to their orbits from astrometric records in the literature.

Optomechanically induced transparency in diamond microdisks - Lake, David P.; Mitchell, Matthew; Hadden, J. P.; Barclay, Paul E. (Conference on Lasers and Electro-Optics, 2017)
Optomechanically induced transparency in a single–crystal diamond microdisk supporting a 2.4 GHz mechanical mode is demonstrated. A cooperativity of C ~ 1.2 for N ~ 2 × 106 intracavity photons is reached, sufficient for coherent photon–phonon coupling.

Optimisation of excitation schemes for 14N overtone MAS NMR using numerically exact simulations - Brinkmann, Andreas; O’dell, Luke A. (Solid State Nuclear Magnetic Resonance, 2017)
Numerically exact simulations of the 14N overtone (14NOT) MAS NMR experiment are used to investigate the effects of the applied magnetic field strength as well as three types of excitation pulse. The results show that both the resolution and sensitivity of 14NOT MAS NMR increase linearly with the applied static magnetic field strength. Standard RF excitation pulses are compared with frequency-swept WURST pulses as well as several composite pulses. WURST pulses are demonstrated to provide the largest bandwidths, while the direction of the frequency sweep is shown to be important when these pulses are used for the direct observation of 14NOT signals. A composite pulse is shown to provide the most efficient excitation overall, but only when applied on resonance. WURST excitation pulses are therefore the best option when studying a sample with unknown 14N NMR parameters.
Keywords: 14N solid-state NMR; overtone spectroscopy; excitation pulses; WURST pulses; composite pulses

Optimal replacement times for machining tool during turning titanium metal matrix composites under variable machining conditions - Shaban, Yasser; Aramesh, Maryam; Yacout, Soumaya; Balazinski, Marek; Attia, Helmi; Kishawy, Hossam (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2017)
Little practical results are known about the cutting tool optimal replacement time, specifically for machining of composite materials. Due to the fact that tool failure represents about 20% of machine down-time, and due to the high cost of machining, in particular when the work piece’s material is very expensive, optimization of tool replacement time is thus fundamental. Finding the optimal replacement time has also positive impact on product quality in terms of dimensions and surface finish. In this article, two new contributions to research on tool replacement are introduced. First, tool replacement mathematical models are proposed. These models are used in order to find the optimal time to tool replacement when the tool is used under variable machining conditions, namely, the cutting speed and the feed rate. Proportional hazards models are used to find an optimal replacement function. Second, this model is obtained during turning titanium metal matrix composites. These composites are a new generation of materials which have proven to be viable in various industrial fields such as biomedical and aerospace, and they are very expensive. Experimental data are obtained and used in order to develop and to validate the proportional hazards models, which are then used to find the optimal replacement conditions.
Keywords: optimal tool replacement; metal matrix composites; cost optimization; availability optimization

Optical limiting in Cu/CuO nanostructures formed by magnetic field-assisted anodization - Mohammadpour, Arash; Eltahlawy, Mohammed; Martino, Albert; Askar, Abdelrahman M.; Kisslinger, Ryan; Fedosejevs, Robert; Shankar, Karthik (Journal of Nanoscience and Nanotechnology, 2017)
The recently developed magnetic field-assisted electroless anodization technique enables more morphological tunability by expanding the parameter space available during nanostructure synthesis and limiting the effects of copper electromigration. We synthesized CuO nanodendrites, nanowalls and nanospheres on both transparent and non-transparent substrates using the magnetic field-assisted anodization of copper foils and vacuum deposited Cu thin films on glass substrates respectively. Non-linear optical characterization of the resulting partially transparent Cu/CuO nanostructures on glass substrates revealed clear optical limiting behavior. When the fluence of the incident 800 nm radiation from a Ti:sapphire laser was increased from 20 mJ cm−2 to 2 J cm−2, the optical transmittance of the Cu/CuO nanostructures decreased by nearly an order of magnitude.
Keywords: anodic nanostructure synthesis; cupric oxide; cuprous oxide; magnetoelectrochemical cell; metal oxide; reverse saturable absorption

Optical gain in rotationally excited nitrogen molecular ions - Azarm, Ali; Corkum, Paul; Polynkin, Pavel (Physical Review A, 2017)
We pump low-pressure nitrogen gas with ionizing femtosecond laser pulses at 1.5 μm wavelength. The resulting rotationally excited N+2 molecular ions generate directional, forward-propagating stimulated and isotropic spontaneous emissions at 428 nm wavelength. Through high-resolution spectroscopy of these emissions, we quantify rotational population distributions in the upper and lower emission levels. We show that these distributions are shifted with respect to each other, which has a strong influence on the transient optical gain in this system. Although we find that electronic population inversion exists in our particular experiment, we show that sufficient dissimilarity of rotational distributions in the upper and lower emission levels could, in principle, lead to gain without net electronic population inversion.

Optical anisotropy in vertically oriented TiO2 nanotube arrays - Zhang, Yun; Farsinezhad, Samira; D Wiltshire, Benjamin; Kisslinger, Ryan; Kar, Piyush; Shankar, Karthik (Nanotechnology, 2017)
Nanofabricated optically anisotropic uniaxial thin films with deep submicron feature sizes are emerging as potential platforms for low-loss all-dielectric metamaterials, and for Dyakonov surface wave-based subwavelength optical confinement and guiding at interfaces with isotropic media. In this context, we investigate the optical properties of one such uniaxial platform, namely self-organized titania nanotube arrays (TNTAs) grown by the bottom-up nanofabrication process of electrochemical anodization on silicon wafer substrates, and subsequently annealed at different temperatures, i.e. 500 °C and 750 °C. We performed detailed quantitative analysis of the structure of the TNTAs using x-ray diffraction and Raman spectroscopy, which revealed a measurable phonon confinement in TNTAs annealed at 500 °C. Variable angle spectroscopic ellipsometry was used to investigate the optical anisotropy in two kinds of TNTAs—those constituted by anatase-phase and those containing a mixture of anatase and rutile phases. Both kinds of TNTAs were found to have positive birefringence (Δn) exceeding 0.06 in the spectral region of interest while mixed phase TNTAs exhibited Δn as high as 0.15. The experimentally measured anisotropy in the refractive index of the TNTAs was compared with the predictions of two different effective medium approximations incorporating the uniaxial geometry. The measured value of Δn for TNTAs exceeded that of bulk anatase single crystals, indicating the potential of nanostructured dielectrics to outperform dielectric crystals of the same material with respect to the magnitude of the achievable directional refractive index contrast.
Keywords: nanophotonics; nanostructured dielectrics; sculptured thin films; specular reflectance; nanorod arrays; nanohole arrays; photonic crystal

On-line estimation of local oscillator noise and optimisation of servo parameters in atomic clocks - Leroux, Ian D.; Scharnhorst, Nils; Hannig, Stephan; Kramer, Johannes; Pelzer, Lennart; Stepanova, Mariia; Schmidt, Piet O. (Metrologia, 2017)
For atomic frequency standards in which fluctuations of the local oscillator (LO) frequency are the dominant noise source, we examine the role of the the servo algorithm that predicts and corrects these frequency fluctuations. We derive the optimal linear prediction algorithm, showing how to measure the relevant spectral properties of the noise and optimise servo parameters while the standard is running, using only the atomic error signal. We find that, for realistic LO noise spectra, a conventional integrating servo with a properly chosen gain performs nearly as well as the optimal linear predictor. Using simple analytical models and numerical simulations, we establish optimum probe times as a function of clock atom number and of the dominant noise type in the local oscillator. We calculate the resulting LO-dependent scaling of achievable clock stability with atom number for product states as well as for maximally-correlated states.
Keywords: quantum projection noise; atomic frequency standards; local oscillator noise; servo optimisation

One-dimensional electron transport layers for perovskite solar cells - Thakur, Ujwal; Kisslinger, Ryan; Shankar, Karthik (Nanomaterials, 2017)
The electron diffusion length (Ln) is smaller than the hole diffusion length (Lp) in many halide perovskite semiconductors meaning that the use of ordered one-dimensional (1D) structures such as nanowires (NWs) and nanotubes (NTs) as electron transport layers (ETLs) is a promising method of achieving high performance halide perovskite solar cells (HPSCs). ETLs consisting of oriented and aligned NWs and NTs offer the potential not merely for improved directional charge transport but also for the enhanced absorption of incoming light and thermodynamically efficient management of photogenerated carrier populations. The ordered architecture of NW/NT arrays affords superior infiltration of a deposited material making them ideal for use in HPSCs. Photoconversion efficiencies (PCEs) as high as 18% have been demonstrated for HPSCs using 1D ETLs. Despite the advantages of 1D ETLs, there are still challenges that need to be overcome to achieve even higher PCEs, such as better methods to eliminate or passivate surface traps, improved understanding of the hetero-interface and optimization of the morphology (i.e., length, diameter, and spacing of NWs/NTs). This review introduces the general considerations of ETLs for HPSCs, deposition techniques used, and the current research and challenges in the field of 1D ETLs for perovskite solar cells.
Keywords: photovoltaics; ordered bulk heterojunctions; solution processing; light scattering; surface traps; electrochemical anodization; solvothermal synthesis; metal oxide; TiO2; ZnO

On-chip single photon filtering and multiplexing in hybrid quantum photonic circuits - Elshaari, Ali W.; Zadeh, Iman Esmaeil; Fognini, Andreas; Reimer, Michael E.; Dalacu, Dan; Poole, Philip J.; Zwiller, Val; Jöns, Klaus D. (Nature Communications, 2017)
Quantum light plays a pivotal role in modern science and future photonic applications. Since the advent of integrated quantum nanophotonics different material platforms based on III–V nanostructures-, colour centers-, and nonlinear waveguides as on-chip light sources have been investigated. Each platform has unique advantages and limitations; however, all implementations face major challenges with filtering of individual quantum states, scalable integration, deterministic multiplexing of selected quantum emitters, and on-chip excitation suppression. Here we overcome all of these challenges with a hybrid and scalable approach, where single III–V quantum emitters are positioned and deterministically integrated in a complementary metal–oxide–semiconductor-compatible photonic circuit. We demonstrate reconfigurable on-chip single-photon filtering and wavelength division multiplexing with a foot print one million times smaller than similar table-top approaches, while offering excitation suppression of more than 95 dB and efficient routing of single photons over a bandwidth of 40 nm. Our work marks an important step to harvest quantum optical technologies’ full potential.

On the role of ice-nucleating aerosol in the formation of ice particles in tropical mesoscale convective systems - Ladino, Luis A.; Korolev, Alexei; Heckman, Ivan; Wolde, Mengistu; Fridlind, Ann M.; Ackerman, Andrew S. (Geophysical Research Letters, 2017)
Over the decades, the cloud physics community has debated the nature and role of aerosol particles in ice initiation. The present study shows that the measured concentration of ice crystals in tropical mesoscale convective systems exceeds the concentration of ice nucleating particles (INPs) by several orders of magnitude. The concentration of INPs was assessed from the measured aerosol particle concentration in the size range of 0.5 to 1 μm. The observations from this study suggest that primary ice crystals formed on INPs make only a minor contribution to the total concentration of ice crystals in tropical mesoscale convective systems. This is found by comparing the predicted INP number concentrations with in situ ice particle number concentrations. The obtained measurements suggest that ice multiplication is the likely explanation for the observed high concentrations of ice crystals in this type of convective system.

On the many ‘3-kiloparsec arms’—shocked wave and nuclear rotation - Vallée, Jacques P. (Astrophysics and Space Science, 2017)
Many features near the Galactic Center have been called ‘3-kiloparsec arms’. We reached a point of having too many divergent data, making it difficult to be constrained by a single physical model. Their differing characteristics suggest different physical and dynamical objects. Radial velocity data on the so-called ‘3-kpc arms’ do not coincide with radial velocities of major spiral arms near 3 kpc, nor near 2 kpc, nor near 4 kpc from the Galactic Center (Figs. 1 and 2). Different ‘3-kpc arm’ features may require different models: turbulence around a shock in a Galactic density wave between 2 and 4 kpc from the Galactic Center (Table 1), or nuclear rotation between 0 and 2 kpc from the Galactic Center region (Table 2), or a putative radial expansion between 0 and 4 kpc from the Galactic Center. Despite their naming as ‘Near 3-kiloparsec arms’ or ‘Far 3-kiloparsec arms’, these features are not major arms. Those ‘3-kpc arms’ features nearer the Galactic Center (within 13° of Galactic longitude) may be different than those farther out (Table 2). Here we show that the plethora of observed ‘3-kpc arm’ features can be separated in two: those with Galactic longitude of 13 degrees or more away from the Galactic Center (Table 1—some of which are possibly associated with the observed major spiral arms), and those within 13 degrees from the Galactic Center (Table 2—some of which are possibly associated with the observed central bars; Figs. 1 and 2).
Keywords: Galaxies: spiral; Galaxy: disk; Galaxy: structure; Methods: statistical; ISM: general; ISM: structure

On a new theoretical framework for RR Lyrae stars. II. Mid-infrared period–luminosity–metallicity relations - Neeley, Jillian R.; Marengo, Massimo; Bono, Giuseppe; Braga, Vittorio F.; Dall’ora, Massimo; Magurno, Davide; Marconi, Marcella; Trueba, Nicolas; Tognelli, Emanuele; Moroni, Pier G. Prada; Beaton, Rachael L.; Freedman, Wendy L.; et al. (The Astrophysical Journal, 2017)
We present new theoretical period–luminosity–metallicity (PLZ) relations for RR Lyræ stars (RRLs) at Spitzer and WISE wavelengths. The PLZ relations were derived using nonlinear, time-dependent convective hydrodynamical models for a broad range of metal abundances (Z = 0.0001–0.0198). In deriving the light curves, we tested two sets of atmospheric models and found no significant difference between the resulting mean magnitudes. We also compare our theoretical relations to empirical relations derived from RRLs in both the field and in the globular cluster M4. Our theoretical PLZ relations were combined with multi-wavelength observations to simultaneously fit the distance modulus, μ 0, and extinction, A V , of both the individual Galactic RRL and of the cluster M4. The results for the Galactic RRL are consistent with trigonometric parallax measurements from Gaia's first data release. For M4, we find a distance modulus of μ 0 = 11.257 ± 0.035 mag with A V = 1.45 ± 0.12 mag, which is consistent with measurements from other distance indicators. This analysis has shown that, when considering a sample covering a range of iron abundances, the metallicity spread introduces a dispersion in the PL relation on the order of 0.13 mag. However, if this metallicity component is accounted for in a PLZ relation, the dispersion is reduced to ~0.02 mag at mid-infrared wavelengths.

Observation of a unique wear morphology of cBN inserts during machining of titanium metal matrix composites (Ti-MMCs); leading to new insights into their machinability - Aramesh, Maryam; Attia, Helmi M.; Kishawy, Hossam A.; Balazinski, Marek (The International Journal of Advanced Manufacturing Technology, 2017)
Titanium-based metal matrix composite (T-MMC) is a relatively new material with increasing demand in different industries particularly in aerospace. Yet, there is a significant lack of knowledge regarding its machinability. Tool wear mechanisms of cBN inserts during turning of TiMMCs including adhesion, abrasion, chemical interactions, and their effects on the wear surface morphology were investigated. A unique wear morphology was observed on both rake and flank surfaces, consisting of different distinct zones. The mechanisms leading to this morphology were discussed for the first time, which has led to new understandings and insights into the machinability of Ti-MMCs and more generally into machinability of titanium-based materials. High-magnification imaging revealed a discontinuity within the adhered material to the tool that appeared as a black zone surrounding the contact area. The brittle fracture in this black zone suggested embrittlement of the adhered material in this region. Further investigation confirmed that a very small amount of magnesium in the workpiece material, which is an impurity left over from the production of the titanium alloy, has a key role in this regard. Thus, it could have a profound effect on the machinability of this class of material. Furthermore, magnesium oxidation was found as the main root cause of fire hazard which is known as one of the main issues associated with machining of titanium-based alloys.
Keywords: cBN inserts; tool wear; machinability analysis; Ti-MMCs

Numerical and experimental testing of a morphing upper surface wing equipped with conventional and morphing ailerons - Botez, Ruxandra M.; Koreanschi, Andreea; Oliviu, Sugar Gabor; Mebarki, Yussef; Mamou, Mahmoud; Tondji, Yvan; Amoroso, Francesco; Pecora, Rosario; Lecce, Leonardo; Amendola, Gianluca; Dimino, Ignazio; Concilio, Antonio (55th AIAA Aerospace Sciences Meeting, 2017)
A new wing-tip concept with morphing upper surface and interchangeable conventional and morphing ailerons was designed, manufactured, bench and wind tunnel tested. The development of this wing tip was done in the frame of an international CRIAQ project, and the purpose was to demonstrate the upper surface morphing and aileron morphing capabilities in improving the wing tip aerodynamic performances. During numerical optimization with ‘in-house’ genetic algorithm software, and during wind tunnel experimental tests, it was demonstrated that the air flow laminar state was extended and drag coefficient reduction were obtained.

Non-sequential design of a thermal radiative baffle for NFIRAOS - Atwood, Jenny; Crane, Jeffrey; Herriot, Glen (Optical Fabrication and Testing part of Optical Design and Fabrication: 9-13 July 2017, Denver, Colorado, United States, 2017)
NFIRAOS, the first-light adaptive optics system for the Thirty Meter Telescope (TMT), has a cooled optical enclosure at -30 deg C with an evacuated, double-pane window to allow light in. NFIRAOS has chosen a radiative baffle design between the windows to mitigate frosting of the outer window and to avoid convective turbulence on either window. Here, we present the design of the baffle and the non-sequential analysis showing sufficient radiation rejection.

Nitrous oxide, methane and carbon dioxide patterns and dynamics from an experimental pig mass grave - Dalva, M.; Moore, T. R.; Kalacska, M.; Leblanc, G. (Forensic Science International, 2017)
The objective of the three-year study was to examine spatial and temporal patterns of fluxes and soil pore air concentrations of methane (CH4), carbon dioxide (CO2) and nitrous oxide (N2O) from an experimental mass grave located in a temperate environment. The mass grave (5 × 10 m) contained twenty pig carcasses at a depth of approximately 1 m was compared to a plot of the same dimensions containing only disturbed soil, as well as an undisturbed plot. Soil pore air CH4 concentrations were sub-ambient (<1.8 ppm) except at 75 and 100 cm depths at the mass grave in years 1 and 2 but decreased in year 3. The consumption of CH4 within the aerobic soil resulted in small negative fluxes at the soil surface. Soil pore air CO2 concentration showed an increase with depth in all three plots, with the largest increase (>100,000 ppm at 1 m) in the mass grave, though there was a marked decrease from years 1 to 3. Surface fluxes of CO2 showed strong seasonal variations, peaking in summer. Soil pore air N2O concentration showed major increases in the mass grave, compared to the other two plots with the pattern maintained over the three years, resulting in larger surface fluxes of N2O. To establish the role of the carcasses in N2O dynamics, we incubated a soil sample containing carcass material which resulted in fast rates of N2O production and consumption. The maintenance of elevated pore air concentration and surface flux of N2O throughout the 3 years suggests that this is a long-term pattern and likely the best of the three gases to use to detect graves. Thus, we suggest that measurement of soil pore air concentrations, especially of N2O, could be a simple and effective approach to help determine the location of clandestine graves.

Nitrogen laser guide star using four wave mixing - Kamer, B.; Rastegari, A.; Rasoulof, M.; Arissian, L. (Conference on Lasers and Electro-Optics, 2017)
We present stimulated emission from nitrogen molecular cation using 800 nm ultrashort pulses. The 427 nm lines are dominated by strong field ionization and the 391 nm are driven by four wave mixing.

Nickel–silver monotectic in alumina crucible for use with contact thermometry - Gotoh, M.; Dedyulin, S. N. (International Journal of Thermophysics, 2017)
Previously, the authors have published work describing a pure Ni fixed point within alumina crucibles. The success of this study stimulated working with the Ni–Ag monotectic point in alumina crucibles. Similar to eutectic points, the Ni–Ag monotectic temperature is an invariant point but it differs from a eutectic reaction in such a way that the monotectic phase change takes place from Ni–Ag liquid solution to Ni–Ag solid solution and Ag rich Ni–Ag liquid solution. In the phase diagram references, the Ni–Ag monotectic phase transition temperature is assigned to be about 20∘C below the pure Ni melting/freezing point. As is the case for pure Ni, mechanical stability is one of the concerns. Therefore, proper cell design is necessary to avoid breakage of the alumina crucible. The techniques used for the fabrication and measurement of the pure Ni cell were applied to the Ni–Ag cell as well. The cells have been successfully fabricated and the temperature measurement at the fixed point was carried out for more than 20 thermal cycles in total. A Pt/Pd thermocouple was used to measure the temperature and was calibrated from the tin point to the gold point to measure the ITS-90. Freezing plateaus are realized with the technique of “recurrent offset freezing method with reserved solid”. The duration of each freezing plateau is a minimum of 30 min. The monotectic transformation temperature for the best performed cell is determined as 1428.27∘C with a combined uncertainty of ±0.06∘C (k=1).
Keywords: fixed point for contact thermometry; monotectic; recurrent offset freezing method

NGC 3105: a young cluster in the outer galaxy - Davidge, T. J. (The Astrophysical Journal, 2017)
Images and spectra of the open cluster NGC 3105 have been obtained with the Gemini Multi-Object Spectrograph on Gemini South. The (i',g' - i') color–magnitude diagram (CMD) constructed from these data extends from the brightest cluster members to g' ~ 23. This is ~4-5 mag fainter than previous CMDs at visible wavelengths and allowing cluster members with sub-solar masses to be sampled. Assuming a half-solar metallicity, comparisons with isochrones yield a distance of 6.6 ± 0.3 kpc. An age of at least 32 Myr is found based on the photometric properties of the brightest stars, coupled with the apparent absence of pre-main-sequence stars in the lower regions of the CMD. The luminosity function of stars between 50 and 70 arcsec from the cluster center is consistent with a Chabrier lognormal mass function. However, at radii smaller than 50 arcsec there is a higher specific frequency of the most massive main-sequence (MS) stars than at larger radii. Photometry obtained from archival SPITZER images reveals that some of the brightest stars near NGC 3105 have excess infrared emission, presumably from warm dust envelopes. Hα emission is detected in a few early-type stars in and around the cluster, building upon previous spectroscopic observations that found Be stars near NGC 3105. The equivalent width of the NaD lines in the spectra of early-type stars is consistent with the reddening found from comparisons with isochrones. Stars with i' ~ 18.5 that fall near the cluster MS have a spectral-type A5V, and a distance modulus that is consistent with that obtained by comparing isochrones with the CMD is found assuming solar neighborhood intrinsic brightnesses for these stars.

Next-generation DNA sequencing of VH/VL repertoires: a primer and guide to applications in single-domain antibody discovery - Henry, Kevin A. (Phage Display, 2017)
Immunogenetic analyses of expressed antibody repertoires are becoming increasingly common experimental investigations and are critical to furthering our understanding of autoimmunity, infectious disease, and cancer. Next-generation DNA sequencing (NGS) technologies have now made it possible to interrogate antibody repertoires to unprecedented depths, typically by sequencing of cDNAs encoding immunoglobulin variable domains. In this chapter, we describe simple, fast, and reliable methods for producing and sequencing multiplex PCR amplicons derived from the variable regions (VH, VHH or VL) of rearranged immunoglobulin heavy and light chain genes using the Illumina MiSeq platform. We include complete protocols and primer sets for amplicon sequencing of VH/VHH/VL repertoires directly from human, mouse, and llama lymphocytes as well as from phage-displayed VH/VHH/VL libraries; these can be easily be adapted to other types of amplicons with little modification. The resulting amplicons are diverse and representative, even using as few as 103 input B cells, and their generation is relatively inexpensive, requiring no special equipment and only a limited set of primers. In the absence of heavy-light chain pairing, single-domain antibodies are uniquely amenable to NGS analyses. We present a number of applications of NGS technology useful in discovery of single-domain antibodies from phage display libraries, including: (i) assessment of library functionality; (ii) confirmation of desired library randomization; (iii) estimation of library diversity; and (iv) monitoring the progress of panning experiments. While the case studies presented here are of phage-displayed single-domain antibody libraries, the principles extend to other types of in vitro display libraries.
Keywords: next-generation DNA sequencing; single-domain antibody; phage display library

Next generation Virgo Cluster survey. XXI. The weak lensing masses of the CFHTLS and NGVS RedGOLD galaxy clusters and calibration of the optical richness - Parroni, Carolina; Mei, Simona; Erben, Thomas; Waerbeke, Ludovic van; Raichoor, Anand; Ford, Jes; Licitra, Rossella; Meneghetti, Massimo; Hildebrandt, Hendrik; Miller, Lance; Côté, Patrick; Covone, Giovanni; et al. (The Astrophysical Journal, 2017)
We measured stacked weak lensing cluster masses for a sample of 1323 galaxy clusters detected by the RedGOLD algorithm in the Canada–France–Hawaii Telescope Legacy Survey W1 and the Next Generation Virgo Cluster Survey at 0.2 < z < 0.5, in the optical richness range 10 < ⋋ 70. This is the most comprehensive lensing study of a ~100% complete and ~80% pure optical cluster catalog in this redshift range. We test different mass models, and our final model includes a basic halo model with a Navarro Frenk and White profile, as well as correction terms that take into account cluster miscentering, non-weak shear, the two-halo term, the contribution of the Brightest Cluster Galaxy, and an a posteriori correction for the intrinsic scatter in the mass–richness relation. With this model, we obtain a mass–richness relation of logM200/M⊙=(14.46 +-0.02)+(1.04 +-0.09)log(⋋/40) (statistical uncertainties). This result is consistent with other published lensing mass–richness relations. We give the coefficients of the scaling relations between the lensing mass and X-ray mass proxies, L X and T X, and compare them with previous results. When compared to X-ray masses and mass proxies, our results are in agreement with most previous results and simulations, and consistent with the expected deviations from self-similarity.
Keywords: galaxies: clusters: general; gravitational lensing: weak

Nanometric assembly of functional terpyridyl complexes on transparent and conductive oxide substrates: structure, properties, and applications - Mondal, Prakash Chandra; Singh, Vikram; Zharnikov, Michael (Accounts of Chemical Research, 2017)
Over the last few decades, molecular assemblies on solid substrates have become increasingly popular, challenging the traditional systems and materials in terms of better control over molecular structure and function at the nanoscale. A variety of such assemblies with high complexity and adjustable properties was generated on the basis of organic, inorganic, organometallic, polymeric, and biomolecular building blocks. Particular versatile elements in this context are terpyridyls due to their wide design flexibility, ease of functionalization, and ability to coordinate to a broad variety of transition-metal ions without forming diastereoisomers, which facilitates tuning of their optical and electronic properties. Specifically, metal–terpyridyl complexes are worthy building blocks for generating optoelectronically active assemblies on technologically relevant transparent and conductive oxide substrates. In this context, the present Account summarizes our recent results on the preparation, characterization, and applications of nanometric (2–10 nm) surface-confined molecular assemblies of Cu2+, Fe2+, Ru2+, and Os2+–terpyridyl complexes on SiOx-based substrates (glass, quartz, silicon, and ITO-coated glass). These assemblies rely on covalent bond formation between the iodo-/chloro-terminated functionalized SiOx substrates and the pendant group (mostly pyridyl) hosted on the terpyridyl complexes. Such an anchoring provides excellent thermal, temporal, radiative, and electrochemical stability to the assemblies as needed for technological applications. The functional, covalently assembled monolayers were extended to fabricate molecular dyads (bilayers), triads (trilayers), and oligomers by an established layer-by-layer procedure using suitable metallolinkers such as Cu2+, Ag+, and Pd2+. The chemical, optical, and electrochemical properties of these assemblies could be precisely adjusted by selection of proper metal–terpyridyl complexes and/or metallolinkers, so that the resulting systems served, relying on the specific design, as sensors, catalysts, molecular logic gates, and photochromic devices. For instance, a Cu-terpyridyl-based assembly on a glass substrate showed “turn on” detection of ascorbic acid. In another example, heterometallic molecular triads were exposed to redox-active NO+ for selective oxidation of the metal ions, and the optical readout was utilized for configuring multiple-input-based molecular logic gates. Furthermore, bias-driven (+0.6 to +1.6 V vs Ag/AgCl) optical properties of the heteroleptic Ru2+/Os2+-terpyridyl monolayers were modulated and “read out” by spectro-electrochemical techniques demonstrating high charge/information density (3–4 × 1014 electrons/cm2). Moreover, the manipulation of the M2+/3+ (M = Fe, Ru, and Os) redox wave in the assembly provided the possibility to create mixed-valence redox-states paving the way toward the fabrication of “multi-bit” memory systems. We truly believe that due to these intriguing characteristics and excellent stability, terpyridyl-based molecular assemblies have the potential to become a versatile platform for the next generation of smart optoelectronic devices.

Multiple populations along the asymptotic giant branch of the globular cluster M4 - Lardo, C.; Salaris, M.; Savino, A.; Donati, P.; Stetson, P. B.; Cassisi, S. (Monthly Notices of the Royal Astronomical Society, 2017)
Nearly all Galactic globular clusters host stars that display characteristic abundance anticorrelations, like the O-rich/Na-poor pattern typical of field halo stars, together with O-poor/Na-rich additional components. A recent spectroscopic investigation questioned the presence of O-poor/Na-rich stars amongst a sample of asymptotic giant branch (AGB) stars in the cluster M4, at variance with the spectroscopic detection of a O-poor/Na-rich component along both the cluster red giant branch (RGB) and horizontal branch. This is contrary to what is expected from the cluster horizontal branch morphology and horizontal branch stellar evolution models. Here, we have investigated this issue by employing the CUBI = (U − B) − (B − I) index, that previous studies have demonstrated to be very effective in separating multiple populations along both the RGB and AGB sequences. We confirm previous results that the RGB is intrinsically broad in the V–CUBI diagram, with the presence of two components that nicely correspond to the two populations identified by high-resolution spectroscopy. We find that AGB stars are distributed over a wide range of CUBI values, in close analogy with what is observed for the RGB, demonstrating that the AGB of M4 also hosts multiple stellar populations.
Keywords: stars: abundances; stars: AGB and post-AGB; globular clusters: general; globular clusters: individual: M4

Multifunctional fiber reinforced polymer composites using carbon and boron nitride nanotubes - Ashrafi, Behnam; Jakubinek, Michael B.; Martinez-Rubi, Yadienka; Rahmat, Meysam; Djokic, Drazen; Laqua, Kurtis; Park, Daesun; Kim, Keun-Su; Simard, Benoit; Yousefpour, Ali (Acta Astronautica, 2017)
Recent progress in nanotechnology has made several nano-based materials available with the potential to address limitations of conventional fiber reinforced polymer composites, particularly in reference to multifunctional structures. Carbon nanotubes (CNTs) are the most prevalent case and offer amazing properties at the individual nanotube level. There are already a few high-profile examples of the use of CNTs in space structures to provide added electrical conductivity for static dissipation and electromagnetic shielding. Boron nitride nanotubes (BNNTs), which are structurally analogous to CNTs, also present a range of attractive properties. Like the more widely explored CNTs, individual BNNTs display remarkable mechanical properties and high thermal conductivity but with contrasting functional attributes including substantially higher thermal stability, high electrical insulation, polarizability, high neutron absorption and transparency to visible light. This presents the potential of employing either or both BNNTs and CNTs to achieve a range of lightweight, functional composites for space structures. Here we present the case for application of BNNTs, in addition to CNTs, in space structures and describe recent advances in BNNT production at the National Research Council Canada (NRC) that have, for the first time, provided sufficiently large quantities to enable commercialization of high-quality BNNTs and accelerate development of chemistry, composites and applications based on BNNTs. Early demonstrations showing the fabrication and limited structural testing of polymer matrix composites, including glass fiber-reinforced composite panels containing BNNTs will be discussed.
Keywords: nanotechnology; nanocomposites; carbon nanotubes; boron nitride nanotubes; buckypaper; glass fiber reinforced polymer composites

Monoclonal antibody protects against acinetobacter baumannii infection by enhancing bacterial clearance and evading sepsis - Nielsen, Travis B.; Pantapalangkoor, Paul; Luna, Brian M.; Bruhn, Kevin W.; Yan, Jun; Dekitani, Ken; Hsieh, Sarah; Yeshoua, Brandon; Pascual, Bryan; Vinogradov, Evgeny; Hujer, Kristine M.; Domitrovic, T nicholas; et al. (The Journal of Infectious Diseases, 2017)
Background: Extremely drug-resistant (XDR) Acinetobacter baumannii is one of the most commonly encountered, highly resistant pathogens requiring novel therapeutic interventions. Methods: We developed C8, a monoclonal antibody (mAb), by immunizing mice with sublethal inocula of a hypervirulent XDR clinical isolate. Results: C8 targets capsular carbohydrate on the bacterial surface, enhancing opsonophagocytosis. Treating with a single dose of C8 as low as 0.5 μg/mouse (0.0167 mg/kg) markedly improved survival in lethal bacteremic sepsis and aspiration pneumonia models of XDR A. baumannii infection. C8 was also synergistic with colistin, substantially improving survival compared to monotherapy. Treatment with C8 significantly reduced blood bacterial density, cytokine production (tumor necrosis factor α, interleukin [IL] 6, IL-1β, and IL-10), and sepsis biomarkers. Serial in vitro passaging of A. baumannii in the presence of C8 did not cause loss of mAb binding to the bacteria, but did result in emergence of less-virulent mutants that were more susceptible to macrophage uptake. Finally, we developed a highly humanized variant of C8 that retains opsonophagocytic activity in murine and human macrophages and rescued mice from lethal infection. Conclusions: We describe a promising and novel mAb as therapy for lethal, XDR A. baumannii infections, and demonstrate that it synergistically improves outcomes in combination with antibiotics.
Keywords: sepsis; monoclonal antibodies; macrophage; infection; bacteria; mice; acinetobacter baumannii

Monitoring non-adiabatic dynamics in CS2 with time- and energy-resolved photoelectron spectra of wavepackets - Wang, Kwanghsi; Mckoy, Vincent; Hockett, Paul; Stolow, Albert; Schuurman, Michael S. (Chemical Physics Letters, 2017)
We report results from a novel fully ab initio method for simulating the time-resolved photoelectron angular distributions around conical intersections in CS2. The technique employs wavepacket densities obtained with the multiple spawning method in conjunction with geometry- and energy-dependent photoionization matrix elements. The robust agreement of the calculated molecular-frame photoelectron angular distributions with measured values for CS2 demonstrates that this approach can successfully illuminate, and disentangle, the underlying coupled nuclear and electronic dynamics around conical intersections in polyatomic molecules.

Molecular dynamics study of guest–host hydrogen bonding in ethylene oxide, trimethylene oxide, and formaldehyde structure I clathrate hydrates - Mohammadi-Manesh, Hossein; Ghafari, Hakime; Alavi, Saman (The Journal of Physical Chemistry C, 2017)
Molecular dynamics simulations are used to study the guest–host hydrogen bonding and guest dynamics in the clathrate hydrate phases of trimethylene oxide (TMO), ethylene oxide (EO), and formaldehyde (FA) as polar guests. Two water models, the SPC/E and TIP4P/ice, were used in the simulations. Binary hydrates are constructed with these guests in the large 14-sided cages and methane placed in the small 12-sided cages of the structure sI clathrate hydrates. The results of these simulations are compared with the nonpolar guests with analogous structures, cyclobutane (CB), cyclopropane (CP), and ethane, respectively, for TMO, EO, and FA. These simulations show that oxygen atoms of the cyclic ethers and carbonyl oxygen of formaldehyde form hydrogen bonds to differing degrees with cage water hydrogen atoms. The TMO size is larger than that of the EO and FA molecules and the closer proximity of the atoms of this large guest to the cage water molecule enhances the probability of guest–host hydrogen bonding in the TMO clathrate. The TMO oxygen atom is tethered by a lattice water hydrogen atom by hydrogen bonding for longer times, which reduces the range of translational and rotational motions of the TMO guests in the cages compared to EO and FA. The effect of guest–host hydrogen bond formation is the insertion of Bjerrum L-defects in the clathrate water lattice. We consider guest dynamic properties such as velocity autocorrelation function (VACF) and orientational autocorrelation function (OACF) of the different guests in these hydrate phases and compare the hydrogen bonding and non-hydrogen bonding analogues. We discuss some other potential experimentally observable effects of the guest–host hydrogen bonding on the guest and water dynamics in the corresponding clathrate hydrates.

Modulation of Th17 and regulatory T-cell responses during murine pregnancy contributes to increased maternal susceptibility to Salmonella Typhimurium infection - Agbayani, Gerard; Wachholz, Kristina; Chattopadhyay, Anindita; Gurnani, Komal; Murphy, Shawn P.; Krishnan, Lakshmi (American Journal of Reproductive Immunology, 2017)
Problem: Salmonella Typhimurium (S. Tm) infection in pregnant mice results in massive placental infection, fetal loss, and exacerbated systemic infection. The Th17 host response can aid control of S. Tm infection, whereas successful pregnancy correlates to a dampened inflammatory and enhanced regulatory T‐cell (Treg) response. Method of study: Mice were infected systemically with S. Tm and tissue bacterial burden, splenic Th17 and Treg cell numbers, and serum cytokines were analyzed. Splenic and/or placental mRNA expression of IL‐17A, RORγ‐t, IL‐10, and TNF was determined. The effects of in vivo CD25+ cell depletion and TLR4 blockade on the course of S. Tm infection and Th17 response were determined. Results: Enhanced S. Tm burden in pregnant mice was associated with time‐dependent increased serum inflammatory cytokines. In vivo, TLR4 blockade reduced splenic S. Tm burden, suggesting detrimental TLR4‐mediated inflammation. However, the splenic and placental Th17 response was reduced in S. Tm‐infected pregnant mice relative to non‐pregnant controls. Alternatively, there was an increase in splenic Treg frequency in pregnant mice and depletion of this subset reduced bacterial burden and increased the Th17 response. Conclusion: Downregulation of Th17 cell responses by Tregs during pregnancy potentially contributes to exacerbation of S. Tm infection in pregnant mice.

Modernization of the real time control and data acquisition systems at the National Research Council of Canada’s 1.5m Tri-Sonic Wind Tunnel - Burns, Greg; Sabbagh, Mazen; Rutherford, Stuart; Cronier, Yves (55th AIAA Aerospace Sciences Meeting, 2017)
The legacy systems that are used for real-time control and data acquisition at the NRC’s 1.5m Tri-Sonic wind tunnel have reached the end of their life cycle, and a project has been initiated to systematically replace them. This paper will describe the approach and design considerations that were used to replace the existing hardware and software systems, some dating back to 1984, with modern off-the-shelf components combined with custom software developed in LabVIEW Real-Time. It will also describe the performance improvements that were achieved as well as some of the new features that were incorporated into the systems.

Minority carrier diffusion length, lifetime and mobility in p-type GaAs and GaInAs - Niemeyer, M.; Ohlmann, J.; Walker, A. W.; Kleinschmidt, P.; Lang, R.; Hannappel, T.; Dimroth, F.; Lackner, D. (Journal of Applied Physics, 2017)
Minority carrier diffusion lengths and lifetimes were determined for p-type Ga(1-x)InxAs with an In-content of 0 ≤ x ≤ 0.53 by cathodoluminescence and time-resolved photoluminescence measurements respectively under low injection conditions; the resulting minority carrier mobilities are also reported. Highly p-doped samples (3 × 1018 cm−3) demonstrate a constant minority carrier diffusion length of (5.0 ± 0.7) μm and a constant lifetime of (3.7 ± 0.7) ns for an In-content up to 21%. Lower doped samples (3 × 1017 cm−3), on the other hand, show an increase in minority carrier diffusion length and lifetime with In-content from (6.3 ± 0.2) μm and (6.2 ± 0.5) ns respectively for GaAs to (14 ± 2) μm and (24.4 ± 0.5) ns respectively for Ga0.79In0.21As. Increasing the In-content to 53% results in a drop in the minority carrier diffusion length independently of the p-doping concentration .This is interpreted as a change in the energy of the Shockley-Read-Hall trap levels within the bandgap as a function of indium concentration.

Minor contribution of quasars to ionizing photon budget at z∼ 6: update on quasar luminosity function at the faint end with subaru/suprime-Cam - Onoue, Masafusa; Kashikawa, Nobunari; Willott, Chris J.; Hibon, Pascale; Im, Myungshin; Furusawa, Hisanori; Harikane, Yuichi; Imanishi, Masatoshi; Ishikawa, Shogo; Kikuta, Satoshi; Matsuoka, Yoshiki; Nagao, Tohru; et al. (The Astrophysical Journal, 2017)
We constrain the quasar contribution to the cosmic reionization based on our deep optical survey of z ~ 6 quasars down to z R = 24.15 using Subaru/Suprime-Cam in three UKIDSS-DXS fields covering 6.5 deg2. In Kashikawa et al. (2015), we select 17 quasar candidates and report our initial discovery of two low-luminosity quasars M1450~ -23 from seven targets, one of which might be a Lyα-emitting galaxy. From an additional optical spectroscopy, none of the four candidates out of the remaining 10 turn out to be genuine quasars. Moreover, the deeper optical photometry provided by the Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP) shows that, unlike the two already-known quasars, the i − z and z − y colors of the last six candidates are consistent with M- or L-type brown dwarfs. Therefore, the quasar luminosity function (QLF) measurement in the previous paper is confirmed. Compiling the QLF measurements from the literature over a wide magnitude range, including an extremely faint AGN candidate from Parsa et al. (2017), to fit them with a double power law, we find that the best-fit faint-end slope is α =-2.04-0.18+0.33 (1.98-0.21+0.48) and characteristic magnitude is M*1450=-25.8-1.9+1.1 (25.7-1.8+1.0) in the case of two (one) quasar detection. Our result suggests that, if the QLF is integrated down to M1450=-18, quasars produce ~1%–12% of the ionizing photons required to fully ionize the universe at z ~ 6 with a 2σ confidence level, assuming that the escape fraction is fesc=1 and the intergalactic medium clumpy factor is C = 3. Even when the systematic uncertainties are taken into account, our result supports the scenario that quasars are the minor contributors of the reionization.

Microscopic characterization to study the mechanism of beneficial CO2 utilization in ready mixed concrete production - Monkman, S.; Grandfield, K.; Dipple, G.; Raki, L. (39th International Conference on Cement Microscopy, ICMA 2017, 2017)
A beneficial carbon dioxide utilization technology has been developed for ready mixed concrete production. Industrial installations have shown that carbon dioxide can be injected into concrete, while it is being batched and mixed, and a strength benefit, circa 10%, can arise. The performance is sensitive to the dose but the CO2 is typically acting on the order of about 0.05% by weight of cement. A series of questions developed - how could such a small addition create a large performance change? Mechanistic understanding would require knowing what the reaction products look like, how they formed and what they were composed of. Microscopic investigations have started to uncover the physiochemical process at work and build evidence for describing the mechanism. SEM was used to examine a model C3S system and show that the action of the CO2 is almost instantaneous - dissolution pits are visible on particle surfaces within 30 seconds of the dose. Reaction products consistent with amorphous calcium carbonate were examined though FIB sectioning and low energy EDS analysis of the chemical composition. Atom Probe Tomography was used to examine the atomic composition of a reaction product in three dimensions.

microRNA-33 regulates macrophage autophagy in atherosclerosis - Ouimet, Mireille; Ediriweera, Hasini; Afonso, Milessa Silva; Ramkhelawon, Bhama; Singaravelu, Ragunath; Liao, Xianghai; Bandler, Rachel C.; Rahman, Karishma; Fisher, Edward A.; Rayner, Katey J.; Pezacki, John P.; Tabas, Ira; et al. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2017)
Objective—Defective autophagy in macrophages leads to pathological processes that contribute to atherosclerosis, including impaired cholesterol metabolism and defective efferocytosis. Autophagy promotes the degradation of cytoplasmic components in lysosomes and plays a key role in the catabolism of stored lipids to maintain cellular homeostasis. microRNA-33 (miR-33) is a post-transcriptional regulator of genes involved in cholesterol homeostasis, yet the complete mechanisms by which miR-33 controls lipid metabolism are unknown. We investigated whether miR-33 targeting of autophagy contributes to its regulation of cholesterol homeostasis and atherogenesis. Approach and Results—Using coherent anti-Stokes Raman scattering microscopy, we show that miR-33 drives lipid droplet accumulation in macrophages, suggesting decreased lipolysis. Inhibition of neutral and lysosomal hydrolysis pathways revealed that miR-33 reduced cholesterol mobilization by a lysosomal-dependent mechanism, implicating repression of autophagy. Indeed, we show that miR-33 targets key autophagy regulators and effectors in macrophages to reduce lipid droplet catabolism, an essential process to generate free cholesterol for efflux. Notably, miR-33 regulation of autophagy lies upstream of its known effects on ABCA1 (ATP-binding cassette transporter A1)-dependent cholesterol efflux, as miR-33 inhibitors fail to increase efflux upon genetic or chemical inhibition of autophagy. Furthermore, we find that miR-33 inhibits apoptotic cell clearance via an autophagy-dependent mechanism. Macrophages treated with anti-miR-33 show increased efferocytosis, lysosomal biogenesis, and degradation of apoptotic material. Finally, we show that treating atherosclerotic Ldlr−/− mice with anti-miR-33 restores defective autophagy in macrophage foam cells and plaques and promotes apoptotic cell clearance to reduce plaque necrosis. Conclusions—Collectively, these data provide insight into the mechanisms by which miR-33 regulates cellular cholesterol homeostasis and atherosclerosis.
Keywords: atherosclerosis; autophagy; hydrolysis; lipid droplets; macrophages

Microbiome and metabolome modifying effects of several cardiovascular disease interventions in apo-E−/− mice - Ryan, Paul M.; London, Lis E. E.; Bjorndahl, Trent C.; Mandal, Rupasri; Murphy, Kiera; Fitzgerald, Gerald F.; Shanahan, Fergus; Ross, R. Paul; Wishart, David S.; Caplice, Noel M.; Stanton, Catherine (Microbiome, 2017)
There is strong evidence indicating that gut microbiota have the potential to modify, or be modified by the drugs and nutritional interventions that we rely upon. This study aims to characterize the compositional and functional effects of several nutritional, neutraceutical, and pharmaceutical cardiovascular disease interventions on the gut microbiome, through metagenomic and metabolomic approaches. Apolipoprotein-E-deficient mice were fed for 24 weeks either high-fat/cholesterol diet alone (control, HFC) or high-fat/cholesterol in conjunction with one of three dietary interventions, as follows: plant sterol ester (PSE), oat β-glucan (OBG) and bile salt hydrolase-active Lactobacillus reuteri APC 2587 (BSH), or the drug atorvastatin (STAT). The gut microbiome composition was then investigated, in addition to the host fecal and serum metabolome.
Keywords: apo-E-deficient; atherosclerosis; cardiovascular disease; microbiome; metabolome

Metagenomic survey of the taxonomic and functional microbial communities of seawater and sea ice from the Canadian Arctic - Yergeau, Etienne; Michel, Christine; Tremblay, Julien; Niemi, Andrea; King, Thomas L.; Wyglinski, Joanne; Lee, Kenneth; Greer, Charles W. (Scientific Reports, 2017)
Climate change has resulted in an accelerated decline of Arctic sea ice since 2001 resulting in primary production increases and prolongation of the ice-free season within the Northwest Passage. The taxonomic and functional microbial community composition of the seawater and sea ice of the Canadian Arctic is not very well known. Bacterial communities from the bottom layer of sea ice cores and surface water from 23 locations around Cornwallis Island, NU, Canada, were extensively screened. The bacterial 16S rRNA gene was sequenced for all samples while shotgun metagenomics was performed on selected samples. Bacterial community composition showed large variation throughout the sampling area both for sea ice and seawater. Seawater and sea ice samples harbored significantly distinct microbial communities, both at different taxonomic levels and at the functional level. A key difference between the two sample types was the dominance of algae in sea ice samples, as visualized by the higher relative abundance of algae and photosynthesis-related genes in the metagenomic datasets and the higher chl a concentrations. The relative abundance of various OTUs and functional genes were significantly correlated with multiple environmental parameters, highlighting many potential environmental drivers and ecological strategies.

Metagenomic and metatranscriptomic analyses reveal the structure and dynamics of a dechlorinating community containing dehalococcoides mccartyi and corrinoid-Providing microorganisms under cobalamin-limited conditions - Men, Yujie; Yu, Ke; Bælum, Jacob; Gao, Ying; Tremblay, Julien; Prestat, Emmanuel; Stenuit, Ben; Tringe, Susannah G.; Jansson, Janet; Zhang, Tong; Alvarez-Cohen, Lisa; Liu, Shuang-Jiang (Applied and Environmental Microbiology, 2017)
The aim of this study is to obtain a systems-level understanding of the interactions between Dehalococcoides and corrinoid-supplying microorganisms by analyzing community structures and functional compositions, activities, and dynamics in trichloroethene (TCE)-dechlorinating enrichments. Metagenomes and metatranscriptomes of the dechlorinating enrichments with and without exogenous cobalamin were compared. Seven putative draft genomes were binned from the metagenomes. At an early stage (2 days), more transcripts of genes in the Veillonellaceae bin-genome were detected in the metatranscriptome of the enrichment without exogenous cobalamin than in the one with the addition of cobalamin. Among these genes, sporulation-related genes exhibited the highest differential expression when cobalamin was not added, suggesting a possible release route of corrinoids from corrinoid producers. Other differentially expressed genes include those involved in energy conservation and nutrient transport (including cobalt transport). The most highly expressed corrinoid de novo biosynthesis pathway was also assigned to the Veillonellaceae bin-genome. Targeted quantitative PCR (qPCR) analyses confirmed higher transcript abundances of those corrinoid biosynthesis genes in the enrichment without exogenous cobalamin than in the enrichment with cobalamin. Furthermore, the corrinoid salvaging and modification pathway of Dehalococcoides was upregulated in response to the cobalamin stress. This study provides important insights into the microbial interactions and roles played by members of dechlorinating communities under cobalamin-limited conditions.

Metabolism of uniformly labeled 13C-eicosapentaenoic acid and 13C-arachidonic acid in young and old men - Léveillé, Pauline; Chouinard-Watkins, Raphaël; Windust, Anthony; Lawrence, Peter; Cunnane, Stephen C; Brenna, J Thomas; Plourde, Mélanie (The American Journal of Clinical Nutrition, 2017)
Background: Plasma eicosapentaenoic acid (EPA) and arachidonic acid (AA) concentrations increase with age. Objective: The aim of this study was to evaluate EPA and AA metabolism in young and old men by using uniformly labeled carbon-13 (13C) fatty acids. Design: Six young (∼25 y old) and 6 old (∼75 y old) healthy men were recruited. Each participant consumed a single oral dose of 35 mg 13C-EPA and its metabolism was followed in the course of 14 d in the plasma and 28 d in the breath. After the washout period of ≥28 d, the same participants consumed a single oral dose of 50 mg 13C-AA and its metabolism was followed for 28 d in plasma and breath. Results: There was a time × age interaction for 13C-EPA (Ptime × age = 0.008), and the shape of the postprandial curves was different between young and old men. The 13C-EPA plasma half-life was ∼2 d for both young and old men (P = 0.485). The percentage dose recovered of 13C-EPA per hour as 13CO2 and the cumulative β-oxidation of 13C-EPA did not differ between young and old men. At 7 d, however, old men had a >2.2-fold higher plasma 13C-DHA concentration synthesized from 13C-EPA compared with young men (Page = 0.03). 13C-AA metabolism was not different between young and old men. The 13C-AA plasma half-life was ∼4.4 d in both young and old participants (P = 0.589). Conclusions: The metabolism of 13C-AA was not modified by age, whereas 13C-EPA metabolism was slightly but significantly different in old compared with young men. The higher plasma 13C-DHA seen in old men may be a result of slower plasma DHA clearance with age. This trial was registered at clinicaltrials.gov as NCT02957188.
Keywords: aging; arachidonic acid; docosahexaenoic acid; eicosapentaenoic acid; metabolism

Mehanical properties of electron beam welded joints in thick gage CA6NM stainless steel - Sarafan, Sheida; Wanjara, Priti; Gholipour, Javad; Champliaud, Henri; Mathieu, Louis (Journal of Materials Engineering and Performance, 2017)
Design of hydroelectric turbine components requires high integrity welds (without detectable volumetric defects) in heavy gage sections of stainless steel materials, such as ASTM A743 grade CA6NM—a low carbon 13% Cr-4% Ni martensitic stainless steel that is manufactured in cast form. In this work, 90-mm-thick plates of CA6NM were joined using a single-pass autogenous electron beam (EB) welding process and the mechanical properties were evaluated in the as-welded condition to characterize the performance of the joints. The static tensile properties that were evaluated in two directions—transverse and longitudinal to the EB weld seam—demonstrated conformance of the joints with the requirements of the ASME Section IX standard. The Charpy impact energies of the EB welds—measured at −18 °C on samples with V-notch roots located in the fusion and heat-affected zones—met the minimum requirements of 27 J specified in ASME Section VIII standard. In addition, bend tests that were conducted on the entire weld cross section displayed no discontinuities on the tension side of the bent joints. Hence, the developed EB welding process was demonstrated to render high-performance joints and promises key advantages for industrialization, such as cost savings through reductions in consumable material, production time and labor intensity.
Keywords: as-welded joints; bend testing; CA6NM martensitic stainless steel; Charpy V-notch testing; electron beam welding; tensile testing

Market mediators and the trade-offs of legitimacy-seeking behaviors in a nascent category - Lee, Brandon H.; Hiatt, Shon R.; Lounsbury, Michael (Organization Science, 2017)
Although existing research has demonstrated the importance of attaining legitimacy for new market categories, few scholars have considered the trade-offs associated with such actions. Using the U.S. organic food product category as a context, we explore how one standards-based certification organization—the California Certified Organic Farmers (CCOF)—sought to balance efforts to legitimate a nascent market category with retaining a shared, distinctive identity among its members. Our findings suggest that legitimacy-seeking behaviors undertaken by the standards organization diluted the initial collective identity and founding ethos of its membership. However, by shifting the meaning of “organic” from the producer to the product, CCOF was able to strengthen the categorical boundary, thereby enhancing its legitimacy. By showing how the organization managed the associated trade-offs, this study highlights the double-edged nature of legitimacy and offers important implications for the literatures on legitimacy and new market category formation.
Keywords: category emergence; legitimacy; market intermediary; collective identity

Manifold-based synthetic oversampling with manifold conformance estimation - Bellinger, Colin; Drummond, Christopher; Japkowicz, Nathalie (Machine Learning, 2017)
Classification domains such as those in medicine, national security and the environment regularly suffer from a lack of training instances for the class of interest. In many cases, classification models induced under these conditions have poor predictive performance on the important minority class. Synthetic oversampling can be applied to mitigate the impact of imbalance by generating additional training instances. In this field, the majority of research has focused on refining the SMOTE algorithm. We note, however, that the generative bias of SMOTE is not appropriate for the large class of learning problems that conform to the manifold property. These are high-dimensional problems, such as image and spectral classification, with implicit feature spaces that are lower-dimensional than their physical data spaces. We show that ignoring this can lead to instances being generated in erroneous regions of the data space. We propose a general framework for manifold-based synthetic oversampling that helps users to select a domain-appropriate manifold learning method, such as PCA or autoencoder, and apply it to model and generate additional training samples. We evaluate data generation on theoretical distributions and image classification tasks that are standard in the manifold learning literature, and empirically show its positive impact on the classification of high-dimensional image and gamma-ray spectra tasks, along with 16 UCI datasets.
Keywords: class imbalance; synthetic oversampling; manifold learning; SMOTE

Managing hydrogen bonding in clathrate hydrates by crystal engineering - Shin, Kyuchul; Moudrakovski, Igor L.; Ratcliffe, Christopher I.; Ripmeester, John A. (Angewandte Chemie International Edition, 2017)
Methanol is one of the most common inhibitors for clathrate hydrate formation. Crystalline clathrate hydrates containing methanol were synthesized and analyzed by powder X‐ray diffraction and 13C NMR spectroscopy. The data obtained demonstrate that methanol can be a helper guest for forming structure I, structure II, and structure H clathrate hydrates, as long as the lattice framework contains NH4F. The latter acts as a lattice stabilizer by providing sites for strong hydrogen bonding of the normally disruptive methanol hydroxy group. NH4F and methanol can be considered key materials for crystal engineering of clathrate hydrates, as the modified lattices allow preparation of hydrates of non‐traditional water‐soluble guests such as alcohols and diols. Methanol takes on the role of an unconventional helper guest. This extends clathrate chemistry to a realm where neither hydrophobic guests nor high pressures are required. This also suggests that more stable lattices can be engineered for applications such as gas storage.

Macroscopic strain-induced transition from quasi-infinite gold nanoparticle chains to defined plasmonic oligomers - Steiner, Anja maria; Mayer, Martin; Seuss, Maximilian; Nikolov, Svetoslav; Harris, Kenneth D.; Alexeev, Alexander; Kuttner, Christian; König, Tobias A.F.; Fery, Andreas (ACS Nano, 2017)
We investigate the formation of chains of few plasmonic nanoparticles—so-called plasmonic oligomers—by strain-induced fragmentation of linear particle assemblies. Detailed investigations of the fragmentation process are conducted by in situ atomic force microscopy and UV–vis–NIR spectroscopy. Based on these experimental results and mechanical simulations computed by the lattice spring model, we propose a formation mechanism that explains the observed decrease of chain polydispersity upon increasing strain and provides experimental guidelines for tailoring chain length distribution. By evaluation of the strain-dependent optical properties, we find a reversible, nonlinear shift of the dominant plasmonic resonance. We could quantitatively explain this feature based on simulations using generalized multiparticle Mie theory (GMMT). Both optical and morphological characterization show that the unstrained sample is dominated by chains with a length above the so-called infinite chain limit—above which optical properties show no dependency on chain length—while during deformation, the average chain length decrease below this limit and chain length distribution becomes more narrow. Since the formation mechanism results in a well-defined, parallel orientation of the oligomers on macroscopic areas, the effect of finite chain length can be studied even using conventional UV–vis–NIR spectroscopy. The scalable fabrication of oriented, linear plasmonic oligomers opens up additional opportunities for strain-dependent optical devices and mechanoplasmonic sensing.
Keywords: atomic force microscopy; generalized multiparticle Mie theory; plasmonic coupling; plasmonic nanoparticles; supra-colloidal assemblies; template-assisted colloidal self-assembly

Machine learning-based methods for analyzing grade crossing safety - Yang, Chunsheng; Trudel, Eric; Liu, Yan (Cluster Computing, 2017)
A grade crossing is defined as an intersection between a roadway and a railway at the same elevation or grade. Multiple new prevention measures have been implemented to reduce the number of train-vehicle collisions; however, crossing safety remains a major issue as accidents still frequently occur. The push for machine learning-based model to analyze risks at grade crossings has also increased to keep up with new technologies. There are many different protection types (gates with bells, cross-buck, stop-sign, mirrors and etc.) that serve to warn or stop oncoming traffic. Many attributes have an inherent impact on accident frequency, including the protection type, train speed, traffic volume and etc. To find out which factors are most important, we propose a machine learning-based method to effectively analyze the impact of multiple factors that affect crossing safety and subsequently provide scientific insight for key factors for enhancing crossing safety. In this work, the Canadian crossing accident database from 2004 to 2013 was used with additional generated features to enhance the performance of models. These include features that were computed using geographical information systems (GIS) and sightline measurements. Based on the performance, the machine learning algorithm, RandomForest is used to rank and analyze 21 attributes for each protection type. From the analysis results it is possible to identify which key factors have the highest influence on improving safety and collision prediction at grade crossings.
Keywords: grade crossing; data-driven modeling; feature generation; machine learning algorithm; randomForest regression; crossing safety; GIS

Low temperature-high selectivity carbon monoxide methanation over yttria-stabilized zirconia-supported Pt nanoparticles - Isaifan, Rima J.; Couillard, Martin; Baranova, Elena A. (International Journal of Hydrogen Energy, 2017)
The high purity hydrogen, free from any traces of carbon monoxide is crucial for the efficient operation of hydrogen proton exchange membrane fuel cells (PEMFCs). In this study we report the low temperature (25–120 °C) carbon monoxide methanation in hydrogen-rich streams over 1 wt. % Pt nanoparticles supported on yttria-stabilized zirconia (YSZ) support. Pt nanoparticles with four average particle sizes 1.9, 3.0, 4.4 and 6.7 nm are investigated. The turnover frequency at 30 °C of CO methanation reaction rate doubles with decreasing Pt mean particle size from 6.7 to 1.9 nm. The high activity of Pt/YSZ catalyst is due to the backspillover of ionic species Oδ− from YSZ support to Pt active sites. Under the reaction conditions, Oδ− forms an “effective” double layer at the catalyst surface that weakens CO (electron acceptor) adsorption and strengthens H2 (electron donor) adsorption bonds and this effect becomes more pronounced as nanoparticle size decreases.
Keywords: platinum nanoparticles; CO methanation; ionic conductivity; yttria-stabilized zirconia; hydrogen purification; oxygen ion promoter

Low cycle fatigue of cast austenitic steel - Wu, X.; Quan, G.; Sloss, C. (Fatigue and fracture test planning, test data acquisitions and analysis, 2017)
Cast austenitic stainless steel 1.4848 is used to manufacture automotive exhaust system components. Low cycle fatigue (LCF) of 1.4848 austenitic steel was investigated through strain-controlled fatigue testing at strain rates of 0.02/s, 0.002/s, and 0.0002/s in the temperature range from room temperature (RT) to 900°C. Its cyclic behavior was characterized in relation to deformation mechanisms. At RT, the material behavior was rate-independent and cyclically stable, which occurred by plasticity. The material exhibited significant cyclic hardening at intermediate temperatures, 400°C to 600°C, with negative strain-rate sensitivity. In this temperature range, dynamic strain aging (DSA) presumably occurred due to slip dragging solute atoms. At high temperatures, 800°C and 900°C, the material exhibited positive rate-dependence in the hysteresis behavior, and the cyclic stress response tended to stabilize with increasing cycles. The high-temperature behavior was presumably controlled by a combination of plasticity and dislocation-glide creep. The integrated creep-fatigue theory (ICFT) was used to describe the deformation and life behaviors based on the identified mechanisms, which were corroborated by fractographic observations. Copyright © 2017 by ASTM International.

Localized detection of D-serine by using an enzymatic amperometric biosensor and scanning electrochemical microscopy - Polcari, David; Perry, Samuel C.; Pollegioni, Loredano; Geissler, Matthias; Mauzeroll, Janine (ChemElectroChem, 2017)
d‐Serine acts as an endogenous co‐agonist for N‐methyl‐d‐aspartate receptors at synapses, making it essential for proper brain development and function. This amino acid has also been linked to several neurodegenerative diseases such as Alzheimer's disease and dementia. Nevertheless, the primary site and mechanism of d‐serine release remains unclear. We recently demonstrated the use of an enzymatic amperometric biosensor for the in vivo quantification of endogenous d‐serine release in Xenopus laevis tadpoles. Herein, we investigate the effect of the permselective poly(meta‐phenylenediamine) electropolymerization conditions on the biosensor's response time and selectivity. Scanning electrochemical microscopy (SECM) is then used with the optimized biosensor to measure localized release of d‐serine from a model system. This SECM methodology, which provides high spatial and temporal resolution, could be useful to investigate the primary site and mechanism of d‐serine release in other biological samples.

Linewidth rebroadening in quantum dot semiconductor lasers - Redlich, Christoph; Lingnau, Benjamin; Huang, Heming; Raghunathan, Ravi; Schires, Kevin; Poole, Philip; Grillot, Frederic; Ludge, Kathy (IEEE Journal of Selected Topics in Quantum Electronics, 2017)
We investigate the interplay between linewidth and α-factor in quantum dot lasers using experimental data and a minimal quantum dot laser rate equation model. The rebroadening of the laser linewidth found experimentally at high injection currents is explained by analytical means and traced back to nonlinear scattering processes. Important differences of the pump current dependent linewidth evolution of quantum dot lasers are highlighted especially if compared to conventional laser devices. Furthermore, we provide a scheme to extract the amplitude-phase coupling as well as effective carrier scattering rates with standard characterization techniques, i.e., linewidth, light versus injected pump current and modulation response measurements.
Keywords: semiconductor lasers; quantum well lasers; nonlinear optics; nonlinear dynamical systems; photonics

Limits on the ultra-bright fast radio burst population from the CHIME pathfinder - Amiri, M.; Bandura, K.; Berger, P.; Bond, J. R.; Cliche, J. F.; Connor, L.; Deng, M.; Denman, N.; Dobbs, M.; Domagalski, R. S.; Fandino, M.; Gilbert, A. J.; et al. (The Astrophysical Journal, 2017)

Light-responsive polymer brushes: active topographic cues for cell culture applications - Kollarigowda, R. H.; Fedele, C.; Rianna, C.; Calabuig, A.; Manikas, A. C.; Pagliarulo, V.; Ferraro, P.; Cavalli, S.; Netti, P. A. (Polymer Chemistry, 2017)
In the call for novel stimuli-responsive biomaterials, azobenzene-containing polymer brushes entail a remarkable potential. In fact, their ability to be patterned at the micro- and nanoscale using interference lithography (IL) might be exploited for the realisation of cell-instructive materials (CIMs). In this work, Disperse Red 1 (DR1)-based photoresponsive polymer brushes were synthesised using a controlled radical polymerisation technique. A sinusoidal pattern was inscribed on the azopolymer brush samples using Lloyd's IL configuration. Interestingly, we found that seeded human umbilical vein endothelial cells (HUVECs) oriented in the pattern direction. Furthermore, using a non-cytotoxic ultrasonication treatment, pattern erasure was achieved. Hence, we envisage the possibility of using these surfaces as reconfigurable cell-instructive biomaterials for tissue engineering applications.

Light curves of the neutron star merger GW170817/SSS17a: implications for r-process nucleosynthesis - Drout, M. R.; Piro, A. L.; Shappee, B. J.; Kilpatrick, C. D.; Simon, J. D.; Contreras, C.; Coulter, D. A.; Foley, R. J.; Siebert, M. R.; Morrell, N.; Boutsia, K.; Di mille, F.; et al. (Science, 2017)
On 17 August 2017, gravitational waves (GWs) were detected from a binary neutron star merger, GW170817, along with a coincident short gamma-ray burst, GRB 170817A. An optical transient source, Swope Supernova Survey 17a (SSS17a), was subsequently identified as the counterpart of this event. We present ultraviolet, optical, and infrared light curves of SSS17a extending from 10.9 hours to 18 days postmerger. We constrain the radioactively powered transient resulting from the ejection of neutron-rich material. The fast rise of the light curves, subsequent decay, and rapid color evolution are consistent with multiple ejecta components of differing lanthanide abundance. The late-time light curve indicates that SSS17a produced at least ~0.05 solar masses of heavy elements, demonstrating that neutron star mergers play a role in rapid neutron capture (r-process) nucleosynthesis in the universe.

Light curve and orbital period analysis of VX lac - Yilmaz, M.; Nelson, R. H.; Şenavci, H. V.; İzci, D. D.; Özavci, I.; Gümüş, D. (Revista mexicana de astronomía y astrofísica, 2017)
In this study, we performed simultaneously light curve and radial velocity, and also period analyses of the eclipsing binary system VX Lac. Four color (BVRI) light curves of the system were analysed using the W-D code. The results imply that VX Lac is a classic Algol-type binary with a mass ratio of q = 0.27, of which the less massive secondary component fills its Roche lobe. The orbital period behaviour of the system was analysed by assuming the light time effect (LITE) from a third body. The O - C analysis yielded a mass transfer rate of dM/dt =1.86 × 10-8 MȮyr-1 and the minimal mass of the third body to be M3 = 0.31Mq. The residuals from mass transfer and the third body were also analysed because another cyclic variation is seen in O - C diagram. This periodic variation was examined under the hypotheses of stellar magnetic activity and fourth body.
Keywords: Binaries: Eclipsing; Stars: Fundamental parameters; Stars: Individual (VX Lac)

A randomized comparison between neurostimulation and ultrasound-guided lateral femoral cutaneous nerve block - Gupta, G.; Radhakrishna, M.; Tamblyn, I.; Tran, D. Q.; Besemann, M.; Thonnagith, A.; Elgueta, M. F.; Robitaille, M. E.; Finlayson, R. J. (U.S. Army Medical Department journal, 2017)
BACKGROUND: This prospective, randomized trial compared neurostimulation (NS) and ultrasound (US) guided lateral femoral cutaneous nerve (LFCN) block. We hypothesized that US would result in a shorter total anesthesia-related time (sum of performance and onset times). METHODS: Twenty-one volunteers were enrolled. The right lower limb was randomized to an NS- or US-guided LFCN block. The alternate technique was employed for the left lower limb. With NS, paresthesias were sought in the lateral thigh at a stimulatory threshold of 0.6 mA (pulse width=0.3 ms; frequency=2 Hz) or lower. With US, local anesthetic was deposited under the inguinal ligament, ventral to the iliopsoas muscle. In both groups, 5 mL of lidocaine 2% were used to anesthetize the nerve. During the procedure of the block, the performance time and number of needle passes were recorded. Subsequently, a blinded observer assessed sensory block in the lateral thigh every minute until 20 minutes. Success was defined as loss of pinprick sensation at a point midway between the anterior superior iliac spine and the lateral knee line. The blinded observer also assessed the areas of sensory block in the anterior, medial, lateral, and posterior aspects of the thigh and mapped this distribution onto a corresponding grid. RESULTS: Both modalities provided comparable success rates (76.2%-95.2%), performance times (162.1 to 231.3 seconds), onset times (300.0 to 307.5 seconds) and total anesthesia related-times (480.1 to 554.0 seconds). However US required fewer needle passes (3.2±2.9 vs 9.5±12.2; P=.009). There were no intergroup differences in terms of the distribution of the anesthetized cutaneous areas. However considerable variability was encountered between individuals and between the 2 sides of a same subject. The most common areas of sensory loss included the central lateral two-eighths anteriorly and the central antero-inferior three-eighths laterally. CONCLUSION: Ultrasound guidance and NS provide similar success rates and total anesthesia-related times for LFCN block. The territory of the LFCN displays wide inter- and intra-individual variability.

Structural characterization of water-metal interfaces - Ryczko, Kevin; Tamblyn, Isaac (Physical Review B, 2017)
We analyze and compare the structural, dynamical, and electronic properties of liquid water next to prototypical metals including Pt, graphite, and graphene. Our results are built on Born-Oppenheimer molecular dynamics (BOMD) generated using density functional theory (DFT) which explicitly include van der Waals (vdW) interactions within a first principles approach. All calculations reported use large simulation cells, allowing for an accurate treatment of the water-electrode interfaces. We have included vdW interactions through the use of the optB86b-vdW exchange correlation functional. Comparisons with the Perdew-Burke-Ernzerhof (PBE) exchange correlation functional are also shown. We find an initial peak, due to chemisorption, in the density profile of the liquid water-Pt interface not seen in the liquid water-graphite interface, liquid water-graphene interface, nor interfaces studied previously. To further investigate this chemisorption peak, we also report differences in the electronic structure of single water molecules on both Pt and graphite surfaces. We find that a covalent bond forms between the single water molecule and the Pt surface but not between the single water molecule and the graphite surface. We also discuss the effects that defects and dopants in the graphite and graphene surfaces have on the structure and dynamics of liquid water.

Sampling algorithms for validation of supervised learning models for Ising-like systems - Portman, Nataliya; Tamblyn, Isaac (Journal of Computational Physics, 2017)
In this paper, we build and explore supervised learning models of ferromagnetic system behavior, using Monte-Carlo sampling of the spin configuration space generated by the 2D Ising model. Given the enormous size of the space of all possible Ising model realizations, the question arises as to how to choose a reasonable number of samples that will form physically meaningful and non-intersecting training and testing datasets. Here, we propose a sampling technique called “ID-MH” that uses the Metropolis–Hastings algorithm creating Markov process across energy levels within the predefined configuration subspace. We show that application of this method retains phase transitions in both training and testing datasets and serves the purpose of validation of a machine learning algorithm. For larger lattice dimensions, ID-MH is not feasible as it requires knowledge of the complete configuration space. As such, we develop a new “block-ID” sampling strategy: it decomposes the given structure into square blocks with lattice dimension N≤5 and uses ID-MH sampling of candidate blocks. Further comparison of the performance of commonly used machine learning methods such as random forests, decision trees, k nearest neighbors and artificial neural networks shows that the PCA-based Decision Tree regressor is the most accurate predictor of magnetizations of the Ising model. For energies, however, the accuracy of prediction is not satisfactory, highlighting the need to consider more algorithmically complex methods (e.g., deep learning).
Keywords: ising model; monte-Carlo sampling; machine learning

The electronic structure of nanoscale interfaces - Tamblyn, I. (Molecular Simulation, 2017)
We review approaches to determining the electronic structure and orbital level alignment at nanoscale interfaces. Errors introduced by common exchange–correlation functionals used in Kohn–Sham density functional theory are discussed. We discuss level alignment results based on many-body perturbation theory within the GW approximation, and highlight the technical challenges and solutions faced when applying this approach to nanoscale interfaces.
Keywords: electronic structure; level alignment; density functional theory; GW

Life prediction of atmospheric plasma-sprayed thermal barrier coatings using temperature-dependent model parameters - Zhang, B.; Chen, Kuiying; Baddour, N.; Patnaik, P. C. (Journal of Thermal Spray Technology, 2017)
The failure analysis and life prediction of atmospheric plasma-sprayed thermal barrier coatings (APS-TBCs) were carried out for a thermal cyclic process. A residual stress model for the top coat of APS-TBC was proposed and then applied to life prediction. This residual stress model shows an inversion characteristic versus thickness of thermally grown oxide. The capability of the life model was demonstrated using temperature-dependent model parameters. Using existing life data, a comparison of fitting approaches of life model parameters was performed. A larger discrepancy was found for the life predicted using linearized fitting parameters versus temperature compared to those using non-linear fitting parameters. A method for integrating the residual stress was proposed by using the critical time of stress inversion. The role of the residual stresses distributed at each individual coating layer was explored and their interplay on the coating’s delamination was analyzed.
Keywords: critical time for stress inversion; CTE mismatch; fitting parameter; life prediction

Land cover, land use, and climate change impacts on endemic cichlid habitats in Northern Tanzania - Kalacska, Margaret; Arroyo-Mora, J.; Lucanus, Oliver; Kishe-Machumu, Mary (Remote Sensing, 2017)
Freshwater ecosystems are among the most threatened on Earth, facing environmental and anthropogenic pressures often surpassing their terrestrial counterparts. Land use and land cover change (LUCC) such as degradation and fragmentation of the terrestrial landscape negatively impacts aquatic ecosystems. Satellite imagery allows for an impartial assessment of the past to determine habitat alterations. It can also be used as a forecasting tool in the development of species conservation strategies through models based on ecological factors extracted from imagery. In this study, we analyze Landsat time sequences (1984–2015) to quantify LUCC around three freshwater ecosystems with endemic cichlids in Tanzania. In addition, we examine population growth, agricultural expansion, and climate change as stressors that impact the habitats. We found that the natural vegetation cover surrounding Lake Chala decreased from 15.5% (1984) to 3.5% (2015). At Chemka Springs, we observed a decrease from 7.4% to 3.5% over the same period. While Lake Natron had minimal LUCC, severe climate change impacts have been forecasted for the region. Subsurface water data from the Gravity Recovery and Climate Experiment (GRACE) satellite observations further show a decrease in water resources for the study areas, which could be exacerbated by increased need from a growing population and an increase in agricultural land use.
Keywords: land cover/land use change; satellite imagery; endemic fish; cichlid; climate change impact

Investigation of the size of the incandescent incipient soot particles in premixed sooting and nucleation flames of n-butane using LII, HIM, and 1 nm-SMPS - Betrancourt, Christopher; Liu, Fengshan; Desgroux, Pascale; Mercier, Xavier; Faccinetto, Alessandro; Salamanca, Maurin; Ruwe, Lena; Kohse-Höinghaus, Katharina; Emmrich, Daniel; Beyer, André; Gölzhäuser, Armin; Tritscher, Torsten (Aerosol Science and Technology, 2017)
Laser-induced incandescence (LII) measurements were conducted to explore the ability of LII to detect small soot particles of less than 10 nm in two sooting flat premixed flames of n-butane: a so-called nucleation flame obtained at a threshold equivalence ratio Φ = 1.75, in which the incipient soot particles undergo only minor soot surface growth along the flame, and a more sooting flame at Φ = 1.95. Size measurements were obtained by modeling the time-resolved LII signals detected using 1064 nm laser excitation. Spectrally-resolved LII signals collected in the nucleation flame display a similar blackbody-like behavior as mature soot. Soot particle temperature was determined from spectrally-resolved detection. LII modeling was conducted using parameters either relevant to those of mature soot or derived from fitting the modeled results to the experimental LII data. Particle size measurements were also carried out using (1) ex situ analysis by helium-ion microscopy (HIM) of particles sampled thermophoretically and (2) online size distribution analysis of microprobe-sampled particles using a 1 nm-SMPS. The size distributions of the incipient soot particles, found in the nucleation flame and in the early soot region of the Φ = 1.95 flame, derived from time-resolved LII signals are in good agreement with HIM and 1 nm-SMPS measurements and are in the range of 2–4 nm. The thermal and optical properties of incipient soot were found to be not radically different from those of mature soot commonly used in LII modeling. This explains the ability of incipient soot particles to produce continuous thermal emissions in the visible spectrum. This study demonstrates that LII is a promising in situ optical particle sizing technique that is capable of detecting incipient soot as small as about 2.5 nm and potentially 2 nm and resolving small changes in soot sizes below 10 nm.

Investigation of ground crew noise exposure for the royal Canadian air force CH-149 cormorant helicopter - Price, A.; Ghinet, S.; Chen, Y.; Grewal, A. (Canadian Acoustics = Acoustique Canadienne, 2017)
Royal Canadian Air Force (RCAF) CH-149 Search and Rescue helicopter aircrew operate in dynamic operational conditions including long-duration search and rescue as well as strenuous open-door hoisting activities. During emergencies, civilians and ground crew may be exposed to aircraft noise within the cabin as well as in the external proximity of the aircraft. Due to the demanding nature of search and rescue activities, civilians, aircrew and ground crew may or may not be equipped with properly fitted hearing protection throughout a noise exposure event. The objective of the recent National Research Council (NRC) – Department of National Defence joint investigation was to characterize the noise levels of the CH-149 helicopter cabin and cockpit throughout 48 representative flight and ground conditions.This paper will outline the NRC ground external noise measurement of the CH-149 Cormorant at Comox Canadian Forces Base, January 2017. The contextual performance of the current in-service RCAF hearing protectors whilst exposed to CH-149 aircraft noise is evaluated. Overall sound pressure levels of 109.8 dB(A) were reported in the proximity of the CH-149 Cormorant throughout standard start-up procedures. It was observed that the directivity of the aircraft engine exhaust and auxiliary power unit exhaust significantly affected external sound pressure levels heterogeneously about the aircraft. In accordance with the Canadian Aviation Occupational Health and Safety Regulations, individuals exposed to aircraft external noise, without properly fitted hearing protection, could exceed their recommended cumulative maximum noise exposure dose within 2 minutes 24 seconds for a single 24 hour period. When equipped with a properly fitted SPH5-CF hearing protector, all locations exhibited significantly reduced sound pressure levels with recommended maximum noise exposure limits in excess of 16 hours, for a single 24 hour period.

Investigating gene function in cereal rust fungi by plant-mediated virus-induced gene silencing - Panwar, Vinay; Bakkeren, Guus (Wheat Rust Diseases, 2017)
Cereal rust fungi are destructive pathogens, threatening grain production worldwide. Targeted breeding for resistance utilizing host resistance genes has been effective. However, breakdown of resistance occurs frequently and continued efforts are needed to understand how these fungi overcome resistance and to expand the range of available resistance genes. Whole genome sequencing, transcriptomic and proteomic studies followed by genome-wide computational and comparative analyses have identified large repertoire of genes in rust fungi among which are candidates predicted to code for pathogenicity and virulence factors. Some of these genes represent defence triggering avirulence effectors. However, functions of most genes still needs to be assessed to understand the biology of these obligate biotrophic pathogens. Since genetic manipulations such as gene deletion and genetic transformation are not yet feasible in rust fungi, performing functional gene studies is challenging. Recently, Host-induced gene silencing (HIGS) has emerged as a useful tool to characterize gene function in rust fungi while infecting and growing in host plants. We utilized Barley stripe mosaic virus-mediated virus induced gene silencing (BSMV-VIGS) to induce HIGS of candidate rust fungal genes in the wheat host to determine their role in plant–fungal interactions. Here, we describe the methods for using BSMV-VIGS in wheat for functional genomics study in cereal rust fungi.
Keywords: virus-induced gene silencing; VIGS; host-induced gene silencing; HIGS; functional genomics; wheat rust fungi; barley stripe mosaic virus; puccinia gene silencing

Intrinsic viscosity of cyclic polystyrene - Jeong, Youncheol; Jin, Ye; Chang, Taihyun; Uhlik, Filip; Roovers, Jacques (Macromolecules, 2017)
The intrinsic viscosity of cyclic polystyrenes (C-PS) and linear polystyrenes (L-PS) with molecular weight (MW) ranging from 16K to 370K was measured in THF using size exclusion chromatography coupled with a triple detection system. The C-PS samples were prepared by a ring-closure reaction of telechelic linear precursor synthesized by anionic polymerization. As-synthesized C-PS samples after the ring-closure reaction contain various byproducts, and they were fractionated by liquid chromatography at the critical condition to obtain highly pure C-PS. While the intrinsic viscosity of L-PS agrees well with the literature data, C-PS shows significantly lower value than the literature values. The Mark–Houwink exponent of C-PS is 0.67, somewhat lower than 0.70 for L-PS in the good solvent over the MW range examined. Therefore, the ratio of the intrinsic viscosity of C-PS to L-PS (g′ = [η]C/[η]L) in THF is not MW independent but decreases as MW increases (0.63 ≥ [η]C/[η]L ≥ 0.57). The trend of intrinsic viscosity agrees well with the computer simulation result. The discrepancy in [η]C from the literature values can largely be attributed to the contamination of linear byproducts in the earlier studies.

Interlayer locking and atomic-scale friction in commensurate small-diameter boron nitride nanotubes - Shin, Homin; Kim, Keun Su; Simard, Benoit; Klug, Dennis D. (Physical Review B, 2017)
Density functional theory applied to small-diameter boron nitride nanotubes (BNNTs) finds out-of-plane structural buckling in contrast to large-diameter tubes that exhibit faceting. Buckling significantly affects interlayer interactions in commensurate double-walled BNNTs. Energy corrugation amplitudes in relative motions of BNNT walls change up to fourfold, depending on interlayer registry relaxation, in marked contrast to carbon nanotubes. Large differences between relaxed and unrelaxed energy corrugations of BNNTs could yield energy dissipation via the strain-induced anelastic relaxation of interlayer locking (or “lattice kinks”), which can be exploited for mechanical damping applications.

Intense-laser solid state physics: unraveling the difference between semiconductors and dielectrics - Mcdonald, C. R.; Vampa, G.; Corkum, P. B.; Brabec, T. (Physical Review Letters, 2017)
Experiments on intense laser driven dielectrics have revealed population transfer to the conduction band to be oscillatory in time. This is in stark contrast to ionization in semiconductors and is currently unexplained. Current ionization theories neglect coupling between the valence and conduction band and therewith, the dynamic Stark shift. Our single-particle analysis identifies this as a potential reason for the different ionization behavior. The dynamic Stark shift increases the band gap with increasing laser intensities, thus suppressing ionization to an extent where virtual population oscillations become dominant. The dynamic Stark shift plays a role dominantly in dielectrics which, due to the larger band gap, can be exposed to significantly higher laser intensities.

Integrated on-chip nano-optomechanical systems - Diao, Zhu; Sauer, Vincent T. K.; Hiebert, Wayne K. (International Journal of High Speed Electronics and Systems, 2017)
Recent developments in integrated on-chip nano-optomechanical systems are reviewed. Silicon-based nano-optomechanical devices are fabricated by a two-step process, where the first step is a foundry-enabled photonic circuits patterning and the second step involves in-house mechanical device release. We show theoretically that the enhanced responsivity of near-field optical transduction of mechanical displacement in on-chip nano-optomechanical systems originates from the finesse of the optical cavity to which the mechanical device couples. An enhancement in responsivity of more than two orders of magnitude has been observed when compared side-by-side with free-space interferometry readout. We further demonstrate two approaches to facilitate large-scale device integration, namely, wavelength-division multiplexing and frequency-division multiplexing. They are capable of significantly simplifying the design complexity for addressing individual nano-optomechanical devices embedded in a large array.
Keywords: nanomechanical resonators; nano-optomechanical systems; nanophotonics

Integral field spectroscopy of the low-mass companion HD 984 B with the Gemini Planet Imager - Johnson-Groh, Mara; Marois, Christian; De Rosa, Robert J.; Nielsen, Eric L.; Rameau, Julien; Blunt, Sarah; Vargas, Jeffrey; Ammons, S. Mark; Bailey, Vanessa P.; Barman, Travis S.; Bulger, Joanna; Chilcote, Jeffrey K.; et al. (The Astronomical Journal, 2017)
We present new observations of the low-mass companion to HD 984 taken with the Gemini Planet Imager (GPI) as a part of the GPI Exoplanet Survey campaign. Images of HD 984 B were obtained in the J (1.12–1.3 μm) and H (1.50–1.80 μm) bands. Combined with archival epochs from 2012 and 2014, we fit the first orbit to the companion to find an 18 au (70-year) orbit with a 68% confidence interval between 14 and 28 au, an eccentricity of 0.18 with a 68% confidence interval between 0.05 and 0.47, and an inclination of 119° with a 68% confidence interval between 114° and 125°. To address the considerable spectral covariance in both spectra, we present a method of splitting the spectra into low and high frequencies to analyze the spectral structure at different spatial frequencies with the proper spectral noise correlation. Using the split spectra, we compare them to known spectral types using field brown dwarf and low-mass star spectra and find a best-fit match of a field gravity M6.5 ± 1.5 spectral type with a corresponding temperature of 2730 ^+120 -180 K. Photometry of the companion yields a luminosity of log(Lbol/L.)=-2.88± 0.07$ dex with DUSTY models. Mass estimates, again from DUSTY models, find an age-dependent mass of 34 ± 1 to 95 ± 4 M Jup. These results are consistent with previous measurements of the object.

Novel bio-nanocomposite hybrids made from polylactide/nanoclay nanocomposites and short flax fibers - Mihai, Mihaela (Journal of Thermoplastic Composite Materials, 2017)
This article aims to formulations and properties of novel hybrid biomaterials containing unique four-phase combinations of polylactide (PLA), nanoclays, flax fibers, and coupling agents. A PLA-grafted maleic anhydride (PLA-g-MA) masterbatch containing 10 wt% PLA-g-MA was obtained by reactive extrusion and was further used, after dilution, as a coupling agent. In addition, three PLA masterbatches containing 10 wt% of three different grades of nanoclays, one untreated nanoclay and two organonanoclays, were also compounded. In a subsequent extrusion step, the nanoclay masterbatches were diluted in PLA down to 4 and 2 wt% while simultaneously incorporating in each one 20 wt% of short flax fibers. Those bio-nanocomposites were compounded without and with an equivalent content of PLA-g-MA, that is, with 4 and 2 wt%, respectively, through the dilution of 10 wt% PLA-g-MA masterbatch. The effects of the nanoclay chemistries, PLA-g-MA, and of flax fibers presence on the properties of bio-nanocomposite hybrid materials were investigated. X-ray diffraction, scanning electron microscopy, transmission electron microscopy, rheology, mechanical properties (tension, flexural, and Izod impact), and reprocess ability tests were used to characterize the bio-nanocomposite hybrid materials. In a second step, PLA-g-MA was replaced by an epoxy/styrene/acrylic copolymer for comparison purpose of their respective effect in bio-nanocomposite performances. Mechanical properties of bio-nanocomposites containing the second coupling agent were also evaluated. The effect of the epoxy/styrene/acrylic copolymer is discussed in comparison with the effect of PLA-g-MA.
Keywords: polylactide; cellulosic fibers; nanoclays; biocomposites; hybrid biocomposites; bio-nanocomposites

Effects of strip temperature and Mn content on galvanizing bath management - Yu, K. R.; Ilinca, F.; Goodwin, F. E. (Galvanizers Association Proceedings 2017, 2017)
Achieving a stable thermal field and adequate control of aluminum and iron content in continuous galvanizing bath operations are of critical importance in achieving automotive quality coated steel products. Previously, numerical models have been developed to describe the flow, temperature and compositional variations in a conventional continuous galvanizing operation. For advanced high strength steels, the strip entry temperature can be different from the mean bath temperature because of over-aging treatments such as carbon partitioning or bainitic transformation that are performed just before entry into the zinc bath. Moreover, advanced high strength steels typically have higher manganese content, which may dissolve into the bath. It is anticipated that the elevated Mn content of the strip could also potentially influence the bath dross formation. This work aims to numerically examine the effects of these two aspects, namely a strip entering the bath at a temperature different from the bath temperature and the Mn content of the strip, on the bath dross formation.
Keywords: dross formation; continuous Galvanizing Bath; numerical modeling; strip Entry Temperature; Mn content

Metallization of various polymers by cold spray - Che, Hanqing; Chu, Xin; Vo, Phuong; Yue, Stephen (Journal of Thermal Spray Technology, 2017)
Previous results have shown that metallic coatings can be successfully cold sprayed onto polymeric substrates. This paper studies the cold sprayability of various metal powders on different polymeric substrates. Five different substrates were used, including carbon fiber reinforced polymer (CFRP), acrylonitrile butadiene styrene (ABS), polyether ether ketone (PEEK), polyethylenimine (PEI); mild steel was also used as a benchmark substrate. The CFRP used in this work has a thermosetting matrix, and the ABS, PEEK and PEI are all thermoplastic polymers, with different glass transition temperatures as well as a number of distinct mechanical properties. Three metal powders, tin, copper and iron, were cold sprayed with both a low-pressure system and a high-pressure system at various conditions. In general, cold spray on the thermoplastic polymers rendered more positive results than the thermosetting polymers, due to the local thermal softening mechanism in the thermoplastics. Thick copper coatings were successfully deposited on PEEK and PEI. Based on the results, a method is proposed to determine the feasibility and deposition window of cold spraying specific metal powder/polymeric substrate combinations.
Keywords: cold spray; deposition window; metallization of polymers; polymeric substrate

Investigation of the feedstock deposition behavior in a cold sprayed 316L/Fe composite coating - Chu, Xin; Chakrabarty, Rohan; Che, Hanqing; Shang, Lihong; Vo, Phuong; Song, Jun; Yue, Stephen (Surface and Coatings Technology, 2017)
Mixing powders in cold spray is a straightforward method to produce composite coatings, but a direct interpretation of the mixed powder deposition behavior from coating microstructure is often difficult. In this study, to investigate the feedstock deposition behavior in a cold sprayed 316L-10 wt% Fe (10Fe) metal-metal composite coating, splats deposited onto the as-polished 316L and Fe coatings with four types of impact scenarios were studied: (i) 316L on 316L, (ii) 316L on Fe, (iii) Fe on 316L, and (iv) Fe on Fe. The splat flattening ratio and coating crater depth/diameter were measured using a light optical microscope (LOM) and an optical profilometer to evaluate the degrees of particle and coating deformation. Finite element (FE) simulations were performed to obtain the splat rebound behavior during impact. A modified ball bond shear test was performed to determine the adhesion strength/energy of the cold spray splats. Results reveal distinct interparticle bonding features in the 10Fe coating, especially at the mixed 316L/Fe interfaces where a preferential location of inter-lamellar cracks can be seen. Similar bonding features were also observed in the deposited splats, indicating the splat on coating tests to be indicative of the coating build-up process. Finally, the feedstock deposition behavior in the 10Fe coating was explained through splat characterizations and FE simulations from hardness, surface oxide layer and particle morphology.
Keywords: cold spray; mixed powder; deposition behavior; splat test; deformation; adhesion

Insights on the high-temperature operational limits of ZrO2-Y2O3 TBCs manufactured via air plasma spray - Lima, Rogerio S.; Marple, Basil R. (Journal of Materials Engineering and Performance, 2017)
The effective high-temperature operation limit of a ZrO2-7-8 wt.%Y2O3 (YSZ) thermal barrier coating (TBC) manufactured via air plasma spray (APS) is considered to be ~1300 °C. This is related to the metastable tetragonal t′-phase formed during the rapid quenching of the YSZ particles during spraying. The t′-phase transforms into the equilibrium tetragonal and cubic phases at temperatures ≥~1300 °C, which can lead to the formation of the monoclinic phase of YSZ upon cooling to room temperature. This formation of the monoclinic phase is accompanied by a volume expansion that leads to TBC failure due to extensive micro-cracking. To further investigate this limitation, an APS YSZ TBC was sprayed on a CMSX-4 substrate. By using a thermal (laser) gradient cyclic testing, a temperature gradient was generated across the TBC/substrate system. The YSZ T-front and substrate backside T-back temperature levels were ~1500 and ~1000 °C, respectively. In cycle conditions (5-min or 1-h hot and 2-min cool), no TBC failure has been observed. This behavior was partially attributed to the unexpected absence of the monoclinic phase of the YSZ in the cycled coatings. Although preliminary, these results are promising regarding increasing the effective high-temperature operational limits of APS YSZ TBCs.
Keywords: aerospace; air plasma spray (APS); life prediction; thermal barrier coating (TBC); thermal conductivity; thermal gradient cyclic testing; ZrO2-7-8 wt.%Y2O3 (YSZ)

In-orbit performance of UVIT and first results - Tandon, S. N.; Hutchings, J. B.; Ghosh, S. K.; Subramaniam, A.; Koshy, G.; Girish, V.; Kamath, P. U.; Kathiravan, S.; Kumar, A.; Lancelot, J. P.; Mahesh, P. K.; Mohan, R.; et al. (Journal of Astrophysics and Astronomy, 2017)
The performance of the ultraviolet telescope (UVIT) on-board AstroSat is reported. The performance in orbit is also compared with estimates made from the calibrations done on the ground. The sensitivity is found to be within ∼15% of the estimates, and the spatial resolution in the NUV is found to exceed significantly the design value of 1.8′′ and it is marginally better in the FUV. Images obtained from UVIT are presented to illustrate the details revealed by the high spatial resolution. The potential of multi-band observations in the ultraviolet with high spatial resolution is illustrated by some results.
Keywords: Ultraviolet astronomy; space astronomy; ultraviolet telescopes; ultraviolet detectors; payloads on AstroSat

In-orbit calibrations of the Ultraviolet Imaging Telescope - Tandon, S. N.; Subramaniam, Annapurni; Girish, V.; Postma, J.; Sankarasubramanian, K.; Sriram, S.; Stalin, C. S.; Mondal, C.; Sahu, S.; Joseph, P.; Hutchings, J.; Ghosh, S. K.; et al. (The Astronomical Journal, 2017)
The Ultra-Violet Imaging Telescope (UVIT) is one of the payloads in ASTROSAT, the first Indian Space Observatory. The UVIT instrument has two 375 mm telescopes: one for the far-ultraviolet (FUV) channel (1300–1800 Å), and the other for the near-ultraviolet (NUV) channel (2000–3000 Å) and the visible (VIS) channel (3200–5500 Å). UVIT is primarily designed for simultaneous imaging in the two ultraviolet channels with spatial resolution better than 1farcs8, along with provisions for slit-less spectroscopy in the NUV and FUV channels. The results of in-orbit calibrations of UVIT are presented in this paper.

Initial structural models of the Aβ42 dimer from replica exchange molecular dynamics simulations - Blinov, Nikolay; Khorvash, Massih; Wishart, David S.; Cashman, Neil R.; Kovalenko, Andriy (ACS Omega, 2017)
Experimental characterization of the molecular structure of small amyloid (A)β oligomers that are currently considered as toxic agents in Alzheimer’s disease is a formidably difficult task due to their transient nature and tendency to aggregate. Such structural information is of importance because it can help in developing diagnostics and an effective therapy for the disease. In this study, molecular simulations and protein–protein docking are employed to explore a possible connection between the structure of Aβ monomers and the properties of the intermonomer interface in the Aβ42 dimer. A structurally diverse ensemble of conformations of the monomer was sampled in microsecond timescale implicit solvent replica exchange molecular dynamics simulations. Representative structures with different solvent exposure of hydrophobic residues and secondary structure content were selected to build structural models of the dimer. Analysis of these models reveals that formation of an intramonomer salt bridge (SB) between Asp23 and Lys28 residues can prevent the building of a hydrophobic interface between the central hydrophobic clusters (CHCs) of monomers upon dimerization. This structural feature of the Aβ42 dimer is related to the difference in packing of hydrophobic residues in monomers with the Asp23–Lys28 SB in on and off states, in particular, to a lower propensity to form hydrophobic contacts between the CHC domain and C-terminal residues in monomers with a formed SB. These findings could have important implications for understanding the difference between aggregation pathways of Aβ monomers leading to neurotoxic oligomers or inert fibrillar structures.
Keywords: glycoproteins; molecular dynamics simulation; oligomers; protein structure

Inhibition of glycosylation on a camelid antibody uniquely affects its FcγRI binding activity - Krahn, Natalie; Spearman, Maureen; Meier, Markus; Dorion-Thibaudeau, July; Mcdougall, Matthew; Patel, Trushar R.; De Crescenzo, Gregory; Durocher, Yves; Stetefeld, Jörg; Butler, Michael (European Journal of Pharmaceutical Sciences, 2017)
Glycoengineering of mAbs has become common practice in attempts to generate the ideal mAb candidate for a wide range of therapeutic applications. The effects of these glycan modifications on the binding affinity of IgG mAbs for FcγRIIIa and their cytotoxicity are well known. However, little is understood about the effect that these modifications have on binding to the high affinity FcγRI receptor. This study analyzed the effect of variable N-glycosylation on a human-llama hybrid mAb (EG2-hFc, 80 kDa) binding to FcγRI including a comparison to a full-sized IgG1 (DP-12, 150 kDa). This was achieved by the addition of three glycosylation inhibitors (swainsonine, castanospermine, and kifunensine) independently to Chinese hamster ovary (CHO) cell cultures to generate hybrid and high mannose glycan structures. Biophysical analysis by circular dichroism, dynamic light scattering and analytical ultra-centrifugation confirmed that the solution-behaviour of the mAbs remained constant over multiple concentrations and glycan treatments. However, changes were observed when studying the interaction of FcγRI with variously glycosylated mAbs. Both mAbs were observed to have a decreased binding affinity upon treatment with swainsonine which produced hybrid glycans. Following de-glycosylation the binding affinity for EG2-hFc was only marginally reduced (6-fold) compared to a drastic (118-fold) decrease for DP-12. In summary, our data suggest that the relatively low molecular weight of chimeric EG2-hFc may contribute to its enhanced stability against glycan changes making it a highly suitable mAb candidate for therapeutic applications.
Keywords: analytical ultracentrifuge; CD spectroscopy; dynamic light scattering; glycosylation inhibitor; monoclonal antibody; N-linked glycosylation; surface plasmon resonance

Infrared observation of a new mixed trimer, CO – (CO2)2 - Barclay, A. J.; Mckellar, A. R. W.; Moazzen-ahmadi, N. (Chemical Physics Letters, 2017)
The infrared spectrum of the weakly-bound trimer CO – (CO2)2 is observed in the carbon monoxide CO stretch region. Both 12C16O – (12C16O2)2 and 12C16O – (12C18O2)2 isotopologues are studied. The trimer band which is composed uniquely of b-type transitions and with missing levels establishes the trimer structure as that of a CO2 dimer plus a CO monomer aligned along the dimer C2 symmetry axis. The dimer to monomer center of mass separation is 3.55 Å, and the structural parameters within the CO2 dimer subunit are about 3.45 Å and 58°. It is not certain if the (CO2)2 remains planar within the trimer.

Influence of soot aging on soot production for laminar propane diffusion flames - Soussi, J. P.; Demarco, R.; Consalvi, J. L.; Liu, F.; Fuentes, A. (Fuel, 2017)
A numerical analysis was conducted to investigate the effect of varying the Oxygen Index (OI) of the oxidizer stream between 21 and 35% on soot production and thermal radiation emitted by laminar axisymmetric propane diffusion flames at atmospheric pressure. The extended enthalpy defect flamelet model, an acetylene/benzene-based two-equation semi-empirical soot production model, and the Full-Spectrum correlated-k radiative property model were used in the numerical simulations. The focus of this study is to demonstrate that it is important to account for the soot aging effect to correctly predict how increasing OI affects the predicted soot production. Three soot surface growth rate models were considered. The first model neglects the soot aging effect and assumes the soot surface growth rate is linearly dependent on soot surface area. The second and third models account for the soot aging effect by assuming the soot surface growth rate is proportional to the square-root of soot surface area and assuming a particle size-dependent sublinear soot surface area, respectively. The predicted flame height, soot volume fraction, radially integrated soot volume fraction and radiant fraction were compared to available experimental data. The first soot model predicted a much higher soot loading increase with increasing OI than observed experimentally. The second and third soot models improve considerably the predicted general behavior of soot loading increase with OI. Soot and combustion gases make comparable contribution to flame radiation under the conditions studied. When the soot aging effect is properly taken into account, the relatively efficient numerical code assessed in this study becomes a suitable tool for predicting soot production and thermal radiation in laminar propane diffusion flames at different OI conditions. Moreover, increasing OI of the oxidizer stream is a remarkable way to enhance the flame radiation where the correct estimation of soot production is essential to predict the radiant fraction of the flame.
Keywords: laminar diffusion flame; propane; oxygen index; soot aging effect; radiant fraction

Individual, model-independent masses of the closest known brown dwarf binary to the Sun - Garcia, E. Victor; Ammons, S. Mark; Salama, Maissa; Crossfield, Ian; Bendek, Eduardo; Chilcote, Jeffrey; Garrel, Vincent; Graham, James R.; Kalas, Paul; Konopacky, Quinn; Lu, Jessica R.; Macintosh, Bruce; et al. (The Astrophysical Journal, 2017)
At a distance of ~2 pc, our nearest brown dwarf neighbor, Luhman 16 AB, has been extensively studied since its discovery 3 years ago, yet its most fundamental parameter—the masses of the individual dwarfs—has not been constrained with precision. In this work, we present the full astrometric orbit and barycentric motion of Luhman 16 AB and the first precision measurements of the individual component masses. We draw upon archival observations spanning 31 years from the European Southern Observatory (ESO) Schmidt Telescope, the Deep Near-Infrared Survey of the Southern Sky (DENIS), public FORS2 data on the Very Large Telescope (VLT), and new astrometry from the Gemini South Multiconjugate Adaptive Optics System (GeMS). Finally, we include three radial velocity measurements of the two components from VLT/CRIRES, spanning one year. With this new data sampling a full period of the orbit, we use a Markov chain Monte Carlo algorithm to fit a 16-parameter model incorporating mutual orbit and barycentric motion parameters and constrain the individual masses to be 27.9 +1.1 -1.0, Mj for the T dwarf and 34.2 +1.3 -1.1, Mj for the L dwarf. Our measurements of Luhman 16 AB's mass ratio and barycentric motion parameters are consistent with previous estimates in the literature utilizing recent astrometry only. The GeMS-derived measurements of the Luhman 16 AB separation in 2014–2015 agree closely with Hubble Space Telescope (HST) measurements made during the same epoch, and the derived mutual orbit agrees with those measurements to within the HST uncertainties of 0.3–0.4 mas.

Improving body composition may reduce the immune and inflammatory responses of firefighters working in the heat - Walker, Anthony; Beatty, Heather E. Wright; Zanetti, Sara; Rattray, Ben (Journal of Occupational and Environmental Medicine, 2017)
Objective: We hypothesized that different body composition and fitness of firefighters would affect immune and inflammatory activity after working in the heat. Methods: Forty-two firefighters worked in the heat (100 ± 5 °C). Changes in leukocytes, platelets, tumor necrosis factor (TNF-α), and C-reactive protein (CRP) were analyzed based on body composition (DXA) and aerobic fitness (VO2max). Results: Higher baseline leukocytes were observed for high body fat (P = 0.002) and low lean mass (P = 0.023) resulting in the highest peak values. Additionally, significantly lower values for TNF-α were observed with high lean mass at all time points. Platelets were unaffected by fitness or body composition. Furthermore, body mass index (BMI) and VO2max played no role. Conclusions: Minimizing body fat and increasing lean mass may reduce immune and inflammatory activity of firefighters in the heat.

Improving and assessing planet sensitivity of the GPI exoplanet survey with a forward model matched filter - Ruffio, Jean-Baptiste; Macintosh, Bruce; Wang, Jason J.; Pueyo, Laurent; Nielsen, Eric L.; Rosa, Robert J. De; Czekala, Ian; Marley, Mark S.; Arriaga, Pauline; Bailey, Vanessa P.; Barman, Travis; Bulger, Joanna; et al. (The Astrophysical Journal, 2017)
We present a new matched-filter algorithm for direct detection of point sources in the immediate vicinity of bright stars. The stellar point-spread function (PSF) is first subtracted using a Karhunen-Loéve image processing (KLIP) algorithm with angular and spectral differential imaging (ADI and SDI). The KLIP-induced distortion of the astrophysical signal is included in the matched-filter template by computing a forward model of the PSF at every position in the image. To optimize the performance of the algorithm, we conduct extensive planet injection and recovery tests and tune the exoplanet spectra template and KLIP reduction aggressiveness to maximize the signal-to-noise ratio (S/N) of the recovered planets. We show that only two spectral templates are necessary to recover any young Jovian exoplanets with minimal S/N loss. We also developed a complete pipeline for the automated detection of point-source candidates, the calculation of receiver operating characteristics (ROC), contrast curves based on false positives, and completeness contours. We process in a uniform manner more than 330 data sets from the Gemini Planet Imager Exoplanet Survey and assess GPI typical sensitivity as a function of the star and the hypothetical companion spectral type. This work allows for the first time a comparison of different detection algorithms at a survey scale accounting for both planet completeness and false-positive rate. We show that the new forward model matched filter allows the detection of 50% fainter objects than a conventional cross-correlation technique with a Gaussian PSF template for the same false-positive rate.

Improvements in the performance of a calibration system for Rogowski coils at high pulsed currents - Djokic, Branislav V. (IEEE Transactions on Instrumentation and Measurement, 2017)
This paper describes improvements of a calibration system for Rogowski coils at high pulsed currents developed at the National Research Council of Canada. This system is designed to provide traceable calibrations of Rogowski coils and weld current meters for users in resistance welding industry, secondary laboratories, and other organizations. The accuracy of the improved calibration system is related to the improved measurement of harmonic content of the test pulsed currents and is estimated for individual tests.

Impact of reperfusion calcium and pH on the resuscitation of hearts donated after circulatory death - White, Christopher; Ambrose, Emma; Müller, Alison; Hatami, Sanaz; Li, Yun; Le, Hoa; Thliveris, James; Arora, Rakesh; Lee, Trevor; Dixon, Ian; Tian, Ganghong; Nagendran, Jayan; et al. (The Annals of Thoracic Surgery, 2017)
Background: Hearts donated after circulatory death may represent an additional donor source. The influx of sodium and calcium ions across the sarcolemma play a central role in the pathogenesis of ischemia-reperfusion injury; however, this process may be inhibited if the initial reperfusion solution is rendered hypocalcemic and acidic. We sought to determine the calcium concentration and pH of the initial reperfusion solution that yielded optimal functional recovery of hearts donated after circulatory death during ex vivo heart perfusion. Methods: Pigs were anesthetized, mechanical ventilation was discontinued, and a 15-minute standoff period was observed after circulatory arrest. Hearts were reperfused with a normothermic cardioplegia of varying calcium concentrations (part 1 [50 μmol/L, n = 4; 220 μmol/L, n = 9; 500 μmol/L, n = 4; and 1,250 μmol/L, n = 5]) and pH (part 2 [7.9, n = 5; 7.4, n = 9; 6.9, n = 8; and 6.4, n = 6]). Myocardial function was then assessed in a physiologic working model 1 hour after initiation of normothermic ex vivo heart perfusion. Results: The calcium concentration and pH of the cardioplegic solution affected the development of myocardial edema (part 1: 50 μmol/L = 5.8% ± 0.9%; 220 μmol/L = 4.3% ± 0.4%; 500 μmol/L = 7.0% ± 0.6%; and 1,250 μmol/L = 6.6% ± 0.8% weight gain, p = 0.015; part 2: 7.9 = 3.6% ± 0.4%, 7.4 = 4.3% ± 0.4%, 6.9 = 3.7% ± 0.6%, and 6.4 = 6.4% ± 1.3% weight gain, p = 0.056) and the recovery of myocardial function (cardiac index part 1: 50 μmol/L = 2.6 ± 0.6; 220 μmol/L = 6.0 ± 0.8; 500 μmol/L = 2.3 ± 0.5; and 1,250 μmol/L = 1.9 ± 0.6 mL · m−1 · g−1, p < 0.001; part 2: 7.9 = 1.5 ± 0.7; 7.4 = 6.0 ± 0.8; 6.9 = 8.4 ± 1.8; and 6.4 = 3.1 ± 0.8 mL · m−1 · g−1, p = 0.003) during ex vivo heart perfusion. Conclusions: Initial reperfusion of hearts donated after circulatory death with a hypocalcemic and moderately acidic cardioplegia minimizes edema and optimizes functional recovery during subsequent ex vivo heart perfusion.

Impact of dust loading on long term portable air cleaner performance - Zuraimi, M. S.; Vuotari, M.; Nilsson, G.; Magee, R.; Kemery, B.; Alliston, C. (Building and Environment, 2017)
Although there has been many studies conducted on the initial performance of portable air cleaners (PACs), there is little research on the evaluation of their long term performance. This paper quantifies the effects of particle loading on PAC particle removal, airflow rate, power consumption and ozone emissions for a HEPA- and electrostatic precipitator (ESP) - based PAC. Ozone emission rates decreased in a linear fashion for the ESP-based PAC suggesting dust masking on the unit's discharge electrode. Performance in terms of particle clean air delivery rates (CADR), airflow rates and power consumption reduced for both units as dust was loaded up to the filter's half-life. For the HEPA based PAC, particle CADR reductions are due to reduced airflow rates. As a consequence, the particle single pass efficiencies (SPEs) grew indicating dust accumulation on the filter. This phenomenon is not observed on the ESP-based PAC where both particle CADR as well as SPE reduced upon dust loading. This study demonstrates the importance of regular filter maintenance for PAC to ensure optimal performance.
Keywords: portable air cleaners; long term performance; HEPA; electrostatic precipitators; particles; ozone

Hybrid quantum photonics - Elshaari, Ali W.; Zadeh, Iman Esmaeil; Fognini, Andreas; Reimer, Michael E.; Dalacu, Dan; Poole, Philip J.; Zwiller, Val; Jöns, Klaus D. (Conference on Lasers and Electro-Optics, 2017)
We deterministically integrate nanowire quantum-emitters in SiN photonic circuits. We generate single-photons, suppress excitation-laser, and isolate specific transitions in the quantum-emitter all on-chip with electrically-tunable filter. Finally, we demonstrate a novel Quantum-WDM channel on-chip.

Hybrid attosecond pulse generation - Hammond, T. J.; Villeneuve, D. M.; Corkum, P. B. (Conference on Lasers and Electro-Optics, 2017)
We combine harmonics from solids and gases to generate isolated attosecond pulses with central frequency controlled by over an octave in the XUV. Spatio-temporal coupling and the carrier-envelope-phase significantly affect the generated half-cycle optical transient field.

Humic acid ameliorates nanoparticle-induced developmental toxicity in zebrafish - Ong, Kimberly J.; Felix, Lindsey C.; Boyle, David; Ede, James D.; Ma, Guibin; Veinot, Jonathan G. C.; Goss, Greg G. (Environmental Science: Nano, 2017)
Many aquatic toxicity experiments are not performed under realistic environmental conditions. We examined several inorganic and organic nanoparticle (NP) formulations (citrate-capped silver NPs, carboxylic acid functionalized single-walled carbon nanotubes, mercaptoundecanoic acid functionalized cadmium selenide NPs, poly(acrylic acid) (PAA)-coated zinc oxide [ZnO] NPs, Nile red-loaded PAA nanocapsules, and uncoated sphere- and leaf-shaped ZnO NPs) to determine whether the presence of humic acid (HA) affects the physicochemical properties (e.g. size, zeta potential, and particle dissolution) of NPs in suspension and ameliorates noted effects on zebrafish (Danio rerio) development. We investigated the toxicological effects of these NPs with and without HA addition during early stages of zebrafish development by measuring survival, hatching success, length, head-tail angle, movement, and protease activity in the chorionic fluid, as well as NP interaction with the chorion. Though NP-induced effects on survival were not mitigated by the presence of HA, hatching inhibition and reduced head-tail angle in developing zebrafish caused by certain NPs were restored to near control values by HA addition. Interestingly, despite the ameliorating effects noted with the addition of HA, combined NP and HA treatments still resulted in reduced enzyme activity and NP interaction with the zebrafish embryo. We suggest that observed effects were NP-specific and not attributed to ionic metal species. In the interest of performing more environmentally representative toxicity studies, HA should be included in standardized laboratory nanotoxicity tests since it alters certain biological effects.

High-dimensional intracity quantum cryptography with structured photons - Sit, Alicia; Bouchard, Frédéric; Fickler, Robert; Gagnon-Bischoff, Jérémie; Larocque, Hugo; Heshami, Khabat; Elser, Dominique; Peuntinger, Christian; Günthner, Kevin; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd; et al. (Optica, 2017)
Quantum key distribution (QKD) promises information-theoretically secure communication and is already on the verge of commercialization. The next step will be to implement high-dimensional protocols in order to improve noise resistance and increase the data rate. Hitherto, no experimental verification of high-dimensional QKD in the single-photon regime has been conducted outside of the laboratory. Here, we report the realization of such a single-photon QKD system in a turbulent free-space link of 0.3 km over the city of Ottawa, taking advantage of both the spin and orbital angular momentum photonic degrees of freedom. This combination of optical angular momenta allows us to create a 4-dimensional quantum state; wherein, using a high-dimensional BB84 protocol, a quantum bit error rate of 11% was attained with a corresponding secret key rate of 0.65 bits per sifted photon. In comparison, an error rate of 5% with a secret key rate of 0.43 bits per sifted photon is achieved for the case of 2-dimensional structured photons. We thus demonstrate that, even through moderate turbulence without active wavefront correction, high-dimensional photon states are advantageous for securely transmitting more information. This opens the way for intracity high-dimensional quantum communications under realistic conditions.

H i kinematics and mass distribution of messier 33 - Kam, S. Z.; Carignan, C.; Chemin, L.; Foster, T.; Elson, E.; Jarrett, T. H. (The Astronomical Journal, 2017)
A new deep H i survey of the galaxy Messier 33 is presented, based on observations obtained at the Dominion Radio Astrophysical Observatory. We observe a perturbed outer gas distribution and kinematics in M33, and confirm the disk warping as a significant twist of the major axis of the velocity field, although no strong tilt is measured, in agreement with previous work. Evidence for a new low-brightness H i component with anomalous velocity is reported. It harbors a large velocity scatter, as its kinematics both exceeds and lags the rotation of the disk, and leaks in the forbidden velocity zone of apparent counterrotation. The observations also reveal wide and multiple-peak H i profiles that can be partly explained by crowded orbits in the framework of the warp model. Asymmetric motions are identified in the velocity field as possible signatures of a lopsided potential and the warp. The mass distribution modeling of the hybrid Hα–H i rotation curve favors a cuspy dark matter halo with a concentration in disagreement with the ΛCDM dark halo mass–concentration relationship. The total mass enclosed in 23 kpc is 8 10^10,M⊙, of which 11% are stars and gas. At the virial radius of the cuspy halo, the resulting total mass is 5 10^11, M⊙, but with a baryonic mass fraction of only 2%. This strongly suggests a more realistic radius encompassing the total mass of M33 that is well smaller than the virial radius of the halo, possibly comparable to the size of the H i disk.

Hashkat: large-scale simulations of online social networks - Ryczko, Kevin; Domurad, Adam; Buhagiar, Nicholas; Tamblyn, Isaac (Social Network Analysis and Mining, 2017)
Hashkat (http://hashkat.org) is a free, open source, agent-based simulation software package designed to simulate large-scale online social networks (e.g., Twitter, Facebook, LinkedIn). It allows for dynamic agent generation, edge creation, and information propagation. The purpose of hashkat is to study the growth of online social networks and how information flows within them. Like real-life online social networks, hashkat incorporates user relationships, information diffusion, and trending topics. Hashkat was implemented in C++ and was designed with extensibility in mind. The software includes Bash and Python scripts for easy installation and usability. In this report, we describe all of the algorithms and features integrated into hashkat before moving on to example use cases. In general, hashkat can be used to understand the underlying topology of social networks, validate sampling methods of such networks, develop business strategy for advertising on online social networks, and test new features of an online social network before going into production.
Keywords: agent-based modeling; Kinetic Monte Carlo; online social network; network evolution; information propagation; simulation

Harmonic generation in solids with direct fiber laser pumping - Lee, Kevin F.; Ding, Xiaoyan; Hammond, T. J.; Fermann, M. E.; Vampa, G.; Corkum, P. B. (Optics Letters, 2017)
High harmonic generation in solids presents the possibility for bringing attosecond techniques to semiconductors and a simple source for frequency comb spectroscopy in the vacuum ultraviolet. We generate up to the seventh harmonic of a Tm fiber laser by focusing in silicon or zinc oxide. The harmonics are strong and stable, with no indication of material damage. Calculations show the potential for generating nineteenth harmonic photons at 12 eV photons of energy.

Halide perovskite solar cells using monocrystalline TiO2 nanorod arrays as electron transport layers: impact of nanorod morphology - Thakur, Ujwal kumar; Askar, Abdelrahman m; Kisslinger, Ryan; Wiltshire, Benjamin d; Kar, Piyush; Shankar, Karthik (Nanotechnology, 2017)
This is the first report of a 17.6% champion efficiency solar cell architecture comprising monocrystalline TiO2 nanorods (TNRs) coupled with perovskite, and formed using facile solution processing without non-routine surface conditioning. Vertically oriented TNR ensembles are desirable as electron transporting layers (ETLs) in halide perovskite solar cells (HPSCs) because of potential advantages such as vectorial electron percolation pathways to balance the longer hole diffusion lengths in certain halide perovskite semiconductors, ease of incorporating nanophotonic enhancements, and optimization between a high contact surface area for charge transfer (good) versus high interfacial recombination (bad). These advantages arise from the tunable morphology of hydrothermally grown rutile TNRs, which is a strong function of the growth conditions. Fluorescence lifetime imaging microscopy of the HPSCs demonstrated a stronger quenching of the perovskite PL when using TNRs as compared to mesoporous/compact TiO2 thin films. Due to increased interfacial contact area between the ETL and perovskite with easier pore filling, charge separation efficiency is dramatically enhanced. Additionally, solid-state impedance spectroscopy results strongly suggested the suppression of interfacial charge recombination between TNRs and perovskite layer, compared to other ETLs. The optimal ETL morphology in this study was found to consist of an array of TNRs ~300 nm in length and ~40 nm in width. This work highlights the potential of TNR ETLs to achieve high performance solution-processed HPSCs.
Keywords: semiconductor; nanostructured titania; solvothermal synthesis; timeresolved photoluminescence; photovoltaics; single crystal nanostructured titania; Mie scattering

Haffner 16 redux: revisiting a young cluster in the outer galaxy - Davidge, T. J. (The Astronomical Journal, 2017)
Images and spectra recorded with the Gemini Multi-Object Spectrograph on Gemini South are used to investigate the stellar content of the open cluster Haffner 16. The (i' ,g' -i') color–magnitude diagram (CMD) constructed from these data extends over 10 mag in i', sampling the cluster main sequence (MS) and 5 mag of the pre-MS (PMS). The fraction of unresolved equal mass binaries among PMS stars is estimated to be 0.6 ± 0.1. The isochrones do not track the PMS on the CMD, in the sense that the PMS has a shallower slope on the CMD than predicted by the models. Still, a dip in star counts, which is associated with the relaxation of PMS stars onto the MS, is identified near i' =17. The depth and brightness of this feature—as well as the morphology of the cluster MS on the CMD—are matched by models with a slightly sub-solar metallicity that have an age of ~20 Myr and a distance modulus of 12.3 ± 0.2. A light profile of Haffner 16 is constructed in the W1 filter (λcen=3.4μm), which suggests that the cluster is surrounded by a diffuse stellar halo. Spectra of candidate cluster MS and PMS stars selected according to location on the CMD are presented. The spectra show characteristics that are suggestive of a sub-solar metallicity. Hα emission is common among objects on the PMS locus on the CMD near i' =18. It is suggested that the location of the Haffner 16 PMS on the CMD is affected by large-scale cool spot activity, likely induced by rapid stellar rotation.
Keywords: open clusters and associations: individual (Haffner 16)

Guest editorial guided lightwaves for sensors and measurement systems: advanced techniques and applications - Xiao, G.; Sun, T.; Rovati, L.; He, Z. (Journal of Lightwave Technology, 2017)
This IEEE/OSA Journal of Lightwave Technology special issue on “Guided Lightwaves for Sensors & Measurement Systems: Advanced Techniques and Applications” is organized by the IEEE Instrumentation and Measurement Society. It aims to highlight the advancement of guided lightwaves in applications to sensors, instrumentation and measurement. The special issue includes both comprehensive review articles and original technical contributions covering the rapid advancement of guided lightwaves in the applications to instrumentation and measurement. 18 invited papers and 22 contributed papers will be published in this issue. The authors are from universities, government labs and industries. We hope that this JLT Special Issue will provide an in-depth look at the topic areas and serve as a valuable reference for the current and future scientists, engineers, and technical applicators working in the related fields.

Growth and characterization of metastable hexagonal nickel thin films via plasma-enhanced atomic layer deposition - Motamedi, Pouyan; Bosnick, Ken; Cui, Kai; Cadien, Ken; Hogan, James David (ACS Applied Materials & Interfaces, 2017)
There is a great interest in various branches of the advanced materials industry for the development of novel methods (and improvements to existing ones) for the deposition of conformal ultrathin metallic films. In most of these applications, like enhanced solar absorbers and microelectronics, achieving the capacity to deposit a conformal thin film on a three-dimensional structure is an important condition. Plasma-enhanced atomic layer deposition (ALD) is known for its potential for growth of conformal thin films with a precise control over the thickness and its capability for deposition at relatively low temperatures (below 500 °C). This study evaluates the potential of plasma-enhanced ALD for growth of conformal nickel thin films, using bis(ethylcyclopentadienyl)nickel and nitrogen/hydrogen plasma as precursors. A comprehensive analysis of the structure, composition, and physical properties of the films was performed. The results indicate that conformal nickel films with low levels of impurity were successfully deposited on sapphire. The films had a roughness of Ra = 1.5 nm and were seen to be under strain. The deposited nickel had a hexagonal crystal structure, with a random in-plane orientation of the grains, while the grains had their c-axes oriented along the normal to the interface. These results pave the way for conformal low-temperature deposition of high-quality nickel thin films on three-dimensional structures.
Keywords: AFM; atomic layer deposition; HCP; hexagonal; nickel; TEM; XRD

Ground state structure of high-energy-density polymeric carbon monoxide - Xia, Kang; Sun, Jian; Pickard, Chris J.; Klug, Dennis D.; Needs, Richard J. (Physical Review B, 2017)
Crystal structure prediction methods and first-principles calculations have been used to explore low-energy structures of carbon monoxide (CO). Contrary to the standard wisdom, the most stable structure of CO at ambient pressure was found to be a polymeric structure of Pna21 symmetry rather than a molecular solid. This phase is formed from six-membered (four carbon + two oxygen) rings connected by C=C double bonds with two double-bonded oxygen atoms attached to each ring. Interestingly, the polymeric Pna21 phase of CO has a much higher energy density than trinitrotoluene (TNT). On compression to about 7 GPa, Pna21 is found to transform into another chainlike phase of Cc symmetry which has similar ring units to Pna21. On compression to 12 GPa, it is energetically favorable for CO to polymerize into a purely single bonded Cmca phase, which is stable over a wide pressure range and transforms into the previously known Cmcm phase at around 100 GPa. Thermodynamic stability of these structures was verified using calculations with different density functionals, including hybrid and van der Waals corrected functionals.

Graphene and silver-nanoprism dispersion for printing optically-transparent electrodes - Sinar, Dogan; Knopf, George K.; Nikumb, Suwas; Tabor, Christopher E.; Kajzar, François; Kaino, Toshikuni; Koike, Yasuhiro (Organic Photonic Materials and Devices XIX, 2017)
Optically transparent electrodes (OTEs) are used for bioelectronics, touch screens, visual displays, and photovoltaic cells. Although the conductive coating for these electrodes is often composed of indium tin oxide (ITO), indium is a very expensive material and thin ITO films are relatively brittle compared to conductive polymer or graphene thin films. An alternative highly conductive optically transparent thin film based on a graphene (G) and silver-nanoprism (AgNP) dispersion is introduced in this paper. The aqueous G ink is first synthesized using carboxymethyl cellulose (CMC) as a stabilizing agent. Silver (Ag) nanoprisms are then prepared separately by a simple thermal process which involves the reduction of silver nitrate by sodium borohydride. These Ag nanoprisms are only a few nanometers thick but have relatively large surface areas (>1000 nm2). As a consequence, the nanoprisms provide more efficient injection of free carriers to the G layer. The concentrated G-AgNP dispersions are then deposited on optically transparent glass and polyimide substrates using an inkjet printer with a HP6602A print head. After printing, these optically thin films can be thermally treated to further increase electrical conductivity. Thermal treatment decomposes CMC which frees elemental carbon from polymer chain and, simultaneously, causes the film to become hydrophobic. Preliminary experiments demonstrate that the G-AgNP films on glass substrates exhibit high conductivity at 70% transparency (550 nm). Additional tests on the Gr-AgNP thin films printed on polymide substrates show mechanical stability under bending with minimal reduction in electrical conductivity or optical transparency.

Gold and uranium concentration by interaction of immiscible fluids (hydrothermal and hydrocarbon) in the Carbon Leader Reef, Witwatersrand Supergroup, South Africa - Fuchs, Sebastian H.J.; Schumann, Dirk; Williams-Jones, Anthony E.; Murray, Andrew J.; Couillard, Martin; Lagarec, Ken; Phaneuf, Michael W.; Vali, Hojatollah (Precambrian Research, 2017)
High-resolution scanning- and transmission-electron microscopy of pyrobitumen-hosted uraninite reveal that uraninite grains are highly porous aggregates of uniformly sized nanocrystals, and that many of their pores are filled by native gold. These texturally late gold grains, in turn, contain small pores occupied by former oil droplets that were converted to pyrobitumen during burial and metamorphism. The pyrobitumen in the pores of the gold grains contains in situ-formed uraninite nanocrystals. Galena also occupies the pores of the uraninite aggregates. In addition, this study reveals the first occurrence of rare lanarkite that engulfs the galena in the pores of the uraninite. On the basis of the nature of the uraninite and the filling of some of its pores with native gold, we propose a mineralization model for the deposition of the uranium and gold in the Carbon Leader Reef that calls upon the interaction of oil and aqueous (hydrothermal) fluids to form micro-emulsions. According to this model, uraninite nanocrystals precipitated from uranium-bearing hydrocarbon liquids and flocculated to form porous, uraninite aggregates. These liquids interacted with auriferous hydrothermal fluids in the Carbon Leader Reef, leading to the formation of a micro-emulsion at the interface between the two fluids. Gold precipitated as native metal around droplets of the oil owing to a reduction in oxygen fugacity, which destabilized the bisulfide species responsible for gold dissolution. Commonly, this process went hand in hand with the flocculation of the uraninite nanocrystals, causing entrapment of the native gold in the pores of the uraninite aggregates. The hydrocarbon liquid, which occurs as droplets in the gold and is the host to the uraninite aggregates, was transformed to pyrobitumen. As a result of this process, a thin pyrobitumen seam containing uraninite nanocrystals formed along the inner walls of the pores in the native gold. Lead introduced by the hydrocarbon liquid precipitated as galena. Interaction of the uraninite with hydrothermal fluids or radiolysis of the pore water facilitated the development of local zones of oxidation between galena and uraninite, which led to the crystallization of rare lanarkite.
Keywords: gold; uranium; emulsions; nanocrystals; electron microscopy; Witwatersrand

Globular clusters as tracers of fine structure in the dramatic shell galaxy NGC 474 - Lim, Sungsoon; Peng, Eric W.; Duc, Pierre-Alain; Fensch, Jérémy; Durrell, Patrick R.; Harris, William E.; Cuillandre, Jean-Charles; Gwyn, Stephen; Lançon, Ariane; Sánchez-Janssen, Rúben (The Astrophysical Journal, 2017)
Globular clusters (GCs) are some of the most visible tracers of the merging and accretion histories of galaxy halos. Metal-poor GCs, in particular, are thought to arrive in massive galaxies largely through dry, minor merging events, but it is rare to see a direct connection between GCs and visible stellar streams. NGC 474 is a post-merger early-type galaxy with dramatic fine structures made of concentric shells and radial streams that have been more clearly revealed by deep imaging. We present a study of GCs in NGC 474 to better establish the relationship between merger-induced fine structure and the GC system. We find that many GCs are superimposed on visible streams and shells, and about 35% of GCs outside 3Re.galaxy are located in regions of fine structure. The spatial correlation between GCs and fine structure is significant at the 99.9% level, which shows that this correlation is not coincidental. The colors of GCs on fine structures are mostly blue, and we also find an intermediate-color population that is dominant in the central region and that will likely passively evolve to have colors consistent with a traditional metal-rich GC population. The association of the blue GCs with fine structures is direct confirmation that many metal-poor GCs are accreted onto massive galaxy halos through merging events and that the progenitors of these mergers are sub-L* galaxies.
Keywords: galaxies: elliptical and lenticular, cD; galaxies: evolution; galaxies: formation; galaxies: individual (NGC 474); galaxies: star clusters: general

Genotype-dependent interaction of lentil lines with Ascochyta lentis - Sari, Ehsan; Bhadauria, Vijai; Vandenberg, Albert; Banniza, Sabine (Frontiers in Plant Science, 2017)
Ascochyta blight of lentil is a prevalent disease in many lentil producing regions and can cause major yield and grain quality losses. The most environmentally acceptable and economically profitable method of control is to develop varieties with high levels of durable resistance. Genetic studies to date suggest that ascochyta blight resistance genes (R-gene) in lentil lines CDC Robin, ILL 7537, 964a-46, and ILL 1704 are non-allelic. To understand how different R-genes manifest resistance in these genotypes and an accession of Lens ervoides, L-01-827A, with high level of resistance to ascochyta blight, cellular and molecular defense responses were compared after inoculation with the causal pathogen Ascochyta lentis. Pathogenicity testing of the resistant lines to A. lentis inoculation revealed significantly lower disease severity on CDC Robin and ILL 7537 compared to ILL 1704 and 964a-46, and no symptoms of disease were observed on L-01-827A. Histological examinations indicated that cell death triggered by the pathogen might be disrupted as a mechanism of resistance in CDC Robin. In contrast, limiting colonization of epidermal cells by A. lentis is a suggested mechanism of resistance in 964a-46. A time-series comparison of the expressions of hallmark genes in salicylic acid (SA) and jasmonic acid (JA) signal transduction pathways between CDC Robin and 964a-46 was conducted. These partially resistant genotypes differed in the timing and the magnitude of SA and JA signaling pathway activation. The SA signaling pathway was only triggered in 964a-46, whereas the JA pathway was triggered in both partially resistant genotypes CDC Robin and 964a-46. The expression of JA-associated genes was lower in 964a-46 than CDC Robin. These observations corroborate the existence of diverse ascochyta blight resistance mechanisms in lentil genotypes carrying different R-genes.
Keywords: histology; cell death; salicylic acid; jasmonic acid; PR-genes

Genetic effects and genotype × environment interactions govern seed oil content in Brassica napus L. - Guo, Yanli; Si, Ping; Wang, Nan; Wen, Jing; Yi, Bin; Ma, Chaozhi; Tu, Jinxing; Zou, Jitao; Fu, Tingdong; Shen, Jinxiong (BMC Genetics, 2017)
As seed oil content (OC) is a key measure of rapeseed quality, better understanding the genetic basis of OC would greatly facilitate the breeding of high-oil cultivars. Here, we investigated the components of genetic effects and genotype × environment interactions (GE) that govern OC using a full diallel set of nine parents, which represented a wide range of the Chinese rapeseed cultivars and pure lines with various OCs.
Keywords: seed oil content; diallel; genetic effects; brassica napus

Gapped excitations in the high-pressure antiferromagnetic phase of URu2Si2 - Williams, T. J.; Barath, H.; Yamani, Z.; Rodriguez-Riviera, J. A.; Leão, J. B.; Garrett, J. D.; Luke, G. M.; Buyers, W. J. L.; Broholm, C. (Physical Review B, 2017)
We report a neutron scattering study of the magnetic excitation spectrum in each of the three temperature and pressure driven phases of URu2Si2. We find qualitatively similar excitations throughout the (H0L) scattering plane in the hidden-order and large-moment phases, with no changes in the ℏω widths of the excitations at the Σ=(1.407,0,0) and Z=(1,0,0) points, within our experimental resolution. There is, however, an increase in the gap at the Σ point from 4.2(2) meV to 5.5(3) meV, consistent with other indicators of enhanced antiferromagnetism under pressure.

Galactic Pal-eontology: abundance analysis of the disrupting globular cluster Palomar 5 - Koch, Andreas; Côté, Patrick (Astronomy & Astrophysics, 2017)
We present a chemical abundance analysis of the tidally disrupted globular cluster (GC) Palomar 5. By co-adding high-resolution spectra of 15 member stars from the cluster’s main body, taken at low signal-to-noise with the Keck/HIRES spectrograph, we were able to measure integrated abundance ratios of 24 species of 20 elements including all major nucleosynthetic channels (namely the light element Na; α-elements Mg, Si, Ca, Ti; Fe-peak and heavy elements Sc, V, Cr, Mn, Co, Ni, Cu, Zn; and the neutron-capture elements Y, Zr, Ba, La, Nd, Sm, Eu). The mean metallicity of −1.56 ± 0.02 ± 0.06 dex (statistical and systematic errors) agrees well with the values from individual, low-resolution measurements of individual stars, but it is lower than previous high-resolution results of a small number of stars in the literature. Comparison with Galactic halo stars and other disrupted and unperturbed GCs renders Pal 5 a typical representative of the Milky Way halo population, as has been noted before, emphasizing that the early chemical evolution of such clusters is decoupled from their later dynamical history. We also performed a test as to the detectability of light element variations in this co-added abundance analysis technique and found that this approach is not sensitive even in the presence of a broad range in sodium of ~0.6 dex, a value typically found in the old halo GCs. Thus, while methods of determining the global abundance patterns of such objects are well suited to study their overall enrichment histories, chemical distinctions of their multiple stellar populations is still best obtained from measurements of individual stars.
Keywords: techniques: spectroscopic; stars: abundances; Galaxy: abundances; Galaxy: evolution; Galaxy: halo; globular clusters: individual: Palomar 5

Galactic dark matter Halos and globular cluster populations. III. Extension to extreme environments - Harris, William E.; Blakeslee, John P.; Harris, Gretchen L. H. (Astrophysical Journal, 2017)

G181.1+9.5: a new high-latitude low-surface brightness supernova remnant - Kothes, Roland; Reich, Patricia; Foster, Tyler J.; Reich, Wolfgang (Astronomy & Astrophysics, 2017)
Context. More than 90% of the known Milky Way supernova remnants (SNRs) are within 5° of the Galactic plane. The discovery of the new high-latitude SNR G181.1+9.5 will give us the opportunity to learn more about the environment and magnetic field at the interface between disk and halo of our Galaxy. Aims. We present the discovery of SNR G181.1+9.5, a new high-latitude SNR, serendipitously discovered in an ongoing survey of the Galactic anti-centre High-Velocity Cloud complex, observed with the DRAO Synthesis Telescope in the 21 cm radio continuum and H i spectral line. Methods. We use radio continuum observations (including the linearly polarized component) at 1420 MHz (observed with the DRAO ST) and 4850 MHz (observed with the Effelsberg 100-m radio telescope) to map G181.1+9.5 and determine its nature as a SNR. High-resolution 21 cm H i line observations and H i emission and absorption spectra reveal the physical characteristics of its local interstellar environment. Finally, we estimate the basic physical parameters of G181.1+9.5 using models for highly-evolved SNRs. Results. G181.1+9.5 has a circular shell-like morphology with a radius of about 16 pc at a distance of 1.5 kpc some 250 pc above the mid-plane. The radio observations reveal highly linearly polarized emission with a non-thermal spectrum. Archival ROSAT X-ray data reveal high-energy emission from the interior of G181.1+9.5 indicative of the presence of shock-heated ejecta. The SNR is in the advanced radiative phase of SNR evolution, expanding into the HVC inter-cloud medium with a density of nHI ≈ 1 cm-3. Basic physical attributes of G181.1+9.5 calculated with radiative SNR models show an upper-limit age of 16 000 yr, a swept-up mass of more than 300M⊙, and an ambient density in agreement with that estimated from H i observations. Conclusions. G181.1+9.5 shows all characteristics of a typical mature shell-type SNR, but its observed faintness is unusual and requires further study.
Keywords: polarization; ISM: magnetic fields; ISM: supernova remnants; ISM: individual objects: G181.1+9.5

Fabrication of right triangular prism retroreflectors through 3½½-axis ultraprecise single point inverted cutting - Hamilton, Benjamin W.; Hussein, Sama; Milliken, Nicolas; Tutunea-Fatan, O. Remus; Bordatchev, Evgueni V. (Computer-Aided Design and Applications, 2017)
Retroreflectors (RR) are passive optical structures that are capable of returning incident light back to the source. The focus of the current study is represented by the right triangular prism (RTP) geometry which could be a more efficient alternative to the traditional inverted corner cube geometry. While current manufacturing practices rely solely on the use of conventional pin-bundling techniques, the work reported in this study presents further enhancements of the previously introduced ultraprecise single point inverted cutting technique which can be used in a manner approximately similar to 3½½-axis kinematics. The experimental results obtained have demonstrated both the feasibility of the proposed fabrication approach as well as the optical viability of the fabricated RTP elements.

Full-dimensional treatment of short-time vibronic dynamics in a molecular high-order-harmonic-generation process in methane - Patchkovskii, Serguei; Schuurman, Michael S. (Physical Review A, 2017)
We present derivation and implementation of the multiconfigurational strong-field approximation with Gaussian nuclear wave packets (MC-SFA-GWP)—a version of the molecular strong-field approximation which treats all electronic and nuclear degrees of freedom, including their correlations, quantum mechanically. The technique allows realistic simulation of high-order-harmonic emission in polyatomic molecules without invoking reduced-dimensionality models for the nuclear motion or the electronic structure. We use MC-SFA-GWP to model isotope effects in high-order-harmonic-generation (HHG) spectroscopy of methane. The HHG emission in this molecule transiently involves the strongly vibronically coupled 2F2 electronic state of the CH4+ cation. We show that the isotopic HHG ratio in methane contains signatures of (a) field-free vibronic dynamics at the conical intersection (CI); (b) resonant features in the recombination cross sections; (c) laser-driven bound-state dynamics; as well as (d) the well-known short-time Gaussian decay of the emission. We assign the intrinsic vibronic feature (a) to a relatively long-lived (≥4 fs) vibronic wave packet of the singly excited ν4 (t2) and ν2 (e) vibrational modes, strongly coupled to the components of the 2F2 electronic state. We demonstrate that these physical effects differ in their dependence on the wavelength, intensity, and duration of the driving pulse, allowing them to be disentangled. We thus show that HHG spectroscopy provides a versatile tool for exploring both conical intersections and resonant features in photorecombination matrix elements in the regime not easily accessible with other techniques.

Frequency domain nonlinear optics - Schmidt, Bruno E.; Gruson, Vincent; Lassonde, Philippe; Ernotte, Guilmot; Leblanc, Adrien; Clerici, Matteo; Morandotti, Roberto; Dimauro, Louis; Corkum, Paul B.; Ibrahim, Heide; Legare, Francois (Nonlinear Optics, 2017)
Frequency-domain Nonlinear Optics (FNO) merges the simplicity of linear optics with the power of nonlinear optics. Employing FNO, we demonstrate pulse shaping in the deep UV and amplification of two-cycle infrared pulses to 2.5 TW.

Freestanding hierarchical porous carbon film derived from hybrid nanocellulose for high-power supercapacitors - Li, Zhi; Ahadi, Kaveh; Jiang, Keren; Ahvazi, Behzad; Li, Peng; Anyia, Anthony O.; Cadien, Ken; Thundat, Thomas (Nano Research, 2017)
Nanocellulose is a sustainable and eco-friendly nanomaterial derived from renewable biomass. In this study, we utilized the structural advantages of two types of nanocellulose and fabricated freestanding carbonized hybrid nanocellulose films as electrode materials for supercapacitors. The long cellulose nanofibrils (CNFs) formed a macroporous framework, and the short cellulose nanocrystals were assembled around the CNF framework and generated micro/mesopores. This two-level hierarchical porous structure was successfully preserved during carbonization because of a thin atomic layer deposited (ALD) Al2O3 conformal coating, which effectively prevented the aggregation of nanocellulose. These carbonized, partially graphitized nanocellulose fibers were interconnected, forming an integrated and highly conductive network with a large specific surface area of 1,244 m2·g–1. The two-level hierarchical porous structure facilitated fast ion transport in the film. When tested as an electrode material with a high mass loading of 4 mg·cm–2 for supercapacitors, the hierarchical porous carbon film derived from hybrid nanocellulose exhibited a specific capacitance of 170 F·g–1 and extraordinary performance at high current densities. Even at a very high current of 50 A·g–1, it retained 65% of its original specific capacitance, which makes it a promising electrode material for high-power applications.
Keywords: supercapacitors; hierarchical structure; atomic layer deposition (ALD); integrated structure

FRB 121102 is coincident with a star-forming region in its host galaxy - Bassa, C. G.; Tendulkar, S. P.; Adams, E. A. K.; Maddox, N.; Bogdanov, S.; Bower, G. C.; Burke-Spolaor, S.; Butler, B. J.; Chatterjee, S.; Cordes, J. M.; Hessels, J. W. T.; Kaspi, V. M.; et al. (The Astrophysical Journal, 2017)
We present optical, near-infrared, and mid-infrared imaging of the host galaxy of FRB 121102 with the Gemini North telescope, the Hubble Space Telescope, and the Spitzer Space Telescope. The FRB 121102 host galaxy is resolved, revealing a bright star-forming region located in the outskirts of the irregular, low-metallicity dwarf galaxy. The star-forming region has a half-light radius of 0.68 kpc (0".20), encompassing the projected location of the compact (<0.7 pc), persistent radio source that is associated with FRB 121102. The half-light diameter of the dwarf galaxy is 5–7 kpc, and broadband spectral energy distribution fitting indicates that it has a total stellar mass of M* ~ 10 8 M.. The properties of the host galaxy of FRB 121102 are comparable to those of extreme emission line galaxies, also known as hosts to some hydrogen-poor superluminous supernovae and long-duration γ-ray bursts. The projected location of FRB 121102 within the star-forming region supports the proposed connection of FRBs with newly born neutron stars or magnetars.

Formation of ligno-polyols: fact or fiction - Ahvazi, Behzad; Wojciechowicz, Olivia; Xu, Ping; Ngo, Tri-Dung; Hawari, Jalal (BioResources, 2017)
The physical and chemical characteristics of several lignin-polyol blends were investigated by qualitative and quantitative methods from the view of biobased polyurethane applications. Four differently isolated biomass lignins from forestry and agricultural residues were blended with polyester polyol, and one was blended with polyethylene glycol. The isolated products were examined thoroughly to elucidate the subsequent lignin and polyol interactions during the premixing stage of biobased polyurethane formulation. Polyol was detected in lignin even after vigorous washings with several organic solvents and Soxhlet extraction. The experimental data coupled with two-dimensional heteronuclear multiple quantum coherence (HMQC) and nuclear magnetic resonance (NMR) spectroscopy confirmed the formation of ligno-polyols via strong intermolecular attractions, as well as some linkages between several lignin hydroxyl and polyol functional groups.
Keywords: lignin; polyester polyol; ligno-polyol; 31P NMR spectroscopy; 2D HMQC; FTIR

Flow and thermal history effects on morphology and tensile behavior of poly (oxymethylene) micro injection molded parts - Kamal, M. R.; El Otmani, R.; Derdouri, A.; Chu, J.-S. (International Polymer Processing, 2017)
The micro injection molding process is a rapidly growing area in plastics processing technology. In this process, the polymer is exposed to both high shear rates and large thermal gradients. In view of the versatility of the process, both commodity and engineering polymers have been used in micro injection molded products. In the present work, poly(oxymethylene) (POM), a partially crystalline engineering polymer, was employed to evaluate the relationships between processing conditions, on one hand, and the morphology and properties of the final part, on the other hand. An unsymmetrical mold cavity to make parts in the form of stepped plaques was used in the study. This resulted in substantial differences in morphology, crystallinity and shrinkage of the zones of different constant thicknesses in the micro parts. Depending on the molding conditions and the location on the micro-part, the microstructure can display up to five crystalline layers. Of particular interest, shish-kebab crystalline structures were observed within the skin of the step with the smallest thickness. Differential scanning calorimetry (DSC) tests are used to distinguish between the melting points of the shish and kebab components of this particular structure. The degree of crystallinity as determined by wide angle X-ray diffraction (WAXD) and shrinkage across the thickness were also found to be highest in the step with the smallest thickness.

First characterization of immunogenic conjugates of Vi negative Salmonella Typhi O-specific polysaccharides with rEPA protein for vaccine development - Salman, M.; St. Michael, F.; Ali, A.; Jabbar, A.; Cairns, C.; Hayes, A.C.; Rahman, M.; Iqbal, M.; Haque, A.; Cox, A.D. (Journal of Immunological Methods, 2017)
Efficacious typhoid vaccines for young children will significantly reduce the disease burden in developing world. The Vi polysaccharide based conjugate vaccines (Vi-rEPA) against Salmonella Typhi Vi positive strains has shown high efficacy but may be ineffective against Vi negative S. Typhi. In this study, for the first time, we report the synthesis and evaluation of polysaccharide-protein conjugates of Vi negative S. Typhi as potential vaccine candidates. Four different conjugates were synthesized using recombinant exoprotein A of Pseudomonas aeruginosa (rEPA) and human serum albumin (HSA) as the carrier proteins, using either direct reductive amination or an intermediate linker molecule, adipic acid dihydrazide (ADH). Upon injection into mice, a significantly higher antibody titer was observed in mice administrated with conjugate-1 (OSP-HSA) (P = 0.0001) and conjugate 2 (OSP-rEPA) (P ≤ 0.0001) as compared to OSP alone. In contrast, the antibody titer elicited by conjugate 3 (OSPADH-HSA) and conjugate 4 (OSPADH-rEPA) were insignificant (P = 0.1684 and P = 0.3794, respectively). We conclude that reductive amination is the superior method to prepare the S. Typhi OSP glycoconjugate. Moreover, rEPA was a better carrier protein than HSA. Thus OSP-rEPA conjugate seems to be efficacious typhoid vaccines candidate, it may be evaluated further and recommended for the clinical trials.
Keywords: Salmonella Typhi Vi negative; OSP antigen; Conjugate vaccines; rEPA; Typhoid; Immunogenicity

Far-infrared observations of a massive cluster forming in the Monoceros R2 filament hub - Rayner, T. S. M.; Griffin, M. J.; Schneider, N.; Motte, F.; Könyves, V.; André, P.; Di Francesco, J.; Didelon, P.; Pattle, K.; Ward-Thompson, D.; Anderson, L. D.; Benedettini, M.; et al. (Astronomy & Astrophysics, 2017)
We present far-infrared observations of Monoceros R2 (a giant molecular cloud at approximately 830 pc distance, containing several sites of active star formation), as observed at 70 μm, 160 μm, 250 μm, 350 μm, and 500 μm by the Photodetector Array Camera and Spectrometer (PACS) and Spectral and Photometric Imaging Receiver (SPIRE) instruments on the Herschel Space Observatory as part of the Herschel imaging survey of OB young stellar objects (HOBYS) Key programme. The Herschel data are complemented by SCUBA-2 data in the submillimetre range, and WISE and Spitzer data in the mid-infrared. In addition, C18O data from the IRAM 30-m Telescope are presented, and used for kinematic information. Sources were extracted from the maps with getsources, and from the fluxes measured, spectral energy distributions were constructed, allowing measurements of source mass and dust temperature. Of177 Herschel sources robustly detected in the region (a detection with high signal-to-noise and low axis ratio at multiple wavelengths), including protostars and starless cores, 29 are found in a filamentary hub at the centre of the region (a little over 1% of the observed area). These objects are on average smaller, more massive, and more luminous than those in the surrounding regions (which together suggest that they are at a later stage of evolution), a result that cannot be explained entirely by selection effects. These results suggest a picture in which the hub may have begun star formation at a point significantly earlier than the outer regions, possibly forming as a result of feedback from earlier star formation. Furthermore, the hub may be sustaining its star formation by accreting material from the surrounding filaments.
Keywords: ISM: individual objects: Mon R2; HII regions; stars: protostars; stars: formation; ISM: structure; dust, extinction

Fabrication of large-area polymeric membranes with micro and nano aperatures - Li, K.; Hernandez-Castro, J. A.; Veres, T. (TechConnect Briefs 2017 Vol. 1 Advanced materials, 2017)
A group of membranes of different materials, including radical and cationic UV lacquer, PFPE urethane methacrylate UV resin (MD700), optical adhesive UV resin with high refractive index (NOA84), as well as thermally curable polydimethylsiloxane (PDMS) have been successfully fabricated by using a simple, yet robust method. The membranes are replicated from an intermediate template with micro- or nano-pillars by using the spontaneous capillary flow (SCF) method. The polymerization is done either by UV or thermal curing. The size of the pores in the membrane ranges from 100 μm down to 200 nm. The thickness of the membranes varies from 10 μm up to 100 μm. As high as 16 of aspect ratio (the thickness of the membrane to the diameter of the pore) has been achieved in membranes with thickness of 100 μm and 6 μm pore diameter. Uniform open-through hole membranes with pore size of 15 μm and thickness of 30 μm over an area of 44×44 mm2 have also been achieved.
Keywords: micro/nano fabrication; micromolding; nanoimprinting; spontaneous capillary flow; UV polymerization

Experimental study of superheated kerosene jet fuel sprays from a pressure-swirl nozzle - Manipurath, Shaji S. (ASME Turbo Expo 2017: Turbomachinery Technical Conference and Exposition, June 26-30, 2017, Charlotte, North Carolina, USA, 2017)
The development of higher thermal stability fuels and the development of onboard fuel deoxygenation systems may permit the preheating of fuel up to about 755 K before the onset of pyrolysis. At a sufficiently high fuel temperature for a given combustion chamber pressure, the flash vaporization of liquid or supercritical state fuel can ensue upon injection into the chamber. The performance of standard aviation turbine engine fuel nozzles, designed for mechanically breaking up liquid sprays, may thus be significantly altered by the employment of severely preheated fuel. An evaluation of heated and superheated Jet A-1 sprays from a pressure-swirl atomizer was implemented in a purpose-built test facility. Laser sheet imaging of the spray yielded simultaneous axial cross-sectional maps of Mie-scatter and fluorescence signals. In addition, particle image velocimetry was also used to measure the spray droplet velocity-field. The results indicated that increasing the fuel’s dimensionless level of superheat ΔT* from −1.8 to 0.6 yielded significant changes in the spray structure; specifically, finer droplet sizes, a more uniform dropsize distribution across the spray, increased spray cone angle till about ΔT* = −0.8 followed by a contraction thereafter, marginally increased spray penetration, and significantly higher localised near nozzle tip droplet velocities. The measurements supported the hypothesis that the initial hollow-cone spray structure evolves to a near solid-cone structure with a central vapour core as the fuel is superheated.

Experimental and numerical investigation of wave forces on partially submerged bodies in close proximity to a fixed structure - Sayeed, Tanvir; Colbourne, Bruce; Molyneux, David; Akinturk, Ayhan (Ocean Engineering, 2017)
Impact loads on an offshore structure due to wave driven icebergs and bergy bits are an important design concern. The hydrodynamic interaction between an iceberg or a bergy bit and an offshore structure, when the two are in close proximity, is an important factor that governs the impact speed and consequently the input energy. Recently, a set of experiments was conducted at the Ocean Engineering Research Center (OERC) of Memorial University of Newfoundland to measure wave loads on different sized spherical masses at different proximities to a fixed structure. A six component dynamometer was used to measure the loads in six regular waves. The objective was to investigate changes in wave load on the sphere at different separation distances from the structure. The experimental results show that the distance to wavelength ratio dictates the corresponding wave loads in horizontal and vertical directions. The mean drift force in the horizontal direction becomes negative (against the direction of wave propagation) for most cases, when the body is close to the structure. Also, as the body is positioned closer to the structure, the non-dimensional RMS forces in the horizontal direction decrease, and the non-dimensional RMS forces in the vertical direction increase. This implies that the approaching body will be slowed down in surge but at the same time will experience increased heave motion. Numerical studies for some of the experimental cases, using the commercial CFD software Flow3D, show good agreement with the experimental data.
Keywords: iceberg; bergy-bit; wave load; hydrodynamic interaction; offshore structure; wave-body interaction

Excited state wavepacket dynamics in NO2 probed by strong-field ionization - Forbes, Ruaridh; Boguslavskiy, Andrey E.; Wilkinson, Iain; Underwood, Jonathan G.; Stolow, Albert (The Journal of Chemical Physics, 2017)
We present an experimental femtosecond time-resolved study of the 399 nm excited state dynamics of nitrogen dioxide using channel-resolved above threshold ionization (CRATI) as the probe process. This method relies on photoelectron-photoion coincidence and covariance to correlate the strong-field photoelectron spectrum with ionic fragments, which label the channel. In all ionization channels observed, we report apparent oscillations in the ion and photoelectron yields as a function of pump-probe delay. Further, we observe the presence of a persistent, time-invariant above threshold ionization comb in the photoelectron spectra associated with most ionization channels at long time delays. These observations are interpreted in terms of single-pump-photon excitation to the first excited electronic X̃ 2A1 state and multi-pump-photon excitations to higher-lying states. The short time delay (< 100 fs) dynamics in the fragment channels show multi-photon pump signatures of higher-lying neutral state dynamics, in data sets recorded with higher pump intensities. As expected for pumping NO2 at 399 nm, non-adiabatic coupling was seen to rapidly re-populate the ground state following excitation to the first excited electronic state, within 200 fs. Subsequent intramolecular vibrational energy redistribution results in the spreading of the ground state vibrational wavepacket into the asymmetric stretch coordinate, allowing the wavepacket to explore nuclear geometries in the asymptotic region of the ground state potential energy surface. Signatures of the vibrationally “hot” ground state wavepacket were observed in the CRATI spectra at longer time delays. This study highlights the complex and sometimes competing phenomena that can arise in strong-field ionization probing of excited state molecular dynamics.

Evidencing fast, massive, and reversible H+ insertion in nanostructured TiO2 electrodes at neutral pH. Where do protons come from? - Kim, Yee-Seul; Kriegel, Sébastien; Harris, Kenneth D.; Costentin, Cyrille; Limoges, Benoît; Balland, Véronique (The Journal of Physical Chemistry C, 2017)
Ongoing developments of sustainable energy technologies based on high-surface-area semiconductive metal oxide electrodes operating under mild and safe aqueous conditions require deep understanding of proton and electron transfer/transport throughout their porous structure. To address this issue, we investigated the electrochemical reductive protonation of high surface area nanostructured amorphous TiO2 electrodes (produced by glancing angle deposition) in both buffered and unbuffered aqueous solutions. Quantitative analysis of the two charge storage mechanisms was achieved, allowing proper deconvolution of the electrical double-layer capacitive charge storage from the reversible faradaic one resulting from the proton-coupled reduction of bulk TiO2. We evidence that this latter process occurs reversibly and extensively (up to an intercalation ratio of 20%) not only under strongly acidic pH conditions but also, more interestingly, under neutral pH with the intercalated proton arising from the buffer rather than water. Moreover, we show that in comparison with reductive Li+ intercalation the proton-coupled electron charge storage occurs more rapidly (in a few seconds). This important finding suggests that a high-rate and high-power charge storage device could potentially be achieved with the reversible H+-coupled charge/discharge process in TiO2 at neutral pH, opening thus new opportunities to the development of eco-friendly batteries for electrical energy storage.

Evaluation of alternative altitude scaling methods for thermal ice protection system in NASA icing research tunnel - Lee, S.; Addy, H. E. Jr.; Broeren, A. P.; Orchard, D. M. (9th AIAA Atmospheric and Space Environments Conference, 2017, 2017)
A test was conducted at NASA Icing Research Tunnel (IRT) to evaluate altitude scaling methods for thermal ice protection systems. Two new scaling methods based on Weber number were compared against an existing method based on Reynolds number. The results generally agreed with the previous set of tests conducted in the National Research Council Canada Altitude Icing Wind Tunnel (AIWT) where the three methods of scaling were also tested and compared along with reference (altitude) icing conditions. In those tests, the Weber number-based scaling methods yielded results much closer to those observed at the reference icing conditions than the Reynolds number-based icing conditions. The test in the NASA IRT used a much larger, asymmetric airfoil with an ice protection system that more closely resembled designs used in commercial aircraft. Following the trends observed during the AIWT tests, the Weber number based scaling methods resulted in smaller runback ice than the Reynolds number based scaling, and the ice formed farther upstream. The results show that the new Weber number based scaling methods, particularly the Weber number with water loading scaling, continue to show promise for ice protection system development and evaluation in atmospheric icing tunnels.

Evaluation of aircrew noise exposure and hearing protection solutions in CH- 147F Chinook Helicopter Cabin - Chen, Y.; Ghinet, S.; Price, A.; Wickramasinghe, V.; Grewal, A. (Forum ..., 2017)
High noise levels in the helicopter cabin affect aircrew communication and reduce aircrew comfort, and may lead to hearing loss in the long-term if flight helmets cannot provide sufficient protection to the aircrew, or are improperly fitted. A cabin noise exposure survey has been performed on a Royal Canadian Air Force (RCAF) CH-147F Chinook heavy lift helicopter to evaluate the noise environment. The insertion loss performance of the flight helmet was characterized in a reverberant acoustic chamber facility. Investigation results showed that the low frequency noise attenuation provided by the RCAF flight helmet was marginal at high speed flight conditions in which significant cabin noise levels existed in the helicopter cabin. To enhance the low frequency hearing protection performance and clarity in voice communication, in-canal Communication Ear Plugs (CEPs) integrated with active noise cancellation (ANC) capability was investigated. Simulation and proof-of-concept test results demonstrated that the ANC in-canal CEPs can serve as a feasible technical solution to provide enhanced noise attenuation to mitigate the low frequency N/rev tonal noise generated by the aerodynamic pressure from the helicopter rotor blades.

eTumorType, an algorithm of discriminating cancer types for circulating tumor cells or cell-free DNAs in blood - Zou, Jinfeng; Wang, Edwin (Genomics, Proteomics & Bioinformatics, 2017)
With the technology development on detecting circulating tumor cells (CTCs) and cell-free DNAs (cfDNAs) in blood, serum, and plasma, non-invasive diagnosis of cancer becomes promising. A few studies reported good correlations between signals from tumor tissues and CTCs or cfDNAs, making it possible to detect cancers using CTCs and cfDNAs. However, the detection cannot tell which cancer types the person has. To meet these challenges, we developed an algorithm, eTumorType, to identify cancer types based on copy number variations (CNVs) of the cancer founding clone. eTumorType integrates cancer hallmark concepts and a few computational techniques such as stochastic gradient boosting, voting, centroid, and leading patterns. eTumorType has been trained and validated on a large dataset including 18 common cancer types and 5327 tumor samples. eTumorType produced high accuracies (0.86–0.96) and high recall rates (0.79–0.92) for predicting colon, brain, prostate, and kidney cancers. In addition, relatively high accuracies (0.78–0.92) and recall rates (0.58–0.95) have also been achieved for predicting ovarian, breast luminal, lung, endometrial, stomach, head and neck, leukemia, and skin cancers. These results suggest that eTumorType could be used for non-invasive diagnosis to determine cancer types based on CNVs of CTCs and cfDNAs.
Keywords: eTumorType; founding clone; copy number variation; non-invasive detection; cancer

Establishment of the model system between phytochemicals and gene expression profiles in Macrosclereid cells of Medicago truncatula - Fu, Fuyou; Zhang, Wentao; Li, Yuan-Yuan; Wang, Hong Li (Scientific Reports, 2017)
Macrosclereid cells, which are a layer in the seed coat of Medicago truncatula, accumulate large amounts of phytochemicals during their development. But little is known about the complex and dynamic changes during macrosclereid cell development. To characterize the phytochemicals and the related gene expression during the development of M. truncatula macrosclereid cells, a high performance liquid chromatography-mass spectrometry (HPLC-MS) assay and microarray study were conducted on transcriptome changes from macrosclereid cell during seed development. A total of 16 flavonoids by HPLC-MS and 4861 genes exhibited significant differences at transcript levels by microarray analysis were identified for macrosclerid cells at six different time points during seed development. 815 abiotic and biotic stress genes, 223 transcriptional factors (TFs), and 155 annotated transporter proteins exhibited differential expression during the development of macrosclereid cells. A total of 102 genes were identified as involved in flavonoid biosynthesis, phenypropanoid biosynthesis, and flavone and flavonol biosynthesis. We performed a weighted gene co-regulatory network (WGCNA) to analyze the gene-flavonoid association and rebuilt the gene regulatory network during macrosclereid cell development. Our studies revealed that macrosclereid cells are, beside as the first barrier of defense against diseases, an excellent model system to investigate the regulatory network that governs flavonoid biosynthesis.

Erythrocyte heat shock protein responses to chronic (in vivo) and acute (in vitro) temperature challenge in diploid and triploid salmonids - Saranyan, Pillai V.; Ross, Neil W.; Benfey, Tillmann J. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2017)
This research investigated how ploidy level (diploid versus triploid) affects the heat shock protein (HSP) response in erythrocytes under different thermal stress regimes, both in vivo and in vitro, in Atlantic salmon (Salmo salar) and brook charr (Salvelinus fontinalis) in order to address the question of why triploids typically have reduced thermal tolerance. A preliminary study confirmed that identical volumes of diploid and triploid erythrocytes (which equates to a smaller number of larger cells for triploids compared to diploids) did not differ in total protein synthesis rates. After chronic (100 d) acclimation of fish to 5, 15 and 25 °C, triploid erythrocytes had lower HSP70, HSP90, heat shock factor 1 (HSF1) and ubiquitin (free and total) levels than diploids in both species. Furthermore, Atlantic salmon erythrocytes showed significantly higher protein breakdown (based on conjugated ubiquitin levels) in triploids than diploids after acute heat stress in vitro, but no significant difference was detected between ploidies after acute cold stress. These results indicate that: 1) triploid erythrocytes synthesize more total protein per cell than diploids as a result of increased cell size; 2) triploids have sufficient total HSP levels for survival under low stress conditions; and 3) the lower basal titres of HSPs in triploids may be a handicap when combating acute stress. Taken together, this suggests that triploids are limited in their ability to withstand thermal stress because of a reduced ability to maintain proteostasis under stressful conditions.
Keywords: triploidy; HSP; stress response; proteostasis; salmonid

Erosive wear behavior of Cold-Sprayed Ni-WC composite coating - Ahmad Alidokht, Sima; Vo, Phuong; Yue, Steve; Chromik, Richard R. (Wear, 2017)
The effect of WC on cold spray deposition and erosive wear performance of Ni-WC composite coatings was studied. WC and Ni powders were fed to the gun from separate hoppers and a blend of Ni-36 vol% WC was sprayed onto mild steel substrates. By using three different WC powder sizes, the effect of WC size on coating build-up and WC retention were tested. Using smaller size WC particle, higher retention of WC into coating was achieved. Using macro-indentation, a relationship between mechanical properties and content of WC was studied. Detailed microstructural analyses and wear loss measurements were conducted to study mechanism involved in solid particle erosion (SPE) of Ni and Ni-WC coatings. One of the Ni-WC coatings with highest WC retention (10.5 vol% WC) was selected for SPE studies. Both Ni and Ni-WC coatings exhibited ductile erosion. Higher erosion resistance of coatings under normal angle compared to oblique angle was related to the formation of a protective tribolayer. It was found that 10.5 vol% WC content was too low to reinforce Ni against erosion under oblique angle. However, under normal angle, the addition of 10.5 vol% WC deteriorated Ni erosion resistance, by preventing tribolayer formation and brittle fracture.
Keywords: cold spray; metal matrix composite; solid particle erosion; surface analysis; WC; subsurface microstructure

Erosion-corrosion mechanism and comparison of erosion-corrosion performance of API steels - Islam, Md. Aminul; Farhat, Zoheir (Wear, 2017)
During the transportation of oil and gas, pipes are exposed to flowing corrosive environment which causes erosion-corrosion. The high degradation rates attributed to this mechanism can create increased challenges to project economy and operation where material integrity, accurate erosion-corrosion rate prediction and long term performance are key concerns. Although the problem caused by the interaction of erosion and corrosion is severe, the mechanism of synergy is still not thoroughly understood because of its complexity. This research focuses on understanding the degradation processes of pipeline steels (API X42, API X70 and API X100) in CO2 containing salt water. The application of cyclic erosion-corrosion allowed the individual contribution of erosion and corrosion components of mass loss to be quantified and mechanisms by which erosion affects corrosion and vice-versa to be identified. The present research also compares the erosion-corrosion performance of different API steels.
Keywords: erosion-corrosion; API steels; synergy; sweet corrosion; degradation mechanism

Equation of state, phonons, and lattice stability of ultrafast warm dense matter - Harbour, L.; Dharma-Wardana, M. W. C.; Klug, D. D.; Lewis, L. J. (Physical Review E, 2017)
Using the two-temperature model for ultrafast matter (UFM), we compare the equation of state, pair-distribution functions g(r), and phonons using the neutral pseudoatom (NPA) model with results from density functional theory (DFT) codes and molecular dynamics (MD) simulations for Al, Li, and Na. The NPA approach uses state-dependent first-principles pseudopotentials from an “all-electron” DFT calculation with finite-T exchange-correlation functional (XCF). It provides pair potentials, structure factors, the “bound” and “free” states, as well as a mean ionization ¯Z unambiguously. These are not easily accessible via DFT+MD calculations which become prohibitive for T/TF exceeding ∼0.6, where TF is the Fermi temperature. Hence, both DFT+MD and NPA methods can be compared up to ∼8eV, while higher T can be addressed via the NPA. The high-Te phonon calculations raise the question of UFM lattice stability and surface ablation in thin UFM samples. The ablation forces in a UFM slab are used to define an “ablation time” competing with phonon formation times in thin UFM samples. Excellent agreement for all properties is found between NPA and standard DFT codes, even for Li where a strongly nonlocal pseudopotential is used in DFT codes. The need to use pseudopotentials appropriate to the ionization state ¯Z is emphasized. The effect of finite-T XCF is illustrated via its effect on the pressure and the electron-density distribution at a nucleus.

Entanglement between more than two hundred macroscopic atomic ensembles in a solid - Zarkeshian, P.; Deshmukh, C.; Sinclair, N.; Goyal, S. K.; Aguilar, G. H.; Lefebvre, P.; Puigibert, M. Grimau; Verma, V. B.; Marsili, F.; Shaw, M. D.; Nam, S. W.; Heshami, K.; et al. (Nature Communications, 2017)
There are both fundamental and practical motivations for studying whether quantum entanglement can exist in macroscopic systems. However, multiparty entanglement is generally fragile and difficult to quantify. Dicke states are multiparty entangled states where a single excitation is delocalized over many systems. Building on previous work on quantum memories for photons, we create a Dicke state in a solid by storing a single photon in a crystal that contains many large atomic ensembles with distinct resonance frequencies. The photon is re-emitted at a well-defined time due to an interference effect analogous to multi-slit diffraction. We derive a lower bound for the number of entangled ensembles based on the contrast of the interference and the single-photon character of the input, and we experimentally demonstrate entanglement between over two hundred ensembles, each containing a billion atoms. We also illustrate the fact that each individual ensemble contains further entanglement.

Energy level alignment at hybridized organic–metal interfaces: the role of many-electron effects - Chen, Yifeng; Tamblyn, Isaac; Quek, Su Ying (The Journal of Physical Chemistry C, 2017)
Hybridized molecule/metal interfaces are ubiquitous in molecular and organic devices. The energy level alignment (ELA) of frontier molecular levels relative to the metal Fermi level (EF) is critical to the conductance and functionality of these devices. However, a clear understanding of the ELA that includes many-electron self-energy effects is lacking. Here, we investigate the many-electron effects on the ELA using state-of-the-art, benchmark GW calculations on prototypical chemisorbed molecules on Au(111), in eleven different geometries. The GW ELA is in good agreement with photoemission for monolayers of benzene diamine on Au(111). We find that in addition to static image charge screening, the frontier levels in most of these geometries are renormalized by additional screening from substrate-mediated intermolecular Coulomb interactions. For weakly chemisorbed systems, such as amines and pyridines on Au, this additional level renormalization (∼1.5 eV) comes solely from static screened exchange energy, allowing us to suggest computationally more tractable schemes to predict the ELA at such interfaces. However, for more strongly chemisorbed thiolate layers, dynamical effects are present. Our ab initio results constitute an important step toward the understanding and manipulation of functional molecular/organic systems for both fundamental studies and applications.

Electronic scan strategy for phased array weather radar using a space–time characterization model - Nguyen, Cuong M.; Chandrasekar, V. (Journal of Atmospheric and Oceanic Technology, 2017)
This paper presents an adaptive scan strategy concept for phased array weather radars (PAWR) with the objective of increasing the scan speed and capturing features of the storm system while maintaining the measurement accuracy. The adaptive scan strategy is developed based on the space–time variability of the storm under observation. Quickly evolving regions are scanned more often and the spatial sampling resolution is matched to the spatial scale. A model that includes the interaction between space and time is used to extract spatial and temporal scales of the medium and to define scanning regions. The temporal scale constrains the radar revisit time, while the measurement accuracy controls the radar’s dwell time. These conditions are employed in a task scheduler that works on a ray-by-ray basis and is designed to balance task priority and radar resources. The scheduler algorithm also includes an optimization procedure for minimizing radar scan time. The model and the scan strategy are demonstrated using simulation data. The results show that the proposed scan strategy can reduce the scan time significantly without compromising data quality.
Keywords: algorithms; radars/radar observations; remote sensing; sampling

Electric-field induced reversible switching of the magnetic easy axis in Co/BiFeO3 on SrTiO3 - Gao, Tieren; Zhang, Xiaohang; Ratcliff, William; Maruyama, Shingo; Murakami, Makoto; Varatharajan, Anbusathaiah; Yamani, Zahra; Chen, Peijie; Wang, Ke; Zhang, Huairuo; Shull, Robert; Bendersky, Leonid A.; et al. (Nano Letters, 2017)
Electric-field (E-field) control of magnetism enabled by multiferroic materials has the potential to revolutionize the landscape of present memory devices plagued with high energy dissipation. To date, this E-field controlled multiferroic scheme has only been demonstrated at room temperature using BiFeO3 films grown on DyScO3, a unique and expensive substrate, which gives rise to a particular ferroelectric domain pattern in BiFeO3. Here, we demonstrate reversible electric-field-induced switching of the magnetic state of the Co layer in Co/BiFeO3 (BFO) (001) thin film heterostructures fabricated on (001) SrTiO3 (STO) substrates. The angular dependence of the coercivity and the remanent magnetization of the Co layer indicates that its easy axis reversibly switches back and forth 45° between the (100) and the (110) crystallographic directions of STO as a result of alternating application of positive and negative voltage pulses between the patterned top Co electrode layer and the (001) SrRuO3 (SRO) layer on which the ferroelectric BFO is epitaxially grown. The coercivity (HC) of the Co layer exhibits a hysteretic behavior between two states as a function of voltage. A mechanism based on the intrinsic magnetoelectric coupling in multiferroic BFO involving projection of antiferromagnetic G-type domains is used to explain the observation. We have also measured the exact canting angle of the G-type domain in strained BFO films for the first time using neutron diffraction. These results suggest a pathway to integrating BFO-based devices on Si wafers for implementing low power consumption and nonvolatile magnetoelectronic devices.
Keywords: electric-field controlled magnetism; exchange coupling; ferroelectric domain; magnetoelectronic device; Multiferroic BiFeO3; neutron diffraction

Efficient internalization of TAT peptide in zwitterionic DOPC phospholipid membrane revealed by neutron diffraction - Chen, Xiaochao; Liu, Shutao; Deme, Bruno; Cristiglio, Viviana; Marquardt, Drew; Weller, Richard; Rao, Pingfan; Wang, Yunqiang; Bradshaw, Jeremy (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2017)
The aim of this study is to investigate the interactions between TAT peptides and a neutral DOPC bilayer by using neutron lamellar diffraction. The distribution of TAT peptides and the perturbation of water distribution across the DOPC bilayer were revealed. When compared to our previous study on an anionic DOPC/DOPS bilayer (X. Chen et al., Biochim Biophys Acta. 2013. 1828 (8), 1982–1988), a much deeper insertion of TAT peptides was found in the hydrophobic core of DOPC bilayer at a depth of 6.0 Å from the center of the bilayer, a position close to the double bond of fatty acyl chain. We conclude that the electrostatic attractions between the positively charged TAT peptides and the negatively charged headgroups of phospholipid are not essential for the direct translocation. Furthermore, the interactions of TAT peptides with the DOPC bilayer were found to vary in a concentration-dependent manner. A limited number of peptides first associate with the phosphate moieties on the lipid headgroups by using the guanidinium ions pairing. Then the energetically favorable water defect structures are adopted to maintain the arginine residues hydrated by drawing water molecules and lipid headgroups into the bilayer core. Such bilayer deformations consequently lead to the deep intercalation of TAT peptides into the bilayer core. Once a threshold concentration of TAT peptide in the bilayer is reached, a significant rearrangement of bilayer will happen and steady-state water pores will form.
Keywords: cell penetrating peptide; TAT peptide; neutron diffraction; phospholipid

Effects of quadratic drag on natural convection in a tilted porous layer with uniform heat flux from the side - Alloui, Z.; Rebhi, R.; Mamou, M.; Vasseur, P. (International Journal of Heat and Mass Transfer, 2017)
This paper reports a numerical study of natural convection in an inclined enclosure filled with a fluid-saturated porous medium. The Darcy-Dupuit model, which includes effects of flow form drag, is used to describe the flow in the porous layer. Thermal boundary conditions of the Neumann type are applied on the long side walls of the enclosure while the short ones are assumed adiabatic. The governing parameters for the problem are the Rayleigh number R, inclination angle φ, form drag parameter G and aspect ratio of the cavity A. A semi-analytical solution, valid for an infinite layer (A ≫ 1), is derived on the basis of the parallel flow approximation. It is demonstrated that both the inclination of the layer and the form drag parameter, have a strong influence on the strength of the natural convection heat transfer within the enclosure. The effect of form drag parameter on the existence of multiple steady state solutions, that are possible for an enclosure slightly inclined around the horizontal position, is investigated. For boundary layer flows in a vertical cavity it is demonstrated that, in the limit of Dupuit regime, the Nusselt number is given by Nu=0.556(R/G)1/4. A good agreement is found between the predictions of the parallel flow approximation and the numerical results obtained by solving the full governing equations.
Keywords: natural convection; tilted porous cavity; form drag effects; heat transfer

Effects of nodal planes on strong-field ionization and high-order-harmonic generation in ring-type molecules - Alharbi, A. F.; Boguslavskiy, A. E.; Thiré, N.; Thekkadath, G. S.; Patchkovskii, S.; Schmidt, B. E.; Légaré, F.; Brabec, T.; Bhardwaj, V. R.; Spanner, M. (Physical Review A, 2017)
We measure the ellipticity dependence of high-harmonic generation (HHG) from unaligned gas-phase ensembles of the five-membered ring molecules 2,3-dihydrofuran (C4H6O), furan (C4H4O), and thiophene (C4H4S). As is normally the case, the HHG emission is suppressed for increased ellipticity since the recollision wave packet leading to HHG is steered away from the parent ion for large ellipticity. However, through comparison with computations of the first step in HHG, namely, strong-field ionization (SFI), we show that the observed differences in the ellipticity dependence for the three molecular species reflect the lateral momentum distributions of the continuum electron responsible for HHG, which in turn provides information about the particular orientation between the molecular axis and the laser field that maximizes the SFI probability. Strikingly, and contrary to the conventional wisdom in the strong-field community, we find that for furan and thiophene the most probable orientation for SFI occurs when the electric field of the laser is aligned near a nodal plane of the corresponding ionizing orbital. 2,3-dihydrofuran, on the other hand, follows the standard expectation that the most probable orientation for SFI occurs when the electric field is aligned away from any nodal plane.

Effects of H2O and CO2 diluted oxidizer on the structure and shape of laminar coflow syngas diffusion flames - Xu, Huanhuan; Liu, Fengshan; Sun, Shaozeng; Zhao, Yijun; Meng, Shun; Tang, Wenbo (Combustion and Flame, 2017)
The effects of up to 30% H2O and CO2 replacement of N2 in air on the structure and shape of laminar coflow syngas (COH2) diffusion flames were experimentally and numerically studied. Temperatures along the flame centerline were measured using a type-B thermocouple. The OH*-chemiluminescence and flame luminance were captured respectively by an intensified CCD camera and a CCD camera to determine the flame height and radii. The syngas diffusion flames were numerically modeled using detailed thermal and transport properties and the chemical reaction mechanism of Davis et al. (2005). Four pairs of artificial species were introduced in additional numerical calculations to isolate the chemical, thermal, transport, and radiative effects of H2O and CO2. The experimental and numerical results show that H2O and CO2 replacement of N2 in the oxidizer reduce the peak flame temperature, but they influence the flame centerline temperature distributions differently. The thermal and radiative effects of both H2O and CO2 addition decrease the flame temperatures. The chemical and transport effects of CO2 and H2O affect flame temperatures differently. H2O addition promotes the OH concentration though H + O2 = O + OH and O + H2O = 2OH, while CO2 addition decreases the OH concentration by suppressing those reactions. The higher concentrations of OH under H2O addition signify higher combustion intensity and hence lead to decreased flame height and radius. In contrast, the addition of CO2 suppresses flame temperature and the overall combustion process, resulting in increased flame height and radius.
Keywords: syngas; H2O and CO2 dilution; laminar coflow diffusion flame; flame structure; flame shape

Effective interactions and adsorption of heterocyclic aromatic hydrocarbons in Kaolinite organic solutions studied by 3D-RISM-KH molecular theory of solvation - Hlushak, Stepan; Kovalenko, Andriy (The Journal of Physical Chemistry C, 2017)
We employ the molecular theory of solvation also known as the three-dimensional reference interaction site model with the Kovalenko–Hirata closure relation (3D-RISM-KH) to study adsorption of several heterocyclic aromatic hydrocarbons (acridine, benzothiophene, carbazole, dibenzothiophene, indole, and phenanthridine), which are intended to represent bitumen fragments on the surfaces of a single-sheet kaolinite nanoparticle in cyclohexane and toluene solvents. In addition to adsorption, we also examine solvent-mediated effective interactions between two kaolinite nanoparticles in organic and aqueous solutions. The proposed adsorption model serves as a simple prototype of suspensions formed during nonaqueous extraction of bitumen from oil sands of the Athabasca Basin. Using the proposed computational approach, excess adsorption isotherms of bitumen fragments on two different faces of kaolinite were calculated and compared in cyclohexane and toluene solvents at several temperatures. Almost all the studied molecules show strong preference for adsorption on the octahedral aluminum hydroxide surface of kaolinite. While adsorption of the molecules on the tetrahedral silicon oxide surface is weaker, it is still significant compared to the octahedral surface and for some of the studied molecules adsorption appears to be stronger than for the octahedral surface. Due to the better surface and bulk solvation properties of toluene, the adsorption of the bitumen fragments in toluene is weaker than in cyclohexane. Potentials of mean force between kaolinite nanoplatelets in cyclohexane at several temperatures were calculated using the 3D-RISM-KH molecular theory of solvation. Evaluation of effective interactions by conventional molecular simulation techniques generally requires costly free energy integration and therefore is usually avoided by adopting simple and often unrealistic semiempirical effective potentials. On the other hand, the 3D-RISM-KH molecular theory of solvation offers a fully atomistic description with all-atom force fields and notable performance advantages over molecular simulations. Obtained in this way potentials of mean force in organic solvents exhibit complex oscillating behavior and generally possess deeper main minima and smaller aggregation barriers than the corresponding potentials in aqueous solution.

Effect of surface organic coatings of cellulose nanocrystals on the viability of mammalian cell lines - Jimenez, Ambar; Jaramillo, Francesca; Hemraz, Usha; Boluk, Yaman; Ckless, Karina; Sunasee, Rajesh (Nanotechnology, Science and Applications, 2017)
Cellulose nanocrystals (CNCs) have emerged as promising candidates for a number of bio-applications. Surface modification of CNCs continues to gain significant research interest as it imparts new properties to the surface of the nanocrystals for the design of multifunctional CNCs-based materials. A small chemical surface modification can potentially lead to drastic behavioral changes of cell-material interactions thereby affecting the intended bio-application. In this work, unmodified CNCs were covalently decorated with four different organic moieties such as a diaminobutane fragment, a cyclic oligosaccharide (β-cyclodextrin), a thermoresponsive polymer (poly[N-isopropylacrylamide]), and a cationic aminomethacrylamide-based polymer using different synthetic covalent methods. The effect of surface coatings of CNCs and the respective dose-response of the above organic moieties on the cell viability were evaluated on mammalian cell cultures (J774A.1 and MFC-7), using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and lactate dehydrogenase assays. Overall, the results indicated that cells exposed to surface-coated CNCs for 24 h did not display major changes in cell viability, membrane permeability as well as cell morphology. However, with longer exposure, all these parameters were somewhat affected, which appears not to be correlated with either anionic or cationic surface coatings of CNCs used in this study.
Keywords: cellulose nanocrystals; surface coating; cell viability; MTT; LDH

Editorial for JRRT ICRI special edition - Magel, Eric (Proceedings of the Institution of Mechanical Engineers, Part F: Journal of Rail and Rapid Transit, 2017)
The International Collaborative Research Initiative (ICRI) on Rolling Contact Fatigue (RCF) and Wear of Rails and Wheels is a virtual community of academics, consultants, researchers, and engineers working in, or having significant involvement with, the international railway industry. The ICRI, formed in 2013, brings together roughly 150 people from 80 organizations in 16 countries to collaborate on topics of mutual interest by leveraging current or future, already funded work. The ICRI has been likened to a “coffee house” where people meet, share and learn what they can, and participate as much as they can for as long as they are seeing some benefit. Much of the interaction is web-based, but there have also been eight half- to full-day workshops at various locations in the United States and Europe, usually in conjunction with other international meetings or conferences.

Early spectra of the gravitational wave source GW170817: evolution of a neutron star merger - Shappee, B. J.; Simon, J. D.; Drout, M. R.; Piro, A. L.; Morrell, N.; Prieto, J. L.; Kasen, D.; Holoien, T. W.-S.; Kollmeier, J. A.; Kelson, D. D.; Coulter, D. A.; Foley, R. J.; et al. (Science, 2017)
On 17 August 2017, Swope Supernova Survey 2017a (SSS17a) was discovered as the optical counterpart of the binary neutron star gravitational wave event GW170817. We report time-series spectroscopy of SSS17a from 11.75 hours until 8.5 days after the merger. Over the first hour of observations, the ejecta rapidly expanded and cooled. Applying blackbody fits to the spectra, we measured the photosphere cooling from 11.000+3400-99 to 9300+300-300 kelvin, and determined a photospheric velocity of roughly 30% of the speed of light. The spectra of SSS17a began displaying broad features after 1.46 days and evolved qualitatively over each subsequent day, with distinct blue (early-time) and red (late-time) components. The late-time component is consistent with theoretical models of r-process–enriched neutron star ejecta, whereas the blue component requires high-velocity, lanthanide-free material.

Dynamical persistence of active sites identified in maltose-binding protein - Nikolić, Dragan; Kovačev-Nikolić, Violeta (Journal of Molecular Modeling, 2017)
This study identifies dynamical properties of maltose-binding protein (MBP) useful in unveiling active site residues susceptible to ligand binding. The described methodology has been previously used in support of novel topological techniques of persistent homology and statistical inference in complex, multi-scale, high-dimensional data often encountered in computational biophysics. Here we outline a computational protocol that is based on the anisotropic elastic network models of 14 all-atom three-dimensional protein structures. We introduce the notion of dynamical distance matrices as a measure of correlated interactions among 370 amino acid residues that constitute a single protein. The dynamical distance matrices serve as an input for a persistent homology suite of codes to further distinguish a small subset of residues with high affinity for ligand binding and allosteric activity. In addition, we show that ligand-free closed MBP structures require lower deformation energies than open MBP structures, which may be used in categorization of time-evolving molecular dynamics structures. Analysis of the most probable allosteric coupling pathways between active site residues and the protein exterior is also presented.
Keywords: anisotropic elastic network model; pairwise correlations; dynamical distances; maltose-binding protein; ligand; allosteric pathway

Dynamic wavefront rotation in the attosecond lighthouse - Balogh, Emeric; Zhang, Chunmei; Ruchon, Thierry; Hergott, Jean-Francois; Quere, Fabien; Corkum, Paul; Nam, Chang Hee; Kim, Kyung Taec (Optica, 2017)
Attosecond pulses propagating in different directions, generated in a rotating wavefront of a driving laser field, can provide a source of multiple isolated attosecond pulses. Clear spatial separation of the attosecond pulses is attained if the divergence of the individual attosecond pulse is smaller than their angular separation, which is limited by the bandwidth of the driving laser pulse. Here we demonstrate both experimentally and numerically that an additional wavefront rotation is imposed during the propagation of the driving laser pulse in a highly ionizing medium. This dynamic wavefront rotation enables the generation of the isolated attosecond pulse even in the case when the conditions derived from a linear diffraction theory do not permit the angular separation. The described nonlinear phenomenon has its roots in the half-cycle ionization events, and may open up new ways to study strong field processes in highly ionizing media.

Dynamic positioning of vessels using a UKF-based observer and an NMPC-based controller - Jayasiri, Awantha; Nandan, Anirudh; Imtiaz, Syed; Spencer, Don; Islam, Shameem; Ahmed, Salim (IEEE Transactions on Automation Science and Engineering, 2017)
This paper presents a solution to the problem of dynamic positioning (DP) of vessels in ice-infested environments using a nonlinear observer and a finite-horizon optimal controlbased approach. An unscented Kalman filter-based nonlinear observer is developed to estimate both the vessel states and the unknown inputs, such as the ice load. To perform better control and disturbance rejection, a nonlinear model predictive controller is employed for DP. The developed modules are integrated with a commercial vessel maneuvering software, and promising realtime results are generated.

Dynamic fragmentation and blast from a reactive material solid - Zhang, Fan; Gauthier, Maxime; Cojocaru, Cristian V. (Propellants, Explosives, Pyrotechnics, 2017)
Structural reactive material (SRM) is consolidated from a fine granular mixture of reactive materials towards the mixture theoretical maximum density with little porosity, thus bearing both high energy density and mechanical strength. A reactive hot spot concept was investigated for fine fragmentation of a SRM solid under explosive loading to augment air blast through rapid reaction of fine SRM fragments. In this concept, micro‐sized reactive materials were distributed in a fuel‐rich SRM solid, such as MoO3 particles consolidated in a particulate aluminum base in 10Al+MoO3. Intermetallic reactions of micro‐sized MoO3 and nearby Al under explosive loading created heat and gas products to form microscale hot spots that initiated local fractures leading to fine fragments of the rest of Al. The SRM solid was made of a thick‐walled cylindrical casing, containing a high explosive in a detonation pressure range of 25–34 GPa with a casing‐to‐explosive mass ratio of 1.78. Experiments in a cylindrical chamber demonstrated the presence of a large amount of fine SRM fragments, whose reaction promptly after detonation significantly enhanced the primary and near field blast wave, as compared to the results from a baseline pure Al‐cased charge, thus indicating the feasibility of the concept.

Direct synthesis of carbon nanotubes on metallic foams as a cathode material with high mass load for lithium–air batteries - Ionescu, Mihnea Ioan (RSC Advances, 2017)
Carbon nanotubes (CNTs) were synthesized directly on metallic substrates by spray pyrolysis chemical vapor deposition. Cathodes containing CNTs with mass loads up to 25.9 mg cm−2 were investigated for Li–air batteries and exhibited a maximum specific discharge capacity of 3348 mA h g−1 for a carbon loading of 4.2 mg cm−2. These results demonstrate that carbon nanomaterials present electrocatalytic activity for the cathode reaction and can be deposited and used directly as cathode materials for developing energy storage devices with improved performances.

Direct measurement of sequence-dependent transition path times and conformational diffusion in DNA duplex formation - Neupane, Krishna; Wang, Feng; Woodside, Michael T. (Proceedings of the National Academy of Sciences, 2017)
The conformational diffusion coefficient, D, sets the timescale for microscopic structural changes during folding transitions in biomolecules like nucleic acids and proteins. D encodes significant information about the folding dynamics such as the roughness of the energy landscape governing the folding and the level of internal friction in the molecule, but it is challenging to measure. The most sensitive measure of D is the time required to cross the energy barrier that dominates folding kinetics, known as the transition path time. To investigate the sequence dependence of D in DNA duplex formation, we measured individual transition paths from equilibrium folding trajectories of single DNA hairpins held under tension in high-resolution optical tweezers. Studying hairpins with the same helix length but with G:C base-pair content varying from 0 to 100%, we determined both the average time to cross the transition paths, τtp, and the distribution of individual transit times, PTP(t). We then estimated D from both τtp and PTP(t) from theories assuming one-dimensional diffusive motion over a harmonic barrier. τtp decreased roughly linearly with the G:C content of the hairpin helix, being 50% longer for hairpins with only A:T base pairs than for those with only G:C base pairs. Conversely, D increased linearly with helix G:C content, roughly doubling as the G:C content increased from 0 to 100%. These results reveal that G:C base pairs form faster than A:T base pairs because of faster conformational diffusion, possibly reflecting lower torsional barriers, and demonstrate the power of transition path measurements for elucidating the microscopic determinants of folding.

Differences between measured and reported volatile organic compound emissions from oil sands facilities in Alberta, Canada - Li, Shao-Meng; Leithead, Amy; Moussa, Samar G.; Liggio, John; Moran, Michael D.; Wang, Daniel; Hayden, Katherine; Darlington, Andrea; Gordon, Mark; Staebler, Ralf; Makar, Paul A.; Stroud, Craig A.; et al. (Proceedings of the National Academy of Sciences, 2017)
Large-scale oil production from oil sands deposits in Alberta, Canada has raised concerns about environmental impacts, such as the magnitude of air pollution emissions. This paper reports compound emission rates (E) for 69–89 nonbiogenic volatile organic compounds (VOCs) for each of four surface mining facilities, determined with a top-down approach using aircraft measurements in the summer of 2013. The aggregate emission rate (aE) of the nonbiogenic VOCs ranged from 50 ± 14 to 70 ± 22 t/d depending on the facility. In comparison, equivalent VOC emission rates reported to the Canadian National Pollutant Release Inventory (NPRI) using accepted estimation methods were lower than the aE values by factors of 2.0 ± 0.6, 3.1 ± 1.1, 4.5 ± 1.5, and 4.1 ± 1.6 for the four facilities, indicating underestimation in the reported VOC emissions. For 11 of the combined 93 VOC species reported by all four facilities, the reported emission rate and E were similar; but for the other 82 species, the reported emission rate was lower than E. The median ratio of E to that reported for all species by a facility ranged from 4.5 to 375 depending on the facility. Moreover, between 9 and 53 VOCs, for which there are existing reporting requirements to the NPRI, were not included in the facility emission reports. The comparisons between the emission reports and measurement-based emission rates indicate that improvements to VOC emission estimation methods would enhance the accuracy and completeness of emission estimates and their applicability to environmental impact assessments of oil sands developments.

DHIGLS: DRAO H i intermediate Galactic latitude survey - Blagrave, K.; Martin, P. G.; Joncas, G.; Kothes, R.; Stil, J. M.; Miville-Deschênes, M. A.; Lockman, Felix J.; Taylor, A. R. (The Astrophysical Journal, 2017)
Observations of Galactic H i gas for seven targeted regions at intermediate Galactic latitude are presented at angular resolution using data from the DRAO Synthesis Telescope (ST) and the Green Bank Telescope (GBT). The DHIGLS data are the most extensive arcminute-resolution measurements of the diffuse atomic interstellar medium beyond those in the Galactic plane. The acquisition, reduction, calibration, and mosaicking of the DRAO ST data and the cross calibration and incorporation of the short-spacing information from the GBT are described. The high quality of the resulting DHIGLS products enables a variety of new studies in directions of low Galactic column density. We analyze the angular power spectra of maps of the integrated H i emission (column density) from the data cubes for several distinct velocity ranges. In fitting power-spectrum models based on a power law, but including the effects of the synthesized beam and noise at high spatial frequencies, we find exponents ranging from -2.5 to -3.0. Power spectra of maps of the centroid velocity for these components give similar results. These exponents are interpreted as being representative of the three-dimensional density and velocity fields of the atomic gas, respectively. We find evidence for dramatic changes in the H i structures in channel maps over even small changes in velocity. This narrow line emission has counterparts in absorption spectra against bright background radio sources, quantifying that the gas is cold and dense and can be identified as the cold neutral medium phase. Fully reduced DHIGLS H i data cubes and other data products are available at www.cita.utoronto.ca/DHIGLS. ï¿½ 2017.

Development of a non-intrusive ultrasound ice sccretion sensor to detect and quantify ice accretion severity - Fuleki, Dan; Sun, Zhigang; Wu, Jason (Kuo-Ting); Miller, Grael (9th AIAA Atmospheric and Space Environments Conference, 2017)
Supercooled liquid water and ice crystals are atmospheric icing conditions that degrade flight safety of aircraft by affecting the performance of the airframe, air data probes and engines. A key way this threat is mitigated is by using icing detectors on the aircraft to either detect the environment or to detect when ice is accreted on a surface. This information allows the aircraft anti-icing systems to be enabled or have the aircraft exit the environment. This paper discusses a non-intrusive technology developed at NRC that can detect ice accretion on a surface and quantify its severity. The technology features a custom thin-film ultrasound transducer made to withstand in-flight conditions, combined with proprietary signal processing algorithms. Initial development was carried out in environmental chamber and icing wind tunnel tests, exposing the prototype sensors to a range of temperature, humidity, altitude and icing conditions. This technology, referred to as the Ultrasound Ice Accretion Sensor (UIAS), was then implemented in a collaborative NASA/Honeywell/ICC ice crystal icing test of a Honeywell/Lycoming turbofan aircraft engine, model ALF502. This was a full scale, altitude engine test which simulated a wide range of inflight ice crystal icing conditions. The UIAS’s were not only effective in detecting when ice had accreted but were also able to estimate the severity of the icing. This detection happened in a very short period of time; much sooner than the early performance warning indicators seen from engine and test cell instrumentation, which is key in providing the aircraft and pilot time to address the icing threat.

Temperature dependence mitigation in stationary Fourier-transform on-chip spectrometers - Herrero-Bermello, Alaine; Velasco, Aitor V.; Podmore, Hugh; Cheben, Pavel; Schmid, Jens H.; Janz, Siegfried; Calvo, María L.; Xu, Dan-Xia; Scott, Alan; Corredera, Pedro (Optics Letters, 2017)
We present two techniques for mitigating the effects of temperature drifts in waveguide spatial heterodyne Fourier-transform on-chip spectrometers. In high-resolution devices, large optical path length differences result in an increased sensitivity to temperature variations and impose stringent requirements on the thermal stabilization system. In order to overcome this limitation, here we experimentally demonstrate two new temperature mitigation techniques based on a temperature-sensitive calibration and phase error correction. The spectrometer chip under analysis comprises an array of 32 Mach–Zehnder interferometers fabricated on a silicon-on-insulator platform. The optical path delays are implemented as microphotonic spirals of linearly increasing length up to 3.779 cm, yielding a spectral resolution of 17 pm. We demonstrate that the degradation in retrieved spectra caused by temperature drift is effectively eliminated by temperature-sensitive calibration and phase error correction.

Flexibility of dehydrated zeolite-X pores quantified by quantum modeling - Mercier, Patrick H. J.; Le Page, Yvon (Acta Crystallographica Section A: Foundations and Advances, 2017)
Keywords: ab-initio simulations of materials; zeolite

Using machine translation for academic writing in English as a second language: results of an exploratory study on linguistic quality - Goulet, Marie-Josée; Simard, Michel; Parra Escartín, Carla; O’brien, Sharon (ASp, 2017)
Nous explorons dans cet article la pertinence d’utiliser la traduction automatique (TA) comme outil d’aide à la rédaction scientifique en anglais langue seconde (ALS). L’expérience, à laquelle ont participé dix chercheurs, comprenait deux tâches : la rédaction d’un texte en ALS et la rédaction d’un texte en langue maternelle. Ce dernier a ensuite été traduit automatiquement et post-édité par le participant. Par la suite, nous avons évalué la qualité linguistique des textes produits dans les deux situations, à partir d’une analyse des modifications linguistiques effectuées par une réviseure professionnelle. Selon nos résultats, la qualité linguistique des textes est sensiblement la même dans les deux situations, tandis que des différences apparaissent dans les dimensions linguistiques et dans les types d’unités touchées. L’article se termine par une réflexion sur les facteurs pouvant influencer ces résultats. Nous concluons en réitérant la pertinence d’étudier l’utilisation de la TA pour la rédaction d’articles en anglais de spécialité.
Keywords: anglais langue seconde; post-édition; rédaction en anglais langue seconde; rédaction scientifique; traduction automatique; academic writing; English as a second language; machine translation; post-editing; writing in English as a second language

An overview of studies to assess the thermal and hygrothermal performance of highly insulated and zero energy ready wall assemblies - Bartko, Michal; Jonkman, Robert; Lacasse, Michael A.; Moore, Travis; Parekh, Anil; Plescia, Silvio (2017)
A key component of energy efficient homes in the ever challenging climate of Canada is the highly insulated and well-designed wall assembly. Over the years, residential walls have been constructed using increasingly more insulation. The increased levels of insulation have offered a major opportunity to reduce heat losses in homes thereby significantly improving their energy efficiency and have thus permitted compliance with requirements for high performance housing standards such as those for ENERGY STAR, R-2000, Net-Zero Energy Ready homes and homes conforming to the Passive House Canada concept. However given the use of higher insulation levels, homebuilders face many challenges with the issues that arise from changes in traditional construction practice, in the case of this paper being concerned with the overall moisture performance, and hence durability, of wall assemblies. Canadian building code authorities also require proven evidence that highly insulated wall systems will not be adversely affected by increases to insulation levels given the many different Canadian climates in which they are expected to perform over the long term. Building code authorities are also concerned with the possible effects of climate change on building design, and consequently, there is a growing need for information related to the resilience of wall assemblies for use in high performance housing and small buildings. Several studies have been undertaken in recent years to demonstrate the thermal and hygrothermal performance of highly insulated wood frame wall assemblies and to determine whether these walls perform as well as or better than NECB compliant walls when subjected to Canadian climate extremes.
Keywords: field study; thermal response; hygorthermal; response; highly insulated; wood-frame walls

Approach to assessing the long-term performance of wall assemblies: durability of low-rise wood-frame walls - Lacasse, Michael A.; Motelli, Martin (XIV DBMC: 14th International Conference on Durability of Building Materials and Components, 29-31 May 2017, Ghent University, Belgium, 2017)
The long-term performance or durability of wall assemblies in respect to the moisture management of components of which comprise the wall depends on the hygrothermal response of the wall to local climate loads. Critical factors in estimating the longevity of wood frame structures include limiting the temperature range, wood moisture content and time of exposure to conditions suitable for the onset, growth and propagation of mould and rot to occur. Several approaches to assessing the vulnerability of wood frame structures to deterioration have been developed in recent years some of which suggest applying a limit-states design (LSD) approach to the performance assessment of the assembly. In this paper emphasis is placed on a further development of the LSD approach within the context of requirements set out in ISO 13823 “General principles on the design of structures for durability”. An example is presented in which the LSD approach is applied to low-rise wood-frame walls, as are built in North America, and that incorporate drainage components, such components forming part of a rain screen wall assembly. The use of this approach permits determining whether wall assemblies incorporating novel components are suitable for use in walls exposed to climates having extreme wind-driven rain conditions. The performance assessment is based on the results derived from hygrothermal simulation.
Keywords: drainage components; limit-states design; long-term performance; wall assembly; wood frame

In vitro evaluation of archaeosome vehicles for transdermal vaccine delivery - Jia, Yimei; Mccluskie, Michael J.; Zhang, Dongling; Monette, Robert; Iqbal, Umar; Moreno, Maria; Sauvageau, Janelle; Williams, Dean; Deschatelets, Lise; Jakubek, Zygmunt J.; Krishnan, Lakshmi (Journal of Liposome Research, 2017)
Archaeosomes composed of archaeal total polar lipids (TPL) or semi-synthetic analog vesicles have been used as vaccine adjuvants and delivery systems in animal models for many years. Typically administered by intramuscular or subcutaneous injections, archaeosomes can induce robust, long-lasting humoral and cell-mediated immune responses against entrapped antigens and provide protection in murine models of infectious disease and cancer. Herein, we evaluated various archaeosomes for transdermal delivery, since this route may help eliminate needle-stick injuries and needle re-use, and therefore increase patient compliance. Archaeosomes composed of TPL from different archaea (Halobacterium salinarum, Methanobrevibacter smithii, Haloferax volcanii) and various semi-synthetic glycolipid combinations were evaluated for their ability to diffuse across the skin barrier using an ex vivo pig skin model and the results were compared to conventional synthetic ester liposomes. Physicochemical characteristics were determined for selected formulations including vesicle size, size distribution, zeta potential, fluidity, antigen (ovalbumin) incorporation efficiency and release. Archaeosomes, in particular those composed of M. smithii TPL or the synthetic glycolipid sulfated S-lactosylarchaeol (SLA) mixed with uncharged glycolipid lactosyl archaeol (LA), appeared to be effective carriers for ovalbumin, achieving much better antigen distribution and vesicle accumulation in the skin epidermis than conventional liposomes. The enhanced skin permeation of archaeosomes may be attributed to their chemical structure and physicochemical properties such as particle size, surface charge, stability, and fluidity of their lipid bilayer.
Keywords: archaeosome; archaeal polar lipids; archaeol; skin diffusion; transdermal; vaccine; adjuvant

Pilot head and neck response to helicopter whole body vibration and head-supported mass - Law, Andrew J.; Wright Beatty, Heather E.; Keillor, Jocelyn; Wickramasinghe, Viresh (AHS International Forum 73 Proceedings, 2017)
Given the prevalence and severity of neck pain among helicopter pilots, the effects of helicopter whole body vibration (WBV) and pilot head-supported mass (HSM) on neck muscle strain and fatigue need to be understood to establish effective mitigating solutions and/or countermeasure protocols. The present study provides a preliminary assessment of pilot head and neck responses under different WBV conditions (i.e. Engines Off, Ground Idle, Hover, and Cruise) and HSM conditions (i.e. Helmet-only, Helmet+NVG) during flight operations on a Bell 412 helicopter. For both pilots, average neck electromyography (EMG) amplitudes were highest during the maximum WBV condition (Cruise) and the maximum HSM condition (Helmet+NVG). This indicates that helicopter WBV and HSM conditions jointly contribute to higher neck muscle loading, which may coincide with elevated neck muscle discomfort, strain, and fatigue. Therefore, effective mitigating solutions (e.g. vibration exposure limits, operational guidelines) must account for the combined effects of WBV and HSM to reduce or prevent neck pain among helicopter pilots.

Single pass laser cold-wire welding of thick section AA6061-T6 aluminum alloy - Mirakhorli, F.; Nadeau, F.; Caron Guillemette, Gabriel (LIA (Laser Institute of America) eNewsletter, 2017)
Extending applications of thick aluminum alloys in various industrial market segments necessitates the development of advanced welding technologies to ensure high integrity welds. In the present work, single pass laser cold-wire welding of 4.8 mm thick AA6061-T6 aluminum plates was carried out in the butt joint configuration. The effect of laser welding parameters such as welding speed, continuous-wave (CW) and pulse-wave (PW) modes (Table 1) on weld integrity, microstructure and mechanical properties was evaluated. Porosity, underfill and excessive penetration were observed as the main imperfections in the fusion zone as displayed in X-Ray photographs (Figure 1) and metallographic pictures (Figure 2). However, the underfill depth and excessive penetration height in the joints manufactured at different welding conditions met the specifications of ISO 13919 standard. Porosity qualifications i.e., Max. porosity and cluster dimensions, and porosity area fraction, in PW mode passed the minimum requirement criteria of the stringent ISO 13919-2 standard quality class (level B), while these porosity qualifications in CW, at 3 m/min welding speed just passed the quality level C criteria as displayed in Table 2. By increasing the welding speed from 3 m/min to 4.5 m/min in CW mode, the maximum single and cluster porosity dimensions, and porosity area fraction are reduced significantly. These results indicate that both laser mode and travel speed can influence the porosity formation during laser cold-wire welding of AA6061-T6 aluminum plate. Welding in PW mode versus CW mode, at the same travel speed and at a similar average power can reduce the porosity area fraction by ~64%. Increasing the welding speed from 3 to 4.5 m/min in CW laser mode reduce the porosity area fraction by ~75%. This can be due to an increase in keyhole stability at higher welding speed.

The effect of sodium chloride on the nanoparticles observed in a laminar methane diffusion flame - Moallemi, Alireza; Kazemimanesh, Mohsen; Kostiuk, Larry W.; Olfert, Jason S. (Combustion and Flame, 2017)
The occurrence of nano-particles along the centerline of a laminar co-flow diffusion flame with a fuel jet diameter of 10 mm was investigated under two conditions: a methane diffusion flame with and without the addition of NaCl particles of the order of 100 nm in diameter in the fuel flow. Samples of nano-particles from different heights above the burner (HAB) were extracted through a small pinhole in a tubular probe and were immediately diluted several thousand times. Subsequent to sampling, particles were directed to a scanning mobility particle sizer (SMPS) to measure the particle size distribution. A rapid thermocouple insertion method was used to measure the temperature of the flow at different axial and radial positions. Extracted nano-particles from different HABs were collected on grids and their structure was studied using transmission electron microscopy (TEM). The spatial temperature field in the flow was not significantly changed with the addition of NaCl particles to the fuel flow. Particle size distributions for the methane-only flame showed different stages of nano-particle evolution, from inception and surface growth to coagulation and oxidation. TEM images showed that primary soot particles had core–shell structures. Particle size distributions for the methane–NaCl flame showed that considerable concentrations of sub-10 nm particles appeared at heights above the burner where soot inception is typically not expected in a methane flame. The TEM images showed that the structure of these nano-particles was similar to cubical NaCl particles. For higher HABs the particle size distribution followed a similar trend as the methane-only flame, except for regions of the flame where coagulation is the dominant process. The addition of NaCl reduced the mobility diameter of soot particles and increased their number concentration. These results indicate that the addition of NaCl to the flame reduces the coagulation between soot primary particles.
Keywords: diffusion flame; soot; NaCl particles; particle size distribution

Effects of salinity, growing media, and photoperiod on bioelectricity production in plant microbial fuel cells with weeping alkaligrass - Md khudzari, J.; Kurian, J.; Gariépy, Y.; Tartakovsky, B.; Raghavan, G. S. V. (Biomass and Bioenergy, 2017)
This study investigated the potential for bioelectricity production of a salt-tolerant plant, the weeping alkaligrass (Puccinellia distans), in a plant microbial fuel cell (MFC). Air-cathode MFCs with a carbon felt anode were assembled in a cylindrical vessel. The MFCs were operated using growing media of different dry organic matter (OM) mass fractions: potting mix (OM: 89%) and sandy loam (OM: 8%), and treated with different NaCl concentrations of 0, 6, and 12 kg m−3. MFC performance was best at a salinity of 6 kg m−3. Over 114 days, the highest power output was obtained from plant MFC (PMFC) in potting mix at 83.7 mW m−2 cathode area with an average power of 12.78 mW m−2, followed by PMFC in sandy loam (maximum: 8.59 mW m−2, average: 8.35 mW m−2). The total biomass production of alkaligrass was 5–25% higher in the potting mix, when compared to the sandy loam. The presence of alkaligrass in PMFC increased the bioelectricity production by 14-fold compared to that of soil MFC (SMFC). In addition to the standard photoperiod of 16/8 h (light/dark), the MFCs were also operated under 24/0 h, 9/15 h, and 0/24 h photoperiods. Power outputs of 9/15 and 0/24 h were clearly decreased due to the effect of photoperiod, while the power outputs of 24/0 and 16/8 h were similar with some evidence of light-related inhibition. Frequent changes in the photoperiod test affected bioelectricity production and thus, a longer recovery time is recommended to reduce the adverse impact of the changes.

Vibrational spectroscopy and thermophysical properties of ultralow sulfur diesel: alternative fuel binary blends - Petrucci, Thiago; Michaelian, Kirk H.; Gieleciak, Rafal; Shen, Jun; Zhou, Jianqin; Gu, Caikang; Neill, W. Stuart; Baesso, Mauro L.; Malacarne, Luis C.; Astrath, Nelson G. C. (Energy & Fuels, 2017)
Four alternative fuels (AF) were blended with ultralow sulfur diesel (ULSD) at five different proportions (10, 20, 30, 50, and 100 vol % AF) to create 20 binary mixtures in this work. Two renewable jet AFs and two renewable diesel AFs were investigated. Interactions between the components in the mixtures were analyzed by means of spectroscopy (Raman, near-infrared), thermophysical (thermal diffusivity, thermo-optic coefficient), and physical (density) techniques. Correlations among the data were investigated using principal component analysis and partial least-squares regression. Trends in Raman intensities and band positions as well as thermophysical properties showed that the AF/ULSD blends resembled two-component mixtures despite the known complexities of the constituents. Specifically, spectra combined according to the percentages of the components in each mixture; thermophysical and physical properties exhibited similar behavior. The spectra showed strong correlations with all three physical properties, creating the possibility for predicting the properties of similar AF/ULSD mixtures. These properties are governed by the chemical compositions of the fuels.

A numerical investigation on NO2 formation reaction pathway in a natural gas–diesel dual fuel engine - Li, Yu; Li, Hailin; Guo, Hongsheng (Combustion and Flame, 2017)
This paper numerically investigated the NO2 formation pathway in a natural gas (NG)–diesel dual fuel engine using a computational fluid dynamics (CFD) model CONVERGE. The fuel chemistry coupled was a reduced primary reference fuel (PRF) mechanism consisting of 45 species and 142 reactions including the NOx mechanism from GRI chemistry. The NO2 formation pathway was investigated by examining the rate of production (ROP) of key species dominating NO2 formation in each cell. The ROP of the key species was further processed to derive the representative creation reactions (RCR) of NO2 (RCRNO2). The simulation revealed that the NO2 produced during main combustion stage was formed in the hot combustion products of n-heptane spray through reaction pathway C7H15 → CH2O → HCO → H → O → NO2 and the interface between the hot combustion products and NG–air mixture dominated by the HO2 produced through reaction pathway CH4 → CH3 → CH2O → HCO → HO2. The NO2 formed in hot combustion products during main combustion stage was later on destructed to NO and was not able to survive through the expansion process. In comparison, the NO2 formed during the post combustion expansion process was dominated by HO2 radical formed in the interface between the NO-containing combustion products and unburned NG–air mixture. It was concluded that the increased conversion from NO to NO2 in a NG–diesel dual fuel engine was due to the increased HO2 produced through the reaction path: CH4 → CH3 → CH2O → HCO → HO2 in the post combustion stage. The availability of methane necessary for the production of HO2 after the completion of the main combustion process was the main factor contributing to the significantly increased NO2 emissions from NG–diesel dual fuel engines. The research aiming at reducing NO2 emissions from dual fuel engines should focus on the approaches capable of significantly improving the combustion efficiency of NG.
Keywords: NO2 formation pathway; NG–diesel dual fuel engine; CFD; chemical kinetics process

Snow friction coefficient for commercial roofing materials - Bartko, Michal; Baskaran, Appupillai (Journal of Cold Regions Engineering, 2017)
Redistribution of snow loads on two adjacent buildings of different heights is addressed. The term slippery roofs is used but it is not defined. Measurements of friction between snow and commercial roofing materials are carried out to help specify the term. In order to determine a static coefficient of friction, the Coulomb friction principle of measuring inclination increase until specimen movement begins is applied. A test apparatus is designed and produced. Single-ply roofing materials such as membranes made of polyvinyl chloride (PVC), thermoplastic polyolefin (TPO), ethylene propylene diene monomer (EPDM), and modified bitumen (MB), as well as painted industrial metal profile specimens are tested. Snow specimens from fresh snow are prepared and tests are carried out under laboratory conditions. For the given conditions, although deviating from full-scale realistic conditions, snow samples slid at different angles depending on the roofing material type. Average values of sliding angle for PVC, TPO, EPDM, and MB membranes and metal sheet are determined to be 6°, 15°, 20°, 57°, and 22°, respectively. Based on the published provisions and given test conditions, commercial roofing materials can be categorized as slippery.

QTL mapping and molecular characterization of the classical D locus controlling seed and flower color in Linum usitatissimum (flax) - Sudarshan, Gurudatt Pavagada; Kulkarni, Manoj; Akhov, Leonid; Ashe, Paula; Shaterian, Hamid; Cloutier, Sylvie; Rowland, Gordon; Wei, Yangdou; Selvaraj, Gopalan (Scientific Reports, 2017)
The flowers of flax (linseed) are blue-hued, ephemeral and self-pollinating, and the seeds are typically brown. A century-old interest in natural yellow seed variants and a historical model point to recessive alleles in B1, D and G loci being responsible, but the functional aspects had remained unknown. Here, we characterized the “D” locus by quantitative trait loci (QTL) mapping and identified a FLAVONOID 3′5′ HYDROXYLASE (F3′5′H) gene therein. It does not belong to the F3′5′H clade, but resembles biochemically characterized F3′Hs (flavonoid 3′ hydroxylase) but without F3′H activity. The genome lacks other F3′H or F3′H-like genes. The apparent neo-functionalization from F3′H is associated with a Thr498 → Ser498 substitution in a substrate recognition site (SRS). The yellow seed and white flower phenotypes of the classical d mutation was found to be due to one nucleotide deletion that would truncate the deduced product and remove three of the six potential SRS, negatively impacting delphinidin synthesis. Delphinidin is sporadic in angiosperms, and flax has no known pollination syndrome(s) with functional pollinator group(s) that are attracted to blue flowers, raising questions on the acquisition of F3′5′H. The appearance of d allele is suggestive of the beginning of the loss of F3′5′H in this species.

Novel approaches to microbial enhancement of oil recovery - Kryachko, Yuriy (Journal of Biotechnology, 2017)
Microbially enhanced oil recovery (MEOR) was shown to be feasible in a number of laboratory experiments and field trials. However, it has not been widely used in the oil industry because necessary conditions cannot always be easily established in an oil reservoir. Novel approaches to MEOR, which are based on newly discovered biosurfactant-mediated MEOR-mechanisms, are discussed in this review. Particularly, the possibility of combining MEOR with chemical enhancement of oil recovery in heterogeneous oil reservoirs, which involves rock surface wettability shifts and emulsion inversions, is discussed. In wider (centimeter/millimeter-scale) rock pores, the activity of (bio)surfactants and microbial cells attached to oil may allow releasing trapped oil blobs through oil-in-water emulsification. After no more oil can be emulsified, the addition of alkali or surfactants, which turn rock surface oil-wet, may help release oil droplets trapped in narrow (micrometer-scale) pores through coalescence of the droplets and water-in-oil emulsification. Experiments demonstrating the possibility of (bio)surfactant-mediated enhancement of immiscible gas-driven oil recovery are also reviewed. Interestingly, very low (bio)surfactant concentrations were shown to be needed for enhancement of immiscible gas-driven oil recovery. Some possible side effects of MEOR, such as unintended bioplugging and microbially influenced corrosion (MIC), are discussed as well.
Keywords: biosurfactant; MEOR; EOR; wettability; interfacial tension; solution gas drive

Safety and biodistribution of sulfated archaeal glycolipid archaeosomes as vaccine adjuvants - McCluskie, Michael J.; Deschatelets, Lise; Krishnan, Lakshmi (Human Vaccines & Immunotherapeutics, 2017)
Archaeosomes are liposomal vesicles composed of ether glycerolipids unique to the domain of Archaea. Unlike conventional ester-linked liposomes, archaeosomes exhibit high stability and possess strong adjuvant and immunostimulatory properties making them an attractive vaccine delivery vehicle. Traditionally comprised of total polar lipids (TPL) or semi-synthetic phospho-glycerolipids of ether-linked isoprenoid phytanyl cores with varied glycol- and amino-head groups, archaeosomes can induce robust and long-lasting humoral and cell-mediated immune responses against antigenic cargo and provide protection in murine models of infectious disease and cancer. However, traditional TPL archaeosome formulations are relatively complex comprising several lipid species. Semi-synthetic archaeosomes tested previously contain a combination of several phospho-glycolipids (negative and neutral charged) to produce a stable, uniform-sized liposome formulation. Moreover, they involve many synthetic steps to arrive at the final desired glycolipid composition. Herein, we present a novel adjuvant formulation comprising a sulfated saccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA). SLA individually or mixed with uncharged glyolipid (lactosylarchaeol, LA) constituted efficacious carrier vesicles for entrapped antigens (ovalbumin or melanoma associated tyrosinase-related protein 2 [TRP-2]) and induction of strong cell-mediated responses in mice and protection against subsequent B16 melanoma tumor challenge. Thus, semi-synthetic sulfated glycolipid archaeosomes represent a new class of adjuvants that will potentially ease manufacturing and scale-up, while retaining immunostimulatory activity.
Keywords: adjuvant; adjuvants; archaeosome; delivery; glycolipid; immune modulators; immune response; mice; vaccine; vaccinology

Laser weldability of Zr-2.5Nb alloy to AISI 410 stainless steel with Ni filler - Chen, Jianyin; Khalifa, Ahmed; Xue, Lijue; King, Mitch (Journal of Materials Processing Technology, 2017)
The nickel interlayer improved the laser weldability of Zr-2.5Nb to AISI 410 stainless steel. The fusion zone contained a large amount of refined and tough dendritic γ-Ni(Fe, Cr) solid solution (182 ∼ 268 HV), while the brittle Zr(Fe, Cr)2 intermetallic compound (1171 ∼ 1460 HV), which was the main phase as the result of direct welding of Zr-2.5Nb to SS410 as well as the source responsible for the welding cracks, disappeared. Only limited quantities of Zr2(Ni, Fe), Zr7Ni10 (and/or Zr2Ni7) intermetallics were present mainly in the form of thin layers (less than 200 μm thick in total) near the fusion interface with Zr-2.5Nb. Those Zr-Ni based intermetallics showed relatively higher toughness and lower hardness (301 ∼ 497 HV) than the brittle Zr(Fe, Cr)2, which reduced the overall cracking sensitivity of the laser-weld.
Keywords: dissimilar metal joining; laser beam welding; Zr-2.5Nb; AISI 410 stainless steel; Ni interlayer

Toxic equivalency factors (TEFs) after acute oral exposure of azaspiracid 1, −2 and −3 in mice - Pelin, M.; Kilcoyne, J.; Nulty, C.; Crain, S. Hess, P.; Tubaro, A.; Sosa, S. (Toxicology Letters, 2017)
Azaspiracids (AZAs) are marine algal toxins that can be accumulated by edible shellfish to cause a foodborne gastrointestinal poisoning in humans. In the European Union, only AZA1, −2 and −3 are currently regulated and their concentration in shellfish is determined through their toxic equivalency factors (TEFs) derived from the intraperitoneal lethal potency in mice. Nevertheless, considering the potential human exposure by oral route, AZAs TEFs should be calculated by comparative oral toxicity data. Thus, the acute oral toxicity of AZA1, −2 and −3 was investigated in female CD-1 mice treated with different doses (AZA1: 135–1100 μg/kg; AZA2 and AZA3: 300–1100 μg/kg) and sacrificed after 24 h or 14 days. TEFs derived from the median lethal doses (LD50) were 1.0, 0.7 and 0.5, respectively for AZA1, −2 and −3. In fact, after 24 h from gavage administration, LD50s were 443 μg/kg (AZA1; 95% CL: 350−561 μg/kg), 626 μg/kg (AZA2; 95% CL: 430−911 μg/kg) and 875 μg/kg (AZA3; 95% CL: 757−1010 μg/kg). Mice dead more than 5 h after the treatment or those sacrificed after 24 h (doses: ≥175 μg AZA1/kg, ≥500 μg AZA2/kg and ≥600 μg AZA3/kg) showed enlarged pale liver, while increased serum markers of liver alteration were recorded even at the lowest doses. Blood chemistry revealed significantly increased serum levels of K+ ions (≥500 mg/kg), whereas light microscopy showed tissue changes in the gastrointestinal tract, liver and spleen. No lethality, macroscopic, tissue or haematological changes were recorded two weeks post exposure, indicating reversible toxic effects. LC–MS/MS analysis of the main organs showed a dose-dependency in gastrointestinal absorption of these toxins: at 24 h, the highest levels were detected in the stomach and, in descending order, in the intestinal content, liver, small intestine, kidneys, lungs, large intestine, heart as well as detectable traces in the brain. After 14 days, AZA1 and AZA2 were still detectable in almost all the organs and intestinal content.
Keywords: azaspiracid; acute oral toxicity; mice; toxic equivalency factors; TEF

Athermal planar-waveguide Fourier-transform spectrometer for methane detection - Podmore, Hugh; Scott, Alan; Cheben, Pavel; Sioris, Chris; Cameron, Peter; Schmid, Jens H.; Schmid, Jens H.; Lohmann, Andrew; Corriveau, Zachary; Lee, Regina (Optics Express, 2017)
We demonstrate a passively thermally-stabilized planar waveguide Fourier-transform spectrometer for remote detection of atmospheric methane. The device is implemented as a spatial heterodyne spectrometer using an array of 100 Mach-Zehnder interferometers (MZIs) on an integrated photonic chip. The spectrometer is buffered against temperature fluctuations by using waveguides with a carefully engineered, athermal geometry. The achieved waveguide thermooptic optic coefficient is 3.5×10−6K−1. Effective entrance aperture is increased over dispersive element spectrometers, without sacrificing spectral resolution, by coupling light independently to each of the 100 MZIs. The output of each MZI is sampled in quadrature, to compensate for non-uniform illumination across the MZI input apertures. The spectrometer is validated using a methane reference cell in a benchtop setup: an interferogram is inverted via least-squares spectral analysis (LSSA) to retrieve multiple absorption lines at a spectral resolution of 50 pm over a 1 nm free spectral range (FSR) centered at λ0 = 1666.5 nm. The retrieved spectrum is compared against the Beer-Lambert absorption law and is found to provide a correct measurement of the volume mixing ratio (VMR) in the optical path.

A study on the effect of inorganic fillers on the dryband arcing erosion of silicone rubber composites - Ghunem, Refat Atef; El-Hag, Ayman H.; Hadjadj, Yazid; Chemey, Edward A. (2017 IEEE Conference on Electrical Insulation and Dielectric Phenomenon, 2017)
This paper investigates the erosion of silicone rubber composites filled with various fillers. The fillers under study are alumina tri-hydrate, magnesium hydroxide and silica in a liquid silicone ru bber. The inclined plane tracking and erosion test was used to compare the erosion of the composite materials at 50 wt% filler level and at 4.5 kV. Simultaneous thermogravimetric and differential thermal analyses are reported which shows various mechanisms by which the fillers can su ppress the dry band arcing erosion. The effect of water of hydration in the alumina tri-hyd rate and magnesium hydroxide is investigated and its effect on the suppression of the dry-band arcing erosion is reported for the composites filled with alumina tri-hydrate and magnesiu m hydroxide.

Variation of the optical properties of soot as a function of particle mass - Dastanpour, Ramin; Momenimovahed, Ali; Thomson, Kevin; Olfert, Jason; Rogak, Steven (Carbon, 2017)
Light absorption and scattering properties of combustion-generated soot particles are important to measurement methods and are used as the inputs for climate models. For decades, mass-specific absorption cross section (MAC) of soot has been assumed to be independent of its size and mass. Here we investigate the size-dependent optical properties of particles produced by a single source. Soot particles were produced by combustion of CH4, and CH4 - N2 mixtures, within a laminar inverted diffusion flame. Extinction and scattering coefficients of mass-classified particles were measured by a Cavity Attenuated Phase Shift Single Scattering Albedo Spectrometer. Primary particle diameter and morphology of particles were characterized by transmission electron microscopy. Graphitization level of the size-classified particles was also investigated by Raman spectroscopy. Here, for the first time we observed that MAC and graphitization level of the soot particles increase with the particle mass. MAC number increases from approximately 4.5 to 8.5 (m2g−1) with the particle mass increasing from 0.05 fg to 8 fg. The soot aggregate size is correlated with primary particle size, which may reflect the inhomogeneity of the combustion environment that could affect the optical properties of soot.

Investigation of erosion-corrosion behavior of (WTi)C based weld overlays - Islam, Md. Aminul; Jiang, Jiaren (Jimmy); Xie, Yongsong; Fiala, Petr (Wear, 2017)
Erosion-corrosion is responsible for severe damage and high maintenance costs in many industrial operations involving slurry handling such as oil sands and mineral processing. While tungsten carbide reinforced Ni-based alloy overlays are frequently used for applications requiring extremely high wear resistance, they tend to suffer from extensive carbide degradation during the weld cladding process which has been shown to severely impair their erosion-corrosion resistance. Recently, new (WTi)C based overlays are being developed to alleviate some of the limitations associated with the nickel-based tungsten carbide overlays. In this study, three different overlays reinforced with (WTi)C and one tungsten carbide were assessed using a slurry pot erosion-corrosion testing apparatus where the total erosion-corrosion (E-C) rate as well as the separate components of synergistic effect was determined. Erosion-corrosion test was performed at 30 °C, in an aqueous slurry containing 35 wt% AFS 50–70 silica sand and 3.5 wt% NaCl. A special SEM technique was employed to examine changes on the specimen surface at specific overlay locations before and after erosion-corrosion test in order to identify the effect of corrosion on erosion and vice-versa. It was found that tungsten is more prone to dissolution in the matrix during the welding process than titanium, which forms W-depletion/Ti-rich layer around the (WTi)C particle. Dissolution of tungsten and titanium promotes the formation of secondary carbides in the matrix. Erosion-corrosion performance of the overlays largely depends on increased fraction of retained primary (WTi)C phase.
Keywords: Erosion-corrosion; synergistic effect; overlays; slurry pot; (WTi)C

Photo-reduced graphene as electrode active materials for supercapacitor applications - Yang, Dongfang (ECS Transactions, 2017)
Graphene is a form of carbon that has high electrical conductivity, a planar structure and substantially high surface area, thereby having the potential for more storage of electrostatic charge for high energy supercapacitors (SC). In this paper, the recent developments on the fabrication of graphene by means of photo-reduction of graphene oxide will be overviewed. The main advantage of the photo-process is that it does not rely on the use of chemicals or high temperature. For example, KrF excimer laser irradiation process for the fabrication of N-doped graphene from graphene oxide will be illustrated and the performance of laser reduced N-doped graphene when it is used as electrode active materials in supercapacitors will also be evaluated.

NRC microwave refractive index gas thermometry implementation between 24.5 K and 84 K - Rourke, P. M. C. (International Journal of Thermophysics, 2017)
The implementation of microwave refractive index gas thermometry at the National Research Council between 24.5 K and 84 K is reported. A new gas-handling system for accurate control and measurement of experimental gas pressure has been constructed and primary thermometry measurements have been performed using a quasi-spherical copper resonator and helium gas at temperatures corresponding to three defining fixed points of the International Temperature Scale of 1990 (ITS-90). These measurements indicate differences between the thermodynamic temperature T and ITS-90 temperature T90 of (T −T90) = −0:60±0:56 mK at T90 = 24:5561 K, (T −T90) = −2:0±1:3 mK at T90 = 54:3584 K, and (T −T90) = −4:0±2:9 mK at T90 = 83:8058 K. The present results at T90 = 24:5561 K and T90 = 83:8058 K agree with previously reported measurements from other primary thermometry techniques of acoustic gas thermometry and dielectric constant gas thermometry, and the result at T90 = 54:3584 K provides new information in a temperature region where there is a gap in other recent data sets.
Keywords: primary thermometry; thermodynamic temperature; T−T90; polarizing gas thermometry; refractive index gas thermometry; RIGT

Issues and strategies for improving measurement uncertainties for solid-state lighting - Zwinkels, Joanne C. (NCSL International measure: The Journal of Measurement Science, 2017)
The use of solid-state lighting (SSL), such as light-emitting-diode (LED) products for general lighting and display applications, has increased dramatically over the past decade. However, there are significant photometric and radiometric metrological challenges with this new lighting technology. The photometric procedures and standards that have been developed for traditional lighting products, such as incandescent and compact fluorescent (CFL) lamps, do not work well for LEDs because they exhibit significantly different characteristics. This paper will discuss these differences in the spectral, geometric, and operating properties of LEDs and how they impact precise photometric measurements and associated performance metrics, such as color rendering index (CRI). The current state-of-the-art uncertainties for photometric measurements of LED lighting products is about a factor of 5 poorer than for traditional lamps, based upon the results of recent interlaboratory comparisons involving both national metrology institutes (NMIs) and accredited laboratories. Reducing the uncertainty of these measurements will have a significant impact on society—both on reducing costs due to energy savings, but also on improving overall lighting quality and performance. For these reasons, there are a number of activities being carried out both at the national and international level to address these LED measurement issues. This article will highlight the current strategies and standardization activities within both the Consultative Committee of Photometry and Radiometry (CCPR) and the International Commission of Illumination (CIE) to develop improved measurement techniques, transfer standards and metrics for the measurement and use of LED lighting in photometry, and to meet consumer needs.

Extracting Wair from the electron beam measurements of Domen and Lamperti - Tessier, F.; Cojocaru, C. D.; Ross, C. K. (Medical Physics, 2017)
Purpose: The average energy expended by an energetic electron to create an ion pair in dry air, Wair, is a key quantity in radiation dosimetry. Although Wair is well established for electron energies up to about 3 MeV, there is limited data for higher energies. The measurements by Domen and Lamperti [Med. Phys. 3, 294–301 (1976)] using electron beams in the energy range from 15 to 50 MeV can, in principle, be used to deduce values for Wair, if the electron stopping power of graphite and air are known. A previous analysis of these data revealed an anomalous variation of 2% in Wair as a function of the electron energy. We use Monte Carlo simulation techniques to reanalyze the original data and obtain new estimates for Wair, and to investigate the source of the reported anomaly. Methods: Domen and Lamperti (DL) reported the ratio of the response of a graphite calorimeter to that of a graphite ionization chamber for broad beams of electrons with energies between 15 and 50 MeV and at different depths in graphite (including depths well beyond the range of the primary electrons, i.e., in the bremsstrahlung photon regime). Using a detailed EGSnrc model of the DL apparatus, as well as up-to-date stopping powers, we compute the dose ratio between the ionization chamber cavity and the calorimeter core, for plane-parallel electron beams. This dose ratio, multiplied by the DL measured ratio, provides a direct estimate for Wair. Results: Despite an improved analysis of the original work, the extracted values of Wair still exhibit an increase as the mean electron energy at the point of measurement decreases below about 15 MeV. This anomalous trend is dubious physically, and inconsistent with extensive data for Wair obtained at lower energies. A thorough sensitivity analysis indicates that this trend is unlikely to stem from errors in extrapolation and correction procedures, uncertainties in electron stopping powers, or bias in calorimetry or ionization chamber measurements. However, we find that results are quite sensitive to the intrinsic graphite mass thickness of the detectors and to the incident beam energy. Conclusions: The DL experiment provides data in an energy regime where the electron stopping power is insensitive to the mean excitation energy of graphite — an issue plaguing Wair experiments at lower energies. Unfortunately, state-of-the-art scrutiny of the original data cannot explain the anomalous trend in terms of perturbation effects or extrapolation bias. It can only be understood in terms of speculative offsets in graphite mass thickness or beam energy. Therefore higher accuracy measurements for electron energies above 15 MeV are recommended to further resolve the value of Wair.
Keywords: average energy to create an ion pair; graphite calorimeter; ionization chamber; megavoltage electrons; EGSnrc; electron stopping powers

The role of selenium in mercury toxicity: current analytical techniques and future trends in analysis of selenium and mercury interactions in biological matrices - Gajdosechova, Zuzana; Mester, Zoltan; Feldmann, Jörg; Krupp, Eva M. (TrAC Trends in Analytical Chemistry, 2017)
Mercury forms potent toxic compounds, which cause irreversible damage to the central nervous system, while selenium, if present in an adequate concentration, is an essential micronutrient needed for the regulation of metabolic processes. The interactions between mercury and selenium have been rigorously scrutinized particularly due to observed protective effects of selenium against mercury toxicity, however very few proposed mechanisms are supported by empirical data. With mercury concentrations steadily rising in the environment, this matter is of urgency, and pushes for the development of new sample preparation protocols and analytical techniques. Softer extraction methods should preserve the true chemical species, while a combination of chromatographic and direct analytical techniques enable identification and quantitation. This review summarizes the state of the art of current analytical techniques, which focus on the interactions between mercury and selenium in biological matrices and outlines the future trends that might fill major gaps in our analytical capabilities.
Keywords: mercury; selenium; bio-molecules; speciation; extraction; ESI–MS; XANES; chromatography; nanoparticles; isotope ratio

Technical note: on the use of cylindrical ionization chambers for electron beam reference dosimetry - Muir, B.R.; McEwen, M. R. (Medical Physics, 2017)
PURPOSE: To investigate the use of cylindrical chambers for electron beam dosimetry independent of energy by studying the variability of relative ion chamber perturbation corrections, one of the main concerns for electron beam dosimetry with cylindrical chambers. METHODS: Measurements are made with sets of cylindrical and plane-parallel reference-class chambers as a function of depth in water in 8 MeV and 18 MeV electron beams. The ratio of chamber readings for similar chambers is normalized in a high-energy electron beam and can be thought of as relative perturbation corrections. Data are plotted as a function of mean electron energy at depth for a range of depths close to the phantom surface to R80 , the depth at which the ionization falls to 80% of its maximum value. Additional, similar measurements are made in a Virtual Water® phantom with cylindrical chambers at the reference depth in a 4 MeV electron beam. RESULTS: The variability of relative ion chamber perturbation corrections for nominally identical cylindrical Farmer-type chambers is found to be less than 0.4%, no worse than plane-parallel chambers with similar specifications. CONCLUSIONS: This work discusses several issues related to the use of plane-parallel ion chambers and suggests that reference-class cylindrical chambers may be appropriate for reference dosimetry of all electron beams. This would simplify the reference dosimetry procedure and improve accuracy of beam calibration.
Keywords: electron beams; ionization chamber; reference dosimetry

Dielectric measurements on polypropylene nanocomposites filled with natural and synthetic Nanoclay - Hadjadj, Y.; Ghunem, R. A. (IEEE, 2017)

Challenges in measuring spherical geometry using terrestrial laser scanners - Muralikrishnan, Balasubramanian; Rachakonda, Prem K.; Shilling, Katharine M.; Lee, Vincent D.; Sawyer, Daniel S.; Cheok, Geraldine S.; Cournoyer, Luc (Proceedings of the Annual Meeting of the ASPE 2017, 2017)
Terrestrial laser scanners (TLS) measure 3D coordinates in a scene by recording the range, the azimuth angle, and elevation angle of discrete points on target surfaces. They are increasingly used in a variety of applications, including manufacturing and civil infrastructure systems. However, the error sources of these instruments are not yet adequately characterized. There is a lack of standardized test procedures [1] and detailed uncertainty budgets for TLS measurements are seldom available. Measuring curved surfaces using TLS has always proved problematic; Lichti et. al [2] describe problems with cylinder measurements. From experiments performed at the laboratories of the Dimensional Metrology Group at NIST, we know that several TLS systems are incapable of obtaining a reliable point cloud from the surface of a spherical target. The changing surface curvature, averaging of the laser spot on the surface, multiple reflections from nearby surfaces and many other factors contribute to the scanned data of the sphere making it appear either smaller (squished) or larger (flared) than the actual sphere. This not only means that the radius of the sphere is incorrectly determined but there is also an error in locating the center of the sphere.In this context, we describe here the challenges involved in measuring a simple geometry, the sphere, using TLS
Keywords: flaring; sphere target; squishing; terrestrial laser scanner

Electron beam water calorimetry measurements to obtain beam quality conversion factors - Muir, Bryan R.; Cojocaru, Claudiu D.; McEwen, Malcolm R.; Ross, Carl K. (Medical Physics, 2017)
Purpose: To provide results of water calorimetry and ion chamber measurements in high-energy electron beams carried out at the National Research Council Canada (NRC). There are three main aspects to this work: (a) investigation of the behavior of ionization chambers in electron beams of different energies with focus on long-term stability, (b) water calorimetry measurements to determine absorbed dose to water in high-energy beams for direct calibration of ion chambers, and (c) using measurements of chamber response relative to reference ion chambers, determination of beam quality conversion factors, kQ, for several ion chamber types. Methods: Measurements are made in electron beams with energies between 8 MeV and 22 MeV from the NRC Elekta Precise clinical linear accelerator. Ion chamber measurements are made as a function of depth for cylindrical and plane-parallel ion chambers over a period of five years to investigate the stability of ion chamber response and for indirect calibration. Water calorimetry measurements are made in 18 MeV and 22 MeV beams. An insulated enclosure with fine temperature control is used to maintain a constant temperature (drifts less than 0.1 mK/min) of the calorimeter phantom at 4°C to minimize effects from convection. Two vessels of different designs are used with calibrated thermistor probes to measure radiation induced temperature rise. The vessels are filled with high-purity water and saturated with H2 or N2 gas to minimize the effect of radiochemical reactions on the measured temperature rise. A set of secondary standard ion chambers are calibrated directly against the calorimeter. Finally, several other ion chambers are calibrated in the NRC 60Co reference field and then cross-calibrated against the secondary standard chambers in electron beams to realize kQ factors. Results: The long-term stability of the cylindrical ion chambers in electron beams is better (always \0:15%) than plane-parallel chambers (0.2% to 0.4%). Calorimetry measurements made at 22 MeV with two different vessel geometries are consistent within 0.2% after correction for the vessel perturbation. Measurements of absorbed dose calibration coefficients for the same secondary standard chamber separated in time by 10 yr are within 0.2%. Drifts in linac output that would affect the transfer of the standard are mitigated to the 0.1% level by performing daily ion chamber normalization measurements. Calibration coefficients for secondary standard ion chambers can be achieved with uncertainties less than 0.4% (k = 1) in high-energy electron beams. The additional uncertainty in deriving calibration coefficients for well-behaved chambers indirectly against the secondary standard reference chambers is negligible. The kQ factors measured here differ by up to 1.3% compared to those in TG-51, an important change for reference dosimetry measurements. Conclusions: The measurements made here of kQ factors for eight plane-parallel and six cylindrical ion chambers will impact future updates of reference dosimetry protocols by providing some of the highest quality measurements of this crucial dosimetric parameter.
Keywords: beam quality conversion factor; electron beams; water calorimetry

Manipulation and quantification of graphene oxide flake size: photoluminescence and cytotoxicity - Coleman, Brian R.; Knight, Timothy; Gies, Valerie; Jakubek, Zygmunt J.; Zou, Shan (ACS Applied Materials and Interfaces, 2017)
Single-layered graphene oxide (GO) has exhibited great promise in the areas of sensing, membrane filtration, supercapacitors, bioimaging, and therapeutic carriers because of its biocompatibility, large surface area, and electrochemical, photoluminescent, and optical properties. To elucidate how the physical dimensions of GO affect its intrinsic properties, we employed sonication to produce more than 130 different sizes of GO in aqueous dispersion and implemented new approaches to characterize various GO properties as a function of the average flake size. New protocols were developed to determine and compare the flake size of GO dispersions sonicated with energies up to 20 MJ/g by using dynamic light scattering and atomic force microscopy (AFM). The relationship between the average flake size and sonication energy per unit mass of GO was observed to follow a power law. AFM height measurements showed that the sonication of GO yielded monolayered flakes. Photoluminescence of GO was characterized as a function of the sonication energy (or the average flake size which is the monotonic function of the sonication energy), excitation wavelength, and pH of the dispersion. The strong dependence of the photoluminescence intensity on pH control and the variation of the photoluminescence intensity with different flake sizes were observed. An intense photoluminescence signal, likely related to the separation of the oxidative debris from the GO framework, was found at the highest sonication energies (E ≳ 15 MJ/g) or under extremely alkaline conditions (pH ≳ 11). The cytotoxicity of GO was studied with various flake sizes. Size- and concentration-dependent cytotoxicity was observed for cell lines NIH 3T3 and A549. The NIH 3T3 cell line also demonstrated time-dependent cytotoxicity.
Keywords: atomic force microscopy; cell viability; dynamic light scattering; pH dependent; sonication

The collisional frequency shift of a trapped-ion optical clock - Vutha, Amar C.; Kirchner, Tom; Dubé, Pierre (Physical Review A, 2017)
Collisions with background gas can perturb the transition frequency of trapped ions in an optical atomic clock. We develop a nonperturbative framework based on a quantum channel description of the scattering process and use it to derive a master equation which leads to a simple analytic expression for the collisional frequency shift. As a demonstration of our method, we calculate the frequency shift of the Sr+ optical atomic clock transition due to elastic collisions with helium.

Temperature induced lipid membrane restructuring and changes in nanomechanics - Bhojoo, Urvi; Chen, Maohui; Zou, Shan (National Research Council Canada. Measurement Science and Standards, 2017)
Keywords: supported lipid bilayers; atomic force microscopy; force mapping; low temperature; force indentation; milk lipids; sphingomyelin; cholesterol

Comparison of the standards of air kerma and absorbed dose to water in Co-60 radiation for the National Research Council Canada and the Laboratorio de Metrologia de Radiaciones Ionizantes, Comisión Chilena de Energía Nuclear - McEwen, Malcolm; Rodriguez, Hernán; Ortega, Fernando; Oyarzun, Carlos (National Research Council Canada. Measurement Science and Standards, 2017)
An indirect comparison has been made of the standards for air kerma and absorbed dose to water in 60Co radiation of the National Research Council (NRC), Canada and of the Laboratorio de Metrologia de Radiaciones Ionizantes (LMRI), Chile. The measurements at the LMRI were carried out in October 2016. The comparison results, based on the calibration coefficients for one transfer standard and evaluated as a ratio of the LMRI and the NRC standards, were 0.9972 for absorbed dose to water, with a combined standard uncertainty of 8.9 × 10-3, and 0.9945 for air kerma, with a combined standard uncertainty of 8.6 × 10-3. The results are analysed in the context of the degrees of equivalence for these quantities published in the BIPM key comparison database. Additional characterization of the LRMI Co-60 irradiator is also described.

Systematic toxicity investigation of graphene oxide evaluating assay selection, cell type, exposure period and flake size - Gies, Valerie; Zou, Shan (National Research Council Canada. Measurement Science and Standards, 2017)
Keywords: GO; cytotoxicity; cell viability; proliferation assays; atomic force microscopy; dynamic light scattering; sonication

Determination of cyanocobalamin in multivitamin supplements with LC-ID4-MS/MS - D'Ulivo, Lucia; Yang, Lu; Ding, Jianfu; Pagliano, Enea; Leek, Donald M.; Thibault, Marie-Pier; Mester, Zoltan (National Research Council Canada. Measurement Science and Standards, 2017)

Behavior and kinetic of hydrolysis of amine boranes in acid media employed in chemical vapor generation - D'Ulivo, L.; Spiniello, R.; Onor, M.; Campanella, B.; Mester, Z.; D'Ulivo, A. (National Research Council Canada. Measurement Science and Standards, 2017)

Uncertainty evaluation in normalization of isotope delta measurement results against international reference materials - Meija, Juris; Chartrand, Michelle (Analytical and Bioanalytical Chemistry, 2017)
Isotope delta measurements are normalized against international reference standards. Although multi-point normalization is becoming a standard practice, the existing uncertainty evaluation practices are either undocumented or are incomplete. For multi-point normalization, we present errors-in-variables regression models for explicit accounting of the measurement uncertainty of the international standards along with the uncertainty that is attributed to their assigned values. This manuscript presents framework to account for the uncertainty that arises due to a small number of replicate measurements and discusses multi-laboratory data reduction while accounting for inevitable correlations between the laboratories due to the use of identical reference materials for calibration. Both frequentist and Bayesian methods of uncertainty analysis are discussed.
Keywords: isotope delta; normalization; uncertainty evaluation; random effects model

The pink tea challenge - D'Ulivo, Lucia (Analytical and Bioanalytical Chemistry, 2017)

The NRC-FCs2 primary frequency standard at the National Research Council Canada - Beatie, Scott; Jian, Bin; Alcock, John; Bernard, John; Gertsvolf, Marina; Hendricks, Rich; Ozimek, Filip; Szymaniec, Krzysztof; Gibble, Kurt (Frequency and Time Forum and IEEE International Frequency Control Symposium (EFTF/IFCS), 2017 Joint Conference of the European, 2017)
At the National Research Council Canada, we are performing final assembly and initial testing of our new atomic fountain clock, NRC-FCs2. This fountain clock incorporates several improvements in the optical, microwave, and computer systems from our previous generation clock, NRC-FCs1, as well as a new physics package designed at the National Physical Laboratory (UK). With these changes, NRC-FCs2 is expected to reach uncertainties <; 5×10-16. We will discuss the recent improvements made in the various subsystems of NRC-FCs2 and present preliminary results in its evaluation.
Keywords: Primary frequency standard; clock; atom cooling and trapping

Absolute frequency measurement of the electric quadrupole transition of 88Sr+ - Dubé, Pierre; Bernard, John E.; Gertsvol, Marina (Frequency and Time Forum and IEEE International Frequency Control Symposium (EFTF/IFCS), 2017 Joint Conference of the European, 2017)
We report a new measurement of the 445 THz electric quadrupole transition of the strontium ion made using a GPS link to the SI second. Compared to our previous measurement reported in 2012, the operation of the optical clock has been improved in several ways, especially from a reduction of the micromotion shifts, of the black body radiation shift, and of the servo tracking errors. Moreover, the stability of the clock has been improved three-fold with state-preparation. The uncertainty of the optical clock during the measurement campaign was 7 mHz. The uncertainty of the frequency measurement was 0.75 Hz, limited primarily by the GPS link and to a lesser extent by the measurement statistics. The new frequency measurement is in good agreement with previously reported values.
Keywords: absolute frequency measurement; single ion clock; optical atomic clock; GPS frequency link

Differential mobility-mass spectrometry double spike isotope dilution study of release of β-methylaminoalanine and proteinogenic amino acids during biological sample hydrolysis - Beach, Daniel G; Kerrin, Elliott S.; Giddings, Sabrina D.; Quilliam, Michael A.; McCarron, Pearse (National Research Council Canada. Measurement Science and Standards, 2017)
The non-protein ammo acid β-methylamino-L-alanine (BMAA) has been linked to neurodegenerative disease and reported throughout the environment. Proposed mechanisms of bioaccumulation, trophic transfer and chronic toxicity of BMAA rely on the hypothesis of protein misincorporation. Poorly selective methods for BMAA analysis have led to controversy. We recently reported a highly selective method for BMAA quantitation using hydrophilic interaction liquid chromatography-differential mobility spectrometry-tandem mass spectrometry (HILIC-DMS-MS/MS). Here, this methodology is expanded to include protein genic amino acids from hydrolyzed biological samples. For BMAA quantitation, we present a double spiking isotope dilution approach using D3-BMAA and 13C15N2-BMAA. We apply these methods to study release of BMAA during acid hydrolysis under a variety of conditions, revealing that the majority of BMAA can be extracted along with only a small proportion of protein. A time course hydrolysis of BMAA from mussel tissue was carried out to assess the recovery of BMAA during sample preparation. The majority of BMAA measured by typical methods was released before a significant proportion of protein was hydrolyzed. Little change was observed in protein hydrolysis beyond typical hydrolysis times but the concentration of BMAA increased linearly. These findings demonstrate protein misincorporation is not the predominant form of BMAA in cycad and shellfish.
Keywords: BMAA; reference materials; FAIMS; DMS; amino acid analysis

Development and characterization of commercial boron nitride nanotube product forms - Jakubinek, M. B.; Martinez-Rubi, Y.; Kim, K. S.; Jakubek, Z. J.; Homenick, C. M.; Zou, S.; Klug, D.; Ashrafi, B.; Guan, J.; Walker, S.; Daroszewska, M.; Kingston, C. T.; et al. (Advanced Materials. TechConnect Briefs 2017. Volume 1, 2017)
Boron nitride nanotubes (BNNTs) are structurally analogous to carbon nanotubes (CNTs) and possess equally impressive mechanical properties along with a different set of multifunctional properties including higher thermal stability than CNTs, wide band gap, electrical insulation, polarizability, high neutron absorption cross-section, and transparency in the visible region. Advances in large-scale BNNT production in recent years, including the hydrogen-assisted BNNT synthesis (HABS) process at NRC Canada, are now enabling broader availability of BNNT-based materials for research and applications. For example, a commercial product (Tekna BNNT-R) derived from the “raw” BNNT produced via the HABS process was released in 2015 and was followed quickly, in 2016, by purified (BNNT-P) and buckypaper (BNNT-BP) product forms. Reliable characterization of these materials, in particular the composition, purity, and quality of BNNTs is critical to build the user base for such nanomaterials products, as was the case for carbon nanotubes, and enable evaluation and comparison of studies using BNNT materials.
Keywords: boron nitride nanotubes; nanotube characterization; buckypaper

Developing hybrid polymer scaffolds using peptide modified biopolymers for cell implantation - Abraham, Sinoj; Kuppan, Purushothaman; Raj, Shammy; Salama, Bassem; Korbutt, Gregory S.; Montemagno, Carlo D. (ACS Biomaterials Science & Engineering, 2017)
Polymeric scaffolds containing biomimics offer exciting therapies with broad potential impact for cellular therapies and thereby potentially improve success rates. Here we report the designing and fabrication of a hybrid scaffold that can prevent a foreign body reaction and maintain cell viability. A biodegradable acrylic based cross-linkable polycaprolactone based polymer was developed and using a multihead electrospinning station to fabricate hybrid scaffolds. This consists of cell growth factor mimics and factors to prevent a foreign body reaction. Transplantation studies were performed subcutaneously and in epididymal fat pad of immuno-competent Balb/c mice and immuno-suppressed B6 Rag1 mice and we demonstrated extensive neo-vascularization and maintenance of islet cell viability in subcutaneously implanted neonatal porcine islet cells for up to 20 weeks of post-transplant. This novel approach for cell transplantation can improve the revascularization and allow the integration of bioactive molecules such as cell adhesion molecules, growth factors, etc.
Keywords: biomimics; biopolymer; subcutaneous; transplantation; vascularization

Developing hierarchically porous MnOx/NC hybrid nanorods for oxygen reduction and evolution catalysis - Pandey, Jay; Hua, Bin; Ng, Wesley; Yang, Ying; Van der Veen, Koen; Chen, Jian; Geels, Norbert J.; Luo, Jing-Li; Rothenberg, Gadi; Yan, Ning (Green Chemistry, 2017)
Electrochemical oxygen reduction and evolution reactions (ORR and OER) play a vital role in the field of energy conversion and storage. The problem is that both processes are sluggish, requiring precious-metal catalysts. Here, starting from abundant precursors and using a simple synthesis approach, we report the preparation of a good bifunctional oxygen electro-catalyst: a composite nanorod of manganese oxides and nitrogen-doped carbon. This material has hierarchical porosity, facilitating the mass transfer within the electrode. The nitrogen-doped carbon forms contiguous 3D network, connecting the isolated MnOx nanoparticles and ensuring superior electrical conductivity. Importantly, the MnOx particles contain manganese of mixed oxidation states; aligned with the nitrogen-doped carbon, this hybrid is among the best non-noble-metal ORR/OER catalysts in alkaline media, outperforming even Pt and RuO2 catalysts.

Determination of the uncertainty contribution of acoustic front ends on sound pressure level measurements - Wu, Lixu (The International Institute of Acoustics and Vibration, 2017)
Sound pressure level measurements are key points to determine whether there is a breach of noise limits. Any measurement made without the knowledge of its uncertainty lacks signifi- cance. For this reason, an open measurement system has been developed at the National Re- search Council Canada for sound pressure level measurements with the focus on measurement uncertainties. For uncertainty evaluation of such a system, the most difficult task is determining the uncertainty contribution of its acoustic front end, or its microphone and preamplifier assem- bly. The acoustic frond end can be modelled as a linear time-invariant system. Once the fre- quency response of the acoustic front end has been measured, its effect on an arbitrary signal can be analyzed. However, measured microphone frequency response does not include phase in- formation, as no country in the world yet has Calibration and Measurement Capability (CMC) for microphone pressure sensitivity phase. With the completion of key comparison CCAUV.A- K5, this situation will change in the near future. Now is the time to determine the uncertainty contribution of acoustic front end using the phase information available, such as that in CCAUV.A-K5. In this paper, a method for the evaluation of the uncertainty contribution of acoustic front ends is presented. The acoustic front end is first modelled as a linear time- invariant system. Its measured frequency response at discrete frequencies is then curve-fit to ob- tain the response covering the entire frequency domain. The output of the acoustic front end is simply the convolution of the input with the acoustic front end's impulse response. The uncer- tainty contribution is finally calculated by propagating the uncertainties of the acoustic front end output at every time instance. Examples are given for typical acoustic front ends with various types of acoustic signals.
Keywords: sound pressure level; measurement uncertainty

Determination of the relationship between expression and functional activity of multidrug resistance-associated protein 1 using scanning electrochemical microscopy - Polcari, David; Hernández-Castro, Javier Alejandro; Li, Kebin; Geissler, Matthias; Mauzeroll, Janine (Analytical Chemistry, 2017)
Cancer cells can develop multidrug resistance (MDR) after prolonged exposure to chemotherapeutic drugs, which is a severe impediment to successful treatment. MDR is typically associated with transmembrane proteins mediating efflux of administered drugs, thereby keeping their intracellular concentration below the threshold required to kill cells. Although expression assays based on flow cytometry and immunostaining have shown that multidrug resistance-associated protein 1 (MRP1) is prevalent in many cancer types, the functional activity of this efflux pump is more difficult to elucidate, especially at the single-cell level. Herein, we report the measurement of MRP1 functional activity in individual cancer cells using scanning electrochemical microscopy (SECM). Cells were cultured onto plastic substrates containing selective adhesion sites. Optical microscopy and SECM revealed that cells adapt to the underlying surface, while MRP1 functional activity increases once the dimensions of the adhesive islands become smaller than those of the cell itself. Time-lapse SECM imaging revealed a suitable window of 30 min to complete each measurement before the cell undergoes blebbing, which is associated with a considerable increase in functional activity. Distinct cell populations were produced by performing a doxorubicin drug challenge on two parental cell lines (e.g., wild-type HeLa cells and MRP1-overexpressing HeLa-R cells). Expression and functional activity of MRP1 were determined using flow cytometry and SECM, and our findings show that these parameters do not directly correlate. This suggests that functional activity may represent a powerful indicator of a cancer cell’s response to chemotherapeutic treatment and should improve our understanding of efflux mechanisms based on MRP1.

Detection of an ∼20 kpc coherent magnetic field in the outskirt of merging spirals: the Antennae galaxies - Basu, Aritra; Mao, S. A.; Kepley, Amanda A.; Robishaw, Timothy; Zweibel, Ellen G.; Gallagher, John. S. (Monthly Notices of the Royal Astronomical Society, 2017)
We present a study of the magnetic field properties of NGC 4038/9 (the ‘Antennae’ galaxies), the closest example of a late stage merger of two spiral galaxies. Wideband polarimetric observations were performed using the Karl G. Jansky Very Large Array between 2 and 4 GHz. Rotation measure synthesis and Faraday depolarization analysis was performed to probe the magnetic field strength and structure at spatial resolution of ∼1 kpc. Highly polarized emission from the southern tidal tail is detected with intrinsic fractional polarization close to the theoretical maximum (0.62 ± 0.18), estimated by fitting the Faraday depolarization with a volume that is both synchrotron emitting and Faraday rotating containing random magnetic fields. Magnetic fields are well aligned along the tidal tail and the Faraday depths shows large-scale smooth variations preserving its sign. This suggests the field in the plane of the sky to be regular up to ∼20 kpc, which is the largest detected regular field structure on galactic scales. The equipartition field strength of ∼ 8.5 μG of the regular field in the tidal tail is reached within a few 100 Myr, likely generated by stretching of the galactic disc field by a factor of 4–9 during the tidal interaction. The regular field strength is greater than the turbulent fields in the tidal tail. Our study comprehensively demonstrates, although the magnetic fields within the merging bodies are dominated by strong turbulent magnetic fields of ∼ 20 μG in strength, tidal interactions can produce large-scale regular field structure in the outskirts.
Keywords: galaxies: ISM; galaxies: magnetic fields

Details of resonant structures within a nice model Kuiper Belt: predictions for high-perihelion TNO detections - Pike, R. E.; Lawler, S. M. (The Astronomical Journal, 2017)
We analyze a detailed Nice model simulation of Kuiper Belt emplacement from Brasser & Morbidelli, where Neptune undergoes a high-eccentricity phase and migrates outward. In this work, which follows from Pike et al., we specifically focus on the details of structures within Neptune's mean-motion resonances and in the high-pericenter population of simulated trans-Neptunian objects (TNOs). We find several characteristics of these populations that should be observable in the distant solar system in future large-scale TNO surveys as a diagnostic of whether or not this mode of Neptune migration occurred in the early solar system. We find that the leading asymmetric libration islands of the n:1 resonances are generally much more populated than the trailing islands. We also find the nonresonant high-q population of TNOs should have higher inclinations than the low-q population due to the importance of Kozai cycling during their emplacement histories. Finally, high-q TNOs should be present in roughly equal numbers on either side of distant mean-motion resonances. These predictions contrast with predictions from other Kuiper Belt emplacement simulations and will be testable by upcoming surveys.
Keywords: Kuiper Belt: general; planets and satellites: dynamical evolution and stability

Designing and assessing wheel/rail profiles for improved rolling contact fatigue and wear performance - Magel, Eric; Kalousek, Joe (Proceedings of the Institution of Mechanical Engineers, Part F: Journal of Rail and Rapid Transit, 2017)
A quick survey of wheel and rail profiles used around the world reveals a huge range of options. Wheels come in cylindrical, conical, and concave variations, while rails range in shape from a very flat 14 in. (350 mm) head radius to a tightly crowned 6 in. (150 mm) head radius. The rationale for implementing one or the other is often institutional inertia—a strong tendency to continue doing what has been done in the past. But the impacts of wheel and rail profiles on the performance of the vehicle/track interaction are large and the decision should not be made lightly. Unfortunately, there are few well-matched “off-the-shelf” solutions from the existing commercially available profiles, such that new rails and wheels often suffer early failures or infant mortality. Through examples and case studies, this paper discusses the significant role that wheel and rail profiles play with respect to performance and safety and makes the case for wheel and rail profiles specifically suited to the needs of each railway. Various techniques for assessing the performance of systems of wheels and rails are reviewed and discussed.
Keywords: pummelling; rolling contact fatigue; wheel/rail design; wheel/rail profiles; wheel/rail wear

Design of thin InGaAsN(Sb) n - i - p junctions for use in four-junction concentrating photovoltaic devices - Wilkins, Matthew M.; Gupta, James; Jaouad, Abdelatif; Bouzazi, Boussairi; Fafard, Simon; Boucherif, Abderraouf; Valdivia, Christopher E.; Arès, Richard; Aimez, Vincent; Schriemer, Henry P.; Hinzer, Karin (Journal of Photonics for Energy, 2017)
Four-junction solar cells for space and terrestrial applications require a junction with a band gap of ∼ 1  eV for optimal performance. InGaAsN or InGaAsN(Sb) dilute nitride junctions have been demonstrated for this purpose, but in achieving the 14    mA / cm 2 short-circuit current needed to match typical GaInP and GaAs junctions, the open-circuit voltage (V OC) and fill factor of these junctions are compromised. In multijunction devices incorporating materials with short diffusion lengths, we study the use of thin junctions to minimize sensitivity to varying material quality and ensure adequate transmission into lower junctions. An n - i - p device with 0.65 - μ m absorber thickness has sufficient short-circuit current, however, it relies less heavily on field-aided collection than a device with a 1 - μ m absorber. Our standard cell fabrication process, which includes a rapid thermal anneal of the contacts, yields a significant improvement in diffusion length and device performance. By optimizing a four-junction cell around a smaller 1-sun short-circuit current of 12.5  mA/cm 2, we produced an InGaAsN(Sb) junction with open-circuit voltage of 0.44 V at 1000 suns (1  sun = 100  mW / c>

Deep learning and the Schrödinger equation - Mills, Kyle; Spanner, Michael; Tamblyn, Isaac (Physical Review A, 2017)
We have trained a deep (convolutional) neural network to predict the ground-state energy of an electron in four classes of confining two-dimensional electrostatic potentials. On randomly generated potentials, for which there is no analytic form for either the potential or the ground-state energy, the model was able to predict the ground-state energy to within chemical accuracy, with a median absolute error of 1.49 mHa. We also investigated the performance of the model in predicting other quantities such as the kinetic energy and the first excited-state energy.

DDO 216-A1: a central globular cluster in a low-luminosity transition-type galaxy - Cole, Andrew A.; Weisz, Daniel R.; Skillman, Evan D.; Leaman, Ryan; Williams, Benjamin F.; Dolphin, Andrew E.; Johnson, L. Clifton; Mcconnachie, Alan W.; Boylan-Kolchin, Michael; Dalcanton, Julianne; Governato, Fabio; Madau, Piero; et al. (The Astrophysical Journal, 2017)
We confirm that the object DDO 216-A1 is a substantial globular cluster at the center of Local Group galaxy DDO 216 (the Pegasus dwarf irregular), using Hubble Space Telescope ACS imaging. By fitting isochrones, we find the cluster metallicity [M/H] = −1.6 ± 0.2, for reddening E(B–V) = 0.16 ± 0.02; the best-fit age is 12.3 ± 0.8 Gyr. There are $≈ 30$ RR Lyrae variables in the cluster; the magnitude of the fundamental mode pulsators gives a distance modulus of 24.77 ± 0.08—identical to the host galaxy. The ratio of overtone to fundamental mode variables and their mean periods make DDO 216-A1 an Oosterhoff Type I cluster. We find a central surface brightness of 20.85 ± 0.17 F814W mag arcsec−2, a half-light radius of $3\buildrel{′′}\over{.} 1$ (13.4 pc), and an absolute magnitude M814 = −7.90 ± 0.16 ($M/M_{\odot }$ ≈ 105). King models fit to the cluster give the core radius and concentration index, r c = $2\buildrel{′′}\over{.} 1$ ± $0\buildrel{′′}\over{.} 9$ and c = 1.24 ± 0.39. The cluster is an "extended" cluster somewhat typical of some dwarf galaxies and the outer halo of the Milky Way. The cluster is projected lesssim30 pc south of the center of DDO 216, unusually central compared to most dwarf galaxy globular clusters. Analytical models of dynamical friction and tidal destruction suggest that it probably formed at a larger distance, up to ~1 kpc, and migrated inward. DDO 216 has an unexceptional specific cluster frequency, S N = 10. DDO 216 is the lowest-luminosity Local Group galaxy to host a 105 ${M}_{\odot }$ globular cluster and the only transition-type (dSph/dIrr) galaxy in the Local Group with a globular cluster.

Data-driven classification of CH-146 manoeuvres using MEMS-IMU sensor system - Cheung, C.; Rubio, A. L.; Valdés, J. J. (AHS International. Annual Forum. Proceedings, 2017)
This paper describes the use of a low-cost standalone MEMS-IMU (micro-electromechanical system - inertial measurement unit) sensor system developed by the National Research Council Canada (NRC) for manoeuvre recognition in helicopters. The system records accelerations, angular rotation rates, magnetic flux, altitude, location and velocity through its IMU and GPS. The MEMS-IMU system was flown on the Bell 412 CH-146 Griffon helicopter in a series of scripted flights consisting of 60 manoeuvres and regimes from the helicopter's usage spectrum. A flight log recorded by passengers with detailed start and stop times and identification of the manoeuvres during flight was key information in the development of manoeuvre recognition models. Statistical tests to analyze the data diversity between each flight showed significant variability of the parameters from flight to flight. Because of this variability and because there was significant imbalance in the distribution of data for the individual manoeuvres, a pooled stratified sampling scheme was used to construct a representative training set for developing data-driven models. Different subsets of the MEMSIMU measurements were explored to exclude GPS and/or magnetometer readings. Even with the different subsets, the classifier results using stratified sampling show that very high overall classification accuracy can be obtained using the measurements from the standalone MEMS-IMU sensor system.

Damage control surgery in weightlessness: a comparative study of simulated torso hemorrhage control comparing terrestrial and weightless conditions - Kirkpatrick, Andrew W.; Mckee, Jessica Lynn; Tien, Homer; Laporta, Anthony J.; Lavell, Kit; Leslie, Tim; King, David R.; Mcbeth, Paul B.; Brien, Susan; Roberts, Derek J.; Franciose, Reginald; Wong, Jonathan; et al. (Journal of Trauma and Acute Care Surgery, 2017)
BACKGROUND Torso bleeding remains the most preventable cause of post-traumatic death worldwide. Remote damage control resuscitation (RDCR) endeavours to rescue the most catastrophically injured, but has not focused on prehospital surgical torso hemorrhage control (HC). We examined the logistics and metrics of intraperitoneal packing in weightlessness in Parabolic flight (0g) compared to terrestrial gravity (1g) as an extreme example of surgical RDCR. METHODS A surgical simulator was customized with high-fidelity intraperitoneal anatomy, a “blood” pump and flowmeter. A standardized HC task was to explore the simulator, identify “bleeding” from a previously unknown liver injury perfused at 80 mm Hg, and pack to gain hemostasis. Ten surgeons performed RDCR laparotomies onboard a research aircraft, first in 1g followed by 0g. The standardized laparotomy was sectioned into 20-second segments to conduct and facilitate parabolic flight comparisons, with “blood” pumped only during these time segments. A maximum of 12 segments permitted for each laparotomy. RESULTS All 10 surgeons successfully performed HC in both 1g and 0g. There was no difference in blood loss between 1g and 0g (p = 0.161) or during observation following HC (p = 0.944). Compared to 1g, identification of bleeding in 0g incurred less “blood” loss (p = 0.032). Overall surgeons rated their personal performance and relative difficulty of surgery in 0g as “harder” (median Likert, 2/5). However, conducting all phases of HC were rated equivalent between 1g and 0g (median Likert, 3/5), except for instrument control (rated slightly harder, 2.75/5). CONCLUSION Performing laparotomies with packing of a simulated torso hemorrhage in a high-fidelity surgical simulator was feasible onboard a research aircraft in both normal and weightless conditions. Despite being subjectively “harder,” most phases of operative intervention were rated equivalently, with no statistical difference in “blood” loss in weightlessness. Direct operative control of torso hemorrhage is theoretically possible in extreme environments if logistics are provided.

Critical phases of viral production processes monitored by capacitance - Petiot, Emma; Ansorge, Sven; Rosa-Calatrava, Manuel; Kamen, Amine (Journal of Biotechnology, 2017)
Over the last decade industrial manufacturing of viral vaccines and viral vectors for prophylactic and therapeutic applications is experiencing a remarkable growth. Currently, the quality attributes of viral derived products are assessed only at the end-point of the production process, essentially because in-process monitoring tools are not available or not implemented at industrial scale. However, to demonstrate process reproducibility and robustness, manufacturers are strongly advised by regulatory agencies to adopt more on-line process monitoring and control. Dielectric spectroscopy has been successfully used as an excellent indicator of the cell culture state in mammalian and yeast cell systems. We previously reported the use of this technique for monitoring influenza and lentiviral productions in HEK293 cell cultures. For both viruses, multi-frequency capacitance measurements allowed not only the on-line monitoring of the production kinetics, but also the identification of the viral release time from the cells. The present study demonstrates that the same approach can be successfully exploited for the on-line monitoring of different enveloped and non-enveloped virus production kinetics in cell culture processes. The on-line monitoring multi-frequency capacitance method was assessed in human HEK293 and Sf9 insect cells expression systems, with viral productions initiated by either infection or transfection. The comparative analyses of all the data acquired indicate that the characteristic capacitance signals were highly correlated with the occurrence of viral replication phases. Furthermore the evolution of the cell dielectric properties (intracellular conductivity and membrane capacitance) were indicative of each main replication steps. In conclusion, multi-frequency capacitance has a great potential for on-line monitoring, supervision and control of viral vector production in cell culture processes.
Keywords: on-line monitoring; capacitance probe; permittivity; characteristic frequency fc; virus production kinetics; dielectric cell properties; membrane capacitance; viral infection

Covalently assembled mnonolayers of homo- and heteroleptic FeII-terpyridyl complexes on SiOx and ITO-coated glass substrates: an experimental and theoretical study - Mondal, Prakash Chandra; Singh, Vikram; Manna, Arun K.; Zharnikov, Michael (ChemPhysChem, 2017)
Well-defined FeII-terpyridyl monolayers were fabricated on SiOx and conductive ITO-coated glass substrates through covalent-bond formation between the metallo-organic complexes and a preassembled coupling layer. Three different homo- and heteroleptic complexes with terminal pyridyl, amine, and phenyl groups were tested. All the films were found to be densely packed and homogeneous, and consist of molecules standing upright. They exhibited high thermal (up to ≈220 °C) and temporal (up to 5 h at 100 °C) stability. The UV/Vis spectra of the monolayers showed pronounced metal-to-ligand charge-transfer bands with a significant redshift compared with the solution spectra of the metallo-ligands with a pendant pyridyl group quaternized with the coupling layer, whereas the shift was significantly smaller when the coupling layer was bonded to the primary amine (−NH2) group of the complex. Cyclic voltammograms of the monolayers showed reversible, one-electron redox behavior and suggested strong electronic coupling between the confined molecules and the underlying substrate. Analysis of the electrochemistry data allowed us to estimate the charge-transfer rate constant between the metal center and the substrate. Additionally, detailed quantum-chemical calculations were performed to support and rationalize the experimentally observed photophysical properties of the FeII-terpyridyl complexes both in the solution state and when bound to a SiOx-based substrate.
Keywords: iron; metalloligands; monolayers; photophysics; rate constants

Coronafacoyl phytotoxin biosynthesis and evolution in the common scab pathogen Streptomyces scabiei - Bown, Luke; Li, Yuting; Berrué, Fabrice; Verhoeven, Joost T. P.; Dufour, Suzanne C.; Bignell, Dawn R. D. (Applied and Environmental Microbiology, 2017)
Coronafacoyl phytotoxins are an important family of plant toxins that are produced by several different phytopathogenic bacteria, including the gammaproteobacterium Pseudomonas syringae and the actinobacterium Streptomyces scabiei (formerly Streptomyces scabies). The phytotoxins consist of coronafacic acid (CFA) linked via an amide bond to different amino acids or amino acid derivatives. Previous work suggested that S. scabiei and P. syringae use distinct biosynthetic pathways for producing CFA, which is subsequently linked to its amino acid partner to form the complete phytotoxin. Here, we provide further evidence that the S. scabiei CFA biosynthetic pathway is novel by characterizing the role of CYP107AK1, a predicted cytochrome P450 that has no homologue in P. syringae. Deletion of the CYP107AK1 gene abolished production of coronafacoyl-isoleucine (CFA-Ile), the primary coronafacoyl phytotoxin produced by S. scabiei. Structural elucidation of accumulated biosynthetic intermediates in the ΔCYP107AK1 mutant indicated that CYP107AK1 is required for introducing the oxygen atom that ultimately forms the carbonyl group in the CFA backbone. The CYP107AK1 gene along with two additional genes involved in CFA-Ile biosynthesis in S. scabiei were found to be associated with putative CFA biosynthetic genes in other actinobacteria but not in other organisms. Analysis of the overall genetic content and organization of known and putative CFA biosynthetic gene clusters, together with phylogenetic analysis of the core biosynthetic genes, indicates that horizontal gene transfer has played an important role in the dissemination of the gene cluster and that rearrangement, insertion, and/or deletion events have likely contributed to the divergent biosynthetic evolution of coronafacoyl phytotoxins in bacteria.
Keywords: biosynthesis; coronafacoyl phytotoxin; coronatine; cytochrome P450; gene cluster; jasmonic acid; Pseudomonas syringae; Streptomyces scabiei; plant pathogens; signaling

Controlling the orbital angular momentum of high harmonic vortices - Kong, Fanqi; Zhang, Chunmei; Bouchard, Frédéric; Li, Zhengyan; Brown, Graham G.; Ko, Dong Hyuk; Hammond, T. J.; Arissian, Ladan; Boyd, Robert W.; Karimi, Ebrahim; Corkum, P. B. (Nature Communications, 2017)
Optical vortices, which carry orbital angular momentum (OAM), can be flexibly produced and measured with infrared and visible light. Their application is an important research topic for super-resolution imaging, optical communications and quantum optics. However, only a few methods can produce OAM beams in the extreme ultraviolet (XUV) or X-ray, and controlling the OAM on these beams remains challenging. Here we apply wave mixing to a tabletop high-harmonic source, as proposed in our previous work, and control the topological charge (OAM value) of XUV beams. Our technique enables us to produce first-order OAM beams with the smallest possible central intensity null at XUV wavelengths. This work opens a route for carrier-injected laser machining and lithography, which may reach nanometre or even angstrom resolution. Such a light source is also ideal for space communications, both in the classical and quantum regimes.

Control of rectification in molecular junctions: contact effects and molecular signature - Nguyen, Quyen van; Martin, Pascal; Frath, Denis; Della Rocca, Maria Luisa; Lafolet, Frederic; Barraud, Clément; Lafarge, Philippe; Mukundan, Vineetha; James, David; Mccreery, Richard L.; Lacroix, Jean-Christophe (Journal of the American Chemical Society, 2017)
Thin layers of oligomers with thickness between 7 and 9 nm were deposited on flat gold electrode surfaces by electrochemical reduction of diazonium reagents, then a Ti(2 nm)/Au top contact was applied to complete a solid-state molecular junction. The molecular layers investigated included donor molecules with relatively high energy HOMO, molecules with high HOMO–LUMO gaps and acceptor molecules with low energy LUMO and terminal alkyl chain. Using an oligo(bisthienylbenzene) based layer, a molecule whose HOMO energy level in a vacuum is close to the Fermi level of the gold bottom electrode, the devices exhibit robust and highly reproducible rectification ratios above 1000 at low voltage (2.7 V). Higher current is observed when the bottom gold electrode is biased positively. When the molecular layer is based on a molecule with a high HOMO–LUMO gap, i.e., tetrafluorobenzene, no rectification is observed, while the direction of rectification is reversed if the molecular layer consists of naphtalene diimides having low LUMO energy level. Rectification persisted at low temperature (7 K), and was activationless between 7 and 100 K. The results show that rectification is induced by the asymmetric contact but is also directly affected by orbital energies of the molecular layer. A “molecular signature” on transport through layers with thicknesses above those used when direct tunneling dominates is thus clearly observed, and the rectification mechanism is discussed in terms of Fermi level pinning and electronic coupling between molecules and contacts.

Context-based abrupt change detection and adaptation for categorical data streams - D’ettorre, Sarah; Viktor, Herna L.; Paquet, Eric (Discovery Science, 2017)
The identification of changes in data distributions associated with data streams is critical in understanding the mechanics of data generating processes and ensuring that data models remain representative through time. To this end, concept drift detection methods often utilize statistical techniques that take numerical data as input. However, many applications produce data streams containing categorical attributes, where numerical statistical methods are not applicable. In this setting, common solutions use error monitoring, assuming that fluctuations in the error measures of a learning system correspond to concept drift. Context-based concept drift detection techniques for categorical streams, which observe changes in the actual data distribution, have received limited attention. Such context-based change detection is arguably more informative as it is data-driven and directly applicable in an unsupervised setting. This paper introduces a novel context-based algorithm for categorical data, namely FG-CDCStream. In this unsupervised method, multiple drift detection tracks are maintained and their votes are combined in order to determine whether a real change has occurred. In this way, change detections are rapid and accurate, while the number of false alarms remains low. Our experimental evaluation against synthetic data streams shows that FG-CDCStream outperforms the state-of-the art. Our analysis further indicates that FG-CDCStream produces highly accurate and representative post-change models.
Keywords: data streams; categorical data; concept drift; context-based change detection; unsupervised learning; ensembles; online learning

Constraining the pitch angle of the galactic spiral arms in the Milky Way - Vallée, Jacques P. (New Astronomy Reviews, 2017)
We carry out analyses of some parameters of the galactic spiral arms, in the currently available samples. We present a catalog of the observed pitch angle for each spiral arm in the Milky Way disk. For each long spiral arm in the Milky Way, we investigate for each individual arm its pitch angle, as measured through different methods (parallaxes, twin-tangent arm, kinematical, etc), and assess their answers. Second, we catalog recent advances in the cartography of the Galaxy (global mean arm pitch, arm number, arm shape, interarm distance at the Sun). We statistically compare the results over a long time frame, from 1980 to 2017. Histograms of about 90 individual results published in recent years (since mid-2015) are compared to 66 earlier results (from 1980 to 2005), showing the ratio of primary to secondary peaks to have increased by almost a factor of 3. Similarly, many earlier discrepancies (expressed in r.m.s.) have been reduced by almost a factor 3.
Keywords: Galaxies: spiral; Galaxy: disk; Galaxy: structure; Methods: statistical; ISM: general; ISM: structure

Consequences of a distant massive planet on the large semimajor axis trans-Neptunian objects - Shankman, C.; Kavelaars, J. J.; Lawler, S. M.; Gladman, B. J.; Bannister, M. T. (The Astronomical Journal, 2017)
We explore the distant giant planet hypothesis by integrating the large-semimajor-axis, large-pericenter trans-Neptunian objects (TNOs) in the presence of the giant planets and an external perturber whose orbit is consistent with the proposed distant, eccentric, and inclined giant planet, so-called planet 9. We find that TNOs with semimajor axes greater than 250 au experience some longitude of perihelion shepherding, but that a generic outcome of such evolutions is that the TNOs evolve to larger pericenter orbits and commonly get raised to retrograde inclinations. This pericenter and inclination evolution requires a massive disk of TNOs (tens of ${M}_{\oplus }$) in order to explain the detection of the known sample today. Some of the highly inclined orbits produced by the examined perturbers will be inside of the orbital parameter space probed by prior surveys, implying a missing signature of the ninth-planet scenario. The distant giant planet scenarios explored in this work do not reproduce the observed signal of simultaneous clustering in argument of pericenter, longitude of the ascending node, and longitude of perihelion in the region of the known TNOs.
Keywords: Kuiper belt: general; planet; disk interactions

Conformational dynamics of the frameshift stimulatory structure in HIV-1 - Ritchie, Dustin B.; Cappellano, Tonia R.; Tittle, Collin; Rezajooei, Negar; Rouleau, Logan; Sikkema, William K.A.; Woodside, Michael T. (RNA, 2017)
Programmed ribosomal frameshifting (PRF) in HIV-1 is thought to be stimulated by a hairpin in the mRNA, although a pseudoknot-like triplex has also been proposed. Because the conformational dynamics of the stimulatory structure under tension applied by the ribosomal helicase during translation may play an important role in PRF, we used optical tweezers to apply tension to the HIV stimulatory structure and monitor its unfolding and refolding dynamics. The folding and unfolding kinetics and energy landscape of the hairpin were measured by ramping the force on the hairpin up and down, providing a detailed biophysical characterization. Unexpectedly, whereas unfolding reflected the simple two-state behavior typical of many hairpins, refolding was more complex, displaying significant heterogeneity. Evidence was found for multiple refolding pathways as well as previously unsuspected, partially folded intermediates. Measuring a variant mRNA containing only the sequence required to form the proposed triplex, it behaved largely in the same way. Nonetheless, very rarely, high-force unfolding events characteristic of pseudoknot-like structures were observed. The rare occurrence of the triplex suggests that the hairpin is the functional stimulatory structure. The unusual heterogeneity of the hairpin dynamics under tension suggests a possible functional role in PRF similar to the dynamics of other stimulatory structures.
Keywords: programmed ribosomal frameshifting; RNA folding; force spectroscopy; optical tweezers

Composite spectra, paper XXI: 14 serpentis - Griffin, R. E. M.; Griffin, R. F. (Astronomische Nachrichten, 2017)
We separate the component spectra of the composite-spectrum binary 14 Serpentis, derive a precise double-lined (SB2) orbit for the system, and investigate the physical properties and evolutionary states of its component stars. The 260-day binary is comprised of an early-K giant plus a late-Am star that is rotating at ∼60–70 km s−1. We find that the system has a mass ratio (M1/M2) of 1.14 ± 0.01, and that the cool star is ∼1.7 times as bright as its hot companion in V, though ∼2.5 times brighter bolometrically. We derive individual masses and logarithmic luminosities of the cool star and the hotter one as 2.05 and 1.8 M⊙, and 1.57 and 1.18 log L⊙, respectively, with corresponding uncertainties close to 0.1 M⊙ and 0.07 log L⊙. Fitting evolutionary tracks to the H–R diagram positions of the two stars suggests that the cool primary is part-way up the red-giant branch and that the system has been evolving for more than 109 years; the absence of Li from its spectrum may support the latter statement. The hotter, less massive companion appears to have left the zero-age main sequence, which accords with the log g<4.0 indicated by comparisons with synthetic spectra, though its radius is currently only 2.5 R⊙.

Complex spiral structure in the HD 100546 transitional disk as revealed by GPI and MagAO - Follette, Katherine B.; Rameau, Julien; Dong, Ruobing; Pueyo, Laurent; Close, Laird M.; Duchêne, Gaspard; Fung, Jeffrey; Leonard, Clare; Macintosh, Bruce; Males, Jared R.; Marois, Christian; Millar-blanchaer, Maxwell A.; et al. (The Astronomical Journal, 2017)
We present optical and near-infrared high-contrast images of the transitional disk HD 100546 taken with the Magellan Adaptive Optics system (MagAO) and the Gemini Planet Imager (GPI). GPI data include both polarized intensity and total intensity imagery, and MagAO data are taken in Simultaneous Differential Imaging mode at Hα. The new GPI H-band total intensity data represent a significant enhancement in sensitivity and field rotation compared to previous data sets and enable a detailed exploration of substructure in the disk. The data are processed with a variety of differential imaging techniques (polarized, angular, reference, and simultaneous differential imaging) in an attempt to identify the disk structures that are most consistent across wavelengths, processing techniques, and algorithmic parameters. The inner disk cavity at 15 au is clearly resolved in multiple data sets, as are a variety of spiral features. While the cavity and spiral structures are identified at levels significantly distinct from the neighboring regions of the disk under several algorithms and with a range of algorithmic parameters, emission at the location of HD 100546 "c" varies from point-like under aggressive algorithmic parameters to a smooth continuous structure with conservative parameters, and is consistent with disk emission. Features identified in the HD 100546 disk bear qualitative similarity to computational models of a moderately inclined two-armed spiral disk, where projection effects and wrapping of the spiral arms around the star result in a number of truncated spiral features in forward-modeled images.

Comparisons of a chemical transport model with a four-year (April to September) analysis of fine- and coarse-mode aerosol optical depth retrievals over the Canadian Arctic - Hesaraki, Sareh; O'neill, Norman T.; Lesins, Glen; Saha, Auromeet; Martin, Randall V.; Fioletov, Vitali E.; Baibakov, Konstantin; Abboud, Ihab (Atmosphere-Ocean, 2017)
We compared April to September retrievals of total, fine-mode (sub-micron), and coarse-mode (super-micron) aerosol optical depth (AOD) from the Aerosol Robotic Network (AERONET) with simulations from a global three-dimensional chemical transport model, the Goddard Earth Observing System (GEOS-Chem), across five Arctic stations and a four-year sampling period. It was determined that the AOD histograms of both the retrievals and the simulations were better represented by a lognormal distribution and that the successful simulation of this empirical feature as well as its consequences (including a better model versus retrieval coefficient of determination in log-log AOD space) represented a general indicator of model evaluation success. Seasonal (monthly averaged) AOD retrievals were sensitive to the way in which the averaging was performed; this was ascribed to the presence of highly variable fine-mode smoke in the western Arctic. The retrieved and modelled station-by-station fine-mode AOD averages showed a peak in April/May that decreased over the summer, while the model underestimated the fine-mode AOD by an average of about 0.004 (∼6%). Both the retrievals and simulations showed seasonal coarse-mode AOD variations with a peak in April/May that was attributed to Asian and/or Saharan dust. The model's success in capturing such weak seasonal events helps to confirm the relevance of the separation of the fine and coarse modes and the general validity of model estimates in the Arctic.
Keywords: AERONET; aerosol optical depth; Arctic; chemical transport model; GEOS-Chem

Comparative analysis highlights variable genome content of wheat rusts and divergence of the mating loci - Cuomo, Christina A.; Bakkeren, Guus; Khalil, Hala Dadr; Panwar, Vinay; Joly, David; Linning, Rob; Sakthikumar, Sharadha; Song, Xiao; Adiconis, Xian; Fan, Lin; Goldberg, Jonathan M.; Levin, Joshua Z.; et al. (G3: Genes, Genomes, Genetics (Bethesda), 2017)
Three members of the Puccinia genus, Puccinia triticina (Pt), P. striiformis f.sp. tritici (Pst), and P. graminis f.sp. tritici (Pgt), cause the most common and often most significant foliar diseases of wheat. While similar in biology and life cycle, each species is uniquely adapted and specialized. The genomes of Pt and Pst were sequenced and compared to that of Pgt to identify common and distinguishing gene content, to determine gene variation among wheat rust pathogens, other rust fungi, and basidiomycetes, and to identify genes of significance for infection. Pt had the largest genome of the three, estimated at 135 Mb with expansion due to mobile elements and repeats encompassing 50.9% of contig bases; in comparison, repeats occupy 31.5% for Pst and 36.5% for Pgt. We find all three genomes are highly heterozygous, with Pst [5.97 single nucleotide polymorphisms (SNPs)/kb] nearly twice the level detected in Pt (2.57 SNPs/kb) and that previously reported for Pgt. Of 1358 predicted effectors in Pt, 784 were found expressed across diverse life cycle stages including the sexual stage. Comparison to related fungi highlighted the expansion of gene families involved in transcriptional regulation and nucleotide binding, protein modification, and carbohydrate degradation enzymes. Two allelic homeodomain pairs, HD1 and HD2, were identified in each dikaryotic Puccinia species along with three pheromone receptor (STE3) mating-type genes, two of which are likely representing allelic specificities. The HD proteins were active in a heterologous Ustilago maydis mating assay and host-induced gene silencing (HIGS) of the HD and STE3 alleles reduced wheat host infection.
Supplemental files are available on the publisher's website
Les fichiers supplémentaires sont disponibles sur le site Web de l'éditeur

Comparative activity and functional ecology of permafrost soils and lithic niches in a hyper-arid polar desert - Goordial, Jacqueline; Davila, Alfonso; Greer, Charles W.; Cannam, Rebecca; Diruggiero, Jocelyne; Mckay, Christopher P.; Whyte, Lyle G. (Environmental Microbiology, 2017)
Permafrost in the high elevation McMurdo Dry Valleys of Antarctica ranks among the driest and coldest on Earth. Permafrost soils appear to be largely inhospitable to active microbial life, but sandstone lithic microhabitats contain a trophically simple but functional cryptoendolithic community. We used metagenomic sequencing and activity assays to examine the functional capacity of permafrost soils and cryptoendolithic communities in University Valley, one of the most extreme regions in the Dry Valleys. We found metagenomic evidence that cryptoendolithic microorganisms are adapted to the harsh environment and capable of metabolic activity at in situ temperatures, possessing a suite of stress response and nutrient cycling genes to fix carbon under the fluctuating conditions that the sandstone rock would experience during the summer months. We additionally identified genes involved in microbial competition and cooperation within the cryptoendolithic habitat. In contrast, permafrost soils have a lower richness of stress response genes, and instead the metagenome is enriched in genes involved with dormancy and sporulation. The permafrost soils also have a large presence of phage genes and genes involved in the recycling of cellular material. Our results underlie two different habitability conditions under extreme cold and dryness: the permafrost soil which is enriched in traits which emphasize survival and dormancy, rather than growth and activity; and the cryptoendolithic environment that selects for organisms capable of growth under extremely oligotrophic, arid and cold conditions. This study represents the first metagenomic interrogation of Antarctic permafrost and polar cryptoendolithic microbial communities.

Comment on: Quasi-elastic neutron scattering investigation of the guest molecule dynamics in the bromomethane clathrate hydrate - Ripmeester, John A.; Ratcliffe, Christopher I. (Fluid Phase Equilibria, 2017)
This comment addresses several points presented in a recent paper in the Journal that affect the interpretation of data obtained in a study of quasi-elastic neutron scattering in methyl bromide clathrate hydrate. The clathrate belongs to a class known as cubic structure I and it has two sites in its hydrogen-bonded network suitable for guest molecules, one in the large cavity in the structure, the other in the small cavity. The data obtained for methyl bromide hydrate were assigned to the two presumed populations of methyl bromide molecules. However, previous composition measurements and NMR data have shown that the small cavity in fact does not contain methyl bromide molecules. This also becomes obvious once the dimensions of the methyl bromide and the host cavity are calculated, the molecule being too large to fit into the cavity by nearly 0.1 nm. Thus the interpretation of data as assigned in the paper cannot be correct. Finally, although the authors claim new insights into guest –host interactions from guest dynamics, this should be presented in light of previous relevant work where this topic has been thoroughly evaluated.
Keywords: clathrate; hydrate; composition; dynamics; NMR

Contrasting root and photosynthesis traits in a large-acreage Canadian durum variety and its distant parent of algerian origin for assembling drought/heat tolerance attributes - Ashe, Paula; Shaterian, Hamid; Akhov, Leonid; Kulkarni, Manoj; Selvaraj, Gopalan (Frontiers in Chemistry, 2017)
In Canada, the world's top exporter of high-protein durum, varietal development over its nearly six-decade history has been driven by a quest for yield improvement without compromise on grain protein content and other quality aspects. Pelissier, a landrace selection from Algeria that was introduced into North America more than a century ago and the variety Strongfield that was released in 2004 are notable. Pelissier, known to elaborate more roots and considered as drought tolerant, has been cultivated commercially and thus deemed adapted. Strongfield has Pelissier in its pedigree, and it remains a high-acreage variety. Strongfield was found to elaborate only about half of the root biomass of Pelissier at maturity in greenhouse trials under well-watered conditions. Extended drought stress caused a significant reduction in the root biomass of both lines. However, Pelissier under drought maintained at least as much root biomass as that of Strongfield under well-watered conditions. In comparison to Pelissier, it had a superior photosynthesis rate (27.16 μmol CO2 m−2 s−1), capacity for carboxylation (Vcmax: 132.83 μmol CO2 m−2 s−1) and electron transport/ribulose-1,5–bisphosphate (RuBP) regeneration (Jmax: 265.40 μmol CO2 m−2 s−1); the corresponding values for Pelissier were 19.62 μmol CO2 m−2 s−1, 91.87 μmol CO2 m−2 s−1, and 163.83 μmol CO2 m−2 s−1, respectively, under well-watered conditions. Under short-term/mild drought conditions, the carbon assimilation rate remained stable in Pelissier while it declined in Strongfield to the Pelissier level. However, Strongfield succumbed to extended drought sooner than Pelissier. Photosynthesis in Strongfield but not Pelissier was found to be sensitive to high temperature stress. These results provide encouraging prospects for further exploitation of beneficial physiological traits from Pelissier in constructing climate-resilient, agronomically favorable wheat ideotypes.
Keywords: abiotic stress; drought; durum wheat; heat; photosynthesis; root

Comment on “Exploring dynamics and cage–guest interactions in clathrate hydrates using solid-state NMR” - Moudrakovski, Igor L.; Ripmeester, John A (The Journal of Physical Chemistry B, 2017)
Structure II tetrahydrofuran (THF) hydrate is one of the most frequently studied clathrate hydrates as it is easily made by freezing a solution of composition THF·17H2O. The resulting hydrate is stable at atmospheric pressure up to a congruent melting point of 277.5 K (4.4 °C).(1, 2) This hydrate is often used as a proxy for studies of materials that are more difficult to prepare, such as natural gas hydrates.(3-8) As a system for learning about guest–host interactions, the dynamics of both guest (THF/THF-d8) and host (H2O/D2O) have been of wide interest as shown by the large number of solid-state NMR and dielectric measurements performed over a temperature range from ∼4 K up to near the melting point at 277.5 K.(9-23) Both guest and water molecular reorientation and water diffusion have been observed, and various mechanistic models, including the effects of various defects, have been proposed to account for the experimental results. Transient guest–host hydrogen bond formation in THF and other ether and ketone hydrates was first proposed by Davidson(11) and confirmed from spectroscopic measurements,(15, 24) molecular dynamics simulation,(25, 26) and single crystal X-ray diffraction.(27) The paper featured in the title of this Comment(23) recently reported yet another set of measurements, six longitudinal 1H relaxation times (T1) on THF·17D2O, this time under magic angle spinning (MAS) conditions, purportedly to obtain high resolution information as there are two sets of resolvable protons on the inequivalent methylene carbons. Since the results of these measurements were very different from T1 measurements taken on static samples, an explanation was proposed that involved changes in the THF reorientational activation energy from ∼4 kJ/m at T < 200 K to nearly 20 kJ/m at T > 200 K. This radical change was attributed to increased hydrogen bonding between THF and D2O. We think this is rather unlikely for ether–water interactions. If we take the difference in activation energies for guest reorientation for cyclopentane hydrate and THF hydrate, ∼16 kJ/mol, attribute this to hydrogen bond formation in THF hydrate, and compare this to the estimated hydrogen bond energy in ice at 16–32 kJ/mol,(28) it would predict that THF should be a good hydrate inhibitor rather than a weakly interacting hydrate guest as it will compete with the hydrogen bond formation between water molecules. We have taken literature T1 data obtained for static samples of sII deuteriohydrates of THF (ethylene oxide (EO)-d4), cyclopentane, and dioxolane (Figure 1) published by Jacobs, Zeidler, and Kanert,(18) (Figure S1) and compared these with the MAS T1 measurements (gray rectangle marked a, Figure 1).(23) The literature T1 data for the three hydrates show that the relaxation rates decrease with increasing temperature, with some flattening out of the curves at the highest temperature of measurements. In agreement with other measurements, this trend in T1 is associated with 1H dipolar relaxation due to the reorientational motion of guest molecules in the hydrate cavities in the fast motion limit. The flattening out of the T1 curves leads to a T1 maximum,(10, 12) and then to a decrease in T1 with increasing temperature as slow water motion starts to contribute to the relaxation. This gives a frequency-dependent T1 decrease, evident from measurements at lower frequencies (10 and 30 MHz(10, 12)) to a new T1 minimum, not observed as it would occur above the sample melting point. This new motion is a reorientation of the water molecules, which is also observable by T1ρ measurements and usually assigned to be a process driven by the diffusion of Bjerrum defects.(29, 30) The guest T1 relaxation responds to this motion by (a) cross relaxation of 1H to 2H in water, (b) spin diffusion to residual 1H in the D2O, and (c) changes in guest motion as the symmetry of the hydrate cages changes when the disorder in the water proton positions becomes dynamic. This picture is generally consistent with all static line width, T1, and T1ρ experimental results.

Combining metabolic and process engineering strategies to improve recombinant glycoprotein production and quality - Karengera, Eric; Durocher, Yves; De Crescenzo, Gregory; Henry, Olivier (Applied Microbiology and Biotechnology, 2017)
Increasing recombinant protein production while ensuring a high and consistent protein quality remains a challenge in mammalian cell culture process development. In this work, we combined a nutrient substitution approach with a metabolic engineering strategy that improves glucose utilization efficiency. This combination allowed us to tackle both lactate and ammonia accumulation and investigate on potential synergistic effects on protein production and quality. To this end, HEK293 cells overexpressing the pyruvate yeast carboxylase (PYC2) and their parental cells, both stably producing the therapeutic glycoprotein interferon α2b (IFNα2b), were cultured in media deprived of glutamine but containing chosen substitutes. Among the tested substitutes, pyruvate led to the best improvement in growth (integral of viable cell density) for both cell lines in batch cultures, whereas the culture of PYC2 cells without neither glutamine nor any substitute displayed surprisingly enhanced IFNα2b production. The drastic reduction in both lactate and ammonia in the cultures translated into extended high viability conditions and an increase in recombinant protein titer by up to 47% for the parental cells and the PYC2 cells. Product characterization performed by surface plasmon resonance biosensing using Sambucus nigra (SNA) lectin revealed that the increase in yield was however accompanied by a reduction in the degree of sialylation of the product. Supplementing cultures with glycosylation precursors and a cofactor were effective at counterbalancing the lack of glutamine and allowed improvement in IFNα2b quality as evaluated by lectin affinity. Our study provides a strategy to reconcile protein productivity and quality and highlights the advantages of PYC2-overexpressing cells in glutamine-free conditions.
Keywords: HEK293 cells; PYC2-overexpression; protein sialylation; nutrient substitution

Modeling and prediction of regional municipal solid waste generation and diversion in Canada using machine learning approaches - Kannangara, Miyuru; Dua, Rahul; Ahmadi, Leila; Bensebaa, Farid (Waste Management, 2017)
The main objective of this study was to develop models for accurate prediction of municipal solid waste (MSW) generation and diversion based on demographic and socio-economic variables, with planned application of generating Canada-wide MSW inventories. Models were generated by mapping residential MSW quantities with socio-economic and demographic parameters of 220 municipalities in the province of Ontario, Canada. Two machine learning algorithms, namely decision trees and neural networks, were applied to build the models. Socio-economic variables were derived from Canadian Census data at regional and municipal levels. A data pre-processing and integration framework was developed in Matlab® computing software to generate datasets with sufficient data quantity and quality for modeling. Results showed that machine learning algorithms can be successfully used to generate waste models with good prediction performance. Neural network models had the best performance, describing 72% of variation in the data. The approach proposed in this study demonstrates the feasibility of creating tools that helps in regional waste planning by means of sourcing, pre-processing, integrating and modeling of publically available data from various sources.
Keywords: municipal solid waste; forecasting; machine learning; modeling; neural networks; decision trees

Structural and immunological characterization of a glycoconjugate based on the delipidated lipopolysaccharide from a nontypeable Helicobacter pylori strain PJ1 containing an extended d - glycero - d - manno -heptan - Altman, Eleonora; Chandan, Vandana; Harrison, Blair A.; Vinogradov, Evgeny (Carbohydrate Research, 2017)
Structural characterization of the lipopolysaccharide (LPS) from a nontypeable Helicobacter pylori strain PJ1 and two corresponding mutants, PJ1 HP1283:cam and PJ1 HP1284:cam, was performed using a combination of NMR and mass spectrometric techniques. It resulted in the core structure that differed significantly from the one proposed previously. Overall architecture of PJ1 LPS was found to be consistent with a structural model described for several other H. pylori strains. It contained a polymer of d-glycero-d-manno-heptose (dd-Hep) as the O-chain component, linked to α-1,6-glucan through a dd-Hep oligosaccharide. H. pylori PJ1 HP1283:cam LPS was missing dd-heptan, terminating with an α-1,6-glucan chain containing 5–13 glucose residues. LPS of strain PJ1 HP1284:cam was missing dd-Hep from the core and had β-GlcNAc attached directly to O-3 of the inner-core ld-Hep residue. To investigate the role of dd-heptan in protective immunity, delipidated LPS (dLPS) from strain PJ1 was conjugated to tetanus toxoid (TT) and immunological properties of the resultant glycoconjugate dLPS(PJ1)-TT determined. The dLPS(PJ1)-TT conjugate was immunogenic in mice and rabbits and induced specific and cross-reactive functional antibodies against homologous and heterologous strains of H. pylori. Whole cell indirect ELISA performed on a selected number of H. pylori isolates confirmed that the immune response correlated with the presence of α-1,6-glucan and was not augmented by the dd-Hep content of these strains.
Keywords: helicobacter pylori; LPS; vaccine; conjugate; structure

Understanding the cold spray deposition efficiencies of 316L/Fe mixed powders by performing splat tests onto as-polished coatings - Chu, Xin; Che, Hanqing; Vo, Phuong; Chakrabarty, Rohan; Sun, Binhan; Song, Jun; Yue, Stephen (Surface and Coatings Technology, 2017)
Some of the current trends in cold spray include the production of metal-metal composite coatings; however, the deposition mechanisms of mixed powders are often vaguely understood. In this study, single component 316L stainless steel and Fe coatings, as well as composite 316L/Fe coatings, were deposited through cold spray and the deposition efficiencies (DE) were measured. The composite coatings featuring various feedstock fractions were produced using a dual powder feeder setup. Splat tests were then performed on the as-polished coatings to investigate the deposition behavior of each component powder on the previously deposited layers. Bond ratio (BR) was determined from the splat tests to correlate with DE. Results show that the 316L powder has a better DE than Fe; whereas the DE of 316L/Fe mixed powder increases with increasing the mixture feedstock Fe fraction. The BR was found to correlate well with the DE of both single component and mixed powders. For the individual deposition behavior of the component powder, the BR of 316L monotonically decreases on the composite coating with an increasing Fe fraction; while the BR of Fe plateaus at a relatively high value regardless of the composite coating composition, which results in the overall increase of mixture DE.
Keywords: cold spray; mixed metal powder; deposition efficiency; splat test; bond ratio

Combing context and commonsense knowledge through neural networks for solving winograd schema problems - Liu, Quan; Jiang, Hui; Ling, Zhen-Hua; Zhu, Xiaodan; Wei, Si; Hu, Yu (2017 AAAI Spring Symposium Series, 2017)
This paper proposes a general framework to combine context and commonsense knowledge for solving the Winograd Schema (WS) and Pronoun Disambiguation Problems (PDP). In the proposed framework, commonsense knowledge bases (e.g. cause-effect word pairs) are quantized as knowledge constraints. The constraints guide us to learn knowledge enhanced embeddings (KEE) from large text corpus. Based on the pre-trained KEE models, this paper proposes two methods to solve the WS and PDP problems. The first method is an unsupervised method, which represents all the pronouns and candidate mentions in continuous vector spaces based on their contexts and calculates the semantic similarities between all the possible word pairs. The pronoun disambiguation procedure could then be implemented by comparing the semantic similarities between the pronoun (to be resolved) and all the candidate mentions. The second method is a supervised method, which extracts features for all the pronouns and candidate mentions and solves the WS problems by training a typical mention pair classification model. Similar to the first method, the features used in the second method are also extracted based on the KEE models. Experiments conducted on the available PDP and WS test sets show that, these two methods both achieve consistent improvements over the baseline systems. The best performance reaches 62% in accuracy on the PDP test set of the first Winograd Schema Challenge.

Colloidal behavior of aqueous cellulose nanocrystal suspensions - Oguzlu, Hale; Danumah, Christophe; Boluk, Yaman (Current Opinion in Colloid & Interface Science, 2017)
In this short review, we discuss the colloidal microstructure of sulfonated cellulose nanocrystal (CNC) suspensions and connect to their rheological behavior in the presence of electrolyte, by changing its surface chemistry and also in dilute water soluble polymer solutions. Presence of electrolyte has a significant effect depending both on the concentrations of CNC and electrolyte. The salt presence on the microstructure of CNC suspensions were successfully explained by DLVO theory. Even within the dilute concentration regime (< 0.5 vol%), CNC particles can form gels either by adding high concentration of electrolyte or low concentration (around overlapping concentration) of non-adsorbing polymer. Addition of water soluble polymers may cause depletion of CNC if the polymer is not adsorbing. It is believed that the depletion flocculation is the case for the effects of carboxymethyl cellulose (CMC) polymer chains in CNC suspensions and cause significant gelling.
Keywords: sulfonated; cellulose nanocrystals; microstructure; rheology; gels; electrolyte; polymer; depletion

Collisional frequency shift of a trapped-ion optical clock - Vutha, Amar C.; Kirchner, Tom; Dubé, Pierre (Physical Review A, 2017)
Collisions with background gas can perturb the transition frequency of trapped ions in an optical atomic clock. We develop a nonperturbative framework based on a quantum channel description of the scattering process and use it to derive a master equation which leads to a simple analytic expression for the collisional frequency shift. As a demonstration of our method, we calculate the frequency shift of the Sr+ optical atomic clock transition due to elastic collisions with helium.

Cold spray of mixed metal powders on carbon fibre reinforced polymers - Che, Hanqing; Chu, Xin; Vo, Phuong; Yue, Stephen (Surface and Coatings Technology, 2017)
Metallization of polymers and polymer composites has attracted interest recently. Cold spray is an emerging coating method, but direct cold spray of metals on carbon fibre reinforced polymer (CFRP) is difficult. Previous results show that tin coatings can be cold sprayed on CFRP, but the deposition efficiency is relatively low. In this work, copper and zinc powders were mixed with tin to investigate the effect of mixing on deposition efficiency of the coating. The mixed metal powders were cold sprayed on CFRP with a low-pressure system at various conditions. Results show that the addition of copper and zinc led to much higher deposition efficiencies compared to the pure tin coating. Based on the results, the deposition mechanism of the mixed metal powders on CFRP is discussed, the effect of mixing powders on deposition efficiency is analyzed and several mechanisms are proposed accordingly.
Keywords: cold spray; mixed metal powders; carbon fibre reinforced polymer; metallization of polymers

Cold spray deposition of Ni and WC-reinforced Ni matrix composite coatings - Alidokht, S. A.; Vo, P.; Yue, S.; Chromik, R. R. (Journal of Thermal Spray Technology, 2017)
Ni-WC composites are ideal protective coatings against wear and are often fabricated using laser cladding and thermal spray processes, but the high temperatures of these processes result in decarburization, which deteriorates the performance of the coating. Cold spray has the potential to deposit Ni-WC composite coatings and retain the composition of the initial WC feedstock. However, the insignificant plastic deformation of hard WC particles makes it difficult to build up a high WC content coating by cold spray. By using three different WC powder sizes, the effect of feedstock powder size on WC retention was tested. To improve WC retention, a WC/Ni composite powder in mixture with Ni was also sprayed. Microstructural characterization, including the deformed structure of Ni splats, retention, distribution, and fragmentation of WC, was performed by scanning electron microscopy. An improvement in WC retention was achieved using finer WC particles. Significant improvement in WC particles retention was achieved using WC/Ni composite powder, with the WC content in the coating being close to that of the feedstock.
Keywords: cold spraying; hardness; metal matrix composite; WC

Coherent imaging of an attosecond electron wave packet - Villeneuve, D. M.; Hockett, Paul; Vrakking, M. J. J.; Niikura, Hiromichi (Science, 2017)
Electrons detached from atoms or molecules by photoionization carry information about the quantum state from which they originate, as well as the continuum states into which they are released. Generally, the photoelectron momentum distribution is composed of a coherent sum of angular momentum components, each with an amplitude and phase. Here we show, by using photoionization of neon, that a train of attosecond pulses synchronized with an infrared laser field can be used to disentangle these angular momentum components. Two-color, two-photon ionization via a Stark-shifted intermediate state creates an almost pure f-wave with a magnetic quantum number of zero. Interference of the f-wave with a spherically symmetric s-wave provides a holographic reference that enables phase-resolved imaging of the f-wave.

Chronic kidney disease of unknown etiology and the effect of multiple-ion interactions - Dharma-Wardana, M. W. C. (Environmental Geochemistry and Health, 2017)
High incidence of chronic kidney disease of unknown etiology (CKDU) prevalent in many countries (e.g., Sri Lanka, equatorial America) is reviewed in the context of recent experimental work and using our understanding of the hydration of ions and proteins. Qualitative considerations based on Hofmeister-type action of these ions, as well as quantitative electrochemical models for the Gibbs free energy change for ionpair formation, are used to explain why (1) fluoride and water hardness due to magnesium ions (but not due to calcium ions) and similarly (2) cadmium ions in the presence of suitable pairing ions can be expected to be more nephrotoxic, while arsenite in the presence of fluoride and hardness may be expected to be less nephrotoxic. No synergy of arsenic with calcium hardness is found. The analysis is applied to a variety of ionic species that may be found in typical water sources to predict their likely combined electrochemical action. These results clarify the origins of chronic kidney disease that has reached epidemic proportions in the North Central Province of Sri Lanka as being most likely due to the joint presence of fluoride and magnesium ions in drinking water. The conclusion is further strengthened by a study of the dietary load of Cd and other toxins in the affected regions and in the healthy regions where the dietary toxin loads and lifestyles are similar, and found to be safe especially when the mitigating effects of micronutrient ionic forms of Zn, Se, as well as corrections for bioavailability are taken into account. The resulting etiological picture is consistent with the views of most workers in the field who have suspected that fluoride and other ions found in the hard water stagnant in shallow household wells were the major causative factors of the disease. Similar incidence of CKDu found in other hot tropical climates is likely to have similar origins.
Keywords: kidney disease; water quality; electrolytes; protein denaturing; fertilizers; soils; metal toxins; fluoride; sri lanka

Chemical mapping of the Milky Way with the Canada–France Imaging Survey: a non-parametric metallicity–distance decomposition of the Galaxy - Ibata, Rodrigo A.; McConnachie, Alan; Cuillandre, Jean-Charles; Fantin, Nicholas; Haywood, Misha; Martin, Nicolas F.; Bergeron, Pierre; Beckmann, Volker; Bernard, Edouard; Bonifacio, Piercarlo; Caffau, Elisabetta; Carlberg, Raymond; et al. (The Astrophysical Journal, 2017)
We present the chemical distribution of the Milky Way, based on 2900 deg2 of u-band photometry taken as part of the Canada–France Imaging Survey. When complete, this survey will cover 10,000 deg2 of the northern sky. By combing the CFHT u-band photometry together with Sloan Digital Sky Survey and Pan-STARRS g,r, and i, we demonstrate that we are able to reliably measure the metallicities of individual stars to ~0.2 dex, and hence additionally obtain good photometric distance estimates. This survey thus permits the measurement of metallicities and distances of the dominant main-sequence (MS) population out to approximately 30 kpc, and provides a much higher number of stars at large extraplanar distances than have been available from previous surveys. We develop a non-parametric distance–metallicity decomposition algorithm and apply it to the sky at 30o < | b| < 70o and to the North Galactic Cap. We find that the metallicity–distance distribution is well-represented by three populations whose metallicity distributions do not vary significantly with vertical height above the disk. As traced in MS stars, the stellar halo component shows a vertical density profile that is close to exponential, with a scale height of around 3 kpc. This may indicate that the inner halo was formed partly from disk stars ejected in an ancient minor merger.
Keywords: galaxies: formation; galaxy: halo; galaxy: stellar content; galaxy: structure; surveys

Charging of carbon thin films in scanning and phase-plate transmission electron microscopy - Hettler, Simon; Kano, Emi; Dries, Manuel; Gerthsen, Dagmar; Pfaffmann, Lukas; Bruns, Michael; Beleggia, Marco; Malac, Marek (Ultramicroscopy, 2017)
A systematic study on charging of carbon thin films under intense electron-beam irradiation was performed in a transmission electron microscope to identify the underlying physics for the functionality of hole-free phase plates. Thin amorphous carbon films fabricated by different deposition techniques and single-layer graphene were studied. Clean thin films at moderate temperatures show small negative charging while thin films kept at an elevated temperature are stable and not prone to beam-generated charging. The charging is attributed to electron-stimulated desorption (ESD) of chemisorbed water molecules from the thin-film surfaces and an accompanying change of work function. The ESD interpretation is supported by experimental results obtained by electron-energy loss spectroscopy, hole-free phase plate imaging, secondary electron detection and x-ray photoelectron spectroscopy as well as simulations of the electrostatic potential distribution. The described ESD-based model explains previous experimental findings and is of general interest to any phase-related technique in a transmission electron microscope.
Keywords: scanning transmission electron microscopy; transmission electron microscopy; electron-beam induced charging; thin film; phase plate; radiation damage; hole-free phase plate; volta phase plate

Characterizing 51 Eri b from 1 to 5 μm: a partly cloudy exoplanet - Rajan, Abhijith; Rameau, Julien; Rosa, Robert J. De; Marley, Mark S.; Graham, James R.; Macintosh, Bruce; Marois, Christian; Morley, Caroline; Patience, Jennifer; Pueyo, Laurent; Saumon, Didier; Ward-duong, Kimberly; et al. (The Astronomical Journal, 2017)

Characterization of wear-resistant materials for handling abrasive/erosive slurries - Xie, Y.; Jiang, J.; Aminul Islam, Md. (20th International Conference on Hydrotransport, 2017)
To characterize wear-resistant materials for handling abrasive/erosive slurries in various industrial operations, a suite of unique test rigs and test methods, including slurry jet erosion, Coriolis slurry scouring erosion, centrifugal slurry impact erosion, slurry sliding abrasion and slurry pot erosion-corrosion, have been developed. These test rigs and methods have been instrumental in facilitating the development of improved wear-resistant materials and optimizing materials selection for slurry transport in mining operations. In this paper, these wear test rigs and methods are introduced. The wear resistance of selected metallic, polymeric, ceramic and composite materials characterized by these methods is reported and discussed.

Characterization of two novel lipopolysaccharide phosphoethanolamine transferases in Pasteurella multocida and their role in resistance to cathelicidin-2 - Harper, Marina; Wright, Amy; St. Michael, Frank; Li, Jianjun; Deveson Lucas, Deanna; Ford, Mark; Adler, Ben; Cox, Andrew D.; Boyce, John D.; Palmer, Guy H. (Infection and Immunity, 2017)
The lipopolysaccharide (LPS) produced by the Gram-negative bacterial pathogen Pasteurella multocida has phosphoethanolamine (PEtn) residues attached to lipid A, 3-deoxy-d-manno-octulosonic acid (Kdo), heptose, and galactose. In this report, we show that PEtn is transferred to lipid A by the P. multocida EptA homologue, PetL, and is transferred to galactose by a novel PEtn transferase that is unique to P. multocida called PetG. Transcriptomic analyses indicated that petL expression was positively regulated by the global regulator Fis and negatively regulated by an Hfq-dependent small RNA. Importantly, we have identified a novel PEtn transferase called PetK that is responsible for PEtn addition to the single Kdo molecule (Kdo1), directly linked to lipid A in the P. multocida glycoform A LPS. In vitro assays showed that the presence of a functional petL and petK, and therefore the presence of PEtn on lipid A and Kdo1, was essential for resistance to the cationic, antimicrobial peptide cathelicidin-2. The importance of PEtn on Kdo1 and the identification of the transferase responsible for this addition have not previously been shown. Phylogenetic analysis revealed that PetK is the first representative of a new family of predicted PEtn transferases. The PetK family consists of uncharacterized proteins from a range of Gram-negative bacteria that produce LPS glycoforms with only one Kdo molecule, including pathogenic species within the genera Vibrio, Bordetella, and Haemophilus. We predict that many of these bacteria will require the addition of PEtn to Kdo for maximum protection against host antimicrobial peptides.
Keywords: lipopolysaccharide; phosphoethanolamine transferase; Pasteurella multocida; 3-deoxy-d-manno-octulosonic acid; cathelicidin; cationic antimicrobial

Characterization of the macrocyclase involved in the biosynthesis of RiPP cyclic peptides in plants - Chekan, Jonathan R.; Estrada, Paola; Covello, Patrick S.; Nair, Satish K. (Proceedings of the National Academy of Sciences, 2017)
Enzymes that can catalyze the macrocyclization of linear peptide substrates have long been sought for the production of libraries of structurally diverse scaffolds via combinatorial gene assembly as well as to afford rapid in vivo screening methods. Orbitides are plant ribosomally synthesized and posttranslationally modified peptides (RiPPs) of various sizes and topologies, several of which are shown to be biologically active. The diversity in size and sequence of orbitides suggests that the corresponding macrocyclases may be ideal catalysts for production of cyclic peptides. Here we present the biochemical characterization and crystal structures of the plant enzyme PCY1 involved in orbitide macrocyclization. These studies demonstrate how the PCY1 S9A protease fold has been adapted for transamidation, rather than hydrolysis, of acyl-enzyme intermediates to yield cyclic products. Notably, PCY1 uses an unusual strategy in which the cleaved C-terminal follower peptide from the substrate stabilizes the enzyme in a productive conformation to facilitate macrocyclization of the N-terminal fragment. The broad substrate tolerance of PCY1 can be exploited as a biotechnological tool to generate structurally diverse arrays of macrocycles, including those with nonproteinogenic elements.

Characterization of surface radar cross sections at W-band at moderate incidence angles - Battaglia, Alessandro; Wolde, Mengistu; D'Adderio, Leo Pio; Nguyen, Cuong; Fois, Franco; Illingworth, Anthony; Midthassel, Rolv (IEEE Transactions on Geoscience and Remote Sensing, 2017)
This paper presents the results of a recent flight campaign conducted over the Great Lakes region and reports the first observations of the W-band normalized backscattered cross section (σ0) for V and H polarization and the linear depolarization ratios (LDRs) from different types of surfaces at moderate incidence angles (<;70°). For sea surfaces, while the observed σ0 behaves as previously reported at small incidence angles, it features a marked decrease with increasing incidence angles between 20° and 50°. There is a strong dependence of normalized backscattered cross sections both on the wind speed and on the wind direction, with larger values found in the presence of higher wind speeds and when the radar antenna is looking upwind. This is in line with theoretical models (though models tend to overpredict the range of variability at a given incidence angle) and with observations at lower frequencies. The LDRs are steadily increasing from values certainly lower than -30 dB, at vertical incidence, to the values of about -10 dB, at the incidence angles of about 60°-70°, with a good matching between observations and theoretical predictions. On the other hand, land surface backscattering properties are not characterized by a strong angular dependence: σ0 and LDR values typically range between -20 and 0 dB and between -15 and -5 dB, respectively. This paper is relevant for spaceborne concepts of W-band radars, which envisage moderate incidence angles to achieve a broad swath needed for global coverage.
Keywords: depolarization ratios; radar surface cross sections; radar theory; W-band

Characterization of O-acetylation in sialoglycans by MALDI-MS using a combination of methylamidation and permethylation - Wu, Zhaoguan; Li, Henghui; Zhang, Qiwei; Liu, Xin; Zheng, Qi; Li, Jianjun (Scientific Reports, 2017)
O-Acetylation of sialic acid in protein N-glycans is an important modification and can occur at either 4-, 7-, 8- or 9-position in various combinations. This modification is usually labile under alkaline reaction conditions. Consequently, a permethylation-based analytical method, which has been widely used in glycomics studies, is not suitable for profiling O-acetylation of sialic acids due to the harsh reaction conditions. Alternatively, methylamidation can be used for N-glycan analysis without affecting the base-labile modification of sialic acid. In this report, we applied both permethylation and methylamidation approaches to the analysis of O-acetylation in sialic acids. It has been demonstrated that methylamidation not only stabilizes sialic acids during MALDI processing but also allow for characterization of their O-acetylation pattern. In addition, LC-MS/MS experiments were carried out to distinguish between the O-acetylated glycans with potential isomeric structures. The repeatability of methylamidation was examined to evaluate the applicability of the approach to profiling of O-acetylation in sialic acids. In conclusion, the combination of methylamidation and permethylation methodology is a powerful MALDI-TOF MS-based tool for profiling O-acetylation in sialic acids applicable to screening of N-glycans.

Characterization of growth patterns of nanoscale organic films on carbon electrodes by surface enhanced Raman spectroscopy - Supur, Mustafa; Smith, Scott R.; Mccreery, Richard L. (Analytical Chemistry, 2017)
Electrochemical deposition of aromatic organic molecules by reduction of diazonium reagents enables formation of molecular layers with sufficient integrity for use in molecular electronic junctions of interest to microelectronics. Characterization of organic films with thicknesses in the 1–10 nm range is difficult with Raman spectroscopy, since most molecular structures of electronic interest have Raman cross sections which are too small to observe as either thin films on solid electrodes or within intact molecular junctions. Layer formation on a 10 nm thick Ag island film on a flat carbon surface (eC/Ag) permitted acquisition of structural information using surface enhanced Raman spectroscopy (SERS), in many cases for molecules with weak Raman scattering. Raman spectra obtained on eC/Ag surfaces were indistinguishable from those on carbon without Ag present, and the spectra of oligomeric molecular layers were completely consistent with those of the monomers. Layer growth was predominantly linear for cases where such growth was sterically allowed, and linear growth correlated strongly with the line width and splitting of the C═C phenyl ring stretches. Molecular bilayers made by successive reduction of different diazonium reagents were also observable and will be valuable for applications of 1–20 nm organic films in molecular electronics.

Characterization of fuel composition and altitude impact on gaseous and particle emissions from a turbojet engine - Chan, Tak W.; Canteenwalla, Pervez; Chishty, Wajid A. (ASME Turbo Expo 2017: Turbomachinery Technical Conference and Exposition. Volume 4A: Combustion, Fuels and Emissions, 2017)
The effects of altitude and fuel composition on gaseous and particle emissions from a turbojet engine were investigated as part of the National Jet Fuels Combustion Program (NJFCP) effort. Two conventional petroleum based jet fuels (a “nominal” and a “worst-case” jet fuel) and two test fuels with unique characteristics were selected for this study. The “worst-case” conventional jet fuel with high flash point and viscosity resulted in reduced combustion efficiency supported by the reduced CO2 emissions and corresponding increased CO and THC emissions. In addition, increased particle number (PN), particle mass (PM), and black carbon (BC) emissions were observed. Operating the engine on a bimodal fuel, composed of heavily branched C12 and C16 iso-paraffinic hydrocarbons with an extremely low cetane number did not significantly impact the engine performance or gaseous emissions but significantly reduced PN, PM, and BC emissions when compared to other fuels. The higher aromatic content and lower hydrogen content in the C-5 fuel were observed to increase PN, PM, and BC emissions. It is also evident that the type of aromatic hydrocarbons has a large impact on BC emissions. Reduction in combustion efficiency resulted in reduced CO2 emissions and increased CO and THC emissions from this engine with increasing altitudes. PN emissions were moderately influenced by altitude but PM and BC emissions were significantly reduced with increasing altitude. The reduced BC emissions with increasing altitude could be a result of reduced combustion temperature which lowered the rate of pyrolysis for BC formation, which is supported by the NOx reduction trend.

Characterization of a versatile reference instrument for traceable fluorescence measurements using different illumination and viewing geometries specified in practical colorimetry. Part 2: sphere geometry (8:d) - Zwinkels, Joanne; Neil, William; Noël, Mario; Côté, Eric (Metrologia, 2017)
In the second part of this two-part series on the development of a versatile reference instrument at the National Research Council of Canada (NRC), we have extended the characterization of the NRC Reference Goniospectrofluorimeter to high-accuracy fluorescence measurements in a sphere geometry (8:d) that is specified in standard test methods for many practical applications in colorimetry. This builds upon the work reported in part-one of this series which described in detail the design, characterization and validation of this new instrument for realizing a total spectral radiance factor scale in a bidirectional (45a:0) geometry. To extend the measurement capabilities to a sphere geometry, it was configured with a large diameter integrating sphere accessory. Preliminary results using a substitution-mode operating procedure showed large sphere errors that were characterized and corrected for. To improve this traceability, the sphere was modified to operate in comparison-mode and this effectively eliminated many of the sphere-related errors that typically limit the accuracy of sphere-based fluorescence measurements. The performance of the instrument configured for a sphere geometry (8:d) with this modified sphere design has been validated by means of comparison measurements of both non-fluorescent and fluorescent artifacts. The reflectance component has been validated using non-fluorescent comparison samples that have been calibrated under the same geometric conditions with traceability to the NRC Absolute Reflectometer (d:0 geometry). The fluorescent-only component has been validated using near-Lambertian fluorescent reflecting materials with traceability to the NRC Reference Spectrofluorimeter (45:0 geometry), under the assumption that this component is nearly the same for these two geometries. This work has enabled NRC to provide an uninterrupted link for improved traceability of fluorescence calibrations that specify a sphere geometry. These calibration requests include many important commercial applications, such as whiteness specification of fluorescently whitened paper and textile samples and color specification of fluorescent safety goods.

Characterising and predicting cyanobacterial blooms in an 8-year amplicon sequencing time course - Tromas, Nicolas; Fortin, Nathalie; Bedrani, Larbi; Terrat, Yves; Cardoso, Pedro; Bird, David; Greer, Charles W.; Shapiro, B Jesse (The ISME Journal, 2017)
Cyanobacterial blooms occur in lakes worldwide, producing toxins that pose a serious public health threat. Eutrophication caused by human activities and warmer temperatures both contribute to blooms, but it is still difficult to predict precisely when and where blooms will occur. One reason that prediction is so difficult is that blooms can be caused by different species or genera of cyanobacteria, which may interact with other bacteria and respond to a variety of environmental cues. Here we used a deep 16S amplicon sequencing approach to profile the bacterial community in eutrophic Lake Champlain over time, to characterise the composition and repeatability of cyanobacterial blooms, and to determine the potential for blooms to be predicted based on time course sequence data. Our analysis, based on 135 samples between 2006 and 2013, spans multiple bloom events. We found that bloom events significantly alter the bacterial community without reducing overall diversity, suggesting that a distinct microbial community—including non-cyanobacteria—prospers during the bloom. We also observed that the community changes cyclically over the course of a year, with a repeatable pattern from year to year. This suggests that, in principle, bloom events are predictable. We used probabilistic assemblages of OTUs to characterise the bloom-associated community, and to classify samples into bloom or non-bloom categories, achieving up to 92% classification accuracy (86% after excluding cyanobacterial sequences). Finally, using symbolic regression, we were able to predict the start date of a bloom with 78–92% accuracy (depending on the data used for model training), and found that sequence data was a better predictor than environmental variables.

Changing relationships between sunspot number, total sunspot area and F 10.7 in cycles 23 and 24 - Tapping, Ken; Morgan, Carly (Solar Physics, 2017)
This article is an update of a study (Tapping and Valdès in Solar Phys.272, 337, 2011) made in the early part of Cycle 24 using an intercomparison of various solar activity indices (including sunspot number and the 10.7 cm solar radio flux), in which it was concluded that a change in the relationship between photospheric and chromospheric/coronal activity took place just after the maximum of Cycle 23 and continued into Cycle 24. Precursors (short-term variations) were detected in Cycles 21 and 22. Since then the sunspot number index data have been substantially revised. This study is intended to be an update of the earlier study and to assess the impact of the revision of the sunspot number data upon those conclusions. This study compares original and revised sunspot number, total sunspot area, and 10.7 cm solar radio flux. The conclusion is that the transient changes in Cycles 21 and 22, and the more substantial change in Cycle 23, remain evident. Cycle 24 shows indications that the deviation was probably another short-term one.
Keywords: Solar Activity Cycle; sunspot number; total sunspot area; 10.7 cm solar radio flux

Cellular uptake and intracellular localization of poly (acrylic acid) nanoparticles in a rainbow trout ( Oncorhynchus mykiss ) gill epithelial cell line, RTgill-W1 - Felix, Lindsey C.; Ortega, Van A.; Goss, Greg G. (Aquatic Toxicology, 2017)
The ever-growing production of engineered nanoparticles (NPs) for use in many agricultural, commercial, consumer, and industrial applications will lead to their accidental or intentional release into the environment. Potential routes of environmental exposure include manufacturing or transport spills, disposal of NP‐containing products down the drain and/or in landfills, as well as direct usage on agricultural land. Therefore, NPs will inevitably contaminate aquatic environments and interact with resident organisms. However, there is limited information regarding the mechanisms that regulate NP transport into fish from the environment. Thus, our primary objective was to elucidate the mechanism(s) underlying cellular uptake and intracellular fate of 3–9 nm poly (acrylic acid) NPs loaded with the fluorescent dye Nile red using a rainbow trout (Oncorhynchus mykiss) gill epithelial cell line (RTgill‐W1). In vitro measurements with NP‐treated RTgill-W1 cells were carried out using a combination of laser scanning confocal microscopy, flow cytometry, fluorescent biomarkers (transferrin, cholera toxin B subunit, and dextran), endocytosis inhibitors (chlorpromazine, genistein, and wortmannin), and stains (4′, 6‐diamidino-2-phenylindole, Hoechst 33342, CellMask Deep Red, and LysoTracker Yellow). Clathrin-mediated endocytosis (CME), caveolae‐mediated endocytosis and macropinocytosis pathways were active in RTgill‐W1 cells, and these pathways were exploited by the non-cytotoxic NPs to enter these cells. We have demonstrated that NP uptake by RTgill‐W1 cells was impeded when clathrin-coated pit formation was blocked by chlorpromazine. Furthermore, colocalization analysis revealed a moderate positive relationship between NPs and LysoTracker Yellow-positive lysosomal compartments indicating that CME was the dominant operative mechanism involved in NP internalization by RTgill-W1 cells. Overall, our results clearly show that fish gill epithelial cells internalized NPs via energy‐dependent endocytotic processes. This study enhances our understanding of complex NP‐cell interactions and the results obtained in vitro imply a potential risk to aquatic organisms.
Keywords: colocalization; endocytosis; fish; internalization; lysosome; nanotoxicology

Cavity designs for GHz frequency combs - Arissian, Ladan; Diels, Jean-Claude (Laser Resonators, Microresonators, and Beam Control XIX, 2017)
A comprehensive modeling of the mode-locked laser is presented. The methodology, based for a large part on space-time analogy, applies to any cavity, but may be particularly important for short cavities with particular emphasis where very tight parameter control is essential. Unlike earlier models the beam deformation by nonlinear index in time and space is completely accounted for. It is shown that the mechanism responsible for starting mode-locking is not only Kerr lensing but also Kerr deflection. The problem of directionality in a ring laser is addressed. Will the operation be bidirectional, or unidirectional, and in the later case in which direction? It is suggested that this question can be addressed by considering the analogy between a ring laser and a quantum mechanical two level system. While it is generally taken for granted that multi-GHz combs can only be obtained by miniaturization of the laser, it is shown that a high frequency comb can be generated in a mode-locked laser by inserting a glass etalon.

Cardio-respirometry disruption in zebrafish (Danio rerio) embryos exposed to hydraulic fracturing flowback and produced water - Folkerts, Erik J.; Blewett, Tamzin A.; He, Yuhe; Goss, Greg G. (Environmental Pollution, 2017)
Hydraulic fracturing to extract oil and natural gas reserves is an increasing practice in many international energy sectors. Hydraulic fracturing flowback and produced water (FPW) is a hyper saline wastewater returned to the surface from a fractured well containing chemical species present in the initial fracturing fluid, geogenic contaminants, and potentially newly synthesized chemicals formed in the fracturing well environment. However, information on FPW toxicological mechanisms of action remain largely unknown. Both cardiotoxic and respirometric responses were explored in zebrafish (Danio rerio) embryos after either an acute sediment-free (FPW-SF) or raw/sediment containing (FPW-S) fraction exposure of 24 and 48 h at 2.5% and 5% dilutions. A 48 h exposure to either FPW fraction in 24–72 h post fertilization zebrafish embryos significantly increased occurrences of pericardial edema, yolk-sac edema, and tail/spine curvature. In contrast, larval heart rates significantly decreased after FPW fraction exposures. FPW-S, but not FPW-SF, at 2.5% doses significantly reduced embryonic respiration/metabolic rates (MO2), while for 5% FPW, both fractions reduced MO2. Expression of select cardiac genes were also significantly altered in each FPW exposure group, implicating a cardiovascular system compromise as the potential cause for reduced embryonic MO2. Collectively, these results support our hypothesis that organics are major contributors to cardiac and respiratory responses to FPW exposure in zebrafish embryos. Our study is the first to investigate cardiac and respiratory sub-lethal effects of FPW exposure, demonstrating that FPW effects extend beyond initial osmotic stressors and verifies the use of respirometry as a potential marker for FPW exposure.
Keywords: hydraulic fracturing; toxicity; respiration; cardiac; zebrafish; embryo

Carbon nanotubes diminish IgE-mediated degranulation in the rat basophilic leukemia (RBL)-2H3 cell line - Ede, James D.; Ortega, Van A.; Boyle, David; Felix, Lindsey; Stafford, James L.; Martinez-Rubi, Yadienka; Simard, Benoit; Goss, Greg G. (NanoImpact, 2017)
The impact of several differentially functionalized SWCNTs, including pristine, unfunctionalized CNTs (U-CNTs) and differentially carboxy-functionalized CNTs (CNT-30, CNT-40 and CNT-50) on degranulation and histamine release of a model mast cell line (RBL-2H3 cells) was investigated. Greater declines in cell viability at 24h were noted when cells were exposed to U-CNTs (78.5 ± 3%) compared to CNT-30 (55.4 ± 4%), CNT-40 (58.4 ± 3%) and CNT-50 (55.8 ± 4%). U-CNT exposure caused a significantly greater decline in IgE-FcεRI-mediated degranulation compared to acid functionalized CNT-30 at all concentrations tested. Importantly, removal of U-CNTs resulted in recovery degranulatory function while no recovery was found in cells exposed to CNT-30. U-CNT exposure resulted in a concomitant reduction in MAPK/ERK activation at 2 h declining to 53.0 ± 11% of control in the 250 mg L− 1 exposure group. However, similar to the degranulatory responses, MAPK/ERK activity could be rescued in RBL-2H3 cells exposed to U-CNTs but not in the AF-CNT exposures. Our results suggest that U-CNT result in reduced downstream activation of signaling kinases and suggests that the diminished degranulatory response observed after U-CNT exposure may result from a reduction in IgE-FcεRI aggregation.
Keywords: degranulation; nanotoxicology; inflammation; carbon nanotubes

Can extensional flow Rupture macromolecules in an electrospinning process? - Sun, Chenggui; Ayranci, Cagri; Chen, Yu; Boluk, Yaman (Journal of Polymer Science Part B: Polymer Physics, 2017)
The fracture of high molecular weight poly(ethylene oxide) (PEO) chains under extensional stretching during the electrospinning of aqueous solutions was investigated by measuring solution viscosities and monitoring the change of molecular weight. The degree of macromolecular chain fractures in 1.0% polymer solutions increased with the increase in molecular weight. The strain rates for stretching and fracturing of macromolecules are critical for the degradation of polymers along with experimental elongational strain rates.
Keywords: chain fracture; electrospun fibers; molecular weight distribution

C-17 Globemaster III Vortex Control Finlets simulation and wind tunnel testing - Mcilwain, Stuart; Carter, Dennis L.; Givogue, Greg; Lorang, Tony; Polito, Ryan; Pereira, Jennifer; Clark, Catherine (35th AIAA Applied Aerodynamics Conference, 2017)
In 2013, Defence Research and Development Canada, in collaboration with the United States Air Force Research Laboratory and the Australian Defence Science Technical Group, embarked on an ambitious development and evaluation program to assess the performance benefits of Vortex Contol (VC) FinletsTM installed on the C-17 Globemaster III aircraft. This paper will discuss three wind tunnel tests and significant complementary computational fluid dynamics analyses that occurred over the course of a year and across international borders. Since the primary role of the Finlets is to reduce drag and hence reduce fuel consumption, or increase range and endurance, the primary objective of this work was to achieve the greatest drag decrement by understanding the flow around the C-17’s tail and the mechanism(s) by which the devices control that flow. The secondary objectives were to determine the effect of the devices on air-drop and stability and control, albeit the latter assessment was limited. The wind tunnel tests demonstrated a maximum reduction in drag of 1.8% with no significant side-effects. Since the devices provide small decrements in drag by changing the complex flow around the empennage, several challenges in testing and simulation were encountered and were generally addressed with inexpensive solutions. To that end, classic and advanced techniques were used during testing with positive success.

BVRI Photometric analysis and spectra of the dwarf solar type Algol binary, V500 Pegasi - Caton, Daniel B.; Samec, Ronald G.; Robb, Russell; Faulkner, Danny R.; Hamme, Walter Van; Clark, Jimmy D.; Shebs, Travis (Publications of the Astronomical Society of the Pacific, 2017)
Observations and analyses of V500 Pegasi taken at the Dark Sky Observatory (DSO), the SARA North Observatory and the Dominion Astrophysical Observatory are presented. V500 Peg is an eclipsing binary with a period of 0.57983 d. The light curves have the appearance of a detached or semi-detached binary. Spectroscopy reveals that it is of F5V-type. A continuous 14-year period study may show an orbital period increase is occurring. This may be due to weak matter transfer with the primary component as the gainer. The light curve has a large difference in primary and secondary amplitudes that is typical of this class of binary. The final solution shows a total secondary eclipse. The solution is that of a classical Algol system (semi-detached with the secondary component filling its Roche lobe), but it is of solar type, with a magnetic spot. This may mean that magnetic braking is interfering in the nuclear evolution. The secondary component has a temperature of ~4700 K (K3), which means it is somewhat overluminous for its mass.

Bulk heterojunction solar cells based on blends of conjugated polymers with ii–vi and iv–vi inorganic semiconductor quantum dots - Kisslinger, Ryan; Hua, Weidi; Shankar, Karthik (Polymers, 2017)
Bulk heterojunction solar cells based on blends of quantum dots and conjugated polymers are a promising configuration for obtaining high-efficiency, cheaply fabricated solution-processed photovoltaic devices. Such devices are of significant interest as they have the potential to leverage the advantages of both types of materials, such as the high mobility, band gap tunability and possibility of multiple exciton generation in quantum dots together with the high mechanical flexibility and large molar extinction coefficient of conjugated polymers. Despite these advantages, the power conversion efficiency (PCE) of these hybrid devices has remained relatively low at around 6%, well behind that of all-organic or all-inorganic solar cells. This is attributed to major challenges that still need to be overcome before conjugated polymer–quantum dot blends can be considered viable for commercial application, such as controlling the film morphology and interfacial structure to ensure efficient charge transfer and charge transport. In this work, we present our findings with respect to the recent development of bulk heterojunctions made from conjugated polymer–quantum dot blends, list the ongoing strategies being attempted to improve performance, and highlight the key areas of research that need to be pursued to further develop this technology.
Keywords: anisotropic nanocrystals; hybrid photovoltaics; interface engineering; nanotechnology; materials processing; tailored nanocomposites; bicontinuous percolation networks; blend characterization

Broth versus surface-grown cells: differential regulation of RsmY/Z small RNAs in Pseudomonas aeruginosa by the Gac/HptB system - Jean-Pierre, Fabrice; Tremblay, Julien; Déziel, Eric (Frontiers in Microbiology, 2017)
Two-component systems are capable of profoundly affecting genetic regulation in bacteria by detecting environmental stimuli, allowing them to quickly adapt. In Pseudomonas aeruginosa, the small RNAs (sRNAs) RsmY and RsmZ are under the control of the GacS/A system. They have been described as ones of the major key players in the control of planktonic and surface-associated behaviors. Genetic regulation by these sRNAs is achieved by the titration of the negative post-transcriptional regulator RsmA which affects the expression of over 500 genes. There is increasing evidence pinpointing the importance of RsmY and RsmZ in the planktonic-sessile P. aeruginosa lifestyles switch control. Using swarming motility as a model, we show here that these sRNA are differentially regulated depending on the selected growth conditions (i.e., planktonic versus surface grown-cells). Also, we report that opposite to planktonically grown cells, rsmZ regulation does not implicate the response regulator GacA in swarming cells. Furthermore, we present data indicating that RsmY/Z expression influence swarming motility via the protein HptB which acts as a negative regulator of these sRNAs and that they do not strictly converge to RsmA as previously reported.

Bright nanoscale source of deterministic entangled photon pairs violating Bell’s inequality - Jöns, Klaus D.; Schweickert, Lucas; Versteegh, Marijn A. M.; Dalacu, Dan; Poole, Philip J.; Gulinatti, Angelo; Giudice, Andrea; Zwiller, Val; Reimer, Michael E. (Scientific Reports, 2017)
Global, secure quantum channels will require efficient distribution of entangled photons. Long distance, low-loss interconnects can only be realized using photons as quantum information carriers. However, a quantum light source combining both high qubit fidelity and on-demand bright emission has proven elusive. Here, we show a bright photonic nanostructure generating polarization-entangled photon pairs that strongly violates Bell’s inequality. A highly symmetric InAsP quantum dot generating entangled photons is encapsulated in a tapered nanowire waveguide to ensure directional emission and efficient light extraction. We collect ~200 kHz entangled photon pairs at the first lens under 80 MHz pulsed excitation, which is a 20 times enhancement as compared to a bare quantum dot without a photonic nanostructure. The performed Bell test using the Clauser-Horne-Shimony-Holt inequality reveals a clear violation (SCHSH > 2) by up to 9.3 standard deviations. By using a novel quasi-resonant excitation scheme at the wurtzite InP nanowire resonance to reduce multi-photon emission, the entanglement fidelity (F = 0.817 ± 0.002) is further enhanced without temporal post-selection, allowing for the violation of Bell’s inequality in the rectilinear-circular basis by 25 standard deviations. Our results on nanowire-based quantum light sources highlight their potential application in secure data communication utilizing measurement-device-independent quantum key distribution and quantum repeater protocols.

BN pegasi: a semidetached eclipsing binary - Nelson, Robert H. (Information Bulletin on Variable Stars, 2017)

Biosynthesis of legionaminic acid and its incorporation into glycoconjugates - Schoenhofen, Ian C.; Young, N. Martin; Gilbert, Michel (Chemical Glycobiology Part A. Synthesis, Manipulation and Applications of Glycans, 2017)
Legionaminic acids are analogs of sialic acid that occur in cell surface glycoconjugates of several bacteria. Because legionaminic acids share the same stereochemistry as sialic acid but differ at C7 and C9, they are interesting analogs to probe the impact of varying exocyclic moieties (C7–C9) on biological activities such as susceptibilities to sialidases, interactions with Siglecs and immunogenicity. There are currently no reports on the bacterial enzymes that transfer legionaminic acids to these cell surface glycoconjugates, but some mammalian and bacterial sialyltransferases display donor promiscuity and can use CMP-Leg5,7Ac2 efficiently enough to transfer Leg5,7Ac2 to their natural acceptor glycans. When the natural activity with CMP-Leg5,7Ac2 is significant but relatively low, an alternate strategy has been to engineer versions with improved activity to transfer Leg5,7Ac2. Importantly, we have found that some bacterial sialyltransferases are very efficient for transferring Leg5,7Ac2 to small synthetic glycans with various aglycones. The two mammalian sialyltransferases that have been tested so far (porcine ST3Gal1 and human ST6Gal1) were found to be more efficient than the bacterial sialyltransferases for the modification of glycoproteins. We provide a review of the sialyltransferases selected to modify different types of glycoconjugates with Leg5,7Ac2, including small synthetic acceptors, glycolipids, and glycoproteins. In the first part, we also propose an optimized biosynthetic pathway for in vitro preparation of the donor CMP-Leg5,7Ac2, based on enzymes selected from two bacteria that naturally produce legionaminic acid.
Keywords: legionaminic; sialyltransferase; glycoconjugate; campylobacter; legionella

Biofuel blending reduces particle emissions from aircraft engines at cruise conditions - Moore, Richard H.; Thornhill, Kenneth L.; Weinzierl, Bernadett; Sauer, Daniel; D’ascoli, Eugenio; Kim, Jin; Lichtenstern, Michael; Scheibe, Monika; Beaton, Brian; Beyersdorf, Andreas J.; Barrick, John; Bulzan, Dan; et al. (Nature, 2017)
Aviation-related aerosol emissions contribute to the formation of contrail cirrus clouds that can alter upper tropospheric radiation and water budgets, and therefore climate1. The magnitude of air-traffic-related aerosol–cloud interactions and the ways in which these interactions might change in the future remain uncertain. Modelling studies of the present and future effects of aviation on climate require detailed information about the number of aerosol particles emitted per kilogram of fuel burned and the microphysical properties of those aerosols that are relevant for cloud formation. However, previous observational data at cruise altitudes are sparse for engines burning conventional fuels, and no data have previously been reported for biofuel use in-flight. Here we report observations from research aircraft that sampled the exhaust of engines onboard a NASA DC‐8 aircraft as they burned conventional Jet A fuel and a 50:50 (by volume) blend of Jet A fuel and a biofuel derived from Camelina oil. We show that, compared to using conventional fuels, biofuel blending reduces particle number and mass emissions immediately behind the aircraft by 50 to 70 per cent. Our observations quantify the impact of biofuel blending on aerosol emissions at cruise conditions and provide key microphysical parameters, which will be useful to assess the potential of biofuel use in aviation as a viable strategy to mitigate climate change.

Biochemical investigation of Rv3404c from Mycobacterium tuberculosis - Dunsirn, Murray M.; Thoden, James B.; Gilbert, Michel; Holden, Hazel M. (Biochemistry, 2017)
The causative agent of tuberculosis, Mycobacterium tuberculosis, is a bacterium with a complex cell wall and a complicated life cycle. The genome of M. tuberculosis contains well over 4000 genes thought to encode proteins. One of these codes for a putative enzyme referred to as Rv3404c, which has attracted research attention as a potential virulence factor for over 12 years. Here we demonstrate that Rv3404c functions as a sugar N-formyltransferase that converts dTDP-4-amino-4,6-dideoxyglucose into dTDP-4-formamido-4,6-dideoxyglucose using N10-formyltetrahydrofolate as the carbon source. Kinetic analyses demonstrate that Rv3404c displays a significant catalytic efficiency of 1.1 × 104 M–1 s–1. In addition, we report the X-ray structure of a ternary complex of Rv3404c solved in the presence of N5-formyltetrahydrofolate and dTDP-4-amino-4,6-dideoxyglucose. The final model of Rv3404c was refined to an overall R-factor of 16.8% at 1.6 Å resolution. The results described herein are especially intriguing given that there have been no published reports of N-formylated sugars associated with M. tuberculosis. The data thus provide a new avenue of research into this fascinating, yet deadly, organism that apparently has been associated with human infection since ancient times.

Bioavailability and chronic toxicity of bismuth citrate to earthworm Eisenia andrei exposed to natural sandy soil - Omouri, Zohra; Hawari, Jalal; Fournier, Michel; Robidoux, Pierre Yves (Ecotoxicology and Environmental Safety, 2017)
The present study describes bioavailability and chronic effects of bismuth to earthworms Eisenia andrei using OECD reproduction test. Adult earthworms were exposed to natural sandy soil contaminated artificially by bismuth citrate. Average total concentrations of bismuth in soil recovered by HNO3 digestion ranged from 75 to 289 mg/kg. Results indicate that bismuth decreased significantly all reproduction parameters of Eisenia andrei at concentrations ≥ 116 mg/kg. However, number of hatched cocoons and number of juveniles seem to be more sensitive than total number of cocoons, as determined by IC50; i.e., 182, 123 and > 289 mg/kg, respectively. Bismuth did not affect Eisenia andrei growth and survival, and had little effect on phagocytic efficiency of coelomocytes. The low immunotoxicity effect might be explained by the involvement of other mechanisms i.e. bismuth sequestered by metal-binding compounds. After 28 days of exposure bismuth concentrations in earthworms tissue increased with increasing bismuth concentrations in soil reaching a stationary state of 21.37 mg/kg dry tissue for 243 mg Bi/kg dry soil total content. Data indicate also that after 56 days of incubation the average fractions of bismuth available extracted by KNO3 aqueous solution in soil without earthworms varied from 0.0051 to 0.0229 mg/kg, while in soil with earthworms bismuth concentration ranged between 0.310–1.347 mg/kg dry soil. We presume that mucus and chelating agents produced by earthworms and by soil or/and earthworm gut microorganisms could explain this enhancement, as well as the role of dermal and ingestion routes of earthworms uptake to soil contaminant.
Keywords: trace metals; soil assessment; bioaccessibility; earthworms; reproduction; phagocytosis

Bioassay-guided isolation of bisepoxylignans from the flower buds of Magnolia biondii Pamp and their antiallergic effects - Zhang, Xing; Qian, Fei; Tan, Jun-Jie; Guo, Fu-Jiang; Kulka, Marianna; Xu, Jin-Wen; Li, Yi-Ming (RSC Advances, 2017)
The dried flower buds of Magnolia biondii Pamp (herbal name, Xin-Yi) are a traditional Chinese medicine with a long history of clinical use in the treatment of allergic rhinitis and sinusitis. However, the constituents responsible for its antiallergic effects remain unidentified. In the present study, a novel bisepoxylignan, isoeudesmin (1), and eight known bisepoxylignans, pluviatilol (2), eudesmin (3), magnolin (4), lirioresinol-B dimethyl ether (5), epimagnolin B (6), kobusin (7), aschantin (8), fargesin (9), were isolated from effective fractions through antiallergic bioassay-guided procedures using mouse bone marrow-derived mast cells (BMMCs) and IgE-induced passive cutaneous anaphylaxis mice. The compound structures were elucidated through nuclear magnetic resonance and mass spectrometry analyses. Compound 1 and compounds 2–6 and 9 exhibited antiallergic effects without affecting the viability of BMMCs. Compounds 2 and 9 showed the strongest effects with IC50 values of 52.18 and 93.03 μM, respectively. In this paper, the structure–activity relationship between these bisepoxylignans and their antiallergic effects is discussed. After evaluating the intensity of the antiallergic effects of the extracts, further separating the fractions, and isolating the purified compounds, we concluded that biosepoxylignans are the main constituents in Xin-Yi contributing to its anti-allergic efficacy.

Au fixed point development at NRC - Dedyulin, S. N.; Gotoh, M.; Todd, A. D. W. (International Journal of Thermophysics, 2017)
Two Au fixed points filled using metal of different nominal purities in carbon crucibles have been developed at the National Research Council Canada (NRC). The primary motivation behind this project was to provide the means for direct thermocouple calibrations at the Au freezing point (1064.18∘C). Using a Au fixed point filled with the metal of maximum available purity [99.9997 % pure according to glow discharge mass spectroscopy (GDMS)], multiple freezing plateaus were measured in a commercial high-temperature furnace. Four Pt/Pd thermocouples constructed and calibrated in-house were used to measure the freezing plateaus. From the calibration at Sn, Zn, Al and Ag fixed points, the linear deviation function from the NIST-IMGC reference function (IEC 62460:2008 Standard) was determined and extrapolated to the freezing temperature of Au. For all the Pt/Pd thermocouples used in this study, the measured EMF values agree with the extrapolated values within expanded uncertainty, thus substantiating the use of 99.9997 % pure Au fixed point cell for thermocouple calibrations at NRC. Using the Au fixed point filled with metal of lower purity (99.99 % pure according to GDMS), the effect of impurities on the Au freezing temperature measured with Pt/Pd thermocouple was further investigated.
Keywords: Gold; Metal fixed point; Pt/Pd thermocouple

Attribution of spring snow water equivalent (SWE) changes over the northern hemisphere to anthropogenic effects - Jeong, Dae Il; Sushama, Laxmi; Naveed Khaliq, M. (Climate Dynamics, 2017)
Snow is an important component of the cryosphere and it has a direct and important influence on water storage and supply in snowmelt-dominated regions. This study evaluates the temporal evolution of snow water equivalent (SWE) for the February–April spring period using the GlobSnow observation dataset for the 1980–2012 period. The analysis is performed for different regions of hemispherical to sub-continental scales for the Northern Hemisphere. The detection–attribution analysis is then performed to demonstrate anthropogenic and natural effects on spring SWE changes for different regions, by comparing observations with six CMIP5 model simulations for three different external forcings: all major anthropogenic and natural (ALL) forcings, greenhouse gas (GHG) forcing only, and natural forcing only. The observed spring SWE generally displays a decreasing trend, due to increasing spring temperatures. However, it exhibits a remarkable increasing trend for the southern parts of East Eurasia. The six CMIP5 models with ALL forcings reproduce well the observed spring SWE decreases at the hemispherical scale and continental scales, whereas important differences are noted for smaller regions such as southern and northern parts of East Eurasia and northern part of North America. The effects of ALL and GHG forcings are clearly detected for the spring SWE decline at the hemispherical scale, based on multi-model ensemble signals. The effects of ALL and GHG forcings, however, are less clear for the smaller regions or with single-model signals, indicating the large uncertainty in regional SWE changes, possibly due to stronger influence of natural climate variability.
Keywords: climate change; detection–attribution; human effects; Northern Hemisphere; snow water equivalent

Assisted design of antibody and protein therapeutics (ADAPT) - Vivcharuk, Victor; Baardsnes, Jason; Deprez, Christophe; Sulea, Traian; Jaramillo, Maria; Corbeil, Christopher R.; Mullick, Alaka; Magoon, Joanne; Marcil, Anne; Durocher, Yves; O’connor-McCourt, Maureen D.; Purisima, Enrico O.; et al. (PLOS ONE, 2017)
Effective biologic therapeutics require binding affinities that are fine-tuned to their disease-related molecular target. The ADAPT (Assisted Design of Antibody and Protein Therapeutics) platform aids in the selection of mutants that improve/modulate the affinity of antibodies and other biologics. It uses a consensus z-score from three scoring functions and interleaves computational predictions with experimental validation, significantly enhancing the robustness of the design and selection of mutants. The platform was tested on three antibody Fab-antigen systems that spanned a wide range of initial binding affinities: bH1-VEGF-A (44 nM), bH1-HER2 (3.6 nM) and Herceptin-HER2 (0.058 nM). Novel triple mutants were obtained that exhibited 104-, 46- and 32-fold improvements in binding affinity for each system, respectively. Moreover, for all three antibody-antigen systems over 90% of all the intermediate single and double mutants that were designed and tested showed higher affinities than the parent sequence. The contributions of the individual mutants to the change in binding affinity appear to be roughly additive when combined to form double and triple mutants. The new interactions introduced by the affinity-enhancing mutants included long-range electrostatics as well as short-range nonpolar interactions. This diversity in the types of new interactions formed by the mutants was reflected in SPR kinetics that showed that the enhancements in affinities arose from increasing on-rates, decreasing off-rates or a combination of the two effects, depending on the mutation. ADAPT is a very focused search of sequence space and required only 20–30 mutants for each system to be made and tested to achieve the affinity enhancements mentioned above.

Application of laboratory and portable attenuated total reflectance infrared spectroscopic approaches for rapid quantification of alpaca serum immunoglobulin G - Elsohaby, Ibrahim; Burns, Jennifer B.; Riley, Christopher B.; Shaw, R. Anthony; Mcclure, J. Trenton; Khodarahmi, Reza (PLOS ONE, 2017)
The objective of this study was to develop and compare the performance of laboratory grade and portable attenuated total reflectance infrared (ATR-IR) spectroscopic approaches in combination with partial least squares regression (PLSR) for the rapid quantification of alpaca serum IgG concentration, and the identification of low IgG (<1000 mg/dL), which is consistent with the diagnosis of failure of transfer of passive immunity (FTPI) in neonates. Serum samples (n = 175) collected from privately owned, healthy alpacas were tested by the reference method of radial immunodiffusion (RID) assay, and laboratory grade and portable ATR-IR spectrometers. Various pre-processing strategies were applied to the ATR-IR spectra that were linked to corresponding RID-IgG concentrations, and then randomly split into two sets: calibration (training) and test sets. PLSR was applied to the calibration set and calibration models were developed, and the test set was used to assess the accuracy of the analytical method. For the test set, the Pearson correlation coefficients between the IgG measured by RID and predicted by both laboratory grade and portable ATR-IR spectrometers was 0.91. The average differences between reference serum IgG concentrations and the two IR-based methods were 120.5 mg/dL and 71 mg/dL for the laboratory and portable ATR-IR-based assays, respectively. Adopting an IgG concentration <1000 mg/dL as the cut-point for FTPI cases, the sensitivity, specificity, and accuracy for identifying serum samples below this cut point by laboratory ATR-IR assay were 86, 100 and 98%, respectively (within the entire data set). Corresponding values for the portable ATR-IR assay were 95, 99 and 99%, respectively. These results suggest that the two different ATR-IR assays performed similarly for rapid qualitative evaluation of alpaca serum IgG and for diagnosis of IgG <1000 mg/dL, the portable ATR-IR spectrometer performed slightly better, and provides more flexibility for potential application in the field.

Application of digital image correlation to the thick adherend shear test - Van Blitterswyk, Jared; Backman, David; Laliberté, Jeremy; Cole, Richard (Joining Technologies for Composites and Dissimilar Materials, Volume 10: Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics, 2017)
The purpose of this study was to develop and validate a novel method for measuring shear deformation during the Thick Adherend Shear Test (TAST), to determine in situ mechanical properties of an adhesive under tensile shear loading, using two-dimensional (2D) Digital Image Correlation (DIC). Shear strains were optically measured using DIC from the bond line and also from adherend deformations; both were compared against measurements made using the ASTM D5656 standard (KGR-1 extensometers). The results from 17 TAST specimens showed that all techniques were in good agreement, however, both DIC techniques had significantly lower variance on measured mechanical properties compared to the KGR-1 extensometers. The use of correlated adherend deformations was the preferred technique for deriving plastic shear strains, and overall produced the lowest scatter on mechanical properties. This study demonstrates the potential for the use of 2D DIC as a more precise, and time-efficient alternative to the KGR-1 extensometers for room temperature in situ characterization of adhesives in shear.
Keywords: Adhesives; Mechanical properties; Single-lap joint; Digital image correlation (DIC); KGR-1 extensometer; Experimental test methods

Antiresonances in the mid-infrared vibrational spectrum of functionalized graphene - Lapointe, François; Rousseau, Bruno; Aymong, Vincent; Nguyen, Minh; Biron, Maxime; Gaufrès, Etienne; Choubak, Saman; Han, Zheng; Bouchiat, Vincent; Desjardins, Patrick; Côté, Michel; Martel, Richard (The Journal of Physical Chemistry C, 2017)
We report anomalous antiresonances in the infrared spectra of doped and disordered single layer graphene. Measurements in both reflection microscopy and transmission configurations of samples grafted with halogenophenyl moieties are presented. Asymmetric transparency windows at energies corresponding to phonon modes near the Γ and K points are observed, in contrast to the featureless spectrum of pristine graphene. These asymmetric antiresonances are demonstrated to vary as a function of the chemical potential and defect density. We propose a model that involves coherent intraband scattering with defects and phonons, thus relaxing the optical selection rule forbidding access to q ≠ Γ phonons. This interpretation of the new phenomenon is supported by our numerical simulations that reproduce the experimental features.

Another brick in the wall: a rhamnan polysaccharide trapped inside peptidoglycan of Lactococcus lactis - Sadovskaya, Irina; Vinogradov, Evgeny; Courtin, Pascal; Armalyte, Julija; Meyrand, Mickael; Giaouris, Efstathios; Palussière, Simon; Furlan, Sylviane; Péchoux, Christine; Ainsworth, Stuart; Mahony, Jennifer; Van Sinderen, Douwe; et al. (mBio, 2017)
Polysaccharides are ubiquitous components of the Gram-positive bacterial cell wall. In Lactococcus lactis, a polysaccharide pellicle (PSP) forms a layer at the cell surface. The PSP structure varies among lactococcal strains; in L. lactis MG1363, the PSP is composed of repeating hexasaccharide phosphate units. Here, we report the presence of an additional neutral polysaccharide in L. lactis MG1363 that is a rhamnan composed of α-l-Rha trisaccharide repeating units. This rhamnan is still present in mutants devoid of the PSP, indicating that its synthesis can occur independently of PSP synthesis. High-resolution magic-angle spinning nuclear magnetic resonance (HR-MAS NMR) analysis of whole bacterial cells identified a PSP at the surface of wild-type cells. In contrast, rhamnan was detected only at the surface of PSP-negative mutant cells, indicating that rhamnan is located underneath the surface-exposed PSP and is trapped inside peptidoglycan. The genetic determinants of rhamnan biosynthesis appear to be within the same genetic locus that encodes the PSP biosynthetic machinery, except the gene tagO encoding the initiating glycosyltransferase. We present a model of rhamnan biosynthesis based on an ABC transporter-dependent pathway. Conditional mutants producing reduced amounts of rhamnan exhibit strong morphological defects and impaired division, indicating that rhamnan is essential for normal growth and division. Finally, a mutation leading to reduced expression of lcpA, encoding a protein of the LytR-CpsA-Psr (LCP) family, was shown to severely affect cell wall structure. In lcpA mutant cells, in contrast to wild-type cells, rhamnan was detected by HR-MAS NMR, suggesting that LcpA participates in the attachment of rhamnan to peptidoglycan.
Keywords: HR-MAS NMR; Lactococcus; cell wall; polysaccharides; rhamnan

Anisotropic permeability in deterministic lateral displacement arrays - Vernekar, Rohan; Krüger, Timm; Loutherback, Kevin; Morton, Keith; W. Inglis, David (Lab on a Chip, 2017)
We uncover anisotropic permeability in microfluidic deterministic lateral displacement (DLD) arrays. A DLD array can achieve high-resolution bimodal size-based separation of microparticles, including bioparticles, such as cells. For an application with a given separation size, correct device operation requires that the flow remains at a fixed angle to the obstacle array. We demonstrate via experiments and lattice-Boltzmann simulations that subtle array design features cause anisotropic permeability. Anisotropic permeability indicates the microfluidic array's intrinsic tendency to induce an undesired lateral pressure gradient. This can cause an inclined flow and therefore local changes in the critical separation size. Thus, particle trajectories can become unpredictable and the device useless for the desired separation task. Anisotropy becomes severe for arrays with unequal axial and lateral gaps between obstacle posts and highly asymmetric post shapes. Furthermore, of the two equivalent array layouts employed with the DLD, the rotated-square layout does not display intrinsic anisotropy. We therefore recommend this layout over the easier-to-implement parallelogram layout. We provide additional guidelines for avoiding adverse effects of anisotropy on the DLD.

Anatomy of the internal bow shocks in the IRAS 04166+2706 protostellar jet - Tafalla, M.; Su, Y.-N.; Shang, H.; Johnstone, D.; Zhang, Q.; Santiago-García, J.; Lee, C.-F.; Hirano, N.; Wang, L.-Y. (Astronomy & Astrophysics, 2017)
Context. Highly collimated jets and wide-angle outflows are two related components of the mass-ejection activity associated with stellar birth. Despite decades of research, the relation between these two components remains poorly understood. Aims. We study the relation between the jet and the outflow in the IRAS 04166+2706 protostar. This Taurus protostar drives a molecular jet that contains multiple emission peaks symmetrically located from the central source. The protostar also drives a wide-angle outflow consisting of two conical shells. Methods. We have used the Atacama Large Millimeter/submillimeter Array (ALMA) interferometer to observe two fields along the IRAS 04166+2706 jet. The fields were centered on a pair of emission peaks that correspond to the same ejection event. The observations were carried out in CO(2–1), SiO(5–4), and SO(JN = 65–54). Results. Both ALMA fields present spatial distributions that are approximately elliptical and have their minor axes aligned with the jet direction. As the velocity increases, the emission in each field moves gradually across the elliptical region. This systematic pattern indicates that the emitting gas in each field lies in a disk-like structure that is perpendicular to the jet axis and whose gas is expanding away from the jet. A small degree of curvature in the first-moment maps indicates that the disks are slightly curved in the manner expected for bow shocks moving away from the IRAS source. A simple geometrical model confirms that this scenario fits the main emission features. Conclusions. The emission peaks in the IRAS 04166+2706 jet likely represent internal bow shocks where material is being ejected laterally away from the jet axis. While the linear momentum of the ejected gas is dominated by the component in the jet direction, the sideways component is not negligible, and can potentially affect the distribution of gas in the surrounding outflow and core.
Keywords: stars: formation; ISM: individual objects: IRAS 04166+2706; ISM: jets and outflows; ISM: molecules; radio lines: ISM

Analysis of gold in rock samples using laser-induced breakdown spectroscopy: matrix and heterogeneity effects - Rifai, Kheireddine; Laflamme, Marcel; Constantin, Marc; Vidal, François; Sabsabi, Mohamad; Blouin, Alain; Bouchard, Paul; Fytas, Konstantinos; Castello, Maryline; Kamwa, Blandine Nguegang (Spectrochimica Acta Part B: Atomic Spectroscopy, 2017)
We used the laser-induced breakdown spectroscopy (LIBS) technique to determine the concentration of gold in rock samples. 44 reference materials (mostly compressed fine powders) of various chemical compositions, with a quasi-homogeneous concentration of gold varying from 0 to 1000 ppm, were used to establish the calibration curve for the Au I 267.59 nm line. A chemometric study based on the principal component analysis (PCA) showed that ~ 83% of the LIBS spectra variations are attributable to the presence of iron in the samples. Two distinct branches were obtained in the calibration curve: one for Si-rich samples (< 5% of iron) and one for Fe-rich samples (> 13% of iron) with limits of detection of 0.8 ppm and 1.5 ppm, respectively. Different normalization schemes of the gold signal were tested in order to reduce the matrix effects. The LIBS analysis was performed on various mineral samples of practical interest, namely two Si-rich uncompressed ore powders, fine and granular, and three bulk drill cores. The fluctuations in the gold concentration measurements appear to be about two times greater in the granular powder (5–10%) than in the fine one (2–5%). A detailed mapping of the gold concentration on a solid drill core was also performed, revealing multiscale heterogeneity of the gold distribution on the surface of the sample.

An optical/near-infrared investigation of HD 100546 b with the Gemini Planet Imager and MagAO - Rameau, Julien; Follette, Katherine B.; Pueyo, Laurent; Marois, Christian; Macintosh, Bruce; Millar-Blanchaer, Maxwell; Wang, Jason J.; Vega, David; Doyon, René; Lafrenière, David; Nielsen, Eric L.; Bailey, Vanessa; et al. (The Astronomical Journal, 2017)
We present H band spectroscopic and Hα photometric observations of HD 100546 obtained with the Gemini Planet Imager and the Magellan Visible AO camera. We detect H band emission at the location of the protoplanet HD 100546 b, but show that the choice of data processing parameters strongly affects the morphology of this source. It appears point-like in some aggressive reductions, but rejoins an extended disk structure in the majority of the others. Furthermore, we demonstrate that this emission appears stationary on a timescale of 4.6 years, inconsistent at the 2σ level with a Keplerian clockwise orbit at 59 au in the disk plane. The H band spectrum of the emission is inconsistent with any type of low effective temperature object or accreting protoplanetary disk. It strongly suggests a scattered-light origin, as this is consistent with the spectrum of the star and the spectra extracted at other locations in the disk.

An efficient spiral microchannel for continuous small particle separations - Yeh, P. Y.; Dai, Z.; Yang, X.; Bergeron, M.; Zhang, Z.; Lin, M.; Cao, X. (Sensors and Actuators B: Chemical, 2017)
We report a new two-step microfluidic device that performs efficient, continuous, and high throughput small particle separation. The separation mechanism is based the on combined effects of inertial focusing in a spiral microchannel followed by particle deflection in a straight microchannel. The particle trajectory was studied using 1 and 5.5 μm fluorescent polystyrene microbeads as model particles to be separated. We demonstrate that at the condition of 0.4 ml/min inlet, 0.15 ml/min acting, and 0.02 ml/min protecting flow rates, the separation efficiencies of 1 μm particles and 5.5 μm particles were 99.7% and 98.3%, and the corresponding purities were 95.7% and 99.6%, respectively. This new design shows a significant separation performance for small particles, and therefore can be potentially integrated as a promising tool to separate rare of-interest particles, such as bacteria from homogenized food matrix as part of sample preparation procedure for food safety inspections.
Keywords: particle separation; microfluidics; inertial focusing; dean vortices; lift force; sample preparation

An EEG brain–computer interface approach for classifying vigilance states in humans: a gamma band focus supports low misclassification rates - Van Benthem, K. D.; Cebulski, S.; Herdman, C. M.; Keillor, J. (International Journal of Human–Computer Interaction, 2017)
This research investigated a brain–computer interface (BCI) for classifying vigilance states. A BCI approach based on event-related potential (ERP) and spectral features of electroencephalographic (EEG) data derived from an auditory oddball paradigm was employed. A 128-channel EEG system recorded potentials while participants simultaneously completed a prolonged visual match-to-sample task. It was hypothesized that better classification rates would be found for a group of “bored” participants, as compared to the not-bored participants. The best classification rates were found by extracting EEG features from gamma frequencies at middle and late latencies (for the standard tones). Critically, the BCI paradigm was most effective for the bored participants (mean misclassification rate = 13%), as compared to the not-bored participants (mean misclassification rate = 21%). These findings extend our knowledge of reliable latencies and spectral features of ERP data most salient to the classification of vigilance states.

Aluminum extrusions for automotive crash applications - Parson, Nick; Fourmann, Jerome; Beland, Jean-Francois (SAE Technical Papers, 2017)
One of the main applications for aluminum extrusions in the automotive sector is crash structures including crash rails, crash cans, bumpers and structural body components. The objective is usually to optimize the energy absorption capability for a given structure weight. The ability to extrude thin wall multi-void extrusions contributes to this goal. However, the alloy used also plays a significant role in terms of the ability to produce the required geometry, strength - which to a large extent controls the energy absorption capability and the “ductility” or fracture behavior which controls the strain that can be applied locally during crush deformation before cracking. This paper describes results of a test program to examine the crush behavior of a range of alloys typically supplied for automotive applications as a function of processing parameters including artificial ageing and quench rate.

Altitude scaling of thermal ice protection systems in running wet operation - Orchard, D. M.; Addy, H. E.; Wright, W. B.; Tsao, J. (Conference Proceeding, 2017)
A study into the effects of altitude on an aircraft thermal Ice Protection System (IPS) performance has been conducted by the National Research Council Canada (NRC) in collaboration with the NASA. The study included tests of an airfoil model, with a heated-air IPS, installed in the NRC’s Altitude Icing Wind Tunnel (AIWT) at altitude and ground level conditions. Two scaling strategies were employed based on Reynolds number and Weber number, the latter combined with matching the ratio of water loading and evaporative rates. The Reynolds number scaled conditions resulted in greater mass of accreted ice that formed further back from the leading edge while the Weber number approach provided a close match to reference altitude conditions in terms of both ice mass, location and shape.

Alternate synthesis to d-glycero-β-d-manno-heptose 1,7-biphosphate - Sauvageau, Janelle; Bhasin, Milan; Guo, Cynthia X.; Adekoya, Itunuoluwa A.; Gray-owen, Scott D.; Oscarson, Stefan; Guazzelli, Lorenzo; Cox, Andrew (Carbohydrate Research, 2017)
d-glycero-β-d-manno-heptose 1,7-biphosphate (HBP) is an enzymatic intermediate in the biosynthesis of the heptose component of lipopolysaccharide (LPS), and was recently revealed to be a pathogen-associated molecular pattern (PAMP) that allows detection of Gram-negative bacteria by the mammalian immune system. Cellular detection of HBP depends upon its stimulation of a cascade that leads to the phosphorylation and assembly of the TRAF-interacting with forkhead-associated domain protein A (TIFA), which activates the transcription factor NF-κB. In this note, an alternate chemical synthesis of HBP is described and its biological activity is established, providing pure material for further assessing and exploiting the biological activity of this compound.
Keywords: d-glycero-β-d-manno-heptose 1,7-biphosphate (HBP); Nuclear factor-kappa B (NF-κB); Pathogen-associated molecular pattern (PAMP); Wittig reaction; TRAF-interacting with forkhead-associated domain protein A (TIFA)

Nitric oxide mediates nitrite-sensing and acclimation and triggers a remodeling of lipids - Dolch, Lina-Juana; Lupette, Josselin; Tourcier, Guillaume; Bedhomme, Mariette; Collin, Séverine; Magneschi, Leonardo; Conte, Melissa; Seddiki, Khawla; Richard, Christelle; Corre, Erwan; Fourage, Laurent; Laeuffer, Frédéric; et al. (Plant Physiology, 2017)
Nitric oxide (NO) is an intermediate of the nitrogen cycle, an industrial pollutant, and a marker of climate change. NO also acts as a gaseous transmitter in a variety of biological processes. The impact of environmental NO needs to be addressed. In diatoms, a dominant phylum in phytoplankton, NO was reported to mediate programmed cell death in response to diatom-derived polyunsaturated aldehydes. Here, using the Phaeodactylum Pt1 strain, 2E,4E-decadienal supplied in the micromolar concentration range led to a nonspecific cell toxicity. We reexamined NO biosynthesis and response in Phaeodactylum. NO inhibits cell growth and triggers triacylglycerol (TAG) accumulation. Feeding experiments indicate that NO is not produced from Arg but via conversion of nitrite by the nitrate reductase. Genome-wide transcriptional analysis shows that NO up-regulates the expression of the plastid nitrite reductase and genes involved in the subsequent incorporation of ammonium into amino acids, via both Gln synthesis and Orn-urea pathway. The phosphoenolpyruvate dehydrogenase complex is also up-regulated, leading to the production of acetyl-CoA, which can feed TAG accumulation upon exposure to NO. Transcriptional reprogramming leading to higher TAG content is balanced with a decrease of monogalactosyldiacylglycerol (MGDG) in the plastid via posttranslational inhibition of MGDG synthase enzymatic activity by NO. Intracellular and transient NO emission acts therefore at the basis of a nitrite-sensing and acclimating system, whereas a long exposure to NO can additionally induce a redirection of carbon to neutral lipids and a stress response.
Keywords: diatoms; Phaeodactylum; nitric oxide; nitrogen cycle; NOA; triacylglycerol

Ultra-broadband mode (de)multiplexer based on a sub-wavelength engineered MMI coupler - Gonzalez-Andrade, D.; Velasco, A. V.; Wanguemert-Perez, J. G.; Ortega-Monux, A.; Halir, R.; Cheben, P. (2017 IEEE Photonics Conference (IPC), 2017)
We present an ultra-broadband two-mode de/multiplexer based on a multimode interference coupler with sub-wavelength grating waveguides, a symmetric Y-junction and a 90° phase shifter. Numerical simulations show insertion losses below 0.18 dB and crosstalk lower than −20.6 dB in a 300 nm wavelength range.
Keywords: mode multiplexing; broadband; silicon-on-insulator; subwavelength grating waveguides

Total synthesis of (6R,10R,13R,14R,16R,17R,19S,20R,21R,24S, 25S,28S,30S,32R,33R,34R,36S,37S,39R)-azaspiracid-3 reveals non-identity with the natural product - Forsyth, Craig J.; Kenton, Nathaniel T.; Adu-Ampratwum, Daniel; Okumu, Antony A.; Zhang, Zhigao; Chen, Yong; Nguyen, Son; Xu, Jianyan; Ding, Yue; McCarron, Pearse; Kilcoyne, Jane; Rise, Frode; et al. (Angewandte Chemie, 2017)
A convergent and stereoselective total synthesis of the previously assigned structure of azaspiracid-3 has been achieved via a late stage NHK coupling to form the C21‒C22 bond with the C20 configuration unambiguously established from L-(+)-tartaric acid. Post-coupling steps involved oxidation to an ynone, modified Stryker reduction of the alkyne, global deprotection, and oxidation of the primary alcohol to the carboxylic acid. The synthetic product matched naturally occurring azaspiracid-3 by mass spectrometry, but differed both chromatographically and spectroscopically.
Keywords: azaspiracids; total synthesis; structure determination; natural products; toxins

Abbreviated closure for remote damage control laparotomy in extreme environments: a randomized trial of sutures versus wound clamps comparing terrestrial and weightless conditions - Kirkpatrick, Andrew W.; Mckee, Jessica Lynn; Tien, Colonel Homer; Laporta, Anthony J.; Lavell, Kit; Leslie, Tim; Mcbeth, Paul B.; Roberts, Derek J.; Ball, Chad G. (The American Journal of Surgery, 2017)
Introduction: Far-Forward Damage Control Laparotomies (DCLs) might provide direct-compression of visceral hemorrhage, however, suturing is a limiting factor, especially for non-physicians. We thus compared abbreviated skin closures comparing skin-suture (SS) versus wound-clamp (WC), on-board a research aircraft in weightlessness (0g) and normal gravity (1g). Methods: Surgeons conducted DCLs on a surgical-simulator; onboard the hangered-aircraft (1g), or during parabolic flight (0g), randomized to either WC or SS. Results: Ten surgeons participated. Two (40%) surgeons randomized to suture in 0g were incapacitated with motion-sickness, and none were able to close in either 1 or 0g. With WC, two completely closed in 1g as did three in 0g, despite having longer incisions (p = 0.016). Overall skin-closure with WC was significantly greater in both 1g (p = 0.016) and 0g (p = 0.008). Conclusions: WC was more effective in 1g and particularly 0g. Future studies should address the utility of abbreviated WC abdominal closure to facilitate potential Far-Forward DCL.
Keywords: exsanguination; operational medicine; tactical medicine; damage control surgery; surgical simulation

A solid state source of photon triplets based on quantum dot molecules - Khoshnegar, Milad; Huber, Tobias; Predojević, Ana; Dalacu, Dan; Prilmüller, Maximilian; Lapointe, Jean; Wu, Xiaohua; Tamarat, Philippe; Lounis, Brahim; Poole, Philip; Weihs, Gregor; Majedi, Hamed (Nature Communications, 2017)
Producing advanced quantum states of light is a priority in quantum information technologies. In this context, experimental realizations of multipartite photon states would enable improved tests of the foundations of quantum mechanics as well as implementations of complex quantum optical networks and protocols. It is favourable to directly generate these states using solid state systems, for simpler handling and the promise of reversible transfer of quantum information between stationary and flying qubits. Here we use the ground states of two optically active coupled quantum dots to directly produce photon triplets. The formation of a triexciton in these ground states leads to a triple cascade recombination and sequential emission of three photons with strong correlations. We record 65.62 photon triplets per minute under continuous-wave pumping, surpassing rates of earlier reported sources. Our structure and data pave the way towards implementing multipartite photon entanglement and multi-qubit readout schemes in solid state devices.
Keywords: quantum dots; quantum information

A review of proton exchange membrane water electrolysis on degradation mechanisms and mitigation strategies - Feng, Qi; Yuan, Xiao−Zi; Liu, Gaoyang; Wei, Bing; Zhang, Zhen; Li, Hui; Wang, Haijiang (Journal of Power Sources, 2017)
Proton exchange membrane water electrolysis (PEMWE) is an advanced and effective solution to the primary energy storage technologies. A better understanding of performance and durability of PEMWE is critical for the engineers and researchers to further advance this technology for its market penetration, and for the manufacturers of PEM water electrolyzers to implement quality control procedures for the production line or on-site process monitoring/diagnosis. This paper reviews the published works on performance degradations and mitigation strategies for PEMWE. Sources of degradation for individual components are introduced. With degradation causes discussed and degradation mechanisms examined, the review emphasizes on feasible strategies to mitigate the components degradation. To avoid lengthy real lifetime degradation tests and their high costs, the importance of accelerated stress tests and protocols is highlighted for various components. In the end, R&D directions are proposed to move the PEMWE technology forward to become a key element in future energy scenarios.
Keywords: proton exchange membrane water electrolysis; durability; degradation mechanism; mitigation

A review of high temperature co-electrolysis of H2O and CO2 to produce sustainable fuels using solid oxide electrolysis cells (SOECs): advanced materials and technology - Zheng, Yun; Wang, Jianchen; Yu, Bo; Zhang, Wenqiang; Chen, Jing; Qiao, Jinli; Zhang, Jiujun (Chemical Society Reviews, 2017)
High-temperature solid oxide electrolysis cells (SOECs) are advanced electrochemical energy storage and conversion devices with high conversion/energy efficiencies. They offer attractive high-temperature co-electrolysis routes that reduce extra CO2 emissions, enable large-scale energy storage/conversion and facilitate the integration of renewable energies into the electric grid. Exciting new research has focused on CO2 electrochemical activation/conversion through a co-electrolysis process based on the assumption that difficult C[double bond, length as m-dash]O double bonds can be activated effectively through this electrochemical method. Based on existing investigations, this paper puts forth a comprehensive overview of recent and past developments in co-electrolysis with SOECs for CO2 conversion and utilization. Here, we discuss in detail the approaches of CO2 conversion, the developmental history, the basic principles, the economic feasibility of CO2/H2O co-electrolysis, and the diverse range of fuel electrodes as well as oxygen electrode materials. SOEC performance measurements, characterization and simulations are classified and presented in this paper. SOEC cell and stack designs, fabrications and scale-ups are also summarized and described. In particular, insights into CO2 electrochemical conversions, solid oxide cell material behaviors and degradation mechanisms are highlighted to obtain a better understanding of the high temperature electrolysis process in SOECs. Proposed research directions are also outlined to provide guidelines for future research.

A rational design for enhanced oxygen reduction: strongly coupled silver nanoparticles and engineered perovskite nanofibers - Zhang, Ya-Qian; Tao, Hong-Biao; Liu, Jun; Sun, Yi-Fei; Chen, Jian; Hua, Bin; Thundat, Thomas; Luo, Jing-Li (Nano Energy, 2017)
For perovskites to become more competitive oxygen reduction reaction (ORR) catalysts, substantial progress is required to advance their enhanced catalytic activity and durability. Herein, a novel method is described to achieve high-performance perovskite ORR catalyst via combining nano architecture designs, internal structures engineering, and Ag nanoparticles (NPs) in situ exsolution. The as-synthesized Ag-(PrBa)0.95Mn2O5+δ catalyst exhibits favorable ORR activity with durability superior to the state-of-the-art Pt/C in alkaline solution. Several characterization techniques were applied alongside density functional theory calculations to understand the possible active sites and the synergistic coupling effects that contributed to the high ORR performance. The strong interfacial anchoring of Ag NPs on the ordered oxygen deficient perovskites leads to significant ligand effect and facilitates electron transfer and ion migration within the oxygen reduction reaction. The systematic engineering of perovskites described here represents a brand new approach to developing highly active and stable catalyst for energy conversion and storage.
Keywords: oxygen reduction; perovskite; mesoporous; Ag exsolution; ordered structure

A auantum light-matter beamsplitter in diamond - England, Duncan; Fisher, Kent; Maclean, Jean-Philippe; Heshami, Khabat; Bustard, Philip; Resch, Kevin; Sussman, Ben (Conference on Lasers and Electro-Optics, 2017)
A quantum memory can be viewed as a light-matter beam-splitter, mapping a photon to a superposition of the output optical mode and stored mode. We use this mechanism to demonstrate non-classical one-photon and two-photon interference.

A preliminary study on bi-layered ceramic electrolytes of mixed conductor and proton conductor - Zhang, Xinge; Robertson, Mark; Deces-Petit, Cyrille (ECS Transactions, 2017)
In this contribution, we present an experimental study of single-layered electrolyte with mixed ion and electron conducting ceramic material SDC (Sm0.2Ce0.8O2-x) and bi-layered electrolyte of the SDC layer with proton conducting ceramic material BCY (BaCe0.9Y0.1O3-x) to enhance the electrolyte performance. Anode supported cell structure was adopted and the button cells were fabricated through conventional tape casting, screen printing and high temperature sintering processes. It was found that the open circuit voltages of the bi-layered electrolyte cells were higher than that of single-layered SDC electrolyte cells. The bi-layered cells showed a decent performance in the temperature range of 500-650°C. Interaction between the two electrolyte materials occurred at high sintering temperature, which led to an increase in electrolyte resistance as well as electrode polarization values.

A practical solution for HVAC prognostics: failure mode and effects analysis in building maintenance - Yang, Chunsheng; Shen, Weiming; Chen, Qiangqiang; Gunay, Burak (Journal of Building Engineering, 2017)
Fault detection, diagnostics, and prognostics (FDD&P) is attracting an amount of attention from building operators and researchers because it can help greatly improve the performance of building operations by reducing energy consumption for heating, ventilation and air-conditioning (HVAC) while improving occupant comfort at the same time. However, FDD&P, particularly HVAC prognostics, for building operations remains with many challenges due to special operation environments of HVAC systems. These challenges include “tolerance or ignorance” of failures in long-haul operations, lack of operation regulations, and even lack of documents for HVAC failure mode and effects analysis (FMEA), which is a systematic method of identifying and preventing system, product and process problems. To address some of these challenges, the authors propose an FMEA method for common building HVAC equipment by exploring work-orders generated by building energy management systems (BEMS) using a data mining approach. With this FMEA approach, it is possible for building operators to isolate and prognose faults practically. The FMEA approach also helps us tackle high impact failures, for which operation data can be acquired and machine learning-based predictive models can be developed. This paper reports some preliminary results in conducting an HVAC FMEA from a large number of work-orders obtained from a BEMS in routine operations. The HVAC FMEA will be used as a guidance tool for data gathering and developing data-driven models for HVAC FDD&P and as a practical solution for HVAC prognostics in case that predictive models are difficult to develop.
Keywords: FMEA; work-order; fault detection and diagnostics (FDD); prognostics; HVAC

A photometric study of the outer halo globular cluster NGC 5824 - Walker, A. R.; Andreuzzi, G.; Martínez-Vázquez, C. E.; Kunder, A. M.; Stetson, P. B.; Cassisi, S.; Monelli, M.; Bono, G.; Dall’ora, M; Vivas, A. K. (The Astronomical Journal, 2017)
Multi-wavelength CCD photometry over 21 years has been used to produce deep color–magnitude diagrams (CMDs) together with light curves for the variables in the Galactic globular cluster NGC 5824. Twenty-one new cluster RR Lyrae stars are identified, bringing the total to 47, of which 42 have reliable periods determined for the first time.
Keywords: galaxy: stellar content; stars: distance; stars: evolution; stars: horizontal-brand; stars: population II

A novel fully automatic measurement of apparent breast volume from trunk surface mesh - Seoud, Lama; Ramsay, Joyce; Parent, Stefan; Cheriet, Farida (Medical Engineering & Physics, 2017)
This paper presents a novel method for assessing apparent breast volume from trunk surface mesh without any manual intervention. The proposed method requires a closed and smooth triangular mesh of the trunk. It comprises four main steps: automatic nipple localization, automatic breasts delineation, chest-wall interpolation and volume computation. The mean curvature is computed for each vertex using a quadratic fitting approach and used as an indicator to determine the convex fold of the breasts. The delineation is modeled as an ellipse in the frontal plane and all the vertices inside it are removed. The remaining ones are used to interpolate the chest wall with radial basis functions. The voxels inside the resulting mesh without breasts are then subtracted from the original voxelized volume to generate the breasts volume. The validation is conducted on 30 adolescent female for each of which an MRI and a trunk surface (TS) acquisitions were available. Three breast volumes are considered: the anatomical volumes (AV) manually segmented on the MRI, the external volumes computed with the proposed method first in prone position (EVP) using the trunk mesh extracted from the MRI, and second, in standing position (EVS) using the TS's mesh. Significant correlations (R> 0.77) are found between each two of the three volumes. AVs are much larger than both EVS and EPS. In fact, the manual segmentation using MRI slices allows for a direct visualization of the breast posterior delineation. Computed automatically, EVS and EPS are highly similar, indicating that the proposed method is robust to changes from prone to standing position. No significant difference between the regressions on the left and right breasts is noted. Fully-automatic 3D breast volumetry from trunk surface mesh is feasible and provides measurements that are highly correlated to manual MRI volumetry and robust to changes in posture.
Keywords: breast volumetry; curvature; surface mesh

A near-infrared Counterpart of 2E1613.5–5053: the Central Source in Supernova Remnant RCW103 - Tendulkar, S. P.; Kaspi, V. M.; Archibald, R. F.; Scholz, P. (The Astrophysical Journal, 2017)
On 2016 June 22, 2E 1613.5−5053, the puzzling central compact object in supernova remnant RCW 103 emitted a magnetar-like burst. Using Director's Discretionary Time, we observed 2E 1613.5−5053 with the Hubble Space Telescope (HST) (WFC3/IR) and we report here on the detection of a previously unseen infrared counterpart.
Keywords: pulsars: individual (2E 1613.1-5053); stars: neutron

A methodology for assessing fatigue life of a countersunk riveted lap joint - Li, Gang; Renaud, Guillaume; Liao, Min; Okada, Takao; Machida, Shigeru (Advances in Aircraft and Spacecraft Science, 2017)
Fatigue life prediction of a multi-row countersunk riveted lap joint was performed numerically. The stress and strain conditions in a highly stressed substructure of the joint were analysed using a global/local finite element (FE) model coupling approach. After validation of the FE models using experimental strain measurements, the stress/strain condition in the local three-dimensional (3D) FE model was simulated under a fatigue loading condition. This local model involved multiple load cases with nonlinearity in material properties, geometric deformation, and contact boundary conditions. The resulting stresses and strains were used in the Smith-Watson-Topper (SWT) strain life equation to assess the fatigue "initiation life", defined as the life to a 0.5 mm deep crack. Effects of the rivet-hole clearance and rivet head deformation on the predicted fatigue life were identified, and good agreement in the fatigue life was obtained between the experimental and the numerical results. Further crack growth from a 0.5 mm crack to the first linkup of two adjacent cracks was evaluated using the NRC in-house tool, CanGROW. Good correlation in the fatigue life was also obtained between the experimental result and the crack growth analysis. The study shows that the selected methodology is promising for assessing the fatigue life for the lap joint, which is expected to improve research efficiency by reducing test quantity and cost.
Keywords: fatigue life; global/local FE model coupling; crack growth; riveted lap joint; the Smith-Watson-Topper (SWT) equation

A medically relevant capsular polysaccharide in Acinetobacter baumannii is a potential vaccine candidate - Yang, Feng-Ling; Lou, Tze-Chi; Kuo, Shu-Chen; Wu, Wan-Ling; Chern, Jeffy; Lee, Yi-Tzu; Chen, Shui-Tsung; Zou, Wei; Lin, Nien-Tsung; Wu, Shih-Hsiung (Vaccine, 2017)
Concerns of Acinetobacter baumannii infection have increased due to the emergence of multi-drug resistance. In the present study, we determined the capsular polysaccharide (CPS) structure of A. baumannii SK44, a clinical isolate from Taiwan, to consist of pentasaccharide repeats. We found that CPS-induced antibody provided 55% protection against challenge in an animal model. The CPS-specific antibody reacted with the surface components of about 62% clinical isolates (342/554 strains) from cross-sectional and longitudinal studies by dot-immunoassay. Pulsed-field gel electrophoresis of positive strains showed the antibody covered different clonalites of A. baumannii clinical isolates. Meanwhile, using the CPS antibody as a probe, we found a number of outer membrane proteins bound to the antibody, including OmpA/motB, TonB-dependent receptor, and Omp38, indicating their association with CPS. These results might lead to the use of the capsular polysaccharide as a vaccine to prevent A. baumannii infection.
Keywords: Acinetobacter baumannii; capsular polysaccharide; passive immunity; clinic population distribution

A likely decade-long sustained tidal disruption event - Lin, Dacheng; Guillochon, James; Komossa, S.; Ramirez-Ruiz, Enrico; Irwin, Jimmy A.; Maksym, W. Peter; Grupe, Dirk; Godet, Olivier; Webb, Natalie A.; Barret, Didier; Zauderer, B. Ashley; Duc, Pierre-Alain; et al. (Nature Astronomy, 2017)
Multiwavelength flares from tidal disruption and accretion of stars can be used to find and study otherwise dormant massive black holes in galactic nuclei. Previous well-monitored candidate flares were short-lived, with most emission confined to within ∼1 year. Here we report the discovery of a well-observed super-long (>11 years) luminous X-ray flare from the nuclear region of a dwarf starburst galaxy. After an apparently fast rise within ∼4 months a decade ago, the X-ray luminosity, though showing a weak trend of decay, has been persistently high at around the Eddington limit (when the radiation pressure balances the gravitational force). The X-ray spectra are soft — steeply declining towards higher energies — and can be described with Comptonized emission from an optically thick low-temperature corona, a super-Eddington accretion signature often observed in accreting stellar-mass black holes. Dramatic spectral softening was also caught in one recent observation, implying either a temporary transition from the super-Eddington accretion state to the standard thermal state, or the presence of a transient highly blueshifted (∼0.36c) warm absorber. All these properties in concert suggest a tidal disruption event with an unusually long super-Eddington accretion phase that has never before been observed.

A high resolution survey of the Galactic Plane at 408 MHz - Tung, A. K.; Kothes, R.; Landecker, T. L.; Geisbüsch, J.; Rizzo, D. Del; Taylor, A. R.; Brunt, C. M.; Gray, A. D.; Dougherty, S. M. (The Astronomical Journal, 2017)
The interstellar medium is a complex "ecosystem" with gas constituents in the atomic, molecular and ionized states, dust, magnetic fields, and relativistic particles. The Canadian Galactic Plane Survey has imaged these constituents at multiple radio and infrared frequencies with angular resolution of the order of arcminutes. This paper presents radio continuum data at 408 MHz over the area of 52o <=l<=193o, -6o.5<=b<=8o.5, with an extension to b=21o in the range of 97o <=l<=120o, with angular resolution 2'8 x 2'8 cosecδ. Observations were made with the Synthesis Telescope at the Dominion Radio Astrophysical Observatory as part of the Canadian Galactic Plane Survey. The calibration of the survey using existing radio source catalogs is described. The accuracy of 408 MHz flux densities from the data is 6%. Information on large structures has been incorporated into the data using the single-antenna survey of Haslam et al. The paper presents the data, describes how it can be accessed electronically, and gives examples of applications of the data to ISM research.
Keywords: ISM: general; ISM: structure; radio continuum: general; surveys

A dynamic strategy for wavelength sensing using the diffracted orders of a grating - Azmayesh-Fard, Seyed M.; Melnyk, Aaron; Lam, Lawrence; Allen, Trevor; Fedosejevs, Robert; Decorby, Ray G. (Lab on a Chip, 2017)
We propose a strategy for real time multicolour detection of light emitting particles under flow conditions, using the diffracted orders of a grating. The method relies on the fact that the spatial (angular/linear) separation between the orders of a diffraction grating is a wavelength dependent quantity. Thus, the difference in arrival times at a fixed detector for neighbouring orders produced by a moving, light-emitting particle can be used as a wavelength sensing mechanism. We demonstrate this functionality using a prototype PDMS microfluidic device that incorporates a focusing transmission grating. A key attribute of this approach is that it requires only a single sensitive detector, such as a photomultiplier tube, in contrast to many conventional approaches which require multiple sensitive detectors or a detector array.

A direct localization of a fast radio burst and its host - Chatterjee, S.; Law, C. J.; Wharton, R. S.; Burke-Spolaor, S.; Hessels, J. W. T.; Bower, G. C.; Cordes, J. M.; Tendulkar, S. P.; Bassa, C. G.; Demorest, P.; Butler, B. J.; Seymour, A.; et al. (Nature, 2017)
Fast radio bursts are astronomical radio flashes of unknown physical nature with durations of milliseconds. Their dispersive arrival times suggest an extragalactic origin and imply radio luminosities that are orders of magnitude larger than those of all known short-duration radio transients. So far all fast radio bursts have been detected with large single-dish telescopes with arcminute localizations, and attempts to identify their counterparts (source or host galaxy) have relied on the contemporaneous variability of field sources or the presence of peculiar field stars or galaxies4. These attempts have not resulted in an unambiguous association with a host or multi-wavelength counterpart. Here we report the subarcsecond localization of the fast radio burst FRB 121102, the only known repeating burst source using high-time-resolution radio interferometric observations that directly image the bursts. Our precise localization reveals that FRB 121102 originates within 100 milliarcseconds of a faint 180-microJansky persistent radio source with a continuum spectrum that is consistent with non-thermal emission, and a faint (twenty-fifth magnitude) optical counterpart. The flux density of the persistent radio source varies by around ten per cent on day timescales, and very long baseline radio interferometry yields an angular size of less than 1.7 milliarcseconds. Our observations are inconsistent with the fast radio burst having a Galactic origin or its source being located within a prominent star-forming galaxy. Instead, the source appears to be co-located with a low-luminosity active galactic nucleus or a previously unknown type of extragalactic source. Localization and identification of a host or counterpart has been essential to understanding the origins and physics of other kinds of transient events, including gamma-ray bursts and tidal disruption events. However, if other fast radio bursts have similarly faint radio and optical counterparts, our findings imply that direct subarcsecond localizations may be the only way to provide reliable associations.

A deep ALMA image of the Hubble Ultra Deep Field - Dunlop, J. S.; Mclure, R. J.; Biggs, A. D.; Geach, J. E.; Michałowski, M. J.; Ivison, R. J.; Rujopakarn, W.; Van kampen, E.; Kirkpatrick, A.; Pope, A.; Scott, D.; Swinbank, A. M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We present the results of the first, deep Atacama Large Millimeter Array (ALMA) imaging covering the full ≃4.5 arcmin2 of the Hubble Ultra Deep Field (HUDF) imaged with Wide Field Camera 3/IR on HST. Using a 45-pointing mosaic, we have obtained a homogeneous 1.3-mm image reaching σ1.3 ≃ 35 μJy, at a resolution of ≃0.7 arcsec. From an initial list of ≃50 > 3.5σ peaks, a rigorous analysis confirms 16 sources with S1.3 > 120 μJy. All of these have secure galaxy counterparts with robust redshifts (〈z〉 = 2.15). Due to the unparalleled supporting data, the physical properties of the ALMA sources are well constrained, including their stellar masses (M*) and UV+FIR star formation rates (SFR). Our results show that stellar mass is the best predictor of SFR in the high-redshift Universe; indeed at z ≥ 2 our ALMA sample contains seven of the nine galaxies in the HUDF with M* ≥ 2 × 1010 M⊙, and we detect only one galaxy at z > 3.5, reflecting the rapid drop-off of high-mass galaxies with increasing redshift. The detections, coupled with stacking, allow us to probe the redshift/mass distribution of the 1.3-mm background down to S1.3 ≃ 10 μJy. We find strong evidence for a steep star-forming ‘main sequence’ at z ≃ 2, with SFR ∝M* and a mean specific SFR ≃ 2.2 Gyr−1. Moreover, we find that ≃85 per cent of total star formation at z ≃ 2 is enshrouded in dust, with ≃65 per cent of all star formation at this epoch occurring in high-mass galaxies (M* > 2 × 1010 M⊙), for which the average obscured:unobscured SF ratio is ≃200. Finally, we revisit the cosmic evolution of SFR density; we find this peaks at z ≃ 2.5, and that the star-forming Universe transits from primarily unobscured to primarily obscured at z ≃ 4.
Keywords: galaxies: evolution; galaxies: high-redshift; galaxies: starburst; cosmology: observations; submillimetre: galaxies

A deconvolution technique to correct deep images of galaxies from instrumental scattered light - Karabal, E.; Duc, P.-A.; Kuntschner, H.; Chanial, P.; Cuillandre, J.-C.; Gwyn, S. (Astronomy & Astrophysics, 2017)
Deep imaging of the diffuse light that is emitted by stellar fine structures and outer halos around galaxies is often now used to probe their past mass assembly. Because the extended halos survive longer than the relatively fragile tidal features, they trace more ancient mergers. We use images that reach surface brightness limits as low as 28.5−29 mag arcsec-2 (g-band) to obtain light and color profiles up to 5–10 effective radii of a sample of nearby early-type galaxies. These were acquired with MegaCam as part of the CFHT MATLAS large programme. These profiles may be compared to those produced using simulations of galaxy formation and evolution, once corrected for instrumental effects. Indeed they can be heavily contaminated by the scattered light caused by internal reflections within the instrument. In particular, the nucleus of galaxies generates artificial flux in the outer halo, which has to be precisely subtracted. We present a deconvolution technique to remove the artificial halos that makes use of very large kernels. The technique, which is based on PyOperators, is more time efficient than the model-convolution methods that are also used for that purpose. This is especially the case for galaxies with complex structures that are hard to model. Having a good knowledge of the point spread function (PSF), including its outer wings, is critical for the method. A database of MegaCam PSF models corresponding to different seeing conditions and bands was generated directly from the deep images. We show that the difference in the PSFs in different bands causes artificial changes in the color profiles, in particular a reddening of the outskirts of galaxies having a bright nucleus. The method is validated with a set of simulated images and applied to three representative test cases: NGC 3599, NGC 3489, and NGC 4274, which exhibits a prominent ghost halo for two of them. This method successfully removes this.
Keywords: galaxies: evolution; galaxies: elliptical and lenticular, cD; galaxies: stellar content; galaxies: photometry; techniques: photometric; techniques: image processing

A dataset for multi-target stance detection - Sobhani, P.; Inkpen, D.; Zhu, X. (Proceedings of Conference of the European Chapter of the Association for Computational Linguistics. Volume 2, 2017)
Current models for stance classification often treat each target independently, but in many applications, there exist natural dependencies among targets, e.g., stance towards two or more politicians in an election or towards several brands of the same product. In this paper, we focus on the problem of multi-target stance detection. We present a new dataset that we built for this task. Furthermore, We experiment with several neural models on the dataset and show that they are more effective in jointly modeling the overall position towards two related targets compared to independent predictions and other models of joint learning, such as cascading classification. We make the new dataset publicly available, in order to facilitate further research in multi-target stance classification. © 2017 Association for Computational Linguistics.
Keywords: computational linguistics; linguistics; current models; joint learning; multi-targets; neural models; classification (of information)

A coupling for success: controlled growth of Co/CoOx nanoshoots on perovskite mesoporous nanofibres as high-performance trifunctional electrocatalysts in alkaline condition - Hua, Bin; Li, Meng; Sun, Yi-Fei; Zhang, Ya-Qian; Yan, Ning; Chen, Jian; Thundat, Thomas; Li, Jian; Luo, Jing-Li (Nano Energy, 2017)
The high cost and poor durability of noble metal electrocatalysts for bifunctional oxygen catalysis and water splitting have hindered the widespread adoption of many energy storage and conversion technologies. In order for these technologies to be more competitive, advanced electrocatalysts with much higher performance and lower cost are required. The structural and chemical flexibilities of perovskite oxides enable them to be easily modified for diverse catalytic applications. Here we combine three strategies to develop a high-performance trifunctional perovskite electrocatalysts: 1) design a mesoporous fibrous nanostructure; 2) couple a dual functional system; and 3) engineer surface oxygen vacancies. The obtained nanomaterial shows promise to catalyze ORR/OER/HER in alkaline conditions, implying that optimization of the internal/external structure via engineering the defect chemistry of a complex perovskite catalyst would be helpful in advancing its catalytic activity. This protocol discloses an exciting new opportunity to design multifunctional perovskite catalysts for energy storage and conversion.
Keywords: double perovskite; nanoarchitectures; synergetic effects; bifunctional oxygen catalysis; overall water splitting

5 years of ambient pressure photoelectron spectroscopy (APPES) at the Swiss Light Source (SLS) - Olivieri, Giorgia; Giorgi, Javier B.; Green, Richard G.; Brown, Matthew A. (Journal of Electron Spectroscopy and Related Phenomena, 2017)
In March of 2012 an endstation dedicated to ambient pressure photoelectron spectroscopy (APPES) was installed at the Swiss Light Source (SLS) synchrotron radiation facility on the campus of the Paul Scherrer Institute (PSI). The endstation is mobile and operated at the vacuum ultraviolet (VUV), Surfaces/Interfaces: Microscopy (SIM) and Phoenix beamlines, which together afford a nearly continuous photon energy range from 5−8000 eV. This broad energy range is by far the widest available to a single currently operational APPES endstation. During its first five years of operation this endstation has been used to address challenging fundamental problems in the areas of soft-matter colloidal nanoscience, environmental science and energy storage—research that encompasses the liquid-nanoparticle, liquid-vapor (or vacuum) and solid-vapor interfaces. Here we present select highlights of these results and offer an outlook to the next five years of APPES research at the SLS.
Keywords: X-ray photoelectron spectroscopy (XPS); near edge X-ray absorption fine structure (NEXAFS); liquid microjet; in situ spectroscopy; electrical double layer; surface potential

25 TW, two-cycle IR laser pulses via frequency domain optical parametric amplification - Gruson, V.; Ernotte, G.; Lassonde, P.; Laramée, A.; Bionta, M. R.; Chaker, M.; Di mauro, L.; Corkum, P. B.; Ibrahim, H.; Schmidt, B. E.; Legaré, F. (Optics Express, 2017)
Broadband optical parametric amplification in the IR region has reached a new milestone through the use of a non-collinear Frequency domain Optical Parametric Amplification system. We report a laser source delivering 11.6 fs pulses with 30 mJ of energy at a central wavelength of 1.8 μm at 10 Hz repetition rate corresponding to a peak power of 2.5 TW. The peak power scaling is accompanied by a pulse shortening of about 20% upon amplification due to the spectral reshaping with higher gain in the spectral wings. This source paves the way for high flux soft X-ray pulses and IR-driven laser wakefield acceleration.

100-fold improvement in carrier drift mobilities in alkanephosphonate-passivated monocrystalline TiO2 nanowire arrays - Mohammadpour, A.; Wiltshire, B. D.; Zhang, Y.; Farsinezhad, S.; Askar, A. M.; Kisslinger, R.; Ren, Y.; Kar, P.; Shankar, K. (Nanotechnology, 2017)
Single crystal rutile titania nanowires grown by solvothermal synthesis are actively being researched for use as electron transporting scaffolds in perovskite solar cells, in low detection limit ultraviolet photodetectors, in photoelectrochemical water-splitting, and in chemiresistive and electrochemical sensing. The electron drift mobility (μ n ) in solution-grown TiO2 nanowires is very low due to a high density of deep traps, and reduces performance in optoelectronic devices. In this study, the effects of molecular passivation of the nanowire surface by octadecylphosphonic acid (ODPA), on carrier transport in TiO2 nanowire ensembles, were investigated using transient space charge limited current measurements. Infrared spectroscopy indicated the formation of a highly ordered phosphonate monolayer with a high likelihood of bidentate binding of ODPA to the rutile surface. We report the hole drift mobility (μ p ) for the first time in unpassivated solvothermal rutile nanowires to be 8.2 × 10−5 cm2 V−1 s−1 and the use of ODPA passivation resulted in μ p improving by nearly two orders of magnitude to 7.1 × 10−3 cm2 V−1 s−1. Likewise, ODPA passivation produced between a 2 and 3 order of magnitude improvement in μ n from ~10−5–10−6 cm2 V−1 s−1 to ~10−3 cm2 V−1 s−1. The bias dependence of the post-transit photocurrent decays in ODPA-passivated nanowires indicated that minority carriers were lost to trapping and/or monomolecular recombination for small values of bias (<5 V). Bimolecular recombination was indicated to be the dominant recombination mechanism at higher bias values.
Keywords: self-assembled monolayer; inorganic semiconductor nanorods; wide bandgap semiconductor; bottom-up nanofabrication; photoconductivity; carrier dynamics; molecular passivation

Review of modeling and simulation of galvanizing operations - Ajersch, Frank; Ilinca, Florin (Steel Research International, 2017)
Worldwide demand for galvanized steel products continues to grow for the assembly of automobile structures that are lighter and more resistant to impact, as well as for applications in the construction and domestic appliance industries. The technical challenges faced by these producers are the ability to coat a variety of low cost, high strength steels in developing a product with minimal surface defects, and reduced consumption of zinc and energy. The performance of the coating process depends on a thorough understanding of the reactions at the steel surface, the bath chemistry, the temperature variation in the bath, and the fluid dynamics of the coating operation. Operational parameters such as line speed, bath configuration, and immersed hardware all contribute to the variability of the process. Numerical simulations of this process have determined the spatial distribution of temperature and composition of the critical constituents in the zinc bath in transient turbulent flow conditions. This simulation is able to identify the rate of formation and the location of the intermetallic dross particles (dross) within the bath. The generation of dross at the surface of the bath is also simulated experimentally using a mixing system with variable agitation and with air or nitrogen gas streams. Industrial tests carried out to continuously monitor the variation of the temperature and the Al and Fe composition are able to confirm the variations determined by the numerical simulations, validating the use of numerical simulation as an important means of analyzing a complex metallurgical process.
Keywords: flow composition and temperature; galvanizing operations; numerical modeling; validation

Characteristics of volcanic ash in a gas turbine combustor and nozzle guide vanes - Jiang, Leiyong; Han, Yinghua; Patnaik, Prakash (Journal of Engineering for Gas Turbines and Power, 2017)
To understand the physics of volcanic ash impact on gas turbine hot-components and develop much-needed tools for engine design and fleet management, the behaviours of volcanic ash in a gas turbine combustor and nozzle guide vanes (NGV) have been numerically investigated. High-fidelity numerical models are generated, and volcanic ash sample, physical and thermal properties are identified. A simple critical particle viscosity - critical wall temperature model is proposed and implemented in all simulations to account for ash particles bouncing off or sticking on metal walls. The results indicate that due to the particle inertia and combustor geometry, the volcanic ash concentration in the NGV cooling passage increases with ash size, density and inlet velocity in general, and can reach three and half times as high as that at the air inlet for the conditions investigated. More importantly, the majority of the ash particles entering the NGV cooling chamber are trapped in the cooling flow passage for all four turbine inlet temperature conditions. This may reveal another volcanic ash damage mechanism originated from engine cooling flow passage. Finally, some suggestions are recommended for further research and development in this challenging field. To the authors' knowledge, it is the first study on detailed ash behaviours inside practical gas turbine hot-components in open literature.

Ethanol-to-methane activity of Geobacter-deprived anaerobic granules enhanced by conductive microparticles - Dubé, Charles-David; Guiot, Serge R. (Process Biochemistry, 2017)
Direct interspecies electron transfer (DIET) has been typically proposed as mechanism of electron transfer among methanogenic populations in granules during anaerobic digestion where Geobacter species play a key role. Using anaerobic granules where Geobacteraceae members were not prevalent − representing only 0.3% of total bacteria −, tests incubated with two co-substrates showed that the rate of methanogenesis from formate and hydrogen diminished in the presence of a non-methanogenic co-substrate such as ethanol. This could indicate that biological DIET occurs and competes with hydrogen and formate during methanogenesis. Moreover, the addition of conductive microparticles, such as stainless steel and granular activated carbon, was found to increase methanogenic activity in disintegrated granules by 190 ± 18% and 175 ± 22% respectively as compared to disintegrated granules devoid of microparticles. The addition of non-conductive microparticles such as porcelain however decreased methanogenic activity by 65 ± 3% of the disrupted granules without microparticle activity. These results indicate that syntrophic bacteria from anaerobic sludge excluding Geobacter species can also carry out conductive mineral mediated DIET.
Keywords: interspecies electron transfer; DIET; anaerobic granular sludge; ethanol; methane-producing activity; substrate-consuming activity

Camelid single-domain antibodies: historical perspective and future outlook - Arbabi-Ghahroudi, Mehdi (Frontiers in Immunology, 2017)
Tremendous effort has been expended over the past two and a half decades to understand many aspects of camelid heavy chain antibodies, from their biology, evolution, and immunogenetics to their potential applications in various fields of research and medicine. In this article, I present a historical perspective on the development of camelid single-domain antibodies (sdAbs or VHHs, also widely known as nanobodies) since their discovery and discuss the advantages and disadvantages of these unique molecules in various areas of research, industry, and medicine. Commercialization of camelid sdAbs exploded in 2001 with a flurry of patents issued to the Vrije Universiteit Brussel (VUB) and later taken on by the Vlaams Interuniversitair Instituut voor Biotechnologie (VIB) and, after 2002, the VIB-founded spin-off company, Ablynx. While entrepreneurial spirit has certainly catalyzed the exploration of nanobodies as marketable products, IP restrictions may be partially responsible for the relatively long time span between the discovery of these biomolecules and their entry into the pharmaceutical market. It is now anticipated that the first VHH-based antibody drug, Caplacizumab, a bivalent anti-vWF antibody for treating rare blood clotting disorders, may be approved and commercialized in 2018 or shortly thereafter. This elusive first approval, along with the expiry of key patents, may substantially alter the scientific and biomedical landscape surrounding camelid sdAbs and pave the way for their emergence as mainstream biotherapeutics.
Keywords: camelid single-domain antibody; heavy chain antibody; VhH; nanobody; antibody engineering; therapeutic antibody

Blackbox modeling of the central heating and cooling plant equipment performance - Gunay, Burak; Shen, Weiming; Yang, Chunsheng (Science and Technology for the Built Environment, 2017)
This paper presents an analysis conducted upon the sensor data gathered from the distribution control system of a central heating and cooling plant in Ottawa, Canada. After observing that the performance of four boilers and five chillers of this plant vary substantially in time under steady-state conditions, data-driven models were developed to explain this variability from the archived sensor data. By employing a forward stepwise regression and a repeated random sub-sampling cross-validation approach, two-layer feed-forward artificial neural network models with seven to fifteen hidden-nodes were selected for each boiler and chiller. The selected boiler models could explain 84 to 95% of the variability in a boiler's efficiency, and the selected chiller models could explain 65 to 94% of the variability in a chiller's coefficient of performance. Among studied nine variables, the most informative ones to predict a boiler's efficiency were identified as follows: flue gas O2 concentration, pressure, part-load ratio, forced draft fan state, and return water flow rate. Unlike boilers, all four studied variables were found useful in predicting a chiller's coefficient of performance. These four variables were the return water flow rate, part-load ratio, outdoor temperature, and return water temperature. A residual analysis was conducted to verify the appropriateness of the selected models to the datasets. In addition, potential use cases for the selected models were discussed with illustrative examples.
Keywords: blackbox model; central heating and cooling plants; artificial neural network; model selection

Ubisol-Q10 (a nanomicellar water- soluble formulation of CoQ10) treatment inhibits Alzheimer-type behavioral and pathological symptoms in a double transgenic mouse (TgAPEswe, PSEN1dE9) model of Alzheimer’s disease - Muthukumaran, Krithika; Kanwar, Annie; Vegh, Caleb; Marginean, Alexandra; Elliott, Austin; Guilbeault, Nicholas; Badour, Alexander; Sikorska, Marianna; Cohen, Jerome; Pandey, Siyaram; Lanctôt, Krista (Journal of Alzheimer's Disease, 2017)
Alzheimer’s disease (AD) is one of the most common neurodegenerative pathologies for which there are no effective therapies to halt disease progression. Given the increase in the incidence of this disorder, there is an urgent need for pharmacological intervention. Unfortunately, recent clinical trials produced disappointing results. Molecular mechanisms of AD are converging on the notion that mitochondrial dysfunction, oxidative stress, and accumulation of dysfunctional proteins are involved in AD pathology. Previously, we have shown that a water-soluble formulation of Coenzyme Q10 (Ubisol-Q10), an integral part of the electron transport chain, stabilizes mitochondria and prevents neuronal cell death caused by neurotoxins or oxidative stress both in vitro and in vivo. In this study, we evaluated the neuroprotective effects of Ubisol-Q10 treatment in double transgenic AD mice. In the present study, we report that providing Ubisol-Q10 in drinking water (at a dose of ∼6 mg/kg/day) reduced circulating amyloid-β (Aβ) peptide, improved long term memory, preserved working spatial memory, and drastically inhibited Aβ plaque formation in 18-month-old transgenic mice compared to an untreated transgenic group. Thus Ubisol-Q10 supplementation has the potential to inhibit the progression of neurodegeneration, leading to a better quality of life for humans suffering with AD.
Keywords: Alzheimer’s disease; amyloid-β plaques; CoQ10; long term memory; working memory

A novel load flow algorithm for islanded AC/DC hybrid microgrids - Nassar, Mohammed E.; Hamad, Amr A.; Salama, M. M. A.; El-saadany, Ehab F. (IEEE Transactions on Smart Grid, 2017)
This paper proposes a novel branch-based load flow approach for isolated hybrid microgrids. This evolving network configuration involves the application of a distinctive operational philosophy that poses significant challenges with respect to conventional load flow techniques. Hybrid microgrids are characterized by small-rating, droop-based distributed generators (DGs) and by variable but coupled frequency and dc voltage levels. In particular, the absence of a slack bus that results from the small DG rating impedes the application of traditional techniques such as branch-based methods. To overcome these limitations, a modified branch-based approach provided the basis for the development of the proposed algorithm. The new algorithm solves the load flow sequentially by dividing the problem into two coupled ac and dc subproblems. The coupling criterion is established by modeling and updating the power exchange between the subgrids, hence enabling an accurate and efficient formulation of the subproblems. For each subproblem, a modified directed forward-backward sweep has been developed to perform the load flow analysis based on consideration of the individual characteristics of each subgrid. Case study results demonstrate that the algorithm is applicable and effective for the steady-state analysis of several operational factors associated with an isolated hybrid microgrid system: 1) load changing, 2) converter outages, and 3) the probabilistic nature of renewable generation and loads.

Nonperturbative harmonic generation in graphene from intense midinfrared pulsed light - Taucer, M.; Hammond, T. J.; Corkum, P. B.; Vampa, G.; Couture, C.; Thiré, N.; Schmidt, B. E.; Légaré, F.; Selvi, H.; Unsuree, N.; Hamilton, B.; Echtermeyer, T. J.; et al. (Physical Review B, 2017)
In solids, high harmonic radiation arises from the subcycle dynamics of electrons and holes under the action of an intense laser field. The strong-field regime opens new opportunities to understand and control carrier dynamics on ultrafast time scales, including the coherent dynamics of quasiparticles such as massless Dirac fermions. Here, we irradiate monolayer and few-layer graphene with intense infrared light to produce nonperturbative harmonics of the fundamental up to the seventh order. We find that the polarization dependence shows surprising agreement with gas-phase harmonics. Using a two-band model, we explore the nonlinear current due to electrons near the Dirac points, and we discuss the interplay between intraband and interband contributions to the harmonic spectrum. This interplay opens new opportunities to access ultrafast and strong-field physics of graphene.

A comparison of future realizations of the kilogram - Stock, Michael; Barat, Pauline; Pinot, Patrick; Beaudoux, Florian; Espel, Patrick; Piquemal, Francois; Thomas, Matthieu; Ziane, Djamel; Abbott, Patrick; Haddad, Darine; Zubarych, Zeina; Pratt, Jon R.; et al. (Metrologia, 2017)
The definition of the kilogram in the International System of Units (SI) is expected to be revised in 2018. The present definition of the kilogram, the mass of the International Prototype of the Kilogram (IPK), adopted in 1889, would then be replaced by a definition based on a fixed numerical value of the Planck constant. The Consultative Committee for Mass and Related Quantities (CCM) has requested that, as one of the essential steps before the redefinition, a comparison of kilogram realizations based on future realization methods, Kibble balances and X-ray crystal density (XRCD) experiments, be organized. This comparison was carried out during 2016 in the form of a "Pilot Study". One aim of the study was to determine the uniformity of mass dissemination after the redefinition by comparing mass calibrations based on different future realization experiments. Another aim was to test the continuity of the mass unit across the redefinition by comparing mass calibrations based on Kibble balances and XRCD experiments with those based on the IPK. This paper describes the organization of the comparison and presents its results.

Sub-ppt determination of butyltins, methylmercury and inorganic mercury in natural waters by dynamic headspace in-tube extraction and GC-ICPMS detection - Hu, Jing; Pagliano, Enea; Hou, Xiandeng; Zheng, Chengbin; Yang, Lu; Mester, Zoltan (Journal of Analytical Atomic Spectrometry, 2017)
A sensitive and accurate method is developed for the simultaneous ultra-trace determination of tributyltin (TBT), dibutyltin (DBT), monobutyltin (MBT), methylmercury (MeHg) and inorganic mercury (iHg) in waters including seawater by dynamic headspace in-tube extraction (dHS-ITEX) and GC-ICPMS detection. Quantitation of TBT, DBT, iHg and MeHg was achieved by isotope dilution mass spectrometry using 117Sn-enriched TBT and DBT, 201Hg-enriched iHg and enriched Me198Hg (NRC CRM EMMS-1), respectively, wherein analyte mass fractions in enriched spikes were determined by reverse isotope dilution at the same time using natural abundance TBT, DBT, iHg and MeHg primary standards by exactly matching the analyte and enriched spikes. Quantitation of MBT was realized by standard addition calibration with 117Sn-enriched DBT serving as the internal standard. The proposed method achieved detection limits of 0.06, 0.08 and 1.1 pg g−1 (as Sn) for TBT, DBT and MBT and 0.08 and 0.4 pg g−1 (as Hg) for MeHg and iHg, respectively. Validation of the proposed method was demonstrated by quantitative spike recoveries of 94–105% at 5 to 50 pg g−1 levels achieved in drinking water, river water and seawater, demonstrating the accuracy of the method. The obtained detection limits are sufficiently low to perform measurements in support of the Water Framework Directive. The developed method was applied for the determination of butyltins, iHg and MeHg in drinking water (AQUA-1), river water (SLRS-6) and seawater (CASS-6 and NASS-7) samples. Values of 0.124 ± 0.041 and 0.157 ± 0.060 pg g−1 (1SD, n = 4) for MeHg in CASS-6 and NASS-7 and values of 1.74 ± 0.61, 22.15 ± 0.13, and 31.42 ± 0.30 pg g−1 (1SD, n = 4) for iHg in SLRS-6, CASS-6 and NASS-7 were obtained, respectively. A value of 2.27 ± 0.45 pg g−1 as Sn for MBT was detected in NASS-7 seawater, whereas other butyltins were below the detection limits in the waters.

Endosomal trafficking regulates receptor-mediated transcytosis of antibodies across the blood brain barrier - Haqqani, Arsalan S.; Delaney, Christie E.; Brunette, Eric; Baumann, Ewa; Farrington, Graham K.; Sisk, William; Eldredge, John; Ding, Wen; Tremblay, Tammy-Lynn; Stanimirovic, Danica B. (Journal of Cerebral Blood Flow & Metabolism, 2017)
Current methods for examining antibody trafficking are either non-quantitative such as immunocytochemistry or require antibody labeling with tracers. We have developed a multiplexed quantitative method for antibody ‘tracking’ in endosomal compartments of brain endothelial cells. Rat brain endothelial cells were co-incubated with blood-brain barrier (BBB)-crossing FC5, monovalent FC5Fc or bivalent FC5Fc fusion antibodies and control antibodies. Endosomes were separated using sucrose-density gradient ultracentrifugation and analyzed using multiplexed mass spectrometry to simultaneously quantify endosomal markers, receptor-mediated transcytosis (RMT) receptors and the co-incubated antibodies in each fraction. The quantitation showed that markers of early endosomes were enriched in high-density fractions (HDF), whereas markers of late endosomes and lysosomes were enriched in low-density fractions (LDF). RMT receptors, including transferrin receptor, showed a profile similar to that of early endosome markers. The in vitro BBB transcytosis rates of antibodies were directly proportional to their partition into early endosome fractions of brain endothelial cells. Addition of the Fc domain resulted in facilitated antibody ‘redistribution’ from LDF into HDF and additionally into multivesicular bodies (MVB). Sorting of various FC5 antibody formats away from late endosomes and lysosomes and into early endosomes and a subset of MVB results in increased antibody transcytosis at the abluminal side of the BBB.
Keywords: intracellular trafficking; blood–brain barrier; mass spectrometry; selected reaction monitoring

Direct writing of inkjet-printed short channel organic thin film transistors - Chu, Ta-Ya; Zhang, Zhiyi; Dadvand, Afshin; Py, Christophe; Lang, Stephen; Tao, Ye (Organic Electronics, 2017)
A direct-writing fabrication process for fully inkjet-printed short-channel organic thin-film transistors (OTFTs) has been developed. Channels as narrow as 800 nm between two printed Ag electrodes were achieved by printing a special Ag ink on an SU-8 interlayer, which can be partially dissolved by the solvents used in the Ag ink. The ridge formed along the printed Ag line edges due to redistribution of the interlayer material during the drying process limits the ink spread, and separates neighboring printed lines, and is the key to defining an ultra-narrow channel for transistor fabrication. The short-channel OTFTs fabricated using this technique have demonstrated well-defined linear and saturation regimes. An extracted mobility of 0.27 cm2/Vs with an on/off ratio of 105 was obtained at a driving voltage of −12 V. The excellent performance of these devices demonstrates the potential of this technique in fabrication of short-channel devices using standard printing technologies.
Keywords: printed electronics; OTFTs; inkjet

Optical design of infrared pyramid wavefront sensor for the MMT - Veran, Jean-Pierre; Mieda, Etsuko; Hinz, Philip M.; Hardy, Tim; Chen, Shaojie; Sivanandam, Suresh; Liu, Siqi; Lardière, Olivier; Hallibert, Pascal; Hull, Tony B.; Kim, Dae Wook (Astronomical Optics: Design, Manufacture, and Test of Space and Ground Systems, 2017)
We report the optical design of an infrared (0.85-1.8 μm) pyramid wavefront sensor (IRPWFS) that is designed for the 6.5m MMT on telescope adaptive optics system using the latest developments in low-noise infrared avalanche photodiode arrays. The comparison between the pyramid and the double-roof prism based wavefront sensors and the evaluation of their micro pupils’ quality are presented. According to our analysis, the use of two double-roof prisms with achromatic materials produces the competitive performance when compared to the traditional pyramid prism, which is difficult to manufacture. The final micro pupils on the image plane have the residual errors of pupil position, chromatism, and distortion within 1/10 pixel over the 2×2 arcsecond field of view, which meet the original design goals.
Keywords: wavefront measurement; pyramid wavefront sensor; pupil imaging; adaptive optics

Investigating the candidacy of the serotype specific rhamnan polysaccharide based glycoconjugates to prevent disease caused by the dental pathogen Streptococcus mutans - St. Michael, Frank; Yang, Qingling; Cairns, Chantelle; Vinogradov, Evgeny; Fleming, Perry; Hayes, Alexander C.; Aubry, Annie; Cox, Andrew D. (Glycoconjugate Journal, 2017)
Dental caries remains a major health issue and the Gram-positive bacterium Streptococcus mutans is considered as the major pathogen causing caries. More recently, S. mutans has been recognised as a cause of endocarditis, ulcerative colitis and fatty acid liver disease along with the likelihood of increased cerebral hemorrhage following a stroke if S. mutans is present systemically. We initiated this study to examine the vaccine candidacy of the serotype specific polysaccharides elaborated by S. mutans. We have confirmed the carbohydrate structures for the serotype specific rhamnan containing polysaccharides from serotypes c, f and k. We have prepared glycoconjugate vaccines using the rhamnan containing polymers from serotypes f and k and immunised mice and rabbits. We consistently obtained a robust immune response to the glycoconjugates with cross-reactivity consistent with the structural similarities of the polymers from the different serotypes. We developed an opsonophagocytic assay which illustrated the ability of the post-immune sera to facilitate opsonophagocytic killing of the homologous and heterologous serotypes at titers consistent with the structural homologies. We conclude that glycoconjugates of the rhamnan polymers of S. mutans are a potential vaccine candidate to target dental caries and other sequelae following the escape of S. mutans from the oral cavity.
Keywords: Streptococcus mutans; conjugate vaccine; serotype polysaccharide; rhamnan

Binding pose and affinity prediction in the 2016 D3R Grand Challenge 2 using the Wilma-SIE method - Hogues, Hervé; Sulea, Traian; Gaudreault, Francis; Corbeil, Christopher R.; Purisima, Enrico O. (Journal of Computer-Aided Molecular Design, 2017)
The Farnesoid X receptor (FXR) exhibits significant backbone movement in response to the binding of various ligands and can be a challenge for pose prediction algorithms. As part of the D3R Grand Challenge 2, we tested Wilma-SIE, a rigid-protein docking method, on a set of 36 FXR ligands for which the crystal structures had originally been blinded. These ligands covered several classes of compounds. To overcome the rigid protein limitations of the method, we used an ensemble of publicly available structures for FXR from the PDB. The use of the ensemble allowed Wilma-SIE to predict poses with average and median RMSDs of 2.3 and 1.4 Å, respectively. It was quite clear, however, that had we used a single structure for the receptor the success rate would have been much lower. The most successful predictions were obtained on chemical classes for which one or more crystal structures of the receptor bound to a molecule of the same class was available. In the absence of a crystal structure for the class, observing a consensus binding mode for the ligands of the class using one or more receptor structures of other classes seemed to be indicative of a reasonable pose prediction. Affinity prediction proved to be more challenging with generally poor correlation with experimental IC50s (Kendall tau ~ 0.3). Even when the 36 crystal structures were used the accuracy of the predicted affinities was not appreciably improved. A possible cause of difficulty is the internal energy strain arising from conformational differences in the receptor across complexes, which may need to be properly estimated and incorporated into the SIE scoring function.
Keywords: protein-ligand docking; protein flexibility; SIE; Wilma

Through-the-coating femtosecond laser inscription of very short fiber Bragg gratings for acoustic and high temperature sensing applications - Hnatovsky, Cyril; Grobnic, Dan; Mihailov, Stephen J. (Optics Express, 2017)
Very short Type I and Type II Bragg gratings, on the order of 100 µm in length, are written through the protective polyimide coating of high NA and standard single mode silica optical fibers with infrared femtosecond pulses and a phase mask. By exploiting the transverse walk-off of apertured diffracted beams produced by the phase mask and a slit placed proximate the mask, complex grating structures are fabricated and characterized. These gratings are suitable for structural health monitoring based on acoustic measurements or localized high-temperature measurements.

McDiarmid drift detection methods for evolving data streams - Pesaranghader, Ali; Viktor, Herna; Paquet, Eric (Statistics, 2017)
Increasingly, Internet of Things (IoT) domains, such as sensor networks, smart cities, and social networks, generate vast amounts of data. Such data are not only unbounded and rapidly evolving. Rather, the content thereof dynamically evolves over time, often in unforeseen ways. These variations are due to so-called concept drifts, caused by changes in the underlying data generation mechanisms. In a classification setting, concept drift causes the previously learned models to become inaccurate, unsafe and even unusable. Accordingly, concept drifts need to be detected, and handled, as soon as possible. In medical applications and military zones, for example, change in behaviors should be detected in near real-time, to avoid potential loss of life. To this end, we introduce the McDiarmid Drift Detection Method (MDDM), which utilizes McDiarmid's inequality in order to detect concept drift. The MDDM approach proceeds by sliding a window over prediction results, and associate window entries with weights. Higher weights are assigned to the most recent entries, in order to emphasize their importance. As instances are processed, the detection algorithm compares a weighted mean of elements inside the sliding window with the maximum weighted mean observed so far. A significant difference between the two weighted means, upper-bounded by the McDiarmid inequality, implies a concept drift. Our extensive experimentation against synthetic and real-world data streams show that our novel method outperforms the state-of-the-art. Specifically, MDDM yields shorter detection delays as well as lower false negative rates, while maintaining high classification accuracies.

Quantum frequency conversion with ultra-broadband tuning in a Raman memory - Bustard, Philip J.; England, Duncan G.; Heshami, Khabat; Kupchak, Connor; Sussman, Benjamin J. (Physical Review A, 2017)
Quantum frequency conversion is a powerful tool for the construction of hybrid quantum photonic technologies. Raman quantum memories are a promising method of conversion due to their broad bandwidths. Here we demonstrate frequency conversion of THz-bandwidth, fs-duration photons at the single-photon level using a Raman quantum memory based on the rotational levels of hydrogen molecules. We shift photons from 765 nm to wavelengths spanning from 673 to 590 nm—an absolute shift of up to 116 THz. We measure total conversion efficiencies of up to 10% and a maximum signal-to-noise ratio of 4.0(1):1, giving an expected conditional fidelity of 0.75, which exceeds the classical threshold of 2/3. Thermal noise could be eliminated by cooling with liquid nitrogen, giving noiseless conversion with wide tunability in the visible and infrared.

Time-bin-to-polarization conversion of ultrafast photonic qubits - Kupchak, Connor; Bustard, Philip J.; Heshami, Khabat; Erskine, Jennifer; Spanner, Michael; England, Duncan G.; Sussman, Benjamin J. (Physical Review A, 2017)
The encoding of quantum information in photonic time-bin qubits is apt for long-distance quantum communication schemes. In practice, due to technical constraints such as detector response time, or the speed with which copolarized time-bins can be switched, other encodings, e.g., polarization, are often preferred for operations like state detection. Here, we present the conversion of qubits between polarization and time-bin encodings by using a method that is based on an ultrafast optical Kerr shutter and attain efficiencies of 97% and an average fidelity of 0.827±0.003 with shutter speeds near 1 ps. Our demonstration delineates an essential requirement for the development of hybrid and high-rate optical quantum networks.

An experimental and numerical study on diesel injection split of a natural gas/diesel dual-fuel engine at a low engine load - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid (Fuel, 2017)
Natural gas/diesel dual-fuel combustion is currently one of the most promising LTC strategies for the next generation of heavy-duty engines. While this concept is not new and it has been deliberated lengthily in the past two decades, several uncertainties still exist. A major shortcoming of this concept is associated with its low thermal efficiency and high level of unburned methane and CO emissions under low engine load conditions. The present paper reports an experimental and numerical study on the effect of different injection strategies (single and two pulses injection of pilot diesel fuel) on the combustion performance and emissions of a heavy duty natural gas/diesel dual-fuel engine at 25% engine load. The results of single diesel injection mode showed that advancing diesel injection timing from 10 to 30°BTDC reduced unburned methane and CO emissions by 62% and 61% and increased thermal efficiency by 6%; however, NOx emissions increased by 74%. In order to achieve NOx – CH4 and NOx – CO trade-off and increased thermal efficiency at low load conditions, the effect of split injection strategy was experimentally and numerically examined. The results of split injection mode revealed that split injection strategy considerably increases the in-cylinder peak pressure compared to that of single injection (10°BTDC). The results showed also that the heat release produced by the first injection of diesel fuel considerably increased the in-cylinder charge temperature before the start of the second injection. The flame zone of the split injection mode is markedly higher than that of the single injection due to larger heat release produced during the first injection which promotes the combustion of the second one. When the first injection timing is close to the second injection timing, the MPRR of split injection mode is higher than that of single injection (10 °BTDC). However, further advancing of the first injection timing continuously decreased the MPRR. OH radical analysis showed that for advanced first injection timings (38–50 °BTDC), the overall growth rate of OH radical becomes slower and its distribution is narrower as indicated by the wider non-reactive blue zones compared with those observed at a late first injection timing in the initial stages of combustion. However, OH radicals gradually grow during last stages of combustion in the expansion stroke, indicating that a more premixed combustion takes place in these cases. For very advanced first injection timing of 55 °BTDC, the OH distribution is similar to that of the single injection mode with lower OH intensity at initial stages of combustion and they barely grow during the late expansion stroke. At this condition, the ignition of premixed mixture is mainly controlled by the second diesel fuel injection. The trade-off between NOx – CH4 and NOx – CO is achieved when applying split injection. Compared to single injection (10 °BTDC), the first injection timing of 50 °BTDC decreased unburned methane and CO emissions by 60% and 63%, respectively, and increased the thermal efficiency by 8.9%. However, NOx emissions were maintained at the same level as single injection mode (10°BTDC).
Keywords: dual-fuel combustion; conventional single diesel injection timing; split injection mode

Three-dimensional numerical simulation of ice accretion using a discrete morphogenetic approach - Szilder, Krzysztof; Lozowski, Edward P. (9th AIAA Atmospheric and Space Environments Conference, 2017)
NRC has developed an original, three-dimensional icing modelling capability, called the “morphogenetic” approach, based on a discrete formulation and simulation of ice formation physics. Morphogenetic icing modelling improves on existing ice accretion models in that it is capable of predicting simultaneous rime and glaze ice accretions and ice accretions with variable density and complex geometries. To partially validate the model, we have performed laboratory experiments of ice accretions on a NACA0012 swept wing in the NRC Altitude Icing Wind Tunnel (AIWT). Ice shapes were recorded and analysed for 30° and 45° sweep angles and for a range of airflow and icing conditions. The swept wing configuration was chosen because it is the most challenging case for all numerical predictive models. The objective of this paper is to compare model and experimental ice predictions on a swept wing, including complex three-dimensional features such as lobster tails. The results show that the morphogenetic approach can produce realistic simulations of both the overall size/shape and the detailed structure of the ice accretions forming on a swept wing. As far as we know, no other numerical icing model can simulate such three-dimensional ice structure complexity.

Neurovascular unit: basic and clinical imaging with emphasis on advantages of ferumoxytol - Netto, Joao Prola; Iliff, Jeffrey; Stanimirovic, Danica; Krohn, Kenneth A.; Hamilton, Bronwyn; Varallyay, Csanad; Gahramanov, Seymur; Daldrup-Link, Heike; D’esterre, Christopher; Zlokovic, Berislav; Sair, Haris; Lee, Yueh; et al. (Neurosurgery, 2017)
Physiological and pathological processes that increase or decrease the central nervous system's need for nutrients and oxygen via changes in local blood supply act primarily at the level of the neurovascular unit (NVU). The NVU consists of endothelial cells, associated blood-brain barrier tight junctions, basal lamina, pericytes, and parenchymal cells, including astrocytes, neurons, and interneurons. Knowledge of the NVU is essential for interpretation of central nervous system physiology and pathology as revealed by conventional and advanced imaging techniques. This article reviews current strategies for interrogating the NVU, focusing on vascular permeability, blood volume, and functional imaging, as assessed by ferumoxytol an iron oxide nanoparticle.
Keywords: blood-brain barrier; imaging; neurovascular unit

An experimental and numerical study of the effect of diesel injection timing on natural gas/diesel dual-fuel combustion at low load - Yousefi, Amin; Birouk, Madjid; Guo, Hongsheng (Fuel, 2017)
Natural gas/diesel dual-fuel combustion compression ignition engine has the potential to reduce NOx and soot emissions. However, this combustion mode still suffers from low thermal efficiency and high level of unburned methane and CO emissions at low load conditions. The present paper reports the results of an experimental and numerical study on the effect of diesel injection timings (ranging from 10 to 50 °BTDC) on the combustion performance and emissions of a heavy duty natural gas/diesel dual-fuel engine at 25% engine load. Both experimental and numerical results revealed that advancing the injection timing up to 30 °BTDC increases the maximum in-cylinder pressure. However, with further advancing the injection timing up to 50 °BTDC, the maximum in-cylinder pressure decreases which is mainly due to the lower in-cylinder temperature before SOC. Moreover, the analysis of OH spatial distribution shows that, at very advanced diesel injection timings, the non-reactive zones are much narrower than later injection timings during the last stages of combustion, indicating a more predominant premixed combustion mode. At retarded diesel injection timings, the consumption of premixed fuel in the outer part of the charge is likely to be a significant challenge for dual-fuel combustion engine at low engine load conditions. However, with advancing the diesel injection timing, the OH radical becomes more uniform throughout the combustion chamber, which confirms that high temperature combustion reactions can occur in the central part of the charge. Diesel injection timing of 30 °BTDC appears to be the conversion point of all conventional dual-fuel combustion modes. Further advancing diesel injection timing beyond this point (30 °BTDC) results in noticeable reduction in NOx and unburned methane emissions, while CO emissions exhibit only slight drop. However, at very advanced diesel injection timings of 46 and 50 °BTDC, NOx and unburned methane emissions continue to drop, whereas CO emissions tend to increase. The results showed also that the highest indicated thermal efficiency is achieved at these very advanced diesel injection timings of 46 and 50 °BTDC. Finally, the results revealed that, by advancing diesel injection timing from 10 °BTDC to 50 °BTDC, NOx, unburned methane, and CO emissions are reduced, respectively, by 65.8%, 83%, and 60% while thermal efficiency is increased by 7.5%.
Keywords: natural gas; dual-fuel combustion; low engine load; diesel injection timing

An experimental and numerical study of natural gas/diesel dual-fuel engine at low load: effect of diesel fuel injection timing - Yousefi, Amin; Birouk, Madjid; Guo, Hongsheng (Proceedings of Combustion Institute, McGill University, May 15-18, 2017, 2017)
One of the most promising alternative combustion strategies is natural gas/diesel dual-fuel combustion. It consists of preparing a premixed mixture of a gaseous fuel and air, whose ignition is triggered by the injection of a small amount of more ignitable fuel, usually diesel fuel. However, this combustion mode still suffers from low thermal efficiency and high level of unburned methane and CO emissions at low load conditions. The present paper reports the results of an experimental and numerical study on the effect of diesel injection timings (10 to 50 °BTDC) on the combustion performance and emissions of dual-fuel combustion at 25% engine load. Analysis of OH spatial distribution shows that, at very advanced diesel injection timings, the non-reactive mixture zones are much lower in OH concentration than other injection timings during the last stages of combustion, indicating a more predominant premixed combustion mode. At retarded diesel injection timings, the consumption of premixed fuel in the outer part of the charge is likely to be a significant challenge for dual-fuel combustion engine at low load conditions. However, with advancing the diesel injection timing, the OH radical becomes more uniform throughout the combustion chamber which confirms that high temperature combustion reactions can occur in the central part of the charge. NOx, unburned methane, and CO emissions are reduced while at the same time the highest indicated thermal efficiency is achieved at very advanced diesel injection timings of 46 and 50°BTDC.

An image-based trajectory planning approach for robust robot programming by demonstration - Vakanski, Aleksandar; Janabi-sharifi, Farrokh; Mantegh, Iraj (Robotics and Autonomous Systems, 2017)
The article proposes a new robot programming-by-demonstration framework, which integrates a visual servoing tracking control to robustly follow a trajectory generated from observed demonstrations. The constraints originating from the use of a visual servoing controller are incorporated into the trajectory learning phase, to guarantee feasibility of the generated plan for task execution. The observational learning is solved as a constrained optimization problem, with an objective to generalize from a set of trajectories of salient features in the image space of a vision camera. The proposed approach is evaluated experimentally for learning trajectories acquired from kinesthetic demonstrations.
Keywords: cognitive robotics; visual servoing; programming by demonstration

Connected and distributed sensing in buildings: improving operation and maintenance - Gunay, Burak; Shen, Weiming (IEEE Systems Man and Cybernetics Magazine, 2017)
The Internet of Things (IoT) is the vision of achieving interconnectivity in physical devices. This aspiration has started to translate into the buildings sector. Modern buildings are increasingly equipped with a wide array of sensors. Numerous wall thermostats, both for the commercial and residential sectors, go beyond temperature sensing and can measure indoor humidity, occupancy, carbon dioxide (CO2) concentration, and light intensity. Examples from recent literature indicate that new buildings are equipped with more than 200 sensors and 100 actuators per 1,000 m2of floor space. Distributed and connected sensing represents an untapped opportunity for us to optimize the operation of buildings by reducing energy use and operation costs and improving occupant comfort, health, and productivity.

The linewidth broadening factor: a length-scale-dependent analytical approach - Benhsaien, Abdessamad; Lu, Zhenguo; Hinzer, Karin; Hall, Trevor James (American Journal of Nano Research and Applications, 2017)
A first-order frequency-dependent formula of the linewidth broadening factor (α–factor) is derived in terms of scattering rates whilst, a mesoscopic disk approach is used in order to accompany the dimension effect to the spontaneous emission lifetime (inverse of scattering rate). An excitonic correction to the relaxation properties is shown to occur provided the binding energy of the electron and hole is comparable to their eigenenergy-separation. The ensuing analysis is independent of the selected III-V material system and resides upon three simplifying assumptions which allow for analytical formulae to be derived.
Keywords: α–factor; linewidth; enhancement; scattering; spontaneous emission; exciton; mesoscopic; quantum dot

Wastewater treatment and online chemical oxygen demand estimation in a cascade of microbial fuel cells - Recio-Garrido, Didac; Adekunle, Ademola; Perrier, Michel; Raghavan, Vijaya; Tartakovsky, Boris (Industrial & Engineering Chemistry Research, 2017)
This study demonstrates degradation of synthetic wastewater in two MFCs hydraulically connected in series. To maximize chemical oxygen demand (COD) removal, external resistance of each MFC is optimized using a perturbation–observation maximum power point algorithm. Under optimal operating conditions a removal efficiency over 90% is achieved at an influent acetate concentration of 750 mg L–1 and organic loading rates ranging from 0.75 to 3.0 g L–1 day–1. Furthermore, regression analysis is used to correlate current and power output of each MFC with the analytically measured COD concentrations, thus providing a means for online COD estimations. The accuracy of online COD estimations is further improved by developing a model-based soft-sensor.

Ability of anaerobic granules for metal-mediated direct interspecies electron transfer - Dubé, Charles-David; Guiot, Serge R. (1st International Congress on Metals in Anaerobic Biotechnologies (IMAB17): Book of Abstracts, 2017)
Keywords: anaerobic granular sludge; interspecies electron transfer; bioactivity; conductive particles

A high-fidelity energy efficient path planner for unmanned airships - Recoskie, Steven; Lanteigne, Eric; Gueaieb, Wail (Robotics, 2017)
This paper presents a comparative study on the effects of grid resolution, vehicle velocity, and wind vector fields on the trajectory planning of unmanned airships. A wavefront expansion trajectory planner that minimizes a multi-objective cost function consisting of flight time, energy consumption, and collision avoidance while respecting the differential constraints of the vehicle is presented. Trajectories are generated using a variety of test environments and flight conditions to demonstrate that the inclusion of a high terrain map resolution, a temporal vehicle velocity, and a spatial wind vector field yields significant improvements in trajectory feasibility and energy economy when compared to trajectories generated using only two of these three elements.
Keywords: path planning; unmanned airship; wavefront expansion

The influence of hydrogen enrichment on the topology of a lean, methane/air turbulent V-flame - Vena, P.; Guo, H.; Galizzi, C.; Kühni, M.; Escudié, D. (Digital Proceedings of 8th European Combustion Meeting, 2017)
The influence of hydrogen enrichment on the topology of lean CH4-H2/air turbulent V-flames was considered. Three equivalence ratios with different levels of hydrogen enrichment were studied for variations in flame topology. The turbulent flame speed and turbulent flame brush thickness both increased with hydrogen enrichment for all flame considered. Flame surface density profiles showed a progressive shift towards the products and curvature PDFs showed a bias towards positive curvatures. Observed trends were attributed to the changes in thermo-diffusive stability of the reactants as Lewis numbers decreased with hydrogen volume fraction.

Heavy and light hole minority carrier transport properties in low-doped n-InGaAs lattice matched to InP - Walker, Alexandre W.; Denhoff, Mike W. (Applied Physics Letters, 2017)
Minority carrier diffusion lengths in low-doped n-InGaAs using InP/InGaAs double-heterostructures are reported using a simple electrical technique. The contributions from heavy and light holes are also extracted using this methodology, including minority carrier mobilities and lifetimes. Heavy holes are shown to initially dominate the transport due to their higher valence band density of states, but at large diffusion distances, the light holes begin to dominate due to their larger diffusion length. It is found that heavy holes have a diffusion length of 54.5 ± 0.6 μm for an n-InGaAs doping of 8.4 × 1015 cm–3 at room temperature, whereas light holes have a diffusion length in excess of 140 μm. Heavy holes demonstrate a mobility of 692 ± 63 cm2/Vs and a lifetime of 1.7 ± 0.2 μs, whereas light holes demonstrate a mobility of 6200 ± 960 cm–2/Vs and a slightly longer lifetime of 2.6 ± 1.0 μs. The presented method, which is limited to low injection conditions, is capable of accurately resolving minority carrier transport properties.

Analysis and modelling of surface Urban Heat Island in 20 Canadian cities under climate and land-cover change - Gaur, Abhishek; Eichenbaum, Markus Kalev; Simonovic, Slobodan P. (Journal of Environmental Management, 2017)
Surface Urban Heat Island (SUHI) is an urban climate phenomenon that is expected to respond to future climate and land-use land-cover change. It is important to further our understanding of physical mechanisms that govern SUHI phenomenon to enhance our ability to model future SUHI characteristics under changing geophysical conditions. In this study, SUHI phenomenon is quantified and modelled at 20 cities distributed across Canada. By analyzing MODerate Resolution Imaging Spectroradiometer (MODIS) sensed surface temperature at the cities over 2002–2012, it is found that 16 out of 20 selected cities have experienced a positive SUHI phenomenon while 4 cities located in the prairies region and high elevation locations have experienced a negative SUHI phenomenon in the past. A statistically significant relationship between observed SUHI magnitude and city elevation is also recorded over the observational period. A Physical Scaling downscaling model is then validated and used to downscale future surface temperature projections from 3 GCMs and 2 extreme Representative Concentration Pathways in the urban and rural areas of the cities. Future changes in SUHI magnitudes between historical (2006–2015) and future timelines: 2030s (2026–2035), 2050s (2046–2055), and 2090s (2091–2100) are estimated. Analysis of future projected changes indicate that 15 (13) out of 20 cities can be expected to experience increases in SUHI magnitudes in future under RCP 2.6 (RCP 8.5). A statistically significant relationship between projected future SUHI change and current size of the cities is also obtained. The study highlights the role of city properties (i.e. its size, elevation, and surrounding land-cover) towards shaping their current and future SUHI characteristics. The results from this analysis will help decision-makers to manage Canadian cities more efficiently under rapidly changing geophysical and demographical conditions.
Keywords: Urban Heat Island; Canada; elevation; city-size; SP model

Preclinical assessment of KAL-ABP target engagement and efficacy using pet, MRI and CSF biomarkers - Kang, Min Su; Shin, Monica; Collins, Louis; Massarweh, Gassan; Soucy, Jean-Paul; Brown, Leslie; Delaney, Christie; Pelletier, Alex; Haqqani, Arsalan; Durocher, Yves; Rennie, Kerry; Stanimirovic, Danica; et al. (Alzheimer's & Dementia, 2017)
We report preclinical study results of a novel anti-amyloid agent (KAL-ABP). KAL-ABP includes an Aβ oligomer binding protein (ABP) fused to “carrier” module that allows the delivery of the active compound through the blood-brain barrier (KAL-ABP-BBB). KAL-ABP has been reported to selectively bind Aβ1-42 oligomer in vitro and ex vivo and prevent its toxicity. Here, using in vivo longitudinal biomarker acquisitions and McGill-R-Thy1-APP transgenic rat model (Tg), we further replicate and extend these results by quantifying KAL-ABP-BBB cerebrospinal fluid concentrations; target engagement via changes in amyloid load with [18F]NAV4694 positron emission tomography scans (NAV-PET); therapeutic efficacy via changes in hippocampal volumetry (MRI-HV) and vasculature. A total of 17 rats (wild type (WT-ABP), N=4; Tg-ABP, N=9; Tg-SAL, N=4). They had an initial dose of either KAL-ABP-BBB 30mg/Kg/IV followed by 15mg/Kg/IV/week, or placebo on the subsequent 4 weeks. 60-minute NAV-PET dynamic scan was acquired concomitantly with a bolus tail vein injection of the radiotracer after a 9-minute transmission scan. The images were reconstructed using Maximum a posteriori algorithm with scatter, dead time, and decay correction. Non-displaceable binding potential (BPND) was generated using cerebellar grey matter as a reference region based on simplified reference tissue model (SRTM). 60-minute scan via Fast Imaging with Steady-state Precession sequence with TE/TR of 2.5/5.0ms was used to generate structural images. Then, MRI-HV (mm3) was acquired via manual segmentation. Susceptibility MRI were acquired using echo planar acquisitions for vasculature. For image processing and statistical analysis, MINC tools, VoxelStats, R, and Prism7 were used. Linear Mixed effect regression model (corrected by sex, age, weight) and simple t-test were used to estimate the target engagement and therapeutic efficacy, respectively. KAL-ABP-BBB reached CSF concentrations of 300 ng/mL. KAL-ABP-BBB intervention reduced global [18F]NAV4694 BPND(27%; p=0.0442) and rectified baseline genotype observation (Tg vs Wt; p=0.0087). KAL-ABP-BBB intervention increased MRI-HV (8%; p=0.0099). No vascular abnormality was observed during KAL-ABP-BBB intervention. This study provides strong evidence that KAL-ABP-BBB crosses the BBB, safely lowers the amyloid burden and mitigates hippocampal atrophy in vivo. Overall, these results invite further clinical study in humans.

Structural and biochemical investigation of PglF from Campylobacter jejuni reveals a new mechanism for a member of the short chain dehydrogenase/reductase superfamily - Riegert, Alexander S.; Thoden, James B.; Schoenhofen, Ian C.; Watson, David C.; Young, N. Martin; Tipton, Peter A.; Holden, Hazel M. (Biochemistry, 2017)
Within recent years it has become apparent that protein glycosylation is not limited to eukaryotes. Indeed, in Campylobacter jejuni, a Gram-negative bacterium, more than 60 of its proteins are known to be glycosylated. One of the sugars found in such glycosylated proteins is 2,4-diacetamido-2,4,6-trideoxy-α-d-glucopyranose, hereafter referred to as QuiNAc4NAc. The pathway for its biosynthesis, initiating with UDP-GlcNAc, requires three enzymes referred to as PglF, PglE, and PlgD. The focus of this investigation is on PglF, an NAD+-dependent sugar 4,6-dehydratase known to belong to the short chain dehydrogenase/reductase (SDR) superfamily. Specifically, PglF catalyzes the first step in the pathway, namely, the dehydration of UDP-GlcNAc to UDP-2-acetamido-2,6-dideoxy-α-d-xylo-hexos-4-ulose. Most members of the SDR superfamily contain a characteristic signature sequence of YXXXK where the conserved tyrosine functions as a catalytic acid or a base. Strikingly, in PglF, this residue is a methionine. Here we describe a detailed structural and functional investigation of PglF from C. jejuni. For this investigation five X-ray structures were determined to resolutions of 2.0 Å or better. In addition, kinetic analyses of the wild-type and site-directed variants were performed. On the basis of the data reported herein, a new catalytic mechanism for a SDR superfamily member is proposed that does not require the typically conserved tyrosine residue.

A conserved DGGK motif is essential for the function of the PglB oligosaccharyltransferase from Campylobacter jejuni - Barre, Yasmin; Nothaft, Harald; Thomas, Cody; Liu, Xin; Li, Jianjun; Ng, Kenneth K. S.; Szymanski, Christine M. (Glycobiology, 2017)
In Campylobacter jejuni, the PglB oligosaccharyltransferase catalyzes the transfer of a heptasaccharide from a lipid donor to asparagine within the D/E-X1-N–X2-S/T sequon (X1,2 ≠ P) or releases this heptasaccharide as free oligosaccharides (fOS). Using available crystal structures and sequence alignments, we identified a DGGK motif near the active site of PglB that is conserved among all Campylobacter species. We demonstrate that amino acid substitutions in the aspartate and lysine residues result in loss of protein glycosylation in the heterologous Escherichia coli system. Similarly, complementation of a C. jejuni pglB knock-out strain with mutated pglB alleles results in reduced levels of N-linked glycoproteins and fOS in the native host. Analysis of the PglB crystal structures from Campylobacter lari and the soluble C-terminal domain from C. jejuni suggests a particularly important structural role for the aspartate residue and the two following glycine residues, as well as a more subtle, less defined role for the lysine residue. Limited proteolysis experiments indicate that conformational changes of wildtype PglB that are induced by the binding of the lipid-linked oligosaccharide are altered by changes in the DGGK motif. Related to these findings, certain Campylobacter species possess two PglB orthologues and we demonstrate that only the orthologue containing the DGGK motif is active. Combining the knowledge gained from the PglB structures and mutagenesis studies, we propose a function for the DGGK motif in affecting the binding of the undecaprenyl-pyrophosphate glycan donor substrate that subsequently influences N-glycan and fOS production.
Keywords: Campylobacter jejuni; lipid-linked oligosaccharide; N-linked protein glycosylation; oligosaccharyltransferase; PglB

Small composite field correction factors for the CyberKnife radiosurgery system: clinical and PCSR plans - Christiansen, Eric Jessie; Muir, Bryan Richard; Belec, Jason; Vandervoort, Eric J. (Physics in Medicine and Biology, 2017)

Development and validation of a biofidelic head form model to assess blast-induced traumatic brain injury - Downes, Devon; Bouamoul, Amal; Ouellet, Simon; Nejad ensan, Manouchehr (The Journal of Defense Modeling and Simulation: Applications, Methodology, Technology, 2017)
Traumatic Blast Injury (TBI) associated with the human head is caused by exposure to a blast loading, resulting in decreased level of consciousness, skull fracture, lesions, or death. This paper presents the simulation of blast loading of a human head form from a free-field blast with the end goal of providing insight into how TBI develops in the human head. The developed numerical model contains all the major components of the human head, the skull, and brain, including the tentorium, cerebral falx, and gray and white matter. A nonlinear finite element analysis was employed to perform the simulation using the Arbitrary Lagrangian–Eulerian finite element method. The simulation captures the propagation of the blast wave through the air, its interaction with the skull, and its transition into the brain matter. The model quantifies the pressure histories of the blast wave from the explosive source to the overpressure on the skull and the intracranial pressure. This paper discusses the technical approach used to model the head, the outcome from the analysis, and the implication of the results on brain injury.

Investigation of a parallel active vibration isolation mount for mitigating N/Rev helicopter vibrations - Fereidooni, Amin; Graham, Silas; Chen, Eric; Wickramasinghe, Viresh K. (25th AIAA/AHS Adaptive Structures Conference, 2017)
This paper presents an active isolation mount using a flexible passive support in parallel with a voice coil actuator. This active mount is designed to reduce the N/rev harmonic vibration of a helicopter at the local seat structure. The active mount is tested in a simple single degree of freedom mechanical system to reduce vibration at a payload mass representative of a 95th percentile pilot. The system is tested experimentally and also modeled in Simulink®. The results from the experiment are compared to those obtained numerically. The active mount was shown to be effective by reducing vibration representative of a Bell-412 helicopter by 11.96 dB (74.77 %).

Test rig development and characterization of magnetorheological elastomers - Martins, Afonso; Fereidooni, Amin; Suleman, Afzal; Wickramasinghe, Viresh K. (25th AIAA/AHS Adaptive Structures Conference, 2017)
In this paper the mechanical properties of commercial magnetorheological elastomer samples are experimentally characterized using compression and shear test rigs developed in-house. The test rigs are designed to provide a continuous magnetic field to the samples during dynamic testing. The magnetic field imposed on the samples is measured in real-time using a Hall effect sensor. In the experimental tests, the magnetorheological elastomer specimens are subjected to cyclic loading at various frequencies and magnetic field strengths. The results show an increase in stiffness and damping as the magnetic field increases.

Brain delivery of an amyloid-β oligomer (AβO)-targeting peptide-therapeutic by a novel blood-brain barrier (BBB)-crossing domain antibody - Chakravarthy, Balu; Atkinson, Trevor; Brown, Leslie; Menard, Michel; Brunette, Eric; Pelletier, Alex; Jiang, Susan; Baumann, Ewa; Ball, Marguerite; Delaney, Christie; Ding, Wen; Star, Alexandra; et al. (Alzheimer's & Dementia, 2017)
We have identified an amyloid-ß (Aß) binding peptide (ABP) that selectively bound pathological Aß1-42 oligomers and reduced Aß- mediated cell toxicity1. ABP also bound Aß deposits in brains of AD transgenic mice and Alzheimer’s disease (AD) patients in vitro, and when directly injected into live transgenic mice (APPSwe and ΔPS1) brain2, suggesting that, when delivered to the brain, ABP can engage Aß and facilitate its clearance. Present study shows brain-delivery of ABP by a novel BBB-crossing domain antibody, and targeting and clearance of Aß in transgenic mice. Recombinant ABP-BBB carrier fusion construct (ABP-BBB) were produced in CHO cells. BBB-permeability of the construct was assessed using in vitro BBB (formed by rat or human brain endothelial cells) and in vivo (rat and mouse) models. Aß binding was determined by ELISA and Western blot overlay assays. For PK/PD studies, serum, CSF and brain levels of ABP-BBB construct and Aß were assessed following iv injection by nanoLC- MRM, ELISA and Western blot methods. ABP-BBB bi-functional fusion protein was successfully expressed in CHO cells. The fusion protein retained both Aß-oligomer binding activity and BBB-permeability in vitro. ABP-BBB transmigrated the in vitro BBB, in contrast to ABP without BBB carrier. When injected iv into rats, ABP-BBB appeared in the CSF in a dose- and time-dependent manner indicating transport of ABP across BBB in vivo. Apparent CNS exposure (Expapp), calculated as CSF[AUC]/serum[AUC], indicated a 15-20-fold increase in Expapp for ABP-BBB compared to non-BBB permeable ABP. This was further confirmed in mouse model wherein following iv injection, the fusion protein was detected in the CSF, and cortical and hippocampal regions of wild type and Tg mice. More importantly, in Tg mice ABP treatment resulted in a significant (∼50%) reduction of Aß levels in the CSF, and brain cortex and hippocampus within 4-weeks.

Hygrothermal performance assessment of stucco-clad wood frame walls having vented and ventilated drainage cavities - Saber, Hamed H.; Lacasse, Michael A.; Moore, Travis V. (Advances in Hygrothermal Performance of Building Envelopes: Materials, Systems and Simulations, 2017)
The long-term performance in respect to moisture management within any wood frame wall assembly depends on the hygrothermal response of the wall to local climate moisture loads. Estimating the wood moisture content, temperature, and time of exposure to conditions suitable for the onset, growth, and propagation of mold or rot are critical parameters when assessing the longevity of wood frame structures. A number of approaches for assessing the vulnerability of wood frame structures to deterioration have been developed in recent years; one of which has been used by NRC-Construction for evaluating the performance of wall assemblies based on the results from hygrothermal simulation. In this paper, an example of the use of this approach for the assessment of a stucco-clad wall incorporating drainage cavities is described as is the use of a mold index to capture the risk of the formation of mold in walls. An example is given in assessing the moisture management of a stucco-clad wood frame wall incorporating vented and ventilated drainage cavities for three Canadian locations.
Keywords: drainage components; hygrothermal response; moisture performance; moisture management; stucco cladding; wood frame

Carbon nanomaterials for electrochemical energy technologies: fundamentals and applications - Sun, Shuhui; Sun, Xueliang; Chen, Zhongwei; Liu, Yuyu; Wilkinson, David P.; Zhang, Jiujun (Taylor & Francis, 2017)
This book offers comprehensive coverage of carbon-based nanomaterials and electrochemical energy conversion and storage technologies such as batteries, fuel cells, supercapacitors, and hydrogen generation and storage, as well as the latest material and new technology development. It addresses a variety of topics such as electrochemical processes, materials, components, assembly and manufacturing, degradation mechanisms, challenges, and strategies. With in-depth discussions ranging from electrochemistry fundamentals to engineering components and applied devices, this all-inclusive reference offers a broad view of various carbon nanomaterials and technologies for electrochemical energy conversion and storage devices.

RANS modelling of turbulence in combustors - Jiang, Lei‐Yong (Turbulence Modelling Approaches: Current State, Development Prospects, Applications, 2017)
Turbulence modelling is a major issue, affecting the precision of current numerical simulations, particularly for reacting flows. The RANS (Reynolds‐averaged Navier‐Stokes) modelling of turbulence is necessary in the development of advanced combustion systems in the foreseeable future. Therefore, it is important to understand advantages and limitations of these models. In this chapter, six widely used RANS turbulence models are discussed and validated against a comprehensive experimental database from a model combustor. The results indicate that all six models can catch the flow features; however, various degrees of agreement with the experimental data are found. The Reynolds stress model (RSM) gives the best performance, and the Rk‐ε model can provide similar predictions as those from the RSM. The Reynolds analogy used in almost all turbulent reacting flow simulations is also assessed in this chapter and validated against the experimental data. It is found that the turbulent Prandtl/Schmidt number has a significant effect on the temperature field in the combustor. In contrast, its effect on the velocity field is insignificant in the range considered (0.2–0.85). For the present configuration and operating conditions, the optimal turbulent Prandtl/Schmidt number is 0.5, lower than the traditionally used value of 0.6–0.85.
Keywords: turbulence modelling; RANS; momentum and scalar modelling; combustor

Ultrafast dissociation of metastable CO2+ in a dimer - Ding, Xiaoyan; Haertelt, M.; Schlauderer, S.; Schuurman, M. S.; Naumov, A. Yu.; Villeneuve, D. M.; Mckellar, A. R. W.; Corkum, P. B.; Staudte, A. (Physical Review Letters, 2017)
We triply ionize the van der Waals bound carbon monoxide dimer with intense ultrashort pulses and study the breakup channel (CO)3+2→C++O++CO+. The fragments are recorded in a cold target recoil ion momentum spectrometer. We observe a fast CO2+ dissociation channel in the dimer, which does not exist for the monomer. We found that a nearby charge breaks the symmetry of a X3Π state of CO2+ and induces an avoided crossing that allows a fast dissociation. Calculation on the full dimer complex shows the coupling of different charge states, as predicted from excimer theory, gives rise to electronic state components not present in the monomer, thereby enabling fast dissociation with higher kinetic energy release. These results demonstrate that the electronic structure of molecular cluster complexes can give rise to dynamics that is qualitatively different from that observed in the component monomers.

On Tanaka-Mura's fatigue crack nucleation model and validation - Wu, Xijia (Fatigue & Fracture of Engineering Materials & Structures, 2017)
Tanaka-Mura's fatigue crack nucleation model is revisited. A dimensional problem is found in their cyclic plastic strain formulation obtained by integration of the displacement function, and hence, it is rederived based on the true strain definition. Using the corrected strain formulation, a new fatigue crack nucleation life expression is obtained, and for the first time, low cycle fatigue lives of several metals and alloys are predicted without resorting to experiments. With such theoretical life as the baseline, other factors such as surface roughness, environment, and even high-temperature damage mechanisms can be delineated in further studies.
Keywords: dislocations; fatigue crack nucleation; fatigue life prediction

An archaeosome-adjuvanted vaccine and checkpoint inhibitor therapy combination significantly enhances protection from murine melanoma - Stark, Felicity; Weeratna, Risini; Deschatelets, Lise; Gurnani, Komal; Dudani, Renu; Mccluskie, Michael; Krishnan, Lakshmi (Vaccines, 2017)
Archaeosomes constitute archaeal lipid vesicle vaccine adjuvants that evoke a strong CD8+ T cell response to antigenic cargo. Therapeutic treatment of murine B16-ovalbumin (B16-OVA) melanoma with archaeosome-OVA eliminates small subcutaneous solid tumors; however, they eventually resurge despite an increased frequency of circulating and tumor infiltrating OVA-CD8+ T cells. Herein, a number of different approaches were evaluated to improve responses, including dose number, interval, and the combination of vaccine with checkpoint inhibitors. Firstly, we found that tumor protection could not be enhanced by repetitive and/or delayed boosting to maximize the CD8+ T cell number and/or phenotype. The in vivo cytotoxicity of vaccine-induced OVA-CD8+ T cells was impaired in tumor-bearing mice. Additionally, tumor-infiltrating OVA-CD8+ T cells had an increased expression of programmed cell death protein-1 (PD-1) compared to other organ compartments, suggesting impaired function. Combination therapy of tumor-bearing mice with the vaccine archaeosome-OVA, and α-CTLA-4 administered concurrently as well as α-PD-1 and an α-PD-L1 antibody administered starting 9 days after tumor challenge given on a Q3Dx4 schedule (days 9, 12, 15 and 18), significantly enhanced survival. Following multi-combination therapy ~70% of mice had rapid tumor recession, with no detectable tumor mass after >80 days in comparison to a median survival of 17–22 days for untreated or experimental groups receiving single therapies. Overall, archaeosomes offer a powerful platform for delivering cancer antigens when used in combination with checkpoint inhibitor immunotherapies.
Keywords: checkpoint inhibitor; PD-1; CTLA-4; tumor-infiltrating lymphocyte (TIL); cancer vaccine; CD8+ T cell response; archaeosome; prime-boost; B16; liposome; tumor vaccine; effector T cell (TE); effector memory T cell (TEM)

Toward failure mode and effect analysis for heating, ventilation and air-conditioning - Yang, Chunsheng; Chen, Qiangqiang; Shen, Weiming; Gunay, Burak (2017 IEEE 21st International Conference on Computer Supported Cooperative Work in Design (CSCWD), 2017)
Fault Detection, Diagnostics and Prognostics (FDD&P) is attracting a lot of attention from building operators and researchers because it can help greatly improve the performance of building operations by reducing energy consumption for heating, ventilation and air-conditioning (HVAC) while improving occupant comfort at the same time. However, FDD&P for building operations remains with many challenges due to special operation environments of HVAC systems. These challenges include `tolerance or ignorance' of failures in long-haul operations, lack of operation regulations, and even lack of documents for HVAC failure mode and effect analysis (FMEA), which is a systematic method of identifying and preventing system, product and process problems. To address some of these challenges, we propose to develop a FMEA for HVAC by exploring work orders generated by building energy management systems (BEMS) using a data mining approach. With the developed HVAC FMEA, it is possible to conduct pre-FDD&P procedures to improve HVAC maintenance and to select the high impact failures in order to acquire the operation data for selected failures and develop machine learning-based predictive models to predict a failure before it occurs and isolate the root component of a given failure. In this paper we report some preliminary results in developing an HVAC FMEA tool from a large number of work orders obtained from a BEMS in routine operations. The developed HVAC FMEA will be used as a guidance tool for data gathering and developing data-driven models for building HVAC FDD&P.
Keywords: FMEA; work Order; Fault Detection and Diagnostics (FDD); prognostics; HVAC

Nanostructured indium tin oxide electrodes immobilized with toll-like receptor proteins for label-free electrochemical detection of pathogen markers - Lin, Donghai; Harris, Kenneth D.; Chan, Nora W.C.; Jemere, Abebaw B. (Sensors and Actuators B: Chemical, 2017)
We describe the development of 3D nanostructured indium-tin oxide (ITO) electrodes, immobilized with toll-like receptor proteins (TLRs) for label-free detection of pathogen-associated molecular patterns (PAMPs). Nanostructured ITO electrodes were fabricated on ITO-coated glass substrates using the glancing angle deposition (GLAD) technique. Two different TLRs (TLR4 and TLR5), which recognize different PAMPs, were immobilized onto different GLAD ITO electrodes using a simple, robust and direct methodology with an epoxysilane as the intermediate layer. The immobilization steps were characterized using microscopy, electrochemical techniques and x-ray photoelectron spectroscopy. The changes to electron charge transfer resistance in electrochemical impedance spectroscopy (EIS) of the TLR-based sensors triggered by independent exposures of the TLR4-modified sensor to E. coli O157:H7 endotoxin (lipopolysaccharide, LPS) and the TLR5-modified sensor to flagellin from Salmonella typhimurium were examined. These sensors showed a wide dynamic range (>104) and two-orders of magnitude lower detection limits and 30 times better sensitivity for LPS and flagellin compared to planar gold and ITO-based TLR sensors. Unlike other sensors that exploit specific pathogen recognition elements, TLR-based EIS biosensors have the potential to carry out broad-spectrum detection and classification of pathogens in near-real time.
Keywords: electrochemical impedance spectroscopy; glancing angle deposition; toll-like receptors; pathogen detection; biosensor

Evaluation of approaches to the abatement of nitrate interference with photochemical vapor generation - Lopes, Gisele S.; Sturgeon, Ralph E.; Grinberg, Patricia; Pagliano, Enea (Journal of Analytical Atomic Spectrometry, 2017)
Photochemical vapor generation (PVG) provides an alternative to chemical vapor generation techniques but suffers severe interference in the presence of oxidizing species, notably nitrate and nitrite. Although the mechanism is not completely understood, scavenging of photogenerated free electrons and hydrogen radicals by NO2− and NO3− likely plays a role in terminating analyte reduction reactions which lead to hydridization, carbonylation or alkylation of analytes. In this study, several strategies for the elimination of nitrate and nitrite from samples prior to PVG were examined. Since the Se(IV)-acetic acid PVG system proved to be extremely sensitive to low levels of these oxidants, wherein 50% loss of generation efficiency is realized at [NO3−] > 2.5 mM, it was used as a test case. To this end, a number of practical approaches to the reduction of nitrate and nitrite were evaluated, including: utilizing sulfamic acid, hydrazine sulfate, sodium thiosulfate and V(III), as well as removal by photo-reduction and quantitative precipitation by nitron. Whereas none of these approaches could be implemented with impunity, a methodology based on UV photolysis of a basic solution containing 2% hydrazine sulfate provided high NO3− removal efficiencies. Residual NO2− was quantitatively eliminated by addition of sulfamic acid to the acidified solution, allowing efficient generation of volatile Se(CH3)2 species. The methodology was tested by application to Certified Reference Material SLRS-3 (river water, acidified to pH 1.6 with nitric acid), achieving 83 ± 2% Se(IV) spike recoveries using PVG sample introduction coupled with ICP-MS for detection, illustrating effective control over interferences and recovery of Se(IV).

Streak camera for strong-field ionization - Kübel, M.; Dube, Z.; Naumov, A. Yu.; Spanner, M.; Paulus, G. G.; Kling, M. F.; Villeneuve, D. M.; Corkum, P. B.; Staudte, A. (Physical Review Letters, 2017)
Ionization of an atom or molecule by a strong laser field produces suboptical cycle wave packets whose control has given rise to attosecond science. The final states of the wave packets depend on ionization and deflection by the laser field, which are convoluted in conventional experiments. Here, we demonstrate a technique enabling efficient electron deflection, separate from the field driving strong-field ionization. Using a midinfrared deflection field permits one to distinguish electron wave packets generated at different field maxima of an intense few-cycle visible laser pulse. We utilize this capability to trace the scattering of low-energy electrons driven by the midinfrared field. Our approach represents a general technique for studying and controlling strong-field ionization dynamics on the attosecond time scale.

A novel affinity TAG, ABTAG, and its application to the affinity screening of single-domain antibodies selected by phage display - Hussack, Greg; Baral, Toya Nath; Baardsnes, Jason; Van faassen, Henk; Raphael, Shalini; Henry, Kevin A.; Zhang, Jianbing; Mackenzie, C. Roger (Frontiers in Immunology, 2017)
ABTAG is a camelid single-domain antibody (sdAb) that binds to bovine serum albumin (BSA) with low picomolar affinity. In surface plasmon resonance (SPR) analyses using BSA surfaces, bound ABTAG can be completely dissociated from the BSA surfaces at low pH, over multiple cycles, without any reduction in the capacity of the BSA surfaces to bind ABTAG. A moderate throughput, SPR-based, antibody screening assay exploiting the unique features of ABTAG is described. Anti-carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) sdAbs were isolated from a phage-displayed sdAb library derived from the heavy chain antibody repertoire of a llama immunized with CEACAM6. Following one or two rounds of panning, enriched clones were expressed as ABTAG fusions in microtiter plate cultures. The sdAb-ABTAG fusions from culture supernatants were captured on BSA surfaces and CEACAM6 antigen was then bound to the captured molecules. The SPR screening method gives a read-out of relative expression levels of the fusion proteins and kinetic and affinity constants for CEACAM6 binding by the captured molecules. The library was also panned and screened by conventional methods and positive clones were subcloned and expressed for SPR analysis. Compared to conventional panning and screening, the SPR-based ABTAG method yielded a considerably higher diversity of binders, some with affinities that were three orders of magnitude higher affinity than those identified by conventional panning.
Keywords: antibody discovery; phage display; surface plasmon resonance; single-domain antibody; nanobody; VHH; carcinoembryonic antigen-related cell adhesion molecule 6

Effect of fungal deterioration on physical and mechanical properties of hemp and flax natural fiber composites - Crawford, Bryn; Pakpour, Sepideh; Kazemian, Negin; Klironomos, John; Stoeffler, Karen; Rho, Denis; Denault, Johanne; Milani, Abbas (Materials, 2017)
The development and application of bio-sourced composites have been gaining wide attention, yet their deterioration due to the growth of ubiquitous microorganisms during storage/manufacturing/in-service phases is still not fully understood for optimum material selection and design purposes. In this study, samples of non-woven flax fibers, hemp fibers, and mats made of co-mingled randomly-oriented flax or hemp fiber (50%) and polypropylene fiber (50%) were subjected to 28 days of exposure to (i) no water-no fungi, (ii) water only and (iii) water along with the Chaetomium globosum fungus. Biocomposite samples were measured for weight loss over time, to observe the rate of fungal growth and the respiration of cellulose components in the fibers. Tensile testing was conducted to measure mechanical properties of the composite samples under different configurations. Scanning electron microscopy was employed to visualize fungal hyphal growth on the natural fibers, as well as to observe the fracture planes and failure modes of the biocomposite samples. Results showed that fungal growth significantly affects the dry mass as well as the tensile elastic modulus of the tested natural fiber mats and composites, and the effect depends on both the type and the length scale of fibers, as well as the exposure condition and time.
Keywords: biocomposites; hemp and flax natural fibers; fungal deterioration; material properties; design considerations

A numerical investigation on methane combustion and emissions from a natural gas-diesel dual fuel engine using CFD model - Li, Yu; Li, Hailin; Guo, Hongsheng; Li, Yongzhi; Yao, Mingfa (Applied Energy, 2017)
Natural gas (NG)-diesel dual fuel engines have been criticized for their high emissions of unburned methane. The past research on methane emissions from dual fuel engines has focused on the measurement of methane concentration in exhaust gases. The development of approaches capable of minimizing methane emissions requests the detailed spatial distribution of methane in-cylinder during the combustion and post combustion processes. However, it is difficult to experimentally measure the spatial distribution of methane in-cylinder. This research presents a numerical study on the combustion process of a NG-diesel dual fuel engine using the computational fluids dynamics (CFD) model CONVERGE coupled with a reduced primary reference fuel (PRF) mechanism. The model was validated against the heat release process and the emissions of nitrogen oxide, methane and carbon monoxide measured in a single cylinder dual fuel engine. The validated CFD model was applied to investigate the combustion of methane and n-heptane and the spatial distribution of methane in the dual fuel engine. This is most likely the first attempt to visualize the spatial distribution of methane in dual fuel engines using CFD. The objective of this study is to numerically simulate the methane combustion process, especially the methane present outside the pilot spray, quantify the methane combustion in each combustion stage, and visualize the spatial methane distribution in cylinder. The results showed that the momentum produced by the pilot fuel injection and combustion pushed the combustion products of pilot fuel and methane within the pilot spray plume toward the unburned methane-air mixture. Such a movement enhanced the mixing of the hot combustion products and the relatively cold unburned methane-air mixture during the main combustion process and dominated the combustion of methane presented outside the pilot fuel spray plume. Based on the simulation results at a low load condition (4.05 bar), the main combustion process consumed 43–53% of the methane fumigated into the intake mixture. The post-combustion oxidation process consumed 17–29% of the intake methane, which was 36.2–51.8% methane that survived the main combustion process. In comparison, 27–35% methane emitted the engine without participating the combustion process. The unburned methane at exhaust valve opening was mainly observed at the center of the cylinder. In comparison, the contribution of the crevice and boundary layer around the cylinder liner to methane emissions was relatively small. The slip of methane through the dual fuel engines was due to the fact that the premixed mixture was too lean to support the propagation of the turbulent flame initiated by the pilot fuel and the lack of pilot fuel vapor reaching the center of the combustion chamber because of the geometric limitations of the fuel injection system and the reduced mass of pilot fuel injected into the cylinder. The approaches aiming to enhance the combustion of methane and minimize methane emissions from dual fuel engines should focus on those capable of increasing the volume of pilot fuel vapor formed after injected into the cylinder.
Keywords: CFD model; dual fuel engine; methane emissions; post-combustion oxidation

Behavior and kinetic of hydrolysis of amine boranes in acid media employed in chemical vapor generation - D'ulivo, Lucia; Spiniello, Roberto; Onor, Massimo; Campanella, Beatrice; Mester, Zoltan; D'ulivo, Alessandro (Analytica Chimica Acta, 2017)
The behavior of NaBH4 (THB) and the amine boranes, NH3BH3 (AB), tertbutylNH2BH3 (TBAB), Me2NHBH3 (DMAB) was investigated in continuous flow chemical vapor generation of H2Se from aqueous SeIV coupled with atomic absorption spectrometry. Unexpected higher efficiency of H2Se generation was obtained with amine boranes compared to THB (TBAB > AB > THB) using millimolar concentration of reductant (0.001–0.1 mol L−1) under strongly acidic conditions (HCl, HClO4, H2SO4, HNO3, 0.5–5 mol L−1 H+). Analytical applicability of the CVG system was tested by the determination of SeIV in natural water samples certified reference materials, using 0.01 mol L−1 TBAB in 0.5 M H2SO4. In order to explain this unexpected higher efficiency of amine boranes with respect of THB, the kinetic of hydrolysis of AB, TBAB and DMAB was investigated in acid media typically employed in chemical vapor generation for trace element determination. The kinetic was investigated by monitoring the rate the hydrogen gas evolved during hydrolysis, using a laboratory made thermostated reaction cell. Kinetics were measured for AB, TBAB and DMAB in 0.1, 0.5, 5 mol L−1 HCl or HClO4 reaction media and in 0.1 mol L−1 cysteine +0.1 mol L−1 HCl or HClO4 buffer, for reaction times from 0 to 30 min. Under strongly acidic conditions, the rates of hydrogen evolution produced by amine boranes hydrolysis appear to be much slower than those predicted by a pseudo-first order reaction and using the rate constants reported in the literature. This suggests that, at elevated acidities (5 mol L−1 HCl or HClO4), the hydrolysis of amine boranes takes place in two steps, generating a first amount of H2 (0.67–1.15 mol) much faster than the remaining about 2 mol. This evidence indicates a different mechanism of hydrolysis to the one accepted in the literature for amine boranes. The relatively high efficiencies of H2Se observed with amine borane reduction of inorganic SeIV at elevated acidities can be addressed to the action of borane intermediates, most probably amine borane cations, formed during amine borane hydrolysis in the same reaction conditions.
Keywords: amine boranes; tetrahydridoborate(-1); hydride generation; selenium determination; mechanism; hydrogen evolution

Resolving and tuning carrier capture rates at a single silicon atom gap state - Rashidi, Mohammad; Lloyd, Erika; Huff, Taleana R.; Achal, Roshan; Taucer, Marco; Croshaw, Jeremiah J.; Wolkow, Robert A. (ACS Nano, 2017)
We report on tuning the carrier capture events at a single dangling bond (DB) midgap state by varying the substrate temperature, doping type, and doping concentration. All-electronic time-resolved scanning tunneling microscopy (TR-STM) is employed to directly measure the carrier capture rates on the nanosecond time scale. A characteristic negative differential resistance (NDR) feature is evident in the scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS) measurements of DBs on both n- and p-type doped samples. We find that a common model accounts for both observations. Atom-specific Kelvin probe force microscopy (KPFM) measurements confirm the energetic position of the DB’s charge transition levels, corroborating STS studies. We show that under different tip-induced fields the DB can be supplied with electrons from two distinct reservoirs: the bulk conduction band and/or the valence band. We measure the filling and emptying rates of the DBs in the energy regime where electrons are supplied by the bulk valence band. We show that adding point charges in the vicinity of a DB shifts observed STS and NDR features due to Coulombic interactions.
Keywords: carrier-capture rates; dangling bonds; noncontact atomic force microscopy; silicon; time-resolved scanning tunneling microscopy

Quantification of methane sources in the Athabasca Oil Sands Region of Alberta by aircraft mass-balance - Baray, Sabour; Darlington, Andrea; Gordon, Mark; Hayden, Katherine L.; Leithead, Amy; Li, Shao-Meng; Liu, Peter S. K.; Mittermeier, Richard L.; Moussa, Samar G.; O'Brien, Jason; Staebler, Ralph; Wolde, Mengistu; et al. (Atmospheric Chemistry and Physics Discussions, 2017)
Aircraft-based measurements of methane (CH4) and other air pollutants in the Athabasca Oil Sands Region (AOSR) were made during a summer intensive field campaign between August 13 and September 7 2013, in support of the Joint Canada–Alberta Implementation Plan for Oil Sands Monitoring. Chemical signatures were used to identify CH4 sources from tailings ponds (BTEX VOC's), open-pit surface mines (NOy and rBC) and elevated plumes from bitumen upgrading facilities (SO2 and NOy). Emission rates of CH4 were determined for the five primary surface mining facilities in the region using two mass balance methods. Emission rates from source categories within each facility were estimated when plumes from the sources were spatially separable. Tailings ponds accounted for 45 % of total CH4 emissions measured from the major surface mining facilities in the region while emissions from operations in the open pit mines accounted for ~ 50 %. The average open pit surface mining emission rates ranged from 1.2 to 2.8 tonnes of CH4 hr−1 for different facilities in the AOSR. Amongst the 19 tailings ponds, Mildred Lake Settling Basin, the oldest pond in the region, was found to be responsible for the majority of tailings ponds emissions of CH4 (> 70 %). The sum of measured emission rates of CH4 from the five major facilities, 19.2 ± 1.1 tonnes CH4 hr−1, was similar to a single mass balance determination of CH4 from all major sources in the AOSR determined from a single flight downwind of the facilities, 23.7 ± 3.7 tonnes CH4 hr−1. The measured hourly CH4 emission rate from all facilities in the AOSR is 48 ± 8 % higher than that extracted for 2013 from the Canadian Green House Gas Reporting Program, a legislated facility-reported Emissions Inventory, converted to hourly units. The measured emissions correspond to an emissions rate of 0.17 ± 0.01 Tg CH4 yr−1, if the emissions are assumed temporally constant, an uncertain assumption. The emission rates reported here are relevant for the summer season. In future, effort should be devoted to measurements in different seasons to further our understanding of seasonal parameters impacting fugitive emissions of CH4 and to allow better estimates of annual emissions and year to year variability.

Application of activated carbon to accelerate detoxification of paralytic shellfish toxins from mussels Mytilus galloprovincialis and scallops Chlamys farreri - Qiu, Jiangbing; Fan, Hua; Liu, Ting; Liang, Xia; Meng, Fanping; Quilliam, Michael A.; Li, Aifeng (Ecotoxicology and Environmental Safety, 2017)
Contamination of economic bivalves with paralytic shellfish toxins (PST) occurs frequently in many parts of the world, which potentially threatens consumer health and the marine aquaculture economy. It is the objective of this study to develop a suitable technology for accelerating detoxification of PST from shellfish using activated carbon (AC). The adsorption efficiency of PST by eight different AC materials and by different particle sizes of wood-based AC (WAC) were tested and compared. Then WAC particles (37–48 µm) were fed to mussels Mytilus galloprovincialis and scallops Chlamys farreri previously contaminated with PST through feeding with dinoflagellate Alexandrium tamarense ATHK. Results showed that the maximum adsorption ratio (65%) of PST was obtained by WAC. No significant differences in adsorption ratios were found between different particle sizes of WAC. The toxicity of mussels decreased by 41% and 68% after detoxification with WAC for 1 d and 3 d, respectively. Meanwhile, the detoxification ratio of mussels was approximately 3 times higher than that of scallops. This study suggests that the WAC could be used to accelerate the detoxification of PST by shellfish.
Keywords: paralytic shellfish toxins; activated carbon; adsorbent detoxification; Mytilus galloprovincialis; Chlamys farreri

Analyses of 16S rRNA and cpn60 gene sequences provide complementary information about potentially useful and harmful oil field microbiota - Kryachko, Yuriy; Semler, Diana; Vogrinetz, John; Lemke, Markus; Irvine, Randy; Davidson, John; Links, Matthew G.; Mccarthy, E. Luke; Haug, Brenda; Hemmingsen, Sean M. (International Biodeterioration & Biodegradation, 2017)
Microbial communities from five wells in a Canadian oil field were characterized by sequencing 16S rRNA and cpn60 gene amplicons. Analysis of 16S rRNA amplicon sequences using the RDPipeline and the Phoenix 2 pipeline showed that amplicons representing Ralstonia, Arcobacter, Sulfurospirillum, Methanohalophilus, Methanocalculus and Methanolobus spp. were abundant in most samples. Amplicons derived from Bacillus and some other genera were detected in samples as well. Analysis of cpn60 sequences confirmed that amplicons derived from Sulfurospirillum, Methanolobus and Bacillus spp. were well represented, and showed that a bacterium highly similar to biosurfactant producing Bacillus mojavensis represented the genus Bacillus. In addition, analysis of cpn60 sequences showed that amplicons derived from the Deltaproteobacteria, particularly Pelobacter carbinolicus, were abundant. However, analysis of cpn60 sequences failed to detect amplicons representing Ralstonia spp. or other representatives of the Betaproteobacteria, indicating possible PCR bias. Our findings suggest that gaps resulting from shortcomings of 16S rRNA and cpn60 gene amplification and analytical systems can be overcome through simultaneous targeting of these conserved genes.
Keywords: taxonomic identification; chaperonin-60; biosurfactant; microbially influenced corrosion; methanogen; primer bias

Trichostatin A increases embryo and green plant regeneration in wheat - Jiang, Fengying; Ryabova, Daria; Diedhiou, Jeremie; Hucl, Pierre; Randhawa, Harpinder; Marillia, Elizabeth-france; Foroud, Nora A.; Eudes, Francois; Kathiria, Palak (Plant Cell Reports, 2017)
In wheat, plant regeneration through microspore culture is an integral part of doubled haploid (DH) production. However, low response to tissue culture and genotype specificity are two major constraints in the broad deployment of this breeding tool. Recently, the structure of chromatin was shown to be linked with cell transitions during tissue culture. Specifically, repression of genes that are required for cell morphogenesis, through acetylation of histones, may play an important role in this process. Reduction of histone acetylation by chemical inhibition may increase tissue culture efficiency. Here, the role of trichostatin A (TSA) in inducing microspore-derived embryos was investigated in wheat. The optimal dose of TSA was determined for wheat cultivars and subsequently validated in F1 hybrids. A significant increase in the efficiency of DH production was observed in both cultivated varieties and F1 hybrids. Thus, the inclusion of TSA in DH protocols for wheat breeding programs is advocated.
Keywords: trichostatin A; wheat microspore culture; embryogenesis; doubled-haploidy; plant regeneration

A critical review of Arctic pack ice driving forces: new sources of data - Timco, G. W.; Sudom, D.; Frederking, R.; Barker, A.; Wright, B. D. (Cold Regions Science and Technology, 2017)
This paper provides the details of ice loading events that can be used to further the understanding of pack ice driving forces in the Beaufort Sea. Several methods have been reviewed and employed including in situ stress measurements, loads on the Molikpaq offshore caisson, shoreline pile-up events, pile-ups and rubble fields on offshore shoals and relic berms, analysis of shear walls on offshore rubble fields, and analysis of deep ridge keels. Over 50 different events are identified with 33 suitable for a pack ice analysis. The data are considered in terms of both the ISO 19906 (2010) Arctic Structures Standard and pack ice pressures that can be exerted across various widths. A new approach is proposed, in which the calculated and measured values from past pack ice pressure events are used to predict limit force.
Keywords: sea ice; driving force; pack ice; limit force; multi-year ice

Maximum pile-up heights for grounded ice rubble - Barker, A.; Timco, G. W. (Cold Regions Science and Technology, 2017)
Large grounded ice features can be found in all regions of the world where there is moving ice. This paper compiles over 230 reported ice pile-ups from several international locations including the Baltic Sea, Gulf of Bothnia, Caspian Sea, Lake Simcoe, Stonehaven Harbour (New Brunswick), west Newfoundland, Alaskan and Canadian Beaufort Sea, Norton Sound, Bering Sea, Somerset Island and offshore Sakhalin. The NRC Particle-in-Cell numerical model is used to augment the data. A plot of the rubble sail height as a function of the ice block thickness shows considerable scatter but a general increase in sail height with increasing ice thickness. The scatter in the data is real and is attributed to the fact that the conditions for producing the maximum sail height are not met in most situations. An upper bound of the data can be represented by Hs,max = 19 hB0.33 where Hs,max is the maximum pile-up height (in m), and hB is the block ice thickness (in m). This equation covers the data range up to 2 m in ice thickness. The data also clearly show that high pile-ups (on the order of 10 to 12 m high) can be generated from thin ice less than 0.5 m thick. Further, sail heights up to 30 m are possible for thicker sea ice.
Keywords: ice; pile-up; maximum height; grounded ice

Probabilistic methods for predicting the remaining life of offshore pipelines - Aljaroudi, Alireda; Thodi, Premkumar; Akinturk, Ayhan; Khan, Faisal; Paulin, Mike (Journal of Pressure Vessel Technology, 2017)
When offshore pipelines approach the end of their design life, their condition could threaten oil flow continuity as well as become a potential safety or environmental hazard. Hence, there is a need to assess the remaining life of pipelines to ensure that they can cope with current and future operational demand and integrity challenges. This paper presents a methodology for assessing the condition of aging pipelines and determining the remaining life that can support extended operation without compromising safety and reliability. Applying this methodology would facilitate a well-informed decision that enables decision makers to determine the best strategy for maintaining the integrity of aging pipelines.
Keywords: corrosion; pipelines; failure; probability; pressure

Validation of an open-source CFD tool to support efficient design of offshore gravity-based structures exposed to extreme waves - Babaei, Hossein; Baker, Scott; Cornett, Andrew (Proceedings of the Twenty-seventh (2017) International Ocean and Polar Engineering Conference, 2017)
Computational Fluid Dynamics (CFD) could be an inexpensive complement and even an alternative to physical modelling for investigating the interaction of ocean waves with offshore structures. CFD models however cannot be relied on unless they are well validated. We validated the OpenFOAM® CFD toolbox, a publically available open-source model, for modelling the interaction of extreme regular and irregular waves with offshore gravity-based structures. CFD results including water levels, pressures and forces generally compared well with results for a physical model test program previously conducted by the National Research Council Canada (NRC).
Keywords: CFD; extreme regular waves; irregular waves; gravity-based structure; OpenFOAM; validation; IHFOAM; OLAFOAM

Verification and validation of an in-ice oil spill trajectory model based on satellite-derived ice drift data - Babaei, M. H.; Watson, David; Burcher, Richard (Proceedings of the 2th International Conference on Port and Ocean Engineering under Arctic Conditions, 2017)
A future increase in hydrocarbon exploration and development activities driven by the probable existence of hydrocarbon reserves and an expected increase in shipping activities due to less severe ice conditions, pose a risk of potential oil spills in the offshore Arctic. Estimating oil spill trajectories is essential in quantifying risks and planning an effective spill response. An in-ice spill trajectory modelling, analysis and visualization tool suitable for spills in highly ice-infested waters has been previously developed at NRC. The source data is historical satellite-derived ice drift. The model has been enhanced by including time dependent land-fast ice extent to better estimate coastal spill trajectories. Two hypothetical in-ice spill scenarios in the Canadian Beaufort Sea were modelled based on 34 years of ice velocity data. In four months starting in November, a deep water spill in ice could travel over 700 km, while for a shallow water spill in ice, the travel distance could exceed 400 km. Depending on how fast an in-ice spill could be cleaned, both investigated deep water and shallow water spills could be an international issue, particularly the deep water spill scenario. Present model results were compared with an observed in-ice spill trajectory in the Barents Sea. Because of an underestimation of ice speeds in the input satellite-derived ice drift dataset, the present model underestimates the extent of the trajectory. However, the model estimated the trajectory of an observed buoy well. Present model results were also compared with an independent numerical study of oil spills in the Beaufort Sea. Coastward motions of an in-ice spill are found to be generally similar, however, along the coast, motions deviate after a certain time in the modelled period. Both models are based on data that are expected to be less accurate in the nearshore zone. We did not investigate what caused this deviation or whether the present model or the independent study is a better representation of reality.
Keywords: oil spill; trajectory modelling; ice; validation; verification; satellite- derived ice drift

Wave load prediction on a stationary bergy bit near a fixed offshore platform - Seo, Dong Cheol; Sayeed, Tanvir; Zaman, M. Hasanat; Akinturk, Ayhan (Volume 3A: Structures, Safety and Reliability, 2017)
Offshore oil and gas operations conducted in harsh environments such offshore Newfoundland may pose additional risks due to collision of smaller ice pieces and bergy bits with the offshore structures, including their topsides in the case of gravity based structures particularly in extreme waves. In this paper, CFD (Computational Fluid Dynamics) prediction for wave loads acting on a bergy bit around a fixed offshore platform is presented. Often the vertical column of a gravity based structure is designed against ice collisions, if operating in such an environment. In practices, topsides are usually protected by being placed sufficiently high from the still water level, away from the reach of the bergy bits. This vertical clearance between the still water level and the topside deck is known an air gap. Hence, the amount of the air gap planned for such an offshore structure is an important factor for the safety of the topsides at a given location. In this study a CFD method is applied to estimate the dynamic response of the bergy bit and provide a reliable air gap to reduce the potential risk of the bergy bit collision. In advance of more complex collision simulations using a free-floating ice for the airgap design, CFD analysis of wave load prediction on a stationary bergy bit is carried out and reported in this paper. In the experiments and CFD simulations, the location of the bergy bit is changed to quantify the change of wave load due to the hydrodynamic interaction between the bergy bit and the platform. Finally, the results of the CFD simulations are compared with the relevant experiment results to confirm the simulation performance prior to the free floating bergy bit simulations.

Ectopic expression of Arabidopsis Target of Rapamycin (AtTOR) improves water-use efficiency and yield potential in rice - Bakshi, Achala; Moin, Mazahar; Kumar, M. Udaya; Reddy, Aramati Bindu Madhava; Ren, Maozhi; Datla, Raju; Siddiq, E. A.; Kirti, P. B. (Scientific Reports, 2017)
The target of Rapamycin (TOR) present in all eukaryotes is a multifunctional protein, regulating growth, development, protein translation, ribosome biogenesis, nutrient, and energy signaling. In the present study, ectopic expression of TOR gene of Arabidopsis thaliana in a widely cultivated indica rice resulted in enhanced plant growth under water-limiting conditions conferring agronomically important water-use efficiency (WUE) trait. The AtTOR high expression lines of rice exhibited profuse tillering, increased panicle length, increased plant height, high photosynthetic efficiency, chlorophyll content and low ∆13C. Δ13C, which is inversely related to high WUE, was as low as 17‰ in two AtTOR high expression lines. These lines were also insensitive to the ABA-mediated inhibition of seed germination. The significant upregulation of 15 stress-specific genes in high expression lines indicates their contribution to abiotic stress tolerance. The constitutive expression of AtTOR is also associated with significant transcriptional upregulation of putative TOR complex-1 components, OsRaptor and OsLST8. Glucose-mediated transcriptional activation of AtTOR gene enhanced lateral root formation. Taken together, our findings indicate that TOR, in addition to its multiple cellular functions, also plays an important role in response to abiotic stress and potentially enhances WUE and yield related attributes.

Arabidopsis thaliana miRNAs promote embryo pattern formation beginning in the zygote - Armenta-medina, Alma; Lepe-soltero, Daniel; Xiang, Daoquan; Datla, Raju; Abreu-goodger, Cei; Gillmor, C. Stewart (Developmental Biology, 2017)
miRNAs are essential regulators of cell identity, yet their role in early embryo development in plants remains largely unexplored. To determine the earliest stage at which miRNAs act to promote pattern formation in embryogenesis, we examined a series of mutant alleles in the Arabidopsis thaliana miRNA biogenesis enzymes DICER-LIKE 1 (DCL1), SERRATE (SE), and HYPONASTIC LEAVES 1 (HYL1). Cellular and patterning defects were observed in dcl1, se and hyl1 embryos from the zygote through the globular stage of embryogenesis. To identify miRNAs that are expressed in early embryogenesis, we sequenced mRNAs from globular stage Columbia wild type (wt) and se-1 embryos, and identified transcripts potentially corresponding to 100 miRNA precursors. Considering genome location and transcript increase between wt and se-1, 39 of these MIRNAs are predicted to be bona fide early embryo miRNAs. Among these are conserved miRNAs such as miR156, miR159, miR160, miR161, miR164, miR165, miR166, miR167, miR168, miR171, miR319, miR390 and miR394, as well as miRNAs whose function has never been characterized. Our analysis demonstrates that miRNAs promote pattern formation beginning in the zygote, and provides a comprehensive dataset for functional studies of individual miRNAs in Arabidopsis embryogenesis.
Keywords: Dicer-like 1 (dcl1); Serrate (se); Hyponastic leaves 1 (hyl1); miRNA; Arabidopsis thaliana; embryo; seed

Annotating and quantifying pri-miRNA transcripts using RNA-Seq data of wild type and serrate-1 globular stage embryos of Arabidopsis thaliana - Lepe-soltero, Daniel; Armenta-medina, Alma; Xiang, Daoquan; Datla, Raju; Gillmor, C. Stewart; Abreu-goodger, Cei (Data in Brief, 2017)
The genome annotation for the model plant Arabidopsis thaliana does not include the primary transcripts from which MIRNAs are processed. Here we present and analyze the raw mRNA sequencing data from wild type and serrate-1 globular stage embryos of A. thaliana, ecotype Columbia. Because SERRATE is required for pri-miRNA processing, these precursors accumulate in serrate-1 mutants, facilitating their detection using standard RNA-Seq protocols. We first use the mapping of the RNA-Seq reads to the reference genome to annotate the potential primary transcripts of MIRNAs expressed in the embryo. We then quantify these pri-miRNAs in wild type and serrate-1 mutants. Finally, we use differential expression analysis to determine which are up-regulated in serrate-1 compared to wild type, to select the best candidates of being bona fide pri-miRNAs expressed in the globular stage embryos. In addition, we analyze a previously published RNA-Seq dataset of wild type and dicer-like 1 mutant embryos at the globular stage. Our data are interpreted and discussed in a separate article.

Estimating the motion-to-photon latency in head mounted displays - Zhao, Jingbo; Allison, Robert S.; Vinnikov, Margarita; Jennings, Sion (2017 IEEE Virtual Reality (VR), 2017)
We present a method for estimating the Motion-to-Photon (End-to-End) latency of head mounted displays (HMDs). The specific HMD evaluated in our study was the Oculus Rift DK2, but the procedure is general. We mounted the HMD on a pendulum to introduce damped sinusoidal motion to the HMD during the pendulum swing. The latency was estimated by calculating the phase shift between the captured signals of the physical motion of the HMD and a motion-dependent gradient stimulus rendered on the display. We used the proposed method to estimate both rotational and translational Motion-to-Photon latencies of the Oculus Rift DK2.
Keywords: motion-to-photon latency; end-to-end latency; head-mounted displays

Effect of atomizer internal geometry on the internal and external two-phase flow in effervescent atomization - Jobehdar, Mona hassanzadeh; Siddiqui, Kamran; Gadallah, Aly H.; Chishty, Wajid A. (Atomization and Sprays, 2017)
An experimental study was conducted to study the internal and external two-phase flow in an effervescent atomizer using high-speed imaging. The impact of the aerator tube configuration and mixing zone length on the size of bubbles inside the mixing zone and the spray droplet characteristics at different gas-to-liquid flow rates ratios were studied. An aerator tube with the conical end base was manufactured and tested. It is observed that the separation bubble at the trailing edge is suppressed by this configuration, which resulted in more uniform and smaller bubbles compared to the standard aerator tube with a flat base. The length of the mixing zone was found to have an impact on the bubble size distribution inside the mixing zone; more uniform and smaller bubbles are generated in the shorter mixing zone. The mixing zone length, however, does not show a distinct impact on the droplet velocity and size. It is concluded that a conical base aerator tube and a shorter mixing zone could significantly improve the spray steadiness and the atomization process.
Keywords: effervescent atomizer; aerator tube; mixing zone; bubble size; spray quality; droplet size; high-speed imaging

Investigation of engine performance at altitude using selected alternative fuels for the National Jet Fuels Combustion Program - Canteenwalla, Pervez; Chishty, Wajid (55th AIAA Aerospace Sciences Meeting, 2017)
The National Research Council Canada (NRC) is an allied partner in the National Jet Fuels Combustion Program (NJFCP), which is a US multi-agency program led by the Federal Aviation Administration (FAA). NJFCP aims to accelerate the ASTM International fuel approval process for alternative jet fuels (AJF) by conducting combustion-related testing and modelling to gain a better understanding of the effect of AJF on engine combustion. In support of NJFCP, NRC has undertaken studies on a turbojet engine to investigate the effect of various fuels on engine ignition at simulated altitude conditions. One baseline conventional petroleum derived jet fuel with “average” physical properties and three test fuels meant to represent AJF with unique characteristics were tested. Significant differences were observed in the ignition performance of the fuels. Despite the test fuel having very different chemical compositions, the fuel physical properties appear to have the predominant influence on the ignition performance.

Experimental evaluation of picas: an electro-optical array for non-cooperative collision sensing on unmanned aircraft systems - Minwalla, Cyrus; Ellis, Kristopher; White, Johnathan (AIAA Information Systems-AIAA Infotech @ Aerospace, 2017)
This paper describes the initial flight test evaluation of the Passive Intelligent Collision Avoidance Sensor (PICAS) developed at the National Research Council of Canada (NRC). PICAS represents the latest iteration of a non-cooperative electro-optical (EO) airborne collision sensing instrument designed to explore technology appropriate for under-25 kg Unmanned Aircraft Systems (UAS). PICAS is a prototype, selectively-sampled, multi- camera array mated to a computing platform capable of simultaneously recording and processing images in real-time. A selective sampling approach tailored the sensor to the performance requirement by varying the angular resolution and field of view as a function of azimuth. PICAS was designed to detect a Cessna 172-sized target at 10 km in the head- on direction. The sensor was flight-tested on a Bell 205 rotorcraft acting as a surrogate UAS and flying collision-course intercepts against a Harvard Mark IV intruder. An NRC developed Collision Intercept Display was utilized to provide beyond visual line of sight guidance for both aircraft to conduct the intercepts. Once the collision geometry was coordinated, the Bell 205 switched to automatic operation, controlling altitude, ground- speed and ground-track for the duration of the run. PICAS was operated in pure recording mode, with each camera recording synchronized and time-stamped images at 15 frames per second. The detection performance was evaluated by simulating the real-time processing algorithms against pre-collected imagery and associated aircraft data. Analysis results indicated that PICAS exceeded the minimum detection requirement throughout its field of view for an under-25 kg UAS operating at an airspeed of 80 knots encountering typical (Cessna 172) intruders on co-altitude collision course geometries in Canadian Class G airspace.

Modeling warpage and shrinkage in thermoplastic blow molded part using BlowView - Benrabah, Z.; Bardetti, A.; Ward, G. (Society of Plastic Engineers. Blow Molding Division, 2017)
Blow molding is one of the most important forming processes for producing complex thermoplastic industrial parts. During these processes, residual stresses caused by inhomogeneous cooling and relaxation of polymer chains, often result in shrinkage and warpage of the final part. Tolerance issues are critical in many extrusion blow molding applications, and therefore part deformation due to solidification needs to be controlled and optimized according to specific design criteria. Part designers in today's global environment are under increasing pressure to reduce part development time to a minimum, yet ensuring the maximum part quality and minimum manufacturing costs. If the dimensional changes of a part can be estimated before a tool is built, the design engineer gets a valuable tool to avoid costly and expensive modifications to the mold. Therefore, the development of an accurate simulation tool, well suited for industrial applications, to predict thermoplastic part deformations due to solidification, has become essential for designers to help achieve an efficient production. The aim of this work is to show the latest advancements in predicting solidification and warpage of Plastic Fuel Tanks using NRC's BlowView software. The numerical warpage simulation results obtained using BlowView will be presented based on an industrial case study. The importance of using the ideal geometry and a uniform mesh representing the mold cavity to perform the warpage analysis, rather than the distorted inflated parison mesh, will be highlighted. The simulation results, in terms of displacements, are also compared to the actual scanned part using the best fit technique in order to exemplify the accuracy and reliability of the proposed approach.

LyP-1 conjugated nanoparticles for magnetic resonance imaging of triple negative breast cancer - Abulrob, Abedelnasser; Corluka, Slavisa; Blasiak, Barbara; Gino falonne, B.; Ponjevic, Dragana; Matyas, John; Tomanek, Boguslaw (Molecular Imaging and Biology, 2017)
Purpose: Triple-negative breast cancer (TNBC) does not express estrogen receptor, progesterone receptor, or Her2/neu. Both diagnosis and treatment of TNBC remain a clinical challenge. LyP-1 is a cyclic 9 amino acid peptide that can bind to breast cancer cells. The goal of this study was to design and characterize LyP-1 conjugated to fluorescent iron oxide nanoparticles (LyP-1-Fe3O4-Cy5.5) as a contrast agent for improved and specific magnetic resonance imaging (MRI) in a preclinical model of TNBC. Procedures: The binding of LyP-1-Fe3O4-Cy5.5 to MDA-MB-231 TNBC cells was evaluated and compared to scrambled peptide bio-conjugated to iron oxide nanoparticles (Ctlpep-Fe3O4-Cy5.5) as a negative control. Following the in vitro study, the MDA-MB-231 cells were injected into mammary glands of nude mice. Mice were divided into two groups: control group received Ctlpep- Fe3O4-Cy5.5 and LyP-1 group received LyP-1-Fe3O4-Cy5.5 (tail vein injection at 2 mg/kg of Fe3O4). Mice were imaged with an in vivo fluorescence imager and a 9.4 T MRI system at various time points after contrast agent injection. The T2 relaxation time was measured to observe accumulation of the contrast agent in breast tumor and muscle for both targeted and non-targeted contrast agents. Results: Immunofluorescence revealed dense binding of the LyP-1-Fe3O4-Cy5.5 contrast agent to MDA-MB-231 cells; while little appreciable binding was observed to the scrambled negative control (Ctlpep-Fe3O4-Cy5.5). Optical imaging performed in tumor-bearing mice showed increased fluorescent signal in mammary gland of animals injected by LyP-1-Fe3O4-Cy5.5 but not Ctlpep- Fe3O4-Cy5.5. The results were confirmed ex vivo by the 2.6-fold increase of fluorescent signal from LyP-1-Fe3O4-Cy5.5 in extracted tumors when compared to the negative control. In MR imaging studies, there was a statistically significant (P < 0.01) difference in normalized T2 between healthy breast and tumor tissue at 1, 2, and 24 h post injection of the LyP-1-Fe3O4-Cy5.5. In animals injected with LyP-1-Fe3O4, distinct ring-like structures were observed with clear contrast between the tumor core and rim. Conclusion: The results demonstrate that LyP-1-Fe3O4 significantly improves MRI contrast of TNBC, hence has the potential to be exploited for the specific delivery of cancer therapeutics.
Keywords: breast cancer; triple negative; MRI; optical imaging; LyP1 peptide; iron oxide nanoparticles; molecular imaging

Spectro-spatial relationship between UAV derived high resolution DEM and SWIR hyperspectral data: application to an ombrotrophic peatland - Arroyo-mora, J. Pablo; Kalacska, Margaret; Lucanus, Oliver; Soffer, Raymond J.; Leblanc, George (Remote Sensing for Agriculture, Ecosystems, and Hydrology XIX, 2017)
Peatlands cover ~3% of the globe and are key ecosystems for climate regulation. To better understand the potential effects of climate change in peatlands, a major challenge is to determine the complex relationship between hydrology, microtopography, vegetation patterns, and gas exchange. Here we study the spectral and spatial relationship of microtopographic features (e.g. hollows and hummocks) and near-surface water through narrow-band spectral indices derived from hyperspectral imagery. We used a very high resolution digital elevation model (2.5 cm horizontal, 2.2 cm vertical resolution) derived from an UAV based Structure from Motion photogrammetry to map hollows and hummocks in the peatland area. We also created a 2 cm spatial resolution orthophoto mosaic to enhance the visual identification of these hollows and hummocks. Furthermore, we collected SWIR airborne hyperspectral (880-2450 nm) imagery at 1 m pixel resolution over four time periods, from April to June 2016 (phenological gradient: vegetation greening). Our results revealed an increase in the water indices values (NDWI1640 and NDWI2130) and a decrease in the moisture stress index (MSI) between April and June. In addition, for the same period the NDWI2130 shows a bimodal distribution indicating potential to quantitatively assess moisture differences between mosses and vascular plants. Our results, using the digital surface model to extract NDWI2130 values, showed significant differences between hollows and hummocks for each time period, with higher moisture values for hollows (i.e. moss dominated). However, for June, the water index for hummocks approximated the values found in hollows. Our study shows the advantages of using fine spatial and spectral scales to detect temporal trends in near surface water in a peatland.

Deformation-mechanism-based modeling of creep behavior of modified 9Cr-1Mo steel - Zhang, X. Z.; Wu, X. J.; Liu, R.; Liu, J.; Yao, M. X. (Materials Science and Engineering: A, 2017)
A deformation-mechanism-based true-stress creep model is proposed for studying the creep behavior of modified 9Cr-1Mo steel in this research. Constant-load creep test is conducted on modified 9Cr-1Mo steel in forged form (F91). The creep data obtained in the present study and those reported from the National Institute for Materials Science (NIMS, Japan) on modified 9Cr-1Mo steels processed by different means are analyzed. It is revealed that the relationship of minimum creep rate versus applied engineering stress exhibits distinct power exponent n in three stress regions, which are associated with different deformation mechanisms. The proposed model considers three well recognized deformation mechanisms: dislocation glide, dislocation climb, and grain boundary sliding. The analyses of the experimental data show that this deformation-mechanism-based model can describe fairly well the entire creep deformation process consisting of primary, steady-state, and tertiary creep.
Keywords: deformation-mechanism-based model; modified 9cr-1mo steel; creep; heat treatment; thermomechanical processing

Comments on “A physical model and constitutive equations for complete characterization of S-N fatigue behavior of metals” - Wu, Xijia (Scripta Materialia, 2017)
In a recent paper published in Acta Materialia [Ravi Chandran, Acta Materialia 121 (2016) 85–103], the author assumed that crack initiates instantaneously to a size proportional to the applied stress minus the fatigue endurance limit over the range between the fatigue limit and the ultimate strength of the material. However, this relationship has never been proven experimentally. It contradicts to the understanding of fatigue crack nucleation from accumulation of persistent slip bands, which is a process, not an instantaneous event, as supported by numerous experimental observations. Therefore, the proposed S-N curve relationship based on instantaneous “crack initiation” should not be deemed as a “physical model”.
Keywords: fatigue crack initiation; fatigue crack nucleation; s-n curve

Gaze-contingent auditory displays for improved spatial attention in virtual reality - Vinnikov, Margarita; Allison, Robert S.; Fernandes, Suzette (ACM Transactions on Computer-Human Interaction, 2017)
Virtual reality simulations of group social interactions are important for many applications, including the virtual treatment of social phobias, crowd and group simulation, collaborative virtual environments (VEs), and entertainment. In such scenarios, when compared to the real world, audio cues are often impoverished. As a result, users cannot rely on subtle spatial audio-visual cues that guide attention and enable effective social interactions in real-world situations. We explored whether gaze-contingent audio enhancement techniques driven by inferring audio-visual attention in virtual displays could be used to enable effective communication in cluttered audio VEs. In all of our experiments, we hypothesized that visual attention could be used as a tool to modulate the quality and intensity of sounds from multiple sources to efficiently and naturally select spatial sound sources. For this purpose, we built a gaze-contingent display (GCD) that allowed tracking of a user’s gaze in real-time and modifying the volume of the speakers’ voices contingent on the current region of overt attention. We compared six different techniques for sound modulation with a base condition providing no attentional modulation of sound. The techniques were compared in terms of source recognition and preference in a set of user studies. Overall, we observed that users liked the ability to control the sounds with their eyes. They felt that a rapid change in attenuation with attention but not the elimination of competing sounds (partial rather than absolute selection) was most natural. In conclusion, audio GCDs offer potential for simulating rich, natural social, and other interactions in VEs. They should be considered for improving both performance and fidelity in applications related to social behaviour scenarios or when the user needs to work with multiple audio sources of information.

Numerical and experimental analyses for natural and non-natural impacted composites via thermographic inspection, ultrasonic C-scan and terahertz imaging - Zhang, Hai; Sfarra, Stefano; Genest, Marc; Sarasini, Fabrizio; Perilli, Stefano; Fernandes, Henrique; Fleuret, Julien; Maldague, Xavier; Bison, Paolo; Burleigh, Douglas (Thermosense: Thermal Infrared Applications XXXIX, 2017)
In this paper, thermographic inspections, ultrasonic C-scan and terahertz imaging were used to detect damages caused by impacts in natural, non-natural and hybrid composites. In particular, different hybrid structures were used. In some samples, numerical simulations were performed to predict the damage. A comparison of the results based on experimental and simulated experiments were afterwards conducted with the aim to explore the inspection capability of each technique.
Keywords: infrared thermography; ultrasound C-scan; continuous wave; terahertz imaging; hybrid composite

Validation of a compact isokinetic total water content probe for wind tunnel characterization at NASA Glenn icing research tunnel and at NRC ice crystal tunnel - Davison, Craig R.; Landreville, Charles; Ratvasky, Thomas P. (9th AIAA Atmospheric and Space Environments Conference, 2017)

Droplet evaporation model for determining liquid water content in engine icing tunnels and examination of the factors affecting liquid water content - Davison, Craig R.; Macleod, James D.; Chalmers, Jennifer L. (9th AIAA Atmospheric and Space Environments Conference, 2017)

Solid particle erosion resistant hard coatings for gas turbine engine applications - Yang, Qi; Zhao, Linruo; Patnaik, Prakash (Progress in Aircraft Icing and Aircraft Erosion Research, 2017)
Aircraft engine components, such as compressor blades, vanes, and impeller blisks/wheels, when operating in a sandy environment, can experience severe erosion damage due to ingestion of sand particles. As erosion progresses, the substantial amount of material removal not only leads to further aerodynamic losses but results in the structural weakening of blades as well. Replacement of the parts, whose erosion damage limits have been reached, significantly increases the maintenance and downtime costs. Applying erosion resistant coatings on airfoil surface has been proven as an effective approach to extending the serviceable life of gas turbine engine components. This chapter provides a comprehensive review of the factors affecting erosion damage to engine components, the basic requirements that erosion resistant coatings need to satisfy, the various coating systems that have been developed with excellent erosion resistance, as well as the erosion durability testing techniques applied to evaluate and qualify erosion-resistant coatings. Several technical challenges related to the development of erosion resistant coatings are also briefly discussed.

A novel generalized approach for real-time tool condition monitoring - Hassan, Mahmoud; Sadek, Ahmad A.; Attia, Helmi; Thomson, Vince (Journal of Manufacturing Science and Engineering, 2017)
In high speed cutting processes, late replacement of defective tools may lead to machine breakdowns and badly affect the product quality, which subsequently lead to scrap parts and high process costs. Accurate tool condition detection is essential to achieve high level of competitiveness via increasing process productivity and standardizing the quality of the produced parts. Therefore, tool condition monitoring (TCM) systems have been widely emphasized as an important principle to achieve these industrial demands. Several studies for tool condition monitoring were carried out to capture tool failure using complex conventional and artificial intelligence techniques. However, these studies suffer from the absence of standardization and generalization. Hence, this paper presents a robust and reliable processing technique for the cutting process signals to extract generalized features in time and frequency domains. The proposed technique masks the effects of the cutting conditions on the extracted features and accentuates the tool condition effect. Characterization and statistical analysis of the processed features were performed to examine their sensitivity to the tool condition. The results revealed the processing technique capability to separate the features extracted from the spindle motor current signals into two mutually exclusive clusters according to their tool condition. The statistical analysis results were employed to optimize the tool condition detection approach using linear discrimination analysis LDA model. The results indicate the capability of the processing technique to minimize the system learning effort and to detect tool wear above the threshold level with accuracy above 90%.
Keywords: condition monitoring; cutting; signals; statistical analysis; failure; wear; machinery; engines; product quality; motors

Influence of laves phase on creep strength of modified 9Cr-1Mo steel - Zhang, X. Z.; Wu, X. J.; Liu, R.; Liu, J.; Yao, M. X. (Materials Science and Engineering: A, 2017)
The influence of Laves phase in the microstructure on the creep strength of a modified 9Cr-1Mo tempered ferritic steel, F91, is investigated in this research. Through additional aging heat treatment up to 5000 h, a pronounced increase of Mo-rich Laves phase is found around Cr-rich carbide M23C6, which is pinned on the prior-austenite grain boundaries and martensitic lath boundaries. This secondary precipitation hardening provided by the Laves phase is rapidly offset by its coarsening into large clusters during long-term thermal exposure and under creep conditions, leading to earlier creep rupture than the pristine material. Uniaxial constant-load creep tests are conducted on both aged and non-aged coupons under the same creep conditions. The creep rupture behavior of both materials is rationalized with the assistance of a deformation-mechanism-based true-stress creep model that was developed in the previous work. The effects of Laves phase on the creep strength of F91 are related to its influence on the well-recognized existing deformation mechanisms: dislocation glide, dislocation climb, and grain boundary sliding.
Keywords: laves phase; modified 9cr-1mo steel; creep; deformation-mechanism-based model; heat treatment

Momentum-resolved electron energy loss spectroscopy for mapping the photonic density of states - Shekhar, Prashant; Malac, Marek; Gaind, Vaibhav; Dalili, Neda; Meldrum, Al; Jacob, Zubin (ACS Photonics, 2017)
Strong nanoscale light–matter interaction is often accompanied by ultraconfined photonic modes and large momentum polaritons existing far beyond the light cone. A direct probe of such phenomena is difficult due to the momentum mismatch of these modes with free space light, however, fast electron probes can reveal the fundamental quantum and spatially dispersive behavior of these excitations. Here, we use momentum-resolved electron energy loss spectroscopy (q-EELS) in a transmission electron microscope to explore the optical response of plasmonic thin films including momentum transfer up to wavevectors (q) significantly exceeding the light line wave vector. We show close agreement between experimental q-EELS maps, theoretical simulations of fast electrons passing through thin films and the momentum-resolved photonic density of states (q-PDOS) dispersion. Although a direct link between q-EELS and the q-PDOS exists for an infinite medium, here we show fundamental differences between q-EELS measurements and the q-PDOS that must be taken into consideration for realistic finite structures with no translational invariance along the direction of electron motion. Our work paves the way for using q-EELS as the preeminent tool for mapping the q-PDOS of exotic phenomena with large momenta (high-q) such as hyperbolic polaritons and spatially dispersive plasmons.
Keywords: band structure; electron energy loss spectroscopy (EELS); nonlocality; photonic density of states; plasmonics

Carbon contamination in scanning transmission electron microscopy and its impact on phase-plate applications - Hettler, Simon; Dries, Manuel; Hermann, Peter; Obermair, Martin; Gerthsen, Dagmar; Malac, Marek (Micron, 2017)
We analyze electron-beam induced carbon contamination in a transmission electron microscope. The study is performed on thin films potentially suitable as phase plates for phase-contrast transmission electron microscopy. Electron energy-loss spectroscopy and phase-plate imaging is utilized to analyze the contamination. The deposited contamination layer is identified as a graphitic carbon layer which is not prone to electrostatic charging whereas a non-conductive underlying substrate charges. Several methods that inhibit contamination are evaluated and the impact of carbon contamination on phase-plate imaging is discussed. The findings are in general interesting for scanning transmission electron microscopy applications.
Keywords: scanning transmission electron microscopy; contamination; electron-beam induced charging; phase plate; graphitized carbon; thin film

Quality evaluation of ultra-thin samples: application to graphene - Cui, K.; Bosnick, K.; Indoe, R.; Malac, M.; Mcleod, R. A. (Microscopy Research and Technique, 2017)
Many new materials emerging are strictly two dimensional (2D), often only one or two monolayers thick. They include transition metal dichalcogenides, such as MoS2, and graphene. Graphene in particular appears to have many potential applications. Typically the crystalline film without contamination is of interest. Therefore, a reliable method is needed to routinely evaluate the quality of the synthesized samples. Here, we present one such candidate method that utilizes standard electron diffraction and low/medium magnification imaging in a rudimentary transmission electron microscope. The electron irradiation dose is very low thus reducing electron irradiation damage of the investigated samples. As an example, the method was applied to the evaluation of as-grown graphene sample quality and a study on heating-induced change in graphene. It can be used to evaluate the volume and areal ratio of crystalline to noncrystalline component. The method is amiable to automated film quality evaluation.

Sample preparation method for 3D size measurements of polystyrene nanoparticles with nominal 30, 50, 70 and 100 nm diameters by electron tomography - Hayashida, Misa; Malac, Marek (Measurement Science and Technology, 2017)
We developed a sample preparation method for 3D electron tomography using a focus-ion-beam-fabricated carbon square-shaped rod to observe the deformation of polystyrene nanoparticles on carbon. The method enables the observation of the interface between the particles and carbon substrate. Polystyrene nanoparticles are increasingly more deformed as their nominal diameter decreases. Our results indicate that electron tomography is a useful approach to correct results from conventional TEM measurements for soft particles.

Computer simulations analysis for determining the polarity of charge generated by high energy electron irradiation of a thin film - Malac, Marek; Hettler, Simon; Hayashida, Misa; Kawasaki, Masahiro; Konyuba, Yuji; Okura, Yoshi; Iijima, Hirofumi; Ishikawa, Isamu; Beleggia, Marco (Micron, 2017)
Detailed simulations are necessary to correctly interpret the charge polarity of electron beam irradiated thin film patch. Relying on systematic simulations we provide guidelines and movies to interpret experimentally the polarity of the charged area, to be understood as the sign of the electrostatic potential developed under the beam with reference to a ground electrode. We discuss the two methods most frequently used to assess charge polarity: Fresnel imaging of the irradiated area and Thon rings analysis. We also briefly discuss parameter optimization for hole free phase plate (HFPP) imaging. Our results are particularly relevant to understanding contrast of hole-free phase plate imaging and Berriman effect.
Keywords: hole-free phase plate; volta phase plate; radiation damage; electron beam induced charging; thon rings; fresnel images

Band gap measurement of Bi2MoxW1-xO6 by low loss electron energy loss spectroscopy - Morales-Cruz, Damasio; Paraguay-Delgado, Francisco; Borja-Urby, Raúl; Basurto-Cereceda, Sofía; Herrera-Pérez, Guillermo; Longo, Paolo; Malac, Marek (Materials Science in Semiconductor Processing, 2017)
This work shows the comparison of high-resolution electron energy loss spectra (HR-EELS) in the low loss region (0−15 eV) to investigate the electronic structure from koechilinite Bi2MoO6 to rusellite Bi2WO6 varying the stoichiometric relation Bi2MoxW1−xO6. The effect of the Mo to W ratio on the bandgap energy was evaluated on individual particles. Two approximations were considered in order to determine the band gap energy value, the first one was a linear fit and the second one was a mathematical fit. Both analyses are in agreement with those ones collected and analyzed by UV–Vis characterization. Our results suggest a direct electronic transition that increases from about 2.53 eV to about 3 eV as the W content increase from 0% to 100% wt. X-ray diffraction was used to corroborate the crystal structure and crystal size; transmission electron microscopy was used to monitor the morphology evolution and UV–Vis spectroscopy in diffuse reflectance mode to determine the Eg. These techniques complement the characterization of these materials.
Keywords: electron energy loss spectroscopy (eels); transmission electron microscopy; band gap; energy loss function; Bi2MoxW1−xO6

Atomic white-out: enabling atomic circuitry through mechanically induced bonding of single hydrogen atoms to a silicon surface - Huff, Taleana R.; Labidi, Hatem; Rashidi, Mohammad; Koleini, Mohammad; Achal, Roshan; Salomons, Mark H.; Wolkow, Robert A. (ACS Nano, 2017)
We report the mechanically induced formation of a silicon–hydrogen covalent bond and its application in engineering nanoelectronic devices. We show that using the tip of a noncontact atomic force microscope (NC-AFM), a single hydrogen atom could be vertically manipulated. When applying a localized electronic excitation, a single hydrogen atom is desorbed from the hydrogen-passivated surface and can be transferred to the tip apex, as evidenced from a unique signature in frequency shift curves. In the absence of tunnel electrons and electric field in the scanning probe microscope junction at 0 V, the hydrogen atom at the tip apex is brought very close to a silicon dangling bond, inducing the mechanical formation of a silicon–hydrogen covalent bond and the passivation of the dangling bond. The functionalized tip was used to characterize silicon dangling bonds on the hydrogen–silicon surface, which was shown to enhance the scanning tunneling microscope contrast, and allowed NC-AFM imaging with atomic and chemical bond contrasts. Through examples, we show the importance of this atomic-scale mechanical manipulation technique in the engineering of the emerging technology of on-surface dangling bond based nanoelectronic devices.
Keywords: AFM; dangling bonds; mechanochemistry; nanofabrication; nanolithography; nanostructures; silicon

Probing electronic structure of stoichiometric and defective SnO2 - Moreno, M. S.; Kas, J. J.; Ma, C.; Wang, F.; Rehr, J. J.; Malac, M. (Physical Review B, 2017)
The electronic structure of stoichiometric tin dioxide (SnO2) is studied by probing its unoccupied states using the fine structure in the electron energy-loss spectra (EELS) at the oxygen-K (O-K) edge. The spectral measurements were performed both at room and at high temperatures (773 K) and compared to ab initio calculations carried out using the real-space multiple-scattering and linearized augmented-plane-wave methods. Important many-body effects are included via quasiparticle corrections calculated within the many-pole GW self-energy approximation. An additional energy-dependent damping is calculated to account for vibrational effects. Results from this paper demonstrated that quantitative agreement between theoretical and experimental spectra can be obtained when nonspherical potentials and quasiparticle self-energy effects are considered and vibrational broadening is included. Modifications of the electronic structure by single oxygen vacancies, both in the bulk and at the (110) surface, also are predicted. Our predictions support the use of O-K EELS as a probe of the defect structures in SnO2 surfaces and nanoparticles.

The spontaneous adhesion of BMMC onto self-assembled peptide nanoscaffold without activation inhibits its IgE-mediated degranulation - Lu, Lei; Arizmendi, Narcy; Kulka, Marianna; Unsworth, Larry D. (Advanced Healthcare Materials, 2017)
Mast cells play a distinct role in the innate immune response. Engineered microenvironments for the express purpose of influencing mast cell activity will provide a novel means of designing biomaterials, as well as a means to systematically investigate mast cell biology in a 3D setting. Here, the effect of nanoscaffolds composed of self-assembling peptides, namely (RADA)4, on bone-marrow-derived murine mast cell (BMMC) activity is reported. Unlike most studies that stimulate mast cells to induce adhesion, this results show that BMMCs spontaneously adhere to the artificial nanoscaffold without initiating their activation. It is observed that the classical immunoglobulin (IgE) antigen-mediated degranulation of adhered BMMC is inhibited by the nanoscaffold, while non-IgE (A23187)-induced degranulation is unaffected. The inhibition of IgE–antigen-mediated degranulation is likely a result of inhibited molecular diffusion within the matrix; antigen diffusion, IgE–FcεRI complex shuttling, and/or formation of multiple IgE–FcεRI clusters may be physically hindered in the presence of the polyvalent nanofiber network. Moreover, the IgE/antigen-induced inflammatory cytokine tumor necrosis factor α release from adherent BMMCs is significantly reduced likely due to interaction with the nanofiber matrix. This work is considered the first step in quantifying mast cell activity in artificial matrices composed of self-assembling peptides.
Keywords: degranulation; IgE; mast cells; self-assembling peptides; TNF-α

Contamination and charging of amorphous thin films suitable as phase plates for phase-contrast transmission electron microscopy - Hettler, Simon; Hermann, Peter; Dries, Manuel; Obermair, Martin; Gerthsen, Dagmar; Malac, Marek (Microscopy and Microanalysis, 2017)

Hole-free phase plate energy filtering imaging of graphene: toward quantitative hole-free phase plate imaging in a TEM - Malac, Marek; Kano, Emi; Hayashida, Misa; Kawasaki, Masahiro; Motoki, Sohei; Egerton, Ray; Ishikawa, Isamu; Okura, Yoshio; Beleggia, Marco (Microscopy and Microanalysis, 2017)

Temperature measurement in a tem using electron diffraction of amorphous films - Hayashida, Misa; Cui, Kai; Malac, Marek (Microscopy and Microanalysis, 2017)

Multiscale computational study of electronic structure and properties of electrochemical nano-systems of perovskites for photovoltaic application - Gusarov, Sergey; Sapelnikova, Karina; Kobryn, Olexander; Shankar, Karthik (ECS Transactions, 2017)
We present the results of multiscale modelling of electronic and structural properties of organo-halide perovskites of the type CH3NH3PbX3 in blends of poly(3-hexylthiophene) (P3HT) or carboxylated poly(3-butylthiophene) (P3BT). For this, we use Molecular Dynamic (MD) simulations with the Universal Force Field (UFF) combined with the Density Functional Theory (DFT). With the DFT, we optimize the geometry and charge distribution in P3BT and P3HT molecules, analyze electronic orbitals and calculate the absorption spectra. With the MD, we determine structural properties of blends. In addition, the analysis of MD trajectories allows us to better choose the initial positions of P3BT or P3HT molecules in the follow-up DFT analysis which is focused on the study of electronic properties on the border of the perovskite-polymer system. These properties define charge transfer processes from donor to acceptor and are utilized in development of new generation organic solar cells.

Engineering matrix-free laser desorption ionization mass spectrometry using glancing angle deposition films - Singh, Rama K.; Bezuidenhout, Louis W.; Jemere, Abebaw; Wang, Zhen; Brett, Michael; Harrison, D. Jed (Rapid Communications in Mass Spectrometry, 2017)
Thin, nanoporous films fabricated using Glancing Angle Deposition (GLAD) technology are demonstrated for solid matrix laser desorption ionization mass spectrometry (SMALDI-MS). GLAD allows facile engineering of naonporosity, film thickness, post alignment, and material composition, as demonstrated here by the fabrication of Co-GLAD and Si-GLAD films for SMALDI, and by exploration of the SMALDI performance as a function of thickness, post density, and angle of the post relative to surface normal. GLAD films were prepared by electron beam evaporation onto silicon substrates, using steep angles of incidence for the vacuum deposition, with computer controlled substrate rotation. LDI from the GLAD films were evaluated using an MDS-Sciex time-of-flight (TOF) MALDI-MS. Co-GLAD films give 6 fmol limit of quantitation for complex carbohydrate derivatives, and slanted-post Si-GLAD films show up to 3 times higher sensitivity than vertical post structures. Reproducibility of both Si and Co films is much higher than conventional MALDI methods for m/z below at least 2100 Daltons. Both reproducibility and detection limits are comparable to or better than other nano-structured materials. Co-GLAD films are significantly better in performance than Co powders or Co thin films on silicon substrates previously evaluated. The flexibility of GLAD for thin film fabrication of LDI materials is demonstrated by the range of nanoporous materials that can be grown, and the fine control over structural conformation, thickness and porosity.

Fabrication of large-area polymer microfilter membranes and their application for particle and cell enrichment - Hernández-Castro, Javier Alejandro; Li, Kebin; Meunier, Anne; Juncker, David; Veres, Teodor (Lab Chip, 2017)
A vacuum assisted UV micro-molding (VAUM) process is proposed for the fabrication of freestanding and defect-free polymer membranes based on a UV-curable methacrylate polymer (MD 700). VAUM is a highly flexible and powerful method for fabricating low cost, robust, large-area membranes over 9 × 9 cm2 with pore sizes from 8 to 20 μm in diameter, 20 to 100 μm in thickness, high aspect ratio (the thickness of the polymer over the diameter of the hole is up to 15 : 1), high porosity, and a wide variety of geometrical characteristics. The fabricated freestanding membranes are flexible while mechanically robust enough for post manipulation and handling, which allows them to be cut and integrated as a plastic cartridge onto thermoplastic 3D microfluidic devices with single or double filtration stages. Very high particle capture efficiencies (≈98%) have been demonstrated in the microfluidic devices integrated with polymer membranes, even when the size of the beads is very close to the size of the pores of the microfilter. About 85% of the capture efficiency has been achieved in cancer cell trapping experiments, in which a breast cancer cell line (MDA-MB-231) spiked with phosphate-buffered saline buffer when the pore size of the filter is 8 μm and the device is operated at a flow rate of 0.1 mL min−1.

Rapid screening and identification of living pathogenic organisms via optimized bioorthogonal non-canonical amino acid tagging - Sherratt, Allison Rae; Rouleau, Yanouchka; Luebbert, Christian; Strmiskova, Miroslava; Veres, Teodor; Bidawid, Sabah; Corneau, Nathalie; Pezacki, John Paul (Cell Chemical Biology, 2017)
Pathogenic bacteria can be a major cause of illness from environmental sources as well as the consumption of contaminated products, giving rise to public health concerns globally. The surveillance of such living organisms in food and water supplies remains an important challenge in mitigating their deleterious societal effects. Here, we have developed an optimized bioorthogonal non-canonical amino acid tagging approach to the imaging, capture, and interrogation of shigatoxigenic/verotoxigenic Escherichia coli (VTEC) and Listeria that enables the distinction between living wild-type pathogenic bacteria. The approaches utilize homopropargylglycine (HPG), as well as optimized growth media, that restricts endogenous methionine biosynthesis in a variety of species of public health concern. Endogenous methionine residues are then replaced with HPG, which can then be modified using a myriad of compatible bioorthogonal reactions for tagging of exclusively live bacteria. The methods reported allow for the very rapid screening and identification of living pathogenic organisms.
Keywords: homopropargylglycine; bioorthogonal chemistry; verotoxigenic; E. coli; Listeria; metabolic labeling; click reaction; live versus dead screening

Single-drop solution electrode discharge-induced cold vapor generation coupling to matrix solid-phase dispersion: a robust approach for sensitive quantification of total mercury distribution in fish - Chen, Qian; Lin, Yao; Tian, Yunfei; Wu, Li; Yang, Lu; Hou, Xiandeng; Zheng, Chengbin (Analytical Chemistry, 2017)
Sensitive quantification of mercury distribution in fish is challenging because of insufficient sensitivities of conventional analytical methods, the limited mass of organs (tens of micrograms to several milligrams), and dilution of analyte concentration from sample digestion. In this work, a simple and robust approach coupling multiwall carbon nanotubes assisted matrix solid-phase dispersion (MWCNTs-MSPD) to single-drop solution electrode glow discharge-induced cold vapor generation (SD-SEGD-CVG) was developed for the sensitive determination of mercury in limited amount of sample. Mercury species contained in a limited amount of sample can be efficiently extracted into a 100 μL of eluent by MWCNTs-MSPD, which are conveniently converted to Hg0 by SD-SEGD-CVG and further transported to atomic fluorescence spectrometry for their determination. Therefore, analyte dilution resulted from sample preparation is avoided and sensitivity is significantly improved. On the basis of consumption of 1 mg of sample, a limit of detection of 0.01 μg L–1 (0.2 pg) was obtained with relative standard deviations (RSDs) of 5.2% and 4.6% for 2 and 20 μg L–1, respectively. The accuracy of the proposed method was validated by analysis of three Certified Reference Materials with satisfying results. To confirm that SD-SEGD-CVG-AFS coupling to MWCNTs-MSPD is a promising method to quantify mercury distribution in fish, this method was successfully applied for the sensitive determination of mercury in seven organs of common carps (muscle, gill, intestine, liver, gallbladder, brain, and eye) after dietary of mercury species. The proposed method provides advantages of minimum sample dilution, low blank, high sample introduction efficiency, high sensitivity, and minimum toxic chemicals and sample consumption.

Contaminant and other elements in soil (CCQM-K127) - Torres, M. Rocio Arvizu; Manzano, J. Velina Lara; Moya, Edith Valle; Horvat, Milena; Jaćimović, Radojko; Zuliani, Tea; Vreča, Polona; Acosta, Osvaldo; Bennet, John; Snell, James; Almeida, Marcelo D.; De Sena, Rodrigo C.; et al. (Metrologia, 2017)
Non-contaminated soils contain trace and major elements at levels representing geochemical background of the region. The main sources of elements as contaminants/pollutants in soils are mining and smelting activities, fossil fuel combustion, agricultural practices, industrial activities and waste disposal. Contaminated/polluted sites are of great concern and represent serious environmental, health and economic problems. Characterization and identification of contaminated land is the first step in risk assessment and remediation activities. It is well known that soil is a complex matrix with huge variation locally and worldwide. According to the IAWG's five year plan, it is recommended to have a key comparison under the measurement service category of soils and sediments for the year 2015. Currently 13 NMI has claimed calibration and measurement capabilities (CMCs) in category 13 (sediments, soils, ores, and particulates): 29 CMCs in soil and 96 CMCs in sediments. In this regard this is a follow-up comparison in the category 13; wherein three key comparisons have been carried out during the years 2000 (CCQM-K13), 2003 (CCQM-K28) and 2004 (CCQM-K44). Since it is important to update the capabilities of NMIs in this category. CENAM and JSI proposed a key comparison in this category and a pilot study in parallel. The proposed study was agreed by IAWG members, where two soils samples were used in both CCQM-K127 representing a non-contaminated soil with low contents of elements (arsenic, cadmium, iron, lead and manganese), and a contaminated soil with much higher content of selected elements (arsenic, cadmium, iron and lead). This broadens the scope and a degree of complexity of earlier measurements in this field. National metrology institutes (NMIs)/designate institutes (DIs) should, therefore, demonstrate their measurement capabilities of trace and major elements in a wide concentration ranges, representing background/reference sites as well as highly contaminated soils by their available analytical methods. This facilitated the investigation into the core capabilities of participants to measure the mass fraction of tested elements in soil and therefore to claim their CMCs as listed in appendix C of the key comparison database (KCDB) under the mutual recognition arrangement of the International Committee for Weights and Measures (CIPM MRA). In total 19 institutes (NMIs/Dis) participated in the key comparison and the reported results of the key comparison were from 18 institutes (NMIs/DIs); 151 measurements were reported for CCQM-K127. The analytical techniques selected by the participant institutes were ICP-MS, ICP-OES, FAAS, ET-AAS and INAA (k0-method of INAA); the sample preparation methods used were based on microwave assisted digestion, except when it was used INAA. After discussions it agreed to use the median as KCRV and the MMADe as u(xKCRV). Generally most of the results of the participants were found to be consistent for all measurements according to their equivalence statements, with the exception of some extreme values, which were identified with a value of di/U(di) higher than 1. This key comparison is a means of providing evidence for practical demonstration of a CCQM comparison calibration and measurement capabilities (CMCs) claims for contaminant and others elements, in low and medium content levels in non-contaminated and contaminated matrices described in category 13.

Concept paper on SI value assignment of purity: model for the classification of peptide/protein purity determinations - Josephs, Ralf D.; Stoppacher, Norbert; Westwood, Steven; Wielgosz, Robert I.; Li, Ming; Quaglia, Milena; Melanson, Jeremy; Martos, Gustavo; Prevoo, Desiree; Wu, Liqing; Scapin, Sandra; Senal, Merve Öztug; et al. (Journal of Chemical Metrology, 2017)
Required metrological tools, such as higher order reference measurements procedures, pure substance and matrix certified reference materials, are established for small well defined molecules. Difficulties still remain in the provision of SI traceable standards in the area of larger biomolecules such as peptides/proteins. The provision of Primary Calibration Reference Services has been identified as a core technical competency for National Measurement Institutes (NMIs). A concept has been elaborated by the Focus Group I on peptide/protein purity for the strategic planning of ongoing Key Comparisons of the Protein Analysis Working Group (PAWG) within the Comité Consultatif pour la Quantité de Matière (CCQM). The assignment of the mass fraction content of high purity peptide/protein materials will be the subject of the CCQM-K115/P55.2 comparison series to directly support NMI services and certified reference materials currently being provided by NMIs.

Differential mobility spectrometry for improved selectivity in hydrophilic interaction liquid chromatography-tandem mass spectrometry analysis of paralytic shellfish toxins - Beach, Daniel G. (Journal of The American Society for Mass Spectrometry, 2017)
Paralytic shellfish toxins (PSTs) are neurotoxins produced by dinoflagellates and cyanobacteria that cause paralytic shellfish poisoning in humans. PST quantitation by LC-MS is challenging because of their high polarity, lability as gas-phase ions, and large number of potentially interfering analogues. Differential mobility spectrometry (DMS) has the potential to improve the performance of LC-MS methods for PSTs in terms of selectivity and limits of detection. This work describes a comprehensive investigation of the separation of 16 regulated PSTs by DMS and the development of highly selective LC-DMS-MS methods for PST quantitation. The effects of all DMS parameters on the separation of PSTs from one another were first investigated in detail. The labile nature of 11α-gonyautoxin epimers gave unique insight into fragmentation of labile analytes before, during, and after the DMS analyzer. Two sets of DMS parameters were identified that either optimized the resolution of PSTs from one another or transmitted them at a limited number of compensation voltage (CV) values corresponding to structural subclasses. These were used to develop multidimensional LC-DMS-MS/MS methods using existing HILIC-MS/MS parameters. In both cases, improved selectivity was observed when using DMS, and the quantitative capabilities of a rapid UPLC-DMS-MS/MS method were evaluated. Limits of detection of the developed method were similar to those without DMS, and differences were highly analyte-dependant. Analysis of shellfish matrix reference materials showed good agreement with established methods. The developed methods will be useful in cases where specific matrix interferences are encountered in the LC-MS/MS analysis of PSTs in complex biological samples.
Keywords: ion mobility; algal toxins; PSP; FAIMS; selexion; reference materials

Trace radioactive impurities in final construction materials for EXO-200 - Leonard, D. S.; Auty, D. J.; Didberidze, T.; Gornea, R.; Grinberg, P.; Maclellan, R.; Methven, B.; Piepke, A.; Vuilleumier, J.-L.; Albert, J. B.; Anton, G.; Badhrees, I.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
We report results from a systematic measurement campaign conducted to identify low radioactivity materials for the construction of the EXO-200 double beta decay experiment. Partial results from this campaign have already been reported in a 2008 paper by the EXO collaboration. Here we release the remaining data, collected since 2007, to the public. The data reported were obtained using a variety of analytic techniques. The measurement sensitivities are among the best in the field. Construction of the EXO-200 detector has been concluded, and Phase-I data was taken from 2011 to 2014. The detector’s extremely low background implicitly verifies the measurements and the analysis assumptions made during construction and reported in this paper.
Keywords: radiopurity; ultra-trace analysis; neutron activation analysis; mass spectrometry; mass spectroscopy; germanium counting; alpha counting; low background; double beta decay; EXO; EXO-200

Quantifying uncertainty in auto-compensating laser-induced incandescence parameters due to multiple nuisance parameters - Hadwin, Paul J.; Sipkens, T. A.; Thomson, K. A.; Liu, F.; Daun, K. J. (Applied Physics B, 2017)
Auto-compensating laser-induced incandescence (AC-LII) can be used to infer the particle volume fraction of a soot-laden aerosol. This estimate requires detailed knowledge of multiple model parameters (nuisance parameters), such as the absorption function of soot, calibration coefficients, and laser sheet thickness, which are imperfectly known. This work considers how uncertainties in the nuisance parameters propagate into uncertainties present in soot volume fraction (SVF) and peak particle temperature estimates derived from LII data. The uncertainty of the nuisance parameters is examined and modeled using maximum entropy prior distributions. This uncertainty is then incorporated into the estimates of SVF and peak temperature through a rigorous marginalization technique. Marginalization is carried out using a Gaussian approximation, which is a fast alternative to techniques previously employed to compute uncertainties of AC-LII-derived quantities.

Effects of particle size distribution and oxygen concentration on the propagation behavior of pulverized coal flames in O2/CO2 atmospheres - Gu, Mingyan; Chen, Xue; Wu, Cengceng; He, Xianhui; Chu, Huaqiang; Liu, Fengshan (Energy & Fuels, 2017)
The ignition and flame propagation behavior of pulverized coal particles in an O2/CO2 atmosphere was studied in a long quartz tube reactor. The effects of mixing ratio of fine (mean diameter 16 μm) and coarse (mean diameter 82 μm) coal particles and oxygen concentration on the ignition characteristics, flame front distance, and flame propagation velocity were investigated by capturing the flame ignition and propagation using a high-speed video camera. The experimental results show that the particle size distribution has a strong influence on the ignition and flame structure of coal particles. Smaller coal particles result in earlier ignition, a smoother flame front, longer flame, and faster flame propagation velocity. Mixing of smaller coal particles with larger ones shortens the ignition delay and enhances the propagation velocity of the flame front. For different coal particle size distributions, the variation of flame propagation velocity with time in general displays an “M”-shaped curve. The curve of flame propagation velocity vs time is single-peaked at 40% oxygen concentration for both coarse and fine particles with mean diameters of 82 and 16 μm, respectively. The effect of oxygen concentration on the flame propagation becomes stronger as the percentage of fine particles increases. The effect of fine coal particles on the volatile release rate of coarse particles was analyzed by numerical simulation. The results show that increasing the ratio of fine coal particles shortens the time for volatile matter release from the coarse coal particles and increases the coarse particle temperature.

Flexographic printing of polycarbazole-based inverted solar cells - Alem, Salima; Graddage, Neil; Lu, Jianping; Kololuoma, Terho; Movileanu, Raluca; Tao, Ye (Organic Electronics, 2017)
The mass production of organic photovoltaics requires high throughput processes capable of producing a functional active layer which is homogenous, pinhole free and of a specified thickness. Common methods to achieve this are slot-die coating and gravure printing. We have demonstrated the fabrication of poly(N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole (PCDTBT) based photovoltaic cells using the flexographic printing technique, which enables high throughput patterned active layers to be deposited on flexible substrates at lower cost. This was achieved by optimizing the flexographic plate pattern, print speed, the solvent and the drying process. By incorporating halftone patterning, a common process in the graphics printing industry, and optimizing the printing speed, the homogeneity of the active layer print was significantly improved. Further studies of suitable solvents and drying conditions led to reduced pinhole formation and improved uniformity. The functionality of the flexographically printed active layer was demonstrated by fabrication of 1 cm2 photovoltaic cells which showed an efficiency of up to 3.5%, which is comparable to alternative deposition techniques. These results demonstrate the suitability of flexography as a fabrication technique for bulk heterojunction organic photovoltaics.
Keywords: organic photovoltaics; flexography; printed electronics; PCDTBT

A numerical study on improving the specific properties of staggered composites by incorporating voids - Mirkhalaf, Mohammad; Ashrafi, Behnam (Materials Today Communications, 2017)
Despite being porous, natural materials such as bone, nacre and tooth enamel possess interesting combinations of stiffness, strength and toughness, an outstanding performance which is hard to achieve in engineering materials. Recent studies show that this performance is rooted in their architectures in which stiff and strong inclusions are arranged in a staggered structure and placed within a softer matrix. These studies however focus on void-free staggered composites. Here, we use finite element analysis and exhaustive exploration of the design space to show that the specific modulus and yield strength of staggered composites can be improved by removing the non-load bearing regions of the matrix material and to show the morphologies emerging from this process. This improvement increases with aspect ratio of the inclusions and with mismatch of properties between the phases and decreases with inclusion content. Particularly, 20–30% increase in the specific modulus and 10–20% increase in specific yield strength can be achieved considering the actual properties of carbon nanotube (or ceramic/mineral platelet) reinforced polymers. The morphologies emerging from our exploration can be used to develop lightweight composites of interest in aerospace, defence, and packaging industries.
Keywords: bio-inspiration; staggered composites; void; finite element analysis; specific properties; nanocomposites

A new approach for manufacturing and processing targets to produce 99mTc with cyclotrons - Matei, L.; Mcrae, G.; Galea, R.; Niculae, D.; Craciun, L.; Leonte, R.; Surette, G.; Langille, S.; Louis, C. St.; Gelbart, W.; Abeysekera, B.; Johnson, R. R. (Modern Physics Letters A, 2017)
The most important radioisotope for nuclear medicine is 99mTc. After the supply crisis of 99Mo starting in 2008, the availability of 99mTc became a worldwide concern. Alternative methods for producing the medical imaging isotope 99m 99mTc are actively being developed around the world. The reaction 100 100Mo(p, 2n) 99mTc provides a direct route that can be incorporated into routine production in nuclear medicine centers that possess medical cyclotrons for production of other isotopes, such as those used for Positron Emission Tomography. This paper describes a new approach for manufacturing targets for the (p, 2n) nuclear reaction on 100Mo and the foundation for the subsequent commercial separation and purification of the 99mTc produced. Two designs of targets are presented. The targets used to produce 99mTc are subject to a number of operational constraints.They must withstand the temperatures generated by the irradiation, accommodate temperature gradients from cooling system of the target, must be resilient and must be easily post-processed to separate the 99mTc. After irradiation, the separation of Tc from Mo was carried out using an innovative two-step approach. The process described in this paper can be automated with modules that easily fit in standard production hot cells found in nuclear medicine facilities.
Keywords: 99mTc; cyclotron; target; target processing

The equilibrium liquidus temperatures of rhenium–carbon, platinum–carbon and cobalt–carbon eutectic alloys - Lowe, D. H.; Todd, A. D. W.; Van den Bossche, R.; Bloembergen, P.; Anhalt, K.; Ballico, M.; Bourson, F.; Briaudeau, S.; Campos, J.; Cox, M. G.; Del Campo, D.; Dury, M. R.; et al. (Metrologia, 2017)
The eutectic alloys rhenium–carbon, platinum–carbon and cobalt–carbon have been proposed as reference standards for thermometry, with temperature and uncertainty values specified within the mise en pratique of the definition of the kelvin. These alloys have been investigated in a collaboration of eleven national measurement institutes and laboratories. Published results reported the point-of-inflection in the melting curve with extremely low uncertainties. However, to be considered as standards it is necessary to stipulate what phenomenon a temperature value has been ascribed to; specifically, this should be a thermodynamic state. Therefore, the data have been further evaluated and the equilibrium liquidus temperatures determined based on a consideration of limits and assuming a rectangular probability distribution. The values are: for rhenium–carbon 2747.91  ±  0.44 K, for platinum–carbon 2011.50  ±  0.22 K and for cobalt–carbon 1597.48  ±  0.14 K, with uncertainties at approximately a 95% coverage probability. It is proposed that these values could be used as the basis of thermodynamic temperature measurement at high temperatures (above 1300 K).

A summary of the Planck constant determinations using the NRC Kibble balance - Wood, B. M.; Sanchez, C. A.; Green, R. G.; Liard, J. O. (Metrologia, 2017)
We present a summary of the Planck constant determinations using the NRC watt balance, now referred to as the NRC Kibble balance. The summary includes a reanalysis of the four determinations performed in late 2013, as well as three new determinations performed in 2016. We also present a number of improvements and modifications to the experiment resulting in lower noise and an improved uncertainty analysis. As well, we present a systematic error that had been previously unrecognized and we have quantified its correction. The seven determinations, using three different nominal masses and two different materials, are reanalysed in a manner consistent with that used by the CODATA Task Group on Fundamental Constants (TGFC) and includes a comprehensive assessment of correlations. The result is a Planck constant of 6.626 070 133(60)  ×10−34 Js and an inferred value of the Avogadro constant of 6.022 140 772(55)  ×1023 mol−1. These fractional uncertainties of less than 10−8 are the smallest published to date.

A critical review of the proposed definitions of fundamental chemical quantities and their impact on chemical communities (IUPAC Technical Report) - Marquardt, Roberto; Meija, Juris; Mester, Zoltan; Towns, Marcy; Weir, Ron; Davis, Richard; Stohner, Jürgen (Pure and Applied Chemistry, 2017)
In the proposed new SI, the kilogram will be redefined in terms of the Planck constant and the mole will be redefined in terms of the Avogadro constant. These redefinitions will have some consequences for measurements in chemistry. The goal of the Mole Project (IUPAC Project Number 2013-048-1-100) was to compile published work related to the definition of the quantity ‘amount of substance’, its unit the ‘mole’, and the consequence of these definitions on the unit of the quantity mass, the kilogram. The published work has been reviewed critically with the aim of assembling all possible aspects in order to enable IUPAC to judge the adequateness of the existing definitions or new proposals. Compilation and critical review relies on the broadest spectrum of interested IUPAC members.
Keywords: mole; proposed new SI; redefinition of the kilogram

Solution to redox titration challenge - Michałowski, Tadeusz; Michałowska-kaczmarczyk, Anna Maria; Meija, Juris (Analytical and Bioanalytical Chemistry, 2017)
This article is the solution to the Analytical Challenge to be found at http://link.springer.com/article/10.1007/s00216-016-0020-0
Cet article est la solution au défi analytique qui est trouvé à http://link.springer.com/article/10.1007/s00216-016-0020-0

Benzene and pyridine on silicon (001): a trial ground for long-range corrections in density functional theory - Warschkow, O.; Bennett, J. M.; Miwa, J. A.; Lopinski, G. P.; Rosei, F.; Mckenzie, D. R.; Marks, N. A. (The Journal of Physical Chemistry C, 2017)
The adsorption chemistry of benzene and pyridine on the silicon (001) surface is characterized by two prominent adsorbate configurations: a precursor structure bonded to a single Si–Si dimer and a “tight-bridge” configuration that connects two adjacent dimers. We examine here the performance of 20 density functionals in predicting the relative stability of these two configurations. Discrepancies between the predicted and experimentally observed preferred structures highlight the importance of long-range exact-exchange terms in these adsorbate systems. These terms, however, tend to be detrimental to the prediction of adsorption and activation energies. We discuss this conundrum in terms of systematic exchange-correlation errors that scale with the number of molecule–surface bonds.

Versatile molecular silver ink platform for printed flexible electronics - Kell, Arnold J.; Paquet, Chantal; Mozenson, Olga; Djavani-tabrizi, Iden; Deore, Bhavana; Liu, Xiangyang; Lopinski, Gregory P.; James, Robert; Hettak, Khelifa; Shaker, Jafar; Momciu, Adrian; Ferrigno, Julie; et al. (ACS Applied Materials & Interfaces, 2017)
A silver molecular ink platform formulated for screen, inkjet, and aerosol jet printing is presented. A simple formulation comprising silver neodecanoate, ethyl cellulose, and solvent provides improved performance versus that of established inks, yet with improved economics. Thin, screen-printed traces with exceptional electrical (<10 mΩ/□/mil or 12 μΩ·cm) and mechanical properties are achieved following thermal or photonic sintering, the latter having never been demonstrated for silver-salt-based inks. Low surface roughness, submicron thicknesses, and line widths as narrow as 41 μm outperform commercial ink benchmarks based on flakes or nanoparticles. These traces are mechanically robust to flexing and creasing (less than 10% change in resistance) and bind strongly to epoxy-based adhesives. Thin traces are remarkably conformal, enabling fully printed metal–insulator–metal band-pass filters. The versatility of the molecular ink platform enables an aerosol jet-compatible ink that yields conductive features on glass with 2× bulk resistivity and strong adhesion to various plastic substrates. An inkjet formulation is also used to print top source/drain contacts and demonstrate printed high-mobility thin film transistors (TFTs) based on semiconducting single-walled carbon nanotubes. TFTs with mobility values of ∼25 cm2 V−1 s−1 and current on/off ratios >104 were obtained, performance similar to that of evaporated metal contacts in analogous devices.
Keywords: additive manufacturing; conductive molecular inks; metal organic decomposition (MOD); photosintering; printed flexible electronics

Determination of europium isotope ratios in natural waters by MC-ICP-MS - Arantes de carvalho, Gabriel Gustinelli; Oliveira, Pedro Vitoriano; Yang, Lu (Journal of Analytical Atomic Spectrometry, 2017)
An analytical protocol for the accurate and precise determination of the europium isotope ratio in low level natural waters is presented for the first time by using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). Parameters affecting the separation of Eu from the matrix by employing a single-step column separation with di(2-ethylhexyl) orthophosphoric acid (HDEHP) resin were investigated in detail. Matrix elements (e.g., alkali, alkali-earth and transition metals) were efficiently removed and Eu was quantitatively separated from other rare earth elements (REEs) by sequential elution using gradient HCl concentrations (from 0.25 to 0.75 mol L−1). Fractionation of Eu isotopes in the column was not observed, since quantitative europium recovery (101.2 ± 0.5% mean and 1 SD, n = 3) was obtained (data based on 150 mL SLRS-6 river water CRM test portions spiked with 1.0 ng mL−1 Eu standard solution). A combined standard-sample bracketing with internal normalization method was employed for the mass bias correction, wherein Gd was added to both the sample and standard as an internal standard. The developed method was validated by processing 0.02 ng mL−1 Eu spiked river water CRM SLRS-6 (wherein Eu was removed first by using the above-mentioned column separation method) using the proposed method, and satisfying results (δ151/153Eu value of 0.01 ± 0.02‰; 1 SD) relative to Eu standard solution were obtained. No significant differences were found in the δ151/153Eu values in river water SLRS-6, drinking water AQUA-1 and collected groundwater samples from Brazil, which ranged from −0.07 ± 0.02 to 0.12 ± 0.24 (mean ± 1 SD, n = 5).

Investigation of the size of the incandescent incipient soot particles in premixed sooting and nucleation flames of n -butane using LII, HIM, and 1 nm-SMPS - Betrancourt, Christopher; Liu, Fengshan; Desgroux, Pascale; Mercier, Xavier; Faccinetto, Alessandro; Salamanca, Maurin; Ruwe, Lena; Kohse-höinghaus, Katharina; Emmrich, Daniel; Beyer, André; Gölzhäuser, Armin; Tritscher, Torsten (Aerosol Science and Technology, 2017)
Laser-induced incandescence (LII) measurements were conducted to explore the ability of LII to detect small soot particles of less than 10 nm in two sooting flat premixed flames of n-butane: a so-called nucleation flame obtained at a threshold equivalence ratio Φ = 1.75, in which the incipient soot particles undergo only minor soot surface growth along the flame, and a more sooting flame at Φ = 1.95. Size measurements were obtained by modeling the time-resolved LII signals detected using 1064 nm laser excitation. Spectrally-resolved LII signals collected in the nucleation flame display a similar blackbody-like behavior as mature soot. Soot particle temperature was determined from spectrally-resolved detection. LII modeling was conducted using parameters either relevant to those of mature soot or derived from fitting the modeled results to the experimental LII data. Particle size measurements were also carried out using (1) ex situ analysis by helium-ion microscopy (HIM) of particles sampled thermophoretically and (2) online size distribution analysis of microprobe-sampled particles using a 1 nm-SMPS. The size distributions of the incipient soot particles, found in the nucleation flame and in the early soot region of the Φ = 1.95 flame, derived from time-resolved LII signals are in good agreement with HIM and 1 nm-SMPS measurements and are in the range of 2–4 nm. The thermal and optical properties of incipient soot were found to be not radically different from those of mature soot commonly used in LII modeling. This explains the ability of incipient soot particles to produce continuous thermal emissions in the visible spectrum. This study demonstrates that LII is a promising in situ optical particle sizing technique that is capable of detecting incipient soot as small as about 2.5 nm and potentially 2 nm and resolving small changes in soot sizes below 10 nm.

Relative range error evaluation of terrestrial laser scanners using a plate, a sphere, and a novel dual-sphere-plate target - Muralikrishnan, Bala; Rachakonda, Prem; Lee, Vincent; Shilling, Meghan; Sawyer, Daniel; Cheok, Geraldine; Cournoyer, Luc (Measurement, 2017)
Terrestrial laser scanners (TLS) are a class of 3D imaging systems that produce a 3D point cloud by measuring the range and two angles to a point. The fundamental measurement of a TLS is range. Relative range error is one component of the overall range error of TLS and its estimation is therefore an important aspect in establishing metrological traceability of measurements performed using these systems. Target geometry is an important aspect to consider when realizing the relative range tests. The recently published ASTM E2938-15 mandates the use of a plate target for the relative range tests. While a plate target may reasonably be expected to produce distortion free data even at far distances, the target itself needs careful alignment at each of the relative range test positions. In this paper, we discuss relative range experiments performed using a plate target and then address the advantages and limitations of using a sphere target. We then present a novel dual-sphere-plate target that draws from the advantages of the sphere and the plate without the associated limitations. The spheres in the dual-sphere-plate target are used simply as fiducials to identify a point on the surface of the plate that is common to both the scanner and the reference instrument, thus overcoming the need to carefully align the target.
Keywords: relative range error; terrestrial laser scanner; sphere target; plate target; dual-sphere-plate target

Methods and considerations to determine sphere center from terrestrial laser scanner point cloud data - Rachakonda, Prem; Muralikrishnan, Bala; Cournoyer, Luc; Cheok, Geraldine; Lee, Vincent; Shilling, Meghan; Sawyer, Daniel (Measurement Science and Technology, 2017)
The Dimensional Metrology Group at the National Institute of Standards and Technology is performing research to support the development of documentary standards within the ASTM E57 committee. This committee is addressing the point-to-point performance evaluation of a subclass of 3D imaging systems called terrestrial laser scanners (TLSs), which are laser-based and use a spherical coordinate system. This paper discusses the usage of sphere targets for this effort, and methods to minimize the errors due to the determination of their centers. The key contributions of this paper include methods to segment sphere data from a TLS point cloud, and the study of some of the factors that influence the determination of sphere centers.

Ensemble and single particle fluorescence characterization of dye-labeled cellulose nanocrystals - Leng, Tianyang; Jakubek, Zygmunt J.; Mazloumi, Mahyar; Leung, Alfred C. W.; Johnston, Linda J. (Langmuir, 2017)
Cellulose nanocrystals (CNCs) have been covalently labeled with both fluorescein and rhodamine and studied by a combination of UV–vis absorption spectroscopy and ensemble and single molecule fluorescence spectroscopy. For all samples, the fluorescence anisotropy and lifetimes were consistent with effects expected for covalently bound dye molecules. Low dye loading levels (∼0.1 dye/particle) were estimated for the fluorescein-labeled CNC which coupled with the strong pH dependence make this a less suitable fluorophore for most applications. Rhodamine-labeled CNCs were prepared from both sulfated and carboxylated CNCs and had loading levels that varied from 0.25 to ∼15 dye molecules/CNC. For the sulfated samples, the absorption due to (nonfluorescent) dimeric dye increased with dye loading; in contrast, the carboxylated sample, which had the highest rhodamine content, had a low dimer yield. Single particle fluorescence studies for two of the rhodamine-labeled CNCs demonstrated that individual particles are readily detected by their stepwise blinking/bleaching behavior and by polarization effects. Overall, the results indicate the importance of understanding the effects of loading on dye photophysics to select an optimal dye concentration to maximize sensitivity while minimizing the effect of the dye on the CNC behavior. The results also demonstrate that CNCs with relatively low dye loadings (e.g., ∼1 dye/particle) are readily detectable by fluorescence and should be adequate for use in fluorescence-based biological assays or to probe the distribution of CNCs in composite materials.

Hydrophilic interaction liquid chromatography-tandem mass spectrometry for quantitation of paralytic shellfish toxins: validation and application to reference materials - Thomas, Krista M.; Beach, Daniel G.; Reeves, Kelley L.; Gibbs, Ryan S.; Kerrin, Elliott S.; Mccarron, Pearse; Quilliam, Michael A. (Analytical and Bioanalytical Chemistry, 2017)
Paralytic shellfish toxins (PSTs) are potent neurotoxins produced by marine dinoflagellates that are responsible for paralytic shellfish poisoning (PSP) in humans. This work highlights our ongoing efforts to develop quantitative methods for PSTs using hydrophilic interaction liquid chromatography-tandem mass spectrometry (HILIC-MS/MS). Compared with the commonly used method of liquid chromatography with post-column oxidation and fluorescence detection (LC-ox-FLD), HILIC-MS/MS has the potential of being more robust, sensitive and straightforward to operate, and provides unequivocal confirmation of toxin identity. The main driving force for the present work was the need for a complementary method to LC-ox-FLD to assign values to shellfish tissue matrix reference materials for PSTs. Method parameters that were optimized included LC mobile and stationary phases, electrospray ionization (ESI) conditions, and MS/MS detection parameters. The developed method has been used in the detection and identification of a wide range of PSTs including less common analogues and metabolites in a range of shellfish and algal samples. We have assessed the matrix effects of shellfish samples and have evaluated dilution, standard addition and matrix matched calibration as means of mitigating them. Validation on one LC-MS/MS system for nine common PST analogues (GTX1-4, dcGTX2&3, STX, NEO, and dcSTX) was completed using standard addition. The method was then transferred to a more sensitive LC-MS/MS system, expanded to include five more PSTs (C1&2, dcNEO and GTX5&6) and validated using matrix matched calibration. Limits of detection of the validated method ranged between 6 and 280 nmol/kg tissue using standard addition in extracts of blue mussels, with recoveries between 92 and 108%. Finally, this method was used in combination with the AOAC Official Method based on LC-ox-FLD to measure PSTs in a new mussel tissue matrix reference material.
Keywords: hydrophilic interaction liquid chromatography; mass spectrometry; algal toxins; paralytic shellfish poisoning; reference material

Determination of cyanocobalamin by isotope dilution LC-MS/MS - D'ulivo, Lucia; Yang, Lu; Ding, Jianfu; Pagliano, Enea; Leek, Donald M.; Thibeault, Marie-Pier; Mester, Zoltán (Analytica Chimica Acta, 2017)
Cyanocobalamin (CNCbl) is an active form of vitamin B12, commonly employed for the preparation of multivitamin supplements and fortified food. In this study, we present a novel analytical method for its determination based on stable isotope dilution liquid chromatography electrospray tandem mass spectrometry (ID LC-MS/MS). Isotopically enriched 13C15NCbl was synthesized in-house and used as internal standard. The method was validated using NIST SRM 3280 multivitamin reference material and by comparison with an independent methodology based on LC-ICPMS. The proposed method provided a detection limit of 57 pg/g and could be applied for the determination of trace level of CNCbl in multivitamin supplements with a relative standard uncertainty better than 3%. The novel ID LC-MS/MS is a primary ratio method that could become a reference for CNCbl determination in multivitamins and food supplements. The method was applied for the characterization of two NRC multivitamin tablet Certified Reference Material (CRM) candidates, VITA-1 and VITB-1 whose CNCbl levels were quantified as 2.64 ± 0.09 and 1.75 ± 0.12 μg/g, respectively.
Keywords: cyanocobalamin; isotope dilution; liquid chromatography mass spectrometry; multivitamins

Experimental assessment of the sudden-reversal of the oxygen dilution effect on soot production in coflow ethylene flames - Wang, Qianlong; Legros, Guillaume; Bonnety, Jérôme; Morin, Céline; Matynia, Alexis; Consalvi, Jean-Louis; Liu, Fengshan (Combustion and Flame, 2017)
Keywords: soot; soot temperature; soot volume fraction; oxygen addition; carbon dioxide dilution

High-purity semiconducting single-walled carbon nanotubes: a key enabling material in emerging electronics - Lefebvre, Jacques; Ding, Jianfu; Li, Zhao; Finnie, Paul; Lopinski, Gregory; Malenfant, Patrick R. L. (Accounts of Chemical Research, 2017)
Semiconducting single-walled carbon nanotubes (sc-SWCNTs) are emerging as a promising material for high-performance, high-density devices as well as low-cost, large-area macroelectronics produced via additive manufacturing methods such as roll-to-roll printing. Proof-of-concept demonstrations have indicated the potential of sc-SWCNTs for digital electronics, radiofrequency circuits, radiation hard memory, improved sensors, and flexible, stretchable, conformable electronics. Advances toward commercial applications bring numerous opportunities in SWCNT materials development and characterization as well as fabrication processes and printing technologies.

Resonant indirect optical absorption in germanium - Menéndez, José; Noël, Mario; Zwinkels, Joanne C.; Lockwood, David J. (Physical Review B, 2017)
The optical absorption coefficient of pure Ge has been determined from high-accuracy, high-precision optical measurements at photon energies covering the spectral range between the indirect and direct gaps. The results are compared with a theoretical model that fully accounts for the resonant nature of the energy denominators that appear in perturbation-theory expansions of the absorption coefficient. The model generalizes the classic Elliott approach to indirect excitons, and leads to a predicted optical absorption that is in excellent agreement with the experimental values using just a single adjustable parameter: the average deformation potential DΓL coupling electrons at the bottom of the direct and indirect valleys in the conduction band. Remarkably, the fitted value, DΓL=4.3×108eV/cm, is in nearly perfect agreement with independent measurements and ab initio predictions of this parameter, confirming the validity of the proposed theory, which has general applicability.

Assessment of several gas radiation models for radiative heat transfer calculations in a three-dimensional oxy-fuel furnace under coal-fired conditions - Kez, V.; Consalvi, J. L.; Liu, F.; Ströhle, J.; Epple, B. (International Journal of Thermal Sciences, 2017)
Oxy-fuel coal combustion is a promising Carbon Capture and Storage technology that allows retro-fitting of existing power plants. Due to high concentrations of CO2 and H2O and the strong and irregular spectral variation of their absorption coefficients, prediction of radiative heat transfer in oxy-fuel combustion systems requires a non-grey gas radiation model. Several models, including narrow-band correlated-k (NBCK), wide-band correlated-k (WBCK), full-spectrum correlated-k (FSCK), and weighted-sum-of-grey-gases (WSGG) models, were used to predict radiative heat transfer by CO2 and H2O in a three-dimensional real-size virtual coal-fired furnace under air- and oxy-fuel (dry and wet flue-gas recycle) conditions. The best agreement with the benchmark solution calculated by the NBCK model with the updated EM2C parameters is achieved by the FSCK model. The WBCK model is less accurate. The WSGG parameter sets of Kangwanpongpan et al. (2012) and Bordbar et al. (2014) are most suited for oxy-fuel combustion among the six sets considered. The FSCK model offers the best performance in terms of both accuracy and computational efficiency among the considered gas radiation models and is recommended for CFD simulations of real-sized oxy-coal systems.
Keywords: oxy-fuel combustion; non-grey gas radiation models; NBCK; WBCK; FSCK; WSGG

Photochemical vapor generation: a radical approach to analyte introduction for atomic spectrometry - Sturgeon, Ralph E. (Journal of Analytical Atomic Spectrometry, 2017)
Photochemical vapor generation (PVG) is the newest subset of widely used vapor generation techniques to be coupled to atomic and mass spectrometries to provide enhanced analyte introduction efficiency. Improved detection power, minimization of potential spectral interferences and the promise of green chemistry serve as additional drivers. PVG has been successfully applied to the conventional suite of elements typically amenable to chemical vapor generation, such as As, Sb, Sn, Bi, Se, Te, Hg and Pb, as well as transition metals (Cd, Fe, Co, Ni and Os) and non-metals (I and Br). This tutorial provides an overview of developments and applications since its inception in 2003, including consideration of needed hardware (UV photochemical reactor and phase separator designs), reaction mechanisms and products, interferences, as well as benefits and short-comings. While significant advances have been made over the past decade in expanding the scope of elements amenable to PVG, the way forward demands elucidation of reaction mechanisms to support optimization, enhance prediction power and provide comprehension and control of potential interferences. In this connection, speculations on ultimate limitations, needed developments and future outlook are also presented. More applications to real-world samples are needed to sustain interest in the field and elicit further investment of research.

Glass chamber method for screening of 4,4′-MDI and TCPP emissions from foam joint sealant - Won, Doyun; Zidek, Angelika; Nong, Gang; Lusztyk, Ewa (Developing Consensus Standards for Measuring Chemical Emissions from Spray Polyurethane Foam (SPF) Insulation, 2017)
One-component foam joint sealant is widely used to seal air leaks by homeowners. Various chemicals can be emitted from a foam joint sealant. The goal of this study was to develop a glass chamber method to examine the emissions of 4,4′-methylenediphenyl diisocyanate (4,4′-MDI) and tris(2-chloroisopropyl)phosphate (TCPP) from foam joint sealants. The concentrations of 4,4′-MDI and TCPP were measured during a 24-h chamber test that involved a 3-L chamber operated at 40°C, 20 % relative humidity (RH), 22.2 air changes per hour, and 2 sampling media (glass filter coated with 9-methylaminomethyl anthracene for 4,4′-MDI and sorbent tube filled with Tenax® TA for TCPP). The 4,4′-MDI concentration peaked within 11 min and decayed to below the lowest limit of quantification within 1 h. The TCPP concentration reached a maximum value at approximately 4 h and decayed relatively slowly or stayed almost constant afterward. The 4,4′-MDI concentration after applying foam joint sealant to all the windows of a small house was predicted to be much lower than the reference value of 0.6 μg/m3 by the U.S. Environmental Protection Agency. Conversely, the higher predicted concentrations of TCPP than the measured indoor levels may imply the potential of foam joint sealants as an important source of TCPP in homes. In addition, the test with 4,4′-MDI for method optimization showed that the effect of environmental factors (temperature and RH) as well as the sink effect by interior surfaces could be significant. When a test method is standardized for 4,4′-MDI emissions, these influential factors should be investigated.
Keywords: 4,4′-methylenediphenyl diisocyanate; tris(2-chloroisopropyl)phosphate; one-component foam joint sealant; chamber method; CAS No. 101-68-8; CAS No. 13674-84-5

Glass chamber method for screening of 4,4′-MDI and TCPP emissions from foam joint sealant - Won, Doyun; Zidek, Angelika; Nong, Gang; Lusztyk, Ewa (Developing Consensus Standards for Measuring Chemical Emissions from Spray Polyurethane Foam (SPF) Insulation, 2017)
One-component foam joint sealant is widely used to seal air leaks by homeowners. Various chemicals can be emitted from a foam joint sealant. The goal of this study was to develop a glass chamber method to examine the emissions of 4,4′-methylenediphenyl diisocyanate (4,4′-MDI) and tris(2-chloroisopropyl)phosphate (TCPP) from foam joint sealants. The concentrations of 4,4′-MDI and TCPP were measured during a 24-h chamber test that involved a 3-L chamber operated at 40°C, 20 % relative humidity (RH), 22.2 air changes per hour, and 2 sampling media (glass filter coated with 9-methylaminomethyl anthracene for 4,4′-MDI and sorbent tube filled with Tenax® TA for TCPP). The 4,4′-MDI concentration peaked within 11 min and decayed to below the lowest limit of quantification within 1 h. The TCPP concentration reached a maximum value at approximately 4 h and decayed relatively slowly or stayed almost constant afterward. The 4,4′-MDI concentration after applying foam joint sealant to all the windows of a small house was predicted to be much lower than the reference value of 0.6 μg/m3 by the U.S. Environmental Protection Agency. Conversely, the higher predicted concentrations of TCPP than the measured indoor levels may imply the potential of foam joint sealants as an important source of TCPP in homes. In addition, the test with 4,4′-MDI for method optimization showed that the effect of environmental factors (temperature and RH) as well as the sink effect by interior surfaces could be significant. When a test method is standardized for 4,4′-MDI emissions, these influential factors should be investigated.
Keywords: 4,4′-methylenediphenyl diisocyanate; tris(2-chloroisopropyl)phosphate; one-component foam joint sealant; chamber method; CAS No. 101-68-8; CAS No. 13674-84-5

Importance of correlation between reverberation times for calculating the uncertainty of measurements according to ISO 354 and ISO 17497-1 - Müller-trapet, Markus (The Journal of the Acoustical Society of America, 2017)
The calculation of measurement uncertainties follows the law of error propagation as described in the Guide to the Expression of Uncertainty in Measurements (GUM). The result can be expressed as a contribution of the variances of the individual input quantities and an additional term related to the correlation between the input quantities. In practical applications, the correlations are usually neglected. This has, e.g., led to the expression included in Annex A of ISO 17497-1 to calculate the precision of the measurement of random-incidence scattering coefficients. To determine whether it is actually justified to neglect the input correlations, this contribution investigates the correlations between the reverberation times used to determine the random-incidence absorption coefficient (ISO 354) and scattering coefficient (ISO 17497-1) in a reverberation chamber. The data used here are taken from measurements in a real-scale and a small-scale reverberation chamber. It is found that for ISO 354 correlations can be neglected. However, for ISO 17497-1, it is important to take correlations into account to obtain the correct measurement uncertainty using error propagation.

Enhancing egress drills: preparation and assessment of evacuee performance - Gwynne, S. M. V.; Kuligowski, E. D.; Boyce, K. E.; Nilsson, D.; Robbins, A. P.; Lovreglio, R.; Thomas, J. R.; Roy-poirier, A. (Fire and Materials, 2017)
This article explores how egress drills – specifically those related to fire incidents - are currently employed, their impact on safety levels, and the insights gained from them. It is suggested that neither the merits of egress drills are well understood, nor the impact on egress performance well characterized. In addition, the manner in which they are conducted varies both between and within regulatory jurisdictions. By investigating their strengths and limitations, this article suggests opportunities for their enhancement possibly through the use of other egress models to support and expand upon the benefits provided.It is by no means suggested that drills are not important to evacuation safety – only that their inconsistent use and the interpretation of the results produced may mean we (as researchers, practitioners, regulators and stakeholders) are not getting the maximum benefit out of this important tool.

Regional variation in wood density and modulus of elasticity of Quebec's main boreal tree species - Giroud, Guillaume; Bégin, Jean; Defo, Maurice; Ung, Chhun-Huor (Forest Ecology and Management, 2017)
Regional variation in wood density and modulus of elasticity (MOE) for the main boreal softwoods (black spruce, balsam fir, jack pine) and hardwoods (paper birch, trembling aspen) of Quebec, Canada, were estimated using near-infrared spectroscopy on 30,159 increment cores from 10,573 inventory plots. An automated near-infrared system was developed for this purpose and calibrated using SilviScan data. Large-scale spatial dependence in wood density and MOE was observed. On average, observations were spatially autocorrelated on longer distances in hardwoods (136–157 km) than softwoods (65–74 km). Overall wood density and MOE increased with temperature and precipitation regardless of species. In addition, a uniform latitudinal gradient related to climate was observed in paper birch and trembling aspen. Conversely, spatial distribution in wood density and MOE was not uniform in softwoods, suggesting a more limited environmental adaptability in comparison to the hardwood species studied. The natural variability of wood density and MOE in these species is now known for the study area. Regional estimates are thus available for various decision-making processes related to forest management, wood allocation, timber market value, protection priorities in firefighting and insect pest control, and forest carbon estimation.

Gel-gel phase separation within milk sphingomyelin domains revealed at the nanoscale using atomic force microscopy - Guyomarc’h, Fanny; Chen, Maohui; Et-Thakafy, Oumaima; Zou, Shan; Lopez, Christelle (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2017)
The milk sphingomyelin (MSM) is involved in the formation of ordered lipid domains in the biological milk fat globule membrane (MFGM), where it accounts for about 30%wt of the polar lipids. Moreover, MSM exhibits a large variety in saturated acyl chain lengths (from C16:0 to C24:0-SM) compared to other natural sphingomyelins, which may impact the packing of MSM molecular species in the gel phase domains and the topography of the MFGM. To investigate this, supported lipid bilayers of synthetic sphingomyelins or of MSM-containing mixtures, including a MFGM polar lipid extract, were imaged at temperatures below the Tm of MSM (i.e. < 34 °C for which MSM is in the gel phase) in hydrated conditions using atomic force microscopy. In all compositions containing MSM, the MSM-rich gel phase domains exhibited lower and upper height levels H, interpreted as two distinct gel phases with ∆ H ~ 0.5–1.1 nm. Two (lower and upper) gel phases were also found for pure C24:0-SM bilayers or for bilayers of a C16:0-SM/C24:0-SM equimolar mixture, while C16:0-SM bilayers were uniformly flat and less thick than C24:0-SM bilayers. The upper gel phase of MSM-containing bilayers was interpreted as mixed interdigitated C24:0-SM molecules, while the lower gel phase was attributed both to fully interdigitated C24:0-SM molecules and non-interdigitated C16:0-SM molecules. These results show that the composition of natural sphingomyelins, inducing a mismatch between the d18:1 sphingosine and the acyl chains, is important in both the internal organization and the topography of biological membranes, especially that of the MFGM. This organization could be involved in specific biological functions, e.g. the insertion of proteins.
Keywords: milk sphingomyelin; phase separation; membrane topography; chain interdigitation; lipid domain

Absolute frequency measurement of the 88Sr+ clock transition using a GPS link to the SI second - Dubé, Pierre; Bernard, John E.; Gertsvolf, Marina (Metrologia, 2017)
We report the results of a recent measurement of the absolute frequency of the 5s2 S1/2 – 4d2 D5/2 transition of the 88Sr + ion. The optical frequency was measured against the international atomic time realization of the SI second on the geoid as obtained by frequency transfer using a global positioning system link and the precise point positioning technique. The measurement campaign yielded more than 100 h of frequency data. It was performed with improvements to the stability and accuracy of the single-ion clock compared to the last measurement made in 2012. The single ion clock uncertainty is evaluated at 1.5 x 10(-17) when contributions from acousto-optic modulator frequency chirps and servo errors are taken into account. The stability of the ion clock is 3 x 10(-15) at 1 s averaging, a factor of three better than in the previous measurement. The results from the two measurement campaigns are in good agreement. The uncertainty of the measurement, primarily from the link to the SI second, is 0.75 Hz (1.7 x 10(-15)). The frequency measured for the S–D clock transition of 88Sr + is Vo = 444779044095485.27(75)Hz.
Keywords: absolute frequency measurement; single-ion clock; optical atomic clock; high-resolution spectroscopy

A simple dendrimer-aptamer based microfluidic platform for E. coli O157:H7 detection and signal intensification by rolling circle amplification - Jiang, Yuqian; Zou, Shan; Cao, Xudong (Sensors and Actuators B: Chemical, 2017)
The majority of foodborne illnesses and deaths are caused by pathogenic bacteria. Therefore there is an increasingly urgent need for rapid, sensitive and cost-effective detection methods in order to avoid or to respond to outbreaks of such diseases in a timely manner. In an attempt to develop a simple and sensitive fluorescence intensity based microfluidic detection platform, PAMAM dendrimer was immobilized onto PDMS microchannel that was further modified with DNA aptamers for detections of E. coli O157:H7 cells. To further improve detection performance, rolling circle amplification (RCA) was employed to enhance the fluorescence signals. In addition, RCA products were characterized by both agarose gel electrophoresis and atomic force microscopy. Our results showed that RCA was able to enhance detection signals by up to 50 times and that the limit of detection of the system was reduced to 102 cells/mL with excellent detection specificities. Therefore, it can be concluded that this simple dendrimer-aptamer based microfluidic detection platform with RCA signal enhancement is a promising method for rapid and sensitive detection for foodborne pathogenic bacteria.
Keywords: signal amplification; lab-on-a-chip; microfluidic device; dendrimer; aptamer; AFM

Probing intermediates of the induction period prior to nucleation and growth of semiconductor quantum dots - Liu, Mingyang; Wang, Kun; Wang, Linxi; Han, Shuo; Fan, Hongsong; Rowell, Nelson; Ripmeester, John A.; Renoud, Romain; Bian, Fenggang; Zeng, Jianrong; Yu, Kui (Nature Communications, 2017)
Little is known about the induction period before the nucleation and growth of colloidal semiconductor quantum dots. Here, we introduce an approach that allows us to probe intermediates present in the induction period. We show that this induction period itself exhibits distinct stages with the evolution of the intermediates, first without and then with the formation of covalent bonds between metal cations and chalcogenide anions. The intermediates are optically invisible in toluene, while the covalent-bonded intermediates become visible as magic-size clusters when a primary amine is added. Such evolution of magic-size clusters provides indirect but compelling evidence for the presence of the intermediates in the induction period and supports the multi-step nucleation model. Our study reveals that magic-size clusters could be readily engineered in a single-size form, and suggests that the existence of the intermediates during the growth of conventional quantum dots results in low product yield.

ICP OES determination of contaminant elements leached from food packaging films - Santos, Éder José Dos; Oliveira, Fernanda Mara Pimentel; Herrmann, Amanda Beatriz; Sturgeon, Ralph Edward (Brazilian Archives of Biology and Technology, 2017)
Determination of potential contaminants elements in food packing films arising from contact with acidic aqueous foods was undertaken by inductively coupled plasma optical emission spectrometry (ICP OES) in accordance with DIN EN 1186-1. Test sections from plastic films were totally immersed in 3% w/v CH3COOH used as the food simulant. Testing was conducted under three conditions: (1) 10 days at 40 ºC; (2) 30 min at 70 ºC and 10 days at 40 ºC; and (3) 30 min at 100 ºC and 10 days at 40 ºC. These time and temperature conditions were considered to be the most severe situations likely to be encountered in practice. Several different containers were investigated, including a borosilicate glass beaker, a glass bottle used for food canning, as well as one of polystyrene. The glass bottle was selected for testing treatments according to procedure (3) and a polystyrene one was chosen for use with procedures (1) and (2). Limits of quantitation were adequate for the determination of Ag, B, Ba, Cd, Cr, Cu, Pb, Sb, Sn and Zn by solution nebulization ICP OES and As by chemical vapor generation (CVG-ICP OES). Results for the analysis of AccuStandard certified reference materials as well as spike recoveries show good agreement with expected concentrations, demonstrating the accuracy and precision of the determinations. Eleven samples of food packing material were analyzed. The lead was present in the range 4.8 - 85.3 µg L-1 in 10 of 11 evaluated packing material, showing the importance of quality control measures.
Keywords: food packaging; ICP OES; contaminant elements

Stephanine from Stephania venosa (Blume) spreng showed effective antiplasmodial and anticancer activities, the latter by inducing apoptosis through the reverse of mitotic exit - Le, Phuong Mai; Srivastava, Vandana; Nguyen, Thanh Tam; Pradines, Bruno; Madamet, Marylin; Mosnier, Joel; Trinh, Thi Thuy; Lee, Hoyun (Phytotherapy Research, 2017)
Extracts from the tubers of Stephania venosa (Blum) Spreng growing in Vietnam significantly inhibited cell proliferation against a number of cancer cells including HeLa, MDA-MB231 and MCF-7 cells. A bioassay-guided fractionation led to the isolation of four aporphine and one tetrahydroprotoberberine alkaloids: dehydrocrebanine 1, tetrahydropalmatine 2, stephanine 3, crebanine 4 and O-methylbulbocapnine 5. The characterization of these compounds was based on MS, NMR and published data. A study by structure–bioactivity relationship on these isolates showed that stephanine is the most active compound. Cell biological studies showed that stephanine induces the reverse of mitotic exit, eventually leading to cell death by apoptosis. This data suggests that stephanine has a unique mode of cell-killing activity against cancer cells, which is seldom observed with known synthetic compounds. In addition to its anticancer property, our data from an in vitro study showed that S. venosa also possesses effective antiplasmodial activity and stephanine was also the most interesting compound but is the most cytotoxic with the lowest selectivity index.

Landau-Zener-Stückelberg interferometry in quantum dots with fast rise times: evidence for coherent phonon driving - Korkusinski, M.; Studenikin, S. A.; Aers, G.; Granger, G.; Kam, A.; Sachrajda, A. S. (Physical Review Letters, 2017)
Manipulating qubits via electrical pulses in a piezoelectric material such as GaAs can be expected to generate incidental acoustic phonons. In this Letter we determine theoretically and experimentally the consequences of these phonons for semiconductor spin qubits using Landau-Zener-Stückelberg interferometry. Theoretical calculations predict that phonons in the presence of the spin-orbit interaction produce both phonon-Rabi fringes and accelerated evolution at the singlet-triplet anticrossing. Observed features confirm the influence of these mechanisms. Additionally, evidence is found that the pulsed gates themselves act as phonon cavities increasing the influence of phonons under specific resonant conditions.

Manipulation of a nuclear spin by a magnetic domain wall in a quantum hall ferromagnet - Korkusinski, M.; Hawrylak, P.; Liu, H. W.; Hirayama, Y. (Scientific Reports, 2017)
The manipulation of a nuclear spin by an electron spin requires the energy to flip the electron spin to be vanishingly small. This can be realized in a many electron system with degenerate ground states of opposite spin polarization in different Landau levels. We present here a microscopic theory of a domain wall between spin unpolarized and spin polarized quantum Hall ferromagnet states at filling factor two with the Zeeman energy comparable to the cyclotron energy. We determine the energies and many-body wave functions of the electronic quantum Hall droplet with up to N = 80 electrons as a function of the total spin, angular momentum, cyclotron and Zeeman energies from the spin singlet ν = 2 phase, through an intermediate polarization state exhibiting a domain wall to the fully spin-polarized phase involving the lowest and the second Landau levels. We demonstrate that the energy needed to flip one electron spin in a domain wall becomes comparable to the energy needed to flip the nuclear spin. The orthogonality of orbital electronic states is overcome by the many-electron character of the domain - the movement of the domain wall relative to the position of the nuclear spin enables the manipulation of the nuclear spin by electrical means.

Demonstration of a compressive-sensing Fourier-transform on-chip spectrometer - Podmore, Hugh; Scott, Alan; Cheben, Pavel; Velasco, Aitor V.; Schmid, Jens H.; Vachon, Martin; Lee, Regina (Optics Letters, 2017)
We demonstrate compressive-sensing (CS) spectroscopy in a planar-waveguide Fourier-transform spectrometer (FTS) device. The spectrometer is implemented as an array of Mach–Zehnder interferometers (MZIs) integrated on a photonic chip. The signal from a set of MZIs is composed of an undersampled discrete Fourier interferogram, which we invert using l1-norm minimization to retrieve a sparse input spectrum. To implement this technique, we use a subwavelength-engineered spatial heterodyne FTS on a chip composed of 32 independent MZIs. We demonstrate the retrieval of three sparse input signals by collecting data from restricted sets (8 and 14) of MZIs and applying common CS reconstruction techniques to this data. We show that this retrieval maintains the full resolution and bandwidth of the original device, despite a sampling factor as low as one-fourth of a conventional (non-compressive) design.

Consequences of spin-orbit coupling at the single hole level: spin-flip tunneling and the anisotropic g factor - Bogan, A.; Studenikin, S. A.; Korkusinski, M.; Aers, G. C.; Gaudreau, L.; Zawadzki, P.; Sachrajda, A. S.; Tracy, L. A.; Reno, J. L.; Hargett, T. W. (Physical Review Letters, 2017)
Hole transport experiments were performed on a gated double quantum dot device defined in a p-GaAs/AlGaAs heterostructure with a single hole occupancy in each dot. The charging diagram of the device was mapped out using charge detection confirming that the single hole limit is reached. In that limit, a detailed study of the two-hole spin system was performed using high bias magnetotransport spectroscopy. In contrast to electron systems, the hole spin was found not to be conserved during interdot resonant tunneling. This allows one to fully map out the two-hole energy spectrum as a function of the magnitude and the direction of the external magnetic field. The heavy-hole g factor was extracted and shown to be strongly anisotropic, with a value of 1.45 for a perpendicular field and close to zero for an in-plane field as required for hybridizing schemes between spin and photonic quantum platforms.

Ultra-slow light propagation by self-induced transparency in ruby in the superhyperfine limit - Riesen, Hans; Rebane, Aleksander; Rajan, Rajitha Papakutty; Hutchison, Wayne; Ganschow, Steffen; Szabo, Alex (Optics Letters, 2017)
Self-induced transparency is reported for circularly polarized light in the R1(−3/2) line of a 30 ppm ruby (3α-Al2O3:Cr3+) at 1.7 K in a magnetic field of B‖c=4.5  T. In such a field and temperature, a 30 ppm ruby is in the so-called superhyperfine limit resulting in a long phase memory time, TM=50  μs, and a thousand-fold slower pulse propagation velocity of ∼300  m/s was observed, compared to the ∼300  km/s measured in the first observation of self-induced transparency (SIT) ∼50 years ago, that employed a ruby with a 500 ppm chromium concentration in zero field and at 4.2 K. To date, this is the slowest pulse propagation ever observed in a SIT experiment.

Multi-layered fabrication of large area PDMS flexible optical light guide sheets - Green, Robert; Knopf, George K.; Bordatchev, Evgueni V. (Organic Photonic Materials and Devices XIX, 2017)
Large area polydimethylsiloxane (PDMS) flexible optical light guide sheets can be used to create a variety of passive light harvesting and illumination systems for wearable technology, advanced indoor lighting, non-planar solar light collectors, customized signature lighting, and enhanced safety illumination for motorized vehicles. These thin optically transparent micro-patterned polymer sheets can be draped over a flat or arbitrarily curved surface. The light guiding behavior of the optical light guides depends on the geometry and spatial distribution of micro-optical structures, thickness and shape of the flexible sheet, refractive indices of the constituent layers, and the wavelength of the incident light. A scalable fabrication method that combines soft-lithography, closed thin cavity molding, partial curing, and centrifugal casting is described in this paper for building thin large area multi-layered PDMS optical light guide sheets. The proposed fabrication methodology enables the of internal micro-optical structures (MOSs) in the monolithic PDMS light guide by building the optical system layer-by-layer. Each PDMS layer in the optical light guide can have the similar, or a slightly different, indices of refraction that permit total internal reflection within the optical sheet. The individual molded layers may also be defect free or micro-patterned with microlens or reflecting micro-features. In addition, the bond between adjacent layers is ensured because each layer is only partially cured before the next functional layer is added. To illustrate the scalable build-by-layers fabrication method a three-layer mechanically flexible illuminator with an embedded LED strip is constructed and demonstrated.
Keywords: flexible large area optical light guide; polydimethylsiloxane (PDMS); micromachining; micro-optical features; soft lithography

Experimental analysis of laser and scanner control parameters during laser polishing of H13 steel - Miller, Joshua D.; Tutunea-Fatan, O. Remus; Bordatchev, Evgueni V. (Procedia Manufacturing, 2017)
Laser polishing is a manufacturing process in which a small amount of material is melted via laser irradiation and molten pool is then redistributed to create a smoother surface finish/superior surface quality. The focus of this study is to generate more comprehensive understanding of the effects that laser and scanner control parameters have on the formation of laser polished lines. A parameter known as “Laser On/Off delay” is varied along with the laser power to study the impact that these parameters have on the synchronization between laser power and beam scanning velocity. It was determined through experimental analysis that the “Laser On delay” parameter plays a significant role on the formation of the laser polished lines, essentially in a region that is outside to the widely characterized “steady state” zone of constant track width. A set of experiments was conducted to identify the combined effect of transient (acceleration/deceleration) phases for laser power and speed on the terminal geometry of the polished line. When the optimal transient combination of power and speed was used, surface quality improvement by 83% (areal surface roughness (Sa) reduction from 1.35 μm to 0.23 μm) was obtained.
Keywords: laser polishing; line formation; surface quality; laser-on-delay; synchronization control

Thermo-physical modelling of track width during laser polishing of H13 tool steel - Mohajerani, Shirzad; Miller, Joshua D.; Tutunea-Fatan, O. Remus; Bordatchev, Evgueni V. (Procedia Manufacturing, 2017)
A three-dimensional CFD model has been developed to predict track width during laser polishing (LP) of H13 tool steel. The developed model incorporates several different mechanisms for heat transfer such as conduction, convection, and radiation as well as temperature dependencies for relevant material properties. Experimental calibration was carried out to obtain adequate absorptivity value. After performing the mesh-sensitivity assessment, simulation results have been validated against experimental data. The relatively low errors obtained suggest that the developed model is capable to accurately describe the effect of process parameters on molten pool dimensions and/or geometry.
Keywords: laser polishing; thermo-physical model; numerical simulation; experimental calibration

Continuous-wave lasing in colloidal quantum dot solids enabled by facet-selective epitaxy - Fan, Fengjia; Voznyy, Oleksandr; Sabatini, Randy P.; Bicanic, Kristopher T.; Adachi, Michael M.; Mcbride, James R.; Reid, Kemar R.; Park, Young-shin; Li, Xiyan; Jain, Ankit; Quintero-bermudez, Rafael; Saravanapavanantham, Mayuran; et al. (Nature, 2017)
Keywords: quantum dots; electronics; photonics and device physics; lasers; LEDs and light sources

Broadband high-efficiency zero-order surface grating coupler for the near- and mid-infrared wavelength ranges - Sánchez-postigo, Alejandro; Wangüemert-pérez, J. Gonzalo; Luque-gonzález, José manuel; Molina-fernández, Íñigo; Cheben, Pavel; Alonso-ramos, Carlos A.; Halir, Robert; Schmid, Jens H.; Ortega-moñux, Alejandro; Cheben, Pavel; Čtyroký, Jiří; Molina-fernández, Iñigo (Integrated Optics: Physics and Simulations III, 2017)
Efficient coupling of light from a chip into an optical fiber is a major issue in silicon photonics, as the dimensions of high-index-contrast photonic integrated waveguides are much smaller than conventional fiber diameters. Surface grating couplers address the coupling problem by radiating the optical power from a waveguide through the surface of the chip to the optical fiber, or vice versa. However, since the grating radiation angle substantially varies with the wavelength, conventional surface grating couplers cannot offer high coupling efficiency and broad bandwidth simultaneously. To overcome this limitation, for the near-infrared band we have recently proposed SOI-based zero-order grating couplers, which, making use of a subwavelength-engineered waveguide and a high-index prism, suppress the explicit dependence between the radiation angle and the wavelength, achieving a 1-dB bandwidth of 126 nm at λ = 1.55 μm. However, in the near-infrared, the bandwidth enhancement of zero-order grating couplers is limited by the effective index wavelength dispersion of the grating. In the mid-infrared spectral region, the waveguide dispersion is lower, alleviating the bandwidth limitation. Here we demonstrate numerically our zero-order grating coupler concept in the mid-infrared at λ = 3.8 μm. Several couplers for the silicon-on-insulator and the germanium-on-silicon nitride platforms are designed and compared, with subdecibel coupling efficiencies and 1-dB bandwidths up to ~680 nm.

Disorder effects in subwavelength grating metamaterial waveguides - Ortega-Moñux, Alejandro; Čtyroký, Jiří; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Molina-Fernández, Íñigo; Halir, Robert (Optics Express, 2017)
Subwavelength grating (SWG) waveguides are integrated photonic structures with a pitch substantially smaller than wavelength for which they are designed, so that diffraction effects are suppressed. SWG operates as an artificial metamaterial with an equivalent refractive index which depends on the geometry of the structure and the polarization of the propagating wave. SWG waveguides have been advantageously used in silicon photonics, resulting in significant performance improvements for many practical devices, including highly efficient fiber-chip couplers, waveguide crossings, broadband multimode interference (MMI) couplers, evanescent field sensors and polarization beam splitters, to name a few. Here we present a theoretical and experimental study of the influence of disorder effects in SWG waveguides. We demonstrate via electromagnetic simulations and experimental measurements that even a comparatively small jitter (~5 nm) in the position and size of the SWG segments may cause a dramatic reduction in the transmittance for wide (multimode) SWG waveguides, while for narrow (single mode) waveguides this effect is negligible. Our study shows that the impact of the jitter on SWG waveguide performance is directly related to the modal confinement.

Entanglement distribution schemes employing coherent photon-to-spin conversion in semiconductor quantum dot circuits - Gaudreau, Louis; Bogan, Alex; Korkusinski, Marek; Studenikin, Sergei; Austing, D guy; Sachrajda, Andrew s (Semiconductor Science and Technology, 2017)
Long distance entanglement distribution is an important problem for quantum information technologies to solve. Current optical schemes are known to have fundamental limitations. A coherent photon-to-spin interface built with quantum dots (QDs) in a direct bandgap semiconductor can provide a solution for efficient entanglement distribution. QD circuits offer integrated spin processing for full Bell state measurement (BSM) analysis and spin quantum memory. Crucially the photo-generated spins can be heralded by non-destructive charge detection techniques. We review current schemes to transfer a polarization-encoded state or a time-bin-encoded state of a photon to the state of a spin in a QD. The spin may be that of an electron or that of a hole. We describe adaptations of the original schemes to employ heavy holes which have a number of attractive properties including a g-factor that is tunable to zero for QDs in an appropriately oriented external magnetic field. We also introduce simple throughput scaling models to demonstrate the potential performance advantage of full BSM capability in a QD scheme, even when the quantum memory is imperfect, over optical schemes relying on linear optical elements and ensemble quantum memories.

Subwavelength Si photonics for near- and mid-infrared applications (conference presentation) - Alonso-ramos, Carlos; Pérez-galacho, Diego; Le roux, Xavier; Benedikovic, Daniel; Maezas, Florent; Zhang, Weiwei; Serna, Samuel; Vakarin, Vladyslav; Durán-valdeiglesias, Elena; Belabas-plougonven, Nadia; Labonté, Laurent; Tanzilli, Sébastien; et al. (Silicon Photonics XII, 2017)
We report our advances in development of subwavelength engineered silicon photonic devices for near- and mid-infrared applications. By periodically patterning Si with a pitch small enough to suppress diffraction, we synthesize an effective photonic medium with refractive index between those of Si and the cladding material. This technique releases new degrees of freedom in engineering of light-matter interaction, chromatic dispersion and light propagation in Si photonic waveguides. We present an overview of our recent results in the realization of novel devices including filters and waveguides for near- and mid-infrared wavelength range.

Possibilities of Bragg filtering structures based on subwavelength grating guiding mechanism (conference presentation) - Kwiecien, Pavel; Litvik, Ján; Richter, Ivan; Ctyroký, Jirí; Cheben, Pavel; Cheben, Pavel; Čtyroký, Jiří; Molina-fernández, Iñigo (Integrated Optics: Physics and Simulations III, 2017)
Silicon-on-insulator (SOI), as the most promising platform, for advanced photonic integrated structures, employs a high refractive index contrast between the silicon “core” and surrounding media. One of the recent new ideas within this field is based on the alternative formation of the subwavelength sized (quasi)periodic structures, manifesting as an effective medium with respect to propagating light. Such structures relay on Bloch wave propagation concept, in contrast to standard index guiding mechanism. Soon after the invention of such subwavelength grating (SWG) waveguides, the scientists concentrated on various functional elements such as couplers, crossings, mode transformers, convertors, MMI couplers, polarization converters, resonators, Bragg filters, and others. Our contribution is devoted to a detailed numerical analysis and design considerations of Bragg filtering structures based on SWG idea. Based on our previous studies where we have shown impossibility of application of various 2 and “2.5” dimensional methods for the proper numerical analysis, here we effectively use two independent but similar in-house approaches based on 3D Fourier modal methods, namely aperiodic rigorous coupled wave analysis (aRCWA) and bidirectional expansion and propagation method based on Fourier series (BEX) tools. As it was recently demonstrated, SWG Bragg filters are feasible. Based on this idea, we propose, simulate, and optimize spectral characteristics of such filters. In particular, we have investigated several possibilities of modifications of original SWG waveguides towards the Bragg filtering, including firstly - simple single-segment changes in position, thickness, and width, and secondly - several types of Si inclusions, in terms of perturbed width and thickness (and their combinations). The leading idea was to obtain required (e.g. sufficiently narrow) spectral characteristic while keeping the minimum size of Si features large enough. We have found that the second approach with the single element perturbations can provide promising designs. Furthermore, even more complex filtering SWG structures can be considered.

Mid- and near-infrared Si waveguides for sensing applications (conference presentation) - Alonso-Ramos, Carlos A.; Roux, Xavier Le; Benedikovic, Daniel; Vakarin, Vladyslav; Durán-Valdeiglesias, Elena; Pérez-Galacho, Diego; Cassan, Eric; Marris-Morini, Delphine; Cheben, Pavel; Vivien, Laurent (Proceedings Volume 10249, Integrated Photonics: Materials, Devices, and Applications IV, 2017)
The large transparency window of silicon (1.1 - 8 μm wavelength range) makes it a promising material for the implementation of on-chip sensors operating over an ultra-wide wavelength range. However, the implementation of the silicon-on-insulator platform is restricted by the absorption of buried oxide layer for wavelengths above 4 μm. Here, we report our advances in development of silicon waveguides for broadband operation extending from near- to mid-infrared wavelengths. We present suspended silicon waveguides that exploit a novel periodic corrugation approach to circumvent the buried oxide absorption problem and provide effective single mode operation simultaneously for near- and mid-infrared wavelengths.

Ultrafast carrier trapping in thick-shell colloidal quantum dots - Jain, Ankit; Voznyy, Oleksandr; Korkusinski, Marek; Hawrylak, Pawel; Sargent, Edward H. (The Journal of Physical Chemistry Letters, 2017)
It has previously been found that Auger processes can lead to femtosecond carrier trapping in quantum dots, limiting their performance in optoelectronic applications that rely on radiative recombination. Using atomistic simulations, we investigate whether a shell can protect carriers from Auger-assisted trapping. For these studies we investigate CdSe/CdS core–shell quantum dots having total diameters reaching up to 10 nm. We find trapping lifetimes as fast as 1 ps for 2 nm shells, and we report that shells as thick as 6 nm are required to suppress trapping fully. The most efficient recombination mechanism is found to proceed through shallow empty traps, suggesting it can be suppressed by filling the traps through doping or external electrochemical potential. Our findings suggest that to achieve efficient light emission, surface traps have to be completely eliminated, even in thick-shell quantum dots.

L-shaped fiber-chip grating couplers with high directionality and low reflectivity fabricated with deep-UV lithography - Benedikovic, Daniel; Alonso-Ramos, Carlos; Pérez-Galacho, Diego; Guerber, Sylvain; Vakarin, Vladyslav; Marcaud, Guillaume; Roux, Xavier Le; Cassan, Eric; Marris-Morini, Delphine; Cheben, Pavel; Boeuf, Frédéric; Baudot, Charles; et al. (Optics Letters, 2017)
Grating couplers enable position-friendly interfacing of silicon chips by optical fibers. The conventional coupler designs call upon comparatively complex architectures to afford efficient light coupling to sub-micron silicon-on-insulator (SOI) waveguides. Conversely, the blazing effect in double-etched gratings provides high coupling efficiency with reduced fabrication intricacy. In this Letter, we demonstrate for the first time, to the best of our knowledge, the realization of an ultra-directional L-shaped grating coupler, seamlessly fabricated by using 193 nm deep-ultraviolet (deep-UV) lithography. We also include a subwavelength index engineered waveguide-to-grating transition that provides an eight-fold reduction of the grating reflectivity, down to 1% (−20  dB). A measured coupling efficiency of −2.7  dB (54%) is achieved, with a bandwidth of 62 nm. These results open promising prospects for the implementation of efficient, robust, and cost-effective coupling interfaces for sub-micrometric SOI waveguides, as desired for large-volume applications in silicon photonics.

A geospatial database model for the management of remote sensing datasets at multiple spectral, spatial and temporal scales - Ifimov, Gabriela; Pigeau, Grace; Arroyo-Mora, J. Pablo; Soffer, Raymond; Leblanc, George (Earth Resources and Environmental Remote Sensing/GIS Applications VIII, 2017)
In this study the development and implementation of a geospatial database model for the management of multiscale datasets encompassing airborne imagery and associated metadata is presented. To develop the multi-source geospatial database we have used a Relational Database Management System (RDBMS) on a Structure Query Language (SQL) server which was then integrated into ArcGIS and implemented as a geodatabase. The acquired datasets were compiled, standardized, and integrated into the RDBMS, where logical associations between different types of information were linked (e.g. location, date, and instrument). Airborne data, at different processing levels (digital numbers through geocorrected reflectance), were implemented in the geospatial database where the datasets are linked spatially and temporally. An example dataset consisting of airborne hyperspectral imagery, collected for inter and intra-annual vegetation characterization and detection of potential hydrocarbon seepage events over pipeline areas, is presented. Our work provides a model for the management of airborne imagery, which is a challenging aspect of data management in remote sensing, especially when large volumes of data are collected.

Lighting-on-demand: balancing occupant needs and energy savings - Dikel, Erhan E.; Veitch, Jennifer A.; Mancini, Sandra; Xue, hui Henry; Valdés, Julio J. (LEUKOS, 2017)
Lighting on demand (LOD) is a high-resolution energy-efficient lighting control technique that dynamically adjusts the lights in a space according to its occupancy. It controls the lights in the space individually such that the area that receives a higher light level is determined by the location of the occupant(s) and, in some cases, by their tasks. In our LOD system, the controls adjust the individual lights above and around the occupant to track him or her while traversing a circulation space. We developed three scenarios with different combinations of light levels in the occupancy and background areas. We built a test bed, developed an occupancy algorithm, and conducted a usability test to demonstrate the acceptability of the LOD system to people walking in the circulation space by asking them to evaluate the conditions they experienced and measuring their walking time. Our test results suggest that in the case of individual occupants walking in a circulation space, the LOD concept is generally acceptable, but there are limits to the dimming potential both for the occupancy area and the background area. Satisfaction seems to be more strongly related to the occupancy area, but walking speed depends on the background level toward which one walks.
Keywords: energy savings; LED; lighting control

Trends in aluminum laser welding: lightweighting applications - Mirakhorli, Fatemeh (National Research Council Canada, 2017)

Cellulose-derived carbon nanofibers/graphene composite electrodes for powerful compact supercapacitors - Kuzmenko, Volodymyr; Wang, Nan; Haque, Mazharul; Naboka, Olga; Flygare, Mattias; Svensson, Krister; Gatenholm, Paul; Liu, Johan; Enoksson, Peter (RSC Advances, 2017)
Herein, we demonstrate a unique supercapacitor composite electrode material that is originated from a sustainable cellulosic precursor via simultaneous one-step carbonization/reduction of cellulose/graphene oxide mats at 800 °C. The resulting freestanding material consists of mechanically stable carbon nanofibrous (CNF, fiber diameter 50–500 nm) scaffolds tightly intertwined with highly conductive reduced graphene oxide (rGO) sheets with a thickness of 1–3 nm. The material is mesoporous and has electrical conductivity of 49 S cm−1, attributed to the well-interconnected graphene layers. The electrochemical evaluation of the CNF/graphene composite electrodes in a supercapacitor device shows very promising volumetric values of capacitance, energy and power density (up to 46 F cm−3, 1.46 W h L−1 and 1.09 kW L−1, respectively). Moreover, the composite electrodes retain an impressive 97% of the initial capacitance over 4000 cycles. With these superior properties, the produced composite electrodes should be the “looked-for” components in compact supercapacitors used for increasingly popular portable electronics and hybrid vehicles.

Visible light emission in graphene field effect transistors - Beltaos, Angela; Bergren, Adam Johan; Bosnick, Ken; Pekas, Nikola; Lane, Stephen; Cui, Kai; Matković, Aleksandar; Meldrum, Al (Nano Futures, 2017)
We present an experimental study of the light-emitting properties of graphene field effect transistors in the visible and near infrared spectral range. Using spectroscopic and imaging techniques, the effects of source–drain and gate voltages on the spectrum and location of the light emission were investigated. Raman spectroscopy, electronic measurements, and scanning electron microscopy combined with energy dispersive x-ray spectroscopy were used to characterize the devices. Results show that the spectral features (peak spectral intensity and wavelength) were controllable via applied source–drain or gate voltages, while the physical location of the light emission was strongly affected by scattering sites, including defects, nanoparticles, and edges. A possible explanation of the observed light emission is the outcoupling of surface plasmons excited by hot carriers in graphene according to the quantum Čerenkov effect. Hence, this work suggests the feasibility of all-electrical graphene devices for applications in light emission and plasmonics.
Keywords: light; emission; graphene; transistor; surface plasmon; hot carrier; Čerenkov

Comparison of cannabinoids with known analgesics using a novel high throughput zebrafish larval model of nociception - Ellis, L. D.; Berrue, F.; Morash, M.; Achenbach, J. C.; Hill, J.; McDougall, J. J. (Behavioural Brain Research, 2017)
It has been established that both adult and larval zebrafish are capable of showing nociceptive responses to noxious stimuli; however, the use of larvae to test novel analgesics has not been fully explored. Zebrafish larvae represent a low-cost, high-throughput alternative to traditional mammalian models for the assessment of product efficacy during the initial stages of drug development. In the current study, a novel model of nociception using zebrafish larvae is described. During the recovery from an acute exposure to low levels of acetic acid, larvae display innate changes in behaviour that may be indicative of nociception. To assess the usefulness of this model for testing potential analgesics, three known synthetic pain medications were assessed (ibuprofen, acetaminophen and tramadol) along with three naturally occurring products (honokiol, tetrahydrocannabinol and cannabidiol). When the effect of each compound on both the acetic acid recovery and control activity was compared there appeared to be both similarities and differences between the compounds. One of the most interesting effects was found for cannabidiol which appeared to oppose the activity change during the recovery period of AA exposed larvae while having a nominal effect on control activity. This would appear to be in line with current research that has demonstrated the nociceptive properties of cannabidiol. Here we have provided a novel model that will complement existing zebrafish models and will expand on the potential use of zebrafish larvae for studying both nociception and new analgesics.
Keywords: zebrafish; cannabinoid; nociception; THC; CBD; pain

Growth, survival, and whole-body proximate and fatty acid composition of haddock, Melanogrammus aeglefinus L., postlarvae fed a practical microparticulate weaning diet - Lall, Santosh P.; Lewis-McCrea, Leah M.; Tibbetts, Sean M. (Journal of the World Aquaculture Society, 2017)
Further development of high-quality feeds for hatchery-reared haddock in the North Atlantic would benefit from a standard formulation that can be used as a reference for hatcheries and laboratory studies. A practical microparticulate diet (PMD) developed and evaluated with newly metamorphosed juvenile haddock, Melanogrammus aeglefinus L., postlarvae is proposed. Survival of fish fed PMD was just as high (88–89%; P > 0.05) as those fed a high-quality imported feed (Biokyowa). Alternatively, fish fed PMD had higher (P < 0.05) final fork lengths (39.5 vs. 35.1 mm), wet weights (851.3 vs. 580.2 mg) and weight gains (1637.2 vs. 1115.7%). No differences (P > 0.05) in whole-body moisture (846–857 g/kg), ash (17–18 g/kg), or protein (101 g/kg) contents were found. Lipid content of fish fed PMD (26 g/kg) was higher (P < 0.05) than those fed Biokyowa (21 g/kg) despite PMD containing 15 g/kg lower dietary lipid, suggesting higher intake and/or lipid retention. The PMD formulation proved to be a highly suitable weaning diet for haddock postlarvae based on high feed acceptance, survival, and fish growth. Given the economic and logistical difficulties associated with importing commercial weaning feeds, this easily produced practical weaning diet has good potential for use by laboratory researchers and farm managers for hatchery-based nutrition research with haddock postlarvae.
Keywords: haddock; marine; microparticulate; postlarvae; weaning

Thermally stable type II FBGs written through polyimide coatings of silica based optical fiber - Grobnic, Dan; Hnatovsky, Cyril; Mihailov, Stephen J. (IEEE Photonics Technology Letters, 2017)
Type II-IR fiber Bragg gratings (FBGs) were written directly through the protective polyimide coatings of off-the-shelf pure silica core and telecom standard Ge-doped silica core single mode fibers using ultrafast IR radiation and the phase mask FBG writing method. Using a short focal length acylindrical lens and nonlinear photoluminescent imaging, type II grating structures could be created when Fourier transform limited pulses were chirped to 500 fs. The resulting gratings in the Ge-doped fibers were thermally stable up to 1000 °C and could be used directly as fabricated without annealing to stabilize the structure.
Keywords: ultrafast optics; fiber Bragg gratings; polyimide

Best-worst scaling more reliable than rating scales: a case study on sentiment intensity annotation - Kiritchenko, Svetlana; Mohammad, Saif (Proceedings of the 55th Annual Meeting of the Association for Computational Linguistics. Volume 2: Short Papers, 2017)
Rating scales are a widely used method for data annotation; however, they present several challenges, such as difficulty in maintaining inter- and intra-annotator consistency. Best–worst scaling (BWS) is an alternative method of annotation that is claimed to produce high-quality annotations while keeping the required number of annotations similar to that of rating scales. However, the veracity of this claim has never been systematically established. Here for the first time, we set up an experiment that directly compares the rating scale method with BWS. We show that with the same total number of annotations, BWS produces significantly more reliable results than the rating scale.

A deep network with visual text composition behavior - Guo, Hongyu (Proceedings of the 55th Annual Meeting of the Association for Computational Linguistics. Volume 2: Short Papers, 2017)
While natural languages are composi- tional, how state-of-the-art neural models achieve compositionality is still unclear. We propose a deep network, which not only achieves competitive accuracy for text classification, but also exhibits compositional behavior. That is, while creating hierarchical representations of a piece of text, such as a sentence, the lower layers of the network distribute their layer-specific attention weights to individual words. In contrast, the higher layers compose meaningful phrases and clauses, whose lengths increase as the networks get deeper until fully composing the sentence.

3D hollow sphere Co3O4/MnO2-CNTs: its high-performance bi-functional cathode catalysis and application in rechargeable zinc-air battery - Li, Xuemei; Xu, Nengneng; Li, Haoran; Wang, Min; Zhang, Lei; Qiao, Jinli (Green Energy & Environment, 2017)
There has been a continuous need for high active, excellently durable and low-cost electrocatalysts for rechargeable zinc-air batteries. Among many low-cost metal based candidates, transition metal oxides with the CNTs composite have gained increasing attention. In this paper, the 3-D hollow sphere MnO2 nanotube-supported Co3O4 nanoparticles and its carbon nanotubes hybrid material (Co3O4/MnO2-CNTs) have been synthesized via a simple co-precipitation method combined with post-heat treatment. The morphology and composition of the catalysts are thoroughly analyzed through SEM, TEM, TEM-mapping, XRD, EDX and XPS. In comparison with the commercial 20% Pt/C, Co3O4/MnO2, bare MnO2 nanotubes and CNTs, the hybrid Co3O4/MnO2-CNTs-350 exhibits perfect bi-functional catalytic activity toward oxygen reduction reaction and oxygen evolution reaction under alkaline condition (0.1 M KOH). Therefore, high cell performances are achieved which result in an appropriate open circuit voltage (∼1.47 V), a high discharge peak power density (340 mW cm−2) and a large specific capacity (775 mAh g−1 at 10 mA cm−2) for the primary Zn-air battery, a small charge–discharge voltage gap and a high cycle-life (504 cycles at 10 mA cm−2 with 10 min per cycle) for the rechargeable Zn-air battery. In particular, the simple synthesis method is suitable for a large-scale production of this bifunctional material due to a green, cost effective and readily available process.
Keywords: bi-functional catalyst; oxygen reduction reaction; oxygen evolution reaction; Activity and stability; rechargeable zinc-air battery

Characterization of the dTDP-Fuc3N and dTDP-Qui3N biosynthetic pathways in Campylobacter jejuni 81116 - Li, Zack Z.; Riegert, Alexander S.; Goneau, Marie-France; Cunningham, Anna M.; Vinogradov, Evgeny; Li, Jianjun; Schoenhofen, Ian C.; Thoden, James B.; Holden, Hazel M.; Gilbert, Michel (Glycobiology, 2017)
The Gram-negative bacterium Campylobacter jejuni 81116 (Penner serotype HS:6) has a class E lipooligosaccharide (LOS) biosynthesis locus containing 19 genes, which encode for 11 putative glycosyltransferases, 1 lipid A acyltransferase and 7 enzymes thought to be involved in the biosynthesis of dideoxyhexosamine (ddHexN) moieties. Although the LOS outer core structure of C. jejuni 81116 is still unknown, recent mass spectrometry analyses suggest that it contains acetylated forms of two ddHexN residues. For this investigation, five of the genes encoding enzymes reportedly involved in the biosyntheses of these sugar residues were examined, rmlA, rmlB, wlaRA, wlaRB and wlaRG. Specifically, these genes were cloned and expressed in Escherichia coli, and the corresponding enzymes were purified and tested for biochemical activity. Here we present data demonstrating that RmlA functions as a glucose-1-phosphate thymidylyltransferase and that RmlB is a thymidine diphosphate (dTDP)-glucose 4,6-dehydratase. We also show, through nuclear magnetic resonance spectroscopy and mass spectrometry analyses, that WlaRG, when utilized in coupled assays with either WlaRA or WlaRB and dTDP-4-keto-6-deoxyglucose, results in the production of either dTDP-3-amino-3,6-dideoxy-d-galactose (dTDP-Fuc3N) or dTDP-3-amino-3,6-dideoxy-d-glucose (dTDP-Qui3N), respectively. In addition, the X-ray crystallographic structures of the 3,4-ketoisomerases, WlaRA and WlaRB, were determined to 2.14 and 2.0 Å resolutions, respectively. Taken together, the data reported herein demonstrate that C. jejuni 81116 utilizes five enzymes to synthesize dTDP-Fuc3N or dTDP-Qui3N and that WlaRG, an aminotransferase, can function on sugars with differing stereochemistry about their C-4′ carbons. Importantly, the data reveal that C. jejuni 81116 has the ability to synthesize two isomeric ddHexN forms.
Keywords: Campylobacter; fucosamine; ketoisomerase; lipooligosaccharide; quinovosamine

Structure of the LPS O-chain from Fusobacterium nucleatum strain 12230 - Vinogradov, Evgeny; Michael, Frank St.; Cox, Andrew D. (Carbohydrate Research, 2017)
Fusobacterium nucleatum is an anaerobic bacterium found in the human mouth where it causes periodontitis. It was also found in colorectal cancer tissues and is linked with pregnancy complications, including pre-term and still births. Cell surface structures of the bacterium could be implicated in pathogenesis. Here we report the following structure of the lipopolysaccharide O-chain of F. nucleatum strain 12230: -6-α-d-Glc-4-β-d-GlcNHBu3NHBuA-3-β-d-QuiNAc4NABu- where ABu and HBu indicate (R)-3-aminobutanoyl and (R)-3-hydroxybutanoyl, respectively; all monosaccharides are in the pyranose form.
Keywords: Fusobacterium nucleatum; lipopolysaccharide; NMR spectroscopy; polysaccharide structure

Vaccination with Shigella flexneri 2a conjugate induces type 2a and cross-reactive type 6 antibodies in humans but not in mice - Farzam, Nahid; Ramon-Saraf, Reut; Banet-Levi, Yonit; Lerner-Geva, Liat; Ashkenazi, Shai; Kubler-Kielb, Joanna; Vinogradov, Evgeny; Robbins, John B.; Schneerson, Rachel (Vaccine, 2017)
Shigella flexneri (S. flexneri) 6 has emerged as an important cause of shigellosis. Our efficacy study of Shigella sonnei and S. flexneri 2a O-specific polysaccharide (O-SP) conjugates in 1–4 year-olds had too few S. flexneri 2a cases for efficacy evaluation but surprisingly showed protection of 3–4 year-olds, S. flexneri 2a-recipients, from S. flexneri 6 infection. To investigate this cross-protection antibodies to both Shigella types were investigated in all sera remaining from previous studies. Twenty to 30% of 3–44 year-old humans injected with S. flexneri 2a conjugate responded with ≥4-fold increases of IgG anti type 6, p < 0.00001. The specificity of these antibodies was shown by inhibition studies. S. flexneri 6 infection of 2 children induced besides S. flexneri 6, also S. flexneri 2a antibodies, at levels of S. flexneri 2a vaccinees. S. flexneri 2a antibodies induced by S. flexneri 6 conjugates could not be studied since no such conjugate was assessed in humans and mice responded almost exclusively to the O-SP of the injected conjugate, with no cross-reactive antibodies. Our results indicate induction of cross-reactive protective antibodies. The O-acetylated disaccharide shared by S. flexneri 6 and 2a O-SPs, is the likely basis for their cross-reactivity. S. flexneri 6 O-SP conjugates, alone and in combination with S. flexneri 2a, merit further investigation for broad S. flexneri protection.
Keywords: Shigella flexneri; LPS; antibody; cross-reactivity; vaccine

Modulation of Th17 and Regulatory T cell responses during murine pregnancy contributes to increased maternal susceptibility to Salmonella Typhimurium infection - Agbayani, Gerard; Wachholz, Kristina; Chattopadhyay, Anindita; Gurnani, Komal; Murphy, Shawn P.; Krishnan, Lakshmi (Placenta, 2017)
Objectives:Salmonella Typhimurium (ST) infection during pregnancy promotes massive placental infection and fetal loss, but also exacerbated systemic infection and maternal death. The inflammatory Th17 response contributes to immunity to ST infection, whereas successful pregnancy correlates to enhanced anti-inflammatory response by regulatory T cells (Tregs). We aimed to determine how Tregs may modulate Th17 immunity against ST infection during pregnancy. Methods: Mice were infected systemically with ST and bacterial burden was enumerated through colony-forming unit assay. Splenic Th17 and Treg cell numbers were determined through flow cytometry. Serum cytokine expression was analyzed using cytometric bead array. Splenic and/or placental mRNA expression of IL-17A, RORγ-t, IL-10 and TNF was determined through qRT-PCR. The effects of in vivo CD25+ cell depletion on infection kinetics and Th17 response were determined. Results: Enhanced bacterial burden during pregnancy was associated with increased serum inflammatory cytokine signature. Splenic and placental Th17 responses were reduced in pregnant infected mice compared to non-pregnant controls. In contrast, splenic Treg numbers were increased in non-infected pregnant mice relative to their non-pregnant counterparts. CD25+ cell depletion reduced bacterial burden while increasing systemic Th17 response in pregnant infected mice. Conclusion: Thus, downregulation of systemic Th17 responses by Tregs during pregnancy may contribute to exacerbation of ST infection.

Investigating the candidacy of a capsular polysaccharide-based glycoconjugate as a vaccine to combat Haemophilus influenzae type a disease: a solution for an unmet public health need - Cox, Andrew D.; Williams, Dean; Cairns, Chantelle; Michael, Frank St.; Fleming, Perry; Vinogradov, Evgeny; Arbour, Mélanie; Masson, Luke; Zou, Wei (Vaccine, 2017)
After the introduction of the glycoconjugate vaccine based upon the capsular polysaccharide of Haemophilus influenzae type b in the mid 1980s there was a remarkable decrease in the number of invasive cases reported for this organism. Since the 1990s several groups have observed the emergence of Haemophilus influenzae type a (Hia), especially in indigenous communities in the northern regions of Canada and Alaska, to a stage where a solution is warranted to prevent further unnecessary deaths due to this pathogen. A glycoconjugate vaccine solution based upon the type a capsular polysaccharide (CPS) was investigated pre-clinically in an effort to illustrate the proof of concept for this approach. In this study we describe the growth of Hia and the isolation, purification and conjugation of the CPS to several carrier proteins. The resulting glycoconjugates were immunised in mice and rabbits provoking sera that facilitated bactericidal killing against all type a strains that we tested. This study has illustrated the pre-clinical proof of concept of a glycoconjugate vaccine based on the CPS of Hia as a solution to this emerging disease.
Keywords: Haemophilus influenzae serotype a; conjugate vaccine; capsular polysaccharide

A review of personal profile features in personalized learning systems - Lapointe, Jean-Francois; Kondratova, Irina; Molyneaux, Heather; Shaikh, Kamran; Vinson, Norman G. (Advances in Human Factors in Training, Education, and Learning Sciences. AHFE 2017, 2017)
This paper reviews literature, market reports and commercial sites in order to identify features of personal profiles. This is a preparatory step in the development of a personalized learning environment. Results indicate that several features can be included as long as they relate to use cases. We also found that privacy concerns might arise when dealing with personal profiles and measures should be taken to ensure compliance with policies and legislations on the topic, to avoid the risk of alienating users.
Keywords: personal profiles; personalized learning

Potential energy savings from high-resolution sensor controls for LED lighting - Dikel, Erhan E.; Newsham, Guy R.; Xue, Henry; Valdés, Julio J. (Energy and Buildings, 2017)
LED lighting systems paired with high-resolution sensor systems offer great potential for substantial energy savings via enhanced control options, and have other value-added features. We used modelling and demonstrations in a full-scale office test bed to illustrate this potential. First, we propose that such a system enables much shorter timeout periods for occupancy sensing: the higher density of sensors provides more reliable occupancy detection and LEDs are impervious to lifetime degradation from the consequent increased switching frequency. We used occupancy data measured in real office environments to estimate that a reduction in timeout period from the current code maximum of 20 minutes to 1 minute would yield 26% additional energy savings. Further, we installed 72 LED luminaires in an office test bed with windows; each luminaire featured a co-located motion sensor and light sensor. The localized light sensor enabled daylight harvesting at each fixture to be optimized to local spatial conditions, yielding an extra 35% energy savings compared to a single photosensor controlling all luminaires, and ensuring better delivery of target horizontal illuminance values across the space. Finally, we demonstrated a combination of local occupancy and daylight harvesting features that resulted in 79% energy savings compared to typical prevailing energy code provisions for open-plan offices.
Keywords: high-resolution sensors; light-emitting diodes (LEDs); energy efficiency; occupancy sensing; daylight harvesting

Experimental demonstration of an apodized-imaging chip-fiber grating coupler for Si3N4 waveguides - Chen, Yang; TBucio, halia Domínguez; Khokhar, Ali Z.; Banakar, Mehdi; Grabska, Katarzyna; Gardes, Frederic Y.; Halir, Robert; Molina-Fernández, Íñigo; Cheben, Pavel; He, Jian-Jun (Optics Letters, 2017)
A silicon nitride waveguide is a promising platform for integrated photonics, particularly due to its low propagation loss compared to other complementary metal–oxide–semiconductor compatible waveguides, including silicon-on-insulator. Input/output coupling in such thin optical waveguides is a key issue for practical implementations. Fiber-to-chip grating couplers in silicon nitride usually exhibit low coupling efficiency because the moderate index contrast leads to weak radiation strengths and poor directionality. Here, we present the first, to the best of our knowledge, experimental demonstration of a recently proposed apodized-imaging fiber-to-chip grating coupler in silicon nitride that images an in-plane waveguide mode to an optical fiber placed at a specific distance above the chip. By employing amplitude and phase apodization, the diffracted optical field of the grating is matched to the fiber mode. High grating directionality is achieved by using staircase grating teeth, which produce a blazing effect. Experimental results demonstrate an apodized-imaging grating coupler with a record coupling efficiency of −1.5  dB and a 3 dB bandwidth of 60 nm in the C-band.

Broadband and high-performance devices for the silicon and silicon-nitride platforms - Molina-Fernández, I.; Halir, Robert; Ortega-Moñux, A.; Wangüemert-Pérez, J. G.; Chen, Yang; He, Jian-Jun; Cheben, Pavel; Schmid, Jens H.; Bucio, T. Domínguez; Khokhar, Ali Z.; Banakar, M.; Grabska, K.; et al. (2017 19th International Conference on Transparent Optical Networks (ICTON), 2017)
The increasing demand for higher data rates and small form factor equipment for optical networks is fuelling research on integrated optical devices with small footprint and broad bandwidth. Here, we present novel design approaches for grating couplers in the silicon and silicon nitride platforms that enable broadband operation and highly efficient coupling. Furthermore, we report experimental findings on compact integrated waveguide splitters that provide virtual perfect performance over more than 300 nm of bandwidth at telecom wavelengths.
Keywords: integrated optics; silicon photonics; multimode interference couplers; grating couplers; subwavelength structures

Recent advances in on-chip Fourier transform spectrometers - Cheben, C.; Podmore, H.; Herrero, A.; Velasco, A. V.; Schmid, J. H.; Scott, A.; Vachon, M.; Lee, R.; Calvo, M. L.; Xu, D. X.; Janz, S.; Corredera, P. (2017 19th International Conference on Transparent Optical Networks (ICTON), 2017)
We report our advances in development of on-chip Fourier-transform spectrometers. Specifically, we present applications of subwavelength engineered waveguides in a new type of a compressive-sensing Fourier-transform spatial heterodyne spectrometer chip. The spectrometer is implemented as an array of Mach-Zehnder interferometers (MZIs) integrated on a photonic chip, in a spatial heterodyne configuration. The signal from a set of MZIs comprises an undersampled discrete Fourier interferogram, which is inverted using L1-norm minimization technique to retrieve a sparse input spectrum. To implement this technique we use a subwavelength-engineered Fourier-transform spectrometer on a chip comprising 32 independent MZIs. We successfully demonstrate the retrieval of sparse input signals by collecting data from restricted sets (8 and 14) of MZIs and applying common compressive-sensing reconstruction techniques to this data. We show that this retrieval maintains the full resolution and bandwidth of the original device despite a sampling factor as low as 1/4th of a conventional (non-compressive) design

Preservation of myocardial perfusion and function by keeping hypertrophied heart empty and beating for valve surgery: an in vivo MR study of pig hearts - Wang, Jian; Xiang, Bo; Deng, Jixian; Lin, Hung-Yu; Freed, Darren H.; Arora, Rakesh C.; Tian, Ganghong (BioMed Research International, 2017)
Objectives. Normothermic hyperkalemic cardioplegia arrest (NHCA) may not effectively preserve hypertrophied myocardium during open-heart surgery. Normothermic normokalemic beating perfusion (NNBP), keeping hearts empty-beating, was utilized as an alternative to evaluate its cardioprotective role. Materials and Methods. Twelve hypertrophied pig hearts at 58.6 ± 7.2 days after ascending aorta banding underwent NNBP and NHCA, respectively. Near infrared myocardial perfusion imaging with indocyanine green (ICG) was conducted to assess myocardial perfusion. Left ventricular (LV) contractile function was assessed by cine MRI. TUNEL staining and western blotting for caspase-3 cleavage and cardiac troponin I (cTnI) degradation were conducted in LV tissue samples. Results. Ascending aortic diameter was reduced by at approximately fifty-eight days after banding. LV wall thickness was significantly higher in aorta banding than in sham operation. Myocardial blood flow reflected by maximum ICG absorbance value was markedly higher in NNBP than in NHCA. The amount of apoptotic cardiomyocyte was significantly lower in NNBP than in NHCA. NNBP alleviated caspase-3 cleavage and cTnI degradation associated with NHCA. NNBP displayed a substantially increased postoperative ejection fraction relative to NHCA. Conclusions. NNBP was better than NHCA in enhancing myocardial perfusion, inhibiting cardiomyocyte apoptosis, and preserving LV contractile function for hypertrophied hearts.

Hypoxia enhances the therapeutic potential of superparamagnetic iron oxide-labeled adipose-derived stem cells for myocardial infarction - Wang, J.; Xiang, B; Deng, J. X.; Lin, H. Y.; Freed, D. H.; Arora, R. C.; Tian, G. H. (Journal of Huazhong University of Science and Technology (Medical Sciences), 2017)
Adipose-derived stem cells (ASCs) induce therapeutic angiogenesis due to pro-angiogenic cytokines secretion. Superparamagnetic iron oxide (SPIO) nanoparticles are critical for magnetic resonance (MR) tracking of implanted cells. Hypoxia is a powerful stimulus for angiogenic activity of ASCs. In this study, we investigated whether therapeutic potency could be enhanced by implantation of hypoxia-preconditioned SPIO-labeled ASCs (SPIOASCs) into the infarcted myocardium. ASCs and SPIOASCs were cultured under 2% O2 (hypoxia) or 95% air (normoxia). Cells were intramyocardially injected into the infarcted myocardium after 48-h culture. We found that hypoxia culture increased the mRNA expression of hypoxia-inducible factor-1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF) in ASCs and SPIOASCs. The VEGF protein in the conditioned medium was significantly higher in hypoxic ASCs and SPIOASCs than in normoxic ASCs and SPIOASCs. The capillary density and left ventricular contractile function in the infarcted myocardium were significantly higher 4 weeks after implantation with hypoxic ASCs and SPIOASCs than with normoxic ASCs and SPIOASCs. Improvement in the capillary density and left ventricle function didn't differ between hypoxic ASCs-transplanted rats and hypoxic SPIOASCs-transplanted rats. Hypoxic culture enhanced the angiogenic efficiency of ASCs. It was concluded that implantation of hypoxic ASCs or SPIOASCs promotes therapeutic angiogenesis and cardiac function recovery in the infarcted myocardium. SPIO labeling does not impact the beneficial effect of hypoxic ASCs.
Keywords: adipose-derived stem cells; hypoxia; myocardial infarction; superparamagnetic iron oxide

President's page: emerging professionals, emerging technologies - Lee, Madeline Dana (The Leading Edge, 2017)
The future generation of members includes students and emerging professionals. Student programs are typically well established, but emerging professionals are a unique demographic often overlooked because they are difficult to define. What is an emerging professional? Within SEG, an emerging professional is defined as a graduate with less than eight years of industry experience; however, capturing statistics is problematic since there is no formal membership category like there is for a student. Therefore, supporting the needs of these members is very challenging. In 2014, SEG took the first step in solving this issue with the inception of the Emerging Professionals International Committee (EPIC), the goal of which is to keep emerging professionals engaged within the Society. At the 2015 Annual Meeting in New Orleans, EPIC had its first social networking event that brought together professionals, emerging professionals, and graduate students. With each passing year, EPIC continues to define an identity and seek support from SEG in building its foundation. In the past year, EPIC social events have been held at a local scale, from Houston to Lisbon, and with many more scheduled for 2017.

The damage control surgery in austere environments research group (DCSAERG): a dynamic program to facilitate real-time telementoring/telediagnosis to address exsanguination in extreme and austere environments - Kirkpatrick, Andrew W.; McKee, Jessica L.; McBeth, Paul B.; Ball, Chad G.; LaPorta, Anthony; Broderick, Timothy; Leslie, Tim; King, David; Wright Beatty, Heather E.; Keillor, Jocelyn; Tien, Homer (Journal of Trauma and Acute Care Surgery, 2017)
Hemorrhage is the most preventable cause of posttraumatic death. Many cases are potentially anatomically salvageable, yet remain lethal without logistics or trained personnel to deliver diagnosis or resuscitative surgery in austere environments. Revolutions in technology for remote mentoring of ultrasound and surgery may enhance capabilities to utilize the skill sets of non-physicians. Thus, our research collaborative explored remote mentoring to empower non-physicians to address junctional and torso hemorrhage control in austere environments. Major studies involved using remote-telementored ultrasound (RTMUS) to identify torso and junctional exsanguination, remotely mentoring resuscitative surgery for torso hemorrhage control, understanding and mitigating physiological stress during such tasks, and the technical practicalities of conducting damage control surgery (DCS) in austere environments. Iterative projects involved randomized guiding of firefighters to identify torso (RCT) and junctional (pilot) hemorrhage using RTMUS, randomized remote mentoring of MedTechs conducting resuscitative surgery for torso exsanguination in an anatomically realistic surgical trainer (“Cut Suit”) including physiological monitoring, and trained surgeons conducting a comparative randomized study for torso hemorrhage control in normal (1g) versus weightlessness (0g). This work demonstrated that firefighters could be remotely mentored to perform just-in-time torso RTMUS on a simulator. Both firefighters and mentors were confident in their abilities, the ultrasounds being 97% accurate. An ultrasound-naive firefighter in Memphis could also be remotely mentored from Hawaii to identify and subsequently tamponade an arterial junctional hemorrhage using RTMUS in a live tissue model. Thereafter, both mentored and unmentored MedTechs and trained surgeons completed resuscitative surgery for hemorrhage control on the Cut-Suit, demonstrating practicality for all involved. While remote mentoring did not decrease blood loss among MedTechs, it increased procedural confidence and decreased physiologic stress. Therefore, remote mentoring may increase the feasibility of non-physicians conducting a psychologically daunting task. Finally, DCS in weightlessness was feasible without fundamental differences from 1g. Overall, the collective evidence suggests that remote mentoring supports diagnosis, noninvasive therapy, and ultimately resuscitative surgery to potentially rescue those exsanguinating in austere environments and should be more rigorously studied.

A three-dimensional transient model for heat transfer in thermoplastic composites during continuous resistance welding - Zammar, Imad; Huq, M. Saiful; Mantegh, Iraj; Yousefpour, Ali; Ahmadi, Mojtaba (Advanced Manufacturing: Polymer & Composites Science, 2017)
The resistance welding technique for thermoplastic composites (TPCs) entails melting the TPC polymer at the joint interface using heat generated by resistive (Joule) heating of a conductive mesh or heating element placed between the surfaces to be welded. The continuous resistance welding (CRW) is an automated large-scale resistance welding technique that consists of a moving voltage source along the heating element creating a continuous weld along its path. This paper presents a transient model that is developed to predict the heat transfer in TPCs in all three dimensions during the CRW process. The model is finite element in nature and includes both the resistive and thermal conductivity behaviors of the material involved. The significance of this modeling approach is that it captures the movement of the electrical connection, as well as the nonuniform distribution of the current and resistive heating along the length and width of the weld seam. The modeling results are compared with experimental data obtained by thermocouples and an infrared camera, and exhibit solid conformance for predicting the trend of variations in weld temperature.
Keywords: thermoplastic composites (TPCs); resistance welding; composite welding; heat transfer; finite element modeling (FEM)

In-flight icing on unmanned aerial vehicle and its aerodynamic penalties - Szilder, K.; Yuan, W. (Progress in Flight Physics. Volume 9, 2017)
A numerical prediction of ice accretion on HQ309, SD7032, and SD7037 airfoils and its aerodynamic penalties is described. Ice accretion prediction on a three-dimensional (3D) swept wing is also presented. In addition to airflow and drop trajectory solvers, NRC's (National Research Council) original, 3D, morphogenetic icing modeling approach has been used. The analysis was performed for a wide range of icing conditions identi¦ed in the FAA (Federal Aviation Administration) Appendix C icing envelope. They cover a range of drop sizes, air temperatures, and liquid water contents. For selected icing conditions, the resulting decrease in lift and increase in drag have been calculated.

Effect of Carreau-Yasuda rheological parameters on subcritical Lapwood convection in horizontal porous cavity saturated by shear-thinning fluid - Khechiba, Khaled; Mamou, Mahmoud; Hachemi, Madjid; Delenda, Nassim; Rebhi, Redha (Physics of Fluids, 2017)
The present study is focused on Lapwood convection in isotropic porous media saturated with non-Newtonian shear thinning fluid. The non-Newtonian rheological behavior of the fluid is modeled using the general viscosity model of Carreau–Yasuda. The convection configuration consists of a shallow porous cavity with a finite aspect ratio and subject to a vertical constant heat flux, whereas the vertical walls are maintained impermeable and adiabatic. An approximate analytical solution is developed on the basis of the parallel flow assumption, and numerical solutions are obtained by solving the full governing equations. The Darcy model with the Boussinesq approximation and energy transport equations are solved numerically using a finite difference method. The results are obtained in terms of the Nusselt number and the flow fields as functions of the governing parameters. A good agreement is obtained between the analytical approximation and the numerical solution of the full governing equations. The effects of the rheological parameters of the Carreau-Yasuda fluid and Rayleigh number on the onset of subcritical convection thresholds are demonstrated. Regardless of the aspect ratio of the enclosure and thermal boundary condition type, the subcritical convective flows are seen to occur below the onset of stationary convection. Correlations are proposed to estimate the subcritical Rayleigh number for the onset of finite amplitude convection as a function of the fluid rheological parameters. Linear stability of the convective motion, predicted by the parallel flow approximation, is studied, and the onset of Hopf bifurcation, from steady convective flow to oscillatory behavior, is found to depend strongly on the rheological parameters. In general, Hopf bifurcation is triggered earlier as the fluid becomes more and more shear-thinning.

Study of the subsonic wall interference in stall of the NASA CRM at the NRC 1.5 m Trisonic Wind Tunnel - Toledano, Alvaro; Weiss, Julien; Morency, François; Broughton, Cabot; Benmeddour, Ali (33rd AIAA Aerodynamic Measurement Technology and Ground Testing Conference, 2017)
The development of flow separation on a model tested at subsonic flow conditions reaching stall is not currently accounted for by the one-variable method, which is the wall correction methodology used at the NRC 1.5 m Trisonic Wind Tunnel. Consequently, while this method provides accurate wall corrections during real-time tests in pre-stall conditions, it is unable to generate reliable corrections in stall conditions. In order to improve the potential theory representation of the model that is essential to the one-variable method, experimental results from a recent test campaign on a semispan version of the NASA Common Research Model (CRM) are used in combination with free-air RANS numerical simulations. The computational results are used to characterize the separation bubble that develops on the model so that it can be represented by an array of singularities added to the current potential theory model of the wing. Additionally, in a modified version of the one-variable method, the potential theory representation of the model is replaced by free-air CFD results to investigate the behavior of wall corrections for a contemporary wide-body transport aircraft tested at low-speed subsonic flow reaching stall conditions.

Alternate environmentally friendly de-painting process for aircraft structures-atmospheric plasma - Merati, Ali; Yanishevsky, Marko; Despinic, Tessa; Lo, Philip; Pankov, Vladimir (Journal of Minerals and Materials Characterization and Engineering, 2017)
During the lifetime of aircraft structures, paint removal and re-application cycles are conducted to restore appearance and to enable inspection for fatigue cracks and corrosion damages. Current paint removals processes, including chemical and abrasive media blasting, yield large amounts of volatile organic compounds and hazardous air pollutants, and generate large quantities of waste which require proper disposal/treatment. They also have the potential to mask surface cracks and decrease the effectiveness of Liquid Penetrant Inspections (LPI). This study compares current paint stripping methods to a novel Atmospheric Plasma (AP) system, which claims to be a more environmentally friendly method. Aluminium and steel coupons were prepared with military aircraft quality topcoat and primer paint schemes and subjected to the three aforemen-tioned paint stripping processes. The results were then characterized in terms of paint removal effectiveness, potential damages to the metallic substrates, and effect on the LPI process. Hardness and conductivity measurements as well as metallographic sectioning and microscopy, were used to characterize the stripped samples. The results indicated that AP had no negative ramifications on detecting fatigue cracks in the substrates, and did not alter the temper, mechanical properties of the aerospace alloys studied. The AP process has the potential to replace current hazardous and less environmentally friendly paint removal methods; though a full systematic qualification and evaluation process is still required for it to be considered as an accepted industrial paint removal process.
Keywords: atmospheric plasma; paint stripping; chemical stripping; media blast; non-destructive testing (ndt); liquid penetrant inspection (lpi); fatigue cracks; aerospace

The effect of atmospheric plasma paint stripping on the fatigue crack growth properties of aluminium substrates - Merati, Ali; Yanishevsky, Marko; Despinic, Tessa; Lo, Philip (Journal of Minerals and Materials Characterization and Engineering, 2017)
Paint removal is a common maintenance requirement for aircraft as well as naval and land vehicles, since external paint gets damaged and loses much of its corrosion protection effectiveness with time. Paint removal is also conducted when metallic aircraft structures are inspected periodically for fatigue cracks and corrosion. The conventional methods of removing paint employed throughout the Canadian Forces mainly include chemical stripping and abrasive media blasting. Chemical stripping involves the use of hazardous chemicals, which are high in Volatile Organic Compounds (VOC) and Hazardous Air Pollutants (HAP). Abrasive media blasting typically results in a substantial quantity of solid waste consisting of paint and blast residues. Such waste is subject to control under increasingly stringent environmental and safety regulations and its disposal is costly. The new Atmospheric Plasma (AP) paint removal process purports to be a high chemical energy, low thermal energy (cold plasma process), that should not damage temperature sensitive substructures, such as heat treated aerospace aluminium alloys. Fatigue strength is one of the key properties in aircraft structures. In order for AP paint stripping to be accepted as an aerospace industry standard paint removal process, it must be thoroughly tested to demonstrate that it does not adversely affect the fatigue properties of the substrate. This paper investigates effect of the paint removal process on fatigue crack growth of 7075-T6 and 2024-T3 aluminium panels.
Keywords: atmospheric plasma; paint stripping; fatigue life; topcoat; primer; non-destructive testing (ndt); fatigue cracks; aerospace; aluminium alloys

Covalent derivatization of boron nitride nanotubes with peroxides and their application in polycarbonate composites - Lin, Shuqiong; Ashrafi, Behnam; Laqua, Kurtis; Kim, Keun Su; Simard, Benoit (New Journal of Chemistry, 2017)
The novel derivatization of boron nitride nanotubes (BNNTs) with two organic peroxides (lauroyl peroxide and dicumyl peroxide) is presented. The functionalized-BNNTs (f-BNNTs) were characterized by FTIR, 1H NMR, TGA, and SEM. These thermally labile peroxides can decompose to generate an alkoxyl radical, or an alkyl radical (with the loss of CO2), which then acts as a Lewis base to attack the electron-deficient boron sites of BNNTs. This results in the covalent formation of R-O-BNNT or R-BNNT bonds. Thin films (15 to 35 μm thickness) of 0.5 to 1.0 wt% lauryl-BNNT/polycarbonate and 1 wt% BNNT-OH/polycarboante composites were fabricated, and their transparency was demonstrated. Semi-transparent, hot-pressed disks (200 μm thickness) of 1.0 wt% cumyloxy-BNNT/polycarbonate and 1.0 wt% lauryl-BNNT/polycarbonate composites were also fabricated and mechanically tested. The Young's modulus and the maximum tensile stress were increased by 12% and 8%, respectively, compared to the corresponding properties of BNNT-free polycarbonate samples.

Erosion properties of ceramic composite material based on nano-mullite whisker and Zirconia-toughened alumina - Erazo, Fabian; Robertson, Taylor; Huang, Xiao; Kearsey, Rick; Yang, Qi (ASME Turbo Expo 2017: Turbomachinery Technical Conference and Exposition, Volume 6: Ceramics; Controls, Diagnostics and Instrumentation; Education; Manufacturing Materials and Metallurgy, 2017)
The improvement of bulk ceramic properties through the addition of a secondary or even tertiary phase is a field of research that has been actively pursued since the mid twentieth century. This pursuit has become more relavent with the adoption of ceramic phases to protect structural components within the hotpath of gas turbines. Improving the properties of these ceramic coatings and tiles has the potential of reducing catastrophic damage events leading to an overall reduction in unplanned maintence and downtime. To date, Several approaches have been undertaken to improve the physical properties of these ceramics including preferential microstructural grain growth and doping to develop metastable crystal phases. This paper examines the effect of whisker additions to a mechanical mixture of oxide ceramics on the erosion properties. The baseline structure is a mechanical mixture of zirconia and alumina particles in the ratio of 89.8vol% alumina to 10.2vol% partially stabalized zirconia. A ratio of 20.0vol% mullite whiskers is incorporated into the structure as a toughening agent. The mullite whiskers are grown using a molten salt method. The overall structural composition is 20.0vol% mullite whiskers, 8.2vol% partially stabilized zirconia, and 71.8vol% alumina. This whisker toughened material is compared to a baseline 89.8vol% alumina 10.2vol% zirconia ceramic. Erosion tests were conducted using a 50 μm diameter alumina erodant with a velocity of 104 m/s. Impingement angles of 30°, 60° and 90° were examined to determine the effect of whisker additions at steeper attack angles. Despite the increased hardness, tensile strength and fracture toughness, whisker-enhanced zirconia-toughened alumina has shown similar erosion rate as non-reinforced ZTA at 30° ad 90° and much higher erostion at 60°. It can be surmised that whisker-enhanced toughening of ceramics has little positive effect on the erosion resistance of ceramics at room temperature and is potentially harmful. Microstructure analysis results are also presented within to illustrate the erosion material removal mode under different conditions.
Keywords: ceramic composites; erosion

Grinding of chromium carbide coatings using electroplated diamond wheels - Shi, Zhongde; Elfizy, Amr; Attia, Helmi; Ouelllet, Gilbert (Journal of Manufacturing Science and Engineering, 2017)
This paper reports an experimental study on grinding of chromium carbide coatings using electroplated diamond wheels. The work was motivated by machining carbide coatings in gas turbine engine applications. The objective is to explore the process conditions and parameters satisfying the ground surface quality requirements. Surface grinding experiments were conducted with water based grinding fluid on chromium carbide coated on flat surfaces of aluminum blocks for rough grinding at a fixed wheel speed vs = 30 m/s, and finish grinding at vs = 30, 60 m/s. The effects of depth of cut and workspeed on grinding power, forces, and surface roughness were investigated for each of the wheel speeds. Material removal rate Q = 20 mm3/s for rough grinding at a grinding width b = 101.6 mm was achieved. It was found that the maximum material removal rate achievable in rough grinding was restricted by chatters, which was mainly due to the large grinding width. The specific energy ranged from 27 to 59 J/mm3 under the tested conditions. Surface roughness Ra = 3.5- 3.8 µm were obtained for rough grinding, while Ra = 0.6 - 1.5 µm were achieved for finish grinding. Surface roughness was not sensitive to grinding parameters under the tested conditions, but was strongly dependent on the diamond grain sizes. Imposing axial wheel oscillations to the grinding motions reduced surface roughness by about 60% under the tested condition. It was proved that it is feasible to grind the chromium carbide coating with electroplated diamond wheels.
Keywords: coatings; grinding; diamonds; wheels; surface roughness; finishes; gas turbines; oscillations; fluids; aluminum

1–2.4 μm near-IR spectrum of the giant planet β Pictoris b obtained with the gemini planet imager - Chilcote, Jeffrey; Pueyo, Laurent; De Rosa, Robert J.; Vargas, Jeffrey; Macintosh, Bruce; Bailey, Vanessa P.; Barman, Travis; Bauman, Brian; Bruzzone, Sebastian; Bulger, Joanna; Burrows, Adam S.; Cardwell, Andrew; et al. (The Astronomical Journal, 2017)
Using the Gemini Planet Imager located at Gemini South, we measured the near-infrared (1.0–2.4 μm) spectrum of the planetary companion to the nearby, young star β Pictoris. We compare the spectrum obtained with currently published model grids and with known substellar objects and present the best matching models as well as the best matching observed objects. Comparing the empirical measurement of the bolometric luminosity to evolutionary models, we find a mass of 12.9 ± 0.2 MJup, an effective temperature of 1724 ± 15 K, a radius of 1.46 ± 0.01 RJup, and a surface gravity of logg=4.18± 0.01 [dex] (cgs). The stated uncertainties are statistical errors only, and do not incorporate any uncertainty on the evolutionary models. Using atmospheric models, we find an effective temperature of 1700–1800 K and a surface gravity of logg=3.5$–4.0 [dex] depending upon the model. These values agree well with other publications and with "hot-start" predictions from planetary evolution models. Further, we find that the spectrum of β Pic b best matches a low surface gravity L2 ± 1 brown dwarf. Finally, comparing the spectrum to field brown dwarfs, we find the the spectrum best matches 2MASS J04062677–381210 and 2MASS J03552337+1133437.

Educational data mining approach for engineering graduate attributes analysis - Bouslimani, Yassine; Durand, Guillaume; Belacel, N. (Proceedings of the Canadian Engineering Education Association (CEEA) Conference, June 19-22, 2016, Halifax, NS, Canada, 2017)
Curriculum improvement and graduate attributes assessments have become recently a serious issue for many Canadian engineering schools. Collecting assessment data concerning graduate attributes and the students’ learning is an important step of curriculum evaluation and the continuous improvement process. To be successful, this improvement process needs appropriate methods and tools for data analysis. Recent developments in the field of Psychometrics and Educational Data Mining (EDM) provide multidimensional item response models able to take into account student and curriculum attributes as parameters. The primary intent of these new models is to predict student successes based on students past performance and the assessment map underlying the tests they completed. We demonstrate in this paper that these models can also be used to analyze the assessment map. In the psychometric and Educational Data mining literature, assessment maps are usually represented as a parameter that associates items to competencies in a matrix called Q-matrix. This concept draws its origins from the Rule-Space Model that was introduced in the eighties to statistically classify student item responses into a set of ideal response patterns associated to different cognitive skills. A method based on the Additive Factor Model has been successfully implemented to analyse the Q-matrix corresponding to the assessment maps used in the graduate assessment process. The results of 17 volunteering anonymous students completing 36 courses at the Université de Moncton between winter 2010 and fall 2015 semesters was analysed with our method. Results obtained provided interesting and useful information regarding the assessment map and the overall assessment process that are presented and discussed in this paper.

Helicopter load signal and fatigue life estimation using low dimensional spaces - Cheung, Catherine; Valdés, Julio J.; Rubio, Alejandro Lehman (2017 International Joint Conference on Neural Networks (IJCNN), 2017)
The accurate estimation of helicopter component loads is an important goal for ensuring safe operation as well as for life cycle management and life extension efforts. In this research, the use of computational intelligence, neural network, and machine learning techniques is explored to estimate helicopter component loads and their fatigue life, in particular the main rotor yoke load of the CH-146 Griffon helicopter. This paper describes efforts to reduce the number of dimensions of the input data using feature generation techniques in the load estimation methodology, beginning with intrinsic dimension analysis to determine the number of intrinsic dimensions in the data. The data set is then mapped using different implicit methods to a low-dimension representation of the original data, which is then used for load estimation and fatigue life analysis for comparison with the results of the original 26-dimension input data. The resulting load signal and fatigue life estimates from the low-dimension representations are in most cases equally if not more accurate than those for the original input data. These promising results show that the low-dimension representations retain the relevant data from the original input data set and perhaps discard spurious data resulting in more accurate estimates.

Extreme learning machines to approximate low dimensional spaces for helicopter load signal and fatigue life estimation - Valdés, Julio J.; Cheung, Catherine; Rubio, Alejandro Lehman (2017 International Joint Conference on Neural Networks (IJCNN), 2017)
As aircraft fleets are required to expand their roles and usage, the accurate estimation of component loads in a helicopter is an important capability for safety and security reasons as well as for life cycle management and life extension efforts. Although dynamic component loads can be measured and monitored directly, these measurement methods are not reliable and are costly and difficult to maintain. Computational intelligence techniques have been successfully used for estimating helicopter dynamic loads and their resulting fatigue life using flight system and control parameters. However, other approaches work on low dimensional spaces with the advantage of smaller number of features and noise reduction due to information fusion. Nonlinear transformations have been used for this purpose, but their computation via implicit methods becomes more complex, time consuming and impractical with data growth. Moreover, the relationships between the features of the original and the target spaces are more difficult to uncover. Extreme Learning Machines (ELM) are used as an explicit functional representation for implicit methods, in particular for the t-SNE mapping. It was found that ELMs provided a good approximation to the implicit mapping, which preserves the appropriateness of the load prediction and damage estimation of critical helicopter components. In addition, the ELM model can be used for processing incoming streams of data, overcoming the limitation of the computation of the low dimensional mapping inherent to the use of implicit methods.

Procedure to decouple reflectance and down-shifting effects in luminescent down-shifting enhanced photovoltaics - Gabr, Ahmed M.; Walker, Alexandre W.; Wilkins, Matthew M.; Kleiman, Rafael; Hinzer, Karin (Optics Express, 2017)
The down-shifting (DS) process is a purely optical approach used to improve the short-wavelength response of a solar cell by shifting high-energy photons to the visible range, which can be more efficiently absorbed by the solar cell. In addition to the DS effect, coupling a DS layer to the top surface of a solar cell results in a change in surface reflectance. The two effects are intermixed and therefore, usually reported as a single effect. Here we propose a procedure to decouple the two effects. Analytical equations are derived to decouple the two effects, that consider the experimentally measured quantum efficiency of the solar cell with and without the DS layer, in addition to transfer matrix simulations of the parasitic absorption in the device structure. In this work, an overall degradation of 0.46 mA/cm2 is observed when adding a DS layer composed of silicon nanocrystals embedded in a quartz matrix to a silicon solar cell of 11% baseline efficiency. To fully understand the contribution from each effect, the surface reflectance and DS effects are decoupled and quantified using the described procedure. We observe an enhancement of 0.27 mA/cm2 in short-circuit current density due to the DS effect, while the surface reflectance effect leads to a degradation of 0.73 mA/cm2 in short-circuit current density.

Strategy to identify the causes and to solve a sludge granulation problem in methanogenic reactors: application to a full-scale plant treating cheese wastewater - Esquivel, Maricela; Laguna, Acela; Baron, Olivier; Mamouni, Rachid El; Guiot, Serge R.; Monroy, Oscar (Environmental Science and Pollution Research, 2017)
Granulation of biomass is at the basis of the operation of the most successful anaerobic systems (UASB, EGSB and IC reactors) applied worldwide for wastewater treatment. Despite of decades of studies of the biomass granulation process, it is still not fully understood and controlled. “Degranulation/lack of granulation” is a problem that occurs sometimes in anaerobic systems resulting often in heavy loss of biomass and poor treatment efficiencies or even complete reactor failure. Such a problem occurred in Mexico in two full-scale UASB reactors treating cheese wastewater. A close follow-up of the plant was performed to try to identify the factors responsible for the phenomenon. Basically, the list of possible causes to a granulation problem that were investigated can be classified amongst nutritional, i.e. related to wastewater composition (e.g. deficiency or excess of macronutrients or micronutrients, too high COD proportion due to proteins or volatile fatty acids, high ammonium, sulphate or fat concentrations), operational (excessive loading rate, sub- or over-optimal water upflow velocity) and structural (poor hydraulic design of the plant). Despite of an intensive search, the causes of the granulation problems could not be identified. The present case remains however an example of the strategy that must be followed to identify these causes and could be used as a guide for plant operators or consultants who are confronted with a similar situation independently of the type of wastewater. According to a large literature based on successful experiments at lab scale, an attempt to artificially granulate the industrial reactor biomass through the dosage of a cationic polymer was also tested but equally failed. Instead of promoting granulation, the dosage caused a heavy sludge flotation. This shows that the scaling of such a procedure from lab to real scale cannot be advised right away unless its operability at such a scale can be demonstrated.
Keywords: anaerobic; cationic polymers; cheese wastewater; granulation; UASB reactor; water upflow velocity; trace metals

Acidogenic digestion of food waste in a thermophilic leach bed reactor: effect of pH and leachate recirculation rate on hydrolysis and volatile fatty acid production - Hussain, Abid; Filiatrault, Mélissa; Guiot, Serge R. (Bioresource Technology, 2017)
The effect of pH control (4, 5, 6, 7) on volatile fatty acids (VFA) production from food waste was investigated in a leach bed reactor (LBR) operated at 50°C. Stabilisation of pH at 7 resulted in hydrolysis yield of 530 g soluble chemical oxygen demand (sCOD)/kg total volatile solids (TVS) added and VFA yield of 247 g COD/kg TVS added, which were highest among all pH tested. Butyric acid dominated the VFA mix (49-54%) at pH of 7 and 6, while acetate composed the primary VFA (41-56%) at pH of 4 and 5. A metabolic shift towards lactic acid production was observed at pH of 5. Improving leachate recirculation rate further improved the hydrolysis and degradation efficiency by 10-16% and the acidification yield to 340 g COD/kg TVS added. The butyric acid concentration of 16.8 g/L obtained at neutral pH conditions is among the highest reported in literature.
Keywords: acidogenic digestion; food waste; leach bed reactor; pH control; leachate recirculation rate

Energy related CO2 conversion and utilization: advanced materials/nanomaterials, reaction mechanisms and technologies - Zheng, Yun; Zhang, Wenqiang; Li, Yifeng; Chen, Jing; Yu, Bo; Wang, Jianchen; Zhang, Lei; Zhang, Jiujun (Nano Energy, 2017)
CO2 conversion to produce useful fuels/chemicals is a promising route for reducing CO2 emission as well as for exploring the promising energy storage method. To facilitate the research and development of CO2 conversion, this paper provides a comprehensive overview of CO2 conversions using advanced materials/nanomaterials and technologies for the production of useful fuels/chemicals. The molecular structure, thermodynamics and kinetics of CO2 are reviewed for the understanding of fundamentals and explaining why C=O double bonds are difficult to break. The mechanisms and features of various conversion technologies are summarized and classified into enzymatic, mineralization, photochemical/photo-electrochemical, thermochemical as well as electrochemical processes. In particular, by comparing electrochemical conversion technologies at low and high temperatures, CO2 conversion at intermediate temperatures is emphasized. Furthermore, the economic feasibility for CO2 utilization is analyzed with cases for the production of various chemicals/fuels. The technical and application challenges of CO2 conversion into useful fuels/chemicals are also summarized, composing mainly of: insufficient fundamental understanding, low product selectivity, as well as low efficiency and stability. To overcome these challenges, future research directions are proposed in this review.
Keywords: carbon dioxide conversion; fuels/chemicals; electrochemical; materials/nanomaterials

Residual stress effects of a fatigue crack on guided lamb waves - Martinez, Marcias J.; Pant, Shashank; Yanishevsky, Marko; Backman, David (Smart Materials and Structures, 2017)
Structural health monitoring has focused on the use of computational models to capture the effect of crack-like discontinuities on the behaviour of acoustic-ultrasonic signals. However, few models have taken into account the effect of geometric complexity in combination with residual stresses generated during the fatigue crack growth process. In this study, a finite element analysis model of a C-channel type aeronautical structure is evaluated under a pitch-catch scenario. Three different finite element model configurations were considered in order to understand the effects that residual stresses of a fatigue crack emanating from a through-hole have on the guided Lamb wave propagation behaviour. The results demonstrate that numerical modelling is able to capture the change in amplitude and the effect of a phase shift on the guided Lamb wave behaviour due to the presence of the discontinuity and the stress field generated during the fatigue crack growth process.

A lipophilic ionic liquid based on formamidinium cations and TFSI: the electric response and the effect of CO2 on conductivity mechanism - Bertasi, Federico; Giffin, Guinevere; Vezzù, Keti; Pace, Guiseppe; Abu-Lebdeh, Yaser; Armand, Michel; Di Noto, Vito (Physical Chemistry Chemical Physics, 2017)
The work describes the preparation of the new lipophilic ionic liquid tetraoctyl-formamidinium bis(trifluoromethanesulfonyl) imide (TOFATFSI), which is miscible with lower alkanes. In particular, this manuscript focuses on the electric behaviour of TOFATFSI in the particularly challenging highly apolar environment of supercritical CO2. The conductivity and relaxation phenomena are revealed through the analysis of the broadband electric spectra with particular emphasis on the effect of temperature and CO2 uptake on the IL conductivity. It is found that temperature boosts the conductivity via an increase in the charge carrier mobility. Also, CO2 absorption affects both the conductivity and the permittivity of the material due to the presence of CO2-IL interactions that modulate the nanostructure and the size of the TOFATFSI aggregates, which increases both the mobility and the density of the charge carriers.

Advanced laser-induced breakdown spectroscopy (LIBS) sensor for gold mining - Harhira, Aïssa; Bouchard, Paul; Rifai, Kheireddine; Haddad, Josette El; Sabsabi, Mohamad; Blouin, Alain; Laflamme, M. (The 56th Conference of Metallurgists COM 2017, 2017)
There is a need in the mining industry for determining quickly and in the field the concentration of gold in mineral ore samples. Existent portable analyzers cannot determine the gold content at the ppm range. Hence, a portable LIBS (Laser-Induced Breakdown Spectroscopy) appears as a good candidate but developments are required to fulfill the needs of the gold mining industry. Developing a functional LIBS based analyzer involves several challenges to be addressed prior to its use in the field. To be of practical use, the analyzer has to probe a representative sampling of the surface of the mineral samples and has to tackle the matrix effect resulting from several mineralogical compositions of the samples. This paper presents the recent on-going work at the National Research Council Canada (NRC) and Laval University using LIBS for gold mining, from the determination of gold-bearing rock composition to direct detection of gold and system prototyping.

GaSb-based single-mode distributed feedback lasers for sensing (conference presentation) - Gupta, James A.; Bezinger, Andrew; Lapointe, Jean; Poitras, Daniel; Aers, Geof C. (Smart Photonic and Optoelectronic Integrated Circuits XIX, 2017)
GaSb-based tunable single-mode diode lasers can enable rapid, highly-selective and highly-sensitive absorption spectroscopy systems for gas sensing. In this work, single-mode distributed feedback (DFB) laser diodes were developed for the detection of various trace gases in the 2-3.3um range, including CO2, CO, HF, H2S, H2O and CH4. The lasers were fabricated using an index-coupled grating process without epitaxial regrowth, making the process significantly less expensive than conventional DFB fabrication. The devices are based on InGaAsSb/AlGaAsSb separate confinement heterostructures grown on GaSb by molecular beam epitaxy. DFB lasers were produced using a two step etch process. Narrow ridge waveguides were first defined by optical lithography and etched into the semiconductor. Lateral gratings were then defined on both sides of the ridge using electron-beam lithography and etched to produce the index-grating. Effective index modeling was used to optimize the ridge width, etch depths and the grating pitch to ensure single-lateral-mode operation and adequate coupling strength. The effective index method was further used to simulate the DFB laser emission spectrum, based on a transfer matrix model for light transmission through the periodic structure. The fabricated lasers exhibit single-mode operation which is tunable through the absorption features of the various target gases by adjustment of the drive current. In addition to the established open-path sensing applications, these devices have great potential for optoelectronic integrated gas sensors, making use of integrated photodetectors and possibly on-chip Si photonics waveguide structures.

Genetically engineered hairy root cultures of Hyoscyamus senecionis and H. muticus: ploidy as a promising parameter in the metabolic engineering of tropane alkaloids - Dehghan, E.; Reed, D. W.; Covello, P. S.; Hasanpour, Z.; Palazon, J.; Oksman-Caldentey, K. M.; Ahmadi, F. S (Plant Cell Reports, 2017)
Key Message: Tetraploidy improves overexpression of h6h and scopolamine production of H. muticus, while in H. senecionis, pmt overexpression and elicitation can be used as effective methods for increasing tropane alkaloids. Abstract: The effects of metabolic engineering in a polyploid context were studied by overexpression of h6h in the tetraploid hairy root cultures of H. muticus. Flow cytometry analysis indicated genetic stability in the majority of the clones, while only a few clones showed genetic instability. Among all the diploid and tetraploid clones, the highest level of h6h transgene expression and scopolamine accumulation was interestingly observed in the tetraploid clones of H. muticus. Therefore, metabolic engineering of the tropane biosynthetic pathway in polyploids is suggested as a potential system for increasing the production of tropane alkaloids. Transgenic hairy root cultures of Hyoscyamus senecionis were also established. While overexpression of pmt in H. senecionis was correlated with a sharp increase in hyoscyamine production, the h6h-overexpressing clones were not able to accumulate higher levels of scopolamine than the leaves of intact plants. Applying methyl jasmonate was followed by a sharp increase in the expression of pmt and a drop in the expression of tropinone reductase II (trII) which consequently resulted in the higher biosynthesis of hyoscyamine and total alkaloids in H. senecionis.
Keywords: hairy roots; metabolic engineering; methyl jasmonate; tetraploidy; tropane alkaloids

Apparent digestibility of nutrients, energy, essential amino acids and fatty acids of juvenile Atlantic salmon (Salmo salar L.) diets containing whole-cell or cell-ruptured Chlorella vulgaris meals at five dietary inclusion levels - Tibbetts, Sean M.; Mann, Jason; Dumas, André (Aquaculture, 2017)
Chlorella vulgaris, one of the most studied microalga for industrial applications, has never before been assessed as a potential ‘low-trophic’ ingredient for Atlantic salmon (Salmo salar L.). The effects on apparent nutrient digestibility coefficients (ADCs) by dietary inclusion of whole-cell or cell-ruptured C. vulgaris meals at five levels were determined. Integrity of nutrients, energy, essential amino acids (EAAs) and fatty acids were well-preserved after cell-rupture processing. Based on microscopy and protein solubility, two Microfluidizer® passes were sufficient for complete cell-rupture as no improvement in solubility (P = 0.998) was achieved with a third pass. Whole-cell C. vulgaris meal reduced ADCs for dry matter, protein, lipid and energy at inclusion as low as 6–12% (P ≤ 0.035), whereas carbohydrate ADC was not affected up to 24% (P ≥ 0.980) and was significantly improved at 30% (P = 0.028). Similarly, starch ADC was not affected by inclusion of whole-cell C. vulgaris meal at any level (P = 0.256). Inclusion of cell-ruptured C. vulgaris meal did not affect ADCs for dry matter when included up to 30% (P ≥ 0.900), protein up to 24% (P ≥ 0.092) or lipid up to 18% (P ≥ 0.124). Energy ADC was not affected up to 12% (P ≥ 0.530) but reduced at higher levels (P ≤ 0.009). Inclusion of cell-ruptured C. vulgaris meal at all levels improved carbohydrate ADC (P ≤ 0.002), due to increased starch digestibility. In fact, starch ADCs of diets containing 18–30% was significantly higher than that of the algae-free control diet (P ≤ 0.009). Similarly, phosphorous ADC was higher in diets containing 18–30% C. vulgaris meals than the algae-free control diet. Dietary ADCs were not affected by moderate inclusion (up to 18%) of whole-cell C. vulgaris meal for most EAAs (P ≥ 0.116), while ADCs for leucine and phenylalanine were reduced when over 12%. Dietary ADCs were not affected by high inclusion (24–30%) of cell-ruptured C. vulgaris meal for any EAA (P ≥ 0.076) and tryptophan and lysine were confirmed as the most limiting EAAs in C. vulgaris meals for Atlantic salmon. Reduced energy digestibility of diets containing C. vulgaris meals was associated with significantly lower ADCs for palmitic, oleic, linoleic and linolenic acids with whole-cell C. vulgaris meal at > 6–12% (P ≤ 0.022) and palmitic and oleic acids with cell-ruptured C. vulgaris meal at > 12–18%. Nevertheless, inclusion of either C. vulgaris meal up to 30% did not affect dietary ADCs for palmitoleic acid, eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) (P ≥ 0.126). Single ingredient ADCs of nutrients, energy, EAAs and major fatty acids are reported for the first time for juvenile Atlantic salmon fed diets containing whole-cell and cell-ruptured C. vulgaris meals.
Keywords: Chlorella; cell-rupture; digestibility; microalgae; salmon

Integrated InAs/InP quantum-dot coherence comb lasers (conference presentation) - Lu, Zhenguo; Liu, Jiaren; Poole, Philip J.; Song, Chun-Ying; Webber, John; Mao, Linda; Chang, Shoude; Ding, Heping; Barrios, Pedro J.; Poitras, Daniel; Janz, Siegfried (Smart Photonic and Optoelectronic Integrated Circuits XIX, 2017)
Current communication networks needs to keep up with the exponential growth of today’s internet traffic, and telecommunications industry is looking for radically new integrated photonics components for new generation optical networks. We at National Research Council (NRC) Canada have successfully developed nanostructure InAs/InP quantum dot (QD) coherence comb lasers (CCLs) around 1.55 m. Unlike uniform semiconductor layers in most telecommunication lasers, in these QD CCLs light is emitted and amplified by millions of semiconductor QDs less than 60 nm in diameter. Each QD acts like an isolated light source acting independently of its neighbours, and each QD emits light at its own unique wavelength. The end result is a QD CCL is more stable and has ultra-low timing jitter. But most importantly, a single QD CCL can simultaneously produce 50 or more separate laser beams at distinct wavelengths over the telecommunications C-band. Utilizing those unique properties we have put considerable effort well to design, grow and fabricate InAs/InP QD gain materials. After our integrated packaging and using electrical feedback-loop control systems, we have successfully demonstrated ultra-low intensity and phase noise, frequency-stabilized integrated QD CCLs with the repetition rates from 10 GHz to 100 GHz and the total output power up to 60 mW at room temperature. We have investigated their relative intensity noises, phase noises, RF beating signals and other performance of both filtered individual channel and the whole CCLs. Those highly phase-coherence comb lasers are the promising candidates for flexible bandwidth terabit coherent optical networks and signal processing applications.

Silicon subwavelength structures for communications and sensing (conference presentation) - Halir, Robert; Luque-González, Juan Manuel; Wangüemert-Pérez, Gonzalo; Ortega-Moñux, Alejandro; Xu, Dan-Xia; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo (Integrated Photonics: Materials, Devices, and Applications IV, 2017)
Silicon sub-wavelength structures have found widespread applications in devices ranging from fiber-to-chip couplers to spectrometers. So far, these structures have been mainly used to engineer the local refractive index. Here we focus on two further applications. We describe how to engineer the waveguide electromagnetic field distribution for enhanced evanescent field sensing, predicting a 6-fold enhancement of the sensitivity compared to conventional waveguides. We furthermore report experimental results on broadband multimode interference couplers, which, by leveraging the inherent anisotropy of the sub-wavelength structures, achieve virtually perfect operation over a bandwidth of more than 300nm at telecom wavelengths.

Design of optical metamaterial waveguide structures (conference presentation) - Ortega-Moñux, Alejandro; Halir, Robert; Sánchez-Postigo, Alejandro; Soler-Penadés, Jordi; Ctyroký, Jirí; Luque-González, José Manuel; Sarmiento-Merenguel, José Darío; Wangüemert-Pérez, Juan Gonzalo; Schmid, Jens H.; Xu, Dan-Xia; Janz, Sigfried; Lapointe, Jean; et al. (Integrated Optics: Physics and Simulations III, 2017)
Subwavelength gratings (SWGs) are periodic structures with a pitch (Λ) smaller than the wavelength of the propagating wave (λ), so that diffraction effects are suppressed. These structures thus behave as artificial metamaterials where the refractive index and the dispersion profile can be controlled with a proper design of the geometry of the structure. SWG waveguides have found extensive applications in the field of integrated optics, such as efficient fiber-chip couplers, broadband multimode interference (MMI) couplers, polarization beam splitters or evanescent field sensors, among others. From the point of view of nano-fabrication, the subwavelength condition (Λ << λ) is much easier to meet for long, mid-infrared wavelengths than for the comparatively short near-infrared wavelengths. Since most of the integrated devices based on SWGs have been proposed for the near-infrared, the true potential of subwavelength structures has not yet been completely exploited. In this talk we summarize some valuable guidelines for the design of high performance SWG integrated devices. We will start describing some practical aspects of the design, such as the range of application of semi-analytical methods, the rigorous electromagnetic simulation of Floquet modes, the relevance of substrate leakage losses and the effects of the random jitter, inherent to any fabrication process, on the performance of SWG structures. Finally, we will show the possibilities of the design of SWG structures with two different state-of-the-art applications: i) ultra-broadband MMI beam splitters with an operation bandwidth greater than 300nm for telecom wavelengths and ii) a set of suspended waveguides with SWG lateral cladding for mid-infrared applications, including low loss waveguides, MMI couplers and Mach-Zehnder interferometers.

Design considerations for competency functionality within a learning ecosystem - Kondratova, Irina; Molyneaux, Heather; Fournier, Helene (Learning and Collaboration Technologies. Novel Learning Ecosystems, 2017)
This paper provides a review of the current trends within competency based training and management and the challenges with competency management frameworks in Canada. The paper builds on earlier work by the authors related to digital systems for competency management, a market analysis report for competency management systems and a literature review on competency management systems in Canada. The authors also elaborate on current and proposed design solutions for competency functionality in the context of the Learning and Performance Support (LPSS) program at the National Research Council of Canada (NRC) and on the results of user surveys and usability studies of the LPSS system related to competency and skills development.
Keywords: competency management; learning and performance support; personal learning environment; collaborative learning

Laser-induced plasmonic colours on metals - Guay, Jean-Michel; Lesina, Antonino Calà; Côté, Guillaume; Charron, Martin; Poitras, Daniel; Ramunno, Lora; Berini, Pierre; Weck, Arnaud (Nature Communications, 2017)
Plasmonic resonances in metallic nanoparticles have been used since antiquity to colour glasses. The use of metal nanostructures for surface colourization has attracted considerable interest following recent developments in plasmonics. However, current top-down colourization methods are not ideally suited to large-scale industrial applications. Here we use a bottom-up approach where picosecond laser pulses can produce a full palette of non-iridescent colours on silver, gold, copper and aluminium. We demonstrate the process on silver coins weighing up to 5 kg and bearing large topographic variations (∼1.5 cm). We find that colours are related to a single parameter, the total accumulated fluence, making the process suitable for high-throughput industrial applications. Statistical image analyses of laser-irradiated surfaces reveal various nanoparticle size distributions. Large-scale finite-difference time-domain computations based on these nanoparticle distributions reproduce trends seen in reflectance measurements, and demonstrate the key role of plasmonic resonances in colour formation.

Dynamic adaptation of online ensembles for drifting data streams - Olorunnimbe, M. Kehinde; Viktor, Herna L.; Paquet, Eric (Journal of Intelligent Information Systems, 2017)
The success of data stream mining techniques has allowed decision makers to analyze their data in multiple domains, ranging from monitoring network intrusion to financial markets analysis and online sales transactions exploration. Specifically, online ensembles that construct accurate models against drifting data streams have been developed. Recently, there has been a surge in interest in mobile (or so-called pocket) data stream mining, aiming to construct near real-time models for data stream mining applications that run on mobile devices. In such a setting, it follows that the computational resources are limited and that there is a need to adapt analytics to map the resource usage requirements. Consequently, the resultant models should not only be highly accurate, but they should also adapt swiftly to changes. In addition, the data mining techniques should be fast, scalable, and efficient in terms of resource allocation. It then becomes important to consider Return on Investment (ROI) issues such as storage requirements and memory utilization. This paper introduces the Adaptive Ensemble Size (AES) algorithm, an extension of the Online Bagging method, to address these issues. Our AES method dynamically adapts the sizes of ensembles, based on ROI usage patterns. We illustrate our approach by analyzing the performances against both synthetic and real-world data streams. The results, when comparing our AES algorithm with the state-of-the-art, indicate that we are able to obtain a high Return on Investment (ROI) and to swiftly adapt to change, without compromising on the predictive accuracy.
Keywords: data streams; metalearning; adaptive ensemble size; return on investment; ozaBag

Cost weighting for neural machine translation domain adaptation - Chen, Boxing; Cherry, Colin; Foster, George; Larkin, Samuel (Proceedings of the First Workshop on Neural Machine Translation, 2017)
In this paper, we propose a new domain adaptation technique for neural machine translation called cost weighting, which is appropriate for adaptation scenarios in which a small in-domain data set and a large general-domain data set are available. Cost weighting incorporates a domain classifier into the neural machine translation training algorithm, using features derived from the encoder representation in order to distinguish in-domain from out-of-domain data. Classifier probabilities are used to weight sentences according to their domain similarity when updating the parameters of the neural translation model. We compare cost weighting to two traditional domain adaptation techniques developed for statistical machine translation: data selection and sub-corpus weighting. Experiments on two large data tasks show that both the traditional techniques and our novel proposal lead to significant gains, with cost weighting outperforming the traditional methods.

Detection of clouds in sky/cloud and aerial images using moment based texture segmentation - Tulpan, Dan; Bouchard, Cajetan; Ellis, Kristopher; Minwalla, Cyrus (2017 International Conference on Unmanned Aircraft Systems (ICUAS), 2017)
Unmanned aircraft flying beyond line of sight in uncontrolled airspace need to maintain adequate separation from local inclement weather patterns for regulatory compliance and operational safety. Although commercial solutions for `weather avoidance' exist, they are tailored to manned aviation and as such either lack the accuracy or the size, weight, and power (SWaP) requirements of small Unmanned Aerial System (UAS). Detection and ranging to the cloud ceiling is a key component of weather avoidance. Proposed herein is a computer vision approach to cloud detection consisting of feature extraction and machine learning. Six image moments on local texture regions were extracted and fused within a classification algorithm for discrimination of cloud pixels. Three different popular classifiers were evaluated for efficacy. Two publicly available datasets of all-sky images were utilized for training and test datasets. The proposed approach was compared to five well-known thresholding techniques via quantitative analysis. Results indicate that our method consistently outperformed the popular thresholding methods across all tested images. Comparison between the classification techniques indicated random forests to possess the highest training accuracy, while multilayer perceptrons showed better prediction accuracy on the test dataset. Upon extending the method to realistic images including background clutter, the random forest classifier demonstrated the best training accuracy of 100% and the best prediction accuracy of 96%. Although computationally more expensive, the random forest classifier also produced the fewest number of false positives. A sensitivity analysis for window sizes is presented for robust validation of the chosen approach, which showed that detection accuracy improved in proportion to window size at the expense of computation time.

Minority carrier diffusion lengths and mobilities in low-doped n-InGaAs for focal plane array applications - Walker, Alexandre W.; Denhoff, Mike W. (Infrared Technology and Applications XLIII, 2017)
The hole diffusion length in n-InGaAs is extracted for two samples of different doping concentrations using a set of long and thin diffused junction diodes separated by various distances on the order of the diffusion length. The methodology is described, including the ensuing analysis which yields diffusion lengths between 70 - 85 um at room temperature for doping concentrations in the range of 5 - 9 x 10^15 cm-3. The analysis also provides insight into the minority carrier mobility which is a parameter not commonly reported in the literature. Hole mobilities on the order of 500 - 750 cm2/Vs are reported for the aforementioned doping range, which are comparable albeit longer than the majority hole mobility for the same doping magnitude in p-InGaAs. A radiative recombination coefficient of (0.5-0.2)x10^-10 cm^-3s^-1 is also extracted from the ensuing analysis for an InGaAs thickness of 2.7 um. Preliminary evidence is also given for both heavy and light hole diffusion. The dark current of InP/InGaAs p-i-n photodetectors with 25 and 15 um pitches are then calibrated to device simulations and correlated to the extracted diffusion lengths and doping concentrations. An effective Shockley-Read-Hall lifetime of between 90-200 us provides the best fit to the dark current of these structures.
Keywords: InGaAs; SWIR; minority carrier diffusion length; mobility; lifetime; doping dependence; modeling and simulation; dark current; pixel pitch

Minority carrier diffusion lengths and mobilities in low-doped n-InGaAs for focal plane array applications - Walker, Alexandre W.; Denhoff, Mike W. (Condensed Matter, 2017)
The hole diffusion length in n-InGaAs is extracted for two samples of different doping concentrations using a set of long and thin diffused junction diodes separated by various distances on the order of the diffusion length. The methodology is described, including the ensuing analysis which yields diffusion lengths between 70 - 85 um at room temperature for doping concentrations in the range of 5 - 9 x 10^15 cm-3. The analysis also provides insight into the minority carrier mobility which is a parameter not commonly reported in the literature. Hole mobilities on the order of 500 - 750 cm2/Vs are reported for the aforementioned doping range, which are comparable albeit longer than the majority hole mobility for the same doping magnitude in p-InGaAs. A radiative recombination coefficient of (0.5-0.2)x10^-10 cm^-3s^-1 is also extracted from the ensuing analysis for an InGaAs thickness of 2.7 um. Preliminary evidence is also given for both heavy and light hole diffusion. The dark current of InP/InGaAs p-i-n photodetectors with 25 and 15 um pitches are then calibrated to device simulations and correlated to the extracted diffusion lengths and doping concentrations. An effective Shockley-Read-Hall lifetime of between 90-200 us provides the best fit to the dark current of these structures.
Keywords: InGaAs; SWIR; minority carrier diffusion length; mobility; lifetime; doping dependence; modeling and simulation; dark current; pixel pitch

Optimization of data processing with the Akinetic swept-laser: algorithm to automatically adjust the a-scan synchronization delay - Rivard, Maxime; Lamouche, Guy (Optical Coherence Tomography and Coherence Domain Optical Methods in Biomedicine XXI, 2017)
The Akinetic swept-laser (Insight, Lafayette, USA) is an all-semiconductor compact and tunable laser source for optical coherence tomography (OCT). Wavelength sweeps with this source are composed of valid data sections interleaved with invalid data sections. The source provides a precise trigger for each wavelength sweep and a “data valid vector” (DVV) file which identifies the indices of the valid data points in a recorded interferogram. In order to identify valid data in real time during acquisition, a delay must be precisely adjusted between the trigger and the wavelength sweep. Optimizing this delay becomes tedious when changing the interferometer configuration in a multi-purpose OCT system. The source provides tools to do this, but they are not automated and require a sample with a single clean reflection. We developed a simple and robust algorithm, integrated in our OCT data acquisition and treatment software, for finding the optimal delay correction that must be applied to accurately identify the valid data obtained with the Akinetic swept-laser. It can perform optimization either from the laser spectrum or from an interferogram and facilitates delay readjustment when the interferometer configuration is modified.

External amplification of OCT swept-sources for challenging applications: from 10 mW to more than 120 mW - Rivard, Maxime; Villeneuve, Alain; Lamouche, Guy (Optical Coherence Tomography and Coherence Domain Optical Methods in Biomedicine XXI, 2017)
For bioimaging applications, commercial swept-sources currently provide enough power (tens of milliwatts) insuring good imaging condition without damaging the tissues. For industrial applications, more power is needed since the amount of light collected can be very low due to challenging measurement conditions or due to poor sample reflectivity. To address this challenge, we explore three different setups to externally amplify the output of a commercial swept-source: a booster semiconductor optical amplifier (BOA), an erbium-doped fiber amplifier (EDFA) and a combination of both. These external amplification setups allow the exploration of emerging OCT applications without the need to develop new hardware.

Ex-vivo evaluation of an early caries detector based on integrated OCT and polarized Raman spectroscopy (conference presentation) - Lamouche, Guy; Padioleau, Christian; Hewko, Mark; Smith, Michael S. D.; Schattka, Bernie J.; Fulton, Crystal; Gauthier, Bruno; Beauchesne, André; Ko, Alex C.; Choo-Smith, Lin-P'ing; Sowa, Michael G. (Lasers in Dentistry XXIII, 2017)
Early detection of incipient caries would allow dentists to provide more effective measures to delay or to reverse caries’ progression at earlier stage. Such earlier intervention could lead to improved oral health for the patients and reduced burden to the health system. Previously, we have demonstrated that the combination of morphological and biochemical information furnished by optical coherence tomography (OCT) and polarized Raman spectroscopy (PRS), respectively, provided a unique tool for dental caries management. In this study we will report the first pre-clinical caries detection system that includes a hand-held probe with a size slightly larger than a tooth brush. This probe presents a novel platform combining both OCT and PRS optics in a very tight space ideal for clinical practice. OCT cross-sectional images of near-surface enamel morphology are obtained with miniaturized MEMS scanning device and are processed in real-time to identify culprit regions. These regions are sequentially analyzed with polarized Raman spectroscopy for further confirmation. PRS is performed using 830nm laser line and four detection channels in order to obtain polarized Raman spectroscopic data, i.e. depolarization ratio of the hydroxyapatite Raman band at ~960 cm-1. A detailed description of this hand-held caries detector and ex-vivo/in-vivo test results will be presented.

Biotin-transfer from a trifunctional crosslinker for identification of cell surface receptors of soluble protein ligands - Tremblay, Tammy-Lynn; Hill, Jennifer J. (Scientific Reports, 2017)
Here we describe a novel crosslinker and its application as a biotin-transfer reagent to identify cell surface receptors of soluble protein ligands on live cells. This crosslinker contains three functional groups: an aldehyde-reactive aminooxy group, a sulfhydryl, and a biotin (ASB). It is readily synthesized via a 3-step addition reaction using standard solid-phase peptide synthesis methods and commercially available intermediates, allowing access to laboratories without specialized synthetic chemistry capabilities. For the biotin-transfer method, ASB is linked to a protein ligand through the sulfhydryl group in a two-step process that allows the introduction of a disulfide bond between the ligand and the crosslinker. Incubation of the labelled ligand with oxidized live cells leads to the formation of crosslinks with aldehyde-containing glycans on the cell surface receptor. Subsequent reduction of the disulfide bond results in biotin transfer from the ligand to the cell surface receptor. Protein biotinylation that is mediated by ligand binding to its receptor is differentiated from background biotinylation events by comparison with a similarly labelled control protein using comparative proteomic mass spectrometry to quantify streptavidin-bound proteins. Using this method, we successfully identified the cell surface receptors of a peptide hormone, a monoclonal antibody, and a single-domain antibody-Fc fusion construct.

Apolipoprotein E isoforms differentially regulate Alzheimer's disease and amyloid-β-induced inflammatory response in vivo and in vitro - Dorey, Evan; Bamji-Mirza, Michelle; Najem, Dema; Li, Yan; Liu, Hong; Callaghan, Debbie; Walker, Douglas; Lue, Lih-Fen; Stanimirovic, Danica; Zhang, Wandong (Journal of Alzheimer's Disease, 2017)
Neuroinflammation plays a critical role in neuronal dysfunction and death of Alzheimer’s disease (AD). ApoE4 is a major risk factor of AD, while ApoE2 is neuroprotective. Little is known about the roles of ApoE isoforms in the neuroinflammation seen in AD. Their roles and mechanisms in Aβ-induced/neuroinflammation were investigated in this study using in vivo and in vitro models. Rat astrocytes were treated with lipid-poor recombinant hApoE and/or Aβ42. Mouse astrocyte lines-expressing lipidated hApoE were treated with Aβ42 and/or vitamin D receptor (VDR) agonist, 1α,25-dihydroxyvitamin D3. Cells and media were harvested for cytokine ELISA, RNA isolated for qRT-PCR, and nuclear protein for transcription factor (TF) arrays and EMSA. hApoE-transgenic and AD mice were mated to generate hApoE2/AD and hApoE4/AD mice. Mice were euthanized at 6 months of age. Brain tissues were collected for cytokine ELISA array, Aβ ELISA, immunoblotting, and immunohistochemistry. hApoE4/AD mice had significantly higher levels of inflammatory cytokines than hApoE2/AD mice. Lipidated hApoE4 significantly promoted inflammatory gene expression induced by Aβ42 but not recombinant hApoE4 in astrocytes as compared to controls. Lipidated hApoE3 provided a certain degree of protection against Aβ42-induced inflammatory response but not recombinant hApoE3 as compared to controls. Both lipidated and recombinant hApoE2 provided protection against Aβ42-induced inflammatory response compared to controls. TF array revealed that ApoE2 strongly activated VDR in Aβ42-treated astrocytes. Application of 1α,25-dihydroxyvitamin D3 completely inhibited Aβ-induced inflammatory gene expression in hApoE4-expressing astrocytes. The results suggest that ApoE4 promotes, but ApoE2 inhibits, AD/Aβ-induced neuroinflammation via VDR signaling. Targeting VDR signaling or active form of VD3 may relieve AD neuroinflammation or/and neurodegeneration.
Keywords: Alzheimer’s disease; amyloid-β peptides; ApoE isoform proteins; neuroinflammation; vitamin D receptorsignaling

Asymmetric Fc engineering for bispecific antibodies with reduced effector function - Escobar-Cabrera, Eric; Lario, Paula; Baardsnes, Jason; Schrag, Joseph; Durocher, Yves; Dixit, Surjit (Antibodies, 2017)
Asymmetric bispecific antibodies are a rapidly expanding therapeutic antibody class, designed to recognize two different target epitopes concurrently to achieve novel functions not available with normal antibodies. Many therapeutic designs require antibodies with reduced or silenced effector function. Although many solutions have been described in the literature to knockout effector function, to date all of them have involved the use of a specific antibody subtype (e.g., IgG2 or IgG4), or symmetric mutations in the lower hinge or CH2 domain of traditional homodimeric monospecific antibodies. In the context of a heterodimeric Fc, we describe novel asymmetric Fc mutations with reduced or silenced effector function in this article. These heteromultimeric designs contain asymmetric charged mutations in the lower hinge and the CH2 domain of the Fc. Surface plasmon resonance showed that the designed mutations display much reduced binding to all of the Fc gamma receptors and C1q. Ex vivo ADCC and CDC assays showed a consistent reduction in activity. Differential scanning calorimetry showed increased thermal stability for some of the designs. Finally, the asymmetric nature of the introduced charged mutations allowed for separation of homodimeric impurities by ion exchange chromatography, providing, as an added benefit, a purification strategy for the production of bispecific antibodies with reduced or silenced effector function.
Keywords: Fc engineering; asymmetric bispecific antibody; ion exchange chromatography; knock-out effector function

Sulfated archaeal glycolipid archaeosomes as a safe and effective vaccine adjuvant for induction of cell-mediated immunity - McCluskie, M. J.; Deschatelets, L.; Krishnan, L. (Human Vaccines and Immunotherapeutics, 2017)
Archaeosomes are liposomal vesicles composed of ether glycerolipids unique to the domain of Archaea. Unlike conventional ester-linked liposomes, archaeosomes exhibit high stability and possess strong adjuvant and immunostimulatory properties making them an attractive vaccine delivery vehicle. Traditionally comprised of total polar lipids (TPL) or semi-synthetic phospho-glycerolipids of ether-linked isoprenoid phytanyl cores with varied glycol- and amino-head groups, archaeosomes can induce robust and long-lasting humoral and cell-mediated immune responses against antigenic cargo and provide protection in murine models of infectious disease and cancer. However, traditional TPL archaeosome formulations are relatively complex comprising several lipid species. Semi-synthetic archaeosomes tested previously contain a combination of several phospho-glycolipids (negative and neutral charged) to produce a stable, uniform-sized liposome formulation. Moreover, they involve many synthetic steps to arrive at the final desired glycolipid composition. Herein, we present a novel adjuvant formulation comprising a sulfated saccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA). SLA individually or mixed with uncharged glyolipid (lactosylarchaeol, LA) constituted efficacious carrier vesicles for entrapped antigens (ovalbumin or melanoma associated tyrosinase-related protein 2 [TRP-2]) and induction of strong cell-mediated responses in mice and protection against subsequent B16 melanoma tumor challenge. Thus, semi-synthetic sulfated glycolipid archaeosomes represent a new class of adjuvants that will potentially ease manufacturing and scale-up, while retaining immunostimulatory activity.
Keywords: adjuvant; archaeosome; delivery; glycolipid; immune modulators; immune response; mice; vaccine; vaccinology

An engineered TGF-β monomer that functions as a dominant negative to block TGF-β signaling - Kim, Sun Kyung; Barron, Lindsey; Hinck, Cynthia S.; Petrunak, Elyse M.; Cano, Kristin E.; Thangirala, Avinash; Iskra, Brian; Brothers, Molly; Vonberg, Machell; Leal, Belinda; Richter, Blair; Kodali, Ravindra; et al. (Journal of Biological Chemistry, 2017)
The transforming growth factor beta isoforms, TGF-β1, -β2, and -β3 are small secreted homodimeric signaling proteins with essential roles in regulating the adaptive immune system and maintaining the extracellular matrix. However, dysregulation of the TGF-β pathway is responsible for promoting the progression of several human diseases, including cancer and fibrosis. In spite of the known importance of TGF-βs in promoting disease progression, no inhibitors have been approved for use in humans. Herein, we describe an engineered TGF-β monomer, lacking the heel helix, a structural motif essential for binding the TGF-β type I receptor, TβRI, but dispensible for binding the other receptor required for TGF-β signaling, the TGF-β type II receptor, TβRII, as an alternative therapeutic modality for blocking TGF-β signaling in humans. As shown through binding studies and crystallography, the engineered monomer retained the same overall structure of native TGF-β monomers and bound TβRII in an identical manner. Cell-based luciferase assays showed that the engineered monomer functioned as a dominant negative to inhibit TGF-β signaling with a Ki of 20 - 70 nM. Investigation of the mechanism showed that the high affinity of the engineered monomer for TβRII, coupled with its reduced ability to non-covalently dimerize and its inability to bind and recruit TβRI, enabled it to bind endogenous TβRII, but prevented it from binding and recruiting TβRI to form a signaling complex. Such engineered monomers provide a new avenue to probe and manipulate TGF-β signaling, and may inform similar modifications of other TGF-β family members.

Generation of monoclonal pan-hemagglutinin antibodies for the quantification of multiple strains of influenza - Manceur, Aziza P.; Zou, Wei; Marcil, Anne; Paquet, Eric; Gadoury, Christine; Jaentschke, Bozena; Li, Xuguang; Petiot, Emma; Durocher, Yves; Baardsnes, Jason; l Rosa-Calatrava, Manue; Ansorge, Sven; et al. (PLoS ONE, 2017)
Vaccination is the most effective course of action to prevent influenza. About 150 million doses of influenza vaccines were distributed for the 2015–2016 season in the USA alone according to the Centers for Disease Control and Prevention. Vaccine dosage is calculated based on the concentration of hemagglutinin (HA), the main surface glycoprotein expressed by influenza which varies from strain to strain. Therefore yearly-updated strain-specific antibodies and calibrating antigens are required. Preparing these quantification reagents can take up to three months and significantly slows down the release of new vaccine lots. Therefore, to circumvent the need for strain-specific sera, two anti-HA monoclonal antibodies (mAbs) against a highly conserved sequence have been produced by immunizing mice with a novel peptide-conjugate. Immunoblots demonstrate that 40 strains of influenza encompassing HA subtypes H1 to H13, as well as B strains from the Yamagata and Victoria lineage were detected when the two mAbs are combined to from a pan-HA mAb cocktail. Quantification using this pan-HA mAbs cocktail was achieved in a dot blot assay and results correlated with concentrations measured in a hemagglutination assay with a coefficient of correlation of 0.80. A competitive ELISA was also optimised with purified viral-like particles. Regardless of the quantification method used, pan-HA antibodies can be employed to accelerate process development when strain-specific antibodies are not available, and represent a valuable tool in case of pandemics. These antibodies were also expressed in CHO cells to facilitate large-scale production using bioreactor technologies which might be required to meet industrial needs for quantification reagents. Finally, a simulation model was created to predict the binding affinity of the two anti-HA antibodies to the amino acids composing the highly conserved epitope; different probabilities of interaction between a given amino acid and the antibodies might explain the affinity of each antibody against different influenza strains.

Correction to binding properties of the transforming growth factor-β coreceptor betaglycan: proposed mechanism for potentiation of receptor complex assembly and signaling - Villarreal, M. M.; Kim, S. K.; Barron, L.; Kodali, R.; Baardsnes, J.; Hinck, C. S.; Krzysiak, T. C.; Henen, M. A.; Pakhomova, O.; Mendoza, V.; O'Connor-McCourt, M. D.; Lafer, E. M.; et al. (Biochemistry, 2017)

Culling of APCs by inflammatory cell death pathways restricts TIM3 and PD-1 expression and promotes the survival of primed CD8 T cells - Patel, Rajen; Kim, Kwangsin; Shutinoski, Bojan; Wachholz, Kristina; Krishnan, Lakshmi; Sad, Subash (Cell Death and Differentiation, 2017)
We evaluated the impact of premature cell death of antigen-presenting cells (APCs) by Caspase-1- and RipK3-signaling pathways on CD8+ T-cell priming during infection of mice with Salmonella typhimurium (ST). Our results indicate that Caspase1 and RipK3 synergize to rapidly eliminate infected APCs, which does not influence the initial activation of CD8+ T cells. However, the maintenance of primed CD8+ T cells was greatly compromised when both these pathways were disabled. Caspase-1- and RipK3-signaling did not influence NF-κB signaling in APCs, but synergized to promote processing of IL-1 and IL-18. Combined deficiency of Caspase1 and RipK3 resulted in compromised innate immunity and accelerated host fatality due to poor processing of IL-18. In contrast, synergism in cell death by Caspase-1- and RipK3 resulted in restriction of PD-1 and TIM3 expression on primed CD8+ T cells, which promoted the survival of activated CD8+ T cells.

The JCMT Gould Belt Survey: a first look at SCUBA-2 observations of the Lupus I molecular cloud - Mowat, C.; Hatchell, J.; Rumble, D.; Kirk, H.; Buckle, J.; Berry, D. S.; Broekhoven-Fiene, H.; Currie, M. J.; Jenness, T.; Johnstone, D.; Mottram, J. C.; Pattle, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
This paper presents observations of the Lupus I molecular cloud at 450 and 850 mum with Submillimetre Common User Bolometer Array (SCUBA-2) as part of the James Clerk Maxwell Telescope Gould Belt Survey (JCMT GBS). Nine compact sources, assumed to be the discs of young stellar objects (YSOs), 12 extended protostellar, pre-stellar and starless cores, and one isolated, low-luminosity protostar, are detected in the region. Spectral energy distributions, including submillimetre fluxes, are produced for 15 YSOs, and each is fitted with the models of Robitaille et al. The proportion of Class 0/I protostars is higher than that seen in other Gould Belt regions such as Ophiuchus and Serpens. Circumstellar disc masses are calculated for more evolved sources, while protostellar envelope masses are calculated for protostars. Up to four very low luminosity objects are found; a large fraction when compared to other Spitzer c2d regions. One YSO has a disc mass greater than the minimum mass solar nebula. 12 starless/protostellar cores are detected by SCUBA-2 and their masses are calculated. The stability of these cores is examined using both the thermal Jeans mass and a turbulent virial mass when possible. Two cores in Lupus I are super-Jeans and contain no known YSOs. One of these cores has a virial parameter of 1.1 ± 0.4, and could therefore be pre-stellar. The high ratio of Class 0/I to Class III YSOs (1:1), and the presence of a pre-stellar core candidate, provides support for the hypothesis that a shock recently triggered star formation in Lupus I.
Keywords: catalogues; stars: formation; stars: pre-main; sequence stars:protostars; ISM: structure; submillimetre: general; stars: pre-main-sequence; stars: protostars

The JCMT Gould Belt Survey: a first look at IC 5146 - Johnstone, D.; Ciccone, S.; Kirk, H.; Mairs, S.; Buckle, J.; Berry, D. S.; Broekhoven-Fiene, H.; Currie, M. J.; Hatchell, J.; Jenness, T.; Mottram, J. C.; Pattle, K.; et al. (The Astrophysical Journal, 2017)
We present 450 and 850 mum submillimeter continuum observations of the IC 5146 star-forming region taken as part of the James Clerk Maxwell Telescope Gould Belt Survey. We investigate the location of bright submillimeter (clumped) emission with the larger-scale molecular cloud through comparison with extinction maps, and find that these denser structures correlate with higher cloud column density. Ninety-six individual submillimeter clumps are identified using FellWalker, and their physical properties are examined. These clumps are found to be relatively massive, ranging from 0.5 M&sun; to 116 M&sun; with a mean mass of 8 M&sun; and a median mass of 3.7 M&sun; . A stability analysis for the clumps suggests that the majority are (thermally) Jeans stable, with M/MJ < 1. We further compare the locations of known protostars with the observed submillimeter emission, finding that younger protostars, i.e., Class 0 and I sources, are strongly correlated with submillimeter peaks and that the clumps with protostars are among the most Jeans unstable. Finally, we contrast the evolutionary conditions in the two major star-forming regions within IC 5146: the young cluster associated with the Cocoon Nebula and the more distributed star formation associated with the Northern Streamer filaments. The Cocoon Nebula appears to have converted a higher fraction of its mass into dense clumps and protostars, the clumps are more likely to be Jeans unstable, and a larger fraction of these remaining clumps contain embedded protostars. The Northern Streamer, however, has a larger number of clumps in total and a larger fraction of the known protostars are still embedded within these clumps.
Keywords: ISM: clouds; ISM: structure; stars: formation; stars: protostars; submillimeter: galaxies; submillimeter: ISM

The massive survey VI: the spatial distribution and kinematics of warm ionized gas in the most massive local early-type galaxies - Pandya, Viraj; Greene, Jenny E.; Ma, Chung-Pei; Veale, Melanie; Ene, Irina; Davis, Timothy A.; Blakeslee, John P.; Goulding, Andy D.; McConnell, Nicholas J.; Nyland, Kristina; Thomas, Jens (The Astrophysical Journal, 2017)
We present the first systematic investigation of the existence, spatial distribution, and kinematics of warm ionized gas as traced by the [O ii] 3727 Å emission line in 74 of the most massive galaxies in the local universe. All of our galaxies have deep integral-field spectroscopy from the volume- and magnitude-limited MASSIVE survey of early-type galaxies with stellar mass long(M*/M.)>11.5(Mk >-25.3 mag) and distance D < 108 Mpc. Of the 74 galaxies in our sample, we detect warm ionized gas in 28, which yields a global detection fraction of 38 ± 6% down to a typical [O ii] equivalent width limit of 2 Å. MASSIVE fast rotators are more likely to have gas than MASSIVE slow rotators with detection fractions of 80 ± 10% and 28 ± 6%, respectively. The spatial extents span a wide range of radii (0.6–18.2 kpc; 0.1–4R e ), and the gas morphologies are diverse, with 17/28 ≈ 61 ± 9% being centrally concentrated, 8/28 ≈ 29 ± 9% exhibiting clear rotation out to several kiloparsecs, and 3/28 ≈ 11 ± 6% being extended but patchy. Three out of four fast rotators show kinematic alignment between the stars and gas, whereas the two slow rotators with robust kinematic measurements available exhibit kinematic misalignment. Our inferred warm ionized gas masses are roughly ~105 M ⊙. The emission line ratios and radial equivalent width profiles are generally consistent with excitation of the gas by the old underlying stellar population. We explore different gas origin scenarios for MASSIVE galaxies and find that a variety of physical processes are likely at play, including internal gas recycling, cooling out of the hot gaseous halo, and gas acquired via mergers.
Keywords: galaxies: elliptical and lenticular, cD; galaxies: evolution; galaxies: ISM; galaxies: kinematics and dynamics; ISM: lines and bands

The massive survey VII: the relationship of angular momentum, stellar mass and environment of early-type galaxies - Veale, Melanie; Ma, Chung-Pei; Greene, Jenny E.; Thomas, Jens; Blakeslee, John P.; McConnell, Micholas; Walsh, Jonelle L.; Ito, Jennifer (Monthly Notices of the Royal Astronomical Society, 2017)
We analyse the environmental properties of 370 local early-type galaxies (ETGs) in the MASSIVE and ATLAS3D surveys, two complementary volume-limited integral-field spectroscopic (IFS) galaxy surveys spanning absolute -band magnitude, or stellar mass. We find these galaxies to reside in a diverse range of environments measured by four methods: group membership (whether a galaxy is a brightest group/cluster galaxy, satellite, or isolated), halo mass, large-scale mass density (measured over a few Mpc), and local mass density (measured within the th neighbour). The spatially resolved IFS stellar kinematics provide robust measurements of the spin parameter and enable us to examine the relationship among, and galaxy environment. We find a strong correlation between and where the average decreases from to below 0.1 with increasing mass, and the fraction of slow rotators increases from % to 90%. We show for the first time that at fixed, there are almost no trends between galaxy spin and environment; the apparent kinematic morphology-density relation for ETGs is therefore primarily driven by and is accounted for by the joint correlations between and spin, and between and environment. A possible exception is that the increased at high local density is slightly more than expected based only on these joint correlations. Our results suggest that the physical processes responsible for building up the present-day stellar masses of massive galaxies are also very efficient at reducing their spin, in any environment.
Keywords: astrophysics of galaxies (astro-ph.GA); cosmology and nongalactic astrophysics (astro-ph.CO)

OSSOS. V. diffusion in the orbit of a high-perihelion distant solar system object - Bannister, Michele T.; Shankman, Cory; Volk, Kathryn; Chen, Ying-Tung; Kaib, Nathan; Gladman, Brett J.; Jakubik, Marian; Kavelaars, J. J.; Fraser, Wesley C.; Schwamb, Megan E.; Petit, Jean-Marc; Wang, Shiang-Yu; et al. (The Astronomical Journal, 2017)
We report the discovery of the minor planet 2013 SY99 on an exceptionally distant, highly eccentric orbit. With a perihelion of 50.0. au, 2013 SY99' s orbit has a semimajor axis of 730 +/- 40. au, the largest known for a high-perihelion trans-Neptunian object (TNO), and well beyond those of (90377) Sedna and 2012 VP113. Yet, with an aphelion of 1420 +/- 90. au, 2013 SY99' s orbit is interior to the region influenced by Galactic tides. Such TNOs are not thought to be produced in the current known planetary architecture of the solar system, and they have informed the recent debate on the existence of a distant giant planet. Photometry from the Canada-France-Hawaii Telescope, Gemini North, and Subaru indicate 2013 SY99 is similar to 250. km in diameter and moderately red in color, similar to other dynamically excited TNOs. Our dynamical simulations show that Neptune's weak influence during 2013 SY99' s perihelia encounters drives diffusion in its semimajor axis of hundreds of astronomical units over 4. Gyr. The overall symmetry of random walks in the semimajor axis allows diffusion to populate 2013 SY99' s orbital parameter space from the 1000 to 2000. au inner fringe of the Oort cloud. Diffusion affects other known TNOs on orbits with perihelia of 45 to 49. au and semimajor axes beyond 250. au. This provides a formation mechanism that implies an extended population, gently cycling into and returning from the inner fringe of the Oort cloud.

ALMA observations of asymmetric molecular gas emission from a protoplanetary disk in the orion nebula - Factor, Samuel M.; Hughes, A. M.; Flaherty, Kevin M.; Mann, Rita K.; Francesco, James Di; Williams, Jonathan P.; Ricci, Luca; Matthews, Brenda C.; Bally, John; Johnstone, Doug (The Astronomical Journal, 2017)
We present Atacama Large Millimeter/submillimeter Array (ALMA) observations of molecular line emission from d216-0939, one of the largest and most massive protoplanetary disks in the Orion Nebula Cluster. We model the spectrally resolved HCO+ (4–3), CO (3–2), and HCN (4–3) lines observed at 0".5 resolution to fit the temperature and density structure of the disk. We also weakly detect and spectrally resolve the CS (7–6) line but do not model it. The abundances we derive for CO and HCO+ are generally consistent with expected values from chemical modeling of protoplanetary disks, while the HCN abundance is higher than expected. We dynamically measure the mass of the central star to be 2.17 ± 0.07M., which is inconsistent with the previously determined spectral type of K5. We also report the detection of a spatially unresolved high-velocity blueshifted excess emission feature with a measurable positional offset from the central star, consistent with a Keplerian orbit at 60 ± 20 au. Using the integrated flux of the feature in HCO+ (4–3), we estimate the total H2 gas mass of this feature to be at least 1.8-8MJupiter, depending on the assumed temperature. The feature is due to a local temperature and/or density enhancement consistent with either a hydrodynamic vortex or the expected signature of the envelope of a forming protoplanet within the disk.
Keywords: planets and satellite: formation; protoplanetary disks; radio line: planetary systems; stars: individual (V2377 Ori); stars: pre-main sequence

Hydrothermal post-treatment of digestate to maximize the methane yield from the anaerobic digestion of microalgae - Nuchdang, S.; Frigon, J-C; Pilon, G.; Phalakornkule, C.; Guiot, S. R. (Waste Management, 2017)
As an alternative to applying the hydrothermal treatment to the raw algal feedstock before the anaerobic digestion (i.e. pre-treatment), one considered a post-treatment scenario where anaerobic digestion is directly used as the primary treatment while the hydrothermal treatment is thereafter applied to the digestate. Hydrothermal treatments such as wet oxidation (WetOx) and hydrothermal carbonization (HTC) were compared at a temperature of 200°C, for initial pressure of 0.1 and 0.82MPa, and no holding time after the process had reached the temperature setpoint. Both WetOx and HTC resulted in a substantial solids conversion (47-62% with HTC, 64-83% with WetOx, both at 0.82MPa) into soluble products, while some total chemical oxygen demand-based carbon loss from the solid-liquid phases was observed (20-39%). This generated high soluble products concentrations (from 6.2 to 10.9g soluble chemical oxygen demand/L). Biomethane potential tests showed that these hydrothermal treatments allowed for a 4-fold improvement of the digestate anaerobic biodegradability. The hydrothermal treatments increased the methane yield to about 200 LSTP CH4/kg volatile solids, when related to the untreated digestate, compared to 66 LSTP CH4/kg volatile solids, without treatment.
Keywords: anaerobic digestion; biomethane; hydrothermal carbonization; microalgae; scenedesmus; solubilization; wet oxidation

Facile synthesis of α-MnO2 with a 3D staghorn coral-like micro-structure assembled by nano-rods and its application in electrochemical supercapacitors - Bing, Yonghong; Zhang, Lei; Mu, Shichun; Zhang, Jiujun (Applied Sciences, 2017)
Manganese oxides with an alpha crystal structure are synthesized via combined solid-state reaction and wet chemical processing, which is a simple and inexpensive synthetic route easy for mass production. The effects of the synthetic reaction duration and the temperature of acid treatments on crystal structure, morphology, and electrochemical capacitive properties of α-MnO2 are discussed. It is evidenced that the samples treated in acid for a longer time at 25 °C display the uniform nanorods that are aggregated to form micro-buildings with fine features on the surface of rods. This microstructure possesses large surface areas and more active sites that are easy to access electrochemically, leading to a better electrochemical capacitive performance. We expected that these results would provide the practical information for shape- and morphology-controlled synthesis for nanostructured functional materials in supercapacitor applications.
Keywords: nanostructured alpha-MnO2; shape controlled synthesis; electrochemical supercapacitor

Physical and electrochemical properties of some phosphonium-based ionic liquids and the performance of their electrolytes in lithium-ion batteries - Salem, Nuha; Zavorine, Serguei; Nucciarone, Donato; Whitbread, Kristina; Moser, Mike; Abu-Lebdeh, Yaser (Journal of The Electrochemical Society, 2017)
In this work, three ionic liquids with two different cations and two different anions: trimethyl propyl phosphonium bis-fluorosulfonyl imide (P1113FSI), trimethyl isobutyl phosphonium bis-fluorosulfonyl imide (P111i4FSI) and trimethyl isobutyl phosphonium bis-trifluoromethylsulfonyl imide (P111i4TFSI) have been characterized and evaluated as electrolytes in lithium ion half-cells. It is found that ionic liquids with FSI− anion have superior properties over their TFSI− counterparts and those with the smaller cation, P1113, have better conductivity and viscosity. The two ionic liquids with FSI anion, P1113FSI and P111i4FSI, are liquid at room temperature and show high conductivities and low viscosities, reaching 10.0 mS/cm and 30 cP at room temperature for P1113FSI. They also exhibit electrochemical windows higher than 5 V and thermal stability exceeding 300°C. Mixing the ionic liquids with 0.5 M LiPF6 increases viscosities, lowers conductivities but improves electrochemical cathodic stability. The electrolyte mixtures have been evaluated in graphite/Li half cells, Li/LiFePO4 and Li/LiMn1.5Ni0.5O4 at C/12 for 100 cycles and at different rates: C/6, C/3, C and 2C for rate capabilities. Battery testing shows that unlike their TFSI− counterparts both ionic liquids with FSI− anion perform well with graphite anode and LiFePO4 cathode but fail with the higher voltage LiMn1.5Ni0.5O4 cathode.
Keywords: battery cathode; battery safety; electrolyte; Lithium ion battery; Phosphonium ionic liquid

A method to calculate the bulk hardness of metal matrix composite using Hadfield steel reinforced with niobium carbide particles as an example - Ma, Liang; Huang, Cheng; Dolman, Kavin; Tang, Xinhu; Yang, Jianjun; Shi, Zheng; Liu, Zhong-Sheng (Mechanics of Materials, 2017)
A conceptual model is proposed in this paper to calculate the bulk hardness of particle-reinforced metal matrix composites. Hadfield steel with niobium carbide particles is taken as an example to show the feasibility of this proposed method. A micro-scale concept called representative equivalent volume is used to investigate the heterogeneous microstructure and the impact of water quenching on the equivalent mechanical properties of the metal matrix composite. Furthermore, the continuum-scale indentation process used in laboratory hardness testing is simulated by the finite element method based on the stress-strain curves obtained from the micro-scale modeling. The simulated hardness is compared with laboratory measurements and a good agreement is observed confirming the model.
Keywords: metal matrix composite; microstructure; hardness; finite element method; hadfield steel; niobium carbide; representative equivalent volume

Amidinium salts: towards enabling electrochemistry in non-polar media from alkanes to ionic liquids - Abu-Lebdeh, Yaser; Hammami, Amer; Abouimrane, Ali; Armand, Michel (Electrochemistry Communications, 2017)
There is little known about electrochemical behavior in non-polar media due to lack of compatible, hydrophobic salts. In this work, this difficult challenge has been overcome by following a strategy based on designing and synthesizing a novel family of organic salts with highly-delocalized cations and anions. The salts are based on the amidinium cation with highly-delocalized positive charge and long alkyl groups that enable good miscibility in heptane, an archetypical, non-polar media, while being hydrophobic, room-temperature ionic liquids. The electrolyte solutions show ionic conductivities that span the range 10− 11–10− 4 S cm− 1 and electrochemical activity which enable their application as antistatic agents and also as new type of hydrophobic electrolytes in various electrochemical devices.
Keywords: amidinium salts; non-polar media; hydrophobic ionic liquids; hydrophobic electrolytes; alkanes; charge delocalization

A 1420 MHz catalog of compact sources in the Northern Galactic Plane - Taylor, A. R.; Leahy, D. A.; Tian, W. W.; Sunstrum, C.; Kothes, R.; Landecker, T. L.; Ransom, R. R.; Higgs, L. A. (The Astronomical Journal, 2017)
We present a catalog of compact sources of radio emission at 1420 MHz in the northern Galactic plane from the Canadian Galactic Plane Survey. The catalog contains 72,758 compact sources with an angular size less than 3' within the Galactic longitude range 52° < ℓ < 192° down to a 5σ detection level of ~1.2 mJy. Linear polarization properties are included for 12,368 sources with signals greater than 4σ QU in the Canadian Galactic Plane Survey (CGPS) Stokes Q and U images at the position of the total intensity peak. We compare CGPS flux densities with cataloged flux densities in the Northern VLA Sky Survey catalog for 10,897 isolated unresolved sources with CGPS flux density greater than 4 mJy to search for sources that show variable flux density on timescales of several years. We identify 146 candidate variables that exhibit high fractional variations between the two surveys. In addition, we identify 13 candidate transient sources that have CGPS flux density above 10 mJy but are not detected in the Northern VLA Sky Survey.

Planar avalanche photodiodes with edge breakdown suppression using a novel selective area growth based process - Pitts, O. J.; Hisko, M.; Benyon, W.; Bonneville, G.; Storey, C.; SpringThorpe, A. J. (Journal of Crystal Growth, 2017)
We propose and demonstrate a novel process to fabricate planar avalanche photodiodes using selective area growth (SAG) followed by a single Zn diffusion through the SAG material using the same dielectric mask. The tapered surface profile of the SAG epitaxy due to the enhancement of the growth rate in the vicinity of the mask edge modifies the diffusion profile, resulting in a gradual reduction of the diffusion depth towards the outer edge of the active area. The associated reduction of the electric field counteracts the edge curvature effect sufficiently to suppress edge breakdown. For undoped InP SAG epitaxy, small areas of higher electric field occur where the mask edge is along the [1 0 0] or [0 1 0] directions, associated with the formation of enhanced ridges in the SAG material in these locations. Similar ridges are observed for Si-doped InP and InP/InGaAs/InP SAG structures, but the enhancement of the electric field in these locations is significantly lower.
Keywords: selective epitaxy; metalorganic vapor phase epitaxy; phosphides; semiconducting III-V materials; avalanche photodiodes

Highly sensitive fiber random-grating-based random laser sensor for ultrasound detection - Xu, Yanping; Zhang, Liang; Gao, Song; Lu, Ping; Mihailov, Stephen; Bao, Xiaoyi (Optics Letters, 2017)
A novel highly sensitive ultrasound sensor based on a random fiber laser is proposed and demonstrated for the first time, to the best of our knowledge. The random fiber laser is constructed with the erbium-doped fiber gain. A fiber random grating provides random-distributed feedback for the random laser and acts as an ultrasound sensing head. The random laser can operate in a single-mode lasing scenario, which offers linear and pure temporal responses to the broadband ultrasonic acoustic emission from 20 kHz to 0.8 MHz. The multiple-interfering reflection spectrum of the random grating provides a large number of steep peak areas over a broad spectral range, which significantly enhances the sensitivity of the random laser sensor and makes it an ideal sensor in harsh environments with large temperature or strain variations. The proposed laser sensor offers signal-to-noise ratio improvement up to 20 dB and higher sensitivity compared with conventional piezoelectric acoustic sensors.

Multi-parameter fiber optic sensors based on fiber random grating - Xu, Yanping; Zhang, Mingjiang; Lu, Ping; Mihailov, Stephen; Bao, Xiaoyi (25th International Conference on Optical Fiber Sensors 24-28 April 2017, Jeju, Republic of Korea, 2017)
Two novel configurations of multi-parameter fiber-optic sensing systems based on the fiber random grating are reported. The fiber random grating is fabricated through femtosecond laser induced refractive index modification over a 10cm standard telecom single mode fiber. In one configuration, the reflective spectrum of the fiber random grating is directly detected and a wavelength-division spectral cross-correlation algorithm is adopted to extract the spectral shifts for simultaneous measurement of temperature, axial strain, and surrounding refractive index. In the other configuration, a random fiber ring laser is constructed by incorporating the random feedback from the random grating. Numerous polarization-dependent spectral filters are formed along the random grating and superimposed to provide multiple lasing lines with high signal-to-noise ratio up to 40dB, which enables a high-fidelity multi-parameter sensing scheme by monitoring the spectral shifts of the lasing lines. Without the need of phase mask for fabrication and with the high physical strength, the random grating based sensors are much simpler and more compact, which could be potentially an excellent alternative for liquid medical sample sensing in biomedical and biochemical applications.
Keywords: multi-parameter fiber-optic sensing; fiber random grating; wavelength-division spectral cross-correlation; random fiber ring laser

Plane-by-plane inscription of grating structures in optical fibers - Lu, P.; Mihailov, Stephen; Ding, Hanjie; Grobnic, Dan; Walker, R.; Coulas, D.; Hnatovsky, C.; Naumov, A. Y. (25th International Conference on Optical Fiber Sensors 24-28 April 2017, Jeju, Republic of Korea, 2017)
Plane-by-plane fabrication of fiber Bragg gratings in optical fibers using short-pulse femtosecond IR laser is proposed and demonstrated. By incorporating a cylindrical lens in the fabrication setup, a plane of index modification can be directly inscribed in fiber core by a single laser pulse through the proposed method. This plane-by-plane method simplifies the grating inscription process and allows for the fabrication of complicated grating structures.
Keywords: fiber Bragg gratings; femtosecond laser; cylindrica lens

High resolution temperature mapping of gas turbine combustor simulator exhaust with femtosecond laser induced fiber Bragg - Walker, Robert B.; Yun, Sangsig; Ding, Huimin; Charbonneau, Michel; Coulas, David; Lu, ping; Mihailov, Stephen J.; Ramachandran, Nanthan (25th International Conference on Optical Fiber Sensors 24-28 April 2017, Jeju, Republic of Korea, 2017)
Femtosecond infrared (fs-IR) laser written fiber Bragg gratings (FBGs), have demonstrated great potential for extreme sensing. Such conditions are inherent in advanced gas turbine engines under development to reduce greenhouse gas emissions; and the ability to measure temperature gradients in these harsh environments is currently limited by the lack of sensors and controls capable of withstanding the high temperature, pressure and corrosive conditions present. This paper discusses fabrication and deployment of several fs-IR written FBG arrays, for monitoring exhaust temperature gradients of a gas turbine combustor simulator. Results include: contour plots of measured temperature gradients, contrast with thermocouple data.
Keywords: femtosecond FBG; ultrafast FBG; high temperature FBG; fiber Bragg grating; temperature sensor array; gas turbine combustor simulator; exhaust temperature mapping; thermocouples

Combustor deployments of femtosecond laser written fiber Bragg grating arrays for temperature measurements surpassing 1000°C - Walker, Robert B.; Ding, Huimin; Coulas, David; Mihailov, Stephen J.; Duchesne, Marc A.; Hughes, Robin W.; McCalden, David J.; Burchat, Ryan; Yandon, Robert; Yun, Sangsig; Ramachandran, Nanthan; Charbonneau, Michel (Micro- and Nanotechnology Sensors, Systems, and Applications IX, 2017)
Femtosecond Infrared (fs-IR) laser written fiber Bragg gratings (FBGs), have demonstrated great potential for extreme sensing. Such conditions are inherent to advanced power plant technologies and gas turbine engines, under development to reduce greenhouse gas emissions; and the ability to measure temperature gradients in these harsh environments is currently limited by the lack of sensors and controls capable of withstanding the high temperature, pressure and corrosive conditions present. This paper reviews our fabrication and deployment of hundreds of fs-IR written FBGs, for monitoring temperature gradients of an oxy-fuel fluidized bed combustor and an aerospace gas turbine combustor simulator.
Keywords: femtosecond FBG; high temperature FBG; fiber Bragg grating; temperature sensor; fluidized bed combustor; gas turbine combustor simulator; exhaust temperature mapping; thermocouples

Nonlinear photoluminescence imaging applied to femtosecond laser manufacturing of fiber Bragg gratings - Hnatovsky, C.; Grobnic, D.; Mihailov, S. J. (Optics Express, 2017)
Nonlinear photoluminescence imaging is used to visualize the intensity distribution of femtosecond laser pulses inside the optical fiber during Bragg grating inscription based on side illumination through a phase mask. This technique, which results in direct imaging of the inscription laser field inside the optical fiber, facilitates i) the characterization of the laser focus in the vicinity of the fiber core and ii) the optimization of the fiber alignment with respect to the laser focus while using pulses with energies several times lower than those used during the actual inscription process. The applicability of this imaging technique is demonstrated for Bragg grating inscription in different optical fibers, including direct inscription through the fiber coating.

Fire tests on full-scale FRP reinforced concrete slabs - Hajiloo, Hamzeh; Green, Mark F.; Noël, Martin; Bénichou, Noureddine; Sultan, Mohamed (Composite Structures, 2017)
The fire resistance of two concrete slabs reinforced completely with glass fibre reinforced polymer (GFRP) bars was experimentally investigated through a full-scale standard fire test. The Canadian standard on design of FRP reinforced buildings (CSA S806) currently requires 60mm of clear concrete cover in a FRP reinforced concrete slab to ensure 2h of fire resistance. The two concrete slabs, which were identical in every aspect except the types of GFRP reinforcing bars, were designed and fabricated with 60mm concrete cover in this experiment to examine the fire resistance of the existing FRP reinforced concrete structures designed using CSA S806. The uniformly distributed loads were applied causing flexural moment of 45kN·m, which was 55% of the ultimate moment resistance of the slabs at room temperatures, and sustained throughout the fire test. Both loaded slabs endured more than three hours of ASTM-E119 standard fire exposure. The results promised a more efficient and economic application of FRP reinforcing bars in concrete construction. The effects of concrete cover, unexposed length in providing adequate anchoring at the ends, and two different types of widely used GFRP reinforcing bar were studied in this research.
Keywords: fire resistance; fibre reinforced polymer; concrete slab; bond strength; numerical analysis

Rapid protein production from stable CHO cell pools using plasmid vector and the cumate gene-switch - Poulain, A.; Perret, S.; Malenfant, F.; Mullick, A.; Massie, B.; Durocher, Y. (Journal of Biotechnology, 2017)
To rapidly produce large amounts of recombinant proteins, the generation of stable Chinese Hamster Ovary (CHO) cell pools represents a useful alternative to large-scale transient gene expression (TGE). We have developed a cell line (CHOBRI/rcTA) allowing the inducible expression of recombinant proteins, based on the cumate gene switch. After the identification of optimal plasmid DNA topology (supercoiled vs linearized plasmid) for PEIpro™ mediated transfection and of optimal conditions for methionine sulfoximine (MSX) selection, we were able to generate CHOBRI/rcTA pools producing high levels of recombinant proteins. Volumetric productivities of up to 900mg/L were reproducibly achieved for a Fc fusion protein and up to 350mg/L for an antibody after 14days post-induction in non-optimized fed-batch cultures. In addition, we show that CHO pool volumetric productivities are not affected by a freeze-thaw cycle or following maintenance in culture for over one month in the presence of MSX. Finally, we demonstrate that volumetric protein production with the CR5 cumate-inducible promoter is three- to four-fold higher than with the human CMV or hybrid EF1α-HTLV constitutive promoters. These results suggest that the cumate-inducible CHOBRI/rcTA stable pool platform is a powerful and robust system for the rapid production of gram amounts of recombinant proteins.
Keywords: CHO; cell pools; inducible expression system; methionine sulfoximine; polyethylenimine; recombinant proteins

Network analysis reveals a signaling regulatory loop in pik3ca-mutated breast predicting survival outcome - McGee, Shauna R.; Tibiche, Chabane; Trifiro, Mark; Wang, Edwin (Genomics, Proteomics and Bioinformatics, 2017)
Mutated genes are rarely common even in the same pathological type between cancer patients and as such, it has been very challenging to interpret genome sequencing data and difficult to predict clinical outcomes. PIK3CA is one of a few genes whose mutations are relatively popular in tumors. For example, more than 46.6% of luminal-A breast cancer samples have PIK3CA mutated, whereas only 35.5% of all breast cancer samples contain PIK3CA mutations. To understand the function of PIK3CA mutations in luminal A breast cancer, we applied our recently-proposed Cancer Hallmark Network Framework to investigate the network motifs in the PIK3CA-mutated luminal A tumors. We found that more than 70% of the PIK3CA-mutated luminal A tumors contain a positive regulatory loop where a master regulator (PDGF-D), a second regulator (FLT1) and an output node (SHC1) work together. Importantly, we found the luminal A breast cancer patients harboring the PIK3CA mutation and this positive regulatory loop in their tumors have significantly longer survival than those harboring PIK3CA mutation only in their tumors. These findings suggest that the underlying molecular mechanism of PIK3CA mutations in luminal A patients can participate in a positive regulatory loop, and furthermore the positive regulatory loop (PDGF-D/FLT1/SHC1) has a predictive power for the survival of the PIK3CA-mutated luminal A patients.
Keywords: network analysis; PIK3CA mutation; network motif; breast cancer; genome sequencing; survival

Accelerated mass production of influenza virus seed stocks in HEK-293 suspension cell cultures by reverse genetics - Milián, Ernest; Julien, Thomas; Biaggio, Rafael; Venereo-Sanchez, Alin; Montes, Johnny; Manceur, Aziza P.; Ansorge, Sven; Petiot, Emma; Rosa-Calatrava, Manuel; Kamen, Amine (Vaccine, 2017)
Despite major advances in developing capacities and alternative technologies to egg-based production of influenza vaccines, responsiveness to an influenza pandemic threat is limited by the time it takes to generate a Candidate Vaccine Virus (CVV) as reported by the 2015 WHO Informal Consultation report titled "Influenza Vaccine Response during the Start of a Pandemic". In previous work, we have shown that HEK-293 cell culture in suspension and serum free medium is an efficient production platform for cell culture manufacturing of influenza candidate vaccines. This report, took advantage of, recombinant DNA technology using Reverse Genetics of influenza strains, and advances in the large-scale transfection of suspension cultured HEK-293 cells. We demonstrate the efficient generation of H1N1 with the PR8 backbone reassortant under controlled bioreactor conditions in two sequential steps (transfection/rescue and infection/production). This approach could deliver a CVV for influenza vaccine manufacturing within two-weeks, starting from HA and NA pandemic sequences. Furthermore, the scalability of the transfection technology combined with the HEK-293 platform has been extensively demonstrated at >100L scale for several biologics, including recombinant viruses. Thus, this innovative approach is better suited to rationally engineer and mass produce influenza CVV within significantly shorter timelines to enable an effective global response in pandemic situations.
Keywords: candidate Vaccine Virus (CVV); influenza virus; large-scale; pandemic; reverse genetics; suspension cell culture; transient transfection; vaccines

Inhibition of soil microbial activity by nitrogen-based energetic materials - Kuperman, Roman G.; Minyard, Morgan L.; Checkai, Ronald T.; Sunahara, Geoffrey I.; Rocheleau, Sylvie; Dodard, Sabine G.; Paquet, Louise; Hawari, Jalal (Environmental Toxicology and Chemistry, 2017)
We investigated individual toxicities of the nitrogen-based energetic materials (EMs) 2,4-dinitrotoluene (2,4-DNT); 2-amino-4,6-dinitrotoluene (2-ADNT); 4-amino-2,6-dinitrotoluene (4-ADNT); and nitroglycerin (NG) on microbial activity in Sassafras sandy loam (SSL) soil, which has physicochemical characteristics that support very high qualitative relative bioavailability for organic chemicals. Batches of SSL soil for basal respiration (BR) and substrate-induced respiration (SIR) assays were separately amended with individual EMs or acetone carrier control. Total microbial biomass carbon (biomass C) was determined from CO2 production increases after addition of 2500 mg/kg of glucose–water slurry to the soil. Exposure concentrations of each EM in soil were determined using US Environmental Protection Agency method 8330A. Basal respiration was the most sensitive endpoint for assessing the effects of nitroaromatic EMs on microbial activity in SSL, whereas SIR and biomass C were more sensitive endpoints for assessing the effects of NG in soil. The orders of toxicity (from greatest to least) were 4-ADNT > 2,4-DNT = 2-ADNT > NG for BR; but for SIR and biomass C, the order of toxicity was NG > 2,4-DNT > 2-ADNT = 4-ADNT. No inhibition of SIR was found up to and including the greatest concentration of each ADNT tested in SSL. These ecotoxicological data will be helpful in identifying concentrations of contaminant EMs in soil that present acceptable ecological risks for biologically mediated processes in soil.
Keywords: ecological risk assessment; energetic materials; explosives; microbial activity; soil toxicity

Characterization of the pro-inflammatory potencies of purified Jatropha phorbol esters by a gene expression-based in vitro bioassay - Pelletier, Guillaume; Padhi, Bhaja; Hamzeh, Mahsa; Halasz, Annamaria; Singh, Manjeet; Hawari, Jalal; Sunahara, Geoffrey (Toxicological and Environmental Chemistry, 2017)
The oil extracted from Jatropha seeds is an emerging biodiesel feedstock that also contains several pro-inflammatory phorbol esters. These phorbol esters can elicit adverse inflammatory responses through activation of the protein kinase C, as previously described for the prototypical phorbol ester 12-O-tetradecanoylphorbol-13-acetate. We extracted and purified the six phorbol esters identified in Jatropha oil and assessed their pro-inflammatory activities using a recently developed gene expression-based bioassay. Borrowing from an approach used for the assessment of dioxin toxicity, we expressed their pro-inflammatory potencies in relation to the potency of 12-O-tetradecanoylphorbol-13-acetate (in terms of 12-O-tetradecanoylphorbol-13-acetate toxic equivalency factors). The pro-inflammatory potencies of Jatropha phorbol esters were orders of magnitudes below the potency of 12-O-tetradecanoylphorbol-13-acetate. Interestingly, the cytotoxicity of phorbol esters did not appear to be directly related to their pro-inflammatory potencies. Calculations based on phorbol ester potencies and concentrations led to overestimation of the pro-inflammatory activity of Jatropha oil, as measured by the same gene expression-based bioassay. The preliminary results presented here suggest that further work on the described approach may lead to the development of valuable tools and metrics to quantify and predict the pro-inflammatory activities of complex phorbol ester mixtures.
Keywords: in vitro assay; MDCK cells; Jatropha oil; phorbol ester; toxic equivalency factor

Process intensification for high yield production of influenza H1N1 Gag virus-like particles using an inducible HEK-293 stable cell line - Venereo-Sanchez, Alina; Simoneau, Melanie; Lanthier, Stéphane; Chahal, Parminder; Bourget, Lucie; Ansorge, Sven; Gilbert, Rénald; Henry, Olivier (Vaccine, 2017)
Influenza virus dominant antigens presentation using virus like particle (VLP) approach is attractive for the development of new generation of influenza vaccines. Mammalian cell platform offers many advantages for VLP production. However, limited attention has been paid to the processing of mammalian cell produced VLPs. Better understanding of the production system could contribute to increasing the yields and making large-scale VLP vaccine manufacturing feasible. In a previous study, we have generated a human embryonic kidney HEK-293 inducible cell line expressing Hemagglutinin (HA) and Neuraminidase (NA), which was used to produce VLPs upon transient transfection with a plasmid containing HIV-1 Gag. In this work, to streamline the production process, we have developed a new HEK-293 inducible cell line adapted to suspension growth expressing the three proteins HA, NA (H1N1 A/PR/8/1934) and the Gag fused to GFP for monitoring the VLP production. The process was optimized to reach higher volumetric yield of VLPs by increasing the cell density at the time of induction without sacrificing the cell specific productivity. A 5-fold improvement was achieved by doing media evaluation at small scale. Furthermore, a 3-L perfusion bioreactor mirrored the performance of small-scale shake flask cultures with sequential medium replacement. The cell density was increased to 14 × 106 cells/ml at the time of induction which augmented by 60-fold the volumetric yield to 1.54 × 1010 Gag-GFP fluorescent events/ml, as measured by flow cytometry. The 9.5-L harvest from the perfusion bioreactor was concentrated by tangential flow filtration at low shear rate. The electron micrographs revealed the presence of VLPs of 100–150 nm with the characteristic dense core of HIV-1 particles. The developed process shows the feasibility of producing high quantity of influenza VLPs from an inducible mammalian stable cell line aiming at large scale vaccine manufacturing.
Keywords: stable cell line; process developmnet; perfusion; TFF; Gag-VLPs; influenza vaccine

Removal of organic carbon and nitrogen in a membraneless flow-through microbial electrolysis cell - Hussain, Abid; Lebrun, Frédérique Matteau; Tartakovsky, Boris (Enzyme and Microbial Technology, 2017)
This study evaluated performance of an upflow membraneless microbial electrolysis cell (MEC) with flow-through electrodes for wastewater treatment. First, methane production and COD removal were evaluated in continuous flow experiments carried out using synthetic and municipal wastewater. A 29–75% increase in methane production was observed under bioelectrochemical conditions as compared to an anaerobic control. Next, simultaneous removal of COD and nitrogen was studied under microaerobic conditions created by continuous air injection to the anodic compartment of the MEC. While the presence of oxygen decreased Coulombic efficiency due to aerobic degradation of COD, enhanced ammonium removal with near zero nitrite and nitrate effluent concentrations was observed. Evidence of direct ammonium oxidation at the anode as well as nitrite and nitrate reduction at the cathode was obtained by comparing performances of MECs operated under anaerobic and microaerobic conditions with the control reactor operated at zero applied voltage.
Keywords: microbial electrolysis cell; flow-through; micro-aerobic; membraneless; nitrogen removal

Draft genome sequence of Pseudoruegeria sp. SK021, a representative of the marine Roseobacter group, isolated from North Sea sediment - Pohlner, Marion; Marshall, Ian; Schreiber, Lars; CYpionka, Heribert; Engelen, Bert (Genome Announcements, 2017)
Pseudoruegeria sp. SK021 is a member of the Roseobacter group, isolated under aerobic conditions from North Sea sediment. The draft genome comprises 3.95 Mb and contains 3,747 protein-coding sequences. Although the strain is nonmotile under laboratory conditions, the entire set of genes for the formation of a flagellar apparatus was found.

Carbon nanotube thin film transistors by droplet electrophoresis - Lefebvre, J.; Ding, J. (Materials Today Communications, 2017)
Spontaneously charged aerosol droplets, each containing a few single-walled carbon nanotubes wrapped in conjugated polymers were precipitated on a target substrate using electrostatic forces. Nanotube networks were assembled on a variety of dielectric surfaces including polymers with low surface energy: Good transistor performance was achieved in all cases. Under proper regime of electrostatic and flow fields, patterns were produced in a maskless fashion and feature sizes below 150 μm were.

Radiation hardness of AlGaAs n-i-p solar cells with higher bandgap intrinsic region - Walker, A. W.; Heckelmann, S.; Tibbits, T.; Lackner, D.; Bett, A. W.; Dimroth, F. (Solar Energy Materials and Solar Cells, 2017)
The radiation hardness of AlGaAs single-junction solar cells is investigated for various n-i-p solar cell designs. The material composition in both the n-p regions is varied between 3.5% and 16% Al-content, whereas the intrinsic region has a higher Al-content between 3.5% and 23%. The beginning-of-life and end-of-life quantum efficiency and current – voltage characteristics are discussed to establish trends as a function of material bandgap. It is found that, increasing the Al-content of AlGaAs tends to increase the radiation hardness of the solar cells up to an efficiency remaining factor of 85%. This enhancement mostly originates from an improved open circuit voltage remaining factor that is caused by a deterioration of the beginning-of-life performance as the Al-content increases. However, a degradation in photocurrent is observed for increasing Al content in the intrinsic region, which is partially due to minority carrier potential barriers at the base/intrinsic heterointerface. In general, increasing the bandgap of the intrinsic region improves radiation hardness, but the formation of potential barriers for minority carriers must be avoided. The diffusion lengths and damage coefficients are also extracted by modeling the quantum efficiency.
Keywords: AlGaAs; n-i-p solar cell; radiation hardness; end-of-life; diffusion length; device modeling

Fe/N/S-composited hierarchically porous carbons with optimized surface functionality, composition and nanoarchitecture as electrocatalysts for oxygen reduction reaction - Wu, Mingjie; Tang, Qiaowei; Dong, Fang; Bai, Zhengyu; Zhang, Lei; Qiao, Jinli (Journal of Catalysis, 2017)
Non-precious Fe/N/S-composited hierarchically porous carbon materials (Fe(x)/N/S-PAD, PAD: poly(acrylamide-co-diallyldimethyl ammonium chlor), x: the weight ratio of FeSO4 7H2O/PAD) are synthesized using a facile silica colloid template approach with FeSO4 7H2O as Fe and S sources, and PAD as N source, respectively. A simultaneous creation of porous structures and surface functionalities (Fe, N and S) of such catalysts is realized just by simply tuning the weight ratio of FeSO4 7H2O and PAD in the synthetic precursors. As a result, a series of catalyst samples with high oxygen reduction reaction (ORR) activity/stability are obtained, demonstrating the promotion role of FeSO4/PAD ratio in synthesizing high-performing catalysts. Particularly, a catalyst (Fe(1.5)/N/S-PAD) with a trace Fe content down to 1.0 wt.% is tested to be superior to a commercial Pt/C catalyst in alkaline media and exhibits impressive ORR performance in acidic media. Combined with characterization results such as TEM, Raman spectra, BET and XPS analysis, it is found that the well-defined micro- and meso-porous structure play the key role in enhancing catalytic ORR performance rather than the final total N contents in the carbon. Regarding the stability of such a catalyst, test using cyclic voltammetry for 5000 cycles in O2-saturated solution shows a negligible degradation rate when compared with Pt/C one, suggesting that this catalyst could be used for catalyzing the high-performing cathode ORR in proton-exchange membrane fuel cells, alkaline fuel cells and metal–air batteries.
Keywords: Fe/N/S-composited hierarchically porous; carbon; surface functionalities; oxygen reduction reaction; active-site formation and nature; fuel cells; metal-air batteries

Angle-resolved RABBIT: theory and numerics - Hockett, Paul (Journal of Physics B: Atomic, Molecular and Optical Physics, 2017)
Angle-resolved (AR) RABBITT measurements offer a high information content measurement scheme, due to the presence of multiple, interfering, ionization channels combined with a phase-sensitive observable in the form of angle and time-resolved photoelectron interferograms. In order to explore the characteristics and potentials of AR-RABBITT, a perturbative 2-photon model is developed; based on this model, example AR-RABBITT results are computed for model and real systems, for a range of RABBITT schemes. These results indicate some of the phenomena to be expected in AR-RABBITT measurements, and suggest various applications of the technique in photoionization metrology.
Keywords: photoionization; angle-resolved; photoelectron spectroscopy; ultrafast; atto

Exemplar-centered supervised shallow parametric data embedding - Min, Martin Renqiang; Guo, Hongyu; Song, Dongjin (Proceedings of the Twenty-Sixth International Joint Conference on Artificial Intelligence, 2017)
Metric learning methods for dimensionality reduction in combination with k-Nearest Neighbors (kNN) have been extensively deployed in many classification, data embedding, and information retrieval applications. However, most of these approaches involve pairwise training data comparisons, and thus have quadratic computational complexity with respect to the size of training set, preventing them from scaling to fairly big datasets. Moreover, during testing, comparing test data against all the training data points is also expensive in terms of both computational cost and resources required. Furthermore, previous metrics are either too constrained or too expressive to be well learned. To effectively solve these issues, we present an exemplar-centered supervised shallow parametric data embedding model, using a Maximally Collapsing Metric Learning (MCML) objective. Our strategy learns a shallow high-order parametric embedding function and compares training/test data only with learned or precomputed exemplars, resulting in a cost function with linear computational complexity for both training and testing. We also empirically demonstrate, using several benchmark datasets, that for classification in two-dimensional embedding space, our approach not only gains speedup of kNN by hundreds of times, but also outperforms state-of-the-art supervised embedding approaches.
Keywords: machine learning; neural networks; data mining

Variation of practice and poor outcomes for extremely low gestation births: ordained before birth? - Janvier, Annie; Baardsnes, Jason; Hebert, Michael; Newell, Stephanie; Marlow, Neil (Archives of Disease in Childhood. Fetal and Neonatal Edition, 2017)
Editorial
Éditorial

Size based enrichment and sorting of Ov90 cancer cells and clusters with a new multistage filtration cartridge reveals distinct phenotypes - Meunier, Anne; Kheireddine, Sara; Hernández-Castro, Javier Alejandro; Veres, Teodor; Juncker, David (Proceedings of the American Association for Cancer Research Annual Meeting 2017; 2017 Apr 1-5; Washington, DC, 2017)
Background: Circulating tumor cells (CTCs) are released in blood from the primary tumor, but although very heterogeneous both in size and marker expression, are very rare and provide information not available from the primary tumor. The identification of CTC cells and clusters could advance our understanding of metastasis and help personalize therapy.1,2 Notably, CTC clusters were shown to have a higher metastatic potential than single cells³ but the process remains poorly understood. We present a multistage filtration system with pore sizes from 20 down to 8 μm for the size-selective enrichment of Ov90 ovarian cancer cells and clusters from blood. Each captured cell population was released, cultured and characterized independently. Methods: We developed a 3D printed multistage filtration cartridge and polymer filters with 20, 15, 12, 10 and 8 μm-diameter pores. Filters were stacked from 20 (top) to 8 μm (bottom) and used to enrich and sort Ov-90 cells spiked in 1:6 mL of blood:PBS. Captured cells were released by removing individual filters from the cartridge, reverse flowing OSE medium, and then cultured separately. Results: Ov-90 clusters were found mostly on the top filter (20 μm) and interestingly, few small clusters (3-4 cells) were found on the 8 and 10 μm filters, suggesting alignment of cluster cells as they pass through the pores.⁴ Cell and nucleus diameters were measured, and a general correlation was found between filter pore size and cell and nucleus size. Interestingly, nucleus size was found to be the single most significant parameter in determining passage of single cells and small clusters through pores. Following cell culture, two distinct phenotypes were observed: cell captured on small pore filters (8-12 μm) grew primarily in a monolayer. Cells captured on filters with larger pores (15-20 μm) first grew as monolayer, but rapidly formed cell aggregates that subsequently detached from the surface. Staining for E-Cadherin, a cell-cell adhesion protein, revealed a loss of expression of cells from filter with larger pores. Conclusion: We developed a new multistage filtration method and selectively enriched and sorted cells based primarily on their nucleus size. We identified two Ov-90 populations with different growth behaviors with low E-cadherin expression on the cells forming clusters, which is known to correlate with metastasis. The application of multistage filters may also reveal different CTC populations based on nucleus and cell size.

Screening platform for development of antibody-drug conjugates against novel targets at the National Research Council of Canada - Jaramillo, Maria Luz; Meury, Luc; Bouchard, Patrice; Matte, Allan; Marcil, Anne; Acchione, Mauro; Hill, Jennifer; Fauteux, Francois (Proceedings of the American Association for Cancer Research Annual Meeting 2017; 2017 Apr 1-5; Washington, DC, 2017)
One of the most promising of the next generation of biologic-based cancer therapeutics builds on the molecular targeting abilities of antibodies by combining them with drugs to generate highly specific antibody-drug conjugates (ADCs). However, the development of ADCs requires time-consuming selection of the antibody for every target and cancer type. High-throughput screening technologies based on the use of conjugated secondary antibodies provide a fast and efficient surrogate assay from which to identify which antibodies are best internalized and suitable for immunoconjugate development into ADCs. As part of its integrated antibody development initiative, NRC has isolated and characterized anti- mouse Fc and anti-human Fc monoclonal antibodies to serve as very selective detective reagents for various IgG isotypes. We have shown that these secondary antibodies are species specific, selective and of high affinity. When conjugated to pH sensitive fluorophores, we have used them to specifically identify internalizing antibodies against tumor targets, which were later validated as ADCs. Furthermore, these secondary conjugates exhibit high specific potency and low background toxicity once conjugated to linkered drugs. This approach allow us to optimize the selection of an antibody for a particular target, tumor type, linker and drug for ADC development. NRC will present results of a screen of 285 mouse antibodies against 20 different targets in 7 different cancer cell lines, using either MCC-DM1 or vc-MMAE-conjugated secondary antibodies. The NRC ADC discovery platform is combining this methodology with our proprietary mRNA and DNA expression database for the selection of appropriate ADC targets. NRC Biologics and Biomanufacturing program is in the process of screening thousands of NRC antibodies generated against a variety of cancer-associated cell surface targets to deliver a steady pipeline of ADCS as part of its drug discovery efforts. This functional screening platform further promotes the integration and advancement of NRC’s capabilities and strengths in the area of biologic-based therapeutics lead candidate selection, including quality attributes and characterization and biomanufacturing. The combined expertise in cell biology, high throughput screening, antibody generation and selection, bioinformatics and expression analysis forms the foundation by which NRC can establish strategic collaborations with other Canadian or international partners to develop antibodies into novel ADC biologics.

A novel computationally-designed TGF beta trap promoting anti-tumor T cell activity - O'Connor-McCourt, Maureen D.; Lenferink, Anne E.; Zwaagstra, John; Sulea, Traian; Collins, Catherine; Singh, Renu; Durocher, Yves; Cantin, Christiane; Koropatnick, James (Proceedings of the American Association for Cancer Research Annual Meeting 2017; 2017 Apr 1-5; Washington, DC, 2017)
AVID200 is a computationally-designed, avidity-enhanced, receptor ectodomain-based trap that binds and neutralizes TGF-beta 1 and 3 with low pM potency. Of the three TGF-beta isoforms, blockade of TGF-beta 2 has been shown to promote cancer metastasis. Therefore, AVID200 is designed to inhibit TGF-beta 1 and 3 only. TGF-beta is a strongly immunosuppressive molecule that, when expressed by cancers, mediates escape from immune surveillance. Increased TGF-beta ligand promotes cancer progression by suppressing anti-tumor immunity, predominantly by suppressing recruitment and activation of anti-tumor T cells. Consequently, TGF-beta is an important therapeutic target in cancer.AVID200 immunotherapy blocks the capacity of TGF-beta 1 and 3 ligands to interact with their receptors. That blockage induces T cell infiltration into tumors, thereby promoting a "T cell-inflamed" tumor state. Multiple trap formats with differing in vitro blocking potency, biophysical traits, and circulating half-lives in rodents have been designed, synthesized, and tested. On the basis of favorable characteristics, the AVID200 molecule was selected for in vivo assessment of efficacy in inhibiting growth of syngeneic 4T1 triple negative breast cancer (TNBC) homografts in immunocompetent host mice. In addition, CD4+ and CD8+ T cells isolated from draining lymph nodes of 4T1 tumor-bearing mice, treated and untreated with AVID200 and other candidate TGF-beta traps, were assessed for activities important in anti-tumor immune activity. We report that AVID200 immunotherapy decreased T-cell apoptosis, stimulated T-cell proliferation in response to tumor cell lysate-loaded dendritic cells, and enhanced the capacity of T-cells to specifically recognize and kill 4T1 tumor cells in ex vivo 2D cultures. The effect of combining AVID200 with immune checkpoint inhibitors in the treatment of syngeneic homografts in immune-competent mice is being assessed. AVID200 is a promising new immunotherapy to selectively inhibit the TGF-beta 1 and 3 isoforms, thereby enhancing desirable anti-tumor immunity while avoiding the tumor-promoting effects resulting from TGF-beta 2 neutralization.

TNF receptor 2 is essential for RIP1-dependent cell death in refractory leukemia - Aguadé-Gorgorio, Julia; McComb, Scott; Eckert, Cornelia; Dobay, Maria Pamela; Cario, Gunnar; Mezzatesta, Caterina; Von Stackelberg, Arend; Stanulla, Martin; Martin, Schrappe; Bourquin, Jean-Pierre; Bornhauser, Beat C. (Proceedings of the American Association for Cancer Research Annual Meeting 2017, 2017 Apr 1-5, Washington, DC, 2017)
The identification of molecular determinants that regulate sensitivity to specific agents is essential for the development of new therapeutic approaches in cancer. We have earlier shown that a subset of refractory acute lymphoblastic leukaemia (ALL) samples respond to SMAC-mimetic (SM) induced IAP depletion by concurrently inducing RIP1-dependent apoptosis and necroptosis. Comparative gene expression profiling indicated a correlation of sensitivity to SM with the expression of TNF receptor 2 (TNFR2) in primary ALL. Using an independent cohort of primary chemotherapy-resistant ALL samples, we found that presence of high TNFR2 expression identified by qPCR predicted ex vivo-sensitivity to SM. High TNFR2 levels also correlated with higher expression of TNFR1. Deletion of either TNFR1 or TNFR2 using CRISPR/Cas9 in primary ALL conferred resistance to treatment with SM, indicating that TNFR1 and 2 are both functionally required for cell death. Concomitant with an important role for TNFR2 in the response to SM, the overexpression of TNFR2 leads to increased sensitivity to TNF through increased activation of the TNFR1/RIP1 death axis. On the mechanistic level, SM induced recruitment of RIP1 to TNFR1, which was abolished in cells deficient for TNFR2. Taken together, our data reveal a novel function of TNFR2 in cell death signalling, as TNFR2 predicts sensitivity to SMAC mimetics and plays a key role in modulating a switch from RIP1-controlled cell survival to cell death.

Uncertainty of relative sensitivity factors in Glow Discharge Mass Spectrometry - Meija, Juris; Methven, Brad; Sturgeon, Ralph E. (Metrologia, 2017)
The concept of relative sensitivity factors required for the correction of the measured ion beam ratios in pin-cell Glow Discharge Mass Spectrometry (GD-MS) is examined in detail. We propose a data-driven model for predicting relative response factors which relies on nonlinear least squares adjustment and analyte/matrix interchangeability phenomena. The model provides a self-consistent set of response factors for any analyte/matrix combination of any element that appears as either analyte or matrix in at least one known response factor.
Keywords: glow discharge mass spectrometry; calibration model; analyte/matrix interchangeability; relatives sensitivity factors; least squares adjustment

Determination of the isotopic composition of iridium using Multicollector-ICPMS - Zhu, Zuhao; Meija, Juris; Zhang, Airong; Mester, Zoltán; Yang, Lu (Analytical Chemistry, 2017)
Like many other elements, iridium is lacking a calibrated, SI traceable isotope ratio measurement. In this study we have undertaken absolute isotope amount ratio measurements of iridium by MC-ICPMS using a state-of-the-art regression model to correct for the instrumental fractionation (mass bias) of isotope ratios using both NIST SRM 997 isotopic thallium and NIST SRM 989 isotopic rhenium as primary calibrators. The optimized regression mass bias correction model is based on incrementally increasing plasma power and short (10–30 min) measurement sessions. This experimental design allows fast implementation of the regression method which would normally require hours-long measurement sessions when executed under constant plasma power. Measurements of four commercial iridium materials provide a calibrated iridium isotope ratio R193/191 = 1.6866(6)k=1 which corresponds to isotopic abundance x191 = 0.372 21(8)k=1 and an atomic weight of Ar(Ir) = 192.217 63(17)k=1. In addition, we present data on a new Certified Reference Material from NRC Canada IRIS-1 which fulfills the requirements of a delta zero reference for iridium isotope ratio measurements.

The effect of zone level occupancy characteristics on adaptive controls - Gunay, Burak; O'Brien, William; Beausoleil-Morrison, Ian; Shen, Weiming; Newsham, Guy; Macdonald, Iain (Proceedings of the 15th IBPSA Conference, August 7-9, 2017, San Francisco, CA, USA, 2017)
The objective of this paper is to examine the energy and comfort impact of the HVAC equipment granularity in offices through building performance simulation. To this end, the occupancy data gathered from 37 private offices in Ottawa, Canada were analysed. For each occupant, four parameters that play an important role over the HVAC operation were extracted. These parameters are the earliest expected arrival time, the latest expected departure time, the latest expected arrival time, and the longest expected duration of intermediate vacancy. Through random sampling from the 37 occupants, hypothetical zones with varying numbers of occupants were created, and EnergyPlus simulations were conducted. Results indicate that the earliest expected arrival time in one-person zones is on average two hours later than it is in twelve-person zones. Similarly, the latest expected departure time in one-person zones is on average two hours earlier than it is in twelve-person zones. Heating and cooling energy use with adaptive occupancy-based temperature setback scheduling in one-person zones is estimated to be 20% less than it is in twelve-person zones.
Keywords: occupancy; HVAC; energy use; adaptive controls

Low-frequency structure-borne sound power measurements using heavyweight reception plates - Reinhold, Steffi; Hopkins, Carl; Zeitler, Berndt (Proceedings of the 24th International Congress on Sound and Vibration, 2017)
To quantify the structure-borne sound power injected by building machinery into heavyweight buildings the reception plate method according to EN 15657-1 can be used to provide input data for the prediction model described in EN 12354-5. This paper concerns the assessment of different sampling strategies for vibration measurements that are needed to determine the reception plate power. This is carried out using a validated finite element model for a heavyweight reception plate with viscoelastic material around its boundaries. The lowest differences between the direct injected power and reception plate power are obtained by using a regular grid of sampling positions over the whole reception plate. These investigations are based on harmonic force excitation of randomly distributed single-contact sources. A numerical approach to estimate the structural behaviour of harmonic point force excitations is compared with measurements on a laboratory heavyweight reception plate. Building machinery have usually more than one contact point to the structure, where they are connected. Therefore, multiple-contact sources such as white goods are also determined. The resulting effects of harmonic multiple-force excitations with different positions on the validated reception plate model are discussed.
Keywords: structure-borne sound power; reception plate; FEM

Radiation efficiency of metal stud plaster-board walls - Schneider, Martin; Zeitler, Berndt (Proceedings of the 24th International Congress on Sound and Vibration, 2017)
The radiation efficiency of different plasterboard walls was determined through measurements in the direct sound transmission facilities at the University of Applied Science in Stuttgart. The radiation efficiency was determined using airborne sound excitation in the source room. The velocity on the plasterboard on the receiving room side was measured using accelerometers and the radiated sound power was calculated from the sound pressure level in the diffuse receiving room. In this study it was identified that the radiation efficiency of identical boards depends strongly on the construction of the wall (shaft wall, single stud wall, double stud wall) and in the low frequency range also on the mass-spring-mass resonance frequency of the double walls. The typical shape of the radiation factor, going from high to low frequencies, shows a decrease below the critical frequency of the plasterboard (at approx. 3 kHz) down to approx.-15 dB in the frequency range from 1250 Hz to 250 Hz. Below 250 Hz the radiation factor increases again, almost up to 0 dB in the frequency region close to the resonance frequency of the mass-spring-mass resonance. Why there is this increase of the radiation efficiency at low frequencies is explained through calculations that are related to the stiffness of the complete construction.
Keywords: radiation efficiency; plasterboard wall

On the relevance of impact source impedance at low frequencies-part 2: floors with floating toppings - Zeitler, Berndt; Schneider, Martin; Sabourin, Ivan (Proceedings of the 24th International Congress on Sound and Vibration, 2017)
Low frequency noise generated from impact sources on floors is becoming more significant due to the trend of using lighter building components. The amount of sound power that gets injected into the floor depends on the impedance matching between the source (e.g. barefoot or shoe walkers) and the receiving surface (e.g. floors unless Spiderman is in the house). In a previous study, it was identified that the impedance of the impact sources at low frequencies has no influence on the power injected into wood or concrete floors without floating toppings. The reason is because the impedance of both the wood and concrete floor is much higher than the source impedance and only the force controls the amount of power injected into the floor. In this current study, calculation models are used to simulate the effect of a floating topping on the injected power by investigating the resulting impedance and impedance match between the floor with a floating topping and the two standardized ISO impact sources (heavy/soft ball and hard tapping machine). Finally, the relevance of impact source impedance at low frequencies will be presented for floors with floating toppings.
Keywords: building acoustics; impact sound; low frequencies; impedance match

Storage of polarization-entangled THz-bandwidth photons in a diamond quantum memory - Fisher, Kent A. G.; England, Duncan G.; MacLean, Jean-Philippe W.; Bustard, Philip J.; Heshami, Khabat; Resch, Kevin J.; Sussman, Benjamin J. (Physical Review A, 2017)
Bulk diamond phonons have been shown to be a versatile platform for the generation, storage, and manipulation of high-bandwidth quantum states of light. Here we demonstrate a diamond quantum memory that stores, and releases on demand, an arbitrarily polarized ∼250 fs duration photonic qubit. The single-mode nature of the memory is overcome by mapping the two degrees of polarization of the qubit, via Raman transitions, onto two spatially distinct optical phonon modes located in the same diamond crystal. The two modes are coherently recombined upon retrieval and quantum process tomography confirms that the memory faithfully reproduces the input state with average fidelity 0.784±0.004 with a total memory efficiency of (0.76±0.03)%. In an additional demonstration, one photon of a polarization-entangled pair is stored in the memory. We report that entanglement persists in the retrieved state for up to 1.3 ps of storage time. These results demonstrate that the diamond phonon platform can be used in concert with polarization qubits, a key requirement for polarization-encoded photonic processing.

Optomechanical design of TMT NFIRAOS subsystems at INO - Nash, Reston; Lardière, Olivier; Lamontagne, Frédéric; Desnoyers, Nichola; Grenier, Martin; Cottin, Pierre; Leclerc, Mélanie; Martin, Olivie; Buteau-Vaillancourt, Louis; Boucher, Marc-André; Andersen, David; Atwood, Jenny; et al. (Optomechanical Engineering 2017, 2017)
The adaptive optics system for the Thirty Meter Telescope (TMT) is the Narrow-Field InfraRed Adaptive Optics System (NFIRAOS). Recently, INO has been involved in the optomechanical design of several subsystems of NFIRAOS, including the instrument selection mirror (ISM), the beam splitter (NBS), and the source simulator system (NSS) comprising the focal plane mask (FPM), the laser guide star (LGS), and natural guide star (NGS) sources. This paper presents an overview of these subsystems and the optomechanical design approaches used to meet the optical performance requirements under environmental constraints.

Mechanism-based modeling for low cycle fatigue of cast austenitic steel - Wu, Xijia; Quan, Guangchun; Sloss, Clayton (Metallurgical and Materials Transactions A, 2017)
A mechanism-based approach—the integrated creep-fatigue theory (ICFT)—is used to model low cycle fatigue behavior of 1.4848 cast austenitic steel over the temperature range from room temperature (RT) to 1173 K (900 °C) and the strain rate range from of 2 × 10−4 to 2 × 10−2 s−1. The ICFT formulates the material’s constitutive equation based on the physical strain decomposition into mechanism strains, and the associated damage accumulation consisting of crack nucleation and propagation in coalescence with internally distributed damage. At room temperature, the material behavior is controlled by plasticity, resulting in a rate-independent and cyclically stable behavior. The material exhibits significant cyclic hardening at intermediate temperatures, 673 K to 873 K (400 °C to 600 °C), with negative strain rate sensitivity, due to dynamic strain aging. At high temperatures >1073 K (800 °C), time-dependent deformation is manifested with positive rate sensitivity as commonly seen in metallic materials at high temperature. The ICFT quantitatively delineates the contribution of each mechanism in damage accumulation, and predicts the fatigue life as a result of synergistic interaction of the above identified mechanisms. The model descriptions agree well with the experimental and fractographic observations.

Col-OSSOS: z band photometry reveals three distinct TNO surface types - Pike, Rosemary E.; Fraser, Wesley C.; Schwamb, Megan E.; Kavelaars, J. J.; Marsset, Michael; Bannister, Michele T.; Lehner, Matthew J.; Wang, Shiang-Yu; Lehner, Matthew J.; Wang, Shiang-Yu; Alexandersen, Mike; Chen, Ying-Tung; et al. (The Astronomical Journal, 2017)
Several different classes of trans-Neptunian objects (TNOs) have been identified based on their optical and near-infrared colors. As part of the Colours of the Outer Solar System Origins Survey (Col-OSSOS), we have obtained g-, r-, and z-band photometry of 26 TNOs using Subaru and Gemini Observatories. Previous color surveys have not utilized z-band reflectance, and the inclusion of this band reveals significant surface reflectance variations between sub-populations. The colors of TNOs in g − r and r − z show obvious structure, and appear consistent with the previously measured bi-modality in g − r. The distribution of colors of the two dynamically excited surface types can be modeled using the two-component mixing models from Fraser & Brown. With the combination of g − r and r − z, the dynamically excited classes can be separated cleanly into red and neutral surface classes. In g − r and r − z, the two dynamically excited surface groups are also clearly distinct from the cold classical TNO surfaces, which are red, with $g-r\gtrsim 0.85$ and r − z lesssim 0.6, while all dynamically excited objects with similar g − r colors exhibit redder r − z colors. The z-band photometry makes it possible for the first time to differentiate the red excited TNO surfaces from the red cold classical TNO surfaces. The discovery of different r − z colors for these cold classical TNOs makes it possible to search for cold classical surfaces in other regions of the Kuiper Belt and to completely separate cold classical TNOs from the dynamically excited population, which overlaps in orbital parameter space.
Keywords: Kuiper belt: general

Insights into organic-aerosol sources via a novel laser-desorption/ionization mass spectrometry technique applied to one year of PM10 samples from nine sites in central Europe - Daellenbach, K. R.; El-Haddad, I.; Karvonen, L.; Vlachou, A.; Corbin, J. C.; Slowik, J. G.; Heringa, M. F.; Bruns, E. A.; Luedin, S. M.; Jaffrezo, J.-L.; Szidat, S.; Piazzalunga, A.; et al. (Atmospheric Chemistry and Physics, 2017)
We assess the benefits of offline laser-desorption/ionization mass spectrometry (LDI-MS) in understanding ambient particulate matter (PM) sources. The technique was optimized for measuring PM collected on quartz-fiber filters using silver nitrate as an internal standard for m/z calibration. This is the first application of this technique to samples collected at nine sites in central Europe throughout the entire year 2013 (819 samples). Different PM sources were identified by positive matrix factorization (PMF) including also concomitant measurements (such as NOx, levoglucosan, and temperature). By comparison to reference mass spectral signatures from laboratory wood burning experiments as well as samples from a traffic tunnel, three biomass-burning factors and two traffic factors were identified. The wood-burning factors could be linked to the burning conditions; the factors related to inefficient burns had a larger impact on air quality in southern Alpine valleys than in northern Switzerland. The traffic factors were identified as primary tailpipe exhaust and most possibly aged/secondary traffic emissions, respectively. The latter attribution was supported by radiocarbon analyses of both the organic and elemental carbon. Besides these sources, also factors related to secondary organic aerosol were separated. The contribution of the wood burning emissions based on LDI-PMF correlates well with that based on AMS-PMF analyses, while the comparison between the two techniques for other components is more complex.

InAs single quantum dots in Wurtzite InP nanowires emitting at telecommunication wavelengths - Haffouz, S.; Dalacu, D.; Poole, P. J. (Photonics Conference (IPC), 2016 IEEE, 2017)
Quantum dots (QDs) embedded in semiconductors nanowires are of great interest for photonic quantum technologies. We have previously reported that QDs in nanowires could be an efficient source for single photons [1] and entangled photon pairs [2] that is required for applications in quantum computation, quantum cryptography and quantum optics. For these later applications, the source has to meet requirements such as high symmetry, high brightness, high extraction efficiency, high-fidelity entanglement and a precise position control at the nanoscale level. The selective area vapor-liquid-solid (VLS) growth process is a very suitable technique to synthesize nanowires with high yield and homogeneity [3]. Moreover, the optical and electronic properties of these QD based sources are controllable by manipulating the nanowire dimension, dot size, and composition. We have been so far very successful in producing high optical quality single InAsP quantum dots in InP nanowire that are emitting in the range of 890-970 nm. The emission wavelength is controlled by the arsenic percentage in the InAsP dot which is about 25%.

Chemical dispersants enhance the activity of oil- and gas condensate-degrading marine bacteria - Tremblay, Ji;ien; Yergeau, E.; Fortin, Nathalie; Cobanli, S.; Elias, Miria; King, Thomas L.; Lee, Kenneth; Greer, Charles W. (ISME Journal, 2017)
Application of chemical dispersants to oil spills in the marine environment is a common practice to disperse oil into the water column and stimulate oil biodegradation by increasing its bioavailability to indigenous bacteria capable of naturally metabolizing hydrocarbons. In the context of a spill event, the biodegradation of crude oil and gas condensate off eastern Canada is an essential component of a response strategy. In laboratory experiments, we simulated conditions similar to an oil spill with and without the addition of chemical dispersant under both winter and summer conditions and evaluated the natural attenuation potential for hydrocarbons in near-surface sea water from the vicinity of crude oil and natural gas production facilities off eastern Canada. Chemical analyses were performed to determine hydrocarbon degradation rates, and metagenome binning combined with metatranscriptomics was used to reconstruct abundant bacterial genomes and estimate their oil degradation gene abundance and activity. Our results show important and rapid structural shifts in microbial populations in all three different oil production sites examined following exposure to oil, oil with dispersant and dispersant alone. We found that the addition of dispersant to crude oil enhanced oil degradation rates and favored the abundance and expression of oil-degrading genes from a Thalassolituus sp. (that is, metagenome bin) that harbors multiple alkane hydroxylase (alkB) gene copies. We propose that this member of the Oceanospirillales group would be an important oil degrader when oil spills are treated with dispersant.

Mouse models of Acinetobacter baumannii infection - Harris, G.; KuoLee, R.; Xu, H. H.; Chen, W. (Current Protocols in Microbiology, 2017)
This unit describes basic protocols for infecting mice through intranasal and intraperitoneal routes with Acinetobacter baumannii to induce associated pneumonia and sepsis, the two most common manifestations of clinical infections with this pathogen. By selecting the appropriate protocols and bacterial strains of different virulence, these mouse models provide an opportunity to study the infection pathogenesis and host-immune responses, and to evaluate the efficacies of prophylactic and therapeutic anti-A. baumannii candidates.
Keywords: acinetobacter; animal models; mouse; pneumonia; sepsis

A disulfide-stabilized human VL single-domain antibody library is a source of soluble and highly thermostable binders - Henry, Kevin A.; Kandalaft, Hiba; Lowden, Michael J.; Rossotti, Martin A.; van Faassen, Henk; Hussack, Greg; Durocher, Yves; Kim, Dae Young; Tanha, Jamshid (Molecular Immunology, 2017)
We have previously shown that incorporation of a second intradomain disulfide linkage into camelid VHH and human VH/VL single-domain antibodies confers increased thermostability. Here, we explored the effects of introducing an additional disulfide linkage, formed between Cys48 and Cys64 (Kabat numbering), into a phage-displayed synthetic human VL library. In comparison to an identical library bearing only the highly conserved Cys23-Cys88 disulfide linkage, the disulfide-stabilized VL library tolerated a similar degree of randomization but retained a higher level of functional diversity after selection with protein L. Both libraries yielded soluble, antigen-specific VLs that recognized a model antigen (maltose-binding protein) with similar affinities, in the micromolar range; however, the disulfide-stabilized antigen-specific VLs were much more thermostable (average ΔTm ∼10 °C) than non-disulfide-stabilized VLs. This work provides proof-of-concept for building synthetic antibody libraries using disulfide-constrained immunoglobulin domains, thus avoiding pitfalls of post-hoc disulfide linkage engineering such as impaired antigen binding and reduced expression yield.
Keywords: single-domain antibody; protein engineering; human VL; phage display; disulfide bond; thermostability

Characterizing the impact of optically induced blurring of a high-resolution phase-shift 3D scanner - Drouin, Marc-Antoine; Blais, François; Picard, Michel; Boisvert, Jonathan; Beraldin, Jean-Angelo (Machine Vision and Applications, 2017)
A model to predict and characterize the impact of out-of-focus blurring on the range uncertainty associated with the measurement by a phase-shift 3D scanner is presented. First, the reduction of the sine wave magnitude introduced by the projector lenses and the camera lenses is considered. Then, the noise reduction effects related to the camera image blurring introduced by the camera lenses are also included in the model. The main results of this study indicate that the uncertainty for a high-resolution system varies and exhibits a slanted “W” shape, which significantly differs from the inverse square of the range expected from the triangulation equation or the slanted “U” shape, which may be intuitively expected when combining blurring caused by a limited depth of field and the triangulation equation. We provide a comprehensive experimental characterization of a purposely constructed 3D scanner designed to isolate the performance degradation caused by out-of-focus projection and acquisition lenses. This scanner is designed to mimic the characteristics of a high-resolution scanner that can be employed for demanding quality control applications. In the tested configurations, the predicted depth-of-fields were within 16.3% of the corresponding measured values. This concordance between the theoretical results and experimental results suggests that the proposed model can be used to assist the design of phase-shift scanners.
Keywords: active 3D imaging; structured light; fringe projection; measurement uncertainty; modeling Geometric optics

Expression profiling of development related genes in rice plants ectopically expressing AtTOR - Bakshi, Achala; Moin, Mazahar; Datla, Raju; Kirti, P. B. (Plant Signaling and Behavior, 2017)
Expression analysis of genes associated with development at different growth stages such as shoot apical meristem (SAM), root apical meristem (RAM), shoot and root tissues 10 DAG, flowers and grains of two high expression transgenic lines of rice ectopically expressing AtTOR revealed the involvement of AtTOR in transcriptional regulation of these genes. We have observed that in the SAM of these two selected lines, TR-2.24 and TR-15.1, OsFON1 and OsFON4 (orthologs of AtCLV1 and AtCLV3, respectively), OsKNOX2, OsKNOX3 and OsWOX3 became up-regulated. The up-regulation of OsFON1 and OsFON4 is likely to be involved in the maintenance of effective meristem size of the inflorescence and phyllotaxis. The grains and spikes of transgenic plants exhibited enhanced transcript levels of OsMADS1, OsMADS6, and OsMADS29 further implicating the role of TOR in modulating the expression of the genes in rice grain formation and development. Moreover, the up-regulation of auxin transporter, PIN1c in RAM and roots derived from seedlings 10 DAG showed the involvement of TOR in root development. The seeds of two high expression lines also showed increased expression of OSE2 and GAMYB transcription factors involved in seed development. In summary, the present study, by heterologous expression of AtTOR in rice, demonstrated the involvement of TOR in regulating genes involved in various growth and developmental stages of rice plant and also in photosynthesis, productivity related functions and water-use efficiency.
Keywords: TOP; transcription factor; cell proliferation; shoots apical meristem

Scalable lentiviral vector production using stable HEK293SF producer cell lines - Manceur, Aziza P.; Kim, Howard; Misic, Vanja; Andreev, Nadejda; Dorion-Thibaudeau, July; Lanthier, Stéphan; Bernier, Alice; Tremblay, Sonia; Gélinas, Anne-Marie; Broussau, Sophie; Gilbert, Rénald; Ansorge, Sven (Human Gene Therapy Methods, 2017)
Lentiviral vectors (LV) represent a key tool for gene and cell therapy applications. The production of these vectors in sufficient quantities for clinical applications remains a hurdle, prompting the field towards developing suspension processes that are conducive to large scale production. We describe here a LV production strategy using a stable inducible producer cell line. The HEK293 cell line employed grows in suspension, thus offering direct scalability, and produces a Green Fluorescent Protein (GFP)-expressing lentiviral vector in the 106 Transduction Units (TU)/ml range without optimization. The stable producer cell line, called clone 92, was derived by stable transfection from a packaging cell line with a plasmid encoding the transgene GFP. The packaging cell line expresses all the other necessary components to produce LV upon induction with cumate and doxycycline. First, we demonstrate that LV production using clone 92 is scalable from 20mL shake flasks to 3L bioreactors. Next, we developed two strategies for high yield LV production in perfusion mode using acoustic cell filter technology in 1 to 3L bioreactors. The first approach uses a basal commercial medium and perfusion mode both pre- and post-induction for increasing cell density and LV recovery. The second approach makes use of a fortified medium formulation to achieve target cell density for induction in batch mode, followed by perfusion mode after induction. Using these perfusion-based strategies, the titer was improved to 3.2 x 107 TU/ml. As a result, cumulative functional LV titers were increased by up to 15-fold compared to batch mode, reaching a cumulative total yield of 8 x 1010 TU/L of bioreactor culture. This approach is easily amenable to large-scale production and commercial manufacturing.
Keywords: lentiviral vector; stable producer; HEK293SF; perfusion; bioprocessing

Single-domain antibodies as versatile affinity reagents for analytical and diagnostic applications - Gonzalez-Sapienza, Gualberto; Rossotti, Martin A.; Tabares-DaRosa, Sofia (Frontiers in Immunology, 2017)
With just three CDRs in their variable domains, the antigen-binding site of camelid heavy-chain-only antibodies (HcAbs) has a more limited structural diversity than that of conventional antibodies. Even so, this does not seem to limit their specificity and high affinity as HcAbs against a broad range of structurally diverse antigens have been reported. The recombinant form of their variable domain [nanobody (Nb)] has outstanding properties that make Nbs, not just an alternative option to conventional antibodies, but in many cases, these properties allow them to reach analytical or diagnostic performances that cannot be accomplished with conventional antibodies. These attributes include comprehensive representation of the immune specificity in display libraries, easy adaptation to high-throughput screening, exceptional stability, minimal size, and versatility as affinity building block. Here, we critically reviewed each of these properties and highlight their relevance with regard to recent developments in different fields of immunosensing applications.
Keywords: nanobodies; VHH; immunodetection; phage display; imaging; haptens

Integrating solids and gases for attosecond pulse generation - Hammond, T. J.; Monchocé, Sylvain; Zhang, Chunmei; Vampa, Giulio; Klug, Dennis; Villeneuve, D. M.; Corkum, P. B. (Nature Photonics, 2017)
Control of the field of few-cycle optical pulses has had an enormous impact on attosecond science. Subcycle pulses open the potential for non-adiabatic phase matching while concentrating the electric field so it can be used most efficiently. However, subcycle field transients have been difficult to generate. We exploit the perturbative response of a sub-100 µm thick monocrystalline quartz plate irradiated by an intense few-cycle 1.8 µm pulse, which creates a phase-controlled supercontinuum spectrum. Within the quartz, the pulse becomes space–time coupled as it generates a parallel second harmonic. Vacuum propagation naturally leads to a subcycle electric-field transient whose envelope is sculpted by the carrier envelope phase of the incident radiation. We show that a second medium (either gas or solid) can generate isolated attosecond pulses in the extreme ultraviolet region. With no optical elements between the components, the process is scalable to very high energy pulses and allows the use of diverse media.
Keywords: high-harmonic generation; nonlinear optics; supercontinuum generation

Molecular frame reconstruction using time-domain photoionization interferometry - Marceau, Claude; Makhija, Varun; Platzer, Dominique; Naumov, A. Yu.; Corkum, P. B.; Stolow, Albert; Villeneuve, D. M.; Hockett, Paul (Physical Review Letters, 2017)
Photoionization of molecular species is, essentially, a multipath interferometer with both experimentally controllable and intrinsic molecular characteristics. In this work, XUV photoionization of impulsively aligned molecular targets (N2) is used to provide a time-domain route to “complete” photoionization experiments, in which the rotational wave packet controls the geometric part of the photoionization interferometer. The data obtained is sufficient to determine the magnitudes and phases of the ionization matrix elements for all observed channels, and to reconstruct molecular frame interferograms from lab frame measurements. In principle, this methodology provides a time-domain route to complete photoionization experiments and the molecular frame, which is generally applicable to any molecule (no prerequisites), for all energies and ionization channels.

Fabrication of high content carbon nanotube-polyurethane sheets with tailorable properties - Rubi, Yadienka Martinez; Ashrafi, Behnam; Jakubinek, Michael B.; Zou, Shan; Laqua, Kurtis; Barnes, Michael; Simard, Benoit (ACS Applied Materials and Interfaces, 2017)
We have fabricated carbon nanotube (CNT)-polyurethane (TPU) sheets via a one-step filtration method that uses a TPU solvent/non-solvent combination. This solution method allows for control of the composition and processing conditions, significantly reducing both the filtration time and the need for large volumes of solvent to debundle the CNTs. Through an appropriate selection of the solvents and tuning the solvent/non-solvent ratio, it is possible to enhance the interaction between the CNTs and the polymer chains in solution and improve the CNT exfoliation in the nanocomposites. The composition of the nanocomposites, which defines the characteristics of the material and its mechanical properties, can be precisely controlled. The highest improvements in tensile properties were achieved at a CNT:TPU weight ratio around 35:65 with a Young’s modulus of 1270 MPa, stress at 50 % strain of 35 MPa, and strength of 41 MPa, corresponding to ~10 fold improvement in modulus and ~7 fold improvement in stress at 50 % strain, while maintaining a high failure strain. At the same composition, CNTs with higher aspect ratio produce nanocomposites with greater improvements (e.g. strength of 99 MPa). Electrical conductivity also shows a maximum near the same composition, where it can exceed the values achieved for the pristine nanotube buckypaper. The trend in mechanical and electrical properties was understood in terms of the CNT-TPU interfacial interactions and morphological changes occurring in the nanocomposite sheets as a function of increasing the TPU content. The availability of such a simple method and the understanding of the structure-properties relationship are expected to be broadly applicable in the nanocomposites field.
Keywords: carbon nanotubes; polymer composites; morphology; mechanical properties; conductivity; AFM

Structural dynamics of a dowelled-joist timber floor in the low-frequency range modelled using finite element simulation - Filippoupolitis, M.; Hopkins, C.; Völtl, R.; Schanda, U.; Mahn, J.; Krajči, L. (Engineering Structures, 2017)
This paper concerns the development and validation of Finite Element Methods (FEM) to simulate the dynamic response of a dowelled-joist timber floor. This is a solid floor comprised of timber joists connected using timber dowels with individual assemblies connected using inclined metal screws. The focus is on the structural dynamics in the low-frequency range up to 200 Hz which is the relevant range for impact sound insulation and vibration serviceability. Dowel connections between the joists that formed each assembly were modelled using either rigid or spring connectors in the FEM models. The validation against experimental modal analysis showed that both approaches were valid in terms of the eigenfrequencies, Modal Assurance Criterion (MAC) and the spatial-average velocity with point excitation. Whilst the FEM model with spring connectors had a higher number of correlated modes in the MAC analysis, this required removal of many spurious modes before predicting the response. The validated models were used to demonstrate the potential in predicting assessment parameters for vibration serviceability that are contained in EN 1995-1-1 (Eurocode 5). This predictive approach to the evaluation of vibration serviceability has the advantage in that it can be used for non-standard timber floors with non-standard boundary conditions or floor plans.
Keywords: timber floor; dowel connections; vibration; modal analysis; vibration serviceability; Eurocode 5

An approach to detect branches and seedpods based on 3D image in low-cost plant phenotyping platform - Cao, Thang; Panjvani, Karim; Dinh, Anh; Wahid, Khan; Bhowmik, Pankaj (2017 IEEE 30th Canadian Conference on Electrical and Computer Engineering (CCECE), 2017)
To meet the high demand for supporting and accelerating progress in breeding of novel traits, plant scientists and breeders have to make more efforts to deal with the need to accurately measure a large number of plants and their characteristics. A variety of imaging methodologies is being deployed to acquire data for quantitative studies of complex traits. When applied to a large number of plants, however, a complete 3D model is very time-consuming for high-throughput phenotyping with an enormous amount of data. In some contexts, complete rebuild of entire plants may not be necessary. With the aim of producing a smaller amount of data per plant, low-cost depth imaging systems can be useful. We propose the use of such a low-cost depth camera, called Time-of-Flight (ToF), to have videos and pictures of the plant in 3D. An application has been developed to display 3D model of a plant and estimate certain characteristics. Counting the number of branches and seedpods of the canola plant have been implemented. Estimating the biomass and crop yield will be deployed in the near future.
Keywords: 3D plant phenotyping; image processing; time-of-flight camera; counting branches and seedpods

Detection of potato diseases using image segmentation and multiclass support vector machine - Islam, Monzurul; Dinh, Anh; Wahid, Khan; Bhowmik, Pankaj (2017 IEEE 30th Canadian Conference on Electrical and Computer Engineering (CCECE), 2017)
Modern phenotyping and plant disease detection provide promising step towards food security and sustainable agriculture. In particular, imaging and computer vision based phenotyping offers the ability to study quantitative plant physiology. On the contrary, manual interpretation requires tremendous amount of work, expertise in plant diseases, and also requires excessive processing time. In this work, we present an approach that integrates image processing and machine learning to allow diagnosing diseases from leaf images. This automated method classifies diseases (or absence thereof) on potato plants from a publicly available plant image database called `Plant Village'. Our segmentation approach and utilization of support vector machine demonstrate disease classification over 300 images with an accuracy of 95%. Thus, the proposed approach presents a path toward automated plant diseases diagnosis on a massive scale.
Keywords: SVM; disease detection; plant Phenotyping

Regression based algorithms for predicting age of an Arabidopsis plant - Panjvani, Karim; Dinh, Anh; Wahid, Khan; Bhowmik, Pankaj (2017 IEEE 30th Canadian Conference on Electrical and Computer Engineering (CCECE), 2017)
This paper presents the analysis of various regression based machine learning algorithms for image-based plant phenotyping application and proposes a technique for plant phenotyping. Capability to predict age/development stage of a plant is one of the important factors for plant phenotyping and for analysis of in-situ crops. With the developed technique, these algorithms can predict age of an Arabidopsis plant based on the given images and mutant types. Publicly available dataset containing 165 images at different development stages and with various mutant types was used for this experiment. Results show that with this technique and different regression algorithms, it can achieve 92% prediction accuracy. Comparatively, linear regression algorithms show greater prediction accuracy than nonlinear algorithms. This method of age prediction can help plant scientists and breeders for better analysis of crops.
Keywords: age prediction; plant phenotyping; machine learning; pattern recognition in plant imaging

Structural characterization of wall and lipidated polysaccharides from Clostridium perfringens ATCC 13124 - Vinogradov, E.; Aubry, A.; Logan, S. M. (Carbohydrate Research, 2017)
Cell surface polysaccharides produced by C. perfringens ATCC 13124 were analyzed using NMR, chemical and immunological methods. Two distinct polymers were identified. The more abundant PS1 had a structure based on a polymer of β-mannosamine with a number of modifications, including varying levels of substitution at O-6 with PEtN, N-acetylation, and different linkages between monosaccharides. The shortest variant of PS1 represented a lipoteichoic acid. It contained only 1-4-linkages between ManNAc residues, minor branching α-Ribf, and glucosyl-glycerol at the reducing end, which was acylated with linear saturated fatty acids C16, C18, and C20 (dominant). Other non-lipidated variants of PS1 contained less PEtN, no α-Ribf, up to 50% 1-3-linkages, and up to 25% ManN with the free amino group. The minor polysaccharide PS2 had a linear regular structure with a -4-α-Rha-3-β-Gal-4-β-GalNAc3PCho- repeating unit, where PCho indicates phosphocholine.
Keywords: clostridium perfringens; NMR spectroscopy; polysaccharide; structure

Leveraging existing occupancy-related data for optimal control of commercial office buildings: a review - Shen, Weiming; Newsham, Guy; Gunay, Burak (Advanced Engineering Informatics, 2017)
A primary strategy for the energy-efficient operation of commercial office buildings is to deliver building services, including lighting, heating, ventilating, and air conditioning (HVAC), only when and where they are needed, in the amount that they are needed. Since such building services are usually delivered to provide occupants with satisfactory indoor conditions, it is important to accurately determine the occupancy of building spaces in real time as an input to optimal control. This paper first discusses the concepts of building occupancy resolution and accuracy and briefly reviews conventional (explicit) occupancy detection approaches. The focus of this paper is to review and classify emerging, potentially low-cost approaches to leveraging existing data streams that may be related to occupancy, usually referred to as implicit/ambient/soft sensing approaches. Based on a review and a comparison of related projects/systems (in terms of occupancy sensing type, resolution, accuracy, ground truth data collection method, demonstration scale, data fusion and control strategies) the paper presents the state-of-the-art of leveraging existing occupancy-related data for optimal control of commercial office buildings. It also briefly discusses technology trends, challenges, and future research directions.
Keywords: occupancy detection; data fusion; commercial office buildings; energy conservation; HVAC control; lighting control

Towards product customization and personalization in IoT-enabled cloud manufacturing - Yang, Chen; Lan, Shulin; Shen, Weiming; Huang, George Q.; Wang, Xianbin; Lin, Tingyu (Cluster Computing, 2017)
Customized/personalized products are gaining more shares in today’s product market. Such products need collective efforts from consumers, manufacturers and third parties. This requirement has not been well addressed due to both market and technology factors. On the other hand, the Internet of Things (IoT) provides real-time sensing/actuating ability and fast transmission capability of data/information, so that remote operation of manufacturing activities and efficient collaboration among stakeholders are greatly facilitated. This provides great opportunities to address the requirement mentioned above. Thus we propose a full-connection model of product design and manufacturing in the IoT-enabled cloud manufacturing environment. The proposed model uses social networks to connect multiple parties and facilitate open innovations, and use IoT to glue physical space to cyber space and cloud manufacturing to provide various elastic services, so that the on-demand workspace, interaction, information sharing or collective problem solving are enabled. We also propose a supporting infrastructure for this model using the latest information and communication technologies. Finally, we present a case study of an RFID enabled production system for customized and personalized product with the ability to enable a new paradigm of “dynamic processes and close collaborations among different roles” and ensure robust production.
Keywords: cloud manufacturing; internet of things; concurrent engineering; social network; big data; radio frequency identification (RFID)

Inverse blackbox modeling of the heating and cooling load in office buildings - Gunay, Burak; Shen, Weiming; Newsham, Guy (Energy and Buildings, 2017)
This paper presents a systematic method to select an inverse blackbox model that can characterize the building-level heating and cooling load patterns parsimoniously. To this end, hourly heating, cooling, and electrical load data were gathered from five office buildings. In addition, concurrent weather data for temperature, solar irradiance, wind speed, and humidity were collected. Using the recent history of weather and electrical load data from the past three hours, 18 different forms of model at varying number of inputs and parameters were formulated for each of the five buildings. After assessing the models’ performance through a cross-validation and a residual analysis, one of the models was selected. The selected model was the one with a one-layer artificial neural network, six inputs, and a one-hour input history. Then, through illustrative examples, different use-cases in which inverse blackbox models can support the operational decision making process are discussed.
Keywords: blackbox modeling; inverse modeling; heating and cooling loads in buildings

Characterization of a building's operation using automation data: a review and case study - Gunay, Burak; Shen, Weiming; Yang, Chunsheng (Building and Environment, 2017)
This paper presents a critical review of the automated on-going commissioning (AOGC) methods for air-handling units (AHU) and variable air volume terminal (VAV) units in commercial buildings. The common faults studied in the literature were identified. The diagnostic approaches taken and the characteristics of the fault-symptom datasets utilized were categorized. It was found that the diagnostics methods were vastly fragmented, and most of them employed pure-statistical approaches. Only a few studies attempted to assimilate the automation data within the underlying physical processes. In addition, a large fraction of the reviewed literature has been devoted to physical faults in AHUs. Only a few studies were conducted to diagnose faults-related with controls programming and faults at the zone level. Upon the literature survey findings, an inverse greybox modelling-based AOGC approach was put forward. Its strengths and weaknesses were demonstrated through a case study conducted using the archived building automation system (BAS) data of an office building in Ottawa, Canada. The results of this case study indicate that inverse greybox modelling-based AOGC is a promising method to diagnose both physical and controls programming related faults at AHUs and VAVs.
Keywords: automated on-going commissioning; fault detection and diagnostics; inverse modelling; greybox modelling; commercial buildings

Relative Molar Response of lipophilic marine algal toxins in liquid chromatography electrospray ionization mass spectrometry - Zendong, Z.; Sibat, M.; Herrenknecht, C.; Hess, P.; McCarron, P. (Rapid Communications in Mass Spectrometry, 2017)
RATIONALE: Accurate quantitative analysis of lipophilic toxins by liquid chromatography-mass spectrometry (LC-MS) requires calibration solution reference materials (RMs) for individual toxin analogs. Untargeted analysis is aimed at identifying a vast number of compounds and thus validation of fully quantitative untargeted methods is not feasible. However, a semi-quantitative approach allowing for profiling is still required and will be strengthened by knowledge of the relative molar response (RMR) of analogs in liquid chromatography-mass spectrometry (LC-MS) with electrospray ionization (ESI). METHODS: RMR factors were evaluated for toxins from the okadaic acid (OA/DTXs), yessotoxin (YTX), pectenotoxin (PTX), azaspiracid (AZA) and cyclic imine (CI) toxin groups, in both solvent standards and environmental sample extracts. Since compound ionization and fragmentation influences the MS response of toxins, RMRs were assessed under different chromatographic conditions (gradient, isocratic) and MS acquisition modes (SIM, SRM, All-ion, target MS/MS) on low and high resolution mass spectrometers. RESULTS: In general, RMRs were not significantly impacted by chromatographic conditions (isocratic vs gradient), with the exception of DTX1. MS acquisition modes had a more significant impact, with PnTX-G and SPX differing notably. For a given toxin group, response factors were generally in the range of 0.5 to 2. The cyclic imines were an exception. CONCLUSIONS: Differences in RMRs between toxins of a same chemical base structure were not significant enough to indicate major issues for non-targeted semi-quantitative analysis, where there is limited or no availability of standards for many compounds, and where high degrees of accuracy are not required. Differences in RMRs should be considered when developing methods that use a standard of a single analogue to quantitate other toxins from the same group.

Valorization of triticale straw biomass as reinforcement in proficient polypropylene biocomposites - Mihai, Mihael; Ton-That, Minh-Tan (Waste and Biomass Valorization, 2017)
This paper presents the relationship between processing, formulation and properties of polypropylene (PP)/triticale straw biocomposites. The effects of triticale content, the presence of maleic anhydride grafted polypropylene (PP-g-MA) as coupling agent and of calcium oxide (CaO) as reactive additive on biocomposite properties are discussed. Biocomposites were prepared by twin-screw extrusion process and injection molding. The compounded biocomposites were characterized in terms of morphology, rheology, thermal and mechanical properties, recycling behavior and fire resistance. The morphological observation shows that a good dispersion of triticale straw in PP can be achieved during the compounding step for all the formulations. Biocomposite viscosity and mechanical properties were increased when triticale straw content increased up to 40 vol%. Mechanical properties were further improved in the presence of PP-g-MA and CaO. The reactive additive, CaO, provides superior strength, modulus as well as fire resistance, and upgrades the triticale straw classification from regular filler to reinforcement category. All biocomposites formulated exhibit a good recycling ability. The results demonstrate that triticale straw acts as a good reinforcement and has a great potential in thermoplastic composites field if the processing technique and formulation are appropriate.
Keywords: triticale; polypropylene; biocomposites; properties; processing

Two-step nucleation of CdS magic-size nanocluster MSC–311 - Zhu, Tingting; Zhang, Baowei; Zhang, Jing; Lu, Jiao; Fan, Hongsong; Rowell, Nelson; Ripmeester, John A.; Han, Shou; Yu, Kui (Chemistry of Materials, 2017)
Nucleation has been generally acknowledged as a rapid but uncontrollable process that is difficult to decouple from the subsequent growth phase. Here, we report our finding that nucleation of semiconductor magic-size clusters (MSCs) can be well-regulated, without a subsequent evolution in size. Colloidal semiconductor CdS MSCs were synthesized by a two-step approach intentionally designed, without the simultaneous formation of nanocrystals of other sizes. The nuclei MSCs exhibit a sharp optical absorption peaking at 311 nm and are thus denoted by MSC–311. We prepared the immediate precursor for MSC–311 denoted by IP311 which is liquid-like, through a reaction which was normally performed to grow CdS conventional quantum dots (QDs), but at a different temperature (180 °C) prior to the nucleation and growth of CdS QDs. We demonstrate that the nucleation of MSC–311 from IP311 followed first order kinetics remarkably well, and the presence of a small amount of methanol accelerated this process effectively. Moreover, the liquid-like prenucleation cluster IP311 and the nuclei MSC–311 have similar masses. Accordingly, we propose that the intramolecular reorganization of IP311 results in the nuclei MSC–311, the formation of which features a two-step nucleation pathway. The present study introduces methodology via absorption spectroscopy to monitor the nucleation kinetics of semiconductor MSCs from their immediate precursors. The repeatable, predictable, and controllable nucleation process investigated here brings a deeper insight into nucleation of other semiconductor nanocrystals and contributes to the foundation for the future development of advanced theoretical models for crystal nucleation.

Laser consolidation: a novel additive manufacturing process for making net-shape functional metallic components for various applications - Xue, Lijue (2017)
Laser consolidation (LC) is a novel additive manufacturing process being developed by the National Research Council Canada (NRC) at its London facility. LC offers unique capabilities in the production of net-shape functional metallic parts requiring no further post-processing. NRC's LC technology has achieved dimensional accuracy of up to +/-0.05 mm with a surface finish up to 1 µm Ra (depending on the materials used in the manufacturing process). The LC process differs from other additive manufacturing technologies by its high precision deposition system that can build functional parts or build features using various alloys and high performance materials on top of an existing part. In this presentation, laser consolidation of various high performance materials (such as Ni-alloys, Co-alloys, Ti-alloys and Al-alloys) will be discussed in respect to their unique microstructure and mechanical properties (including fatigue/fracture properties). The examples will be given on building complex functional components and repairing parts otherwise unrepairable for aerospace, defense and other applications.
Keywords: lasers; shapes; additive manufacturing

Long noncoding miRNA gene represses wheat β-diketone waxes - Huang, D.; Feurtado, J. A.; Smith, M. A.; Flatman, L. K.; Koh, C.; Cutler, A. J. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The cuticle of terrestrial plants functions as a protective barrier against many biotic and abiotic stresses. In wheat and other Triticeae, β-diketone waxes are major components of the epicuticular layer leading to the bluish-white glaucous trait in reproductive-age plants. Glaucousness in durum wheat is controlled by a metabolic gene cluster at the WAX1 (W1) locus and a dominant suppressor INHIBITOR of WAX1 (Iw1) on chromosome 2B. The wheat D subgenome from progenitor Aegilops tauschii contains W2 and Iw2 paralogs on chromosome 2D. Here we identify the Iw1 gene from durum wheat and demonstrate the unique regulatory mechanism by which Iw1 acts to suppress a carboxylesterase-like protein gene, W1-COE, within the W1 multigene locus. Iw1 is a long noncoding RNA (lncRNA) containing an inverted repeat (IR) with >80% identity to W1-COE The Iw1 transcript forms a miRNA precursor-like long hairpin producing a 21-nt predominant miRNA, miRW1, and smaller numbers of related sRNAs associated with the nonglaucous phenotype. When Iw1 was introduced into glaucous bread wheat, miRW1 accumulated, W1-COE and its paralog W2-COE were down-regulated, and the phenotype was nonglaucous and β-diketone-depleted. The IR region of Iw1 has >94% identity to an IR region on chromosome 2 in Ae. tauschii that also produces miRW1 and lies within the marker-based location of Iw2 We propose the Iw loci arose from an inverted duplication of W1-COE and/or W2-COE in ancestral wheat to form evolutionarily young miRNA genes that act to repress the glaucous trait.
Keywords: WAX1; glaucous; inhibitor of wax; long noncoding RNA; small RNA

Molecular cloning of an ester-forming triterpenoid: UDP-glucose 28-O-glucosyltransferase involved in saponin biosynthesis from the medicinal plant Centella asiatica - De Costa, Fernanda; Barber, Carla J. S.; Kim, Yeon-bok; Reed, Darwin W.; Zhang, Haixia; Fett-Neto, Arthur G.; Covello, Patrick S. (Plant Science, 2017)
Triterpene saponins include bioactive compounds with structures consisting of triterpene aglycones (sapogenins) and one or more sugar moieties linked through acetal or ester glycosidic linkages at one or more sites. Centella asiatica (L.) Urban is a medicinal plant that contains bioactive ursane-type saponins, such as madecassoside and asiaticoside. In this work, glucosylation of triterpenoids in C. asiatica was investigated starting with plant extracts. An enzyme capable of glucosylating asiatic and madecassic acids was partially purified. Proteomics methods and cDNA sequence data were employed as tools to obtain a full-length cDNA clone encoding a glucosyltransferase. The recombinant gene product, UGT73AD1, was functionally expressed in Escherichia coli and purified by immobilized metal-affinity chromatography. Purified recombinant UGT73AD1 was found to have a narrow specificity, glucosylating asiatic and madecassic acids at the C28 carboxyl. mRNA accumulated in all tissues tested (leaves, stems, roots and flowers), with highest expression in leaves. Thus, UGT73AD1 was identified as a triterpenoid carboxylic acid: UDP-glucose 28-O-glucosyltransferase that appears to be involved in saponin biosynthesis in C. asiatica.
Keywords: centella asiatica; apiaceae; saponin biosynthesis; glucosyltransferase; UGT73AD1

Rapid amyloid fibril formation by a winter flounder antifreeze protein requires specific interaction with ice - Dubé, André; Leggiadro, Cindy; Ewart, Kathryn Vanya (FEBS Letters, 2017)
A typically α-helical antifreeze protein (wflAFP-6) from winter flounder, Pseudopleuronectes americanus, forms amyloid fibrils during freezing. In this study, the effects of distinct components of the freezing process were examined. Freezing of wflAFP-6 in the presence of template ice was shown to be necessary for rapid conversion to an amyloid conformation. Neither subfreezing temperature nor phase change was sufficient. Thus, specific interaction with the ice surface was essential. The ice-induced formation of amyloid appeared to be unique to this helical antifreeze, it required high concentrations of protein and it occurred over a range of pH values. These results define a method for rapid formation of amyloid by wflAFP-6 on demand under physiological conditions.
Keywords: amyloid; antifreeze protein; ice; Pseudopleuronectes americanus; winter flounder

Interaction of saponin 1688 with phase separated lipid bilayers - Chen, Maohui; Balhara, Vinod; Castillo, Ana Maria Jaimes; Balsevich, John; Johnston, Linda J. (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2017)
Saponins are a diverse family of naturally occurring plant triterpene or steroid glycosides that have a wide range of biological activities. They have been shown to permeabilize membranes and in some cases membrane disruption has been hypothesized to involve saponin/cholesterol complexes. We have examined the interaction of steroidal saponin 1688-1 with lipid membranes that contain cholesterol and have a mixture of liquid-ordered (Lo) and liquid-disordered (Ld) phases as a model for lipid rafts in cellular membranes. A combination of atomic force microscopy (AFM) and fluorescence was used to probe the effect of saponin on the bilayer. The results demonstrate that saponin forms defects in the membrane and also leads to formation of small aggregates on the membrane surface. Although most of the membrane damage occurs in the liquid-disordered phase, fluorescence results demonstrate that saponin localizes in both ordered and disordered membrane phases, with a modest preference for the disordered regions. Similar effects are observed for both direct incorporation of saponin in the lipid mixture used to make vesicles/bilayers and for incubation of saponin with preformed bilayers. The results suggest that the initial sites of interaction are at the interface between the domains and surrounding disordered phase. The preference for saponin localization in the disordered phase may reflect the ease of penetration of saponin into a less ordered membrane, rather than the actual cholesterol concentration in the membrane. Dye leakage assays indicate that a high concentration of saponin is required for membrane permeabilization consistent with the supported lipid bilayer experiments.
Keywords: saponin; lipid bilayer; atomic force microscopy; fluorescence; dye leakage

The role of localized acidity generation in microbially influenced corrosion - Kryachko, Y.; Hemmingsen, S. M. (Current Microbiology, 2017)
Microbially influenced corrosion is of great industrial concern. Microbial coupling of metal oxidation to sulfate-, nitrate-, nitrite-, or CO2-reduction is proton-mediated, and some sulfate-reducing prokaryotes are capable of regulating extracellular pH. The analysis of the corrosive processes catalyzed by nitrate reducing bacteria and methanogenic archaea indicates that these microorganisms may be capable of regulating extracellular pH as well. It is proposed that nutrient limitation at metal-biofilm interfaces may induce activation of enzymatic proton-producing/proton-secreting functions in respiratory and methanogenic microorganisms to make them capable of using Fe0 as the electron donor. This can be further verified through experiments involving measurements of ion and gas concentrations at metal-biofilm interfaces, microscopy, and transcriptomics analyses.
Keywords: biocorrosion; pH; blofilm; sulfate reducing bacteria; nitrate reducing bacteria; methanogen

Shrimp oil extracted from the shrimp processing waste reduces the development of insulin resistance and metabolic phenotypes in diet-induced obese rats - Nair, Sandhya; Gagnon, Jacques; Pelletier, Claude; Tchoukanova, Nadia; Zhang, Junzeng; Ewart, H. Stephen; Ewart, Vanya; Jiao, Guangling; Wang, Yanwen (Applied Physiology, Nutrition, and Metabolism, 2017)
Diet-induced obesity, insulin resistance, impaired glucose tolerance, chronic inflammation and oxidative stress represent the main features of type 2 diabetes mellitus. The present study was conducted to examine the efficacy and mechanisms of shrimp oil on glucose homeostasis in obese rats. Male CD rats fed a high-fat diet (60 kcal% fat) and 20% fructose-drinking water were divided into four groups and treated with the dietary replacement of 0, 10% (SO10), 15% (SO15), or 20% (SO20) of lard with shrimp oil for 10 weeks. Age-matched rats fed a low-fat diet (10 kcal% fat) were used as the normal control. Rats on the high-fat diet showed impaired (p < 0.05) glucose tolerance and insulin resistance compared with rats fed the low-fat diet. Shrimp oil improved (p < 0.05) oral glucose tolerance, insulin response and homeostatic model assessment-estimated insulin resistance index, decreased serum insulin, leptin and hemoglobin A1c and free fatty acids, and increased adiponectin. Shrimp oil also increased (p < 0.05) antioxidant capacity and reduced oxidative stress and chronic inflammation. The results demonstrated that shrimp oil dose-dependently improved glycemic control in obese rats through multiple mechanisms.
Keywords: diet-induced obesity; glucose tolerance; insulin sensitivity; oxidative stress; inﬂammation; rat; obésité d’origine alimentaire; tolérance au glucose; sensibilité insulinique; stress oxydatif; inﬂammation; rat

Flow pattern similarities in the near wake of three bird species suggest a common role for unsteady aerodynamic effects in lift generation - Gurka, Roi; Krishnan, Krishnamoorthy; Ben-Gida, Hadar; Kirchhefer, Adam J.; Kopp, Gregory A.; Guglielmo, Christopher G. (Interface Focus, 2017)
Analysis of the aerodynamics of flapping wings has yielded a general understanding of how birds generate lift and thrust during flight. However, the role of unsteady aerodynamics in avian flight due to the flapping motion still holds open questions in respect to performance and efficiency. We studied the flight of three distinctive bird species: western sandpiper (Calidris mauri), European starling (Sturnus vulgaris) and American robin (Turdus migratorius) using long-duration, time-resolved particle image velocimetry, to better characterize and advance our understanding of how birds use unsteady flow features to enhance their aerodynamic performances during flapping flight. We show that during transitions between downstroke and upstroke phases of the wing cycle, the near wake-flow structures vary and generate unique sets of vortices. These structures appear as quadruple layers of concentrated vorticity aligned at an angle with respect to the horizon (named ‘double branch’). They occur where the circulation gradient changes sign, which implies that the forces exerted by the flapping wings of birds are modified during the transition phases. The flow patterns are similar in (non-dimensional) size and magnitude for the different birds suggesting that there are common mechanisms operating during flapping flight across species. These flow patterns occur at the same phase where drag reduction of about 5% per cycle and lift enhancement were observed in our prior studies. We propose that these flow structures should be considered in wake flow models that seek to account for the contribution of unsteady flow to lift and drag.

The mRNA transportome of the BicD/Egl transport machinery - Vazquez-pianzola, Paula; Schaller, Bogdan; Colombo, Martino; Beuchle, Dirk; Neuenschwander, Samuel; Marcil, Anne; Bruggmann, Rémy; Suter, Beat (RNA Biology, 2017)
mRNA (mRNA) transport focuses the expression of encoded proteins to specific regions within cells providing them with the means to assume specific functions and even identities. BicD and the mRNA binding protein Egl interact with the microtubule motor dynein to localize mRNAs in Drosophila. Because relatively few mRNA cargos were known, we isolated and identified Egl::GFP associated mRNAs. The top candidates were validated by qPCR, in situ hybridization and genetically by showing that their localization requires BicD. In young embryos these Egl target mRNAs are preferentially localized apically, between the plasma membrane and the blastoderm nuclei, but also in the pole plasm at the posterior pole. Egl targets expressed in the ovary were mostly enriched in the oocyte and some were apically localized in follicle cells. The identification of a large group of novel mRNAs associated with BicD/Egl points to several novel developmental and physiological functions of this dynein dependent localization machinery. The verified dataset also allowed us to develop a tool that predicts conserved A'-form-like stem loops that serve as localization elements in 3′UTRs.
Keywords: Bicaudal-D; Drosophila development; egalitarian; mRNA localization; microtubule transport

The crosstalk between Target of Rapamycin (TOR) and Jasmonic Acid (JA) signaling existing in Arabidopsis and cotton - Song, Yun; Zhao, Ge; Zhang, Xueyan; Li, Linxuan; Xiong, Fangjie; Zhuo, Fengping; Zhang, Chaojun; Yang, Zuoren; Datla, Raju; Ren, Maozhi; Li, Fuguang (Scientific Reports, 2017)
Target of rapamycin (TOR) acts as an important regulator of cell growth, development and stress responses in most examined diploid eukaryotes. However, little is known about TOR in tetraploid species such as cotton. Here, we show that TORC1-S6K-RPS6, the major signaling components, are conserved and further expanded in cotton genome. Though the cotton seedlings are insensitive to rapamycin, AZD8055, the second-generation inhibitor of TOR, can significantly suppress the growth in cotton. Global transcriptome analysis revealed that genes associated with jasmonic acid (JA) biosynthesis and transduction were significantly altered in AZD8055 treated cotton seedlings, suggesting the potential crosstalk between TOR and JA signaling. Pharmacological and genetic approaches have been employed to get further insights into the molecular mechanism of the crosstalk between TOR and JA. Combination of AZD8055 with methyl jasmonate can synergistically inhibit cotton growth, and additionally JA levels were significantly increased when cotton seedlings were subjected to AZD8055. JA biosynthetic and signaling mutants including jar1, coi1-2 and myc2-2 displayed TOR inhibitor-resistant phenotypes, whereas COI1 overexpression transgenic lines and jaz10 exhibited sensitivity to AZD8055. Consistently, cotton JAZ can partially rescue TOR-suppressed phenotypes in Arabidopsis. These evidences revealed that the crosstalk between TOR and JA pathway operates in cotton and Arabidopsis.

An extract from shrimp processing by-products protects SH-SY5Y cells from neurotoxicity induced by Aβ25–35 - Zhang, Yongping; Jiao, Guangling; Song, Cai; Gu, Shelly; Brown, Richard; Zhang, Junzeng; Zhang, Pingcheng; Gagnon, Jacques; Locke, Steven; Stefanova, Roumiana; Pelletier, Claude; Zhang, Yi; et al. (Marine Drugs, 2017)
Increased evidence suggests that marine unsaturated fatty acids (FAs) can protect neurons from amyloid-β (Aβ)-induced neurodegeneration. Nuclear magnetic resonance (NMR), high performance liquid chromatography (HPLC) and gas chromatography (GC) assays showed that the acetone extract 4-2A obtained from shrimp Pandalus borealis industry processing wastes contained 67.19% monounsaturated FAs and 16.84% polyunsaturated FAs. The present study evaluated the anti-oxidative and anti-inflammatory effects of 4-2A in Aβ25–35-insulted differentiated SH-SY5Y cells. Cell viability and cytotoxicity were measured by using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) assays. Quantitative PCR and Western blotting were used to study the expression of neurotrophins, pro-inflammatory cytokines and apoptosis-related genes. Administration of 20 μM Aβ25–35 significantly reduced SH-SY5Y cell viability, the expression of nerve growth factor (NGF) and its tyrosine kinase TrkA receptor, as well as the level of glutathione, while increased reactive oxygen species (ROS), nitric oxide, tumor necrosis factor (TNF)-α, brain derived neurotrophic factor (BDNF) and its TrkB receptor. Aβ25–35 also increased the Bax/Bcl-2 ratio and Caspase-3 expression. Treatment with 4-2A significantly attenuated the Aβ25–35-induced changes in cell viability, ROS, GSH, NGF, TrkA, TNF-α, the Bax/Bcl-2 ratio and Caspase-3, except for nitric oxide, BDNF and TrKB. In conclusion, 4-2A effectively protected SH-SY5Y cells against Aβ-induced neuronal apoptosis/death by suppressing inflammation and oxidative stress and up-regulating NGF and TrKA expression.
Keywords: acetone extract from shrimp processing by-product (4-2A); polyunsaturated fatty acids; Aβ25–35; human neuroblastoma cell (SH-SY5Y); neuroprotection; Alzheimer’s disease (AD)

Auxin response cell-autonomously controls ground tissue initiation in the early Arabidopsis embryo - Möller, Barbara K.; Ten hove, Colette A.; Xiang, Daoquan; Williams, Nerys; López, Lorena González; Yoshida, Saiko; Smit, Margot; Datla, Raju; Weijers, Dolf (Proceedings of the National Academy of Sciences, 2017)
Plant organs are typically organized into three main tissue layers. The middle ground tissue layer comprises the majority of the plant body and serves a wide range of functions, including photosynthesis, selective nutrient uptake and storage, and gravity sensing. Ground tissue patterning and maintenance in Arabidopsis are controlled by a well-established gene network revolving around the key regulator SHORT-ROOT (SHR). In contrast, it is completely unknown how ground tissue identity is first specified from totipotent precursor cells in the embryo. The plant signaling molecule auxin, acting through AUXIN RESPONSE FACTOR (ARF) transcription factors, is critical for embryo patterning. The auxin effector ARF5/MONOPTEROS (MP) acts both cell-autonomously and noncell-autonomously to control embryonic vascular tissue formation and root initiation, respectively. Here we show that auxin response and ARF activity cell-autonomously control the asymmetric division of the first ground tissue cells. By identifying embryonic target genes, we show that MP transcriptionally initiates the ground tissue lineage and acts upstream of the regulatory network that controls ground tissue patterning and maintenance. Strikingly, whereas the SHR network depends on MP, this MP function is, at least in part, SHR independent. Our study therefore identifies auxin response as a regulator of ground tissue specification in the embryonic root, and reveals that ground tissue initiation and maintenance use different regulators and mechanisms. Moreover, our data provide a framework for the simultaneous formation of multiple cell types by the same transcriptional regulator.

Identification of crepenynic acid in the seed oil of Atractylodes lancea and A. macrocephala - Sun, Jin-Yue; Guo, Xu; Smith, Mark A. (Journal of the American Oil Chemists' Society, 2017)
Atractylodes rhizome is widely used in traditional Chinese herbal medicine. Although the chemical composition of the root has been studied in detail, the oil content and fatty acid composition of the seeds of Atractylodes species have not been reported. Fatty acyl composition of seeds from Atractylodes lancea and A. macrocephala was determined by gas chromatography and mass spectrometry of fatty acid methyl esters and 3-pyridylcarbinol esters. The predominant fatty acid in the seeds of both species was linolenic acid, but the unusual acetylenic fatty acid, crepenynic acid (cis-9-octadecen-12-ynoic acid), was also observed at levels of 18% in A. lancea and 13–15% in A. macrocephala. Fatty acid content was 24% for the samples of A. lancea and 16–17% for samples from A. macrocephala. sn-1,3 regioselective lipase digestion of seed lipids revealed that crepenynic acid was absent from the sn-2 position of the seed triacylglycerol. Crepenynic acid was also found in the seed oil of Jurinea mollis at 24% and was not present in the sn-2 position of the TAG. A contrasting distribution of crepenynic acid was found in the oil of Crepis rubra, suggesting differences in crepenynic acid synthesis or TAG assembly between these species.
Keywords: Atractylodes; Jurinea; crepenynic acid; acetylenic; seed oil; sn-2 MAG

Measurement uncertainty challenge - Meija, Juris (Analytical and Bioanalytical Chemistry, 2017)
We would like to invite you to participate in the Analytical Challenge, a series of puzzles to entertain and challenge our readers. This special feature of “Analytical and Bioanalytical Chemistry” (ABC) has established itself as a truly unique quiz series, with a new scientific puzzle published every three months. Readers can access the complete collection of published problems with their solutions on the ABC homepage at http://www.springer.com/abc. Test your knowledge and tease your wits in diverse areas of analytical and bioanalytical chemistry by viewing this collection. In the present challenge, measurement uncertainty is the topic. And please note that there is a prize to be won (a Springer book of your choice up to a value of €100). Please read on…

New control methodology for a morphing wing demonstrator - Tchatchueng Kammegne, Michel Joël; Tondji, Yvan; Botez, Ruxandra Mihaela; Grigorie, Lucian Teodor; Mamou, Mahmoud; Mébarki, Youssef (Proceedings of the Institution of Mechanical Engineers, Part G: Journal of Aerospace Engineering, 2017)
A morphing wing can improve the aircraft aerodynamic performance by changing the wing airfoil depending on the flight conditions. In this paper, a new control methodology is presented for a morphing wing demonstrator tested in a subsonic wind tunnel in the open-loop configuration. Actuators integrated inside the wing are used to modify the flexible structure, which is an integral part of the wing. In this project, the actuators are made in-house and controlled with logic control, which is developed within the main frame of this work. The characterization of the flow (laminar or turbulent) over the wing is obtained starting from the pressure signals measured over the flexible part of the wing (upper surface). The signals are acquired by using some pressure sensors (Kulite sensors) incorporated in this flexible part of the wing upper surface. The technique used to collect Kulite pressure data and the post-processing methodology are explained. The recorded pressure data are sometimes subjected to noise, which is filtered before being processed. The standard deviation and power spectrum visualization of the pressure data approaches are used to evaluate the quality of the flow over the wing and estimate the transition point position in the area monitored by the Kulite sensors. In addition, infrared thermography visualization is implemented to observe the transition region over the entire wing upper surface, and to validate the methodology applied to the pressure data in this way. The demonstrator measures 1.5 m chordwise and 1.5 m spanwise. Four miniature actuators fixed on two actuation lines are used to morph the wing. The wing is also equipped with a rigid aileron. The experimental aerodynamic results obtained after post processing validate the numerical prediction for the transition location.

Pilot study on peptide purity: synthetic human C-peptide - Josephs, R. D.; Li, M.; Song, D.; Daireaux, A.; Choteau, T.; Stoppacher, N.; Westwood, S.; Wielgosz, R.; Xiao, P.; Liu, Y.; Gao, X.; Zhang, C.; et al. (Metrologia, 2017)
Under the auspices of the Protein Analysis Working Group (PAWG) of the Comité Consultatif pour la Quantité de Matière (CCQM) a pilot study, CCQM-P55.2, was coordinated by the Bureau International des Poids et Mesures (BIPM) and the Chinese National Institute of Metrology (NIM). Four Metrology Institutes or Designated Institutes and the BIPM participated. Participants were required to assign the mass fraction of human C-peptide (hCP) present as the main component in the comparison sample for CCQM-P55.2. The comparison samples were prepared from synthetic human hCP purchased from a commercial supplier and used as provided without further treatment or purification. hCP was selected to be representative of the performance of a laboratory's measurement capability for the purity assignment of short (up to 5 kDa), non-cross-linked synthetic peptides/proteins. It was anticipated to provide an analytical measurement challenge representative for the value-assignment of compounds of broadly similar structural characteristics. The majority of participants used a quantitative nuclear magnetic resonance spectroscopy (qNMR) corrected for peptide impurities. Other participants provided results obtained by peptide impurity corrected amino acid analysis (PICAA) or elemental analysis (PICCHN). It was decided to assign reference values based on the KCRVs of CCQM-K115 for both the hCP mass fraction and the mass fraction of the peptide related impurities as indispensable contributor regardless of the use of PICAA, mass balance or any other approach to determine the hCP purity. This allowed participants to demonstrate the efficacy of their implementation of the approaches used to determine the hCP mass fraction. In particular it allows participants to demonstrate the efficacy of their implementation of peptide related impurity identification and quantification. The assessment of the mass fraction of peptide impurities is based on the assumption that only the most exhaustive and elaborate set of results is taken for the calculation of the reference value. The reference value for the peptide related impurity mass fractions of the material was 83.3 mg/g with a combined standard uncertainty of 1.5 mg/g. Inspection of the degree of equivalence plots for the mass fraction of peptide impurities and additional information obtained from the peptide related impurity profile indicates that in many cases only a very small number of impurities have been identified and quantified resulting in an underestimation of the peptide related impurity mass fractions. The reference value for the mass fraction of hCP for CCQM-KP55.2 is 801.8 mg/g with a corresponding combined standard uncertainty of 3.1 mg/g. Inspection of the degree of equivalence plots for CCQM-P55.2 for the mass fraction of hCP shows that three results agree with the reference value.

Human response to emergency communication: a review of guidance on alerts and warning messages for emergencies in buildings - Omori, Hidemi; Kuligowski, Erica D.; Gwynne, Steven M. V.; Butler, Kathryn M. (Fire Technology, 2017)
The purpose of this article is to provide guidance on enhancing human response to emergency communication. This guidance can, in turn, help engineers improve the design of emergency notification and messaging systems, which, as a result, can help inform occupant response, reduce occupant evacuation time, and increase occupant safety. The article begins with a literature review on how people respond to emergencies. The Protective Action Decision Model, which describes the decision-making process that precedes human response in disaster events, is used as a framework for the literature collected as part of this review. This model is divided into three pre-decisional and five decisional processes. The method used to create the guidance document is then explained, including the six steps taken to review the literature collected (from 162 engineering and social science sources), generate findings from this literature, and compile the key statements found in the guidance document. Guidance on alerts, visual/audible warnings and dissemination of warning messages are provided. These are organized according to alert/warning type and dissemination method. The findings of the literature review include five guidance statements on alerts, 16 guidance statements on visual warnings, seven guidance statements on audible warnings and eight guidance statements on the dissemination of warning messages. Finally, guidance on emergency message testing, including language, readability and fire drills as a means of response testing, is provided. It is envisioned that this guidance will inform practitioners on the design of future emergency communications and subsequently enhances evacuee performance through a better understanding of the manner in which emergency information is processed and the tools available to provide such information.
Keywords: emergency communication; alerts; warnings; guidance; human response; occupant evacuation; occupant response; emergency notification; emergency messaging; mass notification

Final report on CCQM-K125: elements in infant formula - Merrick, J; Saxby, D.; Dutra, E. S.; Sena, R. C.; Araújo, T. O.; Almeida, M. D.; Yang, L.; Pihillagawa, I. G.; Mester, Z.; Sandoval, S.; Wei, C.; Castillo, M. E. D.; et al. (Metrologia, 2017)
CCQM-K125 was organized by the Inorganic Analysis Working Group (IAWG) of CCQM to assess and document the capabilities of the national metrology institutes (NMIs) or the designated institutes (DIs) to measure the mass fractions of trace elements (K, Cu and I) in infant formula. Government Laboratory, Hong Kong SAR (GLHK) acted as the coordinating laboratory. In CCQM-K125, 25 institutes submitted the results for potassium, 24 institutes submitted the results for copper and 8 institutes submitted the results for iodine. For examination of potassium and copper, most of the participants used microwave-assisted acid digestion methods for sample dissolution. A variety of instrumental techniques including inductively coupled plasma mass spectrometry (ICP-MS), isotope dilution inductively coupled plasma mass spectrometry (ID-ICP-MS), inductively coupled plasma optical emission spectrometry (ICP-OES), atomic absorption spectrometry (AAS), flame atomic emission spectrometry (FAES) and microwave plasma atomic emission spectroscopy (MP-AES) were employed by the participants for determination. For analysis of iodine, most of the participants used alkaline extraction methods for sample preparation. ICP-MS and ID-ICP-MS were used by the participants for the determination. Generally, the participants' results of CCQM-K125 were found consistent for all measurands according to their equivalence statements. Except with some extreme values, most of the participants obtained the values of di/U(di) within ± 1 for the measurands.

Report of the CCQM-K124: trace elements and chromium speciation in drinking water, part A: trace elements in drinking water, part B: chromium speciation in drinking water - Kuroiwa, T.; Fung, W. H.; Zhu, Y.; Inagaki, K.; Sin, D. W. M.; Chu, H. S.; Saxby, D.; Merrick, J.; White, I.; Araujo, T.; Almeida, M. D.; Rodrigues, J.; et al. (Metrologia, 2017)
CCQM-K124 was organized by the Inorganic Analysis Working Group (IAWG) of CCQM to assess and document the capabilities of the national metrology institutes (NMIs) or the designated institutes (DIs) to measure the mass fractions of trace elements (As, B, Cd, Ca, Cr, Hg and Mo) and hexavalent chromium (Cr(VI)) in drinking water. The National Metrology Institute of Japan (NMIJ) and the Government Laboratory, Hong Kong SAR (GLHK) acted as the coordinating laboratories. This comparison is divided into two parts. Part A was organized by the NMIJ and the trace elements were the analytes, and Part B was organised by the GLHK and Cr(VI) was the analyte. In Part A, results were submitted by 14 NMIs and nine DIs. The participants used different measurement methods, though most of them used direct measurement using inductively coupled plasma-optical emission spectrometry (ICP-OES), inductively coupled plasma-mass spectrometry (ICP-MS), and isotope dilution technique with ICP-MS. The results of As, B, Cd, Ca and Cr show good agreement with the exception of some outliers. Concerning Hg, instability was observed when the sample was stored in the light. And some participants observed instability of Mo. Therefore, it was agreed to abandon the Hg and Mo analysis as this sample was not satisfactory for KC. In Part B, results were submitted by six NMIs and one DI. The methods applied were direct measurement using 1,5-diphenylcarbazide (DPC) derivatisation UV-visible spectrophotometry, standard addition using ion chromatography-UV-visible spectrophotometry or HPLC—inductively coupled plasma-mass spectrometry (ICP-MS) and isotope dilution technique with ion chromatography—ICP-MS. The results of all participants show good agreement. Accounting for relative expanded uncertainty, comparability of measurement results for each of As, B, Cd, Ca, Cr and Cr(VI) was successfully demonstrated by the participating NMIs or DIs.

Numerical study of soot formation in laminar coflow methane/air diffusion flames doped by n-heptane/toluene and iso-octane/toluene blends - Consalvi, Jean-Louis; Liu, Fengshan; Kashif, M.; Legros, G. (Combustion and Flame, 2017)
The laminar coflow nitrogen-diluted methane/air diffusion flames doped with a small amount of n-heptane/toluene and iso-octane/toluene binary mixtures, investigated experimentally by Kashif et al. (2015), were simulated numerically by using a detailed reaction mechanism and a sectional polycyclic aromatic hydrocarbon (PAH)-based soot model. The numerical model provides results in reasonable qualitative agreement with the experimental data by using the same chemical mechanism, the same soot model, and the same set of constants employed successfully in a previous study to model the effects of n-heptane/iso-octane doping, demonstrating that this overall model is promising to model soot formation in gasoline flames. Soot production is enhanced monotonically with increasing the toluene content in either the n-heptane/toluene or iso-octane/toluene doping fuel mixture. The increase in benzene and pyrene production displays a non-monotonic and synergistic response to the increase in toluene content. These numerical results are consistent with available experimental results as far as the trends in the effects of increasing the toluene content are concerned. Model results show that the dominant pathways responsible for the synergistic effects on benzene and pyrene production are respectively C6H5CH3 (toluene) + H ↔ A1 (benzene) + CH3 and A3- (C14H9) + C2H2 ↔ A4 (pyrene) + H.
Keywords: laminar coflow diffusion flame; gasoline surrogate; toluene reference fuels; PAH-based soot model; synergistic effects

Bioavailability of immobilized epidermal growth factor: covalent versus noncovalent grafting - Riahi, Nesrine; Murschel, Frederic; Lerouge, Sophie; Durocher, Yves; Henry, Olivier; De crescenzo, Gregory (Biointerphases, 2017)
In an effort to rationalize and optimize an antiapoptotic coating combining chondroitin sulfate (CS) and epidermal growth factor (EGF) for vascular applications, the authors here report the comparison of two grafting strategies aiming to display EGF in an oriented fashion on CS. For that purpose, the authors produced, purified, and characterized a chimeric protein corresponding to EGF that was N-terminally fused to a cysteine and a coil peptide. The chimera was covalently immobilized via its free thiol group or captured via coiled–coil interactions at the surface of a biosensor or on a chondroitin sulfate coating in multiwell plates, mimicking the coating that was previously developed by them for stent-graft surfaces. The interactions of grafted EGF with the soluble domain of its receptor or the impact of grafted EGF upon vascular smooth muscle survival in proapoptotic conditions indicated that the coiled–coil based tethering was the best approach to display EGF. These results, combined to direct enzyme-linked immunosorbent assay measurements, indicated that the coiled–coil tethering approach allowed increasing the amount of bioavailable EGF when compared to covalent coupling, rather than the total amount of grafted EGF, while using much lower concentrations of tagged EGF during incubation.

Data reduction framework for standard atomic weights and isotopic compositions of the elements - Meija, Juris; Possolo, Antonio (Metrologia, 2017)
We outline a general framework to compute consensus reference values of standard atomic weights, isotope ratios, and isotopic abundances, and to evaluate associated uncertainties using modern statistical methods for consensus building that can handle mutually inconsistent measurement results. The multivariate meta-regression approach presented here is directly relevant to the work of the IUPAC Commission on Isotopic Abundances and atomic weights (CIAAW), and we illustrate the proposed method in meta-analyses of the isotopic abundances and atomic weights of zinc, platinum, antimony, and iridium.
Keywords: standard atomic weights; consensus values; multivariate random effects model; meta-analysis; DerSimonian-Laird; dark uncertainty

Processing and in vitro bioactivity of high-strength 45S5 glass-ceramic scaffolds for bone regeneration - Aguilar-Reyes, Ena A.; León-Patiño, Carlos A.; Villicaña-Molina, Esmeralda; Macías-Andrés, Víctor I.; Lefebvre, Louis-Philippe (Ceramics International, 2017)
In this paper, the compressive strength and in vitro bioactivity of sintered 45S5 bioactive glass scaffolds produced by powder technology and polymer foaming were investigated. The sintering temperature of scaffolds was 975 °C. The characterization of scaffolds before immersion in SBF was performed by scanning electron microscopy (SEM) and microtomography (μCT). The scaffolds were also tested for compression, and their density and porosity were measured. After immersion, the samples were observed through SEM and analyzed using EDS, X-ray diffraction (XRD), and infrared spectroscopy (FT-IR). Mass variation was also estimated. The glass-ceramic scaffolds showed a 61.44±3.13% interconnected porosity and an average compressive strength of 13.78±2.43 MPa. They also showed the formation of a hydroxyapatite layer after seven days of immersion in SBF, demonstrating that partial crystallization during sintering did not suppress their bioactivity.
Keywords: sintering; porosity; strength; glass ceramics; biomedical applications

Towards the development of cavitation technology for upgrading bitumen: viscosity change and chemical cavitation yield measurements - Kirpalani, Deepak M.; Mohapatra, Dipti Prakash (Petroleum Science, 2017)
Among the different methods used for reducing viscosity of bitumen, acoustic cavitation during sonication is well recognised. Several chemical methods were used to detect the production of reactive species such as hydroxyl radicals and hydrogen peroxide during acoustic cavitation processes. However, quantification of cavitation yield in sonochemical systems is generally limited to low frequencies and has not been applied to bitumen processing. An empirical determination of the cavitation yield in mid- to high-frequency range (378, 574, 850, 992, and 1173 kHz) was carried out by measuring the amount of iodine liberated from the oxidation of potassium iodide (KI). Further, cavitation yield and the effects of different sonic operating conditions such as power input (16.67%–83.33%) and solute concentration on cavitation yield were carried out in KI solution and sodium carboxymethyl cellulose–water mixture to obtain benchmark changes in rheology and chemistry using these two model fluids. The findings were then applied to bitumen upgrading through sonication. Through this study, it was found that the chemical cavitation yield peaked with a sonication frequency of 574 kHz. It was also found that cavitation yield and viscosity change were correlated directly in bitumen and a 38% lower bitumen viscosity could be obtained by acoustic cavitation.
Keywords: bitumen; cavitation yield; CMC–water; KI solution; viscosity correlation

Sulfated diesters of okadaic acid and DTX-1: self-protective precursors of diarrhetic shellfish poisoning (DSP) toxins - Hu, Tingmo; Leblanc, Patricia; Burton, Ian W.; Walter, John A.; Mccarron, Pearse; Melanson, Jeremy E.; Strangman, Wendy K.; Wright, Jeffrey L. C. (Harmful Algae, 2017)
Many toxic secondary metabolites used for defense are also toxic to the producing organism. One important way to circumvent toxicity is to store the toxin as an inactive precursor. Several sulfated diesters of the diarrhetic shellfish poisoning (DSP) toxin okadaic acid have been reported from cultures of various dinoflagellate species belonging to the genus Prorocentrum. It has been proposed that these sulfated diesters are a means of toxin storage within the dinoflagellate cell, and that a putative enzyme mediated two-step hydrolysis of sulfated diesters such as DTX-4 and DTX-5 initially leads to the formation of diol esters and ultimately to the release of free okadaic acid. However, only one diol ester and no sulfated diesters of DTX-1, a closely related DSP toxin, have been isolated leading some to speculate that this toxin is not stored as a sulfated diester and is processed by some other means. DSP components in organic extracts of two large scale Prorocentrum lima laboratory cultures have been investigated. In addition to the usual suite of okadaic acid esters, as well as the free acids okadaic acid and DTX-1, a group of corresponding diol- and sulfated diesters of both okadaic acid and DTX-1 have now been isolated and structurally characterized, confirming that both okadaic acid and DTX-1 are initially formed in the dinoflagellate cell as the non-toxic sulfated diesters.
Keywords: DSP toxins; okadaic acid; DTX-1; diol esters; sulfated diesters; toxin storage

Key comparison study on peptide purity: synthetic human C-peptide - Josephs, R. D.; Li, M.; Song, D.; Westwood, S.; Stoppacher, N.; Daireaux, A.; Choteau, T.; Wielgosz, R.; Xiao, P.; Liu, Y.; Gao, X.; Zhang, C.; et al. (Metrologia, 2017)
Under the auspices of the Protein Analysis Working Group (PAWG) of the Comité Consultatif pour la Quantité de Matière (CCQM) a key comparison, CCQM-K115, was coordinated by the Bureau International des Poids et Mesures (BIPM) and the Chinese National Institute of Metrology (NIM). Eight Metrology Institutes or Designated Institutes and the BIPM participated. Participants were required to assign the mass fraction of human C-peptide (hCP) present as the main component in the comparison sample for CCQM-K115. The comparison samples were prepared from synthetic human hCP purchased from a commercial supplier and used as provided without further treatment or purification. hCP was selected to be representative of the performance of a laboratory's measurement capability for the purity assignment of short (up to 5 kDa), non-cross-linked synthetic peptides/proteins. It was anticipated to provide an analytical measurement challenge representative for the value-assignment of compounds of broadly similar structural characteristics. The majority of participants used a peptide impurity corrected amino acid analysis (PICAA) approach as the amount of material that has been provided to each participant (25 mg) is insufficient to perform a full mass balance based characterization of the material by a participating laboratory. The coordinators, both the BIPM and the NIM, were the laboratories to use the mass balance approach as they had more material available. It was decided to propose KCRVs for both the hCP mass fraction and the mass fraction of the peptide related impurities as indispensable contributor regardless of the use of PICAA, mass balance or any other approach to determine the hCP purity. This allowed participants to demonstrate the efficacy of their implementation of the approaches used to determine the hCP mass fraction. In particular it allows participants to demonstrate the efficacy of their implementation of peptide related impurity identification and quantification. More detailed studies on the identification/quantification of peptide related impurities and the hydrolysis efficiency revealed that the integrity of the impurity profile of the related peptide impurities obtained by the participant is crucial for the impact on accuracy of the hCP mass fraction assignment. The assessment of the mass fraction of peptide impurities is based on the assumption that only the most exhaustive and elaborate set of results is taken for the calculation of the KCRVPepImp. The KCRVPepImp for the peptide related impurity mass fractions of the material was 83.3 mg/g with a combined standard uncertainty of 1.5 mg/g. Inspection of the degree of equivalence plots for the mass fraction of peptide impurities and additional information obtained from the peptide related impurity profile indicates that in many cases only a very small number of impurities have been identified and quantified resulting in an underestimation of the peptide related impurity mass fractions. The approach to obtain a KCRVhCP for the mass fraction of hCP is based on a mass balance calculation that takes into account the most exhaustive and elaborate set of results for the peptide related impurities KCRVPepImp, the TFA mass fraction value, water and other minor counter ions obtained by the coordinating laboratories. Differences in the quality of the results obtained for both peptides related impurity mass fractions and hCP mass fractions are better weighted and reflected in smaller uncertainties. The KCRVhCP for CCQM-K115 is 801.8 mg/g with a corresponding combined standard uncertainty of 3.1 mg/g. In general, mass balance approaches show smaller uncertainties than PICAA approaches and the majority of results obtained by the PICAA approach are in agreement because of larger corresponding uncertainties.

Highly predictive SNP markers for efficient selection of the wheat leaf rust resistance gene Lr16 - Kassa, Mulualem T.; You, Frank M.; Hiebert, Colin W.; Pozniak, Curtis J.; Fobert, Pierre R.; Sharpe, Andrew G.; Menzies, James G.; Humphreys, D. Gavin; Rezac harrison, Nicole; Fellers, John P.; Mccallum, Brent D.; Mccartney, Curt A. (BMC Plant Biology, 2017)
Background: Lr16 is a widely deployed leaf rust resistance gene in wheat (Triticum aestivum L.) that is highly effective against the North American Puccinia triticina population when pyramided with the gene Lr34. Lr16 is a seedling leaf rust resistance gene conditioning an incompatible interaction with a distinct necrotic ring surrounding the uredinium. Lr16 was previously mapped to the telomeric region of the short arm of wheat chromosome 2B. The goals of this study were to develop numerous single nucleotide polymorphism (SNP) markers for the Lr16 region and identify diagnostic gene-specific SNP marker assays for marker-assisted selection (MAS). Results: Forty-three SNP markers were developed and mapped on chromosome 2BS tightly linked with the resistance gene Lr16 across four mapping populations representing a total of 1528 gametes. Kompetitive Allele Specific PCR (KASP) assays were designed for all identified SNPs. Resistance gene analogs (RGAs) linked with the Lr16 locus were identified and RGA-based SNP markers were developed. The diagnostic potential of the SNPs co-segregating with Lr16 was evaluated in a diverse set of 133 cultivars and breeding lines. Six SNP markers were consistent with the Lr16 phenotype and are accurately predictive of Lr16 for all wheat lines/cultivars in the panel. Conclusions: Lr16 was mapped relative to SNP markers in four populations. Six SNP markers exhibited high quality clustering in the KASP assay and are suitable for MAS of Lr16 in wheat breeding programs.
Keywords: Lr16; leaf rust; puccinia triticina; wheat; triticum aestivum L; disease resistance; single nucleotide polymorphism (SNP); linkage analysis; resistance gene analog (RGA)

Effects of eIFiso4G1 mutation on seed oil biosynthesis - Li, Qiang; Shen, Wenyun; Zheng, Qian; Tan, Yifang; Gao, Jie; Shen, Jinxiong; Wei, Yangdou; Kunst, Ljerka; Zou, Jitao (The Plant Journal, 2017)
Fatty acid biosynthesis is a primary metabolic pathway that occurs in plastids, whereas the formation of glycerolipid molecules for the majority of cellular membrane systems and the deposition of storage lipid in seeds takes place in the cytosolic compartment. In this report, we present a study of an Arabidopsis mutant, ar21, with a novel seed fatty acid phenotype showing a higher content of eicosanoic acid (20:1) and oleic acid (18:1) and a reduced level of α-linolenic acid (18:3). A combination of map-based cloning and whole genome sequencing identified the genetic basis underlying the fatty acid phenotype as a lesion in the plant-specific eukaryotic translation initiation factor eIFiso4G1. Transcriptome analysis on developing seeds revealed a reduced level of plastid-encoded genes. Specifically, decreases in both transcript and protein levels of an enzyme involved in lipid biosynthesis, the β-subunit of the plastidic heteromeric acetyl-CoA carboxylase (htACCase) encoded by accD, were evident in the mutant. Biochemical assays showed that the developing seeds of the mutant possessed a decreased htACCase activity in the plastid but an elevated activity of homomeric acetyl-CoA carboxylase (hmACCase). These results suggested that the increased 20:1 was attributable at least in part to the enhanced cytosolic hmACCase activity. We also detected a significant repression of FATTY ACID DESATURASE 3 (FAD3) during seed development, which correlated with a decreased 18:3 level in seed oil. Together, our study on a mutant of eIFiso4G1 uncovered multifaceted interactions between the cytosolic and plastidic compartments in seed lipid biosynthesis that impact major seed oil traits.
Keywords: arabidopsis thaliana; fatty acid metabolism; acetyl-CoA carboxylase; map-based cloning; metabolic interaction; gene expression

Carbon source and energy harvesting optimization in solid anolyte microbial fuel cells - Adekunle, Ademola; Raghavan, Vijaya; Tartakovsky, Boris (Journal of Power Sources, 2017)
This work investigates the application of a solid anolyte microbial fuel cell (saMFC) as a long-lasting source of electricity for powering electronic devices. Broadly available biodegradable materials such as humus, cattle manure, peat moss, and sawdust are evaluated as solid anolytes. The initial comparison shows significantly higher power production in the saMFC operated using humus as compared to other solid anolytes. At the same time, power production in the humus-based saMFC is found to decline after about 40 days of operation, while the sawdust MFC demonstrates stable performance over the test period. Following this initial comparison, a combined humus - sawdust anolyte is developed to increase saMFC life span. The optimized saMFC demonstrates stable power production for over nine months. Furthermore, power production in the saMFC is maximized by using an intermittent connection to an electrical load (on/off operation) and optimizing the connection/disconnection times. These results demonstrate the feasibility of utilizing solid anolytes for developing inexpensive and long-lasting biobatteries operated on renewable carbon sources.
Keywords: solid anolyte; MFC; periodic connection; optimization; MPPT

Proportional fuzzy feed-forward architecture control validation by wind tunnel tests of a morphing wing - Kammegne, Michel Joël tchatchueng; Botez, Ruxandra Mihaela; Grigorie, Lucian Teodor; Mamou, Mahmoud; Mébarki, Youssef (Chinese Journal of Aeronautics, 2017)
In aircraft wing design, engineers aim to provide the best possible aerodynamic performance under cruise flight conditions in terms of lift-to-drag ratio. Conventional control surfaces such as flaps, ailerons, variable wing sweep and spoilers are used to trim the aircraft for other flight conditions. The appearance of the morphing wing concept launched a new challenge in the area of overall wing and aircraft performance improvement during different flight segments by locally altering the flow over the aircraft’s wings. This paper describes the development and application of a control system for an actuation mechanism integrated in a new morphing wing structure. The controlled actuation system includes four similar miniature electromechanical actuators disposed in two parallel actuation lines. The experimental model of the morphing wing is based on a full-scale portion of an aircraft wing, which is equipped with an aileron. The upper surface of the wing is a flexible one, being closed to the wing tip; the flexible skin is made of light composite materials. The four actuators are controlled in unison to change the flexible upper surface to improve the flow quality on the upper surface by delaying or advancing the transition point from laminar to turbulent regime. The actuators transform the torque into vertical forces. Their bases are fixed on the wing ribs and their top link arms are attached to supporting plates fixed onto the flexible skin with screws. The actuators push or pull the flexible skin using the necessary torque until the desired vertical displacement of each actuator is achieved. The four vertical displacements of the actuators, correlated with the new shape of the wing, are provided by a database obtained through a preliminary aerodynamic optimization for specific flight conditions. The control system is designed to control the positions of the actuators in real time in order to obtain and to maintain the desired shape of the wing for a specified flight condition. The feasibility and effectiveness of the developed control system by use of a proportional fuzzy feed-forward methodology are demonstrated experimentally through bench and wind tunnel tests of the morphing wing model. Proportional fuzzy feed-forward architecture control validation by wind tunnel tests of a morphing wing.
Keywords: actuators; control; experimental validation; morphing wing; wind tunnel test

An extract of the marine alga Alaria esculenta modulates α-synuclein folding and amyloid formation - Giffin, James C.; Richards, Robert C.; Craft, Cheryl; Jahan, Nusrat; Leggiadro, Cindy; Chopin, Thierry; Szemerda, Michael; Mackinnon, Shawna L.; Ewart, K.Vanya (Neuroscience Letters, 2017)
The conversion of α-synuclein from its natively unfolded and α-helical tetrameric forms to an amyloid conformation is central to the emergence of Parkinson’s disease. Therefore, prevention of this conversion may offer an effective way of avoiding the onset of this disease or delaying its progress. At different concentrations, an aqueous extract from the edible winged kelp (Alaria esculenta), was shown to lower and to raise the melting point of α-synuclein. Size fractionation of the extract resulted in the separation of these distinct activities. The fraction below 5 kDa decreased the melting point of α-synuclein, whereas the fraction above 10 kDa raised the melting point. Both of these fractions were found to inhibit the formation of amyloid aggregates by α-synuclein, measured by thioflavin T dye-binding assays; this effect was further confirmed by transmission electron microscopy showing the inhibition of fibril formation. Circular dichroism analysis suggested that the incubation of α-synuclein under fibrillation conditions resulted in the loss of substantial native helical structure in the presence and absence of the fractions. It is therefore likely that the fractions inhibit fibrillation by interacting with the unfolded form of α-synuclein.
Keywords: Parkinson’s disease; alpha-synuclein; amyloid; protein misfolding; brown seaweed; Alaria esculenta

Quantitative molecular diagnostic assays of grain washes for Claviceps purpurea are correlated with visual determinations of ergot contamination - Comte, Alexia; Gräfenhan, Tom; Links, Matthew G.; Hemmingsen, Sean M.; Dumonceaux, Tim J.; Singh, Jaswinder (PLOS ONE, 2017)
We examined the epiphytic microbiome of cereal grain using the universal barcode chaperonin-60 (cpn60). Microbial community profiling of seed washes containing DNA extracts prepared from field-grown cereal grain detected sequences from a fungus identified only to Class Sordariomycetes. To identify the fungal sequence and to improve the reference database, we determined cpn60 sequences from field-collected and reference strains of the ergot fungus, Claviceps purpurea. These data allowed us to identify this fungal sequence as deriving from C. purpurea, and suggested that C. purpurea DNA is readily detectable on agricultural commodities, including those for which ergot was not identified as a grading factor. To get a sense of the prevalence and level of C. purpurea DNA in cereal grains, we developed a quantitative PCR assay based on the fungal internal transcribed spacer (ITS) and applied it to 137 samples from the 2014 crop year. The amount of Claviceps DNA quantified correlated strongly with the proportion of ergot sclerotia identified in each grain lot, although there was evidence that non-target organisms were responsible for some false positives with the ITS-based assay. We therefore developed a cpn60-targeted loop-mediated isothermal amplification assay and applied it to the same grain wash samples. The time to positive displayed a significant, inverse correlation to ergot levels determined by visual ratings. These results indicate that both laboratory-based and field-adaptable molecular diagnostic assays can be used to detect and quantify pathogen load in bulk commodities using cereal grain washes.

On the correlation between free volume, phase diagram and ionic conductivity of aqueous and non-aqueous lithium battery electrolyte solutions over a wide concentration range - Yim, Chae-Ho; Tam, Jasper; Soboleski, Hayden; Abu-lebdeh, Yaser (Journal of The Electrochemical Society, 2017)
There is little known about the transport behavior of ions in electrolyte solutions at very high concentrations and there is currently no one widely-accepted theory or equation to describe it over the whole concentration range. In this work, the ionic conductivity (κ) of lithium salts in aqueous and non-aqueous electrolyte solutions have been measured as a function of concentration (C) and have been fitted to known theoretical and empirical equations. A new, isothermal, semi-empirical equation based on free volume theory: κ=AC exp[−γVo/Vf C] where Vo and Vf are the occupied and unoccupied “free” volume, respectively, gives better fit over the whole concentration range than the known equations. Vf and  V02, ϕ, the apparent molar volume of the salt, were calculated from density measurements and it is found that free volume decreases with concentration in both the aqueous and non-aqueous solutions over the whole range. We hypothesize that the changes to transport properties in solution with concentration are caused by structural changes that switches the conductivity mechanism from vehicular to a Grotthuss-type or a mixture of both. We, for the first time, correlate the origin of Cmax, the concentration of highest conductivity, to the eutectic composition in the salt-solvent phase diagram.
Keywords: conductivity; electrolytes; free volume; Li-ion battery

Bioinformatics identification of new targets for improving low temperature stress tolerance in spring and winter wheat - Tchagang, Alain B.; Fauteux, François; Tulpan, Dan; Pan, Youlian (BMC Bioinformatics, 2017)
Phenotypic studies in Triticeae have shown that low temperature-induced protective mechanisms are developmentally regulated and involve dynamic acclimation processes. Understanding these mechanisms is important for breeding cold-resistant wheat cultivars. In this study, we combined three computational techniques for the analysis of gene expression data from spring and winter wheat cultivars subjected to low temperature treatments. Our main objective was to construct a comprehensive network of cold response transcriptional events in wheat, and to identify novel cold tolerance candidate genes in wheat.
Keywords: wheat; breeding; cold acclimation; cold stress; cold tolerance; low temperature; marker; target; transcriptional regulatory network

Role of skeletal muscle in ear development - Rot, I; Baguma-Nibasheka, M.; Costain, W. J.; Hong, P.; Tafra, R.; Mardesic-Brakus, S.; Mrduljas-Djujic, N.; Saraga-Babic, M.; Kablar, B. (Histol Histopathol, 2017)
The current paper is a continuation of our work described in Rot and Kablar, 2010. Here, we show lists of 10 up- and 87 down-regulated genes obtained by a cDNA microarray analysis that compared developing Myf5-/-:Myod-/- (and Mrf4-/-) petrous part of the temporal bone, containing middle and inner ear, to the control, at embryonic day 18.5. Myf5-/-:Myod-/- fetuses entirely lack skeletal myoblasts and muscles. They are unable to move their head, which interferes with the perception of angular acceleration. Previously, we showed that the inner ear areas most affected in Myf5-/-:Myod-/- fetuses were the vestibular cristae ampullaris, sensitive to angular acceleration. Our finding that the type I hair cells were absent in the mutants' cristae was further used here to identify a profile of genes specific to the lacking cell type. Microarrays followed by a detailed consultation of web-accessible mouse databases allowed us to identify 6 candidate genes with a possible role in the development of the inner ear sensory organs: Actc1, Pgam2, Ldb3, Eno3, Hspb7 and Smpx. Additionally, we searched for human homologues of the candidate genes since a number of syndromes in humans have associated inner ear abnormalities. Mutations in one of our candidate genes, Smpx, have been reported as the cause of X-linked deafness in humans. Our current study suggests an epigenetic role that mechanical, and potentially other, stimuli originating from muscle, play in organogenesis, and offers an approach to finding novel genes responsible for altered inner ear phenotypes.

Optimization and design of an aircraft’s morphing wing-tip demonstrator for drag reduction at low speed, Part I – Aerodynamic optimization using genetic, bee colony and gradient descent algorithms - Koreanschi, Andreea; Sugar Gabor, Oliviu; Acotto, Joran; Brianchon, Guillaume; Portier, Gregoire; Botez, Ruxandra Mihaela; Mamou, Mahmoud; Mebarki, Youssef (Chinese Journal of Aeronautics, 2017)
In this paper, an ‘in-house’ genetic algorithm is described and applied to an optimization problem for improving the aerodynamic performances of an aircraft wing tip through upper surface morphing. The algorithm’s performances were studied from the convergence point of view, in accordance with design conditions. The algorithm was compared to two other optimization methods, namely the artificial bee colony and a gradient method, for two optimization objectives, and the results of the optimizations with each of the three methods were plotted on response surfaces obtained with the Monte Carlo method, to show that they were situated in the global optimum region. The optimization results for 16 wind tunnel test cases and 2 objective functions were presented. The 16 cases used for the optimizations were included in the experimental test plan for the morphing wing-tip demonstrator, and the results obtained using the displacements given by the optimizations were evaluated.
Keywords: artificial bee colony; airfoil optimization; genetic algorithm; morphing wing; optimization

The plant orthology browser: an orthology and gene-order visualizer for plant comparative genomics - Tulpan, Dan; Leger, Serge (The Plant Genome, 2017)
Worldwide genome sequencing efforts for plants with medium and large genomes require identification and visualization of orthologous genes, while their syntenic conservation becomes the pinnacle of any comparative and functional genomics study. Using gene models for 20 fully sequenced plant genomes, including model organisms and staple crops such as Aegilops tauschii Coss., Arabidopsis thaliana (L.) Heynh., Brachypodium distachyon (L.) Beauv., turnip (Brassica rapa L.), barley (Hordeum vulgare L.), rice (Oryza sativa L.), sorghum [Sorghum bicolor (L.) Moench], wheat (Triticum aestivum L.), red wild einkorn (Triticum urartu Tumanian ex Gandilyan), and maize (Zea mays L.), we computationally predicted 1,021,611 orthologs using stringent sequence similarity criteria. For each pair of plant species, we determined sets of conserved synteny blocks using strand orientation and physical mapping. Gene ontology (GO) annotations are added for each gene. Plant Orthology Browser (POB) includes three interconnected modules: (i) a gene-order visualization module implementing an interactive environment for exploration of gene order between any pair of chromosomes in two plant species, (ii) a synteny visualization module providing unique interactive dot plot representations of orthologous genes between a pair of chromosomes in two distinct plant species, and (iii) a search module that interconnects all modules via free-text search capability with online as-you-type suggestions and highlighting that allows exploration of the underlining information without constraint of interface-dependent search fields. The POB is a web-based orthology and annotation visualization tool, which currently supports 20 completely sequenced plant species with considerably large genomes and offers intuitive and highly interactive pairwise comparison and visualization of genomic traits via gene orthology.

Proteomes and biomarkers of the neurovascular unit - Haqqani, A. S.; Stanimirovic, D. B. (Primer on Cerebrovascular Diseases, 2017)
Brain vessels display a distinct phenotype that includes tight junctions and barrier properties of brain endothelial cells, as well as their close association with glial cells and neurons that enable tight coupling of blood flow with brain tissue energy demand. Brain vessels undergo profound molecular, physiological, and anatomical changes and reorganization in response to injury or disease. These changes can be analyzed using integrated system biology approaches. Screening and analyses of protein expression and modifications and their association with pathophysiological vascular responses are an important research approach to identify translational vascular targets and biomarkers useful for modifying or monitoring cerebrovascular disease. This is accomplished by deploying highly sensitive mass spectrometry–based techniques, ranging from whole-proteome screening to targeted quantitative proteomics. This chapter will summarize recent advances in applying these methods to build a neurovascular unit (NVU) “Carta,” an integrated collection of dynamic proteomes of cellular and subcellular compartments of the NVU and brain vessels isolated by various techniques from animal and human brains.
Keywords: brain endothelial cells; brain vessels; cerebrovascular diseases; mass spectroscopy; proteomics; targeted quantitative proteomics

Fiber random grating feedback induced chaos in semiconductor laser with highly suppressed time-delay signature - Xu, Yanping; Zhang, Liang; Zhang, Mingjiang; Lu, Ping; Mihailov, Stephen; Bao, Xiaoyi (Optical Fiber Communication Conference, 2017)
A semiconductor laser with distributed feedbacks from a novel fiber random grating is perturbed to emit chaotically. The time delay signature of the chaotic output is suppressed with the largest extent to date.

Collision detection for virtual environment using particle swarm optimization with adaptive cauchy mutation - Zou, Yanni; Liu, Peter X.; Yang, Chunsheng; Li, Chunquan; Cheng, Qiangqiang (Cluster Computing, 2017)
Rapid and accurate detection of collision between virtual objects is crucial for many virtual reality based applications. In order to ensure a high-level of accuracy and to meet the real-time requirement, a fast collision detection algorithm between soft bodies is proposed. The developed algorithm is a combination of stochastic methods and particle swarm optimization with adaptive Cauchy mutation. The hierarchical bounding box method is used for a rough detection in order to filter out obvious disjoint space, and the problem is converted to a nonlinear optimization problem based on the distance of points. Then particle swarm optimization with adaptive Cauchy mutation is used to find the optimal solution. When it is updated iteratively, keeping some particles experience value and variation of other particles avoids particles trapped in local optimum, which further accelerates the speed of collision detection. The algorithm is implemented and evaluated through experiments and the results confirm the advantages of the developed algorithm.
Keywords: collision detection; hierarchical bounding box; nonlinear optimization; cauchy mutation; particle swarm

Residual stress ANALYSIS in linear friction welded in-service inconel 718 superalloy via neutron diffraction and contour method approaches - Smith, M.; Levesque, J.-B.; Bichler, L.; Sediako, D.; Gholipour, J.; Wanjara, P. (Materials Science and Engineering: A, 2017)
In this study, an analysis of elastic residual stress in Inconel® 718 (IN 718) linear friction welds (LFWs) was carried out. In particular, the suitability of LFW for manufacturing and repair of aero engine components was emulated by joining virgin and in-service (extracted from a turbine disk) materials. The evolution in the residual strains and stresses in the heat-affected zone (HAZ), thermomechanically affected zone (TMAZ) and dynamically recrystallized zone (DRX) of the weld was characterized using the neutron diffraction and contour methods. The results provided insight into diverse challenges in quantitative analysis of residual stresses in welded IN 718 using diffraction techniques. Specifically, judicious selection of the beam width, height and stress-free lattice spacing were seen to be crucial to minimize measurement error and increase accuracy. Further, the contour method – a destructive technique relying on capturing the stress relaxation after electrical discharge machining – was used to characterize the residual stress distribution on two-dimensional plane sections of the welds. Both techniques suggested an increasing magnitude of residual stress originating from the base metal that reached a peak at the weld interface. Both methods indicated that the peak magnitude of residual stresses were below the yield stress of IN 718.
Keywords: inconel 718 superalloy; in-service repair; residual stress; neutron diffraction; contour method

Evaluation of aircrew whole-body vibration exposure on a Canadian CH-147F Chinook Helicopter - Chen, Yong; Ghinet, Sebastian; Price, Andrew; Wickramasinghe, Viresh; Grewal, Anant (Journal of the American Helicopter Society, 2017)
Flight testing was performed on a Royal Canadian Air Force CH-147F Chinook helicopter to investigate aircrew whole-body vibration (WBV) exposure levels in accordance with the MIL-STD-1472G standard. Results showed that the helicopter cabin vibration was dominated at the N/rev harmonics of the three-bladed tandem rotor speed. The aircrew WBV levels varied significantly depending on flight conditions and aircraft load configurations; the highest levels occurred at high-speed level flight and maneuver conditions. With reference to the MIL-STD-1472G guidelines, the aircrew WBV exposure level in the entire tested flight profile was qualitatively rated as “uncomfortable,” and the maximum duration of such missions should be limited to ensure compliance with the limit of the “Vibration Health Risks Guideline Caution Zone.” The aircrew subjective perception survey for this flight profile also confirmed an increase of personnel ride discomfort.

Sequential signal detection for high dynamic range time-resolved laser-induced incandescence - Mansmann, Raphael; Thomson, Kevin; Smallwood, Greg; Dreier, Thomas; Schulz, Christof (Optics Express, 2017)
A new method for collecting time-resolved laser-induced incandescence (TiRe-LII) signals with high dynamic range is presented. Gated photomultiplier tubes (PMT) are used to detect temporal sections of the LII signal. This helps to overcome the limitations of PMTs caused by restricted maximum signal current at the strong initial signal and poor signal-to-noise ratios when the signal intensity approaches the noise level. We present a simple method for increasing the accuracy of two-color pyrometry at later decay times and two advanced strategies for getting high accuracy over the complete temperature trace or even achieve single-shot capability with high dynamic range. Validation measurements in a standardized flame show that the method is sensitive enough to even resolve the local increase in gas temperature as a consequence of heating the soot particles with a laser pulse.

Self-organized nanostructure formation during femtosecond-laser inscription of fiber Bragg gratings - Hnatovsky, Cyril; Grobnic, Dan; Coulas, David; Barnes, Michael; Mihailov, Stephen J. (Optics Letters, 2017)
Periodic planar nanostructures are found in Type II-IR Bragg gratings produced in SMF-28 fiber by side-illuminating it with infrared femtosecond-laser pulses through a phase mask. The planar nanostructures are aligned perpendicular to the laser polarization, as demonstrated using scanning electron microscopy analysis of cleaved fiber samples. Dark field optical microscopy is employed for real-time monitoring of structural changes occurring inside the fiber during the inscription process.

Report of the CCQM-K97: measurement of arsenobetaine standard solution and arsenobetaine content in fish tissue (tunafish) - Ma, L. D.; Wang, J.; Wei, C.; Kuroiwa, T.; Narukawa, T.; Ito, N.; Hioki, A.; Chiba, K.; Yim, Y. H.; Lee, K. S.; Lim, Y. R.; Turk, G. C.; et al. (Metrologia, 2017)
The CCQM-K97 key comparison was organized by the inorganic analysis working group (IAWG) of CCQM as a follow-up to completed pilot study CCQM-P96 and P96.1 to test the abilities of the national metrology institutes to accurately quantitate the mass fraction of arsenobetaine (AsB) in standard solution and in fish tissue. A pilot study CCQM-P133 was parallelized with this key comparison. National Institute of Metrology (NIM), China and National Metrology Institute of Japan (NMIJ) acted as the coordinating laboratories. Six NMIs participated in CCQM-K97 and two institutes participated in CCQM-P133, and all of them submitted the results. Some NMIs submitted more than one results by different methods. The results were in excellent agreement with each other, and obviously better than those of previous P96 and P96.1. Therefore the calibrant which each NMI used was comparable. It shows that the capabilities of some of the participants have been improved after the previous pilot studies.

Calculations of radiative heat transfer in an axisymmetric jet diffusion flame at elevated pressures using different gas radiation models - Chu, Huaqiang; Consalvi, Jean-louis; Gu, Mingyan; Liu, Fengshan (Journal of Quantitative Spectroscopy and Radiative Transfer, 2017)
Radiation heat transfer in axisymmetric jet diffusion flames under conditions relevant to oxygen-enriched combustion at total pressures of 1, 10, 20, and 30 atm was calculated using several gas radiation models: line-by-line (LBL), narrow-band correlated-k (NBCK), wide-band correlated-k (WBCK), full-spectrum correlated-k (FSCK), spectral-line based weight-sum-of-gray-gases (SLW), and weight-sum-of-gray-gases (WSGG). An optimized NBCK model, an optimized FSCK model, and a WBCK model were proposed and evaluated. The LBL results are used as the benchmark solution in the evaluation of other gas radiation models. The optimized NBCK model and the optimized FSCK model are much more computationally efficient than the standard implementation of these models with very little loss in accuracy. The NBCK, WBCK, and FSCK models are accurate and their normalized errors in both the radiative source term and radiative flux remain less than about 7% and display essentially no dependence on the total pressure. Whatever the pressure considered, the FSCK is found to provide accurate predictions by considering only 10 Gauss points. For the same number of gray gases, the SLW is less accurate than the FSCK, especially at pressures higher than the atmospheric pressure. However, its accuracy can be significantly improved to reach that of the FSCKby increasing the number of gray gases. The accuracy of WSGG models deteriorates somewhat with increasing the total pressure in the prediction of radiative heat flux, though it displays no significant dependence on the total pressure in the calculation of the radiative source term. The spectral line broadening has a non-negligible influence on radiative heat transfer in the jet diffusion flame. The somewhat increased inaccuracy of the WSGG model with increasing the total pressure is at least partially due to the application of the model parameters derived at 1 atm to high pressures. The normalized errors of WSGG are about 10 to 20%. The optimized FSCK model is found much more accurate than the popular WSGG model with a comparable computational efficiency and is therefore recommended for large-scale CFD applications.

Indications of chemical bond contrast in AFM images of a hydrogen-terminated silicon surface - Labidi, Hatem; Koleini, Mohammad; Huff, Taleana; Salomons, Mark; Cloutier, Martin; Pitters, Jason; Wolkow, Robert A. (Nature Communications, 2017)
The origin of bond-resolved atomic force microscope images remains controversial. Moreover, most work to date has involved planar, conjugated hydrocarbon molecules on a metal substrate thereby limiting knowledge of the generality of findings made about the imaging mechanism. Here we report the study of a very different sample; a hydrogen-terminated silicon surface. A procedure to obtain a passivated hydrogen-functionalized tip is defined and evolution of atomic force microscopy images at different tip elevations are shown. At relatively large tip-sample distances, the topmost atoms appear as distinct protrusions. However, on decreasing the tip-sample distance, features consistent with the silicon covalent bonds of the surface emerge. Using a density functional tight-binding-based method to simulate atomic force microscopy images, we reproduce the experimental results. The role of the tip flexibility and the nature of bonds and false bond-like features are discussed.

Bioelectrochemical anaerobic sewage treatment technology for Arctic communities - Tartakovsky, Boris; Kleiner, Yehuda; Manuel, Michelle-France (Environmental Science and Pollution Research, 2017)
This study describes a novel wastewater treatment technology suitable for small remote northern communities. The technology is based on an enhanced biodegradation of organic carbon through a combination of anaerobic methanogenic and microbial electrochemical (bioelectrochemical) degradation processes leading to biomethane production. The microbial electrochemical degradation is achieved in a membraneless flow-through bioanode–biocathode setup operating at an applied voltage below the water electrolysis threshold. Laboratory wastewater treatment tests conducted through a broad range of mesophilic and psychrophilic temperatures (5–23 °C) using synthetic wastewater showed a biochemical oxygen demand (BOD5) removal efficiency of 90–97% and an effluent BOD5 concentration as low as 7 mg L−1. An electricity consumption of 0.6 kWh kg−1 of chemical oxygen demand (COD) removed was observed. Low energy consumption coupled with enhanced methane production led to a net positive energy balance in the bioelectrochemical treatment system.
Keywords: bioelectrochemical; anaerobic; psychrophilic; microbial electrolysis cell; wastewater

Structure of the LPS O-chain from Fusobacterium nucleatum strain 10953, containing sialic acid - Vinogradov, Evgeny; St. Michael, Frank; Homma, Kiyonobu; Sharma, Ashu; Cox, Andrew D. (Carbohydrate Research, 2017)
Fusobacterium nucleatum is an anaerobic bacterium found in the human mouth where it causes periodontitis. Recently, it has been gaining attention as a potential causative agent for colorectal cancer and is strongly linked with pregnancy complications including pre-term and still births. Little is known about virulence factors of this organism and thus we have initiated studies to examine the bacterial surface glycochemistry. Consistent with a recent paper suggesting that F. nucleatum strain 10593 can synthesize sialic acid, a staining technique identified sialic acid on the bacterial surface. We isolated lipopolysaccharide from this F. nucleatum strain and performed structural analysis on the O-antigen. Our studies identified a trisaccharide repeating unit of the O-antigen with the following structure: -[→4)-α-Neup5Ac-(2 → 4)-β-d-Galp-(1 → 3)-α-d-FucpNAc4NAc-(1-]- where Ac indicates 4-N-acetylation of ∼30% FucNAc4N residues. The presence of sialic acid as a constituent of the O-antigen is consistent with recent data identifying de novo sialic acid synthesis in this strain.
Keywords: Fusobacterium nucleatum; lipopolysaccharide; sialic acid

Mechanical properties of electron beam welds in heavy-section UNS S41500 martensitic stainless steel - Sarafan, S.; Wanjara, P.; Gholipour, J.; Champliaud, H.; Mathieu, L. (The International Journal of Advanced Manufacturing Technology, 2017)
Single pass autogenous butt welds, without detect- able volumetric defects, were manufactured by electron beam welding 90-mm-thick UNS S41500—a low carbon 13% Cr- 4% Ni martensitic stainless steel typically used for hydroelec- tric turbine applications. The mechanical properties of the joints were evaluated in the as-welded condition by tensile testing, Charpy V-notch testing, and bend testing. Specifically, static tensile loading was conducted on samples extracted transverse and longitudinal to the weld seam. To determine the impact toughness of the electron beam welded joints, the Charpy tests were conducted on samples with V- notch roots located in the fusion and heat-affected zones at −18 °C. The yield strength, ultimate tensile strength, elongation and toughness of the electron beam welds were found to more than adequately meet the minimum acceptance criteria specified in ASME section VIII and IX. Also, the formability of the welds, examined by bend testing, displayed no discon- tinuities on the tension side of the bent joints. These promising mechanical properties determined for the as-welded UNS S41500 stainless steel offer considerable prospects for indus- trializing the electron beam welding process.
Keywords: electron beam welding; UNS S41500 martensitic stainless steel; tensile testing; charpy V-notch testing; bend testing; as-welded joints

Physicochemical properties of engineered nanomaterials - Johnston, Linda J.; Mansfield, Elisabeth; Smallwood, Gregory J. (Metrology and Standardization of Nanotechnology: Protocols and Industrial Innovations, 2017)
This chapter discusses the important physicochemical properties of composition, size, shape, surface properties, and aggregation/agglomeration/dispersion state for nanomaterial characterization. The emission properties of luminescent nanomaterials may yield information on sample agglomeration or aggregation, although typically this will require a detailed understanding of the photophysics of the material and possible energy transfer or quenching mechanisms. One of the most difficult things to address with respect to the state of aggregation, agglomeration, or dispersion of a nanomaterial is the necessity of assessing the dispersion state in an environment relevant to its end use. Beyond the role of surface charge on the colloidal stability of nanomaterial suspensions, the surface functional groups have a major impact on the adsorption of species from the environment and can also modulate the hydrophobicity/hydrophilicity and, in some cases, size and morphology of the material.
Keywords: agglomeration; aggregation; bulk chemical composition; colloidal stability; nanomaterial shapes; nanomaterial size distribution; nanomaterial suspensions; nanomaterials' morphology; surface functional groups

Effective density and volatility of particles sampled from a helicopter gas turbine engine - Olfert, Jason S.; Dickau, Matthew; Momenimovahed, Ali; Saffaripour, Meghdad; Thompson, Kevin; Smallwood, Greg; Stettler, Marc E. J.; Boies, Adam; Sevcenco, Yura; Crayford, Andrew; Johnson, Mark (Aerosol Science and Technology, 2017)
The effective density and size-resolved volatility of particles emitted from a Rolls-Royce Gnome helicopter turboshaft engine are measured at two engine speed settings (13,000 and 22,000 RPM). The effective density of denuded and undenuded particles were measured. The denuded effective densities are similar to the effective densities of particles from a gas turbine with a double annular combustor as well as a wide variety of internal combustion engines. The denuded effective density measurements were also used to estimate the size and number of primary particles in the soot aggregates. The primary particle size estimates show that the primary particle size was smaller at lower engine speed (in agreement with transmission electron microscopy analysis). As a demonstration, the size-resolved volatility of particles emitted from the engine are measured with a system consisting of a differential mobility analyzer, centrifugal particle mass analyzer, condensation particle counter, and catalytic stripper. This system determines the number distributions of particles that contain or do not contain non-volatile material, and the mass distributions of non-volatile material, volatile material condensed onto the surface of non-volatile particles, and volatile material forming independent particles (e.g. nucleated volatile material). It was found that the particulate at 13,000 RPM contained a measurable fraction of purely volatile material with diameters below ∼25 nm and had a higher mass fraction of volatile material condensed on the surface of the soot (6–12%) compared to the 22,000 RPM condition (1–5%). This study demonstrates the potential to quantify the distribution of volatile particulate matter and gives additional information to characterize sampling effects with regulatory measurement procedures.

Manufacturing of recombinant adeno-associated viruses using mammalian expression platforms - Robert, Marc-andré; Chahal, Parminder S.; Audy, Alexandre; Kamen, Amine; Gilbert, Rénald; Gaillet, Bruno (Biotechnology Journal, 2017)
Manufacturing practices for recombinant adeno-associated viruses (AAV) have improved in the last decade through the development of new platforms in conjunction with better production and purification methods. In this review, we discuss the advantages and limitations of the most popular systems and methods employed with mammalian cell platforms. Methods and systems such as transient transfection, packaging and producer cells and adenovirus and herpes simplex virus are described. In terms of best production yields, they are comparable with about 104–105 vector genomes produced per cell but transient transfection of HEK293 cells is by far the most commonly used. For small-scale productions, AAV can be directly purified from the producing cell lysate by ultracentrifugation on a CsCl or iodixanol-step gradient whereas large-scale purification requires a combination of multiple steps. Micro/macrofiltration (i.e. including tangential flow filtration and/or dead-end filtration) and chromatography based-methods are used for large-scale purification. Purified AAV products must then be quantified and characterized to ensure quality. Recent purification methods and current analytical techniques are reviewed here. Finally, AAV technology is very promising, but manufacturing improvements are still required to meet the needs of affordable, safe and effective AAV vectors essential for licensing of gene therapy clinical protocols.
Keywords: gene therapy; HEK293; large-scale manufacturing; mammalian cells; recombinant adeno-associated viruses

Metallization of carbon fibre reinforced polymers by cold spray - Che, Hanqing; Vo, Phuong; Yue, Stephen (Surface and Coatings Technology, 2017)
Carbon fibre reinforced polymer (CFRP) is a very competitive alternative to aluminum for aircraft structures for lightweighting purposes, but this leaves vulnerability against lightning strike. Cold spray is one coating approach to metallize the polymers, making them lightning strike proof. The aim of this work is to investigate the viability of metallizing aircraft quality CFRPs by cold spray. Copper, aluminum and tin were cold sprayed onto the CFRPs with both a high-pressure and a low-pressure cold spray system. A number of different combinations of the gas pressure and gas preheating temperature were used for the cold spray process. Erosion was found to be the key obstacle to developing continuous coatings on the CFRP substrates with the high-pressure system. On the other hand, continuous tin coatings were successfully obtained on CFRP with the low-pressure system, due to the very soft tin coating the substrate through a “crack filling” mechanism. Based on the results, it was proposed that when cold spraying metals on CFRP, it is necessary to differentiate between the development of the first layer and the build-up of subsequent layers. Last but not least, the effect of particle velocity and gas temperature was discussed and the deposition window of tin on CFRP was developed.
Keywords: metallization of polymers; cold spray; carbon fibre reinforced polymer

Cold sprayability of mixed commercial purity Ti Plus Ti6Al4V metal powders - Aydin, Huseyin; Alomair, Mashael; Wong, Wilson; Vo, Phuong; Yue, Stephen (Journal of Thermal Spray Technology, 2017)
In the present work, metallic composite coatings of commercial purity Ti plus Ti6Al4V were produced by cold spraying to explore the effect of mixing on porosity and mechanical properties of the coatings. The coatings were deposited using N2 gas at 800 °C and 4 MPa pressure on 1020 steel substrate. Coating characteristics were studied by examining porosity percentages and Vickers’s hardness. The microstructure was examined using optical and electron microscopy techniques. It was observed that mixing metal powders can lead to improvements in cold sprayability, specifically decreases in the porosity of the ‘matrix’ powder. It is shown that a critical addition can significantly influence porosity, but above this critical level, there is a little change in porosity. Hardness differences between the two powders are considered to be the first-order influence, but differences in particle sizes and morphology may also be contributing factors.
Keywords: cold spray; deposition efficiency; mixed metal powders coating; porosity

Determination of total cyanide in soil by isotope dilution GC/MS following pentafluorobenzyl derivatization - Campanella, Beatrice; Biancalana, Lorenzo; D'ulivo, Lucia; Onor, Massimo; Bramanti, Emilia; Mester, Zoltan; Pagliano, Enea (Analytica Chimica Acta, 2017)
The high toxicity of cyanide, along with its widespread industrial use, has fuelled interest in the development of analytical methods for its determination in complex matrices. In this study, we propose a novel approach for the measurement of total cyanide in soil samples based on single-step derivatization with pentafluorobenzyl bromide (F₅Bn−Br) followed by quantitation with gas chromatography mass spectrometry in negative chemical ionization mode. The reaction between CN⁻ and F₅Bn−Br resulted in the identification of several derivatives such as F₅Bn−CN, (F₅Bn)(F₅Ph)CH−CN, and (F₅Bn)₂(F₅Ph)C−CN. The relative proportion between such compounds was dependent on experimental conditions. When a 100 μL aliquot of an alkaline-aqueous extract was reacted with 700 μL of 1.3% F₅Bn−Br in acetone, the tri-alkylated derivative was the most abundant. In such conditions a detection limit of 0.5 ng/g of CN⁻ was attained. Soil samples were initially spiked with an alkaline solution of K¹³C¹⁵N internal standard and suspended in 7.5% aqueous NaOH. Determination of total cyanide was achieved by digestion of the alkaline extract with H₃PO₄ to produce HCN which was then trapped in 0.1% NaOH in a sealed double vial system, followed by reaction with F₅Bn−Br. Isotope dilution calibration was chosen for quantitation, and the validity of the novel method was demonstrated by analysis of soil Certified Reference Materials (CRMs) and by spike recovery tests.
yes
Keywords: Cyanide; Pentafluorobenzyl bromide; Soil; Isotope dilution; Gas chromatography-mass Spectrometry

Traceability of no-load loss measurements of high-voltage transmission lines - So, Eddy; Arseneau, Rejean (IEEE Transactions on Instrumentation and Measurement, 2017)
This paper describes the traceable measurement of no-load losses of high-voltage transmission lines, including actual no-load loss measurements of 220-kV transmission lines in coastal Peru. The measurement methodology and the evaluation of the no-load losses are discussed in this paper. The development of a new measurement methodology to allow for future live line connections is also described.
Keywords: corona losses; discharges; leakage current measurement and measurement methodology; no-load losses; traceable measurements

Scalable synthesis of hierarchical macropore-rich activated carbon microspheres assembled by carbon nanoparticles for high rate performance supercapacitors - Zhang, Dongdong; Zhao, Jianghong; Feng, Chong; Zhao, Rijie; Sun, Yahui; Guan, Taotao; Han, Baixin; Tang, Nan; Wang, Jianlong; Li, Kaixi; Qiao, Jinli; Zhang, Jiujun (Journal of Power Sources, 2017)
A scalable inverse-microemulsion-polymerization-phase-separation coupling method is applied to successfully prepare hierarchical macropore-rich activated carbon microspheres (ACS) using a phenolic resin (PR) precursor followed by carbonization and KOH activation for the first time. The formed ACS materials are assembled by carbon nanoparticles (CNPs). The macropores interspersed among the component CNPs are formed after removing the non-reactive solvent phase in the course of the polymerization of the reactive PR phase, which occupies ∼64% of the total pore volume (∼2.779 cm3 g−1) of the optimized ACS. In combination with mesopores (∼18% of the total pore volume), the ACS possesses meso/macropores approaching 82% of the total pore volume. Micropores are created in the component CNPs via KOH activation, showing shortened ion transport distances in the nanoscale dimension. Both the hierarchical micro/meso/macroporous structure and the inner nanoparticle morphology (short ion diffusion pathways) can significantly contribute to the rapid transport of electrolyte ions throughout the carbonaceous matrix, resulting in superior rate performance of ACS-based supercapacitors. More importantly, the energy densities of the ACS supercapacitors operating in both aqueous and organic electrolyte retain steady over a wide range of power densities varying dramatically from 0.25 to 14.5 kW kg−1 and to 7.0 kW kg−1, respectively.
Keywords: scalable synthesis; macropore; hierarchical porous; activated carbon microsphere; supercapacitor

Cyanoethylated pullulan as a high-k solution processable polymer gate dielectric for SWCNT TFTs - Lopinski, Gregory; Du, Naiying; Dubey, Girjesh; Lefebvre, Jacques; Li, Zhao; Zou, Shan; Malenfant, Patrick (Organic Electronics, 2017)
Cyanoethylated pullulan (CEP), a high-k solution processable polymer gate dielectric, is used to fabricate bottom gated single wall carbon nanotube (SWCNT) network thin film transistors (TFTs). Both aqueous and organic dispersions of highly semiconducting enriched SWCNTs are used as the channel material. Use of CEP as the dielectric enables fabrication of devices operating at low voltage (<3 V) with high on-state currents, good on/off ratios (∼105), low subthreshold swings (∼200 mV/decade) and minimal hysteresis (<1 V). However, despite high apparent mobilities extracted from gate voltage sweeps, driving these devices at even modest frequencies (>1 Hz) is found to significantly decrease the transconductance. This is shown to be related to a significant frequency dependence of the capacitance associated with a slow polarization response of the dielectric. Despite this limitation, CEP could be a useful dielectric in SWCNT TFTs for applications such as sensors and low frequency amplifiers.
Keywords: polymer dielectric; thin film transistor; carbon nanotubes; printable electronics

Using aminopyrine as a nitrogen-enriched small molecule precursor to synthesize high-performing nitrogen doped mesoporous carbon for catalyzing oxygen reduction reaction - Zhang, Enguang; Wu, Mingjie; Tang, Qiaowei; Gong, Qiaojuan; Sun, Shuhui; Qiao, Jinli; Zhang, Lei (RSC Adv., 2017)
With aminopyrine as a nitrogen-enriched small molecule precursor, a series of nitrogen doped carbon materials have been fabricated and explored as electrocatalysts for oxygen reduction reaction (ORR). The most active catalyst is a nitrogen doped carbon, which was prepared through a facile template-mediated pyrolyzing method using ferric nitrate (Fe(NO3)3·9H2O) as an activation reagent along with nanoscaled silica as a sacrificial support (hereafter referred to as AP/SiO2). The AP/SiO2 is confirmed and identified as having highly active molecule catalytic centers for ORR, due to its possessing a porous, sponge-like and uniform structure with a super-large specific surface area of 932.68 m2 g−1. The AP/SiO2 catalyst exhibited a high onset potential of 0.98 V, a half-wave potential of 0.82 V, and a high number of exchanged electrons (>3.8, close to four) in alkaline media. After 5000 continuous cycles, the material showed almost no negative shift with respect to the Pt/C material. Even in acidic medium, the AP/SiO2 catalyst still showed much higher durability than Pt/C and a low yield of HO2−. This work may have provided a new and simple route in the design and batch-synthesis of highly active and durable carbonaceous electrocatalysts for ORR.

Separation and concentration of Phytophthora ramorum sporangia by inertial focusing in curving microfluidic flows - Clime, Liviu; Li, Kebin; Geissler, Matthias; Hoa, Xuyen D.; Robideau, Gregg P.; Bilodeau, Guillaume J.; Veres, Teodor (Microfluidics and Nanofluidics, 2017)
We present an integrated microfluidic system for performing isolation and concentration of Phytophthora ramorum pathogens using a chip whose working principle is based on inertial lateral migration in curving flows. The chip was fabricated from multiple layers of thermoplastic polymers and features an embedded spiral separation channel along with peristaltic microvalves for fluidic operation and process control. A pumping system paired with a fully programmable pressure manifold is used to boost concentration levels by recirculating the sample liquid multiple times through the separation chip, making it possible to reduce sample volumes from 10 to 1 mL or less. The system was calibrated using fluorescent polymer particles with a nominal diameter of 30 µm which is comparable to that of P. ramorum sporangia. The separation process has been shown to be highly effective and more than 99% of the beads can be recovered in the concentrated batch. Experiments conducted with P. ramorum sporangia have shown that a 5.3-fold increase in pathogen content with 95% recovery can be achieved using three subsequent concentration cycles. The utility of the method has been validated by processing a sample derived from infested Rhododendron leaves where a 6.1-fold increase in the concentration of P. ramorum has been obtained after four concentration cycles. Although specifically designed and demonstrated for sporangia of P. ramorum, the method and related design rules can easily be extended to other microbial organisms, effectively supporting bioanalytical applications where efficient, high-throughput separation of target species is of primary concern.
Keywords: inertial separation; microfluidic chip; plant pathogen detection; pneumatic pumping

The structure of the LPS O-chain of Fusobacterium nucleatum strain 25586 containing two novel monosaccharides, 2-acetamido-2,6-dideoxy-l-altrose and a 5-acetimidoylamino-3,5,9-trideoxy-gluco-non-2-ulosonic acid - Vinogradov, Evgeny; St. Michael, Frank; Cox, Andrew D. (Carbohydrate Research, 2017)
Fusobacterium nucleatum is an anaerobic bacterium found in the human mouth where it causes periodontitis. Recently, it has been gaining attention as a potential causative agent for colorectal cancer and is strongly linked with pregnancy complications including pre-term and still births. Little is known about the virulence factors of this organism, and thus we have initiated studies to examine the bacterium's surface glycochemistry. We isolated lipopolysaccharide (LPS) from F. nucleatum strain 25586 and purified and performed structural analysis on the O-antigen polysaccharide. The polysaccharide contained two novel sugars, 2-acetamido-2,6-dideoxy-l-altrose (l-6dAltNAc) and a 5-acetimidoylamino-3,5,9-trideoxy-gluco-non-2-ulosonic acid (Non5Am), which was tentatively assigned the l-glycero-l-gluco configuration. The polysaccharide was found to have a trisaccharide repeating unit, which is phosphorylated with phosphocholine (PCho), and the following structure was established: -[-4-β-Nonp5Am-4-α-l-6dAltpNAc3PCho-3-β-d-QuipNAc-]- We propose the trivial name ‘fusaminic acid’ for the novel nonulosonic acid. It is the first occurrence of a 9-deoxynonulosonic acid with a hydroxyl group at C-7, which is occupied by an amino group in all monosaccharides of this class described so far.

Towards improving the practical energy density of Li-ion batteries: optimization and evaluation of silicon: graphite composites in full cells - Yim, Chae-Ho; Niketic, Svetlana; Salem, Nuha; Naboka, Olga; Abu-lebdeh, Yaser (Journal of The Electrochemical Society, 2017)
Increasing the energy density of Li-ion batteries is very crucial for the success of electric vehicles, grid-scale energy storage, and next-generation consumer electronics. One popular approach is to incrementally increase the capacity of the graphite anode by integratingsilicon into composites with capacities between 500 and 1000 mAh/g as a transient and practical alternative to the more-challenging,silicon-only anodes. In this work, we have calculated the percentage of improvement in the capacity of silicon:graphite compositesand their impact on energy density of Li-ion full cell. We have used the Design of Experiment method to optimize composites usingdata from half cells, and it is found that 16% improvements in practical energy density of Li-ion full cells can be achieved using 15to 25 wt% of silicon. However, full-cell assembly and testing of these composites using LiNi0.5Mn0.5Co0.5O2cathode have provento be challenging and composites with no more than 10 wt% silicon were tested giving 63% capacity retention of 95 mAh/g at only50 cycles. The work demonstrates that introducing even the smallest amount of silicon into graphite anodes is still a challenge andto overcome that improvements to the different components of the Li-ion battery are required.

Sumoylation in lens differentiation and pathogenesis - Xiang, J-W; Chen, Z-G; Gong, Lili; Xiao, Y.; Qing, W-J; Wang, Lisi; Hu, X-H; Huang, Z-X; Qi, R-L; Yang, T-H; Arrigo, A-P; Zhang, Lei; et al. (Current Molecular Medicine; 17, 2017)
Sumoylation, a post-translational modification discovered over a decade ago, turns out to be a very important regulatory mechanism mediating multiple cellular processes. Recent studies from our laboratory and others also revealed that it plays a crucial role in regulating both differentiation and pathogenesis of the ocular lenses. This review will summarize these progresses.

Antibody delivery mediated by recombinant adeno-associated virus for the treatment of chronic and infectious diseases - Robert, Marc-André; Gilbert, Rénald; Bruno, Gaillet (Current Gene Therapy, 2017)
Monoclonal antibodies (mAbs) based-therapies are currently one of the most successful strategies to treat immune disorders, cancer and infectious diseases. Vectors derived from adeno-associated virus (AAV) are very attractive to deliver the genes coding the mAbs because they allow long-term expression thus, reducing the number of administrations. They can also penetrate biological barriers such as the blood-brain-barrier to transduce cells localized in immunoprivileged organs. Recent animal studies with AAV have demonstrated the capacity of AAV to deliver sufficient quantity of antibodies to confer an efficient immunoprotection against chronic and infectious diseases for several months to years. The treatment was successfully applied either for prophylaxis or therapeutic use, depending on the disease and its progression. In this review, we discuss the advantages and the limitations of AAV for mAb and immunoadhesin delivery. Recent advances in vector design and antibody engineering are also presented. Optimization of the vector design can improve the kinetic and the level of mAbs expression whereas protein engineering can enhance transgene product properties. Furthermore, an exhaustive review of pre-clinical studies for chronic diseases including Alzheimer disease, amyotrophic lateral sclerosis and cancer is presented as well as for infectious diseases.
Keywords: adeno-associated virus; antibody delivery; chronic and infectious diseases; gene therapy; vector design; preclinical studies

Optimization and design of a morphing wing tip aircraft demonstrator for drag reduction at low speeds, Part II – Experimental validation using infra-red transition measurements during wind tunnel tests - Koreanschi, Andreea; Gabor, Oliviu Sugar; Acotto, Joran; Brianchon, Guillaume; Portier, Gregoire; Botez, Ruxandra Mihaela; Mamou, Mahmoud; Mebarki, Youssef (Chinese Journal of Aeronautics, 2017)
In the present paper, an ‘in-house’ genetic algorithm was numerically and experimentally validated. The genetic algorithm was applied to an optimization problem for improving the aerodynamic performances of an aircraft wing tip through upper surface morphing. The optimization was performed for 16 flight cases expressed in terms of various combinations of speeds, angles of attack and aileron deflections. The displacements resulted from the optimization were used during the wind tunnel tests of the wing tip demonstrator for the actuators control to change the upper surface shape of the wing. The results of the optimization of the flow behavior for the airfoil morphing upper-surface problem were validated with wind tunnel experimental transition results obtained with infra-red Thermography on the wing-tip demonstrator. The validation proved that the 2D numerical optimization using the ‘in-house’ genetic algorithm was an appropriate tool in improving various aspects of a wing’s aerodynamic performances.
Keywords: drag reduction; infra-red tests; morphing wing; optimization; wind tunnel test

Bistability and hysteresis induced by form drag in nonlinear subcritical and supercritical double-diffusive Lapwood convection in shallow porous enclosures - Rebhi, Redha; Mamou, Mahmoud; Vasseur, Patrick (Journal of Fluid Mechanics, 2017)
This paper considers natural Lapwood convection in a shallow porous cavity filled with a binary fluid. The investigation is mainly focused on the nonlinear behaviour of subcritical convection and the bistability phenomenon caused by the combined effects of porous medium form drag and double-diffusive convection. The Dupuit–Darcy model, which includes the effect of the form drag at high Reynolds flow, is used to describe the convective flow in the porous matrix. The enclosure is subject to vertical temperature and concentration gradients. ...

Nutritional evaluation of whole and lipid-extracted biomass of the microalga Scenedesmus sp. AMDD for animal feeds: simulated ruminal fermentation and in vitro monogastric digestibility - Tibbetts, Sean M.; Fredeen, Alan H. (Current Biotechnology, 2017)
The present study is the second in a series of projects designed to evaluate the nutritional value of S-AMDD for animal feed applications. The main objective was to generate novel digestibility data of whole-cell and lipid-extracted S-AMDD for both ruminant and monogastric animals including ruminal organic matter digestibility (OMD), apparent metabolizable energy (aME) content, methane (CH4) production, dilute pepsin digestibility (DPD) and two-phase gastric/pancreatic digestibility of protein (GPDProtein) and energy (GPDEnergy). Simulated ruminal fermentations using lactating dairy cattle as rumen fluid donors indicate that both whole-cell and lipid-extracted S-AMDD have excellent potential for use in ruminant animal feeds. Dietary inclusion of whole-cell S-AMDD at 50% forage protein replacement (equivalent to 20% of the total diet) or lipid-extracted S-AMDD at 100% forage protein replacement (equivalent to 32% of the total diet) did not significantly affect OMD or aME content of the control diet. However, OMD was marginally comprised with 100% forage protein replacement with whole-cell S-AMDD (equivalent to 40% of the total diet) relative to the 25 and 50% replacement levels, although not significantly different from the control diet. Diets containing lipid-extracted S-AMDD significantly reduced CH4 production by approximately 50% compared to the control diet (47% reduction) and those containing whole-cell S-AMDD (51% reduction). Since OMD and aME content of diets containing lipid-extracted S-AMDD were unaffected relative to the control diet and whole-cell S-AMDD-containing diets, it seems clear that lipid-extracted S-AMDD contains anti-methanogenic ‘non-fatty acid’ substances that have the ability to suppress rumen methanogenic bacteria without disturbing ruminal digestion. This area warrants further exploration in vivo, especially considering the large volume of algal feed that could be produced without occupying significant land resources. In vitro monogastric digestibility using porcine enzymes indicates that lipid-extracted S-AMDD has potential for use in monogastric animal feeds. Protein and energy digestibility of this product were moderately high (75-84% and 70%, respectively); which resulted in relatively high contents of DP (30%) and DE (14 MJ kg-1). On the other hand, the digestibility of whole-cell S-AMDD was low at 52-61% and 50%, respectively resulting in lower levels of DP (15%) and DE (12 MJ kg-1). Despite the encouraging results for lipid-extracted S-AMDD, the digestibility (particularly of energy) remains marginal for monogastric animals and requires improvement through additional cost-effective cell rupture technologies or the production algal protein concentrates.
Keywords: Microalgae; digestibility; ruminant; monogastric; protein; energy; methane

Evaluation of aircrew whole-body vibration and mitigation solutions for helicopter flight engineers - Chen, Yong; Yapa, U. S.; Price, A.; Wickramasinghe, V. (Forum..., 2017)
Flight testing has been performed on a Bell-205 helicopter to investigate aircrew whole-body vibration (WBV) exposure levels on a rag and tube Flight Engineer (FE) seat in accordance with ISO2631 and MIL-STD1472 standards. Results show that the helicopter cabin vibration is dominated by the N/rev harmonics of the two-bladed main rotor speed. The aircrew WBV levels vary significantly depending on the flight conditions; the highest WBV levels occur at high speed level flight conditions. With reference to the ISO2631 and MIL-STD-1472 guidelines, the aircrew WBV exposure level on the standard FE seat in the entire tested flight profile is qualitatively rated as "uncomfortable". Limiting the maximum duration of such missions to 1 hour would ensure compliance with the limit of ISO2631 vibration health and risk guideline "Caution Zone". It is also noted that the use of gunner seat insert cushion for combat missions can lead to a significant increase in the aircrew WBV levels. However, the use of selected carry-on cushion pads can provide an effective WBV mitigation to the aircrew in the majority of flight conditions. Further occupant WBV tests on a human rated mechanical shaker table also verified that selected carryon seat cushion pads are also effective in the mitigation of occupant WBV levels on the Bell-412 helicopter.

Code national de l'énergie pour les bâtiments - Canada 2017 - Conseil national de recherches Canada. Commission canadienne des codes du bâtiment et de prévention des incendies (Conseil national de recherches Canada. Commission canadienne des codes du bâtiment et de prévention des incendies, 2017)
Le Code national de l'énergie pour les bâtiments – Canada 2017 (CNÉB) est publié par le Conseil national de recherches du Canada (CNRC) et élaboré par la Commission canadienne des codes du bâtiment et de prévention des incendies (CCCBPI) en collaboration avec Ressources naturelles Canada (RNCan). Il renferme les exigences techniques visant la conception éconergétique et la construction de bâtiments neufs. Le CNRC et RNCan publient cette édition provisoire du CNÉB en réponse à des propositions qui améliorent la performance énergétique globale des bâtiments par rapport au CNÉB de 2015. La modélisation de ces modifications proposées indique une amélioration potentielle de l’efficacité énergétique de 10,3 à 14,4 % par rapport à l’édition de 2011. L’édition de 2017 constitue une étape importante dans la concrétisation de l’objectif du Canada en ce qui concerne les nouveaux bâtiments, comme présenté dans le Cadre pancanadien, soit une « consommation énergétique nette zéro » pour les bâtiments d’ici 2030. Le CNÉB de 2017 appuie cet objectif notamment par la réduction de la transmission thermique globale des toitures, des fenêtres et des portes, par la réduction des pertes dues aux ponts thermiques dans les ensembles de construction et par la réduction de l’aire admissible des lanterneaux. Cette nouvelle édition propose également un resserrement des exigences relatives aux systèmes de récupération d’énergie et fait l’introduction d’exigences plus rigoureuses en matière d’éclairage intérieur et extérieur. Elle exige des commandes de température dans les chambres d’hôtels et de motels et l’installation de systèmes de régulation de la demande de ventilation dans les cuisines commerciales. La partie 4 renferme un éclaircissement quant aux exigences de la méthode des solutions de remplacement visant l’éclairage, et la partie 8 propose une harmonisation des exigences de la méthode de conformité par la performance avec les exigences prescriptives. Le CNÉB est un outil indispensable pour les concepteurs de bâtiments, les conseillers et sous-traitants du secteur de l’énergie, les professionnels de la construction et les organismes de réglementation.
Keywords: energy; énergie; heating; chauffage; ventilation; ventilation; air conditioning; conditionnement d’air; building; bâtiment

National Energy Code of Canada for Buildings - 2017 - National Research Council Canada. Canadian Commission on Building and Fire Codes (National Research Council Canada. Canadian Commission on Building and Fire Codes, 2017)
The National Energy Code of Canada for Buildings 2017 (NECB), published by NRC and developed by the Canadian Commission on Building and Fire Codes in collaboration with Natural Resources Canada (NRCan), sets out technical requirements for the energy efficient design and construction of new buildings. NRC and NRCan are publishing this interim edition of the NECB in response to proposals received that improve the overall energy performance of buildings over the 2015 edition. Modelling for these changes indicates a potential energy efficiency improvement of between 10.3 and 14.4 % over the NECB 2011. The 2017 edition is an important step toward Canada’s goal for new buildings, as presented in the Pan-Canadian Framework, of achieving ‘Net Zero Energy Ready (NZER)’ buildings by 2030. The NECB 2017 supports this goal by reducing the overall thermal transmittance of roofs, fenestration and doors; reducing losses through thermal bridging in building assemblies; and, reducing the allowable percentage of skylight area. This new edition also introduces more stringent requirements for energy recovery systems and interior and exterior lighting requirements. It requires temperature controls in individual guest rooms in hotels and motels and demand control ventilation systems in commercial kitchens. In Part 4, it clarifies the lighting trade-off path requirements and in Part 8, it makes performance compliance requirements consistent with prescriptive requirements. The NECB is a must-have for building designers, energy consultants and subcontractors, construction professionals and regulatory officials.
Keywords: energy; énergie; heating; chauffage; ventilation; ventilation; air conditioning; conditionnement d’air; building; bâtiment

Environmental considerations AASHTO mechanistic-empirical pavement design guide: impacts on performance - Maadani, Omran; El Halim, A.O. Abd (Journal of cold regions engineering, 2017)
This paper is a continuation of an earlier overview on the subject and presents the results of a sensitivity analysis that assessed the ability of the Mechanistic Empirical Pavement Design Guide (MEPDG) to portray the impact of temperature and moisture content on flexible pavements performance. The study used the most common asphalt concrete (HL3) and unbound materials (granular A and silty sand) used in Canada. Two binders (PG 52-34 and PG 58.28) and three moisture conditions (dry, wet and optimum) were chosen. Designs performed using level3 of analysis for unbound materials and level 1 for asphalt concrete showed the MEPDG is sensitive to binder performance grades as well as to climatic zones (cold vs. warm). However, the MEPDG showed limited sensitivity to the state of unbound materials where permanent deformation showed negligible changes between wet, dry and optimum conditions.
Keywords: pavement; environmental factors

Overview environmental considerations in AASHTO pavement design guides - Maadani, Omran; El Halim, A.O. Abd (Journal of cold regions engineering, 2017)
This paper, the first of two companion papers, presents an overview of the effect of environmental factors, namely moisture and temperature, on the material properties of flexible pavement road structure considered in the design guides of the American Association of State Highway and Transportation Officials (AASHTO). It considers the historical development of AASHTO design guides and the new Mechanistic Empirical Pavement Design Guide (MEPDG). The study showed the shift in emphasis from total reliance on an empirical method to a combination of mechanistic and empirical methods in the new design guide. Further, moisture and temperature were indirectly considered in the current guide whereas these parameters are accounted for in the new design guide through the resilient modulus and the complex modulus. The sensitivity analyses of environmental consideration using the new design guide software are presented in the following paper.
Keywords: pavement; environmental factors